14th St. Gallen International Breast Cancer Conference 2015: Evidence, Controversies, Consensus - Primary Therapy of Early Breast Cancer: Opinions Expressed by German Experts - Jackisch, Christian; Harbeck, Nadia; Huober, Jens; Von Minckwitz, Gunter; Gerber, Bernd; Kreipe, Hans-Heinrich; Liedtke, Cornelia; Marschner, Norbert; Moebus, Volker; Scheithauer, Heike; Schneeweiss, Andreas; Thomssen, Christoph; et al. (Breast Care, 2015)
The key topics of this year's 14th St. Gallen Consensus Conference on the diagnosis and therapy of primary breast cancer were again questions about breast surgery and axillary surgery, radio-oncology and systemic therapy options in consideration of tumor biology, and the clinical application of multigene assays. This year, the consensus conference took place in Vienna. From a German perspective, it makes sense to substantiate the results of the vote of the international panel representing 19 countries in light of the updated national therapy recommendations of the AGO (Arbeitsgemeinschaft Gynäkologische Onkologie). Therefore, 14 German breast cancer experts, 3 of whom are members of the International St. Gallen Panel, have commented on the voting results of the St. Gallen Consensus Conference 2015 in relation to clinical routine in Germany.
EVALuna2:17563

243rd Statement by the German Society of Gynecology and Obstetrics (DGGG) in Response to the Call for Data on the Safety of PIP Silicone Breast Implants and the Possible Association between Breast Implants and ALCL by the Scientific Committee on Health, Environmental and Emerging Risks (SCHEER) of the European Commission - Blohmer, Jens-Uwe; Sinn, H. Peter; Seelbach-Goebel, Birgit; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36137

2D:4D biomarker reliability and validity in a within-subject pregnancy-childhood-adolescence cohort - Eichler, Anna; Kaufmann, Franziska; Titzmann, Adriana; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Buchholz, Verena Nadine; Kornhuber, Johannes; Lenz, Bernd (Early Human Development, 2023)
Background: A lot of studies use the second-to-fourth digit length ratio (2D:4D) as a biomarker for intrauterine androgen load to predict behavioral and mental health problems. Thus, knowledge of 2D:4D's metric properties, namely reliability and validity, is essential. Method: 2D:4D handscans were available from 149 adolescents (M = 13.32 years, SD = 0.35) and their mothers. For 88 adolescents, there were also primary-school age handscans (M = 7.87 years, SD = 0.68). Prenatal risks for the 1st to 3rd trimesters were recorded during the 3rd trimester of pregnancy (alcohol exposition: meconium biomarker and maternal self-report; nicotine exposition: maternal self-report; maternal depressive symptoms and subjective stress: questionnaires). Results: The 2D:4D ratio was highly stable from childhood to early adolescence. However, both developmental and sex effects were present: The 2D:4D ratio increased with age and was higher in adolescent girls vs. boys. Significant 2D:4D mother-child associations were found for girls. Significant main effects could be found for the prenatal risk factors alcohol (self-report) and nicotine consumption. Conclusion: In line with earlier studies, the 2D:4D biomarker proved to be an inter-individually stable measure with an intra-individual increase from childhood to early adolescence. Sex differences in adolescence and associations with maternal prenatal health behaviour underline the validity of the biomarker. Findings on heritability emphasize the importance of interpreting 2D:4D results in a sex-specific manner.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 2D:4D ratio; Alcohol; Androgen load; Biomarker; Construct validity; Heritability; Nicotine; Pregnancy risk; Prenatal; Retest reliability; Stability; Testosterone exposure

2q36.3 is associated with prognosis for oestrogen receptor-negative breast cancer patients treated with chemotherapy - Li, Jingmei; Lindstroem, Linda S.; Foo, Jia N.; Rafiq, Sajjad; Schmidt, Marjanka K.; Pharoah, Paul D. P.; Michailidou, Kyriaki; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Van'T Veer, Laura J.; Cornelissen, Sten; et al. (Nature Communications, 2014)
Large population-based registry studies have shown that breast cancer prognosis is inherited. Here we analyse single-nucleotide polymorphisms (SNPs) of genes implicated in human immunology and inflammation as candidates for prognostic markers of breast cancer survival involving 1,804 oestrogen receptor (ER)-negative patients treated with chemotherapy (279 events) from 14 European studies in a prior large-scale genotyping experiment, which is part of the Collaborative Oncological Gene-environment Study (COGS) initiative. We carry out replication using Asian COGS samples (n=522, 53 events) and the Prospective Study of Outcomes in Sporadic versus Hereditary breast cancer (POSH) study (n=315, 108 events). Rs4458204_A near CCL20 (2q36.3) is found to be associated with breast cancer-specific death at a genome-wide significant level (n=2,641, 440 events, combined allelic hazard ratio (HR)=1.81 (1.49-2.19); P for trend=1.90 × 10(-9)). Such survival-associated variants can represent ideal targets for tailored therapeutics, and may also enhance our current prognostic prediction capabilities.
EVALuna2:9232

43-jährige Patientin mit rezidivierend auffälligen PAP-Abstrichen - Dietl, Anna; Beckmann, Matthias; Gaß, Paul (Gynäkologe, 2020)
CRIS-Team Scopus Importer:2020-10-09
Keywords: Cervical cancer; Colposcopy; Human papillomavirus; Hysterectomy; Pembrolizumab

ABCA transporter gene expression and poor outcome in epithelial ovarian cancer - Hedditch, Ellen L.; Gao, Bo; Russell, Amanda J.; Lu, Yi; Emmanuel, Catherine; Beesley, Jonathan; Johnatty, Sharon E.; Chen, Xiaoqing; Harnett, Paul; George, Joshy; Williams, Rebekka T.; Flemming, Claudia; et al. (Journal of the National Cancer Institute, 2014)
ATP-binding cassette (ABC) transporters play various roles in cancer biology and drug resistance, but their association with outcomes in serous epithelial ovarian cancer (EOC) is unknown.The relationship between clinical outcomes and ABC transporter gene expression in two independent cohorts of high-grade serous EOC tumors was assessed with real-time quantitative polymerase chain reaction, analysis of expression microarray data, and immunohistochemistry. Associations between clinical outcomes and ABCA transporter gene single nucleotide polymorphisms were tested in a genome-wide association study. Impact of short interfering RNA-mediated gene suppression was determined by colony forming and migration assays. Association with survival was assessed with Kaplan-Meier analysis and log-rank tests. All statistical tests were two-sided.Associations with outcome were observed with ABC transporters of the "A" subfamily, but not with multidrug transporters. High-level expression of ABCA1, ABCA6, ABCA8, and ABCA9 in primary tumors was statistically significantly associated with reduced survival in serous ovarian cancer patients. Low levels of ABCA5 and the C-allele of rs536009 were associated with shorter overall survival (hazard ratio for death = 1.50; 95% confidence interval [CI] =1.26 to 1.79; P = 6.5e-6). The combined expression pattern of ABCA1, ABCA5, and either ABCA8 or ABCA9 was associated with particularly poor outcome (mean overall survival in group with adverse ABCA1, ABCA5 and ABCA9 gene expression = 33.2 months, 95% CI = 26.4 to 40.1; vs 55.3 months in the group with favorable ABCA gene expression, 95% CI = 49.8 to 60.8; P = .001), independently of tumor stage or surgical debulking status. Suppression of cholesterol transporter ABCA1 inhibited ovarian cancer cell growth and migration in vitro, and statin treatment reduced ovarian cancer cell migration.Expression of ABCA transporters was associated with poor outcome in serous ovarian cancer, implicating lipid trafficking as a potentially important process in EOC.
EVALuna2:9230

Abklärungs- und Versorgungsalgorithmen für das Zervixkarzinom - Beckmann, Matthias (Onkologe, 2020)
CRIS-Team Scopus Importer:2020-06-26

Accelerated Partial Breast Irradiation: Identification of High Risk Tumors in Early Hormone Receptor-positive Breast Cancer by Macrophage Shift Classification - Schnellhardt, S.; Erber, Ramona; Büttner-Herold, Maike; Rosahl, M. -C; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, L.; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Accelerated partial breast irradiation: Macrophage polarisation shift classification identifies high-risk tumours in early hormone receptor-positive breast cancer - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2020)
Studies have demonstrated correlations between accumulations of tumour-associated macrophages (TAMs), especially of M2-like phenotype, and increased mortality in advanced breast cancer. We investigated the prognostic potential of both main macrophage phenotypes in early hormone receptor-positive (HR+) breast cancer. The studied cohort of 136 patients participated in an institutional APBI phase II trial. Patient selection was characterized by HR+, small tumour size and no metastasis. Tissue microarrays from pre-RT resection samples were double stained for CD68/CD163 using immunohistochemistry. CD68+/CD163− cells were considered M1-like macrophages and CD68+/CD163+ was representative of M2-like macrophages. M1 and M2 macrophage densities were analysed semi-automatically in the stromal and intraepithelial tumour compartment. Low M1 and high M2 densities were strongly associated with decreased disease-free survival (DFS). Combined TAM phenotype densities were studied after defining a macrophage shift classification: M1-shifted (M1 high, M2 low) and non-shifted (M1 low, M2 low; M1 high, M2 high) tumours entailed a favourable outcome. In contrast, M2-shifted (M1 low, M2 high) TAM populations were associated with extremely reduced DFS. Thus, the full predictive potential of TAMs was revealed in a combined analysis of both phenotypes. The M2-shifted subgroup of tumours is classified as high-risk and probably not suitable for partial breast irradiation.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Accelerated partial breast irradiation; CD163; CD68; Early breast cancer; Hormone receptor-positive; Prognosis; Tumour associated macrophages

Accelerated partial breast irradiation with external beam radiotherapy : First results of the German phase 2 trial - Ott, Oliver J.; Strnad, Vratislav; Stillkrieg, Wilhelm; Uter, Wolfgang; Beckmann, Matthias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
BACKGROUND AND PURPOSE: To evaluate the feasibility and efficacy of external beam three-dimensional (3D) conformal accelerated partial breast irradiation (APBI) for selected patients with early breast cancer. PATIENTS AND METHODS: Between 2011 and 2016, 72 patients were recruited for this prospective phase 2 trial. Patients were eligible for APBI if they had histologically confirmed breast cancer or pure ductal carcinoma in situ (DCIS), a tumor diameter ≤3 cm, clear resection margins ≥2 mm, no axillary lymph node involvement, no distant metastases, tumor bed clips, and were aged ≥50 years. Patients were excluded if mammography showed a multicentric invasive growth pattern, or if they had residual diffuse microcalcifications postoperatively, an extensive intraductal component, or vessel invasion. Patients received 3D conformal external beam APBI with a total dose of 38 Gy in 10 fractions in 1-2 weeks. The trial had been registered at the German Clinical Trials Register, DRKS-ID: DRKS00004417. RESULTS: Median follow-up was 25.5 months (range 1-61 months). Local control was maintained in 71 of 72 patients. The 3‑year local recurrence rate was 2.1% (95% confidence interval, CI: 0-6.1%). Early toxicity (grade 1 radiodermatitis) was seen in 34.7% (25/72). Late side effects ≥ grade 3 did not occur. Cosmetic results were rated as excellent/good in 96.7% (59/61). CONCLUSION: APBI with external beam radiotherapy techniques is feasible with low toxicity and, according to the results of the present and other studies, on the way to becoming a standard treatment option for a selected subgroup of patients.
EVALuna2:32915

Accelerated partial breast irradiation with external beam radiotherapy: results of the German phase 2-trial - Ott, O. J.; Strnad, Vratislav; Sillkrieg, W.; Uter, Wolfgang; Beckmann, Matthias; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Accuracy of colposcopic findings in detecting vaginal intraepithelial neoplasia: a retrospective study - Stuebs, F. A.; Adler, W.; Beckmann, Matthias; Gaß, Paul; Hartmann, Arndt; Mehlhorn, G.; Renner, S. K.; Schulmeyer, Carla; Strehl, J.; Koch, Matthias (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Accuracy of colposcopic findings in detecting vaginal intraepithelial neoplasia: a retrospective study - Stuebs, Frederik A.; Koch, Martin; Mehlhorn, Grit; Gaß, Paul; Schulmeyer, Carla; Hartmann, Arndt; Strehl, Johanna; Adler, Werner; Beckmann, Matthias; Renner, Stefan (Archives of Gynecology and Obstetrics, 2020)
Purpose: Malignancies of the vagina are rare, but colposcopy-directed biopsies play a major role in detecting vaginal intraepithelial lesions. Data of accuracy in detecting neoplasia of the vagina are very rare compared to accuracy in detecting cervical neoplasia. The aim of this study was to evaluate the accuracy of colposcopy-directed biopsy in comparison with clinical findings of the examiner. Methods: The accuracy of colposcopy-directed biopsy was compared with the clinical finding in relation to the patient’s age and the examiner’s level of training. This was done in combination with PAP-smear, HPV-test results, and the history of other malignancies of the lower genital tract. The data were collected between January 2014 and February 2018 at the certified Dysplasia Unit of the University Hospital Erlangen. Results: In total, 253 biopsies from 253 women from the vagina were obtained. The overall accuracy of biopsy in comparison with clinical finding was 52.17% for all entities—benign lesions, low-grade squamous intraepithelial lesions (LSILs), high-grade squamous intraepithelial lesions (HSILs), and vaginal carcinoma. The accuracy for detecting HSIL was 82.46% (47/57), with an underdiagnosis rate of 15.79% and an overdiagnosis rate of 1.79%. Conclusion: With a sensitivity of over 80%, colposcopy-directed biopsy plays an important role in detecting vaginal–HSIL. A highly experienced practitioner is increasing the sensitivity in detecting vaginal–HSIL. Careful examination is required in women with a history of HSIL of the lower genital tract or with simultaneous neoplasia because they are of greater risk of developing vaginal malignancies. The combination of careful clinical work up, PAP-smear, HPV-testing, and colposcopy-guided biopsy is crucial in detecting vaginal–HSIL.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Colposcopy-directed biopsy; High-grade squamous intraepithelial lesion (HSIL); Vaginal cancer; Vaginal intraepithelial neoplasia (VaIN)

Accuracy of colposcopy-directed biopsy in detecting early cervical neoplasia: a retrospective study - Stuebs, Frederik A.; Schulmeyer, Carla E.; Mehlhorn, Grit; Gaß, Paul; Kehl, Sven; Renner, Simone K.; Renner, Stefan; Geppert, Carol-Immanuel; Adler, Werner; Hartmann, Arndt; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2019)
PurposeColposcopy-directed biopsy is a cornerstone method for diagnosing cervical intraepithelial neoplasia. The aim of this study was to evaluate the accuracy of colposcopy-directed biopsy in comparison with definitive surgery.MethodsThe accuracy of colposcopy-directed biopsy was compared with the final histology in relation to different types of transformation zone (TZ), the patient's age, and the examiner's level of training.ResultsThe overall accuracy of biopsy in comparison with definitive surgery was 71.9% for all entitiesbenign lesions, low-grade squamous intraepithelial lesions, high-grade squamous intraepithelial lesions (HSILs), and cervical carcinomawith an underdiagnosis rate of 11.8% and an overdiagnosis rate of 16.5%. The accuracy for detecting HSIL was 88% (401/455), with an underdiagnosis rate of 10.5% and overdiagnosis rate of 1.3%. The accuracy rates for detecting HSIL in women with TZ1, TZ2, or TZ3 were 92.2, 90.5, and 76.5%, respectively. The accuracy rates for detecting HSIL in the different age groups were 93.1% (age 0-34), 83.6% (age 34-55), and 80% (age 55 or older).ConclusionsA combination of the colposcopic findings, cytology, human papillomavirus testing, and colposcopy-directed biopsy is necessary for the correct diagnosis of HSIL. The accuracy rate depends on the TZ and the patient's age. The examiner's level of training does not have any substantial influence on the accuracy.
CRIS-Team WoS Importer:2019-03-08

Accuracy of radiological tumour size assessment and the risk for re-excision in a cohort of primary breast cancer patients - Meier-Meitinger, Martina; Rauh, Claudia; Adamietz, B.; Fasching, Peter; Schwab, Siegfried; Häberle, Lothar; Hein, Alexander; Bayer, Christian M.; Bani, Mayada; Lux, Michael P.; Hartmann, Arndt; Wachter, David Lukas; et al. (Ejso, 2012)
Background: Re-operations after breast conserving surgery (BCS) are necessary, when specimen margins are not free of breast cancer cells. This study explored the accuracy of preoperative tumour size assessment and its influence on the rate of re-excisions and mastectomies. Methods: The study included 1591 patients with invasive breast cancer, who were planned for BCS. Patient, staging and tumor characteristics were evaluated concerning their influence on re-excision and mastectomy rates. Patient and tumor characteristics comprised histopathological tumour size, HER2 status, multifocality, in situ component, grading (G), nodal status and hormone receptor (HR) status. Staging characteristics included deviation from pathological tumour size as measured by clinical examination, sonography and mammography. Results: In 1316 patients (83%) sufficient treatment was possible with one operation. 275 patients (17%) had to undergo at least one further surgery as a result of positive specimen margins. In 138 patients (9%) mastectomy was ultimately necessary. In patients with a positive HER2 status, a larger tumour size, underestimation by ultrasound, an in situ component and multifocality, the risk for a re-operation was about doubled. Tumour size deviation in the mammogram or the clinical tumour size assessment did not have significant influence to the re-excision rates. Conclusion: Tumour size and accurate presurgical assessment of the tumour size itself are independent predictors for the need of a second surgery or even a mastectomy in patients for whom a primary BCS was planned. © 2011 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer; Mastectomy; Re-excision; Tumour size; Ultrasound

Accuracy of sonographic fetal weight estimation: influence of the scan-to-delivery interval in combination with the applied weight estimation formula - Faschingbauer, Florian; Raabe, E.; Heimrich, J.; Faschingbauer, Cornelia; Schmid, M.; Mayr, Andreas; Schild, R. L.; Beckmann, Matthias; Kehl, Sven (Archives of Gynecology and Obstetrics, 2016)
To evaluate the influence of the time interval between examination and delivery on the accuracy of sonographic fetal weight estimation (WE).8723 singleton pregnancies were included in this retrospective cohort study. Fetuses were divided into eight groups with regard to the time interval between estimation and delivery (group 1: 0 days; group 2: 1-3 days; group 3: 4-7 days; group 4: 8-14 days; group 5: 15-21 days; group 6: 22-28 days; group 7: 29-35 days; group 8: 36-42 days). The accuracy of WE was compared between the different time interval groups and five commonly used formulas using means of percentage errors (MPE), medians of absolute percentage errors, and proportions of estimates within 10 % of actual birth weight.In group one, the Hadlock I and Warsof formula showed a systematic underestimation of fetal weight (negative MPEs). No systematic error was found with the Hadlock II formula and the equations of Merz and Shepard showed a systematic overestimation (positive MPEs). MPE values of the Hadlock I, II and Warsof formulas were closest to zero in WEs of group two. From group three to six, MPE values decreased continuously. With the Merz and Shepard equations MPEs were closest to zero in group four.The best accuracy of sonographic WE with most of the commonly used equations is achieved within a scan-to-delivery interval of 1 week.
EVALuna2:5556

Accuracy of vulvoscopic findings in detecting early vulvar neoplasia - Stuebs, F. A.; Mehlhorn, G.; Gaß, Paul; Schulmeyer, Carla; Adler, Werner; Strehl, J.; Hartmann, Arndt; Beckmann, Matthias; Renner, S. K.; Koch, Matthias (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

A comprehensive evaluation of interaction between genetic variants and use of menopausal hormone therapy on mammographic density - Rudolph, Anja; Fasching, Peter; Behrens, Sabine; Eilber, Ursula; Bolla, Manjeet K.; Wang, Qin; Thompson, Deborah; Czene, Kamila; Brand, Judith S.; Li, Jingmei; Scott, Christopher; Pankratz, V. Shane; et al. (Breast Cancer Research, 2015)
Mammographic density is an established breast cancer risk factor with a strong genetic component and can be increased in women using menopausal hormone therapy (MHT). Here, we aimed to identify genetic variants that may modify the association between MHT use and mammographic density.The study comprised 6,298 postmenopausal women from the Mayo Mammography Health Study and nine studies included in the Breast Cancer Association Consortium. We selected for evaluation 1327 single nucleotide polymorphisms (SNPs) showing the lowest P-values for interaction (P int) in a meta-analysis of genome-wide gene-environment interaction studies with MHT use on risk of breast cancer, 2541 SNPs in candidate genes (AKR1C4, CYP1A1-CYP1A2, CYP1B1, ESR2, PPARG, PRL, SULT1A1-SULT1A2 and TNF) and ten SNPs (AREG-rs10034692, PRDM6-rs186749, ESR1-rs12665607, ZNF365-rs10995190, 8p11.23-rs7816345, LSP1-rs3817198, IGF1-rs703556, 12q24-rs1265507, TMEM184B-rs7289126, and SGSM3-rs17001868) associated with mammographic density in genome-wide studies. We used multiple linear regression models adjusted for potential confounders to evaluate interactions between SNPs and current use of MHT on mammographic density.No significant interactions were identified after adjustment for multiple testing. The strongest SNP-MHT interaction (unadjusted P int <0.0004) was observed with rs9358531 6.5kb 5' of PRL. Furthermore, three SNPs in PLCG2 that had previously been shown to modify the association of MHT use with breast cancer risk were found to modify also the association of MHT use with mammographic density (unadjusted P int <0.002), but solely among cases (unadjusted P int SNP×MHT×case-status <0.02).The study identified potential interactions on mammographic density between current use of MHT and SNPs near PRL and in PLCG2, which require confirmation. Given the moderate size of the interactions observed, larger studies are needed to identify genetic modifiers of the association of MHT use with mammographic density.
EVALuna2:9284

A content-based review of mobile health applications for breast cancer prevention and education: Characteristics, quality and functionality analysis - Altmannshofer, Stefanie; Flaucher, Madeleine; Beierlein, Milena; Eskofier, Björn; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna (Digital Health, 2024)
Objective: Mobile Health apps could be a feasible and effective tool to raise awareness for breast cancer prevention and to support women to change their behaviour to a healthier lifestyle. The aim of this study was to analyse the characteristics and quality of apps designed for breast cancer prevention and education. Methods: We conducted a systematic search for apps covering breast cancer prevention topics in the Google Play and Apple App Store accessible from Germany using search terms either in German or in English. Only apps with a last update after June 2020 were included. The apps identified were downloaded and evaluated by two independent researchers. App quality was analysed using the Mobile Application Rating Scale (MARS). Associations of app characteristics and MARS rating were analysed. Results: We identified 19 apps available in the Google Play Store and seven apps available in the Apple App Store that met all inclusion criteria. The mean MARS score was 3.07 and 3.50, respectively. Functionality was the highest-scoring domain. Operating system, developer (healthcare), download rates and time since the last update were significantly associated with overall MARS score. In addition, the presence of the following app functions significantly influenced MARS rating: breast self-examination tutorial, reminder for self-examination, documentation feature and education about breast cancer risk factors. Conclusions: Although most of the apps offer important features for breast cancer prevention, none of the analysed apps combined all functions. The absence of healthcare professionals’ expertise in developing apps negatively affects the overall quality.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Breast cancer; MARS; mHealth; mobile apps; prevention; quality; rating

Active Participation, Mind–Body Stabilization, and Coping Strategies with Integrative Medicine in Breast Cancer Patients - Theuser, Anna-Katharin; Antoniadis, Sophia; Langemann, Hanna; Wasner, Sonja; Grasruck, Katharina; Dietzel-Drentwett, Svenja; Fasching, Peter; Beckmann, Matthias; Hack, Carolin (Integrative Cancer Therapies, 2021)
Purpose: Increasing numbers of breast cancer survivors have led to a growing demand for integrative medicine. When patients have completed treatments associated with severe side effects, attention turns to reducing psychological symptoms, coping behavior, and self-care. The aim of this study was to assess patient-reported benefits in relation to active participation, mind–body stabilization, and coping strategies in breast cancer patients receiving integrative medicine. Methods: In a cross-sectional study, health counseling and treatment provided by a standardized integrative medicine consultancy service at the University Breast Center of Franconia were evaluated in 75 breast cancer patients over a 15-month period. At the baseline, the patients answered a questionnaire on their medical history, symptoms, and the treatment goals they were hoping to achieve with integrative medicine. Patient-reported outcomes relative to active participation, mind–body stabilization, and coping strategies were analyzed. Results: A large majority of the patients had previous experience with integrative medicine (91%). Most reported that they achieved their treatment goals with integrative medicine. Ninety-one percent achieved active participation in cancer treatment, 90% mind–body stabilization, and 79% improvement in coping strategies. Besides active participation, which was greatest in patients with stable disease, the success of integrative therapy was independent of age, concomitant diseases, previous integrative medicine experience, treatment state, and systemic cancer therapy. Conclusion: Breast cancer patients benefit from the counseling and treatment provided with integrative medicine in mind–body stabilization and coping with cancer. Active participation in cancer treatment is important for the patients. Integrative treatment services should form part of routine patient care.
CRIS-Team Scopus Importer:2021-03-19
Keywords: active participation; breast cancer; complementary and alternative medicine; coping; integrative medicine; mind–body; oncology

Addition of triple negativity of breast cancer as an indicator for germline mutations in predisposing genes increases sensitivity of clinical selection criteria - Hoyer, Juliane; Vasileiou, Georgia; Uebe, Steffen; Wunderle, Marius; Kraus, Cornelia; Fasching, Peter; Thiel, Christian; Hartmann, Arndt; Beckmann, Matthias; Lux, Michael P.; Reis, André (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common cancer in women. 12-15% of all tumors are triple-negative breast cancers (TNBC). So far, TNBC has been mainly associated with mutations in BRCA1. The presence of other predisposing genes seems likely since DNA damage repair is a complex process that involves several genes. Therefore we investigated if mutations in other genes are involved in cancer development and whether TNBC is an additional indicator of mutational status besides family history and age of onset. METHODS: We performed a germline panel-based screening of 10 high and low-moderate penetrance breast cancer susceptibility genes (BRCA1, BRCA2, ATM, CDH1, CHEK2, NBN, PALB2, RAD51C, RAD51D and TP53) in 229 consecutive individuals affected with TNBC unselected for age, family history or bilateral disease. Within this cohort we compared the number of mutation carriers fulfilling clinical selection criteria with the total number of carriers identified. RESULTS: Age at diagnosis ranged from 23 to 80 years with an average age of 50.2 years. In 57 women (24.9%) we detected a pathogenic mutation, with a higher frequency (29.7%) in the group manifesting cancer before 60 years. Deleterious BRCA1 mutations occurred in 14.8% of TNBC patients. These were predominantly recurrent frameshift mutations (24/34, 70.6%). Deleterious BRCA2 mutations occurred in 5.7% of patients, all but one (c.1813dupA) being unique. While no mutations were found in CDH1 and TP53, 10 mutations were detected in one of the six other predisposition genes. Remarkably, neither of the ATM, RAD51D, CHEK2 and PALB2 mutation carriers had a family history. Furthermore, patients with non-BRCA1/2 mutations were not significantly younger than mutation negative women (p = 0.3341). Most importantly, among the 57 mutation carriers, ten (17.5%) would be missed using current clinical testing criteria including five (8%) with BRCA1/2 mutations. CONCLUSIONS: In summary, our data confirm and expand previous studies of a high frequency of germline mutations in genes associated with ineffective repair of DNA damage in women with TNBCs. Neither age of onset, contralateral disease nor family history were able to discern all mutation positive individuals. Therefore, TNBC should be considered as an additional criterion for panel based genetic testing.
EVALuna2:34811

A diet rich in Mailllard reaction products protects LDL against copper induced oxidation ex vivo, a human intervention trial - Dittrich, Ralf; Dragonas, Charalampos; Kannenkeril, D.; Hoffmann, Inge; Müller, Andreas; Beckmann, Matthias; Pischetsrieder, Monika (Food Research International, 2009)
Maillard reaction products (MRPs) have antioxidative properties in vitro but the influence of a diet rich in MRPs on oxidative damage in vivo remains unknown. In this study, the influence of thermally processed foods rich in MRPs on copper induced oxidation of human low-density lipoprotein (LDL) in vitro was examined. Moreover, oxidative resistance of LDL (OR) in blood plasma of eight healthy subjects was monitored, who consumed diets poor and rich in MRPs in weekly turn for 3 weeks. Dark beer, bread crust, and roasted coffee led to a statisticaIly significant increased OR in vitro compared to pale beer, bread crumb, and raw coffee. The consumption of a diet rich in MRPS significantly increased plasma OR compared to the diet poor in MRPs by 35.5%. This study indicates that thermally processed foods rich in MRPs inhibit the LDL oxidation in vitro and have the ability to reduce oxidative modification of LDL in vivo.
UnivIS-Import:2015-04-14:Pub.2009.nat.dchph.llmch.adietr
Keywords: Beer; Coffee; Diet; LDL oxidation; Maillard reaction products

Adjuvant radiotherapy and local recurrence in vulvar cancer – a subset analysis of the AGO-CaRE-1 study - Woelber, Linn; Prieske, Katharina; Eulenburg, Christine zu; Corradini, Stefanie; Petersen, Cordula; Bommert, Mareike; Blankenstein, Thomas; Hilpert, Felix; de Gregorio, Nikolaus; Iborra, Severine; Sehouli, Jalid; Ignatov, Atanas; et al. (Gynecologic Oncology, 2021)
Background: The impact of adjuvant radiotherapy (RT) to the vulva with regard to prognosis and local recurrence in patients with vulvar squamous cell cancer (VSCC) is poorly described. Patients and methods: In the AGO-CaRE-1 study 1618 patients with primary VSCC FIGO stage ≥ IB, treated between 1998-2008, were documented. In this retrospective subanalysis, 360 patients were included based on the following criteria: nodal involvement (pN+), known RT treatment and known radiation fields. Results: The majority had pT1b/pT2 tumors (n=299; 83.1%). In 76.7%, R0 resection was achieved. 57/360 (15.8%) N+ patients were treated with adjuvant RT to the groins/pelvis and 146/360 (40.5%) received adjuvant RT to the vulva and groins/pelvis. 157/360 (43.6%) patients did not receive any adjuvant RT. HPV status was available in 162/360 patients (45.0%), 75/162 tumors were HPV+(46.3%), 87/162 (53.7%) HPV-. During a median follow-up of 17.2 months, recurrence at the vulva only occurred in 25.5% of patients without adjuvant RT, in 22.8% of patients with adjuvant RT to groins/pelvis and in 15.8% of patients with adjuvant RT to the vulva and groins/pelvis respectively. The risk reducing effect of local RT was independent of the resection margin status. 50% disease free survival time (50% DFST) indicated a stronger impact of adjuvant RT to the vulva in HPV+ compared to HPV- patients (50% DFST 20.7 months vs. 17.8 months). Conclusion: Adjuvant RT to the vulva was associated with a lower risk for local recurrence in N+ VSCC independent of the resection margin status. This observation was more pronounced in patients with HPV+ tumors in comparison to HPV– tumors.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Adjuvant radiotherapy; HPV; Local recurrence; Prognosis; Vulvar cancer

Adult body mass index and risk of ovarian cancer by subtype: a Mendelian randomization study - Dixon, Suzanne C.; Nagle, Christina M.; Thrift, Aaron P.; Pharoah, Paul D. P.; Pearce, Celeste Leigh; Zheng, Wei; Painter, Jodie N.; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Lambrechts, Diether; Vergote, Ignace; et al. (International Journal of Epidemiology, 2016)
BACKGROUND: Observational studies have reported a positive association between body mass index (BMI) and ovarian cancer risk. However, questions remain as to whether this represents a causal effect, or holds for all histological subtypes. The lack of association observed for serous cancers may, for instance, be due to disease-associated weight loss. Mendelian randomization (MR) uses genetic markers as proxies for risk factors to overcome limitations of observational studies. We used MR to elucidate the relationship between BMI and ovarian cancer, hypothesizing that genetically predicted BMI would be associated with increased risk of non-high grade serous ovarian cancers (non-HGSC) but not HGSC. METHODS: We pooled data from 39 studies (14 047 cases, 23 003 controls) in the Ovarian Cancer Association Consortium. We constructed a weighted genetic risk score (GRS, partial F-statistic = 172), summing alleles at 87 single nucleotide polymorphisms previously associated with BMI, weighting by their published strength of association with BMI. Applying two-stage predictor-substitution MR, we used logistic regression to estimate study-specific odds ratios (OR) and 95% confidence intervals (CI) for the association between genetically predicted BMI and risk, and pooled these using random-effects meta-analysis. RESULTS: Higher genetically predicted BMI was associated with increased risk of non-HGSC (pooled OR = 1.29, 95% CI 1.03-1.61 per 5 units BMI) but not HGSC (pooled OR = 1.06, 95% CI 0.88-1.27). Secondary analyses stratified by behaviour/subtype suggested that, consistent with observational data, the association was strongest for low-grade/borderline serous cancers (OR = 1.93, 95% CI 1.33-2.81). CONCLUSIONS: Our data suggest that higher BMI increases risk of non-HGSC, but not the more common and aggressive HGSC subtype, confirming the observational evidence.
EVALuna2:32972

Adult height is associated with increased risk of ovarian cancer: a Mendelian randomisation study - Dixon-Suen, Suzanne C.; Nagle, Christina M.; Thrift, Aaron P.; Pharoah, Paul D. P.; Ewing, Ailith; Pearce, Celeste Leigh; Zheng, Wei; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Lambrechts, Diether; Vergote, Ignace; et al. (British Journal of Cancer, 2018)
BACKGROUND: Observational studies suggest greater height is associated with increased ovarian cancer risk, but cannot exclude bias and/or confounding as explanations for this. Mendelian randomisation (MR) can provide evidence which may be less prone to bias. METHODS: We pooled data from 39 Ovarian Cancer Association Consortium studies (16,395 cases; 23,003 controls). We applied two-stage predictor-substitution MR, using a weighted genetic risk score combining 609 single-nucleotide polymorphisms. Study-specific odds ratios (OR) and 95% confidence intervals (CI) for the association between genetically predicted height and risk were pooled using random-effects meta-analysis. RESULTS: Greater genetically predicted height was associated with increased ovarian cancer risk overall (pooled-OR (pOR) = 1.06; 95% CI: 1.01-1.11 per 5 cm increase in height), and separately for invasive (pOR = 1.06; 95% CI: 1.01-1.11) and borderline (pOR = 1.15; 95% CI: 1.02-1.29) tumours. CONCLUSIONS: Women with a genetic propensity to being taller have increased risk of ovarian cancer. This suggests genes influencing height are involved in pathways promoting ovarian carcinogenesis.
EVALuna2:209946

A genome-wide gene-environment interaction study of breast cancer risk for women of European ancestry - Middha, Pooja; Wang, Xiaoliang; Behrens, Sabine; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Aronson, Kristan J.; et al. (Breast Cancer Research, 2023)
BACKGROUND: Genome-wide studies of gene-environment interactions (G×E) may identify variants associated with disease risk in conjunction with lifestyle/environmental exposures. We conducted a genome-wide G×E analysis of 7.6 million common variants and seven lifestyle/environmental risk factors for breast cancer risk overall and for estrogen receptor positive (ER +) breast cancer. METHODS: Analyses were conducted using 72,285 breast cancer cases and 80,354 controls of European ancestry from the Breast Cancer Association Consortium. Gene-environment interactions were evaluated using standard unconditional logistic regression models and likelihood ratio tests for breast cancer risk overall and for ER + breast cancer. Bayesian False Discovery Probability was employed to assess the noteworthiness of each SNP-risk factor pairs. RESULTS: Assuming a 1 × 10-5 prior probability of a true association for each SNP-risk factor pairs and a Bayesian False Discovery Probability < 15%, we identified two independent SNP-risk factor pairs: rs80018847(9p13)-LINGO2 and adult height in association with overall breast cancer risk (ORint = 0.94, 95% CI 0.92-0.96), and rs4770552(13q12)-SPATA13 and age at menarche for ER + breast cancer risk (ORint = 0.91, 95% CI 0.88-0.94). CONCLUSIONS: Overall, the contribution of G×E interactions to the heritability of breast cancer is very small. At the population level, multiplicative G×E interactions do not make an important contribution to risk prediction in breast cancer.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Breast cancer; European ancestry; Gene-environment interactions; Genetic epidemiology

Age, treatment and prognosis of patients with squamous cell vulvar cancer (VSCC) - analysis of the AGO-CaRE-1 study - Prieske, Katharina; Woelber, Linn; Muallem, Mustafa Zelal; Eulenburg, Christine; Jueckstock, Julia Kathrin; Hilpert, Felix; de Gregorio, Nikolaus; Iborra, Severine; Ignatov, Atanas; Hillemanns, Peter; Fuerst, Sophie; Strauss, Hans Georg; et al. (Gynecologic Oncology, 2021)
Background: Despite an increasing incidence with simultaneous decreasing age of onset, vulvar squamous cell carcinoma (VSCC) is still a disease that mainly effects the elderly population. Data on the association of age with prognosis and treatment patterns in VSCC are sparse. Methods: This is an analysis of the AGO-CaRE-1 cohort. Patients with VSCC (FIGO stage ≥1B), treated at 29 cancer centers in Germany from 1998 to 2008, were included in a centralized database (n = 1618). In this subgroup analysis patients were analyzed according to age [<50 yrs. (n = 220), 50–69 yrs. (n = 506), ≥70 yrs. (n = 521)] with regard to treatment patterns and prognosis. Only patients with documented age, surgical groin staging and known nodal status were included (n = 1247). Median follow-up was 27.5 months. Results: At first diagnosis, women ≥70 yrs. presented with more advanced tumor stages (<0.001), larger tumor diameter (<0.001), poorer ECOG status (<0.001), more frequent HPV negative tumors (p = 0.03) as well as a higher rate of nodal involvement (<0.001). Disease recurrence occurred significantly more often in elderly patients (p = 0.001) and age as well as ECOG status, microscopic residual resection, tumor stage, grading, and (chemo)radiation were independent prognostic factors for death or recurrence in multivariate analysis. 2-year disease-free survival rates were 59.3% (≥70 yrs), 65.8% (50–69 yrs) and 81.1% (<50 yrs), respectively (p < 0.001). Conclusions: Older women with VSCC present with advanced tumor stages at first diagnosis and have an increased risk of recurrence as well as a decreased 2-year DFS in comparison to younger patients. Potential reasons could be self-awareness and/or more aggressive tumor biology due to HPV independent disease.
CRIS-Team Scopus Importer:2021-03-12
Keywords: Age; Elderly; HPV; Lichen sclerosus; TP53; Vulvar cancer

Aggregation tests identify new gene associations with breast cancer in populations with diverse ancestry - Mueller, Stefanie H.; Lai, Alvina G.; Valkovskaya, Maria; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Lush, Michael; Abu-Ful, Zomoruda; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; et al. (Genome Medicine, 2023)
Background: Low-frequency variants play an important role in breast cancer (BC) susceptibility. Gene-based methods can increase power by combining multiple variants in the same gene and help identify target genes. Methods: We evaluated the potential of gene-based aggregation in the Breast Cancer Association Consortium cohorts including 83,471 cases and 59,199 controls. Low-frequency variants were aggregated for individual genes’ coding and regulatory regions. Association results in European ancestry samples were compared to single-marker association results in the same cohort. Gene-based associations were also combined in meta-analysis across individuals with European, Asian, African, and Latin American and Hispanic ancestry. Results: In European ancestry samples, 14 genes were significantly associated (q < 0.05) with BC. Of those, two genes, FMNL3 (P = 6.11 × 10−6) and AC058822.1 (P = 1.47 × 10−4), represent new associations. High FMNL3 expression has previously been linked to poor prognosis in several other cancers. Meta-analysis of samples with diverse ancestry discovered further associations including established candidate genes ESR1 and CBLB. Furthermore, literature review and database query found further support for a biologically plausible link with cancer for genes CBLB, FMNL3, FGFR2, LSP1, MAP3K1, and SRGAP2C. Conclusions: Using extended gene-based aggregation tests including coding and regulatory variation, we report identification of plausible target genes for previously identified single-marker associations with BC as well as the discovery of novel genes implicated in BC development. Including multi ancestral cohorts in this study enabled the identification of otherwise missed disease associations as ESR1 (P = 1.31 × 10−5), demonstrating the importance of diversifying study cohorts.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Breast cancer susceptibility; Diverse ancestry; Gene regulation; Genome-wide association study; Rare variants

A hybrid method towards automated nipple detection in 3D breast ultrasound images - Wang, Lei; Böhler, Tobias; Zöhrer, Fabian; Georgii, Joachim; Rauh, Claudia; Fasching, Peter; Brehm, Barbara; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Uder, Michael; Hahn, Horst K. (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2014)
In clinical work-up of breast cancer, nipple position is an important marker to locate lesions. Moreover, it serves as an effective landmark to register a 3D automated breast ultrasound (ABUS) images to other imaging modalities, e.g., X-ray mammography, tomosynthesis or magnetic resonance imaging (MRI). However, the presence of speckle noises caused by the interference waves and variant imaging directions poses challenges to automatically identify nipple positions. In this work, a hybrid fully automatic method to detect nipple positions in ABUS images is presented. The method extends the multi-scale Laplacian-based method that we proposed previously, by integrating a specially designed Hessian-based method to locate the shadow area beneath the nipple and areola. Subsequently, the likelihood maps of nipple positions generated by both methods are combined to build a joint-likelihood map, where the final nipple position is extracted. To validate the efficiency and robustness, the extended hybrid method was tested on 926 ABUS images, resulting in a distance error of 7.08±10.96 mm (mean±standard deviation).
EVALuna2:14367

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Aktuelles zum gesetzlichen Früherkennungsprogramm des Zervixkarzinoms in Deutschland - Behrens, Annika; Beckmann, Matthias; Stübs, Frederik (gynäkologische praxis, 2023)
The statutory cancer screening program (GKFP) covers regulations for early detection and screening of cancer for men and women in Germany. Costs for these assessments are covered by the health insurance. The G-BA is in charge of the organized screening, in which women between 20 and 34 years of age are entitled to a yearly screening assessment based on cytology smears. Women of 35 years and older are offered a combination of HPV testing and cytology every 3 years. Data showed a reduced incidence of invasive carcinoma of the cervix as well as of precancerous lesions and overall mortality. Participation in screening assessments for cervical cancer is recommended independently of HPV vaccination status for all women in the according age range. Prophylactic vaccination against HPV high risk types are recommended for all children and adolescents independently of the gender between 9–14 years of age, but before the first sexual intercourse. However, the license according to the European Medicines Agency (EMA) covers all children irrespective of the gender starting at 9 years of age without defining an upper age limit. At the moment, two HPV vaccines are available. For both vaccines, a 2-dose-vaccination regimen is recommended. HPV vaccination can also be valuable for adolescents and adults older than 17 years and to reduce reinfection rates after HPV infection. In this case, HPV vaccination is solely a prophylactic measure and has no therapeutic effect.
CRIS-Team Scopus Importer:2023-10-20
Keywords: cervical carcinoma; primary prevention; prophylactic vaccination; screening

A large-scale assessment of two-way SNP interactions in breast cancer susceptibility using 46 450 cases and 42 461 controls from the breast cancer association consortium - Milne, Roger L.; Herranz, Jesus; Michailidou, Kyriaki; Dennis, Joe; Tyrer, Jonathan P.; Zamora, M. Pilar; Arias-Perez, Jose Ignacio; Gonzalez-Neira, Anna; Pita, Guillermo; Alonso, M. Rosario; Wang, Qin; Bolla, Manjeet K.; et al. (Human Molecular Genetics, 2014)
Part of the substantial unexplained familial aggregation of breast cancer may be due to interactions between common variants, but few studies have had adequate statistical power to detect interactions of realistic magnitude. We aimed to assess all two-way interactions in breast cancer susceptibility between 70 917 single nucleotide polymorphisms (SNPs) selected primarily based on prior evidence of a marginal effect. Thirty-eight international studies contributed data for 46 450 breast cancer cases and 42 461 controls of European origin as part of a multi-consortium project (COGS). First, SNPs were preselected based on evidence (P < 0.01) of a per-allele main effect, and all two-way combinations of those were evaluated by a per-allele (1 d.f.) test for interaction using logistic regression. Second, all 2.5 billion possible two-SNP combinations were evaluated using Boolean operation-based screening and testing, and SNP pairs with the strongest evidence of interaction (P < 10(-4)) were selected for more careful assessment by logistic regression. Under the first approach, 3277 SNPs were preselected, but an evaluation of all possible two-SNP combinations (1 d.f.) identified no interactions at P < 10(-8). Results from the second analytic approach were consistent with those from the first (P > 10(-10)). In summary, we observed little evidence of two-way SNP interactions in breast cancer susceptibility, despite the large number of SNPs with potential marginal effects considered and the very large sample size. This finding may have important implications for risk prediction, simplifying the modelling required. Further comprehensive, large-scale genome-wide interaction studies may identify novel interacting loci if the inherent logistic and computational challenges can be overcome.
EVALuna2:9207

Amniotic-Umbilical-to-Cerebral Ratio-A Novel Ratio Combining Doppler Parameters and Amniotic Fluid Volume to Predict Adverse Perinatal Outcome in SGA Fetuses at Term - Stumpfe, Florian; Faschingbauer, Florian; Kehl, Sven; Pretscher, Jutta; Emons, Julius; Gaß, Paul; Mayr, Andreas; Schmid, Matthias; Beckmann, Matthias; Stelzl, Patrick (Ultraschall in der Medizin, 2020)
Purpose â Introduction of a novel ratio-the amniotic-umbilical-to-cerebral ratio (AUCR)-to predict adverse perinatal outcome in SGA fetuses at term and comparison of its predictive accuracy with established parameters. Materials and Methods â This retrospective cohort study included 165 singleton pregnancies with SGA fetuses (birth weight <âŠ10 thpercentile) at term. Cases with planned vaginal delivery and documented pulsatility indices (PI) of the umbilical artery (UA), middle cerebral artery (MCA), and single deepest pocket (SDP) were included. CPR was calculated as the ratio between MCA PI and UA PI, UCR as the ratio between UA PI and MCA PI. AUCR was defined as follows: SDP/(UA PI/MCA PI). Adverse perinatal outcomes were defined as operative intervention (OI), OI due to fetal distress, admission to the neonatal intensive care unit (NICU), and composite adverse perinatal outcome (CAPO). Associations between Doppler parameters and these outcomes were estimated using regression analyses. Results â OI was statistically significantly associated with UCR, SDP, and AUCR, whereas no association was observed for UA PI, MCA PI, and CPR. Fetuses requiring OI due to fetal distress revealed a significantly higher UA PI and UCR as well as a lower MCA PI, CPR, and AUCR. With regard to NICU admission and CAPO, a significantly higher UA PI and lower CPR were found. Furthermore, a significant association was shown for SDP, UCR, and AUCR. AUCR achieved the best area under the curve for all outcome parameters. Conclusion â AUCR leads to an improvement in the prediction of unfavorable outcome in SGA fetuses at term. Furthermore, results of our study show that UCR might be superior to CPR.
CRIS-Team Scopus Importer:2020-11-13
Keywords: amniotic fluid; AUCR; CPR; SDP; UCR

Analyses of germline variants associated with ovarian cancer survival identify functional candidates at the 1q22 and 19p12 outcome loci - Glubb, Dylan M.; Johnatty, Sharon E.; Quinn, Michael C. J.; O'Mara, Tracy A.; Tyrer, Jonathan P.; Gao, Bo; Fasching, Peter; Beckmann, Matthias; Lambrechts, Diether; Vergote, Ignace; Edwards, Digna R. Velez; Beeghly-Fadiel, Alicia; et al. (Oncotarget, 2017)
We previously identified associations with ovarian cancer outcome at five genetic loci. To identify putatively causal genetic variants and target genes, we prioritized two ovarian outcome loci (1q22 and 19p12) for further study. Bioinformatic and functional genetic analyses indicated that MEF2D and ZNF100 are targets of candidate outcome variants at 1q22 and 19p12, respectively. At 19p12, the chromatin interaction of a putative regulatory element with the ZNF100 promoter region correlated with candidate outcome variants. At 1q22, putative regulatory elements enhanced MEF2D promoter activity and haplotypes containing candidate outcome variants modulated these effects. In a public dataset, MEF2D and ZNF100 expression were both associated with ovarian cancer progression-free or overall survival time. In an extended set of 6,162 epithelial ovarian cancer patients, we found that functional candidates at the 1q22 and 19p12 loci, as well as other regional variants, were nominally associated with patient outcome; however, no associations reached our threshold for statistical significance (p<1×10-5). Larger patient numbers will be needed to convincingly identify any true associations at these loci.
EVALuna2:36127

Analysis and classification of oncology activities on the way to workflow based single source documentation in clinical information systems - Wagner, Stefan; Beckmann, Matthias; Wullich, Bernd; Seggewies, Christof; Ries, Markus; Buerkle, Thomas; Prokosch, Hans-Ulrich (BMC Medical Informatics and Decision Making, 2015)
Today, cancer documentation is still a tedious task involving many different information systems even within a single institution and it is rarely supported by appropriate documentation workflows.In a comprehensive 14 step analysis we compiled diagnostic and therapeutic pathways for 13 cancer entities using a mixed approach of document analysis, workflow analysis, expert interviews, workflow modelling and feedback loops. These pathways were stepwise classified and categorized to create a final set of grouped pathways and workflows including electronic documentation forms.A total of 73 workflows for the 13 entities based on 82 paper documentation forms additionally to computer based documentation systems were compiled in a 724 page document comprising 130 figures, 94 tables and 23 tumour classifications as well as 12 follow-up tables. Stepwise classification made it possible to derive grouped diagnostic and therapeutic pathways for the three major classes - solid entities with surgical therapy - solid entities with surgical and additional therapeutic activities and - non-solid entities. For these classes it was possible to deduct common documentation workflows to support workflow-guided single-source documentation.Clinical documentation activities within a Comprehensive Cancer Center can likely be realized in a set of three documentation workflows with conditional branching in a modern workflow supporting clinical information system.
EVALuna2:145

Analysis of GDF15 and IGFBP7 in Hyperemesis Gravidarum Support Causality - Fejzo, Marlena S.; Fasching, Peter; Schneider, Michael; Schwitulla, Judith; Beckmann, Matthias; Schwenke, Eva; Macgibbon, Kimber W.; Mullin, Patrick M. (Geburtshilfe und Frauenheilkunde, 2019)
Objective Hyperemesis gravidarum, severe nausea and vomiting in pregnancy, occurs in up to 2% of pregnancies and leads to significant weight loss, dehydration, electrolyte imbalance, and ketonuria. It is associated with both maternal and fetal morbidity. Familial aggregation studies and twin studies suggest a genetic component. In a recent GWAS, we showed that placentation, appetite, and cachexia genes GDF15 and IGFBP7 are linked to hyperemesis gravidarum (HG). The purpose of this study is to determine whether GDF15 and IGFBP7 are upregulated in HG patients. Methods We compared serum levels of GDF15 and IGFBP7 at 12 and 24 weeks' gestation in women hospitalized for HG, and two control groups, women with nausea and vomiting of pregnancy (NVP), and women with no NVP. Results We show GDF15 and IGFBP7 serum levels are significantly increased in women with HG at 12 weeks' gestation. Serum levels of hCG are not significantly different between cases and controls. At 24 weeks gestation, when symptoms have largely resolved, there is no difference in GDF15 and IGFBP7 serum levels between cases and controls. Conclusion This study supports GDF15 and IGFBP7 in the pathogenesis of HG and may be useful for prediction and diagnosis. The GDF15-GFRAL brainstem-activated pathway was recently identified and therapies to treat conditions of abnormal appetite are under intense investigation. Based on our findings, HG should be included.
CRIS-Team Scopus Importer:2019-05-02
Keywords: GDF15; GFRAL; hyperemesis gravidarum; IGFBP7; nausea and vomiting of pregnancy

Analysis of motives and patient satisfaction in oncological second opinions provided by a certified university breast and gynecological cancer center - Löhberg, Christian; Meyer, Julia; Häberle, Lothar; Hack, Carolin; Jud, Sebastian; Hein, Alexander; Wunderle, Marius; Emons, Julius; Gaß, Paul; Fasching, Peter; Egloffstein, Sainab; Krebs, Jessica; et al. (Archives of Gynecology and Obstetrics, 2020)
Purpose: Second opinions in oncology are becoming increasingly important in an era of more complex treatments and a growing demand for information by patients. Therefore, we analyzed their effects and influencing factors like patients’ motives, subjective extent of information and satisfaction with communications. Methods: This prospective study evaluated second opinions for patients with breast cancer or gynecological malignancy. The patients received a questionnaire before and two months after, which inquired expectations, reasons, and satisfaction with the second opinion and the attending physicians. Results: A total of 164 patients were included and the majority had breast cancer (75.0%). Receiving the second opinion made 89.7% feel better informed, their need for information decreased (from 75.3% to 39.2%, P < 0.0001), and satisfaction with doctor–patient communications increased (from 61.9 to 91.8%, P = 0.0002). There were various reasons for requesting a second opinion, e.g., the extremely stressful situation of a cancer diagnosis, hope for change in the treatment recommendation or dissatisfaction with the initial physicians. Conclusions: Second opinions can lead to significantly greater patient satisfaction, meeting the need for information and leading to better management of patients in the extremely stressful situation of a cancer diagnosis. Doctor–patient communications play a key role.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Breast cancer; Doctor–patient communication; Gynecological malignancy; Oncology center; Patient satisfaction; Second opinion

Analysis of Oncological Second Opinions in a Certified University Breast and Gynecological Cancer Center in Relation to Complementary and Alternative Medicine - Hack, Carolin; Wasner, Sonja; Meyer, Julia; Häberle, Lothar; Jud, Sebastian; Hein, Alexander; Wunderle, Marius; Emons, Julius; Gaß, Paul; Fasching, Peter; Egloffstein, Sainab; Beckmann, Matthias; et al. (Complementary Medicine Research, 2020)
Introduction: Oncological second opinions are becoming increasingly important given more complex treatment strategies, simultaneously more patients use complementary and alternative medicine (CAM), and many comprehensive cancer centers initiate integrative medicine programs. The present study focuses on analyzing the effects of a second opinion in relation to attitudes toward CAM. Methods: In this prospective study patients (n = 97) with a diagnosis of breast cancer or gynecological malignancies who had requested a second opinion received a questionnaire before and after the second opinion concerning their attitudes toward CAM. Results: The majority of patients had breast cancer (72.2%, n = 70). Only 6.2% (n = 6) stated that they had been informed about CAM by the doctors who treated them first, 21.6% (n = 21) had received information about it when seeking the second opinion. After the first opinion, 42.3% (n = 41) wanted to try CAM, the same proportion trusted orthodox medicine alone. After the second opinion, 24 patients (24.7%) wanted to try CAM, while 38.1% (n = 37) relied exclusively on orthodox medicine. There was a significant correlation between an increased patients' need for information and interest in CAM (p = 0.02). Conclusions: Today, aspects of CAM still are very often no part of oncological first and second opinions. This might hence lead to discouraging patients to try out CAM and therefore integrative medicine programs in comprehensive cancer centers might be problem-solving.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Breast cancer; Complementary and alternative medicine; Gynecological malignancies; Integrative medicine; Oncological center; Second opinion

Analysis of Oncological Second Opinions in a Certified University Breast and Gynecological Cancer Center Regarding Consensus between the First and Second Opinion and Conformity with the Guidelines - Lux, Michael P.; Wasner, Sonja; Meyer, Julia; Häberle, Lothar; Hack, Carolin; Jud, Sebastian; Hein, Alexander; Wunderle, Marius; Emons, Julius; Gaß, Paul; Fasching, Peter; Egloffstein, Sainab; et al. (Breast Care, 2020)
Introduction: Oncological second opinions are becoming increasingly important in the era of complex treatments and established certified cancer centers. Oncological guidelines with the highest levels of evidence are available, but these can only be effective to the extent that they are implemented. Therefore, we analyzed the effects of second opinions with regard to their agreement with first opinions and conformity with guidelines. Methods: In 164 patients with a diagnosis of breast cancer or gynecological malignancy who requested a second opinion, the first and second opinions, established at the interdisciplinary tumor conference, and conformity with the guidelines were evaluated. Results: The first opinion was not in agreement with the guidelines in 34.8% (15.2% diagnosis, 12.8% surgical therapy, 13.4% systemic therapy, and 5.5% radiotherapy), and the recommendations were optimized in the second opinion in 56.7% (28.7% diagnosis, 15.9% surgical therapy, 30.5% systemic therapy, and 8.5% radiotherapy). Conclusions: Oncological second opinions showed significant effects and one-third of first opinions were not in conformity with the guidelines. In a significant proportion of cases, the existing treatment plan was changed or supplemented to allow modern and individualized treatment approaches.
CRIS-Team Scopus Importer:2020-09-04

A network analysis to identify mediators of germline-driven differences in breast cancer prognosis - Escala-Garcia, Maria; Abraham, Jean; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Ashworth, Alan; Auer, Paul L.; Auvinen, Päivi; Beckmann, Matthias; Beesley, Jonathan; Behrens, Sabine; Benitez, Javier; et al. (Nature Communications, 2020)
Identifying the underlying genetic drivers of the heritability of breast cancer prognosis remains elusive. We adapt a network-based approach to handle underpowered complex datasets to provide new insights into the potential function of germline variants in breast cancer prognosis. This network-based analysis studies 7.3 million variants in 84,457 breast cancer patients in relation to breast cancer survival and confirms the results on 12,381 independent patients. Aggregating the prognostic effects of genetic variants across multiple genes, we identify four gene modules associated with survival in estrogen receptor (ER)-negative and one in ER-positive disease. The modules show biological enrichment for cancer-related processes such as G-alpha signaling, circadian clock, angiogenesis, and Rho-GTPases in apoptosis.
CRIS-Team Scopus Importer:2020-01-24

A New Sonographic Weight Estimation Formula for Fetuses with Congenital Diaphragmatic Hernia - Faschingbauer, Florian; Mayr, Andreas; Geipel, A.; Gembruch, U.; Dammer, U.; Raabe, E.; Beckmann, Matthias; Kehl, Sven; Schild, R. L.; Siemer, J.; Schmid, M. (Ultraschall in der Medizin, 2015)
The accuracy of the sonographic weight estimation (WE) of fetuses with congenital diaphragmatic hernia (CDH) is significantly lower than that of fetuses without any malformations. The objective of this study was to develop and evaluate the first specific sonographic weight formula for fetuses with CDH.In a retrospective, multicenter, cohort study, a statistical estimation technique known as "multivariable fractional polynomial regression" was applied to a group of 146 fetuses with CDH. Each fetus underwent an ultrasound examination with complete biometric parameters within 7 days of delivery. A new formula was derived using the obtained data and was then compared with other commonly used equations. The accuracy of the different formulas was compared using means of signed percentage errors (SPE), medians of absolute percentage errors (MAPE), and fractions of estimates within prespecified error bounds.The new derived formula is: EFW = 10^(4.6729 107 371 + 0.2365 011 768 * HC + 0.2228 897 682 * FL^2 - 0.0129 895 773 * FL^3 - 1.0470 039 072 * (FL * HC)^0.5 + 0.0004 314 661 * (AC * HC) - [in case of liver herniation] 0.0062 112 122), where EFW is the estimated fetal weight, HC is the head circumference, AC is the abdominal circumference, and FL is the femur length. The new formula proved to be superior to other established equations, showing both the lowest median absolute percentage error (MAE: 6.97) and mean signed percentage error (SPE: 0.40), and the best distribution of absolute percentage errors within prespecified error bounds.This new formula significantly improves weight estimation in fetuses with CDH.
EVALuna2:5474

A New Sonographic Weight Estimation Formula for Small-for-Gestational-Age Fetuses - Faschingbauer, Florian; Dammer, Ulf; Raabe, Eva; Kehl, Sven; Schmid, Matthias; Schild, Ralf L.; Beckmann, Matthias; Mayr, Andreas (Journal of Ultrasound in Medicine, 2016)
The purpose of this study was to develop a new specific weight estimation formula for small-for-gestational-age (SGA) fetuses that differentiated between symmetric and asymmetric growth patterns.A statistical estimation technique known as component-wise gradient boosting was applied to a group of 898 SGA fetuses (symmetric, n = 750; asymmetric, n = 148). A new formula was derived from the data obtained and was then compared to other commonly used equations.The new formula derived is as follows: estimated fetal weight = e^[1.3734627 + 0.0057133 × biparietal diameter + 0.0011282 × head circumference + 0.0201147 × abdominal circumference + 0.0183081 × femur length - 0.0000177 × biparietal diameter(2) - 0.0000018 × head circumference(2) - 0.0000297 × abdominal circumference(2) -0.0001007 × femur length(2) + 0.0397563 × I(sex = male) + 0.0064505 × gestational age (days) + 0.0096528 × I(SGA = asymmetric)], where the function I denotes an indicator function, which is 1 if the expression is fulfilled (sex = male; SGA type = asymmetric) and otherwise 0. In the whole study group and the 2 subgroups, the new formula showed the lowest median absolute percentage error, mean percentage error, and random error and the best distribution of absolute percentage errors within prespecified error bounds.The new formula substantially improves weight estimation in SGA fetuses.
EVALuna2:5572

An intergenic risk locus containing an enhancer deletion in 2q35 modulates breast cancer risk by deregulating IGFBP5 expression - Wyszynski, Asaf; Hong, Chi-Chen; Lam, Kristin; Michailidou, Kyriaki; Lytle, Christian; Yao, Song; Zhang, Yali; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Hopper, John L.; Southey, Melissa C.; et al. (Human Molecular Genetics, 2016)
Breast cancer is the most diagnosed malignancy and the second leading cause of cancer mortality in females. Previous association studies have identified variants on 2q35 associated with the risk of breast cancer. To identify functional susceptibility loci for breast cancer, we interrogated the 2q35 gene desert for chromatin architecture and functional variation correlated with gene expression. We report a novel intergenic breast cancer risk locus containing an enhancer copy number variation (enCNV; deletion) located approximately 400Kb upstream to IGFBP5, which overlaps an intergenic ERα-bound enhancer that loops to the IGFBP5 promoter. The enCNV is correlated with modified ERα binding and monoallelic-repression of IGFBP5 following oestrogen treatment. We investigated the association of enCNV genotype with breast cancer in 1,182 cases and 1,362 controls, and replicate our findings in an independent set of 62,533 cases and 60,966 controls from 41 case control studies and 11 GWAS. We report a dose-dependent inverse association of 2q35 enCNV genotype (percopy OR = 0.68 95%CI 0.55-0.83, P = 0.0002; replication OR = 0.77 95% CI 0.73-0.82, P = 2.1 × 10-19) and identify 13 additional linked variants (r2 > 0.8) in the 20Kb linkage block containing the enCNV (P = 3.2 × 10-15- 5.6 × 10-17). These associations were independent of previously reported 2q35 variants, rs13387042/rs4442975 and rs16857609, and were stronger for ER-positive than ER-negative disease. Together, these results suggest that 2q35 breast cancer risk loci may be mediating their effect through IGFBP5.
EVALuna2:33321

Anti-Müllerian hormone (AMH) levels in premenopausal breast cancer patients treated with taxane-based adjuvant chemotherapy - A translational research project of the SUCCESS A study - Trapp, Elisabeth; Steidl, J.; Rack, B.; Kupka, M. S.; Andergassen, U.; Jueckstock, J.; Kurt, A.; Vilsmaier, T.; De Gregorio, A.; De Gregorio, N.; Tzschaschel, M.; Lato, C.; et al. (BREAST, 2017)
BACKGROUND: Premenopausal women undergoing chemotherapy are at high risk for premature ovarian failure and its long-term consequences. Data on potential markers to evaluate ovarian reserve pre- and posttreatment are limited. Anti-Müllerian hormone (AMH) known for ovarian reserve in reproductive medicine could be a surrogate marker and was assessed in premenopausal breast cancer patients of the SUCCESS A study (EUDRA-CT no. 2005-000490-21). METHODS: We identified 170 premenopausal patients, age ≤ 40 years at trial entry, who received FEC-Doc as taxane-anthracylince based chemotherapy. Blood samples were taken at three time points: Before, four weeks after and two years after adjuvant chemotherapy. Serum AMH-levels were evaluated in a central laboratory by a quantitative immunoassay AMH Gen II ELISA (Beckman Coulter, Brea, USA). RESULTS: Median age was 36 years (21-40 years). Median serum AMH-level before chemotherapy was 1.37 ng/ml (range < 0.1-11.3 ng/ml). Four weeks after chemotherapy AMH-levels dropped in 98.6% of the patients to <0.1 ng/ml (range < 0.1-0.21 ng/ml). After two years, 73.3% (n = 101) showed no evidence of ovarian function recovery (AMH <0.1 ng/ml, range < 0.1-3.9 ng/ml). Permanent chemotherapy induced amenorrhea occurred only in 50.6% of the patients. CONCLUSIONS: In this analysis, premenopausal patients showed a high rate of ovarian impairment reflected by low AMH-levels after chemotherapy.
EVALuna2:36126

Antioxidant effect of aqueous extract of four plants with therapeutic potential on gynecological diseases; Semen persicae, Leonurus cardiaca, Hedyotis diffusa, and Curcuma zedoaria - Ji, Shaojian; Fattahi, Amir; Raffel, Nathalie; Hoffmann, Inge; Beckmann, Matthias; Dittrich, Ralf; Schrauder, Michael G. (European Journal of Medical Research, 2017)
BACKGROUND: Little information is available concerning antioxidant effects of plant teas (water boiled) which are used more commonly in traditional Chinese medicine than other extracts. Thus, we addressed this issue by evaluating the ability of teas from four different plants with therapeutic potential on gynecological diseases. METHODS: The aqueous extracts of Semen persicae, Leonurus cardiaca, Hedyotis diffusa, and Curcuma zedoaria rhizome were prepared and then their effects on copper-induced low-density lipoprotein cholesterol (LDL-C) oxidation were evaluated by spectrophotometric method. Density gradient ultracentrifugation method was recruited to isolate LDL-C from healthy individuals. RESULTS: Our results showed that adding 10, 20, and 30 µl S. persicae could increase the lag phase duration of LDL-C oxidation compared with control reaction 12, 21, and 33%, respectively. The most effective delay (87%) was observed when 30 µl H. diffusa was added to the reaction. In cases of L. cardiaca and C. zedoaria, we found no significant influence on the lag phase duration (p > 0.05). Moreover, our findings about starting point of the decomposition phase were almost in parallel with the lag phase results, as 30 µl of S. persicae or H. diffusa teas could significantly increase the initiation time of decomposition (p < 0.05). CONCLUSIONS: In conclusion our results showed that both S. persicae and H. diffusa teas and not L. cardiaca and C. zedoaria could have medicinal therapeutic effects partly through direct oxidation prevention.
EVALuna2:36118

A prediction model for pathological complete response after neoadjuvant chemotherapy of HER2-negative breast cancer patients - Häberle, Lothar; Erber, Ramona; Gaß, Paul; Hein, Alexander; Jud, Sebastian; Langemann, Hanna; Rauh, C.; Hack, Caroline; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Beckmann, Matthias; Lux, Michael P.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

A randomized phase III study evaluating pegylated liposomal doxorubicin versus capecitabine as first-line therapy for metastatic breast cancer: results of the PELICAN study - Harbeck, Nadia; Saupe, Steffen; Jaeger, Elke; Schmidt, Marcus; Kreienberg, Rolf; Mueller, Lothar; Otremba, Burkhard Joerg; Waldenmaier, Dirk; Dorn, Julia; Warm, Mathias; Scholz, Michael; Untch, Michael; et al. (Breast Cancer Research and Treatment, 2017)
PURPOSE: The PELICAN trial evaluates for the first time efficacy and safety of pegylated liposomal doxorubicin (PLD) versus capecitabine as first-line treatment of metastatic breast cancer (MBC). METHODS: This randomized, phase III, open-label, multicenter trial enrolled first-line MBC patients who were ineligible for endocrine or trastuzumab therapy. Cumulative adjuvant anthracyclines of 360 mg/m2 doxorubicin or equivalent were allowed. Left ventricular ejection fraction of >50 % was required. Patients received PLD 50 mg/m2 every 28 days or capecitabine 1250 mg/m2 twice daily for 14 days every 21 days. The primary endpoint was time-to-disease progression (TTP). RESULTS: 210 patients were randomized (n = 105, PLD and n = 105, capecitabine). Adjuvant anthracyclines were given to 37 % (PLD) and 36 % (capecitabine) of patients. No significant difference was observed in TTP [HR = 1.21 (95 % confidence interval, 0.838-1.750)]. Median TTP was 6.0 months for both PLD and capecitabine. Comparing patients with or without prior anthracyclines, no significant difference in TTP was observed in the PLD arm (log-rank P = 0.64). For PLD versus capecitabine, respectively, overall survival (median, 23.3 months vs. 26.8 months) and time-to-treatment failure (median, 4.6 months vs. 3.7 months) were not statistically significantly different. Compared to PLD, patients on capecitabine experienced more serious adverse events (P = 0.015) and more cardiac events among patients who had prior anthracycline exposure (18 vs. 8 %; P = 0.31). CONCLUSION: Both PLD and capecitabine are effective first-line agents for MBC.
EVALuna2:36160

A Review of Integrative Medicine in Gynaecological Oncology - Kalder, M.; Mueller, T.; Fischer, D.; Mueller, A.; Bader, W.; Beckmann, Matthias; Brucker, C.; Hack, Carolin; Hanf, V.; Hasenburg, A.; Hein, Alexander; Jud, Sebastian; et al. (Geburtshilfe und Frauenheilkunde, 2016)
In recent years complementary and alternative medicine (CAM) has increasingly been the focus of international research. Numerous subsidised trials (7903) and systematic reviews (651) have been published, and the evidence is starting to be integrated into treatment guidelines. However, due to insufficient evidence and/or insufficient good quality evidence, this has mostly not translated to practice recommendations in reviews by the Cochrane collaboration gynaecology group. There is nevertheless a not insignificant number of CAM providers and users. The percentage of oncology patients who use CAM varies between 5 and 90 %. Doctors have been identified as the main providers of CAM. Half of gynaecologists offer CAM because of personal conviction or on suggestion from colleagues. This must be viewed in a critical light, since CAM is mostly practiced without appropriate training, often without sufficient evidence for a given method - and where evidence exists, practice guidelines are lacking - and lack of safety or efficacy testing. The combination of patient demand and lucrativeness for doctors/alternative medicine practitioners, both based on supposed effectiveness CAM, often leads to its indiscriminate use with uncertain outcomes and significant cost for patients. On the other hand there is published, positive level I evidence for a number of CAM treatment forms. The aim of this article is therefore to review the available evidence for CAM in gynaecological oncology practice. The continued need for research is highlighted, as is the need to integrate practices supported by good evidence into conventional gynaecological oncology.
EVALuna2:32999

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Cuellar-Partida, Gabriel; Lu, Yi; Dixon, Suzanne C.; Fasching, Peter A.; Hein, Alexander; Burghaus, Stefanie; Beckmann, Matthias; Lambrechts, Diether; Van Nieuwenhuysen, Els; Vergote, Ignace; Vanderstichele, Adriaan; Doherty, Jennifer Anne; et al. (Human genetics, 2016)
Epithelial ovarian cancer (EOC) is one of the deadliest common cancers. The five most common types of disease are high-grade and low-grade serous, endometrioid, mucinous and clear cell carcinoma. Each of these subtypes present distinct molecular pathogeneses and sensitivities to treatments. Recent studies show that certain genetic variants confer susceptibility to all subtypes while other variants are subtype-specific. Here, we perform an extensive analysis of the genetic architecture of EOC subtypes. To this end, we used data of 10,014 invasive EOC patients and 21,233 controls from the Ovarian Cancer Association Consortium genotyped in the iCOGS array (211,155 SNPs). We estimate the array heritability (attributable to variants tagged on arrays) of each subtype and their genetic correlations. We also look for genetic overlaps with factors such as obesity, smoking behaviors, diabetes, age at menarche and height. We estimated the array heritabilities of high-grade serous disease ([Formula: see text] = 8.8 ± 1.1 %), endometrioid ([Formula: see text] = 3.2 ± 1.6 %), clear cell ([Formula: see text] = 6.7 ± 3.3 %) and all EOC ([Formula: see text] = 5.6 ± 0.6 %). Known associated loci contributed approximately 40 % of the total array heritability for each subtype. The contribution of each chromosome to the total heritability was not proportional to chromosome size. Through bivariate and cross-trait LD score regression, we found evidence of shared genetic backgrounds between the three high-grade subtypes: serous, endometrioid and undifferentiated. Finally, we found significant genetic correlations of all EOC with diabetes and obesity using a polygenic prediction approach.
EVALuna2:33325

Assessment of breast volume changes during human pregnancy using a three-dimensional surface assessment technique in the prospective CGATE study - Bayer, Christian M.; Bani, Mayada; Schneider, Michael; Dammer, Ulf; Raabe, Eva; Haeberle, Lothar; Faschingbauer, Florian; Schneeberger, Sabine; Renner, Stefan; Fischer, Dorothea; Schulz-Wendtland, Rüdiger; Fasching, Peter; et al. (European Journal of Cancer Prevention, 2014)
Pregnancies and breastfeeding are two important protective factors concerning breast cancer risk. Breast volume and breast volume changes might be a breast phenotype that could be monitored during pregnancy and breastfeeding without ionizing radiation or expensive equipment. The aim of the present study was to document changes in breast volume during pregnancy prospectively. In the prospective Clinical Gravidity Association Trial and Evaluation programme, pregnant women were followed up prospectively from gestational week 12 to birth. Three-dimensional breast surface imaging and subsequent volume assessments were performed. Factors influencing breast volume at the end of the pregnancy were assessed using linear regression models. Breast volumes averaged 420 ml at the start of pregnancy and 516 ml at the end of pregnancy. The first, second and third quartiles of the volume increase were 41, 95 and 135 ml, respectively. Breast size increased on average by 96 ml, regardless of the initial breast volume. Breast volume increases during pregnancy, but not all womens' breasts respond to pregnancy in the same way. Breast volume changes during pregnancy are an interesting phenotype that can be easily assessed in further studies to examine breast cancer risk.
EVALuna2:14487

Assessment of mammographic density before and after first full-term pregnancy - Löhberg, Christian; Heusinger, Katharina; Jud, Sebastian; Häberle, Lothar; Hein, Alexander; Rauh, Claudia; Bani, Mayada; Lux, Michael P.; Schrauder, Michael G.; Bayer, Christian M.; Helbig, Cosima; Grolik, Ronald; et al. (European Journal of Cancer Prevention, 2010)
Mammographic density (MD) has consistently been found as one of the strongest breast cancer risk factors. In our study, both qualitative and quantitative density measurements were performed in a hospital-based group of premenopausal women before and after first full-term pregnancy providing an opportunity for direct evaluation of the effects of one pregnancy on MD. Mammograms were obtained from 23 women before and after first full-term pregnancy and from 28 nulliparous controls. MD was determined by a standard qualitative assessment method using the Breast Imaging Reporting and Data System, and a quantitative computer-based threshold method (0-100%). The mean age at mammography before and after pregnancy was 31 and 34 years, respectively, with a mean difference of 40 months between mammographies. The quantitative density assessment showed a significant reduction in relative MD after pregnancy of 12 percentage points (8.6-15.4), compared with 3.1 (0.0-6.2) in the nulliparous control group (P<0.001). A reduction in MD of more than 10% was seen in 52% of the patients, compared with 18% of the controls. The qualitative density assessment confirmed a reduction in MD after pregnancy by one Breast Imaging Reporting and Data System category (P=0.02). This longitudinal study showed that MD can be influenced by one full-term pregnancy. This effect was seen with both quantitative and qualitative assessment methods. It may be hypothesized that breast cancer risk reduction associated with pregnancy is mediated through a direct reduction of MD, and MD assessment might be incorporated in individualizing risk assessment and prevention. © 2010 Wolters Kluwer Health | Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer risk; mammographic density; pregnancy

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, Julius; Fasching, Peter; Wunderle, Marius; Heindl, Felix; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, Marcus; Polifka, Iris; Wachter, David; et al. (Therapeutic Advances in Medical Oncology, 2020)
Background: Mammography can identify calcifications up to 50–100 μm in size as a surrogate parameter for breast cancer or ductal carcinoma in situ (DCIS). Microcalcifications measuring <50 µm are also associated with breast cancer or DCIS and are frequently not detected on mammography, although they can be detected with dark-field imaging. This study examined whether additional breast examination using X-ray dark-field imaging can increase the detection rate of calcifications. Advances in knowledge: (1) evaluation of additional modality of breast imaging; (2) specific evaluation of breast calcifications. Implications for patient care: the addition of X-ray dark-field imaging to conventional mammography could detect additional calcifications. Methods: Talbot–Lau X-ray phase–contrast imaging and X-ray dark-field imaging were used to acquire images of breast specimens. The radiation dosage with the technique is comparable with conventional mammography. Three X-ray gratings with periods of 5–10 µm between the X-ray tube and the flat-panel detector provide three different images in a single sequence: the conventional attenuation image, differential phase image, and dark-field image. The images were read by radiologists. Radiological findings were marked and examined pathologically. The results were described in a descriptive manner. Results: A total of 81 breast specimens were investigated with the two methods; 199 significant structures were processed pathologically, consisting of 123 benign and 76 malignant lesions (DCIS or invasive breast cancer). X-ray dark-field imaging identified 15 additional histologically confirmed carcinoma lesions that were visible but not declared suspicious on digital mammography alone. Another four malignant lesions that were not visible on mammography were exclusively detected with X-ray dark-field imaging. Conclusions: Adding X-ray dark-field imaging to digital mammography increases the detection rate for breast cancer and DCIS associated lesions with micrometer-sized calcifications. The use of X-ray dark-field imaging may be able to provide more accurate and detailed radiological classification of suspicious breast lesions. Adding X-ray dark-field imaging to mammography may be able to increase the detection rate and improve preoperative planning in deciding between mastectomy or breast-conserving therapy, particularly in patients with invasive lobular breast cancer.
CRIS-Team Scopus Importer:2020-09-25
Keywords: breast cancer; interferometry; mammography; microcalcifications

Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with prognosis of estrogen receptor-negative breast cancer after chemotherapy - Lei, Jieping; Rudolph, Anja; Moysich, Kirsten B.; Rafiq, Sajjad; Behrens, Sabine; Goode, Ellen L.; Pharoah, Paul Pd; Seibold, Petra; Fasching, Peter; Andrulis, Irene L.; Kristensen, Vessela N.; Couch, Fergus J.; et al. (Breast Cancer Research, 2015)
Tumor lymphocyte infiltration is associated with clinical response to chemotherapy in estrogen receptor (ER) negative breast cancer. To identify variants in immunosuppressive pathway genes associated with prognosis after adjuvant chemotherapy for ER-negative patients, we studied stage I-III invasive breast cancer patients of European ancestry, including 9,334 ER-positive (3,151 treated with chemotherapy) and 2,334 ER-negative patients (1,499 treated with chemotherapy).We pooled data from sixteen studies from the Breast Cancer Association Consortium (BCAC), and employed two independent studies for replications. Overall 3,610 single nucleotide polymorphisms (SNPs) in 133 genes were genotyped as part of the Collaborative Oncological Gene-environment Study, in which phenotype and clinical data were collected and harmonized. Multivariable Cox proportional hazard regression was used to assess genetic associations with overall survival (OS) and breast cancer-specific survival (BCSS). Heterogeneity according to chemotherapy or ER status was evaluated with the log-likelihood ratio test.Three independent SNPs in TGFBR2 and IL12B were associated with OS (P <10?³) solely in ER-negative patients after chemotherapy (267 events). Poorer OS associated with TGFBR2 rs1367610 (G > C) (per allele hazard ratio (HR) 1.54 (95% confidence interval (CI) 1.22 to 1.95), P = 3.08 × 10??) was not found in ER-negative patients without chemotherapy or ER-positive patients with chemotherapy (P for interaction <10-3). Two SNPs in IL12B (r² = 0.20) showed different associations with ER-negative disease after chemotherapy: rs2546892 (G > A) with poorer OS (HR 1.50 (95% CI 1.21 to 1.86), P = 1.81 × 10??), and rs2853694 (A > C) with improved OS (HR 0.73 (95% CI 0.61 to 0.87), P = 3.67 × 10??). Similar associations were observed with BCSS. Association with TGFBR2 rs1367610 but not IL12B variants replicated using BCAC Asian samples and the independent Prospective Study of Outcomes in Sporadic versus Hereditary Breast Cancer Study and yielded a combined HR of 1.57 ((95% CI 1.28 to 1.94), P = 2.05 × 10??) without study heterogeneity.TGFBR2 variants may have prognostic and predictive value in ER-negative breast cancer patients treated with adjuvant chemotherapy. Our findings provide further insights into the development of immunotherapeutic targets for ER-negative breast cancer.
EVALuna2:9270

Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with risk of clear cell ovarian cancer - Hampras, Shalaka S.; Sucheston-Campbell, Lara E.; Cannioto, Rikki; Chang-Claude, Jenny; Modugno, Francesmary; Doerk, Thilo; Hillemanns, Peter; Preus, Leah; Knutson, Keith L.; Wallace, Paul K.; Hong, Chi-Chen; Friel, Grace; et al. (Oncotarget, 2016)
Regulatory T (Treg) cells, a subset of CD4+ T lymphocytes, are mediators of immunosuppression in cancer, and, thus, variants in genes encoding Treg cell immune molecules could be associated with ovarian cancer.In a population of 15,596 epithelial ovarian cancer (EOC) cases and 23,236 controls, we measured genetic associations of 1,351 SNPs in Treg cell pathway genes with odds of ovarian cancer and tested pathway and gene-level associations, overall and by histotype, for the 25 genes, using the admixture likelihood (AML) method. The most significant single SNP associations were tested for correlation with expression levels in 44 ovarian cancer patients.The most significant global associations for all genes in the pathway were seen in endometrioid (p = 0.082) and clear cell (p = 0.083), with the most significant gene level association seen with TGFBR2 (p = 0.001) and clear cell EOC. Gene associations with histotypes at p < 0.05 included: IL12 (p = 0.005 and p = 0.008, serous and high-grade serous, respectively), IL8RA (p = 0.035, endometrioid and mucinous), LGALS1 (p = 0.03, mucinous), STAT5B (p = 0.022, clear cell), TGFBR1 (p = 0.021 endometrioid) and TGFBR2 (p = 0.017 and p = 0.025, endometrioid and mucinous, respectively).Common inherited gene variation in Treg cell pathways shows some evidence of germline genetic contribution to odds of EOC that varies by histologic subtype and may be associated with mRNA expression of immune-complex receptor in EOC patients.
EVALuna2:9345

Association analysis identifies 65 new breast cancer risk loci - Michailidou, Kyriaki; Lindstrom, Sara; Dennis, Joe; Beesley, Jonathan; Hui, Shirley; Kar, Siddhartha; Lemacon, Audrey; Soucy, Penny; Glubb, Dylan; Rostamianfar, Asha; Bolla, Manjeet K.; Wang, Qin; et al. (Nature, 2017)
Breast cancer risk is influenced by rare coding variants in susceptibility genes, such as BRCA1, and many common, mostly non-coding variants. However, much of the genetic contribution to breast cancer risk remains unknown. Here we report the results of a genome-wide association study of breast cancer in 122,977 cases and 105,974 controls of European ancestry and 14,068 cases and 13,104 controls of East Asian ancestry. We identified 65 new loci that are associated with overall breast cancer risk at P < 5 × 10-8. The majority of credible risk single-nucleotide polymorphisms in these loci fall in distal regulatory elements, and by integrating in silico data to predict target genes in breast cells at each locus, we demonstrate a strong overlap between candidate target genes and somatic driver genes in breast tumours. We also find that heritability of breast cancer due to all single-nucleotide polymorphisms in regulatory features was 2-5-fold enriched relative to the genome-wide average, with strong enrichment for particular transcription factor binding sites. These results provide further insight into genetic susceptibility to breast cancer and will improve the use of genetic risk scores for individualized screening and prevention.
EVALuna2:9385

Association between breast cancer risk factors and molecular type in postmenopausal patients with hormone receptor-positive early breast cancer - Wunderle, Marius; Pretscher, Jutta; Brucker, Sara Y.; Volz, Bernhard; Hartmann, Arndt; Fießler, Cornelia; Hein, Alexander; Häberle, Lothar; Jud, Sebastian; Lux, Michael P.; Janni, Wolfgang; Löhberg, Christian; et al. (Breast Cancer Research and Treatment, 2019)
PurposeEvidence shows that genetic and non-genetic risk factors for breast cancer (BC) differ relative to the molecular subtype. This analysis aimed to investigate associations between epidemiological risk factors and immunohistochemical subtypes in a cohort of postmenopausal, hormone receptor-positive BC patients.MethodsThe prospective, single-arm, multicenter phase IV PreFace study (Evaluation of Predictive Factors Regarding the Effectivity of Aromatase Inhibitor Therapy) included 3529 postmenopausal patients with hormone receptor-positive early BC. Data on their epidemiological risk factors were obtained from patients' diaries and their medical histories. Data on estrogen receptor, progesterone receptor, and HER2 receptor status were obtained from pathology reports. Patients with incomplete information were excluded. Data were analyzed using conditional inference regression analysis, analysis of variance, and the chi-squared test.ResultsIn a cohort of 3392 patients, the strongest association with the molecular subtypes of BC was found for hormone replacement therapy (HRT) before diagnosis of early BC. The analysis showed that patients who took HRT at diagnosis had luminal A-like BC more often (83.7%) than those who had never taken HRT or had stopped taking it (75.5%). Luminal B-like BC and HER2-positive BC were diagnosed more often in women who had never taken HRT or had stopped taking it (13.3% and 11.2%, respectively) than in women who were taking HRT at diagnosis of BC (8.3% and 8.0%, respectively).ConclusionsThis analysis shows an association between HRT and the distribution of molecular subtypes of BC. However, no associations between other factors (e.g., age at diagnosis, body mass index, smoking status, age at menopause, number of deliveries, age at first delivery, breastfeeding history, or family history) were noted.
CRIS-Team WoS Importer:2019-03-29

Association between mammographic density and pregnancies relative to age and BMI: a breast cancer case-only analysis - Hack, Carolin; Emons, Julius; Jud, Sebastian; Heusinger, Katharina; Adler, Werner; Gaß, Paul; Haeberle, Lothar; Heindl, Felix; Hein, Alexander; Schulz-Wendtland, Rüdiger; Uder, Michael; Hartmann, Arndt; et al. (Breast Cancer Research and Treatment, 2017)
Percentage mammographic density (PMD) is a major risk factor for breast cancer (BC). It is strongly associated with body mass index (BMI) and age, which are themselves risk factors for breast cancer. This analysis investigated the association between the number of full-term pregnancies and PMD in different subgroups relative to age and BMI.Patients were identified in the breast cancer database of the University Breast Center for Franconia. A total of 2410 patients were identified, for whom information on parity, age, and BMI, and a mammogram from the time of first diagnosis were available for assessing PMD. Linear regression analyses were conducted to investigate the influence on PMD of the number of full-term pregnancies (FTPs), age, BMI, and interaction terms between them.As in previous studies, age, number of FTPs, and BMI were found to be associated with PMD in the expected direction. However, including the respective interaction terms improved the prediction of PMD even further. Specifically, the association between PMD and the number of FTPs differed in young patients under the age of 45 (mean decrease of 0.37 PMD units per pregnancy) from the association in older age groups (mean decrease between 2.29 and 2.39 PMD units). BMI did not alter the association between PMD and the number of FTPs.The effect of pregnancies on mammographic density does not appear to become apparent before the age of menopause. The mechanism that drives the effect of pregnancies on mammographic density appears to be counter-regulated by other influences on mammographic density in younger patients.
EVALuna2:14710

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhao, Zhiguo; Wen, Wanqing; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Zhang, Ben; Long, Jirong; Shu, Xiao-Ou; Schmidt, Marjanka K.; Milne, Roger L.; Garcia-Closas, Montserrat; Chang-Claude, Jenny; et al. (Cancer Causes & Control, 2016)
PURPOSE: Type 2 diabetes (T2D) has been reported to be associated with an elevated risk of breast cancer. It is unclear, however, whether this association is due to shared genetic factors. METHODS: We constructed a genetic risk score (GRS) using risk variants from 33 known independent T2D susceptibility loci and evaluated its relation to breast cancer risk using the data from two consortia, including 62,328 breast cancer patients and 83,817 controls of European ancestry. Unconditional logistic regression models were used to derive adjusted odds ratios (ORs) and 95 % confidence intervals (CIs) to measure the association of breast cancer risk with T2D GRS or T2D-associated genetic risk variants. Meta-analyses were conducted to obtain summary ORs across all studies. RESULTS: The T2D GRS was not found to be associated with breast cancer risk, overall, by menopausal status, or for estrogen receptor positive or negative breast cancer. Three T2D associated risk variants were individually associated with breast cancer risk after adjustment for multiple comparisons using the Bonferroni method (at p < 0.001), rs9939609 (FTO) (OR 0.94, 95 % CI = 0.92-0.95, p = 4.13E-13), rs7903146 (TCF7L2) (OR 1.04, 95 % CI = 1.02-1.06, p = 1.26E-05), and rs8042680 (PRC1) (OR 0.97, 95 % CI = 0.95-0.99, p = 8.05E-04). CONCLUSIONS: We have shown that several genetic risk variants were associated with the risk of both T2D and breast cancer. However, overall genetic susceptibility to T2D may not be related to breast cancer risk.
EVALuna2:32983

Association of genomic variants at PAX8 and PBX2 with cervical cancer risk - Ramachandran, Dhanya; Wang, Yingying; Schuermann, Peter; Huelse, Fabienne; Mao, Qianqian; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; Hirchenhain, Christine; Schmidmayr, Monika; Mueller, Florian; Runnebaum, Ingo; et al. (International Journal of Cancer, 2021)
Cervical malignancy is triggered by human papillomavirus infection but the risk for cervical cancer has a hereditary component. From a recent Genome Wide Association Study meta-analysis, 2q14.1 (PAX8) and 6p21.32 (PBX2) have been proposed as novel cervical cancer susceptibility loci. We investigated the two main signals at these loci in an independent case-control series of 2578 cases with cervical dysplasia or carcinoma and 1483 healthy females. We find significant associations for both variants, rs10175462 at PAX8 and rs2856437 at PBX2, with overall cervical disease (rs10175462: odds ratio [OR] 0.82, 95% confidence interval [CI] 0.74-0.91, P = 2.4 × 10−4; rs2856437: OR 1.52, 95% CI 1.14-2.02, P =.004). Both variants showed evidence of association with invasive squamous cervical cancer (rs10175462: OR 0.80, 95% CI 0.68-0.94, P =.006; rs2856437: OR 1.56, 95% CI 1.03-2.36, P =.036) and with high-grade dysplasia (rs10175462: OR 0.79, 95%CI 0.70-0.90, P = 1.9 × 10−4; rs2856437: OR 1.58, 95% CI 1.15-2.17, P =.005). A combined analysis of high-grade dysplasia and invasive cervical cancer also showed significant associations for both variants (rs10175462: OR 0.81, 95% CI 0.73-0.91, P = 2.4 × 10−4; rs2856437: OR 1.57, 95% CI 1.18-2.10, P =.002). No association was detected for rs2856437 with low-grade dysplasia, while rs10175462 showed weak evidence of association (P =.05). RNA analyses in cervical samples revealed that PAX8 transcripts were upregulated in HPV-positive lesions (P =.008) but this was not observed in the presence of the protective minor allele of rs10175462. The rs10175462 genotype also correlated with reduced levels of the lncRNA PAX8-AS1 (P <.001). Taken together, our results extend the evidence for a link between genomic risk variants at the HLA region (PBX2) with cervical disease and support PAX8 as the first consistent non-HLA cervical cancer susceptibility locus.
CRIS-Team Scopus Importer:2021-05-21
Keywords: association study; cervical malignancy; eQTL; HPV infection; single nucleotide polymorphism

Association of genomic variants at the human leukocyte antigen locus with cervical cancer risk,HPVstatus and gene expression levels - Ramachandran, Dhanya; Schuermann, Peter; Mao, Qianqian; Wang, Yingying; Bretschneider, Lisa-Marie; Speith, Lisa-Marie; Huelse, Fabienne; Enssen, Julia; Bousset, Kristine; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; et al. (International Journal of Cancer, 2020)
The human leukocyte antigen (HLA) locus on chromosome 6 has been reported to be associated with cervical cancer. We investigated two independent single-nucleotide polymorphisms in a large case-control series of cervical dysplasia and carcinoma that has been newly established by the German Cervigen Consortium, comprising a total of 2481 cases and 1556 healthy females. We find significant associations for both variants, rs9272117 atHLA-DQA1and rs2844511 atMICAandHCP5, with cervical disease. Both variants showed evidence of association with invasive cervical cancer (rs9272117: OR 0.89, 95% CI 0.79-0.99,P= .036; rs2844511: OR 1.17, 95% CI 1.04-1.31,P= .008) and with high-grade dysplasia (rs9272117: OR 0.78, 95% CI 0.70-0.87,P= 7.1 x 10(-6); rs2844511: OR 1.13, 95% CI 1.01-1.26,P= .035), as well as in a combined analysis of both groups (rs9272117: OR 0.83, 95% CI 0.75-0.91,P= 6.9 x 10(-5); rs2844511: OR 1.14, 95% CI 1.04-1.26,P= .005). Variant rs2844511, but not rs9272117, also showed modest evidence of association with low-grade dysplasia (OR 1.26, 95% CI 1.04-1.54,P= .019). In case-only analyses, rs2844511 tended to predict HPV status (P= .044) and rs9272117 tended to associate with HPV16 (P= .022). RNA studies in cervical samples showed a significant correlation in the transcript levels ofMICA,HCP5andHLA-DQA1, suggesting extensive co-regulation. All three genes were upregulated in HPV16-positive samples. In stratified analyses, rs9272117 was associated withHLA-DQA1levels, specifically in HPV-positive samples, while rs2844511 was associated withMICAandHCP5levels. The risk allele of rs2844511 was required for correlations betweenMICAorHCP5withHLA-DQA1. Altogether, our results support 6p21.32-33 as the first consistent cervical cancer susceptibility locus and provide evidence for a link between genetic risk variants, HPV16 status and transcript levels ofHLA-DQA1,HCP5andMICA, which may contribute to tumor immune evasion.
CRIS-Team WoS Importer:2020-07-24

Association of germline genetic variants with breast cancer-specific survival in patient subgroups defined by clinic-pathological variables related to tumor biology and type of systemic treatment - Morra, Anna; Escala-Garcia, Maria; Beesley, Jonathan; Keeman, Renske; Canisius, Sander; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Auer, Paul L.; Augustinsson, Annelie; Freeman, Laura E. Beane; et al. (BREAST CANCER RES, 2021)
Background Given the high heterogeneity among breast tumors, associations between common germline genetic variants and survival that may exist within specific subgroups could go undetected in an unstratified set of breast cancer patients. Methods We performed genome-wide association analyses within 15 subgroups of breast cancer patients based on prognostic factors, including hormone receptors, tumor grade, age, and type of systemic treatment. Analyses were based on 91,686 female patients of European ancestry from the Breast Cancer Association Consortium, including 7531 breast cancer-specific deaths over a median follow-up of 8.1 years. Cox regression was used to assess associations of common germline variants with 15-year and 5-year breast cancer-specific survival. We assessed the probability of these associations being true positives via the Bayesian false discovery probability (BFDP < 0.15). Results Evidence of associations with breast cancer-specific survival was observed in three patient subgroups, with variant rs5934618 in patients with grade 3 tumors (15-year-hazard ratio (HR) [95% confidence interval (CI)] 1.32 [1.20, 1.45], P = 1.4E-08, BFDP = 0.01, per G allele); variant rs4679741 in patients with ER-positive tumors treated with endocrine therapy (15-year-HR [95% CI] 1.18 [1.11, 1.26], P = 1.6E-07, BFDP = 0.09, per G allele); variants rs1106333 (15-year-HR [95% CI] 1.68 [1.39,2.03], P = 5.6E-08, BFDP = 0.12, per A allele) and rs78754389 (5-year-HR [95% CI] 1.79 [1.46,2.20], P = 1.7E-08, BFDP = 0.07, per A allele), in patients with ER-negative tumors treated with chemotherapy. Conclusions We found evidence of four loci associated with breast cancer-specific survival within three patient subgroups. There was limited evidence for the existence of associations in other patient subgroups. However, the power for many subgroups is limited due to the low number of events. Even so, our results suggest that the impact of common germline genetic variants on breast cancer-specific survival might be limited.
CRIS-Team WoS Importer:2021-09-03

Association of molecular subtypes with breast cancer risk factors: a case-only analysis - Rauh, Claudia; Gaß, Paul; Heusinger, Katharina; Haeberle, Lothar; Jud, Sebastian; Hein, Alexander; Löhberg, Christian; Lux, Michael P.; Wachter, David; Heimrich, Jutta; Strehl, Johanna D.; Haller, Florian; et al. (European Journal of Cancer Prevention, 2015)
As breast cancer (BC) screening identifies many BCs with a good prognosis, which might be overdiagnosed and therefore overtreated, the identification of subgroups with a high risk for aggressive subtypes might be helpful. The aim of this case-case analysis was to investigate the association between epidemiological risk factors and molecular subtypes in a cohort of BC patients. Epidemiological risk factors for 2587 BC patients were obtained using a structured questionnaire and from the patients' charts. The histopathological information (estrogen and progesterone receptor, HER2 and Ki-67) used in the analysis was retrieved from the original pathology reports. Analyses using conditional inference regression trees were carried out on these data. The strongest influence factor on the distribution of the molecular subtypes was age at first diagnosis of BC. An influence of BMI was also identified in patients aged either more than 42 years or 49.6 years or less. Older patients aged more than 49.6 years and perimenopausal women with a BMI of 32.4 kg/m or less were most likely to develop luminal A-like BC. Young patients aged 42 years or less and perimenopausal patients with a BMI more than 32.4 kg/m more often developed triple-negative BC. The study confirmed that age at diagnosis is an important factor influencing the distribution of molecular subtypes. In the perimenopausal group, it may be postulated that BMI plays a critical role in the pathogenesis of BC, defining a subgroup that is more likely to develop triple-negative BC or luminal B-like disease and another group in which there is a more postmenopausal distribution pattern.
EVALuna2:5482

Association of prenatal alcohol exposure and prenatal maternal depression with offspring low-grade inflammation in early adolescence - Maschke, Janina; Roetner, Jakob; Bösl, Sophia; Plank, Anne-Christine; Rohleder, Nicolas; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; et al. (International Journal of Environmental Research and Public Health, 2021)
(1) This longitudinal study aimed to investigate the link between prenatal alcohol exposure and prenatal maternal depression with the offspring’s low-grade inflammatory status. (2) Prenatal alcohol exposure was determined via maternal self-report during the 3rd trimester of pregnancy (self-report+: n = 29) and the meconium alcohol metabolite Ethyl Glucuronide (EtG), collected at birth (≥30 ng/g: n = 23). The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for prenatal maternal depressive symptoms during the 3rd trimester (≥10: n = 35). Fifteen years later, 122 adolescents (M = 13.32 years; 48.4% female) provided blood samples for the analysis of high sensitivity C-reactive protein (hsCRP; M = 0.91; SD = 1.28). (3) Higher hsCRP levels were found in EtG positive adolescents (p = 0.036, ηp2 = 0.04) and an inverse non-significant dose–response relation with hsCRP (r = −0.35, p = 0.113). For maternal self-reported prenatal alcohol consumption (p = 0.780, ηp2 = 0.00) and prenatal depressive symptoms (p = 0.360, ηp2 = 0.01) no differences for hsCRP levels between the affected and unaffected groups were found. (4) Adolescents with prenatal alcohol exposure are at risk for low-grade systemic inflammation. The EtG biomarker may be more accurate compared to self-reports. The findings suggest that prenatal maternal depression does not evoke low-grade systemic inflammation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Early adolescence; High-sensitivity C-reactive protein (hsCRP); Low-grade systemic inflammation; Maternal self-report; Meconium ethyl glucuronide (EtG); Pregnancy; Prenatal alcohol exposure (PAE); Prenatal depression

Association of the CHEK2 c.1100delC variant, radiotherapy, and systemic treatment with contralateral breast cancer risk and breast cancer-specific survival. - Morra, Anna; Schreurs, Maartje A.C.; Andrulis, Irene L.; Anton-Culver, Hoda; Augustinsson, Annelie; Beckmann, Matthias; Behrens, Sabine; Bojesen, Stig E.; Bolla, Manjeet K.; Brauch, Hiltrud; Broeks, Annegien; Buys, Saundra S.; et al. (Cancer Medicine, 2023)
BACKGROUND: Breast cancer (BC) patients with a germline CHEK2 c.1100delC variant have an increased risk of contralateral BC (CBC) and worse BC-specific survival (BCSS) compared to non-carriers. AIM: To assessed the associations of CHEK2 c.1100delC, radiotherapy, and systemic treatment with CBC risk and BCSS. METHODS: Analyses were based on 82,701 women diagnosed with a first primary invasive BC including 963 CHEK2 c.1100delC carriers; median follow-up was 9.1 years. Differential associations with treatment by CHEK2 c.1100delC status were tested by including interaction terms in a multivariable Cox regression model. A multi-state model was used for further insight into the relation between CHEK2 c.1100delC status, treatment, CBC risk and death. RESULTS: There was no evidence for differential associations of therapy with CBC risk by CHEK2 c.1100delC status. The strongest association with reduced CBC risk was observed for the combination of chemotherapy and endocrine therapy [HR (95% CI): 0.66 (0.55-0.78)]. No association was observed with radiotherapy. Results from the multi-state model showed shorter BCSS for CHEK2 c.1100delC carriers versus non-carriers also after accounting for CBC occurrence [HR (95% CI): 1.30 (1.09-1.56)]. CONCLUSION: Systemic therapy was associated with reduced CBC risk irrespective of CHEK2 c.1100delC status. Moreover, CHEK2 c.1100delC carriers had shorter BCSS, which appears not to be fully explained by their CBC risk.
EVALuna2:539549

Association of vitamin D levels and risk of ovarian cancer: a Mendelian randomization study - Ong, Jue-Sheng; Cuellar-Partida, Gabriel; Lu, Yi; Fasching, Peter A.; Hein, Alexander; Burghaus, Stefanie; Beckmann, Matthias; Lambrechts, Diether; Van Nieuwenhuysen, Els; Vergote, Ignace; Vanderstichele, Adriaan; Doherty, Jennifer Anne; et al. (International Journal of Epidemiology, 2016)
BACKGROUND: In vitro and observational epidemiological studies suggest that vitamin D may play a role in cancer prevention. However, the relationship between vitamin D and ovarian cancer is uncertain, with observational studies generating conflicting findings. A potential limitation of observational studies is inadequate control of confounding. To overcome this problem, we used Mendelian randomization (MR) to evaluate the association between single nucleotide polymorphisms (SNPs) associated with circulating 25-hydroxyvitamin D [25(OH)D] concentration and risk of ovarian cancer. METHODS: We employed SNPs with well-established associations with 25(OH)D concentration as instrumental variables for MR: rs7944926 (DHCR7), rs12794714 (CYP2R1) and rs2282679 (GC). We included 31 719 women of European ancestry (10 065 cases, 21 654 controls) from the Ovarian Cancer Association Consortium, who were genotyped using customized Illumina Infinium iSelect (iCOGS) arrays. A two-sample (summary data) MR approach was used and analyses were performed separately for all ovarian cancer (10 065 cases) and for high-grade serous ovarian cancer (4121 cases). RESULTS: The odds ratio for epithelial ovarian cancer risk (10 065 cases) estimated by combining the individual SNP associations using inverse variance weighting was 1.27 (95% confidence interval: 1.06 to 1.51) per 20 nmol/L decrease in 25(OH)D concentration. The estimated odds ratio for high-grade serous epithelial ovarian cancer (4121 cases) was 1.54 (1.19, 2.01). CONCLUSIONS: Genetically lowered 25-hydroxyvitamin D concentrations were associated with higher ovarian cancer susceptibility in Europeans. These findings suggest that increasing plasma vitamin D levels may reduce risk of ovarian cancer.
EVALuna2:33317

Associations of obesity and circulating insulin and glucose with breast cancer risk: a Mendelian randomization analysis - Shu, Xiang; Wu, Lang; Khankari, Nikhil K.; Shu, Xiao-Ou; Wang, Thomas J.; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Milne, Roger L.; Schmidt, Marjanka K.; Pharoah, Paul D. P.; et al. (International Journal of Epidemiology, 2019)
Background: In addition to the established association between general obesity and breast cancer risk, central obesity and circulating fasting insulin and glucose have been linked to the development of this common malignancy. Findings from previous studies, however, have been inconsistent, and the nature of the associations is unclear.
CRIS-Team WoS Importer:2019-10-08

Associations of prenatal depressive symptoms with DNA methylation of HPA axis-related genes and diurnal cortisol profiles in primary school-aged children - Stonawski, Valeska; Frey, Stefan; Golub, Yulia; Rohleder, Nicolas; Kriebel, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Heinrich, Hartmut; et al. (Development and Psychopathology, 2018)

Associations of prenatal depressive symptoms with DNA methylation of HPA axis-related genes and diurnal cortisol profiles in primary school-aged children - Stonawski, Valeska; Frey, Stefan; Golub, Yulia; Rohleder, Nicolas; Kriebel, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Heinrich, Hartmut; Moll, Gunther; et al. (Development and Psychopathology, 2019)
Epigenetic DNA modifications in genes related to the hypothalamic-pituitary-adrenal (HPA) axis are discussed as a mechanism underlying the association between prenatal depression and altered child HPA activity. In a longitudinal study, DNA methylation changes related to prenatal depressive symptoms were investigated in 167 children aged 6 to 9 years. At six candidate genes, 126 cytosine-guanine dinucleotides were considered without correcting for multiple testing due to the exploratory nature of the study. Further associations with the basal child HPA activity were examined. Children exposed to prenatal depressive symptoms exhibited lower bedtime cortisol (p = .003, ηp2 = 0.07) and a steeper diurnal slope (p = .023, ηp2 = 0.06). For total cortisol release, prenatal exposure was related to lower cortisol release in boys, and higher release in girls. Furthermore, prenatal depressive symptoms were associated with altered methylation in the glucocorticoid receptor gene (NR3C1), the mineralocorticoid receptor gene (NR3C2), and the serotonin receptor gene (SLC6A4), with some sex-specific effects (p = .012-.040, ηp2 = 0.03-0.04). In boys, prenatal depressive symptoms predicted bedtime cortisol mediated by NR3C2 methylation, indirect effect = -0.07, 95% confidence interval [-0.16, -0.02]. Results indicate relations of prenatal depressive symptoms to both child basal HPA activity and DNA methylation, partially fitting a mediation model, with exposed boys and girls being affected differently.
EVALuna2:36373

A Standard Mammography Unit - Standard 3D Ultrasound Probe Fusion Prototype: First Results - Schulz-Wendtland, Rüdiger; Jud, Sebastian; Fasching, Peter; Hartmann, Arndt; Radicke, Marcus; Rauh, Claudia; Uder, Michael; Wunderle, Marius; Gaß, Paul; Langemann, Hanna; Beckmann, Matthias; Emons, Julius (Geburtshilfe und Frauenheilkunde, 2017)
The combination of different imaging modalities through the use of fusion devices promises significant diagnostic improvement for breast pathology. The aim of this study was to evaluate image quality and clinical feasibility of a prototype fusion device (fusion prototype) constructed from a standard tomosynthesis mammography unit and a standard 3D ultrasound probe using a new method of breast compression.Imaging was performed on 5 mastectomy specimens from patients with confirmed DCIS or invasive carcinoma (BI-RADS ((TM)) 6). For the preclinical fusion prototype an ABVS system ultrasound probe from an Acuson S2000 was integrated into a MAMMOMAT Inspiration (both Siemens Healthcare Ltd) and, with the aid of a newly developed compression plate, digital mammogram and automated 3D ultrasound images were obtained.The quality of digital mammogram images produced by the fusion prototype was comparable to those produced using conventional compression. The newly developed compression plate did not influence the applied x-ray dose. The method was not more labour intensive or time-consuming than conventional mammography. From the technical perspective, fusion of the two modalities was achievable.In this study, using only a few mastectomy specimens, the fusion of an automated 3D ultrasound machine with a standard mammography unit delivered images of comparable quality to conventional mammography. The device allows simultaneous ultrasound - the second important imaging modality in complementary breast diagnostics - without increasing examination time or requiring additional staff.
EVALuna2:6849

A transcriptome-wide association study of 229,000 women identifies new candidate susceptibility genes for breast cancer - Wu, Lang; Shi, Wei; Long, Jirong; Guo, Xingyi; Michailidou, Kyriaki; Beesley, Jonathan; Bolla, Manjeet K.; Shu, Xiao-Ou; Lu, Yingchang; Cai, Qiuyin; Al-Ejeh, Fares; Rozali, Esdy; et al. (Nature Genetics, 2018)
The breast cancer risk variants identified in genome-wide association studies explain only a small fraction of the familial relative risk, and the genes responsible for these associations remain largely unknown. To identify novel risk loci and likely causal genes, we performed a transcriptome-wide association study evaluating associations of genetically predicted gene expression with breast cancer risk in 122,977 cases and 105,974 controls of European ancestry. We used data from the Genotype-Tissue Expression Project to establish genetic models to predict gene expression in breast tissue and evaluated model performance using data from The Cancer Genome Atlas. Of the 8,597 genes evaluated, significant associations were identified for 48 at a Bonferroni-corrected threshold of P < 5.82 × 10, including 14 genes at loci not yet reported for breast cancer. We silenced 13 genes and showed an effect for 11 on cell proliferation and/or colony-forming efficiency. Our study provides new insights into breast cancer genetics and biology.
EVALuna2:51301

Attention, cognitive control and motivation in ADHD: Linking event-related brain potentials and DNA methylation patterns in boys at early school age - Heinrich, Hartmut; Grunitz, Juliane; Stonawski, Valeska; Frey, Silke; Wahl, Simone; Albrecht, Bjoern; Goecke, Tamme W.; Beckmann, Matthias; Kornhuber, Johannes; Fasching, Peter; Moll, Gunther; Eichler, Anna (Scientific Reports, 2017)
In order to better understand the underpinnings of attention-deficit/hyperactivity disorder (ADHD), we targeted the relationship of attentional, cognitive control and motivational processes with DNA methylation patterns of 60 candidate genes in boys at early school age. Participants (6 to 8 years; N = 82) were selected from a German longitudinal cohort (FRANCES). ADHD-related behaviour was assessed via maternal ratings. Performance and event-related potential measures (inter alia Cue-P3 and Nogo-P3), which were recorded in a motivational go/nogo task, indicated diminished attentional orienting, reduced inhibitory response control and a larger motivational effect on performance in ADHD already at this relatively young age. Methylation patterns were analysed in buccal cell DNA with the Illumina HumanMethylation 450K array. For CpG sites at genes of the dopaminergic (COMT, ANKK1) and the neurotrophic (BDNF, NGFR) system, associations with the Nogo-P3 as well as ADHD symptom severity were found suggesting that these systems are involved in response control deficits in ADHD. Methylation effects related to both functional aspects and ADHD behaviour were also observed for DPP10 and TPH2. Epigenetic mechanisms may play a role in ADHD-associated deficits but findings need to be replicated in larger samples and are limited by the fact that only peripheral methylation could be considered.
EVALuna2:33560

Automated artifact detection in abbreviated dynamic contrast-enhanced (DCE) MRI-derived maximum intensity projections (MIPs) of the breast - Kapsner, Lorenz; Ohlmeyer, Sabine; Folle, Lukas; Laun, Frederik Bernd; Nagel, Armin Michael; Liebert, Andrzej; Schreiter, Hannes; Beckmann, Matthias; Uder, Michael; Wenkel, Evelyn; Bickelhaupt, Sebastian (European Radiology, 2022)
Objectives To automatically detect MRI artifacts on dynamic contrast-enhanced (DCE) maximum intensity projections (MIPs) of the breast using deep learning. Methods Women who underwent clinically indicated breast MRI between October 2015 and December 2019 were included in this IRB-approved retrospective study. We employed two convolutional neural network architectures (ResNet and DenseNet) to detect the presence of artifacts on DCE MIPs of the left and right breasts. Networks were trained on images acquired up to and including the year 2018 using a 5-fold cross-validation (CV). Ensemble classifiers were built with the resulting CV models and applied to an independent holdout test dataset, which was formed by images acquired in 2019. Results Our study sample contained 2265 examinations from 1794 patients (median age at first acquisition: 50 years [IQR: 17 years]), corresponding to 1827 examinations of 1378 individuals in the training dataset and 438 examinations of 416 individuals in the holdout test dataset with a prevalence of image-level artifacts of 53% (1951/3654 images) and 43% (381/876 images), respectively. On the holdout test dataset, the ResNet and DenseNet ensembles demonstrated an area under the ROC curve of 0.92 and 0.94, respectively. Conclusion Neural networks are able to reliably detect artifacts that may impede the diagnostic assessment of MIPs derived from DCE subtraction series in breast MRI. Future studies need to further explore the potential of such neural networks to complement quality assurance and improve the application of DCE MIPs in a clinical setting, such as abbreviated protocol
Keywords: Artifacts; Magnetic resonance imaging; Breast; Contrast agent; Neural network

Awareness of breast cancer incidence and risk factors among healthy women in Germany: an update after 10 years - Poehls, Uwe G.; Hack, Carolin; Wunderle, Marius; Renner, Stefan P.; Lux, Michael P.; Beckmann, Matthias; Fasching, Peter; Nabieva, Naiba (European Journal of Cancer Prevention, 2019)
Early breast cancer detection programs depend for effectiveness on the participation rate, which is affected by risk factor awareness. This study investigated changes in women's risk factor awareness between 2004 and 2016. Results from a 2004 survey of 2107 healthy women were compared with new data obtained using the same questionnaire in 2016, with 866 participants indicating their knowledge and perceptions regarding breast cancer incidence, risk factors, risk perceptions, and levels of concern. Logistic regression models assessed the influence of time point (2004 vs. 2016) on correct recognition of risk factors such as age at first childbirth, childlessness, lack of breastfeeding, hormone replacement therapy (HRT), and family history. Regression models were adjusted for common sociodemographic characteristics. Reproductive risk factors were regarded as influencing breast cancer risk less often. In 2004, age at first birth, childlessness, and lack of breastfeeding were regarded as risk factors by 24, 32, and 37%, respectively, in comparison with only 15, 18, and 23% in 2016. All changes were statistically significant. Awareness of HRT as a risk factor increased significantly (36-57%), and family history was recognized as a risk by 75 and 73% in 2004 and 2016, respectively. Most women recognized family history as a breast cancer risk factor. This did not change, reflecting the topic's media prominence. Awareness of HRT as a risk factor increased, probably owing to public information after the large HRT studies. It is unclear why reproductive risk factors are less frequently recognized; educational programs should address this information deficit.
CRIS-Team Scopus Importer:2019-10-08

Beeinträchtigung der Gonadenfunktion nach Chemo- und Strahlentherapie im Kindes- und Jugendalter: Handlungsempfehlungen nach der S1 Leitlinie - Borgmann-Staudt, Anja; Jantke, Andreas; Hinz, Stefan; Beckmann, Matthias; Dittrich, Ralf; Lotz, Laura; Balcerek, Magdalena (Monatsschrift Kinderheilkunde, 2023)
CRIS-Team Scopus Importer:2023-05-26

Berlin, 03.01.2017 240th Opinion of DZK in Collaboration with FZB, DGI, DGPI, GPP, DGGG, DRG and DGMP on Tuberculous Screening in Pregnant Women in the Context of 36 (4) Infection Protection Act (IfSG) - Seelbach-Goebe, Birgit; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36157

Berlin, 15th July 2016 Report on the Outline of the "Guideline for Obtaining Blood and Blood Components and for the Usage of Blood Products (Guideline of Haemotherapy)" Report of the German Society of Gynaecology and Obstetrics (GSGO) - Wallwiener, Diethelm; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32964

Berlin, 16.08.2017 250th Statement of the German Society of Gynecology and Obstetrics e. V. for the Modification of the Cancer Awareness Guidelines (KFE-RL) Mammography Screening: Letters of invitation and decision-making as well as other Changes in Section III B of the CRCD - Seelbach-Goebel, Birgit; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36125

Berlin, 17.02.2017 244th Statement of the German Society of Gynecology and Obstetrics e. V. for the Modification of Children's RiLi until the Age of 6: Examination Book for Children for Extended Neonatal Screening and Screening for Cystic Fibrosis - Seelbach-Goebel, Birgit; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36124

Berlin, 18th May 2017 245th Opinion of the DGGG on transcervical Radiofrequency Ablation with intrauterine Ultrasound Guidance in Uterine Myomas - Runnebaum, Ingo; Seelbach-Goebel, Birgit; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36138

Berlin, 20th April 2016 Statement on the planned Design of the G-BA for Changing of Directives on medical Measures for artificial Insemination (KB -RL) - Semen Analysis Parameter for an Indication for Intracytoplasmic Sperm Injection rather than In-vitro-Fertilization - Wallwiener, Diethelm; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32973

Berlin, 20th June 2016 Report for Modification of the Guideline about the Early Detection of Diseases in Children under the Age of 6 Years (Children's Guideline): Screening for critical congenital Heart Disease using Pulse Oximetry in Newborn Report of the German Society of Gynaecology and Obstetrics (GSGO) - Wallwiener, Diethelm; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32965

Berlin, 25.05.2016 Opinion for Changes of Early Cancer Detection-Guideline (KFE-RL): Cervical Cancer - screening - Wallwiener, Diethelm; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32974

Berlin, 27.01.2017 242nd Statement of the German Society for Gynecology and Obstetrics e. V. in cooperation with the Professional Association of Gynecologists e. V. Amending the DMP - A - RL: Supplement to Annex 3 (DMP Breast Cancer) and Appendix 4 (Breast Cancer Documentation) - Seelbach-Goebel, Birgit; Beckmann, Matthias W.; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36123

Berlin, 29 July 2016 Opinion on the Preliminary Report of the IQTiG on the planning-relevant Quality Indicators - Wallwiener, Diethelm; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32949

Berlin, 2nd May 2016 Opinion on the Preliminary Report A10-03 - Wallwiener, Diethelm; Beckmann, Matthias; Schulz-Wendtland, Ruediger (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:14675

Berlin, January 11, 2016-Opinion for the Assessment on Testing the Magnetic Resonance Imaging-guided focused Ultrasound Surgery for the Treatment of Uterine Myomas (MRgFUS-TUF) - Wallwiener, Diethelm; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32984

Berufgruppenspezifische Akzeptanz der elektronischen Patientenakte im Kontext der Geburtshilfe - Sohn, Stefan; Beckmann, Matthias; Raß, Matthias; Schöffski, Oliver; Sippel, Wilfried; Zagel, Christian; Beckmann, Kai (Deutsche Gesellschaft für Medizinische Informatik, Biometrie und Epidemiologie., 2009)
WiSo2-Import:2015-10-02:467

Brain and breast cancer cells with pten loss of function reveal enhanced durotaxis and rhob dependent amoeboid migration utilizing 3d scaffolds and aligned microfiber tracts - Wieland, Annalena; Strissel, Pamela; Schorle, Hannah; Bakirci, Ezgi; Janzen, Dieter; Beckmann, Matthias; Eckstein, Markus; Dalton, Paul D.; Strick, Reiner (Cancers, 2021)
Background: Glioblastoma multiforme (GBM) and metastatic triple-negative breast cancer (TNBC) with PTEN mutations often lead to brain dissemination with poor patient outcome, thus new therapeutic targets are needed. To understand signaling, controlling the dynamics and mechanics of brain tumor cell migration, we implemented GBM and TNBC cell lines and designed 3D aligned microfibers and scaffolds mimicking brain structures. Methods: 3D microfibers and scaffolds were printed using melt electrowriting. GBM and TNBC cell lines with opposing PTEN genotypes were analyzed with RHO-ROCK-PTEN inhibitors and PTEN rescue using live-cell imaging. RNA-sequencing and qPCR of tumor cells in 3D with microfibers were performed, while scanning electron microscopy and confocal microscopy addressed cell morphology. Results: In contrast to the PTEN wildtype, GBM and TNBC cells with PTEN loss of function yielded enhanced durotaxis, topotaxis, adhesion, amoeboid migration on 3D microfibers and significant high RHOB expression. Functional studies concerning RHOB-ROCK-PTEN signaling confirmed the essential role for the above cellular processes. Conclusions: This study demonstrates a significant role of the PTEN genotype and RHOB expression for durotaxis, adhesion and migration dependent on 3D. GBM and TNBC cells with PTEN loss of function have an affinity for stiff brain structures promoting metastasis. 3D microfibers represent an important tool to model brain metastasizing tumor cells, where RHO-inhibitors could play an essential role for improved therapy.
CRIS-Team Scopus Importer:2021-10-29
Keywords: 3D microfiber; 3D tumor model; Amoeboid cell migration; Brain cancer; Breast cancer; Durotaxis; PTEN; RHO; ROCK; Topotaxis

BRCA2 Hypomorphic Missense Variants Confer Moderate Risks of Breast Cancer - Shimelis, Hermela; Mesman, Romy L. S.; Von Nicolai, Catharina; Ehlen, Asa; Guidugli, Lucia; Martin, Charlotte; Calleja, Fabienne M. G. R.; Meeks, Huong; Hallberg, Emily; Hinton, Jamie; Lilyquist, Jenna; Hu, Chunling; et al. (Cancer Research, 2017)
Breast cancer risks conferred by many germline missense variants in the BRCA1 and BRCA2 genes, often referred to as variants of uncertain significance (VUS), have not been established. In this study, associations between 19 BRCA1 and 33 BRCA2 missense substitution variants and breast cancer risk were investigated through a breast cancer case-control study using genotyping data from 38 studies of predominantly European ancestry (41,890 cases and 41,607 controls) and nine studies of Asian ancestry (6,269 cases and 6,624 controls). The BRCA2 c.9104A>C, p.Tyr3035Ser (OR = 2.52; P = 0.04), and BRCA1 c.5096G>A, p.Arg1699Gln (OR = 4.29; P = 0.009) variant were associated with moderately increased risks of breast cancer among Europeans, whereas BRCA2 c.7522G>A, p.Gly2508Ser (OR = 2.68; P = 0.004), and c.8187G>T, p.Lys2729Asn (OR = 1.4; P = 0.004) were associated with moderate and low risks of breast cancer among Asians. Functional characterization of the BRCA2 variants using four quantitative assays showed reduced BRCA2 activity for p.Tyr3035Ser compared with wild-type. Overall, our results show how BRCA2 missense variants that influence protein function can confer clinically relevant, moderately increased risks of breast cancer, with potential implications for risk management guidelines in women with these specific variants. Cancer Res; 77(11); 2789-99. ©2017 AACR.
EVALuna2:36140

BRCA2 Polymorphic Stop Codon K3326X and the Risk of Breast, Prostate, and Ovarian Cancers - Meeks, Huong D.; Song, Honglin; Michailidou, Kyriaki; Bolla, Manjeet K.; Dennis, Joe; Wang, Qin; Barrowdale, Daniel; Frost, Debra; Mcguffog, Lesley; Ellis, Steve; Feng, Bingjian; Buys, Saundra S.; et al. (Journal of the National Cancer Institute, 2016)
BACKGROUND: The K3326X variant in BRCA2 (BRCA2*c.9976A>T; p.Lys3326*; rs11571833) has been found to be associated with small increased risks of breast cancer. However, it is not clear to what extent linkage disequilibrium with fully pathogenic mutations might account for this association. There is scant information about the effect of K3326X in other hormone-related cancers. METHODS: Using weighted logistic regression, we analyzed data from the large iCOGS study including 76 637 cancer case patients and 83 796 control patients to estimate odds ratios (ORw) and 95% confidence intervals (CIs) for K3326X variant carriers in relation to breast, ovarian, and prostate cancer risks, with weights defined as probability of not having a pathogenic BRCA2 variant. Using Cox proportional hazards modeling, we also examined the associations of K3326X with breast and ovarian cancer risks among 7183 BRCA1 variant carriers. All statistical tests were two-sided. RESULTS: The K3326X variant was associated with breast (ORw = 1.28, 95% CI = 1.17 to 1.40, P = 5.9x10(-) (6)) and invasive ovarian cancer (ORw = 1.26, 95% CI = 1.10 to 1.43, P = 3.8x10(-3)). These associations were stronger for serous ovarian cancer and for estrogen receptor-negative breast cancer (ORw = 1.46, 95% CI = 1.2 to 1.70, P = 3.4x10(-5) and ORw = 1.50, 95% CI = 1.28 to 1.76, P = 4.1x10(-5), respectively). For BRCA1 mutation carriers, there was a statistically significant inverse association of the K3326X variant with risk of ovarian cancer (HR = 0.43, 95% CI = 0.22 to 0.84, P = .013) but no association with breast cancer. No association with prostate cancer was observed. CONCLUSIONS: Our study provides evidence that the K3326X variant is associated with risk of developing breast and ovarian cancers independent of other pathogenic variants in BRCA2. Further studies are needed to determine the biological mechanism of action responsible for these associations.
EVALuna2:33125

BRCA mutations and their influence on pathological complete response and prognosis in a clinical cohort of neoadjuvantly treated breast cancer patients - Wunderle, Marius; Gaß, Paul; Häberle, Lothar; Flesch, Vivien M.; Rauh, Claudia; Bani, Mayada; Hack, Carolin; Schrauder, Michael G.; Jud, Sebastian; Emons, Julius; Erber, Ramona; Ekici, Arif Bülent; et al. (Breast Cancer Research and Treatment, 2018)
PURPOSE: BRCA1/2 mutations influence the molecular characteristics and the effects of systemic treatment of breast cancer. This study investigates the impact of germline BRCA1/2 mutations on pathological complete response and prognosis in patients receiving neoadjuvant systemic chemotherapy. METHODS: Breast cancer patients were tested for a BRCA1/2 mutation in clinical routine work and were treated with anthracycline-based or platinum-based neoadjuvant chemotherapy between 1997 and 2015. These patients were identified in the tumor registry of the Breast Center of the University of Erlangen (Germany). Logistic regression and Cox regression analyses were performed to investigate the associations between BRCA1/2 mutation status, pathological complete response, disease-free survival, and overall survival. RESULTS: Among 355 patients, 59 had a mutation in BRCA1 or in BRCA2 (16.6%), 43 in BRCA1 (12.1%), and 16 in BRCA2 (4.5%). Pathological complete response defined as "ypT0; ypN0" was observed in 54.3% of BRCA1/2 mutation carriers, but only in 22.6% of non-carriers. The adjusted odds ratio was 2.48 (95% CI 1.26-4.91) for BRCA1/2 carriers versus non-carriers. Patients who achieved a pathological complete response had better disease-free survival and overall survival rates compared with those who did not achieve a pathological complete response, regardless of BRCA1/2 mutation status. CONCLUSIONS: BRCA1/2 mutation status leads to better responses to neoadjuvant chemotherapy in breast cancer. Pathological complete response is the main predictor of disease-free survival and overall survival, independently of BRCA1/2 mutation status.
EVALuna2:34606

Breast cancer patients' satisfaction with individual therapy goals and treatment in a standardized integrative medicine consultancy service - Hack, Carolin; Antoniadis, Sophia; Hackl, Janina; Langemann, Hanna; Schwitulla, Judith; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: Complementary medicine services are nowadays usually quite heterogeneous, and little information is available on standards for running an integrative medicine consultancy service. This study aimed to assess patients' satisfaction with a standardized treatment service on integrative medicine. METHODS: Using a cross-sectional design, 75 breast cancer patients from the integrative medicine consultancy service at the University Breast Center for Franconia were evaluated between January 2016 and March 2017. At primary consultation, patients answered a standardized questionnaire on their medical history and treatment goals regarding integrative medicine. In a subsequent interview, patients evaluated their satisfaction with the treatment service and individual treatment goals. RESULTS: 72% of the patients (n = 54) reported high satisfaction with the overall approach of the treatment service. 76% of the patients (n = 57) were very satisfied or satisfied with their individual treatment plans. The most frequently reported goals were to slow tumor progression (n = 64, 85.3%), reducing the side effects of conventional cancer treatments (n = 60, 80%), and a desire to participate actively in the treatment of breast cancer (n = 64, 85.3%). CONCLUSIONS: Using a standardized procedure in integrative medicine allows a high quality level to be offered to patients. Overall, breast cancer patients report very high satisfaction with the integrative medicine consultancy service and state long-term treatment goals. Hence, long-term treatment with integrative medicine methods should be taken into consideration.
EVALuna2:209947

Breast cancer risk assessment in a mammography screening program and participation in the IBIS-II chemoprevention trial - Löhberg, Christian; Jud, Sebastian; Häberle, Lothar; Heusinger, Katharina; Dilbat, Gerhard; Hein, Alexander; Rauh, Claudia; Dall, Peter; Rix, Nadine; Heinrich, Sabrina; Buchholz, Stefan; Lex, Benno; et al. (Breast Cancer Research and Treatment, 2010)
It has been shown in several studies that antihormonal compounds can offer effective prophylactic treatment to prevent breast cancer. In view of the low participation rates in chemoprevention trials, the purpose of this study was to identify the characteristics of women taking part in a population-based mammography screening program who wished to obtain information about the risk of breast cancer and then participate in the the International Breast Cancer Intervention Study II (IBIS-II) trial, a randomized double-blind controlled chemoprevention trial comparing anastrozole with placebo. A paper-based survey was conducted in a population-based mammography screening program in Germany between 2007 and 2009. All women who met the criteria for the mammography screening program were invited to complete a questionnaire. A total of 2,524 women completed the questionnaire, and 17.7% (n = 446) met the eligibility criteria for the IBIS-II trial after risk assessment. The women who wished to receive further information about chemoprevention were significantly younger (P < 0.01) and had significantly more children (P = 0.03) and significantly more relatives with breast cancer (P < 0.001). There were no significant differences between the participants with regard to body mass index or hormone replacement therapy. Normal mammographic findings at screening were the main reason (42%) for declining to participate in the IBIS-II trial or attend risk counseling. The ultimate rate of recruitment to the IBIS-II trial was very low (three women). Offering chemoprevention to women within a mammography screening unit as part of a paper-based survey resulted in low participation rates for both, the survey and the final participation in the IBIS-II trial. More individualized approaches and communication of breast cancer risk at the time of the risk assessment might be helpful to increase the participation and the understanding of chemopreventive approaches. © 2010 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer risk; Chemoprevention trial; IBIS-II; Mammography screening; Patient recruitment

Breast Cancer Risk Factors and Survival by Tumor Subtype: Pooled Analyses from the Breast Cancer Association Consortium - Morra, Anna; Jung, Audrey Y.; Behrens, Sabine; Keeman, Renske; Ahearn, Thomas U.; Anton-Culver, Hoda; Arndt, Volker; Augustinsson, Annelie; Auvinen, Päivi K.; Beane Freeman, Laura E.; Becher, Heiko; Beckmann, Matthias; et al. (Cancer Epidemiology Biomarkers & Prevention, 2021)
BACKGROUND: It is not known whether modifiable lifestyle factors that predict survival after invasive breast cancer differ by subtype. METHODS: We analyzed data for 121,435 women diagnosed with breast cancer from 67 studies in the Breast Cancer Association Consortium with 16,890 deaths (8,554 breast cancer specific) over 10 years. Cox regression was used to estimate associations between risk factors and 10-year all-cause mortality and breast cancer-specific mortality overall, by estrogen receptor (ER) status, and by intrinsic-like subtype. RESULTS: There was no evidence of heterogeneous associations between risk factors and mortality by subtype (Padj > 0.30). The strongest associations were between all-cause mortality and BMI ≥30 versus 18.5-25 kg/m2 [HR (95% confidence interval (CI), 1.19 (1.06-1.34)]; current versus never smoking [1.37 (1.27-1.47)], high versus low physical activity [0.43 (0.21-0.86)], age ≥30 years versus <20 years at first pregnancy [0.79 (0.72-0.86)]; >0-<5 years versus ≥10 years since last full-term birth [1.31 (1.11-1.55)]; ever versus never use of oral contraceptives [0.91 (0.87-0.96)]; ever versus never use of menopausal hormone therapy, including current estrogen-progestin therapy [0.61 (0.54-0.69)]. Similar associations with breast cancer mortality were weaker; for example, 1.11 (1.02-1.21) for current versus never smoking. CONCLUSIONS: We confirm associations between modifiable lifestyle factors and 10-year all-cause mortality. There was no strong evidence that associations differed by ER status or intrinsic-like subtype. IMPACT: Given the large dataset and lack of evidence that associations between modifiable risk factors and 10-year mortality differed by subtype, these associations could be cautiously used in prognostication models to inform patient-centered care.
CRIS-Team Scopus Importer:2021-04-16

Breast cancer risk - From genetics to molecular understanding of pathogenesis - Fasching, Peter; Ekici, Arif Bülent; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Schneider, Michael; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Several advancements over the last decade have triggered the developments in the field of breast cancer risk research. One of them is the availability of the human genome sequence along with cheap genotyping possibilities. Another is the globalization of research, which has led to the growth of research collaboration into large international consortia that facilitate the pooling of clinical and genotype data of hundreds of thousands of patients and healthy control individuals. This review concerns with the recent developments in breast cancer risk research and focuses on the discovery of new genetic breast cancer risk factors and their meaning in the context of established non-genetic risk factors. Finally the clinical application is highly dependent on the accuracy of breast cancer risk prediction models, not only for all breast cancer patients, but also for molecular subtypes, preferably for those which are associated with an unfavorable prognosis. Recently risk prediction incorporates all possible risk factors, which include epidemiological risk factors, mammographic density and genetic risk factors. © Georg Thieme Verlag KG Stuttgart• New York•.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA; breast cancer risk; gene-environment interaction; genetic risk factors; prediction models

Breast Cancer Risk Genes - Association Analysis in More than 113,000 Women - Dorling, Leila; Carvalho, Sara; Allen, Jamie; Gonzalez-Neira, Anna; Luccarini, Craig; Wahlstrom, Cecilia; Pooley, Karen A.; Parsons, Michael T.; Fortuno, Cristina; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; et al. (New England Journal of Medicine, 2021)
BACKGROUND
CRIS-Team WoS Importer:2021-03-26

Breast cancer risk - Genes, environment and clinics Mammakarzinomrisiko - Gene, Umwelt und Klinik - Fasching, Peter; Ekici, Arif Bülent; Adamietz, B. R.; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2011)
The information available about breast cancer risk factors has increased dramatically during the last 10 years. In particular, studies of low-penetrance genes and mammographic density have improved our understanding of breast cancer risk. In addition, initial steps have been taken in investigating interactions between genes and environmental factors. This review concerns with actual data on this topic. Several genome-wide association studies (GWASs) with a casecontrol design, as well as large-scale validation studies, have identified and validated more than a dozen single nucleotide polymorphisms (SNPs) associated with breast cancer risk. They are located not only in or close to genes known to be involved in cancer pathogenesis, but also in genes not previously associated with breast cancer pathogenesis, or may even not be related to any genes. SNPs have also been identified that alter the lifetime risk in BRCA mutation carriers. With regard to nongenetic risk factors, studies of postmenopausal hormone replacement therapy (HRT) have revealed important information on how to weigh up the risks and benefits of HRT. Mammographic density (MD) has become an accepted and important breast cancer risk factor. Lifestyle and nutritional considerations have become an integral part of most studies of breast cancer risk, and some improvements have been made in this field as well. More than 10 years after the publication of the first breast cancer prevention studies with tamoxifen, other substances such as raloxifene and aromatase inhibitors have been investigated and have also been shown to have preventive potential. Finally, mammographic screening systems have been implemented in most Western countries during the last decade. These may be developed further by including more individualized methods of predicting the patients breast cancer risk. © Georg Thieme Verlag KG Stuttgart - New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA (breast cancer antigen); breast; breast feeding; CAM (Complementary and Alternative medicine); cancer registry; estrogen receptor

Breast cancer risks associated with missense variants in breast cancer susceptibility genes - Dorling, Leila; Carvalho, Sara; Allen, Jamie; Parsons, Michael T.; Fortuno, Cristina; Gonzalez-Neira, Anna; Heijl, Stephan M.; Adank, Muriel A.; Ahearn, Thomas U.; Andrulis, Irene L.; Auvinen, Paivi; Becher, Heiko; et al. (Genome Medicine, 2022)
Background Protein truncating variants in ATM, BRCA1, BRCA2, CHEK2, and PALB2 are associated with increased breast cancer risk, but risks associated with missense variants in these genes are uncertain. Methods We analyzed data on 59,639 breast cancer cases and 53,165 controls from studies participating in the Breast Cancer Association Consortium BRIDGES project. We sampled training (80%) and validation (20%) sets to analyze rare missense variants in ATM (1146 training variants), BRCA1 (644), BRCA2 (1425), CHEK2 (325), and PALB2 (472). We evaluated breast cancer risks according to five in silico prediction-of-deleteriousness algorithms, functional protein domain, and frequency, using logistic regression models and also mixture models in which a subset of variants was assumed to be risk-associated. Results The most predictive in silico algorithms were Helix (BRCA1, BRCA2 and CHEK2) and CADD (ATM). Increased risks appeared restricted to functional protein domains for ATM (FAT and PIK domains) and BRCA1 (RING and BRCT domains). For ATM, BRCA1, and BRCA2, data were compatible with small subsets (approximately 7%, 2%, and 0.6%, respectively) of rare missense variants giving similar risk to those of protein truncating variants in the same gene. For CHEK2, data were more consistent with a large fraction (approximately 60%) of rare missense variants giving a lower risk (OR 1.75, 95% CI (1.47-2.08)) than CHEK2 protein truncating variants. There was little evidence for an association with risk for missense variants in PALB2. The best fitting models were well calibrated in the validation set. Conclusions These results will inform risk prediction models and the selection of candidate variants for functional assays and could contribute to the clinical reporting of gene panel testing for breast cancer susceptibility.
CRIS-Team WoS Importer:2022-06-03

Breast cancer risk variants at 6q25 display different phenotype associations and regulate ESR1, RMND1 and CCDC170 - Dunning, Alison M.; Michailidou, Kyriaki; Kuchenbaecker, Karoline B.; Thompson, Deborah; French, Juliet D.; Beesley, Jonathan; Healey, Catherine S.; Kar, Siddhartha; Pooley, Karen A.; Lopez-Knowles, Elena; Dicks, Ed; Barrowdale, Daniel; et al. (Nature Genetics, 2016)
We analyzed 3,872 common genetic variants across the ESR1 locus (encoding estrogen receptor α) in 118,816 subjects from three international consortia. We found evidence for at least five independent causal variants, each associated with different phenotype sets, including estrogen receptor (ER(+) or ER(-)) and human ERBB2 (HER2(+) or HER2(-)) tumor subtypes, mammographic density and tumor grade. The best candidate causal variants for ER(-) tumors lie in four separate enhancer elements, and their risk alleles reduce expression of ESR1, RMND1 and CCDC170, whereas the risk alleles of the strongest candidates for the remaining independent causal variant disrupt a silencer element and putatively increase ESR1 and RMND1 expression.
EVALuna2:33329

Breast MRI texture analysis for prediction of BRCA-associated genetic risk - Vasileiou, Georgia; Costa, Maria J.; Long, Christopher; Wetzler, Iris; Hoyer, Juliane; Kraus, Cornelia; Popp, Bernt; Emons, Julius; Wunderle, Marius; Wenkel, Evelyn; Uder, Michael; Beckmann, Matthias; et al. (BMC Medical Imaging, 2020)
BACKGROUND: BRCA1/2 deleterious variants account for most of the hereditary breast and ovarian cancer cases. Prediction models and guidelines for the assessment of genetic risk rely heavily on criteria with high variability such as family cancer history. Here we investigated the efficacy of MRI (magnetic resonance imaging) texture features as a predictor for BRCA mutation status. METHODS: A total of 41 female breast cancer individuals at high genetic risk, sixteen with a BRCA1/2 pathogenic variant and twenty five controls were included. From each MRI 4225 computer-extracted voxels were analyzed. Non-imaging features including clinical, family cancer history variables and triple negative receptor status (TNBC) were complementarily used. Lasso-principal component regression (L-PCR) analysis was implemented to compare the predictive performance, assessed as area under the curve (AUC), when imaging features were used, and lasso logistic regression or conventional logistic regression for the remaining analyses. RESULTS: Lasso-selected imaging principal components showed the highest predictive value (AUC 0.86), surpassing family cancer history. Clinical variables comprising age at disease onset and bilateral breast cancer yielded a relatively poor AUC ( 0.56). Combination of imaging with the non-imaging variables led to an improvement of predictive performance in all analyses, with TNBC along with the imaging components yielding the highest AUC (0.94). Replacing family history variables with imaging components yielded an improvement of classification performance of 4%, suggesting that imaging compensates the predictive information arising from family cancer structure. CONCLUSIONS: The L-PCR model uncovered evidence for the utility of MRI texture features in distinguishing between BRCA1/2 positive and negative high-risk breast cancer individuals, which may suggest value to diagnostic routine. Integration of computer-extracted texture analysis from MRI modalities in prediction models and inclusion criteria might play a role in reducing false positives or missed cases especially when established risk variables such as family history are missing.
CRIS-Team Scopus Importer:2020-08-07
Keywords: BRCA1/2; Breast cancer; HBOC; L-PCR; MRI; Texture analysis

Breast Tumor Analysis Using Shifted-Excitation Raman Difference Spectroscopy (SERDS) - Gebrekidan, Medhanie; Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Emons, Julius; Beckmann, Matthias; Bräuer, Andreas (Technology in Cancer Research & Treatment, 2018)
We used a shifted-excitation Raman difference spectroscopy method for the ex vivo classification of resected and formalin-fixed breast tissue samples as normal (healthy) tissue, fibroadenoma, or invasive carcinoma. We analyzed 8 tissue samples containing invasive carcinoma that were surrounded by normal tissue and 3 tissue samples with fibroadenoma only. We made various measurement sites on various tissue samples, in total 240 measurements for each type of tissue. Although the acquired raw spectra contain enough information to clearly differentiate between normal and tumor (fibroadenoma and invasive carcinoma) tissue, the differentiation between fibroadenoma and invasive carcinoma was possible only after the shifted-excitation Raman difference spectroscopy isolation of pure Raman spectra from the heavily fluorescence interfered raw spectra. We used 784 and 785 nm as excitation wavelengths for the shifted-excitation Raman difference spectroscopy method. The differences in the obtained pure Raman spectra are assigned to the different chemical compositions of normal breast tissue, fibroadenoma, and invasive breast carcinoma. Principal component analysis and linear discriminant analysis showed excellent classification results in the Raman shift range between 1000 and 1800 cm-1. Invasive breast carcinoma was identified with 99.15% sensitivity, and the absence of invasive carcinoma was identified with 90.40% specificity. Tumor tissue in tumor-containing tissue was identified with 100% sensitivity, and the absence of tumor in no-tumor containing tissue was identified with 100% specificity. As gold standard for the determination of the sensitivity and the specificity, we considered the conventional histopathological classification. In summary, shifted-excitation Raman difference spectroscopy could be potentially very useful to support histopathological diagnosis in breast pathology.
EVALuna2:34855

Breast volume assessment with a smart phone device compared to MRI - Behrens, Annika; Wunderle, Marius; Häberle, Lothar; Stamminger, Marc; Zint, Daniel; Emons, Julius; Heindl, Felix; Hack, Caroline; Ohlmeyer, Sabine; Uder, Michael; Beckmann, Matthias; Fasching, Peter (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Can a university reproductive medicine centre be financed under the pre-existing general conditions in Germany? - Hildebrandt, Thomas; Oversohl, Nicola; Dittrich, Ralf; Lotz, Laura; Beckmann, Matthias; Lux, Michael P. (Geburtshilfe und Frauenheilkunde, 2019)
Background Reduced resources for financing healthcare services are available to the German health system. For this reason, demographic development represents one of the greatest challenges for the German health system. Reproductive medicine can offer potential solutions and counteract the ageing of the population through an increase in the birth rate. Most reproductive medical treatments take place in private centres. For the development of new, innovative therapeutic approaches, continuing education and scientific advancement, university centres are essential. Materials and Methods Using multistage contribution margin accounting, IVF and ICSI treatments at the University Fertility Centre Franken (UFF) were investigated in 2012. The cost situation from the perspective of the patient couple and the statutory payer were contrasted with the cost and revenue situation of the service provider as a university reproductive medicine centre. Results The costs for the patient couple for an IVF treatment cycle were 538.71 € and for an ICSI cycle, 700.07 €. For the payer, the costs, including the university flat rate (194.80 €) to be paid, amount to 733.51 € for an IVF cycle and 894.87 € for an ICSI cycle. The payments of the patient couple and the payer were added and this yielded total costs of 1272.22 € and 1594.94 €. The University Fertility Centre Franken, as a part of the Department of Gynaecology of the Erlangen University Hospital, incurred costs of 1364.47 € for an IVF treatment cycle and 1423.48 € for an ICSI treatment cycle. In addition, the OB/GYN clinic had to pay the university hospital a flat general expense rate of 14.9% of the income. There was thus a loss for the department of gynaecology of 281.81 € for an IVF cycle and 66.19 € for an ICSI cycle. Discussion From the perspective of a university reproductive medicine centre, IVF and ICSI treatments currently cannot be performed in a cost-covering manner. At the same time, a reproductive medicine treatment cycle represents a significant financial burden on the patient couple due to only partial cost coverage by most statutory health insurance funds. This therefore demonstrates a need for action in health policy to revise and, in the interest of the patient couples, reproductive medicine centres and, not least of all, in the interest of society, to improve existing cost absorption policies and thus also benefit from this as a society over the long term.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Continuing education; Endocrinology; Financial resources; ICSI; IVF; Reproductive medicine

Candidate locus analysis of the TERT-CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Carvajal-Carmona, Luis G.; O'Mara, Tracy A.; Painter, Jodie N.; Lose, Felicity A.; Dennis, Joe; Michailidou, Kyriaki; Tyrer, Jonathan P.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; Pooley, Karen; Beesley, Jonathan; et al. (Human genetics, 2015)
Several studies have reported associations between multiple cancer types and single-nucleotide polymorphisms (SNPs) on chromosome 5p15, which harbours TERT and CLPTM1L, but no such association has been reported with endometrial cancer. To evaluate the role of genetic variants at the TERT-CLPTM1L region in endometrial cancer risk, we carried out comprehensive fine-mapping analyses of genotyped and imputed SNPs using a custom Illumina iSelect array which includes dense SNP coverage of this region. We examined 396 SNPs (113 genotyped, 283 imputed) in 4,401 endometrial cancer cases and 28,758 controls. Single-SNP and forward/backward logistic regression models suggested evidence for three variants independently associated with endometrial cancer risk (P = 4.9 × 10(-6) to P = 7.7 × 10(-5)). Only one falls into a haplotype previously associated with other cancer types (rs7705526, in TERT intron 1), and this SNP has been shown to alter TERT promoter activity. One of the novel associations (rs13174814) maps to a second region in the TERT promoter and the other (rs62329728) is in the promoter region of CLPTM1L; neither are correlated with previously reported cancer-associated SNPs. Using TCGA RNASeq data, we found significantly increased expression of both TERT and CLPTM1L in endometrial cancer tissue compared with normal tissue (TERT P = 1.5 × 10(-18), CLPTM1L P = 1.5 × 10(-19)). Our study thus reports a novel endometrial cancer risk locus and expands the spectrum of cancer types associated with genetic variation at 5p15, further highlighting the importance of this region for cancer susceptibility.
EVALuna2:9280

Can Sonographic Fetal Biometry Predict Adverse Perinatal Outcome? - Pretscher, Jutta; Schwenke, Eva; Baier, Friederike; Kehl, Sven; Schneider, Michael; Stumpfe, Florian Matthias; Schmid, Matthias; Beckmann, Matthias; Mayr, Andreas; Schild, Ralf; Faschingbauer, Florian (Ultraschall in der Medizin, 2019)
Objective To evaluate the association of sonographic fetal biometry (sonographic head circumference (soHC), sonographic abdominal circumference (soAC), estimated fetal weight (EFW)) with mode of delivery and adverse perinatal outcome. Methods Singleton pregnancies with a gestational age ≥ 37 weeks and an ultrasound examination with complete biometric parameters within 7 days before delivery were retrospectively included. The association between soHC, soAC, EFW and fetal (5-min Apgar < 7, pH < 7.1, neonatal intensive care unit (NICU) admission, shoulder dystocia (ShD)) and maternal (obstetric intervention (OI): caesarean or vaginal operative delivery, obstetric anal sphincter injury syndrome (OASIS), postpartum hemorrhage (pph)) adverse outcomes were analyzed using univariate and multivariate logistic regression analyses. Results 12 396 women were included and 3479 (28.07 %) needed an OI. Multivariate analyses demonstrated significant contributions for the prediction of OI by soHC and soAC, whereas EFW did not reach significance. The highest OR was shown for soHC (1087, p < 0.001). ShD occurred in 73 (0.59 %) of the deliveries. Multivariate analyses showed that significant contributions for the prediction of ShD were provided only by soAC (OR 1460, p = 0.007). For the other maternal and neonatal adverse outcome parameters, no significant association with the biometric measurements could be demonstrated in the multivariate analyses. The overall detection rates for the prediction of adverse perinatal outcome by the different biometric parameters and EFW were poor. Conclusion Obstetric management decisions should not be based solely on measurements of biometric parameters or EFW.
CRIS-Team Scopus Importer:2019-05-02
Keywords: adverse perinatal outcome; biometric parameters; fetal weight estimation; mode of delivery; ultrasound

CCNE1 and survival of patients with tubo-ovarian high-grade serous carcinoma: An Ovarian Tumor Tissue Analysis consortium study - Kang, Eun Young; Weir, Ashley; Meagher, Nicola S.; Farrington, Kyo; Nelson, Gregg S.; Ghatage, Prafull; Lee, Cheng Han; Riggan, Marjorie J.; Bolithon, Adelyn; Popovic, Gordana; Leung, Betty; Tang, Katrina; et al. (Cancer, 2023)
Background: Cyclin E1 (CCNE1) is a potential predictive marker and therapeutic target in tubo-ovarian high-grade serous carcinoma (HGSC). Smaller studies have revealed unfavorable associations for CCNE1 amplification and CCNE1 overexpression with survival, but to date no large-scale, histotype-specific validation has been performed. The hypothesis was that high-level amplification of CCNE1 and CCNE1 overexpression, as well as a combination of the two, are linked to shorter overall survival in HGSC. Methods: Within the Ovarian Tumor Tissue Analysis consortium, amplification status and protein level in 3029 HGSC cases and mRNA expression in 2419 samples were investigated. Results: High-level amplification (>8 copies by chromogenic in situ hybridization) was found in 8.6% of HGSC and overexpression (>60% with at least 5% demonstrating strong intensity by immunohistochemistry) was found in 22.4%. CCNE1 high-level amplification and overexpression both were linked to shorter overall survival in multivariate survival analysis adjusted for age and stage, with hazard stratification by study (hazard ratio [HR], 1.26; 95% CI, 1.08-1.47, p =.034, and HR, 1.18; 95% CI, 1.05-1.32, p =.015, respectively). This was also true for cases with combined high-level amplification/overexpression (HR, 1.26; 95% CI, 1.09-1.47, p =.033). CCNE1 mRNA expression was not associated with overall survival (HR, 1.00 per 1-SD increase; 95% CI, 0.94-1.06; p =.58). CCNE1 high-level amplification is mutually exclusive with the presence of germline BRCA1/2 pathogenic variants and shows an inverse association to RB1 loss. Conclusion: This study provides large-scale validation that CCNE1 high-level amplification is associated with shorter survival, supporting its utility as a prognostic biomarker in HGSC.
CRIS-Team Scopus Importer:2023-02-17
Keywords: CCNE1 amplification; cyclin E1 expression; high-grade serous carcinoma; ovarian cancer; prognosis

Cerebroplacental versus Umbilicocerebral Ratio—Analyzing the Predictive Value Regarding Adverse Perinatal Outcomes in Low- and High-Risk Fetuses at Term - Stumpfe, Florian; Mayr, Andreas; Schneider, Michael; Kehl, Sven; Stübs, Frederik; Antoniadis, Sophia; Titzmann, Adriana; Pontones, Constanza; Bayer, Christian M.; Beckmann, Matthias; Faschingbauer, Florian (Medicina, 2023)
Background and Objectives: The aim of this study was to investigate the prediction of adverse perinatal outcomes using the cerebroplacental (CPR) and umbilicocerebral (UCR) ratios in different cohorts of singleton pregnancies. Materials and Methods: In this retrospective cohort study, we established our own Multiple of Median (MoM) for CPR and UCR. The predictive value for both ratios was studied in the following outcome parameters: emergency cesarean delivery, operative intervention (OI), OI due to fetal distress, 5-min Apgar < 7, admission to neonatal intensive care unit, and composite adverse perinatal outcome. The performance of the ratios was assessed in the following cohorts: total cohort (delivery ≥ 37 + 0 weeks gestation, all birth weight centiles), low-risk cohort (delivery ≥ 37 + 0 weeks gestation, birth weight ≥ 10. centile), prolonged pregnancy cohort (delivery ≥ 41 + 0 weeks gestation, birth weight ≥ 10. centile) and small-for-gestational-age fetuses (delivery ≥ 37 + 0 weeks gestation, birth weight < 10. centile). The underlying reference values for MoM were estimated using quantile regression depending on gestational age. Prediction performance was evaluated using logistic regression models assessing the corresponding Brier score, combining discriminatory power and calibration. Results: Overall, 3326 cases were included. Across all cohorts, in the case of a significant association between a studied outcome parameter and CPR, there was an association with UCR, respectively. The Brier score showed only minimal differences for both ratios. Conclusions: Our study provides further evidence regarding predictive values of CPR and UCR. The results of our study suggest that reversal of CPR to UCR does not improve the prediction of adverse perinatal outcomes.
CRIS-Team Scopus Importer:2023-09-08
Keywords: cerebroplacental ratio; CPR; UCR; umbilicocerebral ratio

Cervical cancer Zervixkarzinom - Beckmann, Matthias; Schmidberger, H. (Onkologe, 2020)
CRIS-Team Scopus Importer:2020-06-30

Cervical intraepithelial neoplasia grade 2/3: development during pregnancy and postpartum - Stübs, Frederik; Mergel, F.; Koch, M. C.; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; Mehlhorn, G. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Cervical intraepithelial neoplasia grade 3: development during pregnancy and postpartum - Stübs, Frederik; Mergel, Franziska; Koch, Martin; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; Mehlhorn, Grit (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aims of the present study were to evaluate the development of untreated cervical intraepithelial neoplasia (CIN) 3 during pregnancy and to assess persistence, progression, and regression rates postpartum to identify factors associated with regression. Methods: In a tertiary gynecology and obstetrics department, a total of 154 pregnant women with CIN 3 were treated in the dysplasia unit. The follow-up findings were analyzed retrospectively on the basis of histological, cytological, and human papillomavirus (HPV) testing of 154 pregnant women confirmed as having CIN 3 in colposcopically guided biopsies. Results: The rates of persistence, regression, and progression of CIN 3 in these women were 76.1%, 20% and 3.2%, respectively. Data for the delivery mode was available for 126 women. The rate of regression was almost twice as high with vaginal delivery as with cesarean section, at 27.4 vs. 15.2%, whereas the rate of progression was lower with vaginal delivery, at 2.7 vs. 6.5%. Conclusion: The rate of persistence of CIN observed in this study is comparable to that reported in other studies. The study provides strong evidence for greater regression among women who have vaginal deliveries. Careful work-up is recommended postpartum for this group of women in order to rule out persistent CIN 3 or invasive disease.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); Mode of delivery; Pregnancy; Treatment

Challenges and Opportunities for Real-World Evidence in Metastatic Luminal Breast Cancer - Lüftner, Diana; Hartkopf, Andreas D.; Lux, Michael P.; Overkamp, Friedrich; Tesch, Hans; Titzmann, Adriana; Pöschke, Patrik; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; Belleville, Erik; Janni, Wolfgang; et al. (Breast Care, 2021)
Background: The therapeutic armamentarium for patients with metastatic breast cancer is becoming more and more specific. Recommendations from clinical trials are not available for all treatment situations and patient subgroups, and it is therefore important to collect real-world data. Summary: To develop recommendations for up-to-date treatments and participation in clinical trials for patients with metastatic breast cancer, the Prospective Academic Translational Research PRAEGNANT Network was established to optimize the quality of oncological care in the advanced therapeutic setting. The main aim of PRAEGNANT is to systematically record medical care for patients with metastatic breast cancer in the real-life setting, including the outcome and side effects of different treatment strategies, to monitor quality-of-life changes during therapy, to identify patients eligible for participation in clinical studies, and to allow targeted therapies based on the molecular structures of breast carcinomas. Key Messages: This article describes the PRAEGNANT network and sheds light on the question of whether the various end points from clinical trials can be transferred to the real-world treatment situation.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Breast cancer; Luminal; Metastasis; PRAEGNANT; Real-world evidence

Characterization of Molecular Subtypes of Paget Disease of the Breast Using Immunohistochemistry and In Situ Hybridization - Wachter, David; wachter, peter wolf; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Riener, Marc-Oliver; Hartmann, Arndt; Strehl, Johanna D. (Archives of Pathology & Laboratory Medicine, 2018)
CONTEXT: - Paget disease of the breast, in most cases, represents intraepidermal spread of ductal carcinoma in situ. Molecular subtypes of invasive carcinoma of the breast have prognostic and therapeutic significance and show characteristic distribution. Little is known about the distribution of molecular subtypes in Paget disease of the breast. OBJECTIVES: - To examine the distribution of molecular subtypes in Paget disease of the breast and to compare them to concurrent invasive carcinoma of the breast, if present. DESIGN: - We examined 48 cases of Paget disease of the breast with immunohistochemistry and antibodies against estrogen and progesterone receptors, human epidermal growth factor receptor 2 (HER2), and Ki-67, as well as HER2 chromogenic in situ hybridization, to classify the cases into molecular subtypes. Then, we compared the results to the molecular subtypes of associated, invasive carcinoma of the breast, if present. RESULTS: - The HER2 subtype was the most common found in Paget disease of the breast, followed by the luminal B subtype and 2 cases of the triple-negative subtype. The associated, invasive carcinoma cases were most often of the luminal B subtype, followed by the HER2 subtype and the triple-negative subtype. The molecular subtype of Paget disease and invasive carcinoma was congruent in most of the cases. CONCLUSIONS: - Molecular subtypes of invasive carcinoma of the breast can already be detected in Paget disease. The distribution of molecular subtypes of Paget disease and of Paget disease-associated, invasive carcinoma differs from invasive carcinoma without associated Paget disease, with the HER2 subtype overrepresented in Paget disease and associated, invasive carcinoma and the luminal and triple-negative subtypes underrepresented.
EVALuna2:34808

Characterization of the impact of immune checkpoint inhibitors on platelet activation and aggregation - Schlüter, Julian; Cunningham, Sarah; Zimmermann, Robert; Achenbach, Susanne; Kramer, Rafaela; Erdmann, Michael; Beckmann, Matthias; Heinzerling, Lucie; Hackstein, Holger (Immunobiology, 2023)
Immune checkpoint inhibitors (ICIs) are effective oncological drugs which block cellular check-point receptors typically targeted by tumor immune evasion strategies. Despite their benefits, clinicians have reported treatment-associated thromboembolism during ICI therapy in recent years. Though several theories on this ICI-associated pathogenesis exist, the direct effects of ICIs on platelets remains unknown. We therefore investigated the potential direct and indirect effect of PD-1, PD-L1 and CTLA-4-targeting ICIs on platelet functionality in multifaceted in vitro experiments. Interestingly, we could not observe a clear effect of ICI on platelet aggregation and primary hemostasis in whole blood and platelet concentrate-based assays. Furthermore, the presence of ICIs in toll-like receptor stimulation had no significant impact on platelet surface marker expression. In a second approach, we investigated the indirect immunological impact of ICIs on platelet activation by exposing platelets to supernatants from ICI- and Staphylococcal enterotoxin B-exposed PBMCs. Whereas ICIs affected IL-2 levels in supernatants, we could not detect clear differences in the secretion of pro-thrombogenic factors and platelet responses. The obtained data suggest that the direct influence of ICIs on platelet activation or the influence of altered T cell function on platelet activation cannot be considered a major factor in the development of thrombotic events.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Immune checkpoint inhibitors; Platelet activation; Platelet function tests; Platelets; Thrombosis

Characterizing mammographic images by using generic texture features - Häberle, Lothar; Wagner, Florian; Fasching, Peter; Jud, Sebastian; Heusinger, Katharina; Löhberg, Christian; Hein, Alexander; Bayer, Christian M.; Hack, Carolin; Lux, Michael P.; Binder, Katja; Elter, Matthias; et al. (Breast Cancer Research, 2012)
Introduction: Although mammographic density is an established risk factor for breast cancer, its use is limited in clinical practice because of a lack of automated and standardized measurement methods. The aims of this study were to evaluate a variety of automated texture features in mammograms as risk factors for breast cancer and to compare them with the percentage mammographic density (PMD) by using a case-control study design.Methods: A case-control study including 864 cases and 418 controls was analyzed automatically. Four hundred seventy features were explored as possible risk factors for breast cancer. These included statistical features, moment-based features, spectral-energy features, and form-based features. An elaborate variable selection process using logistic regression analyses was performed to identify those features that were associated with case-control status. In addition, PMD was assessed and included in the regression model.Results: Of the 470 image-analysis features explored, 46 remained in the final logistic regression model. An area under the curve of 0.79, with an odds ratio per standard deviation change of 2.88 (95% CI, 2.28 to 3.65), was obtained with validation data. Adding the PMD did not improve the final model.Conclusions: Using texture features to predict the risk of breast cancer appears feasible. PMD did not show any additional value in this study. With regard to the features assessed, most of the analysis tools appeared to reflect mammographic density, although some features did not correlate with PMD. It remains to be investigated in larger case-control studies whether these features can contribute to increased prediction accuracy. © 2012 Fasching et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2021-07-19

Chylous ascites after lymphadenectomy for gynecological malignancies - Thiel, Falk C.; Parvanta, Parnian; Hein, Alexander; Mehlhorn, Grit; Lux, Michael P.; Renner, Stefan; Preisner, Achim; Beckmann, Matthias; Schrauder, Michael G. (Journal of Surgical Oncology, 2016)
BACKGROUND AND OBJECTIVES: Chylous ascites, an accumulation of milky-white lymph fluid in the peritoneal cavity, is a rare complication following retroperitoneal lymphadenectomy. This study evaluated the appearance and management of chylous ascites following lymphadenectomy for gynecological malignancies. METHODS: A total of 931 patients who underwent lymphadenectomy for gynecological malignancies at Erlangen University Hospital between 2002 and 2013 were reviewed retrospectively. RESULTS: Chylous ascites occurred postoperatively in 28 of the 931 patients (3.0%). All patients with chylous ascites had undergone combined systematic para-aortic and pelvic lymphadenectomy (SAPL). Patients with chylous ascites had a larger mean number of lymph nodes removed (51.9 vs. 40.0, P = 0.002) and the proportion of laparoscopic SAPLs was significantly higher (20/28; 71.4%) in comparison with open surgery (8/28; 28.6%) (P < 0.0001). Additional parameters, such as the number of positive lymph nodes, were not significantly associated with the occurrence of chylous ascites. Conservative management was sufficient to resolve chylous ascites in all observed cases, with a mean time to resolution of 8 days. CONCLUSIONS: Postoperative chylous ascites was more frequently observed in patients with laparoscopic SAPL in comparison with open SAPL and was strongly associated with a larger mean number of removed lymph nodes. J. Surg. Oncol. 2016;114:613-618. © 2016 Wiley Periodicals, Inc.
EVALuna2:32952

Circulating micro-RNAs as potential blood-based markers for early stage breast cancer detection - Schrauder, Michael G.; Strick, Reiner; Schulz-Wendtland, Rüdiger; Strissel, Pamela; Kahmann, Laura; Loehberg, Christian R.; Lux, Michael P.; Jud, Sebastian; Hartmann, Arndt; Hein, Alexander; Bayer, Christian M.; Bani, Mayada; et al. (PLoS ONE, 2012)
Introduction: MicroRNAs (miRNAs, miRs) are a class of small, non-coding RNA molecules with relevance as regulators of gene expression thereby affecting crucial processes in cancer development. MiRNAs offer great potential as biomarkers for cancer detection due to their remarkable stability in blood and their characteristic expression in many different diseases. We investigated whether microarray-based miRNA profiling on whole blood could discriminate between early stage breast cancer patients and healthy controls. Methods: We performed microarray-based miRNA profiling on whole blood of 48 early stage breast cancer patients at diagnosis along with 57 healthy individuals as controls. This was followed by a real-time semi-quantitative Polymerase Chain Reaction (RT-qPCR) validation in a separate cohort of 24 early stage breast cancer patients from a breast cancer screening unit and 24 age matched controls using two differentially expressed miRNAs (miR-202, miR-718). Results: Using the significance level of p<0.05, we found that 59 miRNAs were differentially expressed in whole blood of early stage breast cancer patients compared to healthy controls. 13 significantly up-regulated miRNAs and 46 significantly down-regulated miRNAs in our microarray panel of 1100 miRNAs and miRNA star sequences could be detected. A set of 240 miRNAs that was evaluated by radial basis function kernel support vector machines and 10-fold cross validation yielded a specificity of 78.8%, and a sensitivity of 92.5%, as well as an accuracy of 85.6%. Two miRNAs were validated by RT-qPCR in an independent cohort. The relative fold changes of the RT-qPCR validation were in line with the microarray data for both miRNAs, and statistically significant differences in miRNA-expression were found for miR-202. Conclusions: MiRNA profiling in whole blood has potential as a novel method for early stage breast cancer detection, but there are still challenges that need to be addressed to establish these new biomarkers in clinical use. © 2012 Schrauder et al.
CRIS-Team Scopus Importer:2021-07-19

Circulating miR-148b and miR-133a as biomarkers for breast cancer detection - Shen, Jie; Hu, Qiang; Schrauder, Michael; Yan, Li; Wang, Dan; Medico, Leonardo; Guo, Yuqing; Yao, Song; Zhu, Qianqian; Liu, Biao; Qin, Maochun; Beckmann, Matthias; et al. (Oncotarget, 2014)
Circulating microRNAs have drawn a great deal of attention as promising novel biomarkers for breast cancer. However, to date, the results are mixed. Here, we performed a three-stage microRNA analysis using plasma samples from breast cancer patients and healthy controls, with efforts taken to address several pitfalls in detection techniques and study design observed in previous studies. In the discovery phase with 122 Caucasian study subjects, we identified 43 microRNAs differentially expressed between breast cancer cases and healthy controls. When those microRNAs were compared with published data from other studies, we identified three microRNAs, including miR-148b, miR-133a and miR-409-3p, whose plasma levels were significantly higher in breast cancer cases than healthy controls and were also significant in previous independent studies. In the validation phase with 50 breast cancer cases and 50 healthy controls, we validated the associations with breast cancer detection for miR-148b and miR-133a (P = 1.5×10-6 and 1.3×10-10, respectively). In the in-vitro study phase, we found that both miR-148b and miR-133a were secreted from breast cancer cell lines, showing their secretory potential and possible tumor origin. Thus, our data suggest that both miR-148b and miR-133a have potential use as biomarkers for breast cancer detection.
EVALuna2:17449

Circulating tumor cells predict survival in early average-to-high risk breast cancer patients - Rack, Brigitte; Schindlbeck, Christian; Jueckstock, Julia; Andergassen, Ulrich; Hepp, Philip; Zwingers, Thomas; Friedl, Thomas W. P.; Lorenz, Ralf; Tesch, Hans; Fasching, Peter; Fehm, Tanja; Schneeweiss, Andreas; et al. (Journal of the National Cancer Institute, 2014)
Circulating tumor cells (CTCs) have been shown to predict reduced survival outcomes in metastatic breast cancer.CTCs were analyzed in 2026 patients with early breast cancer before adjuvant chemotherapy and in 1492 patients after chemotherapy using the CellSearch System. After immuno-magnetic enrichment for cells expressing the epithelial-cell adhesion molecule, CTCs were defined as nucleated cells expressing cytokeratin and lacking CD45. The patients were followed for a median of 35 months (range = 0-54). Kaplan-Meier analyses and the log-rank test were used for survival analyses. All statistical tests were two-sided.Before chemotherapy, CTCs were detected in 21.5% of patients (n = 435 of 2026), with 19.6% (n = 136 of 692) of node-negative and 22.4% (n = 299 of 1334) of node-positive patients showing CTCs (P < .001). No association was found with tumor size, grading, or hormone receptor status. After chemotherapy, 22.1% of patients (n = 330 of 1493) were CTC positive. The presence of CTCs was associated with poor disease-free survival (DFS; P < .0001), distant DFS (P < .001), breast cancer-specific survival (P = .008), and overall survival (OS; P = .0002). CTCs were confirmed as independent prognostic markers in multivariable analysis for DFS (hazard ratio [HR] = 2.11; 95% confidence interval [CI] = 1.49 to 2.99; P < .0001) and OS (HR = 2.18; 95% CI = 1.32 to 3.59; P = .002). The prognosis was worst in patients with at least five CTCs per 30 mL blood (DFS: HR = 4.51, 95% CI = 2.59 to 7.86; OS: HR = 3.60, 95% CI = 1.56 to 8.45). The presence of persisting CTCs after chemotherapy showed a negative influence on DFS (HR = 1.12; 95% CI = 1.02 to 1.25; P = .02) and on OS (HR = 1.16; 95% CI = 0.99 to 1.37; P = .06) CONCLUSIONS: These results suggest the independent prognostic relevance of CTCs both before and after adjuvant chemotherapy in a large prospective trial of patients with primary breast cancer.
EVALuna2:17454

Clinical and pathological associations of PTEN expression in ovarian cancer: a multicentre study from the Ovarian Tumour Tissue Analysis Consortium - Martins, Filipe Correia; Couturier, Dominique Laurent; Paterson, Anna; Karnezis, Anthony N.; Chow, Christine; Nazeran, Tayyebeh M.; Odunsi, Adekunle; Gentry-Maharaj, Aleksandra; Vrvilo, Aleksandra; Hein, Alexander; Talhouk, Aline; Osorio, Ana; et al. (British Journal of Cancer, 2020)
Background: PTEN loss is a putative driver in histotypes of ovarian cancer (high-grade serous (HGSOC), endometrioid (ENOC), clear cell (CCOC), mucinous (MOC), low-grade serous (LGSOC)). We aimed to characterise PTEN expression as a biomarker in epithelial ovarian cancer in a large population-based study. Methods: Tumours from 5400 patients from a multicentre observational, prospective cohort study of the Ovarian Tumour Tissue Analysis Consortium were used to evaluate associations between immunohistochemical PTEN patterns and overall survival time, age, stage, grade, residual tumour, CD8+ tumour-infiltrating lymphocytes (TIL) counts, expression of oestrogen receptor (ER), progesterone receptor (PR) and androgen receptor (AR) by means of Cox proportional hazard models and generalised Cochran–Mantel–Haenszel tests. Results: Downregulation of cytoplasmic PTEN expression was most frequent in ENOC (most frequently in younger patients; p value = 0.0001) and CCOC and was associated with longer overall survival in HGSOC (hazard ratio: 0.78, 95% CI: 0.65–0.94, p value = 0.022). PTEN expression was associated with ER, PR and AR expression (p values: 0.0008, 0.062 and 0.0002, respectively) in HGSOC and with lower CD8 counts in CCOC (p value < 0.0001). Heterogeneous expression of PTEN was more prevalent in advanced HGSOC (p value = 0.019) and associated with higher CD8 counts (p value = 0.0016). Conclusions: PTEN loss is a frequent driver in ovarian carcinoma associating distinctly with expression of hormonal receptors and CD8+ TIL counts in HGSOC and CCOC histotypes.
CRIS-Team Scopus Importer:2020-06-26

Clinical Characteristics and Prognosis of HER2-0 and HER2-Low-Positive Breast Cancer Patients: Real-World Data from Patients Treated with Neoadjuvant Chemotherapy - Pöschke, Patrik; Fasching, Peter; Adler, Werner; Rübner, Matthias; Beckmann, Matthias; Hack, Carolin; Heindl, Felix; Hartmann, Arndt; Erber, Ramona; Gaß, Paul (Cancers, 2023)
In our study, we observed the long-term survival outcomes investigated for HER2-0 and HER2-low-positive breast cancer patients who received neoadjuvant chemotherapy. Between 1998 and 2020, 10,333 patients with primary breast cancer were treated, including 1373 patients with HER2-0 or HER2-low-positive disease with neoadjuvant chemotherapy. Descriptive analyses were performed, and logistic regression models and survival analyses were calculated for disease-free survival (DFS) and overall survival (OS). Among the 1373 patients, 930 (67.73%) had HER2-low-positive and 443 (32.27%) had HER2-0 tumors. Patients with HER2-0 tumors had a significantly better pathological complete response, 29.25% vs. 20.09%, and pathological complete response/in situ, 31.97% vs. 24.08%, than patients with HER2-low-positive tumors (p < 0.001; p = 0.003), regardless of the hormone receptor (HR) status. No statistically significant differences were observed for the HR-positive (p = 0.315; p = 0.43) or HR-negative subgroups (p = 0.573; p = 0.931). DFS and OS were significantly longer for HR-positive, HER2-low-positive patients (log-rank p = 0.02; p = 0.012). OS was significantly longer for HR-negative, HER2-0 patients (log-rank p = 0.032). No significant DFS differences were found for the HR-negative cohort (log-rank p = 0.232). For the overall cohort, no significant differences were noted between HER2-low-positive and HER2-0 patients, either for DFS (log-rank p = 0.220) or OS (log-rank p = 0.403). These results show different survival outcomes for HER2-0 and HER2-low-positive tumors relative to HR status. These different cohorts can be identified using standardized immunohistochemistry, even retrospectively.
CRIS-Team Scopus Importer:2023-10-20
Keywords: breast cancer; HER2; HER2-0; HER2-low-positive; neoadjuvant therapy; prognosis

Clinical parameters affecting survival outcomes in patients with low-grade serous ovarian carcinoma: An international multicentre analysis - May, Taymaa; Bernardini, Marcus; Lheureux, Stephanie; Aben, Katja K.H.; Bandera, Elisa V.; Beckmann, Matthias; Benitez, Javier; Berchuck, Andrew; Bjørge, Line; Carney, Michael E.; Cramer, Daniel W.; Defazio, Anna; et al. (Canadian Medical Association Journal, 2023)
Background: Women with low-grade ovarian serous carcinoma (LGSC) benefit from surgical treatment; however, the role of chemotherapy is controversial. We examined an international database through the Ovarian Cancer Association Consortium to identify factors that affect survival in LGSC. Methods: We performed a retrospective cohort analysis of patients with LGSC who had had primary surgery and had overall survival data available. We performed univariate and multivariate analyses of progression-free survival and overall survival, and generated Kaplan-Meier survival curves. Results: Of the 707 patients with LGSC, 680 (96.2%) had available overall survival data. The patients' median age overall was 54 years. Of the 659 patients with International Federation of Obstetrics and Gynecology stage data, 156 (23.7%) had stage I disease, 64 (9.7%) had stage II, 395 (59.9%) had stage III, and 44 (6.7%) had stage IV. Of the 377 patients with surgical data, 200 (53.0%) had no visible residual disease. Of the 361 patients with chemotherapy data, 330 (91.4%) received first-line platinum-based chemotherapy. The median follow-up duration was 5.0 years. The median progression-free survival and overall survival were 43.2 months and 110.4 months, respectively. Multivariate analysis indicated a statistically significant impact of stage and residual disease on progression-free survival and overall survival. Platinum-based chemotherapy was not associated with a survival advantage. Conclusion: This multicentre analysis indicates that complete surgical cytoreduction to no visible residual disease has the most impact on improved survival in LGSC. This finding could immediately inform and change practice.
CRIS-Team Scopus Importer:2023-08-11

Clinical validation of genetic variants associated with in vitro chemotherapy-related lymphoblastoid cell toxicity - Fasching, Peter; Häberle, Lothar; Rack, Brigitte; Li, Liang; Hein, Alexander; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, Julie M.; Rübner, Matthias; Jenkins, Gergory; Fridley, Brooke; et al. (Oncotarget, 2017)
Hematotoxicity is one of the major side effects of chemotherapy. The aim of this study was to examine the association between single nucleotide polymorphisms (SNPs) and hematotoxicity in breast cancer patients in a subset of patients of the SUCCESS prospective phase III chemotherapy study. All patients (n = 1678) received three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide (FEC) followed by three cycles of docetaxel or docetaxel/gemcitabine, depending on randomization. Germline DNA was genotyped for 246 SNPs selected from a previous genome-wide association study (GWAS) in a panel of lymphoblastoid cell lines, with gemcitabine toxicity as the phenotype. All SNPs were tested for their value in predicting grade 3 or 4 neutropenic or leukopenic events (NLEs). Their prognostic value in relation to overall survival and disease-free survival was also tested. None of the SNPs was found to be predictive for NLEs during treatment with docetaxel/gemcitabine. Two SNPs in and close to the PIGB gene significantly improved the prediction of NLEs after FEC, in addition to the factors of age and body surface area. The top SNP (rs12050587) had an odds ratio of 1.38 per minor allele (95% confidence interval, 1.17 to 1.62). No associations were identified for predicting disease-free or overall survival. Genetic variance in the PIGB gene may play a role in determining interindividual differences in relation to hematotoxicity after FEC chemotherapy.
EVALuna2:9381

Collective forces of tumor spheroids in three-dimensional biopolymer networks - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
We describe a method for quantifying the contractile forces that tumor spheroids collectively exert on highly nonlinear three-dimensional collagen networks. While three-dimensional traction force microscopy for single cells in a nonlinear matrix is computationally complex due to the variable cell shape, here we exploit the spherical symmetry of tumor spheroids to derive a scale-invariant relationship between spheroid contractility and the surrounding matrix deformations. This relationship allows us to directly translate the magnitude of matrix deformations to the total contractility of arbitrarily sized spheroids. We show that our method is accurate up to strains of 50% and remains valid even for irregularly shaped tissue samples when considering only the deformations in the far field. Finally, we demonstrate that collective forces of tumor spheroids reflect the contractility of individual cells for up to 1 hr after seeding, while collective forces on longer timescales are guided by mechanical feedback from the extracellular matrix.
CRIS-Team WoS Importer:2020-05-22

Combined Associations of a Polygenic Risk Score and Classical Risk Factors With Breast Cancer Risk - Kapoor, Pooja Middha; Mavaddat, Nasim; Choudhury, Parichoy Pal; Wilcox, Amber N.; Lindström, Sara; Behrens, Sabine; Michailidou, Kyriaki; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Jung, Audrey; Abu-Ful, Zomoroda; et al. (Journal of the National Cancer Institute, 2021)
We evaluated the joint associations between a new 313-variant PRS (PRS313) and questionnaire-based breast cancer risk factors for women of European ancestry, using 72 284 cases and 80 354 controls from the Breast Cancer Association Consortium. Interactions were evaluated using standard logistic regression and a newly developed case-only method for breast cancer risk overall and by estrogen receptor status. After accounting for multiple testing, we did not find evidence that per-standard deviation PRS313 odds ratio differed across strata defined by individual risk factors. Goodness-of-fit tests did not reject the assumption of a multiplicative model between PRS313 and each risk factor. Variation in projected absolute lifetime risk of breast cancer associated with classical risk factors was greater for women with higher genetic risk (PRS313 and family history) and, on average, 17.5% higher in the highest vs lowest deciles of genetic risk. These findings have implications for risk prevention for women at increased risk of breast cancer.
CRIS-Team Scopus Importer:2021-03-26

Common Genetic Variation In Cellular Transport Genes and Epithelial Ovarian Cancer (EOC) Risk - Chornokur, Ganna; Lin, Hui-Yi; Tyrer, Jonathan P.; Lawrenson, Kate; Dennis, Joe; Amankwah, Ernest K.; Qu, Xiaotao; Tsai, Ya-Yu; Jim, Heather S. L.; Chen, Zhihua; Chen, Ann Y.; Permuth-Wey, Jennifer; et al. (PLoS ONE, 2015)
Defective cellular transport processes can lead to aberrant accumulation of trace elements, iron, small molecules and hormones in the cell, which in turn may promote the formation of reactive oxygen species, promoting DNA damage and aberrant expression of key regulatory cancer genes. As DNA damage and uncontrolled proliferation are hallmarks of cancer, including epithelial ovarian cancer (EOC), we hypothesized that inherited variation in the cellular transport genes contributes to EOC risk.In total, DNA samples were obtained from 14,525 case subjects with invasive EOC and from 23,447 controls from 43 sites in the Ovarian Cancer Association Consortium (OCAC). Two hundred seventy nine SNPs, representing 131 genes, were genotyped using an Illumina Infinium iSelect BeadChip as part of the Collaborative Oncological Gene-environment Study (COGS). SNP analyses were conducted using unconditional logistic regression under a log-additive model, and the FDR q<0.2 was applied to adjust for multiple comparisons.The most significant evidence of an association for all invasive cancers combined and for the serous subtype was observed for SNP rs17216603 in the iron transporter gene HEPH (invasive: OR = 0.85, P = 0.00026; serous: OR = 0.81, P = 0.00020); this SNP was also associated with the borderline/low malignant potential (LMP) tumors (P = 0.021). Other genes significantly associated with EOC histological subtypes (p<0.05) included the UGT1A (endometrioid), SLC25A45 (mucinous), SLC39A11 (low malignant potential), and SERPINA7 (clear cell carcinoma). In addition, 1785 SNPs in six genes (HEPH, MGST1, SERPINA, SLC25A45, SLC39A11 and UGT1A) were imputed from the 1000 Genomes Project and examined for association with INV EOC in white-European subjects. The most significant imputed SNP was rs117729793 in SLC39A11 (per allele, OR = 2.55, 95% CI = 1.5-4.35, p = 5.66x10-4).These results, generated on a large cohort of women, revealed associations between inherited cellular transport gene variants and risk of EOC histologic subtypes.
EVALuna2:9283

Common germline polymorphisms associated with breast cancer-specific survival - Pirie, Ailith; Guo, Qi; Kraft, Peter; Canisius, Sander; Eccles, Diana M.; Rahman, Nazneen; Nevanlinna, Heli; Chen, Constance; Khan, Sofia; Tyrer, Jonathan; Bolla, Manjeet K.; Wang, Qin; et al. (Breast Cancer Research, 2015)
Previous studies have identified common germline variants nominally associated with breast cancer survival. These associations have not been widely replicated in further studies. The purpose of this study was to evaluate the association of previously reported SNPs with breast cancer-specific survival using data from a pooled analysis of eight breast cancer survival genome-wide association studies (GWAS) from the Breast Cancer Association Consortium.A literature review was conducted of all previously published associations between common germline variants and three survival outcomes: breast cancer-specific survival, overall survival and disease-free survival. All associations that reached the nominal significance level of P value <0.05 were included. Single nucleotide polymorphisms that had been previously reported as nominally associated with at least one survival outcome were evaluated in the pooled analysis of over 37,000 breast cancer cases for association with breast cancer-specific survival. Previous associations were evaluated using a one-sided test based on the reported direction of effect.Fifty-six variants from 45 previous publications were evaluated in the meta-analysis. Fifty-four of these were evaluated in the full set of 37,954 breast cancer cases with 2,900 events and the two additional variants were evaluated in a reduced sample size of 30,000 samples in order to ensure independence from the previously published studies. Five variants reached nominal significance (P <0.05) in the pooled GWAS data compared to 2.8 expected under the null hypothesis. Seven additional variants were associated (P <0.05) with ER-positive disease.Although no variants reached genome-wide significance (P <5 x 10(-8)), these results suggest that there is some evidence of association between candidate common germline variants and breast cancer prognosis. Larger studies from multinational collaborations are necessary to increase the power to detect associations, between common variants and prognosis, at more stringent significance levels.
EVALuna2:9296

Common non-synonymous SNPs associated with breast cancer susceptibility: findings from the Breast Cancer Association Consortium - Milne, Roger L.; Burwinkel, Barbara; Michailidou, Kyriaki; Arias-Perez, Jose-Ignacio; Pilar Zamora, M.; Menendez-Rodriguez, Primitiva; Hardisson, David; Mendiola, Marta; Gonzalez-Neira, Anna; Pita, Guillermo; Rosario Alonso, M.; Dennis, Joe; et al. (Human Molecular Genetics, 2014)
Candidate variant association studies have been largely unsuccessful in identifying common breast cancer susceptibility variants, although most studies have been underpowered to detect associations of a realistic magnitude. We assessed 41 common non-synonymous single-nucleotide polymorphisms (nsSNPs) for which evidence of association with breast cancer risk had been previously reported. Case-control data were combined from 38 studies of white European women (46 450 cases and 42 600 controls) and analyzed using unconditional logistic regression. Strong evidence of association was observed for three nsSNPs: ATXN7-K264R at 3p21 [rs1053338, per allele OR = 1.07, 95% confidence interval (CI) = 1.04-1.10, P = 2.9 × 10(-6)], AKAP9-M463I at 7q21 (rs6964587, OR = 1.05, 95% CI = 1.03-1.07, P = 1.7 × 10(-6)) and NEK10-L513S at 3p24 (rs10510592, OR = 1.10, 95% CI = 1.07-1.12, P = 5.1 × 10(-17)). The first two associations reached genome-wide statistical significance in a combined analysis of available data, including independent data from nine genome-wide association studies (GWASs): for ATXN7-K264R, OR = 1.07 (95% CI = 1.05-1.10, P = 1.0 × 10(-8)); for AKAP9-M463I, OR = 1.05 (95% CI = 1.04-1.07, P = 2.0 × 10(-10)). Further analysis of other common variants in these two regions suggested that intronic SNPs nearby are more strongly associated with disease risk. We have thus identified a novel susceptibility locus at 3p21, and confirmed previous suggestive evidence that rs6964587 at 7q21 is associated with risk. The third locus, rs10510592, is located in an established breast cancer susceptibility region; the association was substantially attenuated after adjustment for the known GWAS hit. Thus, each of the associated nsSNPs is likely to be a marker for another, non-coding, variant causally related to breast cancer risk. Further fine-mapping and functional studies are required to identify the underlying risk-modifying variants and the genes through which they act.
EVALuna2:9242

Common variants at the CHEK2 gene locus and risk of epithelial ovarian cancer - Lawrenson, Kate; Iversen, Edwin S.; Tyrer, Jonathan; Weber, Rachel Palmieri; Concannon, Patrick; Hazelett, Dennis J.; Li, Qiyuan; Marks, Jeffrey R.; Berchuck, Andrew; Lee, Janet M.; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Carcinogenesis, 2015)
Genome-wide association studies have identified 20 genomic regions associated with risk of epithelial ovarian cancer (EOC), but many additional risk variants may exist. Here, we evaluated associations between common genetic variants [single nucleotide polymorphisms (SNPs) and indels] in DNA repair genes and EOC risk. We genotyped 2896 common variants at 143 gene loci in DNA samples from 15 397 patients with invasive EOC and controls. We found evidence of associations with EOC risk for variants at FANCA, EXO1, E2F4, E2F2, CREB5 and CHEK2 genes (P <= 0.001). The strongest risk association was for CHEK2 SNP rs17507066 with serous EOC (P = 4.74 x 10(-7)). Additional genotyping and imputation of genotypes from the 1000 genomes project identified a slightly more significant association for CHEK2 SNP rs6005807 (r (2) with rs17507066 = 0.84, odds ratio (OR) 1.17, 95% CI 1.11-1.24, P = 1.1×10(-7)). We identified 293 variants in the region with likelihood ratios of less than 1:100 for representing the causal variant. Functional annotation identified 25 candidate SNPs that alter transcription factor binding sites within regulatory elements active in EOC precursor tissues. In The Cancer Genome Atlas dataset, CHEK2 gene expression was significantly higher in primary EOCs compared to normal fallopian tube tissues (P = 3.72×10(-8)). We also identified an association between genotypes of the candidate causal SNP rs12166475 (r (2) = 0.99 with rs6005807) and CHEK2 expression (P = 2.70×10(-8)). These data suggest that common variants at 22q12.1 are associated with risk of serous EOC and CHEK2 as a plausible target susceptibility gene.
EVALuna2:9297

Comparison of 6q25 breast cancer hits from Asian and European genome wide association studies in the Breast Cancer Association consortium (BCAC) - Hein, Rebecca; Maranian, Melanie; Hopper, John L.; Kapuscinski, Miroslaw K.; Southey, Melissa C.; Park, Daniel J.; Schmidt, Marjanka K.; Broeks, Annegien; Hogervorst, Frans B. L.; Bueno-De-Mesquit, H. Bas; Muir, Kenneth R.; Lophatananon, Artitaya; et al. (PLoS ONE, 2012)
The 6q25.1 locus was first identified via a genome-wide association study (GWAS) in Chinese women and marked by single nucleotide polymorphism (SNP) rs2046210, approximately 180 Kb upstream of ESR1. There have been conflicting reports about the association of this locus with breast cancer in Europeans, and a GWAS in Europeans identified a different SNP, tagged here by rs12662670. We examined the associations of both SNPs in up to 61,689 cases and 58,822 controls from forty-four studies collaborating in the Breast Cancer Association Consortium, of which four studies were of Asian and 39 of European descent. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI). Case-only analyses were used to compare SNP effects in Estrogen Receptor positive (ER+) versus negative (ER-) tumours. Models including both SNPs were fitted to investigate whether the SNP effects were independent. Both SNPs are significantly associated with breast cancer risk in both ethnic groups. Per-allele ORs are higher in Asian than in European studies [rs2046210: OR (A/G) = 1.36 (95% CI 1.26-1.48), p = 7.6×10-14 in Asians and 1.09 (95% CI 1.07-1.11), p = 6.8×10-18 in Europeans. rs12662670: OR (G/T) = 1.29 (95% CI 1.19-1.41), p = 1.2×10-9 in Asians and 1.12 (95% CI 1.08-1.17), p = 3.8×10-9 in Europeans]. SNP rs2046210 is associated with a significantly greater risk of ER- than ER+ tumours in Europeans [OR (ER-) = 1.20 (95% CI 1.15-1.25), p = 1.8×10-17 versus OR (ER+) = 1.07 (95% CI 1.04-1.1), p = 1.3×10-7, pheterogeneity = 5.1×10-6]. In these Asian studies, by contrast, there is no clear evidence of a differential association by tumour receptor status. Each SNP is associated with risk after adjustment for the other SNP. These results suggest the presence of two variants at 6q25.1 each independently associated with breast cancer risk in Asians and in Europeans. Of these two, the one tagged by rs2046210 is associated with a greater risk of ER- tumours. © 2012 Hein et al.
CRIS-Team Scopus Importer:2021-07-19

Comparison of C-Reactive Protein in Dried Blood Spots and Saliva of Healthy Adolescents - Plank, Anne-Christine; Maschke, Janina; Rohleder, Nicolas; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Eichler, Anna; Moll, Gunther; Kratz, Oliver (Frontiers in Immunology, 2021)
Background/AimDetermining C-reactive protein (CRP) by non-invasive methods is of great interest for research addressing inflammation in young people. However, direct comparisons of such methods applied in children and adolescents are lacking so far. This study aimed to evaluate the association between CRP measured in dried blood spots (DBS CRP) and in saliva (sCRP), two less invasive alternatives to venipuncture, in 12- to 14-year-old adolescents. To evaluate the validity of both measurements in the context of biobehavioral studies, the potential of DBS CRP and sCRP to discriminate between defined BMI subgroups was assessed. Materials and MethodsCRP levels in DBS and saliva collected from 87 healthy adolescents (M = 13.25 years, SD = 0.30, 51.7% females) were determined using high sensitive CRP ELISA for serum and salivary CRP ELISA, respectively. Characteristics and correlation of both measurements were assessed for the total sample and for three subgroups classified by BMI percentile ranges (A: <= 25; B: 26-74; C: >= 75). ResultsIn the total sample, DBS CRP and sCRP were significantly associated (r = 0.59, p < 0.001). Splitting the sample into BMI-dependent subgroups revealed similarly strong associations of DBS CRP with sCRP for all three groups (A: r = 0.51; B: r = 0.61; C: r = 0.53). However, comparing the mean CRP values per BMI subgroup, one-way ANOVA reported significant differences for DBS CRP, but not for sCRP mean values. ConclusionsThe significant correlation of DBS CRP with sCRP was independent of the investigated BMI range groups, yet BMI-dependent distinction was only provided by DBS CRP mean values. Overall, our results suggest that DBS CRP is likely to reflect systemic inflammation more precisely. Salivary CRP can be alternatively determined in studies with adolescents when conditions require it, given the oral health status is assessed. Considering that DBS CRP and sCRP share only 35% of common variance, further studies should examine their specific validity.
CRIS-Team WoS Importer:2022-01-14

Comparison of dienogest and progesterone effects on uterine contractility in the extracorporeal perfusion model of swine uteri - Oppelt, Patricia; Weber, Meike; Mueller, Andreas; Boosz, Alexander; Hoffmann, Inge; Raffel, Nathalie; Lotz, Laura; Beckmann, Matthias; Dittrich, Ralf (Acta Obstetricia Et Gynecologica Scandinavica, 2018)
INTRODUCTION: Endometriosis is associated with hyperperistalsis and dysperistalsis in the uterus, and it has been shown that progesterone leads to a decrease in uterine contractility. The synthetic gestagen dienogest is often administered in women who are receiving conservative treatment for endometriosis, and it may be the treatment of choice. The present study investigated the effects of dienogest on uterine contractility in comparison with the known inhibitory effect of progesterone. MATERIAL AND METHODS: Eighty swine uteri were examined using an established extracorporeal perfusion model. The uteri were perfused for at least 4 hours with progesterone, dienogest, or a modified Krebs-Ringer solution as the control group, with uterine contractions being measured using an intrauterine microchip catheter. The amplitude and frequency of contractions and the area under the curve (AUC), reflecting overall contractility, were measured at two separate locations (the isthmus and fundus). RESULTS: Progesterone led to a significant decrease in the amplitude of uterine contractions and to reduced overall pressure (AUC) at the isthmus and fundus. Dienogest led to a significant decrease in the amplitude of contractions and overall pressure (AUC) in the area of the isthmus, but the decrease near the fundus was not significant. The frequency of uterine contractions was not influenced by either progesterone or dienogest. CONCLUSIONS: These results confirm the known inhibitory effect of progesterone on uterine contractility (relative to amplitude of contractions and overall contractility), affecting the whole organ. Perfusion of the uterus with dienogest also led to a general decrease in uterine contractility similar to the effect of progesterone.
EVALuna2:209948

Comparison of methods for isolation and quantification of circulating cell-free DNA from patients with endometriosis - Hübner, Hanna; Lubrich, Hannah; Blum, Simon; Antoniadis, Sophia; Lermann, Johannes; Ekici, Arif Bülent; Fasching, Peter; Beckmann, Matthias; Rübner, Matthias; Burghaus, Stefanie (Reproductive Biomedicine Online, 2021)
Research question: Which is the optimal extraction method for isolating and quantifying circulating cell-free DNA (ccfDNA) from patients with endometriosis? Endometriosis is a common benign disease, associated with pain, infertility and reduced quality of life. Endometriosis is also a known risk factor for various cancers. Robust biomarkers for early detection and prediction of prognosis, however, are lacking. CcfDNA is an easy to obtain biomarker associated with prognosis of cancer patients and enables non-invasive analysis of somatic mutations. Recently, elevated levels of ccfDNA were detected in patients with endometriosis. Design: Two different ccfDNA extraction methods were compared: Maxwell RSC ccfDNA plasma kit (Maxwell) and QiAamp minElute ccfDNA mini kit (QIAamp). The ccfDNA and circulating mitochondrial DNA (mtDNA) quantities from 34 patients diagnosed with endometriosis were analysed. Fluorometric measurement and quantitative reverse transcription polymerase chain reaction (qRT-PCR) of short and long ALU and mtDNA fragments were used to quantiy ccfDNA. Results: The yield of ccfDNA isolated with the Maxwell method was significantly higher compared with the QIAamp method (P < 0.0001). Integrity of ccfDNA was significantly higher in the QIAamp isolate (P < 0.0001). Recovered mtDNA was not significantly different between both extraction methods used. Conclusions: The choice of extraction method can significantly influence the ccfDNA output and integrity. Both methods, however, enabled isolation of sufficient ccfDNA for further downstream applications. With this approach, isolation of ccfDNA could enable the non-invasive detection and analysis of somatic mutation within endometriosis tissue.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CcfDNA; Circulating cell-free DNA; Endometriosis; Mitochondrial DNA; Plasma; Quantification

Comparison of Obstetric Efficacy and Safety of the Kiwi OmniCup with Conventional Vacuum Extraction - Siggelkow, W.; Schwarz, N.; Beckmann, Matthias; Kehl, Sven; Faschingbauer, Florian; Schild, R. L. (Geburtshilfe und Frauenheilkunde, 2014)
Purpose: The aim of the present study was to compare the safety and efficacy of the Kiwi OmniCup system with conventional vacuum delivery. Methods: A retrospective study of operative vaginal deliveries was done for 4682 births. The procedures included 217 operative vaginal deliveries (4.6 %), 79 of which were done using conventional vacuum extraction (37 %) and 138 using the Kiwi system (63 %). Results: Use of the Kiwi system was associated with a significant reduction in episiotomies (61 vs. 76 % in the control group; p < 0.05). The rates of successful completion of birth were comparable for the two systems (94 % with the Kiwi system and 99 % with conventional vacuum delivery). Cup detachment occurred significantly more often in the Kiwi group (p < 0.005), requiring a change to a different method of birth significantly more often. It was necessary to change the procedure significantly more often from the mid-pelvis (p < 0.05). The incidence of maternal and foetal injuries was similar for the two systems. Conclusions: With regard to obstetric efficacy and safety and foetal and maternal injuries, the Kiwi system is an acceptable alternative to the conventional vacuum cup. The advantages of the Kiwi system are its significantly lower episiotomy rate and its ease and rapidity of use.
EVALuna2:17446

Comparison of oocyte quality in IVF/ICSI cycles between patients with histologically proven endometriosis and patients where endometriosis has been excluded by laparoscopy - Dittrich, Ralf; Hoffmann, Inge; Beckmann, Matthias; Lotz, Laura (2017)
EVALuna2:36132

Comparison of preoperative and postoperative sexual function in patients with deeply infiltrating endometriosis with and without bowel resection - Lermann, Johannes; Topal, Nalan; Renner, Stefan P.; Beckmann, Matthias; Burghaus, Stefanie; Adler, Werner; Heindl, Felix (European Journal of Obstetrics Gynecology and Reproductive Biology, 2019)
Objective: To analyze preoperative and postoperative sexual function following surgery for deeply infiltrating endometriosis (DIE)with and without bowel involvement. Study design: Patients with DIE who underwent surgery between 2001 and 2011 with segmental bowel resection (WB)or without segmental bowel resection (WOB)were surveyed using the German version of the Massachusetts General Hospital Sexual Functioning Questionnaire (KFSP). Responses were given on a six-point scale for the items sexual interest, sexual arousal, orgasm, lubrication, and general sexual satisfaction. As there are no cut-off values for the existence of sexual function disorders, a control group with no history of endometriosis was evaluated. Differences between the preoperative and postoperative results, as well as between WB, WOB, and a control group, were compared using the Wilcoxon test, Mann–Whitney U test, and Fisher's exact test. Results: Eighty-nine patients without bowel resection (mean age 34.3 years; mean follow-up 63.2 months), 87 patients with bowel resection (mean age 37.7 years; mean follow-up 69.6 months), and 100 control patients aged 21–58 years (mean age 35.0 years)were evaluated. Preoperatively, both treatment groups had significantly poorer scores in all categories in comparison with the control group. The WOB group improved significantly in all categories postoperatively, with no further significant differences from the control group. No significant postoperative improvement was observed in the WB group, and the group had significantly poorer scores in comparison with the control group. The number of previous operations is associated with significantly poorer postoperative KFSP results. Sterility and age > 40 years are associated with significantly less improvement in the KFSP, although with lower initial values. Conclusions: Patients with DIE with or without bowel involvement have significantly impaired sexual function preoperatively. Complete resection of endometriosis in the WOB group was able to improve sexual function, as the women had sexual scores similar to those in the healthy control group postoperatively. Possible explanations for the lack of postoperative improvement of sexual function after segmental bowel resection include the type of surgery carried out, or injury to the affected nerves resulting from the endometriosis.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Deeply infiltrating endometriosis; Lubrication; Massachusetts General Hospital Sexual Functioning Questionnaire; Rectovaginal septum; Sexual function; Sexual satisfaction

Comparison of reoperation rates, perioperative outcomes in women with endometrial cancer when the standard of care shifts from open surgery to laparoscopy - Boosz, Alexander; Häberle, Lothar; Renner, Stefan; Thiel, Falk; Mehlhorn, Grit; Beckmann, Matthias; Mueller, Andreas (Archives of Gynecology and Obstetrics, 2014)
To analyze reoperation rates and perioperative outcomes after long-term follow-up of two surgical approaches in the treatment of endometrial cancer when the standard of care shifts from open surgery to laparoscopy at a university hospital.In this retrospective monocenter study a total of 267 patients with endometrial cancer were included; 107 women underwent laparoscopy and 160 laparotomy. All of the patients received total hysterectomy, bilateral salpingo-oophorectomy, and pelvic and para-aortic lymphadenectomy, depending on individual pathological features (e.g. high risk for positive lymph nodes) and the expertise of the surgeon.Repeat surgery was needed significantly more often in the laparotomy group in comparison with the laparoscopy group (11.9 vs. 0.9 %, respectively; P < 0.001). Hospital stays were longer in the laparotomy group in comparison with laparoscopy (16.2 vs. 9.5 days; P < 0.000001). Postoperative complications were significantly more frequent in the laparotomy group in comparison with laparoscopy (25.0 vs. 10.3 %; P < 0.01). Operating times and preoperative and postoperative hemoglobin differences were similar in the two groups (193.9 vs. 190.6 min, 2.0 vs. 1.8 g/dl). Intraoperative complication rates were similar in the two groups (3.8 vs. 5.6 %).Laparoscopy is a safe alternative to laparotomy for low risk endometrial cancer patients and offers markedly improved perioperative outcomes with a lower reoperation rate and fewer postoperative complications when the standard of care shifts from open surgery to laparoscopy in a university hospital.
EVALuna2:17458

Comparison of Sonography versus Digital Breast Tomosynthesis to Locate Intramammary Marker Clips - Schulz-Wendtland, Rüdiger; Dankerl, Peter; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Jud, Sebastian; Rauh, C.; Bayer, C. M.; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: This study aimed to compare the accuracy of sonography versus digital breast tomosynthesis to locate intramammary marker clips placed under ultrasound guidance. Patients and Methods: Fifty patients with suspicion of breast cancer (lesion diameter less than 2 cm [cT1]) had ultrasound-guided core needle biopsy with placement of a marker clip in the center of the tumor. Intramammary marker clips were subsequently located with both sonography and digital breast tomosynthesis. Results: Sonography detected no dislocation of intrammammary marker clips in 42 of 50 patients (84 %); dislocation was reported in 8 patients (16 %) with a maximum dislocation of 7 mm along the x-, y- or z-axis. Digital breast tomosynthesis showed accurate placement without dislocation of the intramammary marker clip in 48 patients (96 %); 2 patients (4 %) had a maximum clip dislocation of 3 mm along the x-, y- or z-axis (p < 0.05). Conclusion: The use of digital breast tomosynthesis could improve the accuracy when locating intramammary marker clips compared to sonography and could, in future, be used to complement or even completely replace sonography.
EVALuna2:6724

Comparison of Whole Ovary Cryotreatments for Fertility Preservation - Lotz, Laura; Hauenstein, Tanja; Nichols-Burns, S. M.; Strissel, Pamela; Hoffmann, I.; Findeklee, S.; Dittrich, Ralf; Beckmann, Matthias; Oppelt, Patricia (Reproduction in Domestic Animals, 2015)
The goal of this study was to compare a traditional slow-freeze method (TF) with an open unidirectional slow freeze cooling system (UF) for whole ovary cryopreservation. Therefore, whole pig ovaries were randomly assigned to (A) fresh control, (B) traditional slow freeze (TF) or (C) unidirectional slow freeze (UF). Ovaries were perfused with 10% DMSO in Krebs-Ringer. For TF, whole ovaries were placed in specimen jars containing 10% DMSO and placed into a specialized container for freezing filled with propan-2-ol. For UF, whole ovaries were placed within a specially designed container containing 10% DMSO and transferred to a specialized freezing machine (CTE 920). Histological evaluation demonstrated intact morphology of follicles in all groups; however, an overall decrease of follicle numbers in TF (46%) and UF (50%) compared to fresh control. Live/dead assay indicated significantly lower populations of live cells in both TF (60%) and UF (58%) compared to fresh tissue (74%). TUNEL assay confirmed a difference in percentage of apoptotic follicles between fresh and TF, but there was no significant difference between fresh and UF. To improve the structural and functional integrity of whole ovaries, further investigation, especially into directional freezing, is needed. Whole ovary cryopreservation could provide opportunities for women facing fertility loss due to chemo- or radiotherapy treatment.
EVALuna2:17545

Complementary and alternative medicine and musculoskeletal pain in the first year of adjuvant aromatase inhibitor treatment in early breast cancer patients - Hack, Caroline; Häberle, Lothar; Brucker, S. Y.; Janni, W.; Volz, B.; Löhberg, Christian; Hartkopf, A. D.; Walter, C. B.; Baake, G.; Fridman, A.; Malter, W.; Wuerstlein, R.; et al. (BREAST, 2020)
Background: Patients with breast cancer (BC) show strong interest in complementary and alternative medicine (CAM), particularly for adverse effects of adjuvant endocrine treatment — e.g., with letrozole. Letrozole often induces myalgia/limb pain and arthralgia, with potential noncompliance and treatment termination. This analysis investigated whether CAM before aromatase inhibitor (AI) therapy is associated with pain development and the intensity of AI-induced musculoskeletal syndrome (AIMSS) during the first year of treatment. Patients and methods: The multicenter phase IV PreFace study evaluated letrozole therapy in postmenopausal, hormone receptor–positive patients with early BC. Patients were asked about CAM use before, 6 months after, and 12 months after treatment started. They recorded pain every month for 1 year in a diary including questions about pain and numeric pain rating scales. Data were analyzed for patients who provided pain information for all time points. Results: Of 1396 patients included, 901 (64.5%) had used CAM before AI treatment. Throughout the observation period, patients with CAM before AI treatment had higher pain values, for both myalgia/limb pain and arthralgia, than non-users. Pain increased significantly in both groups over time, with the largest increase during the first 6 months. No significant difference of pain increase was noted regarding CAM use. Conclusions: CAM use does not prevent or improve the development of AIMSS. Pain intensity was generally greater in the CAM group. Therefore, because of the risk of non-compliance and treatment discontinuation due to the development of higher pain levels, special attention must be paid to patient education and aftercare in these patients.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Aromatase inhibitors; Arthralgia; Breast cancer; Complementary and alternative medicine; Endocrine therapy/treatment; Integrative medicine; Letrozole; Myalgia

Complementary and alternative medicine (CAM) in women with endometriosis - Adamietz, Alexandra; Boosz, Alexander; Mueller, Andreas; Hornung, Daniela; Trunk, Katharina; Beckmann, Matthias; Dittrich, Ralf; Hack, Carolin (European Journal of Obstetrics Gynecology and Reproductive Biology, 2021)
Objective: This study aimed to provide an overview of the extent to which women with endometriosis are informed about, interested in, and make use of CAM, and to evaluate which of the methods are most often applied. Study Design: A retrospective, two-center cohort study was conducted using a validated questionnaire among women with laparoscopically confirmed endometriosis at two urban teaching hospitals, certified as endometriosis centres. Results: A total of 592 patients were included in the study and received the questionnaire; 114 (19.3 %) were included in the data analysis. Most of the women were not receiving hormone therapy at the time of the study (n = 60, 52.6 %). Most (n = 75, 65.8 %) were interested in CAM, but only a minority (n = 12, 10.5 %) had detailed knowledge about it. A total of 81 patients (71.1 %) had used at least one CAM method for disease management; the five most frequently used CAM methods were exercise (n = 55, 48.2 %), vitamins (n = 40, 35.1 %), yoga (n = 38, 33.3 %), homeopathy (n = 32, 28.1 %), and trace elements (n = 27, 23.7 %). Conclusions: In our study population, women with endometriosis are strongly interested in using CAM, but have only limited information about it. Nevertheless, a majority of the patients had used at least one CAM method to relieve symptoms associated with the disease and the most often used was exercise.
CRIS-Team Scopus Importer:2021-05-21
Keywords: CAM; Complementary and alternative medicine; Endometriosis

Comprehensive characterization of endometriosis patients and disease patterns in a large clinical cohort - Blum, Simon; Fasching, Peter; Hildebrandt, Thomas; Lermann, Johannes; Heindl, Felix; Born, Tilman; Lubrich, Hannah; Antoniadis, Sophia; Becker, Karina; Fahlbusch, Christine; Heusinger, Katharina; Burghaus, Stefanie; et al. (Archives of Gynecology and Obstetrics, 2021)
Purpose In many diseases, it is possible to classify a heterogeneous group into subgroups relative to tumor biology, genetic variations, or clinical and pathological features. No such classification is available for endometriosis. In our retrospective case-case analysis we defined subgroups of endometriosis patients relative to the type and location of the endometriosis lesion and relative to basic patient characteristics. Methods From June 2013 to July 2017, a total of 1576 patients with endometriosis diagnosed at surgery were included in this study. The patients' history and clinical data were documented using a web-based remote data entry system. To build subgroups, all possible combinations of endometriosis locations/types (peritoneal; ovarian endometriosis; deeply infiltrating endometriosis; adenomyosis) were used. Due to the variation in group sizes, they were combined into five substantial larger groups. Results Age, pregnancy rate, and live birth rate were identified as characteristics that significantly differed between the five patient groups that were defined. No significant differences were noted in relation to body mass index, length of menstrual cycle, age at menarche, reason for presentation, or educational level. Conclusion This study describes basic patient characteristics in relation to common clinical subgroups in a large clinical cohort of endometriosis patients. Epidemiological information about different clinical groups may be helpful in identifying groups with specific clinical courses, potentially suggesting novel approaches to early detection and to surgical and systemic treatment.
CRIS-Team WoS Importer:2021-09-10

Comprehensive genetic assessment of the ESR1 locus identifies a risk region for endometrial cancer - O'Mara, Tracy A.; Glubb, Dylan M.; Painter, Jodie N.; Cheng, Timothy; Dennis, Joe; Attia, John; Holliday, Elizabeth G.; Mcevoy, Mark; Scott, Rodney J.; Ashton, Katie; Proietto, Tony; Otton, Geoffrey; et al. (Endocrine-Related Cancer, 2015)
Excessive exposure to estrogen is a well-established risk factor for endometrial cancer (EC), particularly for cancers of endometrioid histology. The physiological function of estrogen is primarily mediated by estrogen receptor alpha, encoded by ESR1. Consequently, several studies have investigated whether variation at the ESR1 locus is associated with risk of EC, with conflicting results. We performed comprehensive fine-mapping analyses of 3633 genotyped and imputed single nucleotide polymorphisms (SNPs) in 6607 EC cases and 37 925 controls. There was evidence of an EC risk signal located at a potential alternative promoter of the ESR1 gene (lead SNP rs79575945, P=1.86×10(-5)), which was stronger for cancers of endometrioid subtype (P=3.76×10(-6)). Bioinformatic analysis suggests that this risk signal is in a functionally important region targeting ESR1, and eQTL analysis found that rs79575945 was associated with expression of SYNE1, a neighbouring gene. In summary, we have identified a single EC risk signal located at ESR1, at study-wide significance. Given SNPs located at this locus have been associated with risk for breast cancer, also a hormonally driven cancer, this study adds weight to the rationale for performing informed candidate fine-scale genetic studies across cancer types.
EVALuna2:9261

Comprehensive visualization of paresthesia in breast cancer survivors - Jud, Sebastian; Hatko, Reinhard; Maihoefner, Christian; Bani, Mayada; Schrauder, Michael G.; Lux, Michael P.; Beckmann, Matthias; Bani, Gassan; Eder, Irina; Fasching, Peter; Löhberg, Christian; Rauh, Claudia; et al. (Archives of Gynecology and Obstetrics, 2014)
As breast cancer survivors are benefiting increasingly from advanced forms of therapy, the side effects of locoregional treatment in the adjuvant setting are becoming more and more important. This article presents a new method of assessing the spatial distribution of paresthesia in breast cancer survivors after different locoregional treatments.A structured questionnaire assessing paresthesia, with body pictograms for marking paresthesia areas, was completed by 343 breast cancer survivors. The image information was digitized, generating gray-scale summation images with numbers from 0, indicating black (100 % of the patients had paresthesia), to 255, indicating white (none had paresthesia). The resulting map visualization showed the locations of paresthesia on body pictograms. The group included patients who had undergone breast-conserving surgery (BCS) and mastectomy, and also patients who had received percutaneous and interstitial radiation.A total of 56.5 % of the patients stated that they had paresthesia. The paresthesia areas were distributed within the range suggested by clinical experience. Most patients stated that they had paresthesia in the upper outer quadrant and axilla. Patients who had undergone mastectomy or percutaneous radiotherapy appeared to have more paresthesia on some areas of the body surface. Patients who had undergone mastectomy indicated larger areas of paresthesia than those with BCS-4,066 pixels (px) vs. 2,275 px. Radiotherapy did not appear to influence the spatial distribution of paresthesia.Paresthesia is a common symptom after breast cancer treatment. This paper describes a new method of assessing this side effect to improve and individualize treatment for it in the future.
EVALuna2:17450

Computerized patient identification for the EMBRACA clinical trial using real-time data from the PRAEGNANT network for metastatic breast cancer patients - Hein, Alexander; Gaß, Paul; Walter, Christina Barbara; Taran, Florin-Andrei; Hartkopf, Andreas; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Wuerstlein, Rachel; Lounsbury, Debra; et al. (Breast Cancer Research and Treatment, 2016)
EVALuna2:154
Keywords: BRCA1; BRCA2; Breast cancer; Clinical trial eligibility; PARP inhibitors; Talazoparib

Concentrations of N epsilon-Carboxymethyllysine in Human Breast Milk, Infant Formulas, and Urine of Infants - Dittrich, Ralf; Hoffmann, Inge; Stahl, Peter; Müller, Andreas; Beckmann, Matthias; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2006)
Maillard products, such as Nε-carboxymethyllysine (CML), are readily formed during the manufacturing of infant formulas. Little has been known, however, about the presence of CML in human breast milk and about the uptake of CML by infants. In this study, CML was measured in the serum and breast milk of 32 healthy mothers by ELISA. CML concentrations in breast milk (137 ± 82.7 ng/mL) were significantly lower than in the serum (399 ± 67.8 ng/mL, p < 0.001) and on average 35-fold lower than in infant formulas (4754 ± 4299.5 ng/mL). CML was also measured in the urine of 21 infants, which were fed with breast milk or formulas. Although there was a tendency toward higher urinary CML excretion in infants fed with hypoallergenic formulas compared to breast-fed ones, the differences were not significant. Neonates that were delivered by vaginal birth had significantly higher concentrations of CML compared to those delivered by caesarean section (1306 ± 653 vs 601 ± 220 ng/mL, p = 0.012). It is conclued that CML passes from the serum into the breast milk, but the levels are by far lower than in infant formulas. In very young neonates (≤3 days), the mode of delivery has a greater influence on urinary CML excretion than the nutrition. © 2006 American Chemical Society.
UnivIS-Import:2015-04-14:Pub.2006.nat.dchph.llmch.concen
Keywords: Advanced glycation end-products; Breast milk; Infant formulas; Maillard products; N; Newborn; Urine

Concept paper on the technique of cryopreservation, removal and transplantation of ovarian tissue for fertility preservation - Beckmann, Matthias; Lotz, Laura; Toth, Bettina; Baston-Buest, Dunja Maria; Fehm, Tanja; Frambach, Torsten; Germeyer, Ariane; Goeckenjan, Maren; Haeberlin, Felix; Henes, Melanie; Hirchenhain, Jens; Huebner, Stephanie; et al. (Geburtshilfe und Frauenheilkunde, 2019)
The cryopreservation of ovarian tissue with subsequent transplantation of the tissue represents an established method of fertility protection for female patients who have to undergo gonadotoxic therapy. The procedure can be performed at any point in the cycle and thus generally does not lead to any delay in oncological therapy. With the aid of this procedure, more than 130 births to date worldwide have been able to be recorded. The birth rate is currently approximately 30% and it can be assumed that this will increase through the further optimisation of the cryopreservation and surgical technique. The concept paper presented here is intended to provide guidance for managing cryopreservation and transplantation of ovarian tissue to German-speaking reproductive medicine centres.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Cryopreservation; Fertility protection; FertiPROTEKT; Ovarian tissue; Transplantation

Concordance Rate of Colposcopy in Detecting Cervical Intraepithelial Lesions - Stübs, Frederik; Dietl, Anna; Behrens, Annika; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul; Koch, Martin C. (Diagnostics, 2022)
Background: The purpose of this research is to estimate the rate of concordance, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of colposcopy for high-grade squamous lesions and carcinomas (HSIL+). Methods: We conducted a retrospective study of colposcopies performed in the certified Dysplasia Unit in Erlangen between January 2015 and May 2022 (7.5 years). The colposcopic findings were correlated with biopsies obtained during examinations or surgery. Cases without histology were excluded. The primary outcome was the rate of concordance between the colposcopic and histological findings in relation to the type of transformation zone (TZ), examiner's level of experience and age of the patients. Results: A total of 4778 colposcopies in 4001 women were analyzed. The rates of concordance for CIN I/LSIL, CIN II/HSIL, CIN III/HSIL, and carcinoma were 43.4%, 59.5%, 78.5%, and 53.9%, respectively. The rate of concordance was lowest for TZ3 and highest for colposcopists with more than 10 years' experience. Conclusions: Colposcopy is an important, feasible, and effective method. Careful work-up needs to be performed for women with TZ3 who are over 35 years old, as they are at the highest risk of being misdiagnosed. The highest concordance for detecting HSIL+ was seen for colposcopists with >10 years' experience.
CRIS-Team WoS Importer:2022-11-11

Concordance rate of vulvoscopic findings in detecting early vulvar neoplasia - Stuebs, Frederik A.; Mehlhorn, Grit; Gaß, Paul; Schulmeyer, Carla; Adler, Werner; Strehl, Johanna; Hartmann, Arndt; Beckmann, Matthias; Renner, Stefan; Koch, Martin (Gynecologic Oncology, 2020)
Purpose: Colposcopy-guided punch biopsy is a cornerstone method for diagnosing vulvar diseases. The aim of this study was to evaluate the concordance rate of clinical findings in vulvar diseases during examinations, in comparison with colposcopy-directed punch biopsy. We also developed a new classification to simplify the categorization of vulvoscopic findings. Methods: The concordance rate of the clinical findings was compared with the final histology results from punch biopsies. The data were collected between January 2014 and May 2017 at the Erlangen University Hospital. Results: A total of 482 colposcopy-directed punch biopsies of the vulva were obtained in 420 women. The overall concordance rate of the clinical findings in comparison with the histological vulvar punch-biopsy findings was 53.9% for all entities — benign lesions, lichen, low- and high-grade squamous intraepithelial lesions (LSIL/HSILs), and vulvar carcinoma. The concordance rate for detecting LSILs was 64.3% (45/70). The concordance rate for detecting HSILs was 62.3% and for Vulvar carcinoma 65.2%. Conclusions: Punch biopsy of suspicious lesions continues to be a cornerstone in diagnosing HSILs and carcinoma of the vulva. Careful work-up of the vulva is recommended when patients have symptoms such as pruritus or pain. The new classification is more specific for diagnosing lesions in the vulva.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Colposcopy-directed punch biopsy; High-grade squamous intraepithelial lesion (HSIL); Vulvar cancer; Vulvar intraepithelial neoplasia (VIN)

Considerations on the Improved Integration of Medical Guidelines into Routine Clinical Practice - a Review and Concept Proposal - Beckmann, Matthias; Schlieter, H.; Richter, P.; Wesselmann, S. (Geburtshilfe und Frauenheilkunde, 2016)
Medical guidelines have become established as the standard for the comprehensive synopsis of all available information (scientific trials, expert opinion) on diagnosis and treatment recommendations. The transfer of guidelines to clinical practice and subsequent monitoring has however proven difficult. In particular the potential interaction between guideline developers and guideline users has not been fully utilised. This review article analyses the status quo and existing methodological and technical information solutions supporting the guideline life cycle. It is shown that there are numerous innovative developments that in isolation do not provide comprehensive support. The vision of the "Living Guidelines 2.0" is therefore presented. This outlines the merging of guideline development and implementation on the basis of clinical pathways and guideline-based quality control, and building on this, the generation of information for guideline development and research.
EVALuna2:32985

Consortium analysis of gene and gene-folate interactions in purine and pyrimidine metabolism pathways with ovarian carcinoma risk - Kelemen, Linda E.; Terry, Kathryn L.; Goodman, Marc T.; Webb, Penelope M.; Bandera, Elisa V.; Mcguire, Valerie; Rossing, Mary Anne; Wang, Qinggang; Dicks, Ed; Tyrer, Jonathan P.; Song, Honglin; Kupryjanczyk, Jolanta; et al. (Molecular Nutrition & Food Research, 2014)
We reevaluated previously reported associations between variants in pathways of one-carbon (1-C) (folate) transfer genes and ovarian carcinoma (OC) risk, and in related pathways of purine and pyrimidine metabolism, and assessed interactions with folate intake.Odds ratios (OR) for 446 genetic variants were estimated among 13,410 OC cases and 22,635 controls, and among 2281 cases and 3444 controls with folate information. Following multiple testing correction, the most significant main effect associations were for dihydropyrimidine dehydrogenase (DPYD) variants rs11587873 (OR = 0.92; p = 6 × 10(-5)) and rs828054 (OR = 1.06; p = 1 × 10(-4)). Thirteen variants in the pyrimidine metabolism genes, DPYD, DPYS, PPAT, and TYMS, also interacted significantly with folate in a multivariant analysis (corrected p = 9.9 × 10(-6)) but collectively explained only 0.2% of OC risk. Although no other associations were significant after multiple testing correction, variants in SHMT1 in 1-C transfer, previously reported with OC, suggested lower risk at higher folate (p(interaction) = 0.03-0.006).Variation in pyrimidine metabolism genes, particularly DPYD, which was previously reported to be associated with OC, may influence risk; however, stratification by folate intake is unlikely to modify disease risk appreciably in these women. SHMT1 SNP-by-folate interactions are plausible but require further validation. Polymorphisms in selected genes in purine metabolism were not associated with OC.
EVALuna2:9231

Copy Number Variants Are Ovarian Cancer Risk Alleles at Known and Novel Risk Loci - Devries, Amber A.; Dennis, Joe; Tyrer, Jonathan P.; Peng, Pei-Chen; Coetzee, Simon G.; Reyes, Alberto L.; Plummer, Jasmine T.; Davis, Brian D.; Chen, Stephanie S.; Dezem, Felipe Segato; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Journal of the National Cancer Institute, 2022)
Background Known risk alleles for epithelial ovarian cancer (EOC) account for approximately 40% of the heritability for EOC. Copy number variants (CNVs) have not been investigated as EOC risk alleles in a large population cohort. Methods Single nucleotide polymorphism array data from 13 071 EOC cases and 17 306 controls of White European ancestry were used to identify CNVs associated with EOC risk using a rare admixture maximum likelihood test for gene burden and a by-probe ratio test. We performed enrichment analysis of CNVs at known EOC risk loci and functional biofeatures in ovarian cancer-related cell types. Results We identified statistically significant risk associations with CNVs at known EOC risk genes; BRCA1 (P-EOC = 1.60E-21; OREOC = 8.24), RAD51C (Phigh-grade serous ovarian cancer [HGSOC] = 5.5E-4; odds ratio [OR](HGSOC) = 5.74 del), and BRCA2 (P-HGSOC = 7.0E-4; ORHGSOC = 3.31 deletion). Four suggestive associations (P < .001) were identified for rare CNVs. Risk-associated CNVs were enriched (P < .05) at known EOC risk loci identified by genome-wide association study. Noncoding CNVs were enriched in active promoters and insulators in EOC-related cell types. Conclusions CNVs in BRCA1 have been previously reported in smaller studies, but their observed frequency in this large population-based cohort, along with the CNVs observed at BRCA2 and RAD51C gene loci in EOC cases, suggests that these CNVs are potentially pathogenic and may contribute to the spectrum of disease-causing mutations in these genes. CNVs are likely to occur in a wider set of susceptibility regions, with potential implications for clinical genetic testing and disease prevention.
CRIS-Team WoS Importer:2022-10-21

Correction: Collective forces of tumor spheroids in three-dimensional biopolymer networks. - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
EVALuna2:417751

Correction to: Breast cancer patients' satisfaction with individual therapy goals and treatment in a standardized integrative medicine consultancy service - Hack, Carolin; Antoniadis, Sophia; Hackl, Janina; Langemann, Hanna; Schwitulla, Judith; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Archives of Gynecology and Obstetrics, 2018)
In the original version of this article contained an error in figure 1. It was provided in German.
EVALuna2:209949

Correction to: Introducing multiple-choice questions to promote learning for medical students: effect on exam performance in obstetrics and gynecology (Archives of Gynecology and Obstetrics, (2020), 302, 6, (1401-1406), 10.1007/s00404-020-05758-1) - Jud, Sebastian; Cupisti, Susanne; Frobenius, Wolfgang; Winkler, Andrea; Schultheis, Franziska; Antoniadis, Sophia; Beckmann, Matthias; Heindl, Felix (Archives of Gynecology and Obstetrics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00404-021-06112-9.
CRIS-Team Scopus Importer:2021-07-02

Correlation between referral cytology and in-house colposcopy-guided cytology for detecting early cervical neoplasia - Schulmeyer, Carla; Stübs, Frederik; Gaß, Paul; Renner, Stefan; Hartmann, Arndt; Strehl, Johanna; Mehlhorn, Grit; Geppert, Carol-Immanuel; Adler, Werner; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2019)
Purpose: The current cervical cancer screening program in Germany recommends that the results showing suspected HPV infection should be further examined in specialized colposcopy units. This study aimed to correlate externally documented Pap smear results with in-house colposcopy-guided Pap cytology results and compare colposcopy-guided biopsy and postoperative histopathology results. Methods: Clinical data were analyzed from 3627 examinations in 2844 patients who visited a university certified dysplasia unit from 2014 to 2017; 2212 patients underwent complete assessments, including Pap smear, colposcopy, HPV testing, colposcopy-guided biopsy, and/or surgery. The results were analyzed descriptively. Results: External and in-house Pap results were consistent in 1054 ofthe 2212 patients (47.65%). Referral cytology showed a higher grade than in-house in 456 (20.61%) and a lower grade in 702 (31.74%). Using the histopathological findings as the gold standard, overdiagnosis in the referral cytology was noted in 180 patients (13.19%), underdiagnosis in 263 (19.27%), and concordant findings in 922 (67.55%). For in-house cytology, overdiagnosis was found in 133 patients (10.74%), underdiagnosis in 192 (15.51%), and accurate diagnosis with congruent cytology and histopathology findings in 913 (73.75%). Conclusions: The rate of detection of cervical abnormalities differs significantly depending on whether the examination is performed routinely or in specialized units. Colposcopy-guided Pap smears correlate significantly better with histology than referral cytology results without colposcopic guidance. More severe lesions were also detected more accurately.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Cervical cancer screening; Cervical intraepithelial neoplasia (CIN); Dysplasia; High-grade squamous intraepithelial lesion (HSIL); Low-grade squamous intraepithelial lesion (LSIL); Pap smear; Precancerous lesions of the cervix

Correlation of histological and macroscopic findings in peritoneal endometriosis - Strehl, Johanna; Hackl, Janina; Wachter, David; Klingsiek, Peter; Burghaus, Stefanie; Renner, Stefan; Fasching, Peter; Hartmann, Arndt; Beckmann, Matthias (International Journal of Clinical and Experimental Pathology, 2014)
In the last two decades, a color based concept of disease activity in peritoneal endometriosis has been in use in the clinical context, with red lesions being considered active and black or white lesions being interpreted as less active or dormant.Our aim was to analyze 4 main color categories of peritoneal endometriosis (black, white, red and brown) in one single patient group using histomorphological and immunohistochemical methods.65 endometriosis lesions (30 black, 17 white, 11 brown, 7 red) were resected from 47 premenopausal, nulliparous women which had not received exogenous hormones for at least six months prior to the operation. Specimen workup, histomorphological analysis and immunohistochemical analysis were performed in a standardized manner.The color categories showed a broad overlap in proliferative activity and hormone receptor expression. Differences were found in lesion morphology. Adjacent stromal reaction in particular showed a marked increase from red through brown and black to white lesions. Differences were also seen in gland pattern and gland content.Lesion colors in peritoneal endometriosis seem to be determined by gland content and a varying adjacent stromal reaction and more likely reflect an aging process than different levels of disease activity.
EVALuna2:6566

Correlation of mammographic density and serum calcium levels in patients with primary breast cancer - Hack, Carolin; Stoll, Martin; Jud, Sebastian; Heusinger, Katharina; Adler, Werner; Haeberle, Lothar; Ganslandt, Thomas; Heindl, Felix; Schulz-Wendtland, Rüdiger; Uder, Michael; Beckmann, Matthias; Fasching, Peter; et al. (Cancer Medicine, 2017)
Percentage mammographic breast density (PMD) is one of the most important risk factors for breast cancer (BC). Calcium, vitamin D, bisphosphonates, and denosumab have been considered and partly confirmed as factors potentially influencing the risk of BC. This retrospective observational study investigated the association between serum calcium level and PMD. A total of 982 BC patients identified in the research database at the University Breast Center for Franconia with unilateral BC, calcium and albumin values, and mammogram at the time of first diagnosis were included. PMD was assessed, using a semiautomated method by two readers. Linear regression analyses were conducted to investigate the impact on PMD of the parameters of serum calcium level adjusted for albumin level, and well-known clinical predictors such as age, body mass index (BMI), menopausal status and confounder for serum calcium like season in which the BC was diagnosed. Increased calcium levels were associated with reduced PMD (P = 0.024). Furthermore, PMD was inversely associated with BMI (P < 0.001) and age (P < 0.001). There was also an association between PMD and menopausal status (P < 0.001). The goodness-of-fit of the regression model was moderate. This is the first study assessing the association between serum calcium level and PMD. An inverse association with adjusted serum calcium levels was observed. These findings add to previously published data relating to vitamin D, bisphosphonates, denosumab, and the RANK/RANKL signaling pathway in breast cancer risk and prevention.
EVALuna2:175

Correlation of short-term variation and Doppler parameters with adverse perinatal outcome in low-risk fetuses at term - Stumpfe, Florian M.; Kehl, Sven; Pretscher, Jutta; Baier, Friederike; Bayer, Christian M.; Schwenke, Eva; Schneider, Michael; Mayr, Andreas; Schild, Ralf L.; Schmid, Matthias; Beckmann, Matthias; Faschingbauer, Florian (Archives of Gynecology and Obstetrics, 2019)
ObjectiveTo evaluate the association of short-term variation (STV) and Doppler parameters with adverse perinatal outcome in low-risk fetuses at term.MethodsThis was a retrospective study of 1008 appropriate-for-gestational age (AGA) term fetuses. Doppler measurements [umbilical artery (UA), middle cerebral artery (MCA), and cerebroplacental ratio (CPR)] and computerized CTG (cCTG) with STV analysis were performed prior to active labor (4cm cervical dilatation) within 72h of delivery. The association between Doppler indices and STV values with adverse perinatal outcome was analyzed using univariate regression analysis.ResultsNo significant association between Doppler parameters and the need for secondary cesarean delivery (CD) or operative vaginal delivery (OVD) was shown. Regarding fetuses delivered by CD due to fetal distress, regression analyzes revealed significantly higher UA PI MoM. However, the differences in MCA PI MoM and CPR MoM were not statistically significant. Fetuses with the need for emergency CD showed significantly higher UA PI MoM, lower MCA PI MoM and lower CPR MoM. Neonates with a 5-min Apgar score <7 had significantly lower MCA PI MoM and neonatal acidosis (UA pH 7.10) showed a significant association with UA PI MoM. None of the assessed outcome parameters were significantly associated to STV.ConclusionDoppler indices assessed close to delivery in low-risk fetuses at term show a moderate association with adverse outcome parameters,whereas STV does not appear to predict poor perinatal outcome in this group of fetuses.
CRIS-Team WoS Importer:2019-03-08

Correlation of short-term variation and Doppler parameters with adverse perinatal outcome in small-for-gestational age fetuses at term - Stumpfe, Florian M.; Faschingbauer, Florian; Kehl, Sven; Pretscher, Jutta; Stelzl, Patrick; Mayr, Andreas; Schild, Ralf L.; Schmid, Matthias; Beckmann, Matthias; Schneider, Michael (Archives of Gynecology and Obstetrics, 2019)
Objective: To evaluate the association of short-term variation (STV) and Doppler parameters with adverse perinatal outcome in small-for-gestational-age (SGA) fetuses at term. Methods: In this retrospective single-center study 97 patients with singleton SGA fetuses at term (≥ 37 + 0 weeks’ gestation) were examined. Inclusion criteria were a birth weight < 10th centile, cephalic presentation and planned vaginal birth. Only cases with available Doppler measurements of umbilical artery (UA) and middle cerebral artery (MCA) with calculated cerebroplacental ratio (CPR) in combination with a computerized CTG (cCTG) and STV 72 h prior to delivery were eligible for analysis. Pulsatility indices (PI) were converted into multiples of median (MoM), adjusted for gestational age. The association between Doppler indices and STV values with mode of delivery [secondary cesarean delivery (CD), operative vaginal delivery (OVD), as well as secondary CD and OVD due to fetal distress] and neonatal outcome [UA blood pH ≤ 7.15 and the need of admission to the neonatal intensive care unit (NICU)] was analyzed using logistic regression analysis. Results: There was a significant association between UA PI MoM and the rate of CD. CD due to fetal distress, OVD and OVD due to fetal distress did not show a correlation with the evaluated Doppler parameters. Furthermore, we did not find an association between low UA birth pH and Doppler parameters while neonates with the need of admission to NICU had significant higher UA PI MoM and significant lower MCA PI MoM and CPR MoM. Regarding STV, a significant effect of low STV on NICU admission was found while none of the other assessed outcome parameters were significantly associated with STV. Conclusion: STV and Doppler parameters in SGA fetuses at term are significantly associated to the rate of NICU admission.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Cardiotocography; Cerebroplacental ratio; Computerized CTG; Doppler; Fetal distress; SGA; Short-term variation; small-for-gestational age

Corrigendum to “Initial experience with CDK4/6 inhibitor-based therapies compared to antihormone monotherapies in routine clinical use in patients with hormone receptor positive, HER2 negative breast cancer — Data from the PRAEGNANT research network for the first 2 years of drug availability in Germany” (The Breast (2020) 54 (88–95), (S0960977620301648), (10.1016/j.breast.2020.08.011)) - Schneeweiss, Andreas; Ettl, Johannes; Lüftner, Diana; Beckmann, Matthias; Belleville, Erik; Fasching, Peter; Fehm, Tanja N.; Geberth, Matthias; Häberle, Lothar; Hadji, Peyman; Hartkopf, Andreas D.; Hielscher, Carsten; et al. (BREAST, 2021)
In Fig. 2c and f of our publication Schneeweiss et al. [1] we mistakenly placed wrong Kaplan Meier Plots. In the attached figure this was corrected. All other estimates concerning the survival including the regression models are correct. We apologize for the mistake. 1. Schneeweiss A, Ettl J, Luftner D et al. Initial experience with CDK4/6 inhibitor-based therapies compared to antihormone monotherapies in routine clinical use in patients with hormone receptor positive, HER2 negative breast cancer - Data from the PRAEGNANT research network for the first 2 years of drug availability in Germany. Breast 2020; 54: 88–95.Fig. 2. Progression-free survival (PFS) and overall survival (OS) for the total group analyzed. CDK4/6i, CDK4/6 inhibitors; ET, endocrine therapy; OS, overall survival; PFS, progression-free survival. [Table presented]
CRIS-Team Scopus Importer:2021-01-15

Cost effectiveness of bilateral risk-reducing mastectomy and salpingo-oophorectomy - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Csorba, Roland; Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (European Journal of Medical Research, 2019)
BACKGROUND: Growing demand for risk-reducing surgery in individuals with inherited susceptibility to cancer leads to the question whether these procedures are cost effective for the executing hospitals. This study compared the clinical costs for bilateral risk-reducing mastectomy (BRRM) with and without different types of reconstruction, risk-reducing salpingo-oophorectomy (RRSO), and their combinations with corresponding reimbursements in the statutory health-care system in Germany. PATIENTS AND METHODS: Real total costs of care for BRRM with and without reconstruction, RRSO, and their combinations were calculated as the sum of all personnel and technical costs. These costs calculated in a German University hospital were compared with the sum of all reimbursements in the German DRG-based health-care system. RESULTS: While sole RRSO, BRRM without reconstruction, and BRRM with secondary DIEP (deep inferior epigastric perforator)-reconstruction still result in a small benefit, we even found shortfalls for the hospital with all other prophylactic operations under consideration. The calculated deficits were especially high for BRRM with implant-based breast reconstruction and for combined operations when the risk reduction is achieved with a minimum of separate operations. CONCLUSIONS: Risk-reducing surgery in BRCA-mutation carriers is frequently not cost-covering for the executing hospitals in the German health-care system. Thus, appropriate concepts are required to ensure a nationwide care.
CRIS-Team Scopus Importer:2019-09-24
Keywords: BRCA; Breast cancer; Cost effectiveness; Genetic counseling; Ovarian cancer

Cost-effectiveness of risk-reducing surgeries in preventing hereditary breast and ovarian cancer - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Wiesmann da Silva Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (BREAST, 2017)
Risk-reducing surgeries are a feasible option for mitigating the risk in individuals with inherited susceptibility to cancer, but are the procedures cost-effective in the current health-care system in Germany? This study compared the health-care costs for bilateral risk-reducing mastectomy (BRRM) and risk-reducing (bilateral) salpingo-oophorectomy (RRSO) with cancer treatment costs that could potentially be prevented.The analysis is based on interdisciplinary consultations with individuals with a high familial risk for breast and ovarian cancer at the University Breast Center for Franconia (Germany) between 2009 and 2013 (370 consultations; 44 patients with BRCA1 mutations and 26 with BRCA2 mutations). Health-care costs for risk-reducing surgeries in BRCA mutation carriers were calculated as reimbursements in the German diagnosis-related groups (DRG) hospital pricing system. These costs for the health-care system were compared with the potential cancer treatment costs that could possibly be prevented by risk-reducing surgeries.Long-term health-care costs can be reduced by risk-reducing surgeries after genetic testing in BRCA mutation carriers. The health-care system in Germany would have saved EUR 136,295 if BRRM had been performed and EUR 791,653 if RRSO had been performed before the development of cancer in only 50% of the 70 mutation carriers seen in our center. Moreover, in patients with combined RRSO and BRRM (without breast reconstruction), one further life-year for a 40-year-old BRCA mutation carrier would cost EUR 2,183.Intensive care, including risk-reducing surgeries in BRCA mutation carriers, is cost-effective from the point of view of the health-care system in Germany.
EVALuna2:9369

Cross-Cancer Genome-Wide Association Study of Endometrial Cancer and Epithelial Ovarian Cancer Identifies Genetic Risk Regions Associated with Risk of Both Cancers - Glubb, Dylan M.; Thompson, Deborah J.; Aben, Katja K. H.; Alsulimani, Ahmad; Amant, Frederic; Annibali, Daniela; Attia, John; Barricarte, Aurelio; Beckmann, Matthias; Berchuck, Andrew; Bermisheva, Marina; Bernardini, Marcus Q.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2021)
Background: Accumulating evidence suggests a relationship between endometrial cancer and ovarian cancer. Independent genome-wide association studies (GWAS) for endometrial cancer and ovarian cancer have identified 16 and 27 risk regions, respectively, four of which overlap between the two cancers. We aimed to identify joint endometrial and ovarian cancer risk loci by performing a meta-analysis of GWAS summary statistics from these two cancers.
CRIS-Team WoS Importer:2021-03-12

Cullin 7 and Fbxw 8 expression in trophoblastic cells is regulated via oxygen tension: Implications for intrauterine growth restriction - Fahlbusch, Fabian; Dawood, Yousif Louay; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Tzschoppe, Anja; Schneider, Holm; Strissel, Pamela; Beckmann, Matthias; Schleussner, Ekkehard; Rübner, Matthias; Dörr, Helmuth-Günther; et al. (Journal of Maternal-Fetal & Neonatal Medicine, 2012)
Objective: The F-box protein Fbxw8 is a cofactor of Cullin 7 (Cul7), which regulates protein transfer to the proteasome and cell growth. Cul7 or Fbxw8 deficiency is associated with intrauterine growth restriction (IUGR) due to abnormal placental development leading to poor oxygen supply to the fetus. We studied the role of hypoxia for Fbxw8 and Cul7 expression in trophoblastic cells. Methods: Immunomagnetic bead-separated extravillous trophoblast (EVT) and villous trophoblast (VT) and trophoblast cell lines were incubated with 1 or 8% O2. Fbxw8 and Cul7 expression was determined in IUGR versus matched control placentas. Results: Fbxw8 was expressed uniformly in trophoblasts, whereas Cul7 expression was most prominent in trophoblast cell lines. Hypoxia reduced expression of Cul7 and Fbxw8 in all trophoblastic cells, except for villous trophoblasts. In vivo, Cul7 and Fbxw8 were detected in syncytiotrophoblast cells, VT, and EVT cells. Although no significant changes in expression levels of Fbxw8 or Cul7 were noted in IUGR compared with control placentas, Fbxw8 expression correlated negatively with gestational age in the control, but not in the IUGR group. Conclusion: Fbxw8 and Cul7 expression reveals a complex regulation in trophoblastic cells. Our findings suggest that dysregulation of Cul7 and Fbxw8 expression might affect trophoblast turnover in IUGR. © 2012 Informa UK, Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Cul7; Fbxw8; IUGR; Oxygen; Placenta; Trophoblast

Culture of Individually Required Number of 2-Pronuclei-Stage Oocytes - Patient Participation in Decision-Making is in Accordance with the Aim of Avoiding Surplus Embryo Freezing - Cupisti, Susanne; Mueller, A.; Hildebrandt, T.; Hackl, J.; Beckmann, Matthias; Dittrich, Ralf (Geburtshilfe und Frauenheilkunde, 2014)
Background: The aim of this study was to evaluate how many embryos will develop if more than 3 2-pronuclei-stage oocytes (2-PNOs) are cultured at the patient's request and in accordance with the Germany Embryo Protection Law. Methods: A total of 106 cycles of patients undergoing their 1st, 2nd or 3rd cycle of IVF or ICSI treatment in 2010 were prospectively included in the study. In each individual case, a decision was taken prior to treatment about the number of 2-PNOs to be cultured after each cycle. Results: Ninety female patients were treated for a total of 106 cycles. A mean of two to six 2-PNOs were cultivated for a period of between 3 and 6 days for each patient. After culture, no viable embryo was identified for 5 patients (4.7 %), a single viable embryo was identified for 37 cycles (34.7 %), and 2 viable embryos were identified for 52 cycles (48.8 %). Eleven patients (10.3 %) had 3 viable embryos after a further 11 cycles and 1 patient had 4 viable embryos in a single cycle. Ten of the patients with 3 embryos each opted to have all 3 embryos transferred in the same cycle. This meant that a single embryo from one patient with 3 viable embryos and a single embryo of the patient with 4 viable embryos were cryopreserved after culture. The pregnancy rate was 19 % per embryo transfer and 25 % per blastocyst transfer (20 pregnancies in total). All cryopreserved embryos were transferred in a subsequent cycle. Discussion: Based on this study it is possible to make a statement about the number of viable embryos which should be cultivated to obtain, at best, two embryos for transfer without running an unacceptably high risk of producing too many embryos which would then need to be cryopreserved. Only 12 patients (13.3 %) had more than 2 viable embryos. The number of supernumerary pre-implantation-stage embryos was acceptably low (only 2 patients had additional viable embryos, 2.2 %). This means that it is possible to fulfil the wishes of individual patients while complying with the German Embryo Protection Law.
EVALuna2:17451

CYP19A1 fine-mapping and Mendelian randomization: estradiol is causal for endometrial cancer - Thompson, Deborah J.; O'Mara, Tracy A.; Glubb, Dylan M.; Painter, Jodie N.; Cheng, Timothy; Folkerd, Elizabeth; Doody, Deborah; Dennis, Joe; Webb, Penelope M.; Gorman, Maggie; Martin, Lynn; Hodgson, Shirley; et al. (Endocrine-Related Cancer, 2016)
Candidate gene studies have reported CYP19A1 variants to be associated with endometrial cancer and with estradiol (E2) concentrations. We analyzed 2937 single nucleotide polymorphisms (SNPs) in 6608 endometrial cancer cases and 37 925 controls and report the first genome wide-significant association between endometrial cancer and a CYP19A1 SNP (rs727479 in intron 2, P=4.8×10(-11)). SNP rs727479 was also among those most strongly associated with circulating E2 concentrations in 2767 post-menopausal controls (P=7.4×10(-8)). The observed endometrial cancer odds ratio per rs727479 A-allele (1.15, CI=1.11-1.21) is compatible with that predicted by the observed effect on E2 concentrations (1.09, CI=1.03-1.21), consistent with the hypothesis that endometrial cancer risk is driven by E2. From 28 candidate-causal SNPs, 12 co-located with three putative gene-regulatory elements and their risk alleles associated with higher CYP19A1 expression in bioinformatical analyses. For both phenotypes, the associations with rs727479 were stronger among women with a higher BMI (Pinteraction=0.034 and 0.066 respectively), suggesting a biologically plausible gene-environment interaction.
EVALuna2:9315

CYP2B6*6 is associated with increased breast cancer risk - Justenhoven, Christina; Pentimalli, Daniela; Rabstein, Sylvia; Harth, Volker; Lotz, Anne; Pesch, Beate; Bruening, Thomas; Doerk, Thilo; Schuermann, Peter; Bogdanova, Natalia; Park-Simon, Tjoung-Won; Couch, Fergus J.; et al. (International Journal of Cancer, 2014)
The cytochrome P450 2B6 (CYP2B6) is involved in the metabolism of testosterone. Functional changes in this enzyme may influence endogenous hormone exposure, which has been associated with risk of breast cancer. To assess potential associations between two functional polymorphisms CYP2B6_516_G>T (rs3745274) and CYP2B6_785_A>G (rs2279343) and breast cancer risk, we established a specific matrix-assisted laser desorption/ionization time-of-flight mass spectrometry assay. The GENICA breast cancer case-control study showed associations between the variant genotypes CYP2B6_516_TT and CYP2B6_785_GG and breast cancer risk with odds ratios (ORs) of 1.34 (p = 0.001) and 1.31 (p = 0.002), respectively. A similar effect was observed for carriers of the CYP2B6_516_T allele in a validation study including four independent studies from Germany, Sweden and USA. In a pooled analysis of all five studies involving 4,638 breast cancer cases and 3,594 controls of European ancestry, carriers of the CYP2B6_516_G and the CYP2B6_785_G variant had an increased breast cancer risk with ORs of 1.10 (p = 0.027) and 1.10 (p = 0.031), respectively. We conclude that the genetic variants CYP2B6_516_G and CYP2B6_785_G (designated CYP2B6*6), which are known to decrease activity of the CYP2B6 enzyme, contribute to an increased breast cancer risk.
EVALuna2:9206

CYP2D6 genotype and adjuvant tamoxifen: meta-analysis of heterogeneous study populations - Province, M. A.; Goetz, M. P.; Brauch, H.; Flockhare, D. A.; Hebert, J. M.; Whaley, R.; Suman, V. J.; Schroth, W.; Winter, S.; Zembutsu, H.; Mushiroda, Taisei; Newman, W. G.; et al. (Clinical Pharmacology & Therapeutics, 2014)
The International Tamoxifen Pharmacogenomics Consortium was established to address the controversy regarding cytochrome P450 2D6 (CYP2D6) status and clinical outcomes in tamoxifen therapy. We performed a meta-analysis on data from 4,973 tamoxifen-treated patients (12 globally distributed sites). Using strict eligibility requirements (postmenopausal women with estrogen receptor-positive breast cancer, receiving 20 mg/day tamoxifen for 5 years, criterion 1); CYP2D6 poor metabolizer status was associated with poorer invasive disease-free survival (IDFS: hazard ratio = 1.25; 95% confidence interval = 1.06, 1.47; P = 0.009). However, CYP2D6 status was not statistically significant when tamoxifen duration, menopausal status, and annual follow-up were not specified (criterion 2, n = 2,443; P = 0.25) or when no exclusions were applied (criterion 3, n = 4,935; P = 0.38). Although CYP2D6 is a strong predictor of IDFS using strict inclusion criteria, because the results are not robust to inclusion criteria (these were not defined a priori), prospective studies are necessary to fully establish the value of CYP2D6 genotyping in tamoxifen therapy.
EVALuna2:17447

Cytology and High-Risk Human Papillomavirus Test for Cervical Cancer Screening Assessment - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul (Diagnostics, 2022)
Background: A new nationwide screening strategy was implemented in Germany in January 2020. No data are available for women referred to certified dysplasia units for secondary clarification after primary diagnosis by a local physician. We therefore investigated combined testing with Papanicolaou smears and high-risk human papillomavirus (hrHPV) and compared the data with the final histological findings. Methods: Between January 2015 and October 2020, all referred women who underwent colposcopy of the uterine cervix in our certified dysplasia unit were included. Cytology findings were classified using the Munich III nomenclature. Results: A total of 3588 colposcopies were performed in 3118 women, along with Pap smear and hrHPV co-testing, followed by histology. Women with Pap II-p (ASC-US) and a positive hrHPV co-test had a 22.4% risk for cervical intraepithelial neoplasia (CIN) 3/high-grade squamous intraepithelial lesion (HSIL). The risk of CIN 3/HSIL was 83.8% in women with Pap IVa-p (HSIL) and a positive hrHPV co-test. A positive hrHPV co-test increased the risk for HSIL+ (OR 5.942; 95% CI, 4.617 to 7.649; p < 0.001) as compared to a negative hrHPV co-test. Conclusions: The accuracy of Pap smears is comparable with the screening results. A positive hrHPV test increases the risk for HSIL+ fivefold. Colposcopy is necessary to diagnose HSIL+ correctly.
CRIS-Team WoS Importer:2022-08-12

Cytology and HPV Co-Testing for Detection of Vaginal Intraepithelial Neoplasia: A Retrospective Study. - Stübs, Frederik; Dietl, Anna; Koch, Martin C.; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Mehlhorn, Grit; Beckmann, Matthias; Schulmeyer, Carla; Heindl, Felix; Emons, Julius; et al. (Cancers, 2023)
(1) Background: Vaginal intraepithelial neoplasia (VaIN) is a rare premalignant disease caused by persistent human papillomavirus (HPV) infection. Diagnosing VaIN is challenging; abnormal cytology and positive HPV tests are usually the first signs, but published data on their accuracy for detecting it are rare and contradictory. The aim of this study is to compare the results of hrHPV and cytology co-testing with the histological findings of the vagina. (2) Methods: In the certified Dysplasia Unit at Erlangen University Hospital, cytology and HPV samples from the uterine cervix or vaginal wall after hysterectomy were obtained between 2015 and 2023 and correlated with histological findings in biopsies from the vaginal wall. Women without vaginal biopsy findings or concomitant cervical disease were excluded. (3) Results: In all, 279 colposcopies in 209 women were included. The histological results were: benign (n = 86), VaIN I/vLSIL (n = 116), VaIN II/vHSIL (n = 41), VaIN III/vHSIL (n = 33), and carcinoma (n = 3). Accuracy for detecting VaIN was higher in women with previous hysterectomies. Positive HPV testing during colposcopy increased the likelihood for VaIN II/III/vHSIL threefold. The detection rate for VaIN III/vHSIL was 50% after hysterectomy and 36.4% without hysterectomy. (4) Conclusions: Women with risk factors for VaIN, including HPV-16 infection or prior HPV-related disease, need careful work-up of the entire vaginal wall. Hysterectomy for HPV-related disease and a history of cervical intraepithelial neoplasia (CIN) also increased the risk for VaIN II/III/vHSIL.
EVALuna2:540622

Cytology and hrHPV for cervical cancer screening assessment - Stübs, Frederik; Koch, M. C.; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, G.; Gaß, Paul; Schulmeyer, Carla (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Deactivating attachment strategies associate with early processing of facial emotion and familiarity in middle childhood: an ERP study - Kungl, Melanie; Vrticka, Pascal; Heinisch, Christine; Beckmann, Matthias; Fasching, Peter; Ziegler, Clara; Spangler, Gottfried (Attachment and Human Development, 2022)
Neurophysiological evidence suggests associations between attachment and the neural processing of emotion expressions. This study asks whether this relationship is also evident in middle childhood, and how it is affected by facial familiarity. Attachment strategies (deactivation, hyperactivation) were assessed in 51 9- to 11-year olds using a story stem completion task. Event-related potentials (ERPs) were recorded during children's passive viewing of mother and stranger emotional faces (angry/happy). At the stage of facial information encoding (N250), attachment deactivation was associated with a pattern pointing to increased vigilance towards angry faces. Further, the attention-driven LPP was increased to happy mother faces as highly salient stimuli overall, but not in children scoring high on deactivation. These children did not discriminate between mothers' facial emotions and showed a general attentional withdrawal from facial stimuli. While our results on attachment deactivation support a two-stage processing model, no effect of hyperactivation was found.
CRIS-Team WoS Importer:2022-10-21

Design and Implementation of a Single Source Multipurpose Hospital-Wide Clinical Trial Registry - Sommer, Marcus; Kirchner, Melanie; Gulden, Christian; Egloffstein, Sainab; Lux, Michael P.; Beckmann, Matthias; Mackensen, Andreas; Prokosch, Hans-Ulrich (ICT FOR HEALTH SCIENCE RESEARCH, 2019)
CRIS-Team WoS Importer:2021-10-18

Design and Implementation of a Single Source Multipurpose Hospital-Wide Clinical Trial Registry - Sommer, Marcus; Kirchner, Melanie; Gulden, Christian; Egloffstein, Sainab; Lux, Michael P.; Beckmann, Matthias; Mackensen, Andreas; Prokosch, Hans-Ulrich (Studies in health technology and informatics, 2019)
IT-supported patient recruitment, serious adverse event reporting as well as making information about clinical trials accessible to the public on websites, are still major challenges in clinical trials. Too often the distribution of information about trials being performed within a hospital across numerous institutions and IT systems is a barrier to provide efficient IT support for such scenarios. Thus, the essential prerequisite to mastering those challenges is to achieve one single point of truth with adequate, complete, accurate and up-to-date information about all clinical trials running at a hospital. We describe the design and implementation of such a single source clinical trial registry serving multiple purposes at a university hospital.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Clinical trials as topic; electronic health record; registries

Design and Implementation of a Single Source Multipurpose Hospital-Wide Clinical Trial Registry. - Sommer, Marcus; Kirchner, Melanie; Gulden, Christian; Egloffstein, Sainab; Lux, Michael P.; Beckmann, Matthias; Mackensen, Andreas; Prokosch, Hans-Ulrich (Studies in health technology and informatics, 2019)
IT-supported patient recruitment, serious adverse event reporting as well as making information about clinical trials accessible to the public on websites, are still major challenges in clinical trials. Too often the distribution of information about trials being performed within a hospital across numerous institutions and IT systems is a barrier to provide efficient IT support for such scenarios. Thus, the essential prerequisite to mastering those challenges is to achieve one single point of truth with adequate, complete, accurate and up-to-date information about all clinical trials running at a hospital. We describe the design and implementation of such a single source clinical trial registry serving multiple purposes at a university hospital.
EVALuna2:184246

Desire to Have Children Among Transgender People in Germany: A Cross-Sectional Multi-Center Study - Auer, Matthias K.; Fuss, Johannes; Nieder, Timo O.; Briken, Peer; Biedermann, Sarah; Stalla, Guenter K.; Beckmann, Matthias; Hildebrandt, Thomas (Journal of Sexual Medicine, 2018)
Many trans individuals undergo medical interventions that result in irreversible loss of fertility. Little is known about their desire to have children and attitudes toward fertility preservation options.To study how the desire for children and the use of fertility preservation options varies among trans women and trans men in different transitioning stages in Germany.In this cross-sectional multi-center study, N = 99 trans women and N = 90 trans men were included. Of these, 26 of each sex were just about to start medical treatment.Outcome parameter were the prevalence and determinants of a desire to have children in trans persons.Before treatment, a desire for children was significantly higher in trans men compared to trans women (P = .016). In contrast, in those who had already started treatment, a current desire to have children was equally present in about one fourth of participants of both genders while the interest in having children in the future was significantly higher in trans women (69.9%) than in trans men (46.9%; P = .034). Although 76.1% of trans women and 76.6% of trans men indicated that they had at least thought about preserving germ cells before starting medical transition, only 9.6% of trans women and 3.1% of trans men had put this idea into practice. Most trans men in both groups indicated that insemination of a female partner with sperm from an unrelated donor was a suitable option to fulfill their child wish, potentially explaining their low interest in preserving their own germ cells. Finally, a logistic regression analysis accounting for potential confounders revealed that overall trans women were more than twice as likely to have a current desire to have children (odds ratio 2.58), and this wish was on average 5.3% lower with each year of increasing age.A low level of fertility preservation among trans persons is contrasted by a high level of desire for children. This highlights the importance of counseling trans individuals regarding fertility preservation options.To our knowledge, this is the first study that addresses desire to have children in a clinical sample of trans women. It is also the first that investigates this issue among trans men who have not started medical treatment, and the first comparison of both genders. A limitation for the generalization of our results is the special legal context in Germany that forbids oocyte donation for reciprocal in vitro fertilization. Reproductive desire is high among trans individuals, but the use of reproductive options is surprisingly low. Auer MK, Fuss J, Nieder TO, et al. Desire to Have Children Among Transgender People in Germany: A Cross-Sectional Multi-Center Study. J Sex Med 2018;15:757-767.
EVALuna2:157267

Detection of circulating tumor cells using manually performed immunocytochemistry (MICC) does not correlate with outcome in patients with early breast cancer - Results of the German SUCCESS-A- trial - Jueckstock, Julia; Rack, Brigitte; Friedl, Thomas W. P.; Scholz, Christoph; Steidl, Julia; Trapp, Elisabeth; Tesch, Hans; Forstbauer, Helmut; Lorenz, Ralf; Rezai, Mahdi; Haeberle, Lothar; Alunni-Fabbroni, Marianna; et al. (BMC Cancer, 2016)
BACKGROUND: Recently, the prognostic significance of circulating tumor cells (CTCs) in primary breast cancer as assessed using the Food-and-Drug-Administration-approved CellSearch® system has been demonstrated. Here, we evaluated the prognostic relevance of CTCs, as determined using manually performed immunocytochemistry (MICC) in peripheral blood at primary diagnosis, in patients from the prospectively randomized multicenter SUCCESS-A trial (EudraCT2005000490-21). METHODS: We analyzed 23 ml of blood from 1221 patients with node-positive or high risk node-negative breast cancer before adjuvant taxane-based chemotherapy. Cells were separated using a density gradient followed by epithelial cell labeling with the anti-cytokeratin-antibody A45-B/B3, immunohistochemical staining with new fuchsin, and cytospin preparation. All cytospins were screened for CTCs, and the cutoff for positivity was at least one CTC. The prognostic value of CTCs with regard to disease-free survival (DFS), distant disease-free survival (DDFS), breast-cancer-specific survival (BCSS), and overall survival (OS) was assessed using both univariate analyses applying the Kaplan-Meier method and log-rank tests, and using multivariate Cox regressions adjusted for other predictive factors. RESULTS: In 20.6 % of all patients (n = 251) a median of 1 (range, 1-256) CTC was detected, while 79.4 % of the patients (n = 970) were negative for CTCs before adjuvant chemotherapy. A pT1 tumor was present in 40.0 % of patients, 4.8 % had G1 grading and 34.6 % were node-negative. There was no association between CTC positivity and tumor stage, nodal status, grading, histological type, hormone receptor status, Her2 status, menopausal status or treatment. Univariate survival analyses based on a median follow-up of 64 months revealed no significant differences between CTC-positive and CTC-negative patients with regard to DFS, DDFS, BCSS, or OS. This was confirmed by fully adjusted multivariate Cox regressions, showing that the presence of CTCs (yes/no) as assessed by MICC did not predict DFS, DDFS, BCSS or OS. CONCLUSIONS: We could not demonstrate prognostic relevance regarding CTCs that were quantified using the MICC method at the time of primary diagnosis in our cohort of early breast cancer patients. Further studies are necessary to evaluate if the presence of CTCs assessed using MICC has prognostic relevance, or can be used for risk stratification and treatment monitoring in adjuvant breast cancer. TRIAL REGISTRATION: The ClinicalTrial.gov registration ID of this prospectively randomized trial is NCT02181101 ; the (retrospective) registration date was June 2014 (study start date September 2005).
EVALuna2:32969

Detection of microcalcifications in spiral breast computed tomography with photon-counting detector is feasible: A specimen study - Wetzl, Matthias; Wenkel, Evelyn; Balbach, Eva; Dethlefsen, Ebba; Hartmann, Arndt; Emons, Julius; Kuhl, Christiane; Beckmann, Matthias; Uder, Michael; Ohlmeyer, Sabine (Diagnostics, 2021)
The primary objective of the study was to compare a spiral breast computed tomography system (SBCT) to digital breast tomosynthesis (DBT) for the detection of microcalcifications (MCs) in breast specimens. The secondary objective was to compare various reconstruction modes in SBCT. In total, 54 breast biopsy specimens were examined with mammography as a standard reference, with DBT, and with a dedicated SBCT containing a photon-counting detector. Three different reconstruction modes were applied for SBCT datasets (Recon1 = voxel size (0.15 mm)3, smooth kernel; Recon2 = voxel size (0.05 mm)3, smooth kernel; Recon3 = voxel size (0.05 mm)3, sharp kernel). Sensitivity and specificity of DBT and SBCT for the detection of suspicious MCs were analyzed, and the McNemar test was used for comparisons. Diagnostic confidence of the two readers (Likert Scale 1 = not confident; 5 = completely confident) was analyzed with ANOVA. Regarding detection of MCs, reader 1 had a higher sensitivity for DBT (94.3%) and Recon2 (94.9%) compared to Recon1 (88.5%; p < 0.05), while sensitivity for Recon3 was 92.4%. Respectively, reader 2 had a higher sensitivity for DBT (93.0%), Recon2 (92.4%), and Recon3 (93.0%) compared to Recon1 (86.0%; p < 0.05). Specificities ranged from 84.7–94.9% for both readers (p > 0.05). The diagnostic confidence of reader 1 was better with SBCT than with DBT (DBT 4.48 ± 0.88, Recon1 4.77 ± 0.66, Recon2 4.89 ± 0.44, and Recon3 4.75 ± 0.72; DBT vs. Recon1/2/3: p < 0.05), while reader 2 found no differences. Sensitivity and specificity for the detection of MCs in breast specimens is equal for DBT and SBCT when a small voxel size of (0.05 mm)3 is used with an equal or better diagnostic confidence for SBCT compared to DBT.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Breast cancer; Microcalcifications; Reconstruction modes; Spiral breast CT

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Determinants of transplantation success with cryopreserved ovarian tissue: data from 196 women of the FertiPROTEKT network - Lotz, Laura; Bender-Liebenthron, J.; Dittrich, Ralf; Häberle, Lothar; Beckmann, Matthias; Germeyer, A.; Korell, M.; Saenger, N.; Kruessel, J. S.; Von Wolff, Michael (Human Reproduction, 2022)
STUDY QUESTION What are the pregnancy and live birth rates for ovarian tissue transplantation and which factors are associated with the success rate? SUMMARY ANSWER Pregnancy and live birth rates per transplanted woman are 32.7% and 26.5% and success rate is associated with female age and first versus repeated transplantation. WHAT IS KNOWN ALREADY Live birth rates after ovarian tissue transplantations have been reported to be between around 24% and 41% per patient. Success rates seem to be negatively associated with increasing female age at the time of tissue cryopreservation and with pelvic radiation. Success rates are apparently not reduced after overnight transportation of ovarian tissue before freezing. STUDY DESIGN, SIZE, DURATION Registry analysis of 244 transplantations in 196 women, performed by 26 FertiPROTEKT network centres from 2007 to 2019 with follow-up till December 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS Orthotopic ovarian tissue transplantations were performed in 196 women, 191 with previous malignant and 5 with previous non-malignant diseases. Size of transplanting centres varied between 1 and 100 transplantations per centre (median: 2). Factors possibly associated with success rate such as female age, first and repeated transplantation, experience of the transplanting centre and overnight transportation of the ovarian tissue before freezing were analysed. MAIN RESULTS AND THE ROLE OF CHANCE Average age of all 196 transplanted women was 31.3 years (SD 5.2; range 17-44) at the time of cryopreservation of tissue and 35.9 years (SD 4.8; range 23-47) at the time of transplantation. Pregnancy rate was 30.6% (95% CI, 24.2-37.6%) per first transplantation and 32.7% (95% CI, 26.1-39.7%) per patient. Pregnancy rate was higher after first transplantation (30.6% (95% CI, 24.2-37.6%)) compared to second and subsequent transplantations (11.8% (95% CI, 3.3-27.5%)). Live birth rate per first transplantation was 25.0% (95% CI, 19.1-31.7%) and per patient 26.5% (95% CI, 20.5-33.3%). Success rate decreased with increasing age at the time of ovarian tissue freezing. Live birth rate was 28.2% (95% CI, 20.9-36.3%) in women <35 years and 16.7% (95% CI, 7.9-29.3%) in women >35 years. Pregnancy rates after first transplantation were higher in centres who had performed >= 10 transplantations (35.1%) compared to centres with <10 transplantation (25.4%) (P = 0.12). Corresponding live birth rates were 27.0% and 18.6%. Success rates were not different in women with and without overnight transportation of tissue before cryopreservation. LIMITATIONS, REASONS FOR CAUTION The data were drawn from a registry analysis. Data such as ovarian reserve and premature ovarian insufficiency were not available for all women. Data might be influenced by different follow-up policies of the centres. WIDER IMPLICATIONS OF THE FINDINGS The study reveals the high potential of ovarian tissue freezing and transplantation, but only if freezing is performed in younger women. The study suggests focus should be placed on the first and not on repeated transplantations. It also opens the discussion of whether transplantation should rather be performed by experienced centres. STUDY FUNDING/COMPETING INTEREST(S) No funding. No competing interests.
CRIS-Team WoS Importer:2022-11-04

Detyrosinated tubulin is decreased in fetal vessels of preeclampsia placentas - Huebner, H.; Knoerr, B.; Betzler, A.; Kehl, Sven; Baier, F.; Wachter, David Lukas; Strick, Reiner; Beckmann, Matthias; Fahlbusch, F. B.; Rübner, Matthias; Hartner, Andrea (Placenta, 2018)
INTRODUCTION: Preeclampsia is a hypertensive, gestational disease, which is still the leading cause of pregnancy related morbidity and mortality. The impairment of placental angiogenesis and vascularization is discussed to be of etiopathologic relevance. Deytrosination and tyrosination of α-tubulin is important for the stability and dynamics of microtubules. An increase of α-tubulin detyrosination leads to microtubule stabilization, which is an essential prerequisite for physiologic vascular tube morphogenesis during angiogenesis. So far, little is known about the specific localization of detyrosinated (detyr) and tyrosinated (tyr) tubulin in the placenta and its relevance for preeclampsia. METHODS: Placental expression of detyr- and tyr-tubulin was analyzed by immunohistochemistry, immunofluorescence and western blot. For western blot quantification we used biopsies from healthy placentas (n = 21) and placentas from pregnancies complicated with small for gestational age (n = 5), preeclampsia (n = 5) or both (n = 5). RESULTS: Specific placental localization of detyr-tubulin was detected in the fetal endothelial cells of the placenta. Villous and extravillous trophoblasts as well as villous stroma cells were tyr-tubulin positive. Detyr-tubulin protein expression was significantly decreased in placentas complicated by preeclampsia. CONCLUSIONS: In summary, we report an accumulation of detyr-tubulin in villous vessels of the placenta and a significantly reduced level of detyr-tubulin in placental biopsies of preeclampsia cases. The reduction of placental detyr-tubulin in preeclampsia could suggest a deficit in villous vascular plasticity and might be associated with the impaired arborization of the disease.
EVALuna2:34296

Development and Validation of a Standardized Questionnaire and Standardized Diary for Use in Integrative Medicine Consultations in Gynecologic Oncology - Hack, Carolin; Huettner, N. B. M.; Fasching, Peter; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Use of complementary and alternative medicine (CAM) in diagnoses is not standardized and is very heterogeneous. There are few published standards on integrative medicine consultations or CAM-specific validated follow-up questionnaires. The aim of this study was to develop a standard for integrative medicine consultations, a patient questionnaire which could be used as a basis for medical decisions, and a diary to evaluate the course of the integrative therapy. Patients and Methods: Between June 2013 and September 2014 a standardized integrative medicine consultation in gynecologic oncology was developed and implemented at the Department of Gynecology and Obstetrics of Erlangen University Hospital. A standard operating procedure for consultations was developed; the necessary instruments were developed and validated. Results: Overall patient assessment of the integrative medicine questionnaire and the integrative medicine diary with regard to the time required for completion, comprehensibility, complexity and functionality was positive. Patients evaluated the standardized overall concept of the integrative medicine consultation and its instruments as suitable. Conclusion: Our team is one of the first study groups to develop, validate and publish a standard procedure for integrative medicine consultations. In future, the standard operating procedure for integrative medicine procedures of the Department of Gynecology and Obstetrics of Erlangen University Hospital could be introduced in other hospitals and certified breast cancer centers and gynecologic cancer centers. This would offer patients maximum security and a standardized quality of care in integrative medicine.
EVALuna2:17565

DGGG Guidelines Programme: Status Quo - Quo Vadis! - Beckmann, Matthias; Linde, I.; Buetof, C.; Kreienberg, R.; Gaß, Paul (Geburtshilfe und Frauenheilkunde, 2014)
The Guidelines programme of the German Society of Gynaecology and Obstetrics (DGGG) is an executive part of the DGGG Guidelines Commission. It includes in-house planning and organisation of all guidelines as well as representation outside of the DGGG. This article does not concern the development of the guidelines as much as it concerns the planning, organisation, registration, editing and publication of the guidelines in context of the DGGG Guidelines programme. It targets interested parties, especially authors and coordinators of guidelines.
EVALuna2:17455

Diabetes and prognosis in a breast cancer cohort - Schrauder, Michael; Fasching, Peter A.; Häberle, Lothar; Lux, Michael P.; Rauh, Claudia; Hein, Alexander; Bayer, Christian M.; Heusinger, Katharina; Hartmann, Arndt; Strehl, Johanna D.; Wachter, David; Schulz-Wendtland, Rüdiger; et al. (Journal of Cancer Research and Clinical Oncology, 2011)
Purpose: Epidemiological studies indicated that type 2 diabetes mellitus may increase breast cancer risk and mortality. The aim of this retrospective cohort study was to examine the effect of diabetes on the clinical course and the prognosis of early stage breast cancer in relation to tumour and patient characteristics. Methods: The cohort analyzed in this study consisted of 4,056 patients with invasive primary breast cancer. We compared overall survival, distant metastasis-free survival and local recurrence free survival between breast cancer patients with and without diabetes. Results: In our cohort 276 breast cancer patients (6.8%) were affected by diabetes compared to 3,780 patients (93.2%) without diabetes. Women with diabetes were significantly older, had larger tumours, and a higher rate of lymph node involvement. After a follow-up period of 5 years, stratification for age and adjustment for other prognostic factors, overall mortality following breast cancer was significantly higher in diabetic breast cancer patients (hazard ratio, HR 1.92; 95% confidence interval, CI 1.49-2.48). We found no significant differences in distant metastasis-free survival and local recurrence free survival between the two groups, but we found a slightly significant higher rate of distant metastasis in the group of patients with diabetes and oestrogen receptor negative tumours (HR 2.28; CI 1.31-3.97). Conclusion: In this study, patients with diabetes and oestrogen receptor negative breast cancer had a more than 2-fold higher risk for distant metastasis compared to patients without diabetes. Diabetes was also associated with an almost 2-fold increase in mortality within the 5 years follow-up period. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer; Cohort study; Diabetes mellitus; Distant metastasis; Local recurrence; Survival

Diagnosis and Treatment of Endometriosis. Guideline of the DGGG, SGGG and OEGGG (S2k Level, AWMF Registry Number 015/045, August 2020) - Burghaus, Stefanie; Schäfer, Sebastian D.; Beckmann, Matthias; Brandes, Iris; Brünahl, Christian; Chvatal, Radek; Drahoå ovský, Jan; Dudek, Wojciech; Ebert, Andreas D.; Fahlbusch, Christine; Fehm, Tanja; Fehr, Peter Martin; et al. (Geburtshilfe und Frauenheilkunde, 2021)
Aims The aim of this official guideline published and coordinated by the German Society of Gynaecology and Obstetrics (DGGG) in cooperation with the Austrian Society for Gynaecology and Obstetrics (OEGGG) and the Swiss Society for Gynaecology and Obstetrics (SGGG) was to provide consensus-based recommendations for the diagnosis and treatment of endometriosis based on an evaluation of the relevant literature. Methods This S2k guideline represents the structured consensus of a representative panel of experts with different professional backgrounds commissioned by the Guideline Committee of the DGGG, OEGGG and SGGG. Recommendations Recommendations on the epidemiology, aetiology, classification, symptomatology, diagnosis and treatment of endometriosis are given and special situations are discussed.
CRIS-Team Scopus Importer:2021-04-23
Keywords: diagnosis; endometriosis; guideline; pelvic pain; treatment

Diagnosis, Therapy and Follow-up of Cervical Cancer. Guideline of the DGGG, DKG and DKH (S3-Level, AWMF Registry No. 032/033OL, May 2021) – Part 1 with Recommendations on Epidemiology, Screening, Diagnostics and Therapy - Beckmann, Matthias; Stübs, Frederik; Koch, Martin; Mallmann, Peter; Dannecker, Christian; Dietl, Anna; Sevnina, Anna; Mergel, Franziska; Lotz, Laura; Hack, Carolin; Ehret, Anne; Gantert, Daniel; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Aim This update of the interdisciplinary S3 guideline on the Diagnosis, Therapy and Follow-up of Cervical Cancer (AWMF Registry No. 032/033OL) was published in March 2021. This updated guideline was funded by German Cancer Aid (Deutsche Krebshilfe) as part of the German Guideline Program in Oncology. The guideline was coordinated by the German Society of Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG) and the Working Group on Gynecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie, AGO) of the German Cancer Society (Deutsche Krebsgesellschaft, DKG). Method The process of updating the S3 guideline dating from 2014 was based on an appraisal of the available evidence using the criteria of evidence-based medicine, adaptations of existing evidence-based national and international guidelines or - if evidence was lacking - on a consensus of the specialists involved in compiling the update. After an initial review of the current literature was carried out according to a prescribed algorithm, several areas were identified which, in contrast to the predecessor version from September 2014, required new recommendations or statements which took account of more recently published literature and the appraisal of the new evidence. Recommendations The short version of this guideline consists of recommendations and statements on the epidemiology, screening, diagnostic workup and therapy of patients with cervical cancer. The most important new aspects included in this updated guideline include the newly published FIGO classification of 2018, the radical open surgery approach for cervical cancers up to FIGO stage IB1, and use of the sentinel lymph node technique for tumors ≤ 2 cm. Other changes include the use of PET-CT, new options in radiotherapy (e.g., intensity-modulated radiotherapy, image-guided adaptive brachytherapy), and drug therapies to treat recurrence or metastasis.
CRIS-Team Scopus Importer:2022-03-04
Keywords: cervical cancer; cervical intraepithelial neoplasia; follow-up; guideline; therapy

Diagnosis, Therapy and Follow-up of Cervical Cancer. Guideline of the DGGG, DKG and DKH (S3-Level, AWMF Registry No. 032/033OL, May 2021) – Part 2 with Recommendations on Psycho-oncology, Rehabilitation, Follow-up, Recurrence, Palliative Therapy and Healthcare Facilities - Fehm, Tanja; Stübs, Frederik; Koch, Martin; Mallmann, Peter; Dannecker, Christian; Dietl, Anna; Sevnina, Anna; Mergel, Franziska; Lotz, Laura; Hack, Carolin; Ehret, Anne; Gantert, Daniel; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Aim This is an update of the interdisciplinary S3-guideline on the Diagnosis, Therapy and Follow-up of Cervical Cancer (AWMF Registry No. 032/033OL), published in March 2021. The work on the updated guideline was funded by German Cancer Aid (Deutsche Krebshilfe) as part of the German Guideline Program in Oncology. The guideline was coordinated by the German Society of Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG) and the Working Group on Gynecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie, AGO) of the German Cancer Society (Deutsche Krebsgesellschaft, DKG). Method The process used to update the 2014 S3-guideline was based on an appraisal of the available evidence using the criteria of evidence-based medicine, adaptations of existing evidence-based national and international guidelines or - if evidence was lacking - on the consensus of the specialists involved in compiling the update. After an initial review of the current literature was carried out according to a prescribed algorithm, several areas were identified which, in contrast to the predecessor version from September 2014, required new recommendations or statements which would take account of more recently published literature and the recent appraisal of new evidence. Recommendations The short version of this guideline consists of recommendations and statements on palliative therapy and follow-up of patients with cervical cancer. The most important aspects included in this updated guideline are the new FIGO classification published in 2018, the radical open surgery approach used to treat cervical cancer up to FIGO stage IB1, and the use of the sentinel lymph node technique for tumors ≤ 2 cm. Other changes include the use of PET-CT, new options in radiotherapy (e.g., intensity-modulated radiotherapy, image-guided adaptive brachytherapy), and drug therapies to treat recurrence or metastasis.
CRIS-Team Scopus Importer:2022-02-25
Keywords: cervical cancer; cervical intraepithelial neoplasia; follow-up; guideline; therapy

Diagnosis, Therapy and Follow-up of Vaginal Cancer and Its Precursors. Guideline of the DGGG and the DKG (S2k-Level, AWMF Registry No. 032/042, October 2018) - Schnürch, Hans Georg; Ackermann, Sven; Alt-Radtke, Celine D.; Angleitner, Lukas; Barinoff, Jana; Beckmann, Matthias; Böing, Carsten; Dannecker, Christian; Fehm, Tanja; Gaase, Rüdiger; Gaß, Paul; Gebhardt, Marion; et al. (Geburtshilfe und Frauenheilkunde, 2019)
Purpose This is an official guideline, published and coordinated by the Gynecological Oncology Working Group (AGO) of the German Cancer Society (DKG) and the German Society for Gynecology and Obstetrics (DGGG). Vaginal cancers are rare tumors, which is why there is very little evidence on these tumors. Knowledge about the optimal clinical management is limited. This first German S2k guideline on vaginal cancer has aimed to compile the most current expert knowledge and offer new recommendations on the appropriate treatment as well as providing pointers about individually adapted therapies with lower morbidity rates than were previously generally available. The purpose of this guideline is also to set up a register to record data on treatment data and the course of disease as a means of obtaining evidence in future. Methods The present S2k guideline was developed by members of the Vulvar und Vaginal Tumors Commission of the AGO in an independently moderated, structured, formal consensus process and the contents were agreed with the mandate holders of the participating scientific societies and organizations. Recommendations To optimize the daily care of patients with vaginal cancer: 1. Monitor the spread pattern; 2. Follow the step-by-step diagnostic workup based on initial stage at detection; 3. As part of individualized clinical therapeutic management of vaginal cancer, follow the sentinel lymph node protocol described here, where possible; 4. Participate in the register study on vaginal cancer.
CRIS-Team Scopus Importer:2019-11-05
Keywords: sentinel lymph node biopsy; vaginal cancer; VaIN

Diagnostic Accuracy of Breast Medical Tactile Examiners (MTEs): A Prospective Pilot Study - Lux, Michael P.; Emons, Julius; Bani, Mayada; Wunderle, Marius; Sell, Charlotte; Preuss, Caroline; Rauh, Claudia; Jud, Sebastian; Heindl, Felix; Langemann, Hanna; Geyer, Thomas; Brandl, Anna-Lisa; et al. (Breast Care, 2019)
Background: The usefulness of clinical breast examination (CBE) in general and in breast cancer screening programs has been a matter of debate. This study investigated whether adding vision-impaired medical tactile examiners (MTEs) improves the predictiveness of CBE for suspicious lesions and analyzed the feasibility and acceptability of this approach. Methods: The prospective study included 104 patients. Physicians and MTEs performed CBEs, and mammography and ultrasound results were used as the gold standard. Sensitivity and specificity were calculated and logistic regression models were used to compare the predictive value of CBE by physicians alone, MTEs alone, and physicians and MTEs combined. Results: For CBEs by physicians alone, MTEs alone, and both combined, sensitivity was 71, 82, and 89% and specificity was 55, 45, and 35%, respectively. Using adjusted logistic regression models, the validated areas under the curve were 0.685, 0.692, and 0.710 (median bootstrapped p value (DeLong) = 0.381). Conclusion: The predictive value for a suspicious breast lesion in CBEs performed by MTEs in patients without prior surgery was similar to that of physician-conducted CBEs. Including MTEs in the CBE procedure in breast units thus appears feasible and could be a way of utilizing their skills. (c) 2019 S. Karger AG, Basel
CRIS-Team WoS Importer:2019-03-22

Did you drink alcohol during pregnancy? Inaccuracy and discontinuity of women's self-reports: On the way to establish meconium ethyl glucuronide (EtG) as a biomarker for alcohol consumption during pregnancy - Eichler, Anna; Grunitz, Juliane; Grimm, Jennifer; Walz, Lisa; Raabe, Eva; Goecke, Tamme W.; Beckmann, Matthias; Kratz, Oliver; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Kornhuber, Johannes (Alcohol, 2016)
Consuming alcohol during pregnancy is one of the most verified prenatal risk factors for impaired child development. Information about the amount of alcohol consumed prenatally is needed to anticipate negative effects and to offer timely support. Women's self-reports are not reliable, often influenced by social stigmas and retrospective recall bias, causing biomarkers of intrauterine ethanol exposure to become more and more relevant. The present study compares both women's gestational and retrospective self-reports of prenatal alcohol consumption with levels of ethyl glucuronide (EtG) in meconium. Women (n = 180) gave self-reports of prenatal alcohol consumption both during their 3rd trimester (gestational self-report) and when their children were 6-8 years old (retrospective self-report). Child meconium was collected after birth and analyzed for EtG. No individual feedback of children's EtG level was given to the women. All analyses were run separately for two cut-offs: 10 ng/g (limit of detection) and 120 ng/g (established by Goecke et al., 2014). Mothers of children with EtG values above 10 ng/g (n = 42) tended to report prenatal alcohol consumption more frequently. There was no trend or significance for the EtG cut-off of 120 ng/g (n = 26) or for retrospective self-report. When focusing on women who retrospectively reported alcohol consumption during pregnancy, a claim to five or more consumed glasses per month made an EtG over the 10 ng/g and the 120 ng/g cut-off more probable. Women whose children were over the 10 ng/g EtG cut-off were the most inconsistent in their self-report behavior, whereas the consistency in the above 120 ng/g EtG group was higher than in any other group. The next step to establish EtG as a biomarker for intrauterine alcohol exposure is to correlate EtG values in meconium with child developmental impairments.
EVALuna2:23752

Die Bedeutung mütterlicher präpartaler Depression und Mutter-Kind-Bindung für die Entwicklung der kindlichen Emotionsregulation: Erste Befunde einer Längsschnittstudie - Ziegler, Clara; Zalan, Vera; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (50. Jahreskongress der Deutschen Gesellschaft für Psychologie, 2016)

Differential effects of low birthweight and intrauterine growth restriction on umbilical cord blood insulin-like growth factor concentrations - Tzschoppe, Anja; Riedel, Christina; Von Kries, Ruediger; Struwe, Ellen; Rascher, Wolfgang; Dörr, Helmuth-Günther; Beckmann, Matthias; Schild, Ralf L.; Goecke, Tamme W.; Flyvbjerg, Allan; Frystyk, Jan; Doetsch, Joerg (Clinical Endocrinology, 2015)
Alterations in the growth hormone-insulin-like growth factor (IGF) axis have been considered as a causal factor for intrauterine growth restriction (IUGR) and for the increased risk of metabolic disease in later life. We compared members of the IGF axis in umbilical cord blood between IUGR neonates, small for gestational age without foetal restriction (SGA) and appropriate for gestational age (AGA) neonates.Prospective controlled multicenter study.Sixteen ultrasound-proven IUGR, 8 SGA and 40 AGA neonates.Concentrations of total IGF-I and total IGF-II by immunoassays, bioactive IGF by cell-based bioassay and IGFBP-I in mixed venous and arterial umbilical cord blood samples at birth. Auxological parameters at birth.IGF-I concentrations in IUGR [17·7 ?g/l (CI 13·8;21·6)] were clearly below those in AGA [48·3 ?g/l (CI 43·7;52·9)] and SGA neonates [36·0 ?g/l (CI 26·6;45·4)]. IGF-II levels were significantly reduced in IUGR [201·4 ?g/l (CI 190·2;212·6)] compared to AGA neonates [231·2 ?g/l (CI 220·6;241·9)]. A trend for lower IGF-II concentrations was observed in IUGR when compared to SGA neonates [232·0 ?g/l (CI 207·2;256·8)]. These differences could not be explained by confounding. For IGFBP-1, a trend towards higher values in IUGR was observed.Low IGF-I cord blood concentrations in hypotrophic neonates after IUGR might not only result from low birthweight per se, but also reflect prenatal placental environment. Alterations of the IGF axis could be in the causal pathway of IUGR and thus constitute a potential surrogate marker for IUGR in the assessment of foetal programming.
EVALuna2:17440

Differential prognostic relevance of patho-anatomical factors among different tumor-biological subsets of breast cancer: Results from the adjuvant SUCCESS A study - Deniz, Miriam; Degregorio, Amelie; Degregorio, Nikolaus; Bekes, Inga; Widschwendter, Peter; Schochter, Fabienne; Ernst, Kristina; Scholz, Christoph; Bauer, Emanuel C. A.; Aivazova-Fuchs, Viktoria; Weissenbacher, Tobias; Kost, Bernd; et al. (BREAST, 2019)
Objectives: In breast cancer, large tumor size, positive nodal stage and a triple-negative tumor subtype are associated with reduced survival, but the interactions between these prognostic factors are not well understood.
CRIS-Team WoS Importer:2019-03-20

Digital Maternity Records: Motivation, Acceptance, Requirements, Usability and Prototype Evaluation of an Interface for Physicians and Midwives - Dörflinger, Luisa; Nissen, Michael; Jäger, Katharina; Wirth, Markus; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Beckmann, Matthias; Gradl, Stefan; Eskofier, Björn (Mensch und Computer 2021, 2021)
Maternity records (”Mutterpass”) are a central tool in Germany’s antenatal care. Its digitalisation offers advantages such as improved readability, data standardisation, analysability, digital assistance and the avoidance of media breaks. Despite the examined necessity and technical possibility, no system has been implemented yet. In this work, we address this gap by assessing physicians’ and midwives’ perception, motivation, acceptance and requirements of a digital maternity record and its user interface in particular. Nine medical professionals participated in semi-structured interviews. Based on the results, an interface prototype was subsequently developed. The prototype laid a particular focus on two different gravidogram implementations. Thirteen medical professionals participated in the interactive user interface study, which aimed to assess general acceptance, completion time, error rate and implemented assistance functions compared to the analogue counterpart. Results show that the implementation of the digital maternity logbook is of value and that its advantages are both accepted and demanded by medical professionals. Eight key requirements were identified. A tabular gravidogram prototype, inspired by the analogue maternity record, was favoured over a more novel list prototype. Users presented a clear learning curve of the digital system. Nevertheless, the digital average completion time is 30% higher than its analogue counterpart. The digital prototype lead to a lower average number of errors per entry (0.45±0.3 vs. 0.58±0.4). With respect to digital maternity records, this work underlines user acceptance, summarizes key user requirements and presents a first step on the path to a digital maternity record interface for medical professionals. On a broader scale, it delivers insights based on several metrics with respect to digitalisation in an area that is still highly dominated by long established paper-based tools.

Digit ratio (2D:4D) and behavioral symptoms in primary-school aged boys - Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Beckmann, Matthias; Goecke, Tamme W.; Fasching, Peter; Muschler, Marcel-Rene; Bouna-Pyrrou, Polyxeni; Lenz, Bernd; Kornhuber, Johannes (Early Human Development, 2018)
The second-to-forth digit length ratio (2D:4D) is considered to be a biomarker for intrauterine androgen levels. It is associated with adult and child mental health problems, primarily with behavioral symptoms and predominantly in males. Using a cross-sectional design, we examined whether 2D:4D was associated with conduct disorder (CD) symptoms in 138 primary-school aged children (54% boys, Mage = 7.70 years) and considered child sex as a moderating factor. Children's digit lengths were measured from hand scans and mothers rated the behavioral/emotional symptoms of their child. The regression analyses revealed that 2D:4D ratios were associated with behavioral symptoms in boys (β = -0.260, p = 0.026), but not in girls (β = -0.040, p = 0.762). Child emotional symptoms, analyzed as a control, were not significantly correlated with 2D:4D. In conclusion, prenatal brain hyperandrogenization - operationalized by the 2D:4D biomarker - could result in behavioral symptoms in boys at early school age, reflecting one predictor for early onset CD. Our data support the use of 2D:4D as a marker of prenatal androgen exposure.
EVALuna2:36369

Discordance between Primary Breast Cancer and Ipsilateral Breast Cancer Tumor Recurrence as a Function of Distance - Jud, Sebastian; Hatko, Reinhard; Emons, Julius; Lauterbach, Bianca; Hack, Carolin; Preuss, Caroline; Adler, Werner; Beckmann, Matthias; Heindl, Felix (Journal of Clinical Medicine, 2020)
Background: Risk factors for ipsilateral breast cancer tumor recurrence (IBTR) are well established and include grading, nodal status, and receptor status. Little is known about the influence of the local distance between the primary tumor and recurrences on changes in tumor characteristics and prognosis. Methods: In a retrospective setting, we analyzed primary breast cancers and their recurrences. Localizations of primary and recurrent breast cancer were recorded to calculate the relative distance in pixels. Analysis was performed regarding tumor characteristics, relative distance between both, and their impact on breast cancer prognosis. Results: In a cohort of 142 patients with ipsilateral recurrence, no statistically significant difference could be shown in the change in tumor characteristics depending on distance. Progesterone receptor (PR) and estrogene receptor (ER) status changed in 22.7% and 14.9% of cases, respectively. human epidermal growth factor receptor 2 (ERBB2, HER2) status changed in 18.3% of cases. Survival was in accordance with the literature, with luminal-A-like tumors as best and triple negative breast cancers (TNBC) as worst prognosis. With a threshold of 162 pixels, the survival was significantly better in the group with shorter distance. Conclusion: Change in tumor characteristics from primary breast cancer to recurrence occurs more often in PR than ER. In contrast to other work, in this dataset, recurrences with a larger distance to the primary tumor had a worse prognosis in univariate analysis. A Cox model might indicate the possibility that this influence is independent of other risk factors.
CRIS-Team WoS Importer:2021-01-15

Discourse Is Research at German University Clinics still desirable, possible and effective? - Summary of the Discussion Forum at the 61st DGGG-Congress 2016 in Stuttgart - Puppe, Julian; Schott, Sarah; Eismann, Sabine; Tzschaschel, Marie; Rody, Achim; Woeckel, Achim; Lermann, Johannes; Gabriel, Lena; Beckmann, Matthias; Gaß, Paul (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36135

Disseminated tumour cells from the bone marrow of early breast cancer patients: Results from an international pooled analysis - Hartkopf, Andreas D.; Brucker, Sara Y.; Taran, Florin Andrei; Harbeck, Nadia; von Au, Alexandra; Naume, Bjørn; Pierga, Jean Yves; Hoffmann, Oliver; Beckmann, Matthias; Rydén, Lisa; Fehm, Tanja; Aft, Rebecca; et al. (European Journal of Cancer, 2021)
Purpose: Presence of disseminated tumour cells (DTCs) in the bone marrow (BM) has been described as a surrogate of residual disease in patients with early breast cancer (EBC). PADDY (Pooled Analysis of DTC Detection in Early Breast Cancer) is a large international analysis of pooled data that aimed to assess the prognostic impact of DTCs in patients with EBC. Experimental design: Individual patient data were collected from 11 centres. Patients with EBC and available follow-up data in whom BM sampling was performed at the time of primary diagnosis before receiving any anticancer treatment were eligible. DTCs were identified by antibody staining against epithelial cytokeratins. Multivariate Cox regression was used to compare the survival of DTC-positive versus DTC-negative patients. Results: In total, 10,307 patients were included. Of these, 2814 (27.3%) were DTC-positive. DTC detection was associated with higher tumour grade, larger tumour size, nodal positivity, oestrogen receptor and progesterone receptor negativity, and HER2 positivity (all p < 0.001). Multivariate analyses showed that DTC detection was an independent prognostic marker for overall survival, disease-free survival and distant disease-free survival with hazard ratios (HR) and 95% confidence intervals (CI) of 1.23 (95% CI: 1.06–1.43, p = 0.006), 1.30 (95% CI: 1.12–1.52, p < 0.001) and 1.30 (95% CI: 1.08–1.56, p = 0.006), respectively. There was no association between locoregional relapse-free survival and DTC detection (HR 1.21; 95% CI 0.68–2.16; p = 0.512). Conclusions: DTCs in the BM represent an independent prognostic marker in patients with EBC. The heterogeneous metastasis-initiating potential of DTCs is consistent with the concept of cancer dormancy.
CRIS-Team Scopus Importer:2021-07-23
Keywords: Bone marrow; Disseminated tumour cells; Early breast cancer; Micrometastases; Prognosis; Tumour staging

DNA methylation outliers in normal breast tissue identify field defects that are enriched in cancer - Teschendorff, Andrew E.; Gao, Yang; Jones, Allison; Rübner, Matthias; Beckmann, Matthias; Wachter, David; Fasching, Peter; Widschwendter, Martin (Nature Communications, 2016)
Identifying molecular alterations in normal tissue adjacent to cancer is important for understanding cancer aetiology and designing preventive measures. Here we analyse the DNA methylome of 569 breast tissue samples, including 50 from cancer-free women and 84 from matched normal cancer pairs. We use statistical algorithms for dissecting intra- and inter-sample cellular heterogeneity and demonstrate that normal tissue adjacent to breast cancer is characterized by tens to thousands of epigenetic alterations. We show that their genomic distribution is non-random, being strongly enriched for binding sites of transcription factors specifying chromatin architecture. We validate the field defects in an independent cohort and demonstrate that over 30% of the alterations exhibit increased enrichment within matched cancer samples. Breast cancers highly enriched for epigenetic field defects, exhibit adverse clinical outcome. Our data support a model where clonal epigenetic reprogramming towards reduced differentiation in normal tissue is an important step in breast carcinogenesis.
EVALuna2:6810

Documentation in Gynaecologic Oncology: Conflicts between quality management, science, efficacy, and liability Dokumentation in der gynäkologischen Onkologie: Im Spannungsfeld zwischen Qualitätssicherung und Wissenschaft, Ergonomie und Rechtssicherheit - Beckmann, K.; Jud, Sebastian; Hein, Alexander; Heusinger, K.; Bayer, Christian M.; Schwenk, M.; Häberle, Lothar; Beckmann, Matthias (Gynäkologe, 2010)
The rapid growth in medical documentation seen in recent decades has affected gynaecologic oncology as well. Particularly for malignant disorders the need for longitudinal and horizontal documentation, centralisation, guideline conformity, and quality management requires dealing with huge stores of data, often in different systems together (mammography screening, internal patient files, DMP, BQS/AQUA, studies, etc). Thanks in part to these redundancies, the mass of data can take on gigantic proportions. Some relief might be found from increased digitalisation, standardisation, and centralisation urged in the new German National Cancer Plan, mainly with respect to repeat data. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Cancer registers; German National Cancer Plan; Quality management; Therapy guidelines

Documentation Time and Effort and Associated Resources for Patients with Primary Breast Cancer from Diagnosis to End of Follow-Up - Results of a Multicentre Validation - Beckmann, Matthias; Sell, C.; Aydogdu, M.; Brucker, S. Y.; Fehm, T.; Janni, W.; Kreienberg, R.; Kuemmel, S.; Neumann, M.; Scharl, A.; Schleicher, B.; Wallwiener, D.; et al. (Gesundheitswesen, 2016)
INTRODUCTION: Tumour documentation is essential for quality assurance of oncological therapies and as a source of reliable information about the in- and outpatient care. The documentation effort and the associated resource consumption were analysed for the example of breast cancer. MATERIAL AND METHODS: The different steps in the care of patients with primary breast cancer in a standardised disease situation were defined from initial diagnosis to the end of the follow-up. After the pilot phase, a multicentre validation (n=7 centres) was performed with the support of the Federal Ministry of Health. The documentation time points were horizontally collected and analysed with regard to amount, duration and personnel expenses. RESULTS: 57% of the documentation costs are caused by the physicians. Regarding the different centres, documentation costs were calculated between € 352.82 and € 1 084.08 per patient from diagnosis to completion of aftercare. Non-certified centres had a reduced documentation effort and thus lower costs. CONCLUSIONS: The results demonstrate the need for a reduction of the documentation effort - particularly for physicians - the most expensive profession in the health system. A quality improvement is expected from the certification with its special requirements. In this context, there is a justified demand for an adequate remuneration of the documentation effort for certified centres. Furthermore, it is necessary to reduce the number of variables for quality assurance and to define them centrally. A comprehensive multi-disciplinary documentation should be achieved. Investments in a single data set and interface enhancements of existing documentation systems should be realised.
EVALuna2:33544

Does Anti-Müllerian hormone vary during a menstrual cycle? A systematic review and meta-analysis - Khodavirdilou, Rasa; Pournaghi, Marjaneh; Rastgar Rezaei, Yeganeh; Hajizadeh, Khadijeh; Khodavirdilou, Lida; Javid, Farzin; Hamdi, Kobra; Shahnazi, Mahnaz; Nouri, Mohammad; Fattahi, Amir; Beckmann, Matthias; Dittrich, Ralf (Journal of Ovarian Research, 2022)
Objective: Numerous studies have indicated that the level of the Anti-Müllerian hormone (AMH), one of the main markers for the ovarian reserve, does not fluctuate throughout a menstrual cycle, while some studies have rejected this finding. The purpose of this systematic and meta-analysis study is to consensus on all contradictory studies that have measured AMH levels throughout the menstrual cycle and to investigate the exact extent of AMH variation in a cycle. Methods: The protocol for this meta-analysis was registered at PROSPERO before data extraction. Relevant studies were identified by systematic search in PubMed, ScienceDirect, Embase, Cochrane Library, and Google Scholar with no limitation on publication date. Longitudinal studies which have evaluated AMH levels in the follicular and luteal phases of an unstimulated (natural) menstrual cycle in healthy women without endocrinology or ovarian disorders were included. We used the JBI Critical Appraisal Checklist for assessing the quality of studies found eligible for meta-analysis. Results: A total of 11 studies involving 733 women with regular menstrual cycles were included. The results showed that the AMH level in the follicular phase was significantly higher than in the luteal phase (95% Cl = 0.11 [0.01 to 0.21]; p < 0.05) and it varies about 11.5% from the luteal phase. The analysis of studies which had also examined the ovulatory phase (n = 380) showed that the serum levels of AMH in the ovulatory phase (about 2.02 ng/ml) did not significantly vary compared to follicular (95% Cl = 0.11 [-0.10 to 0.33]; p = 0.30) and luteal (95% Cl = 0.06 [-0.08 to 0.20]; p = 0.43) phases. Conclusions: According to the results of this study, AMH levels differ between follicular and luteal phases which might be due to ovarian response to the gonadotropins. It seems the phase of AMH measurement needs to be considered for interpretation of the serum AMH test.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Anti mullerian hormone; Fullicular phase; Luteal phase; Menstrual cycle; Meta-analysis; Ovulation; Systematic review

Does anxiety impact the neural processing of child faces in mothers of school-aged children? An ERP study using an emotional Go/NoGo task - Kungl, Melanie; Rutherford, Helena J.V.; Heinisch, Christine; Beckmann, Matthias; Fasching, Peter; Spangler, Gottfried (Social Neuroscience, 2020)
Maternal anxiety during pregnancy and the early postpartum period is associated with heightened neural processing of neutral infant faces as measured by event-related potentials (ERPs). However, less is known about how anxiety shapes neural face processing in mothers of older children. In our study, 36 mothers of 8–10 year old children completed a Go/NoGo task consisting of neutral and emotional (happy, fearful) facial expressions posed by unfamiliar school-aged children while EEG was recorded. Higher levels of maternal anxiety -indexed via self-report- were associated with delayed behavioral responses to children’s fearful faces and increased N170 and LPP amplitudes elicited by children’s neutral faces. While anxiety was also positively related to the LPP elicited by children’s emotional faces, it only led to increased N170 amplitude responses to children’s fearful, but not happy, faces and only when they were NoGo cues. The study replicates and extends prior findings examining the impact of maternal anxiety on neural responses to neutral infant faces to later stages of parenting with further neural markers and emotional expressions being affected. Findings evidence the importance of studying these associations beyond infancy to increase our knowledge about processes potentially underlying the relation between anxiety and less optimal parenting across development.
CRIS-Team Scopus Importer:2020-07-24
Keywords: EEG/ERP; emotional faces; Go/NoGo task; LPP; Maternal anxiety; N170

Does differential HLA-E and -F expression cause an aberrant immune tolerance in preeclampsia and HELLP? - Würfel, Franziska; Hübner, Hanna; Strick, Reiner; Fasching, Peter; Beckmann, Matthias; Wuerfel, Wolfgang; Rübner, Matthias (2016)
EVALuna2:32977

Does Induction of Labor for Preterm Premature Rupture of Membranes at 34 Weeks of Gestation Increase the Risk for Cesarean Section Erhöht die Geburtseinleitung wegen eines frühen vorzeitigen Blasensprungs ab 34+0 SSW das Risiko für einen Kaiserschnitt - Puhl, Alexander; Weiss, Christel; Schneid, Anna; Zahn, Eva; Kraft, Katrina; Pretscher, Jutta; Faschingbauer, Florian; Beckmann, Matthias; Kehl, Sven (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Purpose Induction of labor at 34 weeks of gestation is often linked to increased risk for cesarean section. Recently, the PPROMT trial demonstrated a higher cesarean section rate when labor wasinduced for preterm premature rupture of membranes (PPROM). The purpose of this study was thereforeto evaluate the success rate of induction of labor for PPROM at 34 and 35 weeks of gestation in comparison with a higher gestational age. Material and Methods In this historic cohort study, cases with labor inductions for PPROM ≥ 34 weeks of gestation were included. Induction of labor at 34 and 35 weeks of gestation (group 1) were compared with those performed at 36 weeks (group 2) and 37 weeks (group 3). Induction of labor was started 12 to 24 hours after (preterm) premature rupture of membranes. Antibiotics were given routinely. The primary outcome was the rate of cesarean section. Results There were significantly more cesarean sections in group 3 in comparison with group 2 (7 vs. 25, p=0.0136). However, univariable and multiple logistic regression analysis of the primary outcome measure showed that there was no impact of the group affiliation on cesarean section rate. Significant parameters influencing the risk of cesarean section were body mass index and Bishop score. Conclusion Induction of labor for PPROM at 34 weeks of gestation is not associated with an increased rate of cesarean section.
CRIS-Team Scopus Importer:2020-11-06
Keywords: induction of labor; moderate preterm birth; premature rupture of membranes; preterm premature rupture of membranes

Does it make sense to refreeze ovarian tissue after unexpected occurrence of endometriosis when transplanting the tissue? - Dietl, Anna; Dittrich, Ralf; Hoffmann, Inge; Denschlag, Dominik; Hanjalic-Beck, Aida; Muller, Andreas; Beckmann, Matthias; Lotz, Laura (Journal of Ovarian Research, 2022)
Background: Ovarian insufficiency is a major concern for long-term cancer survivors. Ovarian tissue cryopreservation for fertility preservation is an emerging technique that has proven successful over the past decade through transplantation of frozen-thawed ovarian tissue. Compared to other established techniques, such as oocyte freezing, ovarian tissue cryopreservation preserves actual organ function and thus the production of sex hormones. Endometriosis in perimenopausal women is rare, however it can be surprising diagnosis in the planned transplantation of cryopreserved ovarian tissue and the already thawed tissue may not be transplanted, so that it has to be refrozen. Results: Ovarian function returned in the patient two months after transplantation, as shown by estrogen production. Ten months after the ovarian tissue transplantation mild stimulation with FSH was initiated in accordance with a low-dose protocol. When ultrasonography revealed a follicle 17 mm in size in the ovarian graft, hCG was added and after follicular puncture one oocyte was obtained. The oocyte could be fertilized by IVF and transferred to the uterus. On day 14 after embryo-transfer, a positive hCG-Level was detected and after an uncomplicated pregnancy a healthy child was delivered. Conclusions: We report the first pregnancy and live birth achieved using transplantation of thawed and refrozen ovarian tissue in a woman treated by chemotherapy and subsequent endometriosis surgery. Refreezing of cryopreserved ovarian tissue is not a hindrance to successful transplantation of ovarian tissue. Against the background of increasing numbers of candidates for transplantation of ovarian tissue is expected that the combination chemotherapy followed by endometriosis will increase.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Cancer; Chemotherapy; Cryopreservation; Endometriosis; Fertility preservation; Iatrogenic ovarian failure; Ovarian tissue transplantation; Refreezing

Does stimulation with human gonadotropins and gonadotropin-releasing hormone agonist enhance and accelerate the developmental capacity of oocytes in human ovarian tissue xenografted into severe combined immunodeficient mice? - Lotz, Laura; Schneider, Heike; Hackl, Janina; Wachter, David; Hoffmann, Inge; Jurgons, Roland; Beckmann, Matthias; Dittrich, Ralf (Fertility and Sterility, 2014)
To assess the capacity of human frozen-thawed ovarian follicles matured in xenografts to form metaphase II (MII) oocytes after xenotransplantation and exogenous stimulation.Prospective controlled animal study.University hospital gynecology research unit.Ovarian fragments were obtained from 17 women with malignant diseases who wished to cryopreserve ovarian tissue for later pregnancy before chemotherapy.Eighty-eight female severe combined immunodeficient (SCID) mice.Cryopreserved human ovarian tissue was grafted into oophorectomized SCID mice. The mice were divided into three groups: Group A received hMG alone every 2 days for a maximum of 24 weeks; group B additionally received nRH agonist (GnRHa) every 4 weeks; and group C was an untreated control group.Follicular density, morphology, proliferation, oocyte maturation, malignant cell contamination.Follicle survival and development were similar in all three groups. No significant interactions between the stimulation protocols and grafting duration were noted. Three MII oocytes were observed in grafted follicles. Two MII oocytes were harvested without stimulation. None of the mice showed signs of reintroduced malignancy, nor did microscopic evaluation of the grafts raise any suspicion of residual malignant disease.After xenotransplantation, human primordial follicles can be matured to MII oocytes even without stimulation. Administering human gonadotropin and GnRHa does not enhance the developmental capacity of xenografted oocytes. The optimal stimulation schedule for grafted tissue remains unknown.
EVALuna2:6659

Dose adjustment of cisplatin, etoposide, and ifosfamide according to kidney function: a retrospective analysis and implications for medication safety - Grafe, Carolin; Semrau, Sabine; Hein, Alexander; Beckmann, Matthias; Mackensen, Andreas; Dörje, Frank; Fromm, Martin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)
Clearance of cisplatin, etoposide, and ifosfamide depends on kidney function and dosages should be adjusted in patients with renal impairment. However, there is still limited data on the adherence of physicians to dosing recommendations for these drugs in cancer patients with renal impairment. Three thousand four hundred forty-eight prescriptions to 369 patients, treated in the Comprehensive Cancer Center of a German university hospital, were retrospectively evaluated. The administered relative doses of cisplatin, etoposide, and ifosfamide were compared with relative doses recommended at the time of prescription according to the patients' creatinine clearance. Cisplatin is contraindicated according to two German summary of product characteristics (SmPC) in patients with a creatinine clearance < 60 mL/min. Nevertheless, 37 cisplatin prescriptions were made for this group of patients (i.e., 2.0% of all cisplatin prescriptions). According to one German SmPC (valid in the year of data analysis), etoposide dosage should be reduced in patients with a creatinine clearance from 15 to 50 mL/min, while it is contraindicated below 15 mL/min. Thirteen etoposide prescriptions were without dose reduction in patients with creatinine clearance from 15 to 50 mL/min (1.5% of all etoposide prescriptions); one patient received etoposide with creatinine clearance below 15 mL/min. In 8.9% of ifosfamide prescriptions, patients did not receive a reduced dose in spite of respective recommendations. Dosages of cisplatin, etoposide, and ifosfamide are not always adjusted as recommended in patients with renal impairment. Consistent international dosing recommendations (e.g., in SmPCs), preferentially included in clinical decision support systems, should be developed to tackle this problem.
EVALuna2:25784

Dose-Response Association of CD8+ Tumor-Infiltrating Lymphocytes and Survival Time in High-Grade Serous Ovarian Cancer - Goode, Ellen L.; Block, Matthew S.; Kalli, Kimberly R.; Vierkant, Robert A.; Chen, Wenqian; Fogarty, Zachary C.; Gentry-Maharaj, Aleksandra; Toloczko, Aleksandra; Hein, Alexander; Bouligny, Aliecia L.; Jensen, Allan; Osorio, Ana; et al. (JAMA Oncology, 2017)
Importance: Cytotoxic CD8+ tumor-infiltrating lymphocytes (TILs) participate in immune control of epithelial ovarian cancer; however, little is known about prognostic patterns of CD8+ TILs by histotype and in relation to other clinical factors. Objective: To define the prognostic role of CD8+ TILs in epithelial ovarian cancer. Design, Setting, and Participants: This was a multicenter observational, prospective survival cohort study of the Ovarian Tumor Tissue Analysis Consortium. More than 5500 patients, including 3196 with high-grade serous ovarian carcinomas (HGSOCs), were followed prospectively for over 24 650 person-years. Exposures: Following immunohistochemical analysis, CD8+ TILs were identified within the epithelial components of tumor islets. Patients were grouped based on the estimated number of CD8+ TILs per high-powered field: negative (none), low (1-2), moderate (3-19), and high (≥20). CD8+ TILs in a subset of patients were also assessed in a quantitative, uncategorized manner, and the functional form of associations with survival was assessed using penalized B-splines. Main Outcomes and Measures: Overall survival time. Results: The final sample included 5577 women; mean age at diagnosis was 58.4 years (median, 58.2 years). Among the 5 major invasive histotypes, HGSOCs showed the most infiltration. CD8+ TILs in HGSOCs were significantly associated with longer overall survival; median survival was 2.8 years for patients with no CD8+ TILs and 3.0 years, 3.8 years, and 5.1 years for patients with low, moderate, or high levels of CD8+ TILs, respectively (P value for trend = 4.2 × 10−16). A survival benefit was also observed among women with endometrioid and mucinous carcinomas, but not for those with the other histotypes. Among HGSOCs, CD8+ TILs were favorable regardless of extent of residual disease following cytoreduction, known standard treatment, and germline BRCA1 pathogenic mutation, but were not prognostic for BRCA2 mutation carriers. Evaluation of uncategorized CD8+ TIL counts showed a near-log-linear functional form. Conclusions and Relevance: This study demonstrates the histotype-specific nature of immune infiltration and provides definitive evidence for a dose-response relationship between CD8+ TILs and HGSOC survival. That the extent of infiltration is prognostic, not merely its presence or absence, suggests that understanding factors that drive infiltration will be the key to unraveling outcome heterogeneity in this cancer.
EVALuna2:34270

Double-balloon catheter and sequential oral misoprostol versus oral misoprostol alone for induction of labour at term: a retrospective cohort study - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Heimrich, Jutta; Beckmann, Matthias; Faschingbauer, Florian; Suetterlin, Marc (European Journal of Obstetrics Gynecology and Reproductive Biology, 2016)
OBJECTIVE: To evaluate the efficacy of induction of labour using a double-balloon catheter and, if necessary, sequential oral misoprostol without delay after removal of the catheter, in comparison with oral misoprostol alone. STUDY DESIGN: This retrospective cohort study included women undergoing induction of labour with oral misoprostol or double-balloon catheter with sequential oral misoprostol in singleton pregnancies at term. The catheter was placed in the evening and removed when there was no onset of labour within 12h. Then oral misoprostol was started within 3h. Primary outcome measure was the caesarean section rate. RESULTS: There were 13,082 deliveries during the study period with 3466 labour inductions out of which 1032 were eligible and analysed. The caesarean section rate was significantly lower in the double-balloon catheter group (26.1% vs. 17.3, p=0.021). Furthermore, in the combination group, the induction-to-delivery interval was shorter (median values 1144 vs. 1365min, p=0.001) and there were more deliveries within 24h (51.9 vs. 64.7%, p=0.003) and 48h (87.4 vs. 95.8%, p=0.002). When stratifying for parity, there were less caesarean sections in the combination group (37.2% vs. 24.2%, p=0.015) in nulliparous women, too. In both, nulliparous and parous women, the induction-to-delivery interval was shorter (1742 vs. 1400min, 0.005; 1020 vs. 912min, p=0.018). Especially in parous women, the rates of delivery within 24h (62.6% vs. 79.0%, p=0.007) and 48h (88.6% vs. 99.0%, p=0.007) were higher in the combination group. CONCLUSION: Double-balloon catheter and sequential oral misoprostol without long delay in absent onset of labour after removal of the catheter resulted in less caesarean section and shorter induction-to-delivery interval in comparison with oral misoprostol alone.
EVALuna2:32958

Double-balloon catheter and sequential vaginal prostaglandin E2 versus vaginal prostaglandin E2 alone for induction of labor after previous cesarean section - Kehl, Sven; Weiss, Christel; Wamsler, Michael; Beyer, Jana; Dammer, Ulf; Heimrich, Jutta; Faschingbauer, Florian; Suetterlin, Marc; Beckmann, Matthias; Schleussner, Ekkehard (Archives of Gynecology and Obstetrics, 2016)
PURPOSE: To evaluate the efficacy of inducing labor using a double-balloon catheter and vaginal prostaglandin E2 (PGE2) sequentially, in comparison with vaginal PGE2 alone after previous cesarean section. METHODS: A total of 264 pregnant women with previous cesarean section undergoing labor induction at term were included in this prospective multicentre cohort study. Induction of labor was performed either by vaginal PGE2 gel or double-balloon catheter followed by vaginal PGE2. The primary outcome measure was the cesarean section rate. RESULTS: The cesarean section rate was 37 % without any statistically significant difference between the two groups (PGE2: n = 41, 37 % vs. balloon catheter/PGE2: n = 41, 42 %; P = 0.438). The median (range) number of applications of PGE2 [2 (1-10) versus 1 (0-8), P < 0.001] and the total amount of PGE2 used in median (range) mg [2 (1-15) vs. 1 (0-14), P = 0.001] was less in the balloon catheter/PGE2 group. Factors significantly increasing risk for cesarean section were "no previous vaginal delivery" (OR 5.391; CI 2.671-10.882) and "no oxytocin augmentation during childbirth" (OR 2.119; CI 1.215-3.695). CONCLUSIONS: The sequential application of double-balloon catheter and vaginal PGE2 is as effective as the sole use of vaginal PGE2 with less applications and total amount of PGE2.
EVALuna2:32988

Editor's Comment on the Review of the German IVF Register and the Subsequent Discussion - Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32975

Effect of Premature Rupture of Membranes on Induction of Labor: A Historical Cohort Study - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Baier, Friederike; Faschingbauer, Florian; Beckmann, Matthias; Suetterlin, Marc; Pretscher, Jutta (Geburtshilfe und Frauenheilkunde, 2017)
Objective: The aim of this study was to assess the influence of premature rupture of membranes (PROM) on the induction of labor. Material and Method: This historical cohort study analyzed 1861 inductions of labor at term using misoprostol which occurred between 2010 and 2015. Exclusion criteria included intrauterine fetal death, previous cesarean section, and fetal structural or chromosomal anomalies. Induction of labor for PROM (PROM group) was compared to induction for other indications (no-PROM group); the primary outcome measure was the cesarean section rate. Results: The cesarean section rate for the PROM group was significantly lower (21.9% vs. 26.3%, p = 0.029). The induction-to-delivery interval was shorter (mean: 972 [854 - 6734] min vs. 1741 [97 - 10 834] min, p < 0.0001) and the rates of vaginal birth within 24 hours (80.9 vs. 52.0%, p = 0.0001) and 48 hours (98.4 vs. 85.3%, p = 0.0001) were higher in the PROM group. The impact of PROM on the cesarean section rate was not significant in multivariate analysis; however, PROM was found to have the greatest effect on the induction-to-delivery interval (p < 0.0001). Conclusion: Premature rupture of membranes significantly affects various outcome measures when delivery is induced, particularly the induction-to-delivery interval.
EVALuna2:36121

Effects of an App-Based Mindfulness Intervention during Pregnancy on the Infant’s Prenatal Androgen Exposure: A Randomized Controlled Pilot Trial - Siegmann, Eva-Maria; Eichler, Anna; Buchholz, Verena Nadine; Gerlach, Jennifer; Pontones, Constanza; Titzmann, Adriana; Arnaud, Nicolas; Consortium, Imac Mind; Mühle, Christiane; Beckmann, Matthias; Fasching, Peter; Kratz, Oliver; et al. (Journal of Clinical Medicine, 2023)
Prenatal androgen exposure modulates the development of the brain, with lasting effects on its function and behavior over the infant’s life span. Environmental factors during pregnancy, in particular maternal stress, have been shown to influence the androgen load of the unborn child. We here addressed the research gap on whether a mindfulness intervention or a pregnancy education administered to pregnant women more affects the androgen exposure of the unborn child (quantified by the proxies of second-to-fourth digit length ratio (2D:4D) and anogenital distance assessed one year after delivery and at delivery, respectively). Moreover, we tested the mindfulness intervention’s effects on maternal perceived stress, anxiety, depressiveness, and mindfulness. Pregnant women (gestation weeks 8–14) were randomized to a 15-week app-based mindfulness-oriented intervention (N = 72) or a pregnancy education intervention (control condition; N = 74). The mindfulness-oriented group did not significantly differ from the pregnancy education group in infants’ 2D:4D or anogenital distance (partial η2 ≤ 0.01) or in maternal stress, anxiety, depressiveness, or mindfulness. However, the descriptive results indicate that across pregnancy, stress and anxiety decreased and mindfulness increased in both groups. Overall, this study did not show that the mindfulness intervention (relative to the pregnancy education) reduced the prenatal androgen exposure of the unborn children or improved the maternal outcomes significantly.
CRIS-Team Scopus Importer:2023-10-20
Keywords: digit ratio; mindfulness; prenatal programming

Effects of interactions between progesterone and prostaglandin on uterine contractility in a perfused swine uterus model - Kuenzel, Julian; Geisler, Klaudija; Maltaris, Theodoros; Mueller, Andreas; Hoffmann, Inge; Schneider, Heike; Beckmann, Matthias; Dittrich, Ralf; Oppelt, Patricia (In Vivo, 2014)
Uterine quiescence at the time of embryo transfer is a prerequisite for successful in vitro fertilization (IVF). This study assessed whether prostaglandin-induced contractions in the perfused swine uterus can be reduced by progesterone.Fifty-eight non-pregnant swine uteri were perfused using an established extracorporeal perfusion model. Intrauterine pressure changes during perfusion with prostaglandin (PG) administration (PGE1, PGE2, PGF2?) and progesterone (1 pg/ml, 10 pg/ml, 25 pg/ml, 50 pg/ml) were assessed using an intrauterine double-chip microcatheter.The contraction-stimulating effect of PGs was clearly reduced by progesterone. Only PGE1 still triggered relevant contractions during continuous perfusion with progesterone solution, up to a concentration of 10 pg/ml. With PGE2 and PGF2?, a clear reduction of uterine contractility was observed even at at a progesterone concentration of 1 pg/ml.The extracorporal perfusion model of swine uteri shows that PG-induced contractions can be reduced in a dose-dependent manner by progesterone.
EVALuna2:17462

Effects of prenatal alcohol consumption on cognitive development and ADHD-related behaviour in primary-school age: a multilevel study based on meconium ethyl glucuronide - Eichler, Anna; Hudler, Linda; Grunitz, Juliane; Grimm, Jennifer; Raabe, Eva; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Heinrich, Hartmut (The journal of child psychology and psychiatry, 2018)
BACKGROUND: Alcohol intake during pregnancy is considered to be a risk factor for child development. Child biomarkers of intrauterine alcohol exposure have been rarely studied. We investigated whether a meconium alcohol metabolite (ethyl glucuronide, EtG) was associated with cognitive development, ADHD-related behaviour and neurophysiological markers of attention and executive control of children at primary-school age. METHODS: Mothers provided self-report on prenatal alcohol consumption during their 3rd trimester. Meconium samples were collected at birth. A total of 44 children with a meconium EtG above the detection limit (≥10 ng/g) and 44 nonexposed matched controls were compared. A second threshold (≥154 ng/g) was applied to study the dose effects. When children reached primary-school age, mothers rated ADHD-related behaviour, child cognitive development was measured using an IQ test battery, and event-related potentials were recorded during a cued go/nogo task. RESULTS: Children in both EtG-positive groups allocated fewer attentional resources than controls to the go/nogo task (reduced P3 component in go-trials). Children with a meconium EtG above 154 ng/g were also found to have an IQ that was six points lower than the other groups. Within the EtG ≥ 154 ng/g group, there was a positive correlation between EtG value and ADHD-related behaviour. These significant effects were not observed in relation to the maternal self-report data. CONCLUSIONS: Associations between EtG and cognitive deficits, attentional resource capacity and ADHD-related behaviour could be documented with effects that were partially dose-dependent. In addition to maternal self-reports, this biomarker of intrauterine alcohol exposure may be considered as a predictor of child development.
EVALuna2:33526

Effects of whole-body electromyostimulation combined with individualized nutritional support on body composition in patients with advanced cancer: a controlled pilot trial - Schink, Kristin; Herrmann, Hans J.; Schwappacher, Raphaela; Meyer, Julia; Orlemann, Till; Waldmann, Elisabeth; Wullich, Bernd; Kahlmeyer, Andreas; Fietkau, Rainer; Lubgan, Dorota; Beckmann, Matthias; Hack, Carolin; et al. (BMC Cancer, 2018)
BACKGROUND: Physical exercise and nutritional treatment are promising measures to prevent muscle wasting that is frequently observed in advanced-stage cancer patients. However, conventional exercise is not always suitable for these patients due to physical weakness and therapeutic side effects. In this pilot study, we examined the effect of a combined approach of the novel training method whole-body electromyostimulation (WB-EMS) and individualized nutritional support on body composition with primary focus on skeletal muscle mass in advanced cancer patients under oncological treatment. METHODS: In a non-randomized controlled trial design patients (56.5% male; 59.9 ± 12.7 years) with advanced solid tumors (UICC III/IV, N = 131) undergoing anti-cancer therapy were allocated to a usual care control group (n = 35) receiving individualized nutritional support or to an intervention group (n = 96) that additionally performed a supervised physical exercise program in form of 20 min WB-EMS sessions (bipolar, 85 Hz) 2×/week for 12 weeks. The primary outcome of skeletal muscle mass and secondary outcomes of body composition, body weight and hand grip strength were measured at baseline, in weeks 4, 8 and 12 by bioelectrical impedance analysis and hand dynamometer. Effects of WB-EMS were estimated by linear mixed models. Secondary outcomes of physical function, hematological and blood chemistry parameters, quality of life and fatigue were assessed at baseline and week 12. Changes were analyzed by t-tests, Wilcoxon signed-rank or Mann-Whitney-U-tests. RESULTS: Twenty-four patients of the control and 58 of the WB-EMS group completed the 12-week trial. Patients of the WB-EMS group had a significantly higher skeletal muscle mass (0.53 kg [0.08, 0.98]; p = 0.022) and body weight (1.02 kg [0.05, 1.98]; p = 0.039) compared to controls at the end of intervention. WB-EMS also significantly improved physical function and performance status (p < 0.05). No significant differences of changes in quality of life, fatigue and blood parameters were detected between the study groups after 12 weeks. CONCLUSIONS: Supervised WB-EMS training is a safe strength training method and combined with nutritional support it shows promising effects against muscle wasting and on physical function in advanced-stage cancer patients undergoing treatment. TRIAL REGISTRATION: ClinicalTrials.gov NCT02293239 (Date: November 18, 2014).
EVALuna2:35141

Effekte von Peer Teaching in einem geburtshilflich-gynäkologischen Praktikum - Frobenius, Wolfgang; Ganslandt, Thomas; Juenger, J.; Beckmann, Matthias; Cupisti, S. (Geburtshilfe und Frauenheilkunde, 2009)
Obstetrics gynecology medical education peer teaching block course OSCE Background: Due to limited staffing resources and the need to preserve patients' privacy, it is difficult to improve the assessed practical courses in gynecology required by law for the licensing of physicians in Germany (Ärztliche Approbations- ordnung, ÄAppO). A previously published project showed that including structured practical teaching (skills training) using suitable obstetric and gynecological models in courses taught by specially trained student teachers (peer teachers) represents a potential solution to the problem. However, there are as yet no data regarding the effectiveness of this approach. Aim: Aim of the study was to determine the effectiveness of a peer-assisted skills training for students as part of a gynecological and obstetric practical course for theoretical and practical examinations (objective structured clinical examination, mini-OSCE) (primary end point). How do students who have been taught in this way rate the educational quality, teaching atmosphere, personal learning progress, and this type of practical course overall (secondary end points)? Methods: Following the implementation of a skills training section during a practical course, students (n = 139) were randomly assigned to 24 groups. Most groups consisted of six participants. Half of these groups, with a total of 71 students, received peer teaching during skills training, while the other half (n = 68) were taught by postgraduate lecturers. The rest of the one-week practical course, including the theoretical and practical examinations, was identical for all groups. The results of a theoretical and practical examination, also newly implemented (primary end point) and the results of the evaluation before (comparability of the groups) and after the practical course (secondary end points) were analyzed. Results: The groups taught by postgraduate lecturers did not differ with regard to age, sex, num die Ergebnisse der Evaluation vor (Vergleichbarkeit der Gruppen) und nach dem Praktikum (sekundare Endpunkte). Ergebnisse: Die von postgraduierten Dozenten unterrichteten Gruppen unterschieden sich hinsichtlich Alter, Geschlecht, Semesterzahl und fachspezifischer Vorbildung nicht von den durch Peer Teacher geschulten Studierenden. An den 3 überwiegend praktischen OSKE-Stationen erzielten die Studierenden der Post- graduierten-Gruppe 58,26±3,2 (95%-KI 57,5-59,5) von 62 Punkten, in der Peer-Teacher-Gruppe waren es 58,82±2,6 (95%-KI 58,2-59,4) (p = 0,27). Bei der Bearbeitung der Stationen mit Fall- darstellungen, fur die beiden Gruppen in Seminaren von postgra- duierten Dozenten vermittelter Stoff relevant war, erreichte die Postgraduierten-Gruppe 26,52±3,2 (95%-KI 25,7-27,3) von 30 Punkten, in der Peer-Teacher-Gruppe waren es 26,29 ±2,7 (95%-KI 25,6-27,0) (p = 0,64). Auch in der abschließenden Evaluation hinsichtlich Motivation der Ausbilder, Lernklima sowie Effektivität der praktischen Prüfungsvorbereitung gab es keine signifikanten Unterschiede. Die postgraduierten Dozenten schnitten lediglich bei der Vermittlung des theoretischen Hintergrunds und der Beantwortung von Fragen signifikant besser ab als die Peer Teacher. Schlussfolgerung: Zur Vermittlung der Prinzipien grundlegender praktischer ärztlicher Fertigkeiten in einem frauenheilkund- lichen Blockpraktikum ist ein Teaching durch speziell geschulte Peers ebenso effektiv wie der Unterricht durch postgraduierte Dozenten. ber of completed semesters, or prior specialist training from the students who were taught by the peer teachers. In the purely practical OSCE stations, the students in the postgraduate group achieved 58.26 ±3.2 (95 % CI, 57.5-59.5) out of a total of 62 points, while in the peer teacher group they scored 58.82 ±2.6 (95% CI, 58.2-59.4) (p = 0.27). In dealing with the case descriptions, for which material taught to both groups in seminars by postgraduate lecturers was relevant, the postgraduate group achieved 26.52±3.2 (95% CI, 25.7-27.3) of 30 points, while in the peer teacher group the figure was 26.29 ±2.7 (95% CI, 25.6-27.0) (p = 0.64). In the final evaluation regarding the motivation of the trainers, the teaching atmosphere, and the effectiveness of preparation for the practical examination, no significant differences were found. The postgraduate lecturers only had significantly better results than the peer teachers when conveying the theoretical background and responding to questions. Conclusions: To communicate the principles of basic practical medical skills in a gynecological practical course, teaching by specially trained peers is just as effective as teaching by postgraduate teachers. © Georg Thieme Verlag KG Stuttgart.
CRIS-Team Scopus Importer:2021-11-16

Efficacy and safety of AEZS-108 (LHRH agonist linked to doxorubicin) in women with advanced or recurrent endometrial cancer expressing LHRH receptors: a multicenter phase 2 trial (AGO-GYN5) - Emons, Guenter; Gorchev, Grigor; Harter, Philipp; Wimberger, Pauline; Staehle, Anne; Hanker, Lars; Hilpert, Felix; Beckmann, Matthias; Dall, Peter; Gruendker, Carsten; Sindermann, Herbert; Sehouli, Jalid (International Journal of Gynecological Cancer, 2014)
Advanced or recurrent endometrial cancer (EC) no longer amenable to surgery or radiotherapy is a life-threatening disease with limited therapeutic options left. Eighty percent of ECs express receptors for luteinizing hormone-releasing hormone (LHRH), which can be targeted by AEZS-108 (zoptarelin doxorubicin acetate). This phase 2 trial was performed to assess the efficacy and safety of AEZS-108 in this group of patients.Patients had FIGO (Fédération Internationale de Gynécologie et d'Obstétrique) III or IV or recurrent EC, LHRH receptor-positive tumor status, and at least had 1 measurable lesion (Response Evaluation Criteria in Solid Tumors). Prior anthracycline therapy was not allowed. Patients received AEZS-108 as a 2-hour infusion on day 1 of a 21-day cycle. The treatment was continued for a maximum of 6 to 8 cycles. The primary end point was the response rate determined by the Response Evaluation Criteria in Solid Tumors.From April 2008 to November 2009, 44 patients were included in the study at 8 centers in Germany (AGO) and 3 centers in Bulgaria. Forty-three of these patients were eligible. Two (5%) patients had a complete remission, and 8 (18%) achieved a partial remission. Stable disease for at least 6 weeks was observed in 44%. The median time to progression was 7 months, and the median overall survival was 15 months. The most frequently reported grade 3 or 4 adverse effects were neutropenia (12%) and leucopenia (9%).AEZS-108, an LHRH-agonist coupled to doxorubicin, has significant activity and low toxicity in women with advanced or recurrent LHRH receptor-positive EC, supporting the principle of receptor-mediated targeted chemotherapy.
EVALuna2:17445

Efficacy of neoadjuvant pertuzumab in addition to chemotherapy and trastuzumab in routine clinical treatment of patients with primary breast cancer: a multicentric analysis - Fasching, Peter; Hartkopf, Andreas D.; Gaß, Paul; Häberle, Lothar; Akpolat-Basci, Leyla; Hein, Alexander; Volz, Bernhard; Taran, Florin-Andrei; Nabieva, Naiba; Pott, Birgit; Overkamp, Friedrich; Einarson, Hanna; et al. (Breast Cancer Research and Treatment, 2019)
PurposeNeoadjuvant combination treatment with chemotherapy (CTX), trastuzumab (TZM), and pertuzumab (PTZ) has been shown to result in higher pathological complete response rates (pCR) in comparison with treatment with chemotherapy and trastuzumab (CTX/TZM). This analysis was aimed at real-world validation of these results from prospective randomized trials.MethodsIn a retrospective analysis conducted in the PRAEGNANT network, patients were eligible for inclusion if they had either received neoadjuvant therapy with CTX/TZM or chemotherapy, trastuzumab, and pertuzumab (CTX/TZM/PTZ) and subsequently underwent surgery for their primary breast cancer. The effect of the two neoadjuvant regimens on pCR in addition to commonly applicable predictors of pCR was analyzed in 300 patients from three study sites, using logistic regression analyses with treatment arm, age, clinical tumor stage, grading, and hormone receptor status as predictors.ResultspCR with complete disappearance of all tumor cells was seen in 30.2% (n=58) of patients treated with CTX/TZM and in 52.8% (n=57) of those treated with CTX/TZM/PTZ. CTX/TZM/PTZ was positively associated with pCR (adjusted odds ratio 2.44; 95% CI 1.49-4.02). Mastectomy rates were not influenced by the therapy.ConclusionsThe results of clinical trials were confirmed in this dataset of patients who were treated outside of clinical trials in everyday routine work. pCR rates can be improved by 20% with pertuzumab in routine clinical use.
CRIS-Team WoS Importer:2019-03-15

Einfluss der COVID-19 Pandemie auf die Leistungszahlen eines universitären und zertifizierten Kontinenz- und Beckenbodenzentrums - Heindl, Felix; Winkler, M.; Schreiter, S.; Born, Tilman; Füller, Andreas; Schulmeyer, Carla; Beckmann, Matthias; Burghaus, Stefanie; Becker, Karina (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Elective gynaecological operations during sars-cov-2-pandemic. Durchführung von elektiven und benignen gynäkologischen operationen während der sars-cov-2-pandemie - Burghaus, Stefanie; Beckmann, Matthias; Hein, Alexander (Journal für Reproduktionsmedizin und Endokrinologie, 2021)
The SARS-CoV-2-pandemic led to a request in March 2020 for hospitals to postpone all medically not urgent operations, thus freeing up treatment and intensive care capacities. In gynaecology, this has particularly affected patients undergoing reproductive medical treatment, as well as patients with benign gynaecological diseases such as endome-triosis and uterine fibroids. The present study is intended to show how surgical interventions can be carried out during the SARS-CoV-2 pandemic, taking into account staff and patient safety, and what measures must be undertaken to do so. J Reproduktionsmed Endokrinol 2021; 18 (1): 8–12.
CRIS-Team Scopus Importer:2021-05-28
Keywords: COVID-19; Elective surgery; Gynaecology; SARS-CoV-2

Electrospun patterned porous scaffolds for the support of ovarian follicles growth: a feasibility study - Liverani, Liliana; Amir, Fattahi; Raffel, Nathalie; Preis, Alexander; Hoffmann, Inge; Boccaccini, Aldo R.; Beckmann, Matthias; Dittrich, Ralf (Scientific Reports, 2019)
Recently, the interest of the scientific community is focused on the application of tissue engineering approach for the fertility restoration. In this paper innovative patterned electrospun fibrous scaffolds were fabricated and used as 3D system for porcine follicles culture. The obtained scaffolds demonstrated to be a suitable support which did not alter or interfere with the typical spherical follicles morphology. The fibrillar structure of the scaffolds mimics the morphology of the healthy native tissue. The use of porcine follicles implied many advantages respect to the use of mouse model. Relevant results showed that more than the scaffold pattern and struts dimension, the selection of proper biomaterials improve the follicles adhesion and development.
CRIS-Team WoS Importer:2019-02-21

ELECTROSPUN SCAFFOLDS FOR OVARIAN TISSUE ENGINEERING: KEY POINTS OF SCAFFOLD-FOLLICLES INTERACTIONS - Liverani, Liliana; Bleisinger, Nathalie; Hoffmann, Inge; Beckmann, Matthias; Dittrich, Ralf; Boccaccini, Aldo R. (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Endocrine Treatment with 2 Years of Tamoxifen versus 2 Years of Exemestane in Postmenopausal Patients with High-Risk Early Breast Cancer and Persisting Circulating Tumor Cells - First Results of the SUCCESS C Endocrine Treatment Sub-Study - Schochter, Fabienne; Rack, Brigitte; Tzschaschel, Marie; Polasik, Arkadius; Andergassen, Ulrich; Trapp, Elisabeth; Alunni-Fabbroni, Marianna; Schneeweiss, Andreas; Muller, Volkmar; Pantel, Klaus; Gade, Joerg; Lorenz, Ralf; et al. (Oncology Research and Treatment, 2018)
Optimal choice and sequence of endocrine treatment following adjuvant chemotherapy in postmenopausal early breast cancer patients are still under discussion and treatment stratification factors are missing.Postmenopausal women with HER2-negative, hormone receptor-positive tumors and persisting circulating tumor cells (CTCs; assessed using the FDA-approved CellSearch® System, Janssen Diagnostics, LLC) after chemotherapy were randomized to 2 years of tamoxifen followed by 3 years of exemestane (tamoxifen-exemestane group, n = 54) or 5 years of exemestane (exemestane-only group, n = 54). CTCs were again assessed after the first 2 years of endocrine treatment. In addition, safety data were compared between the 2 groups.The 2 groups were well-balanced with regard to baseline characteristics. The CTC clearance rate after 2 years was 89% in the exemestane-only group and 97% in the tamoxifen-exemestane group (exact Fisher test, p = 0.36). The safety profile showed good tolerability with few grade 3 or 4 adverse events in both groups.The similar CTC clearance rate after 2 years of endocrine therapy with exemestane or tamoxifen, and the safety profiles obtained may indicate comparable efficacy and tolerability of both endocrine treatment regimens. However, these results have to be confirmed by final survival and safety analysis.
EVALuna2:56172

Endogenous Retroviral-K Envelope Is a Novel Tumor Antigen and Prognostic Indicator of Renal Cell Carcinoma - Weyerer, Veronika; Strissel, Pamela; Stohr, Christine; Eckstein, Markus; Wach, Sven; Taubert, Helge; Brandl, Lisa; Geppert, Carol-Immanuel; Wullich, Bernd; Cynis, Holger; Beckmann, Matthias; Seliger, Barbara; et al. (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is one of the ten most common cancers for men and women with an approximate 75% overall 5-year survival. Sixteen histological tumor subtypes exist and the most common are papillary, chromophobe and clear cell renal cell carcinoma (ccRCC) representing 85% of all RCC. Although epigenetically silenced, endogenous retroviral (ERV) genes become activated in tumors and function to ignite immune responses. Research has intensified to understand ERV protein function and their role as tumor antigens and targets for cancer (immune) therapy. ERV-K env is overexpressed and implicated as a therapeutic target for breast cancer, however studies in RCC are limited. In this investigation a human RCC tissue microarray (TMA) (n=374) predominantly consisting of the most common histological tumor subtypes was hybridized with an ERV-K env antibody and correlated with patient clinical data. TMA results showed the highest amount of ERV-K env protein expression and the strongest significant membrane expression in ccRCC versus other RCC subtypes. High ERV-K env total protein expression of all tumor subtypes significantly correlated with low tumor grading and a longer disease specific survival using multivariable analyses. Cell proliferation and invasion were assayed using the kidney cell lines HEK293 with wild-type p53 and a ccRCC cell line MZ1257RC mutated for p53. Transfecting these cell lines with a codon optimized ERV-K113 env overexpressing CMV vector was performed with or without 5'-Aza-2'-deoxycytidine (Aza) treatment to sustain promoter de-methylation. MZ1257RC showed induction of ERV-K113 expression and significantly increased both proliferation and invasion in the presence or absence of Aza. HEK293 cells demonstrated a restriction of ERV-K113 env expression and invasion with no changes in proliferation in the absence of Aza. However, in the presence of Aza despite increased ERV-K113 env expression, an inhibition of HEK293 proliferation and a further restriction of invasion was found. This study supports ERV-K env as a single prognostic indicator for better survival of RCC, which we propose represents a new tumor antigen. In addition, ERV-K env significantly regulates proliferation and invasion depending on p53 status and Aza treatment.
CRIS-Team WoS Importer:2021-05-14
Keywords: tumor antigen; renal cell carcinoma; patient prognosis; p53; ERV-K; invasion; azacytidine; endogenous retrovirus

Endometrial Dating Method Detects Individual Maturation Sequences During the Secretory Phase - Alfer, Joachim; Fattahi, Amir; Bleisinger, Nathalie; Krieg, JÜrgen; Behrens, Rolf; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Classen-Linke, Irmgard; Popovici, Roxana M. (In Vivo, 2020)
BACKGROUND/AIM: This study assessed whether a new immunohistochemical dating method allows precise endometrial dating allowing optimal timing for embryo transfer. PATIENTS AND METHODS: A novel method was used for endometrial dating, with parameters including menstrual cycle days, Noyes histological criteria, along with immunohistochemical expression pattern of estrogen and progesterone receptors and proliferation marker Ki-67. Endometrial maturation was analyzed on days +5 to +10 after ovulation or progesterone administration in 217 biopsies from 151 subfertile patients during the secretory phase. RESULTS: Endometrial maturation varied individually, occurring 1.68±1.67 days late. Comparison of histological maturation with clinical days after ovulation showed a delay of about 2 days. CONCLUSION: Endometrial maturation requires 8 days, rather than the expected 6 days, to reach the histological mid-secretory phase. This is not a delay and is also seen in fertile patients. The new analysis method used is superior to that using Noyes criteria alone and provides a better basis for determining conditions for optimal timing of embryo transfers.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Endometrial dating; endometrial receptivity; estrogen receptor; progesterone receptor; window of implantation

Endometrial delay is found to be part of a normal individual dynamic transformation process - Alfer, Joachim; Popovici, Roxana M.; Fattahi, Amir; Krieg, Juergen; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Bleisinger, Nathalie (Archives of Gynecology and Obstetrics, 2021)
Purpose: Limited information is clinically available concerning endometrial receptivity; assessing endometrial transformation status is therefore an urgent topic in assisted reproductive technology. This study aimed to investigate individual endometrial transformation rates during the secretory phase in subfertile patients using personal endometrial transformation analysis. Methods: Monitoring was carried out during the secretory phase to obtain endometrial receptivity profiles. For the investigation, two endometrial biopsies were taken within one menstrual cycle. The extended endometrial dating was based on the Noyes criteria, combined with immunohistochemical analyses of hormone receptors and proliferation marker Ki-67. Biopsies were taken mainly at days ovulation (OV, n = 76)/hormone replacement therapy (HRT, n = 58) + 5 and + 10. Results: The results of the two biopsies were correlated with the clinically expected day of the cycle and showed temporal delays or hypercompensations, diverging from the expected cycle days by 0.5–5 days. In comparison with the first biopsies, the transformation rate in the second biopsies showed compensation, augmented delay, or constant transformation in 48.69, 22.37, and 28.94% of cases for ovulation in natural cycles and 56.89, 25.85, and 17.26% for HRT cycles, respectively. Conclusion: The study revealed an individually dynamic transformation process of the endometrium, with the ability to compensate or enlarge an initial “delay”, which is now identified as a normal individual transformation process during the secretory phase. This information is of great importance for the scientific investigation of dynamic changes in endometrial tissue, as well as for the timing of embryo transfers.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Delay; Endometrium; Maturation; Receptivity

Endometriose – gynäkologische Diagnostik und Therapie: Was sollten Schmerzmediziner*innen wissen? - Burghaus, Stefanie; Beckmann, Matthias (Schmerz, 2021)
Background: Endometriosis is one of the most common diseases in women of reproductive age. Despite characteristic symptoms such as dysmenorrhea, chronic abdominal pain, dysuria, dyschezia and dyspareunia, the average latency until diagnosis is around 10 years. In addition to the individual limitations, the disease also has economic and health policy relevance. The complaints are followed by reductions in working hours, cyclically recurring short-term sick leave or presenteeism with reduced performance. Objective: An overview of the main recommendations of the S2k guideline on the diagnosis and treatment of endometriosis. Material and methods: For the S2k guideline “Diagnostics and therapy of endometriosis”, a systematic literature search was conducted in PubMed and Cochrane according to a defined algorithm and over a period of more than 5 years, from 01.01.2014 to 31.12.2018. For the evaluation, 322 publications, including systematic reviews, meta-analyses and randomized controlled trials were considered and these were assessed by 41 mandate holders and representatives from 25 Association of the Scientific Medical Societies in Germany (AWMF) and non-AWMF professional societies, organizations, associations and working groups of the German Society for Gynecology and Obstetrics (DGGG), as well as two patient target groups. Results: In a structured consensus process, 48 recommendations and 27 statements were formulated, which are presented in extracts in this paper. Discussion: Interdisciplinary cooperation is essential in the treatment of patients with (suspected) endometriosis. This team should include all necessary disciplines in a cross-sectoral network. This is most likely to be achieved in a certified structure.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Classification/endometriosis; Interdisciplinary care team; Laparoscopy; Progestins; Ultrasonography; transvaginal

Endometriosis as a risk factor for ovarian or endometrial cancer - results of a hospital-based case-control study - Burghaus, Stefanie; Haeberle, Lothar; Schrauder, Michael G.; Heusinger, Katharina; Thiel, Falk; Hein, Alexander; Wachter, David; Strehl, Johanna; Hartmann, Arndt; Ekici, Arif Bülent; Renner, Stefan; Beckmann, Matthias; et al. (BMC Cancer, 2015)
No screening programs are available for ovarian or endometrial cancer. One reason for this is the low incidence of the conditions, resulting in low positive predictive values for tests, which are not very specific. One way of addressing this problem might be to use risk factors to define subpopulations with a higher incidence. The aim of this study was to investigate the extent to which a medical history of endometriosis can serve as a risk factor for ovarian or endometrial cancer.In a hospital-based case-control analysis, the cases represented patients with endometrial or ovarian cancer who were participating in studies aimed at assessing the risk for these diseases. The controls were women between the age of 40 and 85 who were invited to take part via a newspaper advertisement. A total of 289 cases and 1016 controls were included. Using logistic regression models, it was tested whether self-reported endometriosis is a predictor of case-control status in addition to age, body mass index (BMI), number of pregnancies and previous oral contraceptive (OC) use.Endometriosis was reported in 2.1 % of the controls (n = 21) and 4.8 % of the cases (n = 14). Endometriosis was a relevant predictor for case-control status in addition to other predictive factors (OR 2.63; 95 % CI, 1.28 to 5.41).This case-control study found that self-reported endometriosis may be a risk factor for endometrial or ovarian cancer in women between 40 and 85 years. There have been very few studies addressing this issue, and incorporating it into a clinical prediction model would require a more precise characterization of the risk factor of endometriosis.
EVALuna2:6731

Endometriosis in women undergoing ovarian tissue transplantation due to premature menopause after gonadotoxic treatment or spontaneous premature ovarian failure - Lotz, Laura; Dietl, Anna; Hoffmann, Inge; Mueller, Anrdreas; Burghaus, Stefanie; Beckmann, Matthias; Dittrich, Ralf (Acta Obstetricia Et Gynecologica Scandinavica, 2022)
Introduction: Cryopreservation of ovarian tissue with subsequent transplantation is an efficient option for restoring fertility in women at risk of premature ovarian failure. The association between infertility and endometriosis is well recognized. Although endometriosis usually ends with the onset of natural or iatrogen menopause due to declining estrogen levels, endometriosis can in rare cases occur after menopause. This study aims to investigate women with premature menopause who were diagnosed with endometriosis during laparoscopy for ovarian tissue transplantation, and to address the questions of how endometriotic lesions after cytotoxic treatment and premature menopause might be explained, whether endometriosis affects pregnancy rates, and whether there is an association between endometriosis and the original cancer. Material and Methods: Seventeen patients who had undergone ovarian tissue transplantation to restore their fertility and who were diagnosed with endometriosis during transplantation were included in this retrospective study. The endometriosis foci were completely removed and ovarian tissue was transplanted into the pelvic peritoneum. Preexisting conditions, use of hormonal preparations, endometriosis stage pain assessment, as well as pregnancy and live birth rate were evaluated. Results: The mean age of the patients was 29.5 ± 6.3 years (range 14–39) at the time of ovarian tissue harvest and 34.6 ± 4.3 years (range 28–40) at transplantation. Prior to transplantation, four patients had taken hormone replacement therapy, four women oral contraceptives and two patients’ tamoxifen. Twelve women had stage I endometriosis and five stage II endometrioses according to the rASRM classification. Four patients reported dysmenorrhea. None of the women complained of general pelvic pain or dyspareunia. The pregnancy rate in the study population was 41.2%, with a live birth rate of 35.3%. The pregnancies occurred in three cases after spontaneous conception, in four women after a natural cycle IVF/ICSI. Conclusions: This study highlights the under-researched association between endometriosis in women entering premature or early menopause either after gonadotoxic treatment or due to primary ovarian insufficiency. As more and more patients seek to have their cryopreserved ovarian tissue transplanted to fulfill their desire to have children, specialists will inevitably encounter women with this condition.
CRIS-Team Scopus Importer:2022-05-20
Keywords: cryopreservation; endometriosis; gonadotoxic; infertility; ovarian tissue; premature ovarian failure; transplantation

Enrichment of putative PAX8 target genes at serous epithelial ovarian cancer susceptibility loci - Kar, Siddhartha P.; Adler, Emily; Tyrer, Jonathan; Hazelett, Dennis; Anton-Culver, Hoda; Bandera, Elisa V.; Beckmann, Matthias; Berchuck, Andrew; Bogdanova, Natalia; Brinton, Louise; Butzow, Ralf; Campbell, Ian; et al. (British Journal of Cancer, 2017)
BACKGROUND: Genome-wide association studies (GWAS) have identified 18 loci associated with serous ovarian cancer (SOC) susceptibility but the biological mechanisms driving these findings remain poorly characterised. Germline cancer risk loci may be enriched for target genes of transcription factors (TFs) critical to somatic tumorigenesis. METHODS: All 615 TF-target sets from the Molecular Signatures Database were evaluated using gene set enrichment analysis (GSEA) and three GWAS for SOC risk: discovery (2196 cases/4396 controls), replication (7035 cases/21 693 controls; independent from discovery), and combined (9627 cases/30 845 controls; including additional individuals). RESULTS: The PAX8-target gene set was ranked 1/615 in the discovery (PGSEA<0.001; FDR=0.21), 7/615 in the replication (PGSEA=0.004; FDR=0.37), and 1/615 in the combined (PGSEA<0.001; FDR=0.21) studies. Adding other genes reported to interact with PAX8 in the literature to the PAX8-target set and applying an alternative to GSEA, interval enrichment, further confirmed this association (P=0.006). Fifteen of the 157 genes from this expanded PAX8 pathway were near eight loci associated with SOC risk at P<10-5 (including six with P<5 × 10-8). The pathway was also associated with differential gene expression after shRNA-mediated silencing of PAX8 in HeyA8 (PGSEA=0.025) and IGROV1 (PGSEA=0.004) SOC cells and several PAX8 targets near SOC risk loci demonstrated in vitro transcriptomic perturbation. CONCLUSIONS: Putative PAX8 target genes are enriched for common SOC risk variants. This finding from our agnostic evaluation is of particular interest given that PAX8 is well-established as a specific marker for the cell of origin of SOC.
EVALuna2:36153

Epithelial-Mesenchymal Transition (EMT) Gene Variants and Epithelial Ovarian Cancer (EOC) Risk - Amankwah, Ernest K.; Lin, Hui-Yi; Tyrer, Jonathan P.; Lawrenson, Kate; Dennis, Joe; Chornokur, Ganna; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Bruinsma, Fiona; Bandera, Elisa V.; Bean, Yukie T.; et al. (Genetic Epidemiology, 2015)
Epithelial-mesenchymal transition (EMT) is a process whereby epithelial cells assume mesenchymal characteristics to facilitate cancer metastasis. However, EMT also contributes to the initiation and development of primary tumors. Prior studies that explored the hypothesis that EMT gene variants contribute to epithelial ovarian carcinoma (EOC) risk have been based on small sample sizes and none have sought replication in an independent population. We screened 15,816 single-nucleotide polymorphisms (SNPs) in 296 genes in a discovery phase using data from a genome-wide association study of EOC among women of European ancestry (1,947 cases and 2,009 controls) and identified 793 variants in 278 EMT-related genes that were nominally (P < 0.05) associated with invasive EOC. These SNPs were then genotyped in a larger study of 14,525 invasive-cancer patients and 23,447 controls. A P-value <0.05 and a false discovery rate (FDR) <0.2 were considered statistically significant. In the larger dataset, GPC6/GPC5 rs17702471 was associated with the endometrioid subtype among Caucasians (odds ratio (OR) = 1.16, 95% CI = 1.07-1.25, P = 0.0003, FDR = 0.19), whereas F8 rs7053448 (OR = 1.69, 95% CI = 1.27-2.24, P = 0.0003, FDR = 0.12), F8 rs7058826 (OR = 1.69, 95% CI = 1.27-2.24, P = 0.0003, FDR = 0.12), and CAPN13 rs1983383 (OR = 0.79, 95% CI = 0.69-0.90, P = 0.0005, FDR = 0.12) were associated with combined invasive EOC among Asians. In silico functional analyses revealed that GPC6/GPC5 rs17702471 coincided with DNA regulatory elements. These results suggest that EMT gene variants do not appear to play a significant role in the susceptibility to EOC.
EVALuna2:9299

Erlangen, 28th November 2016 241th Opinion of the DGGG: Opinion on the Subject of Zikavirus Infection during Pregnancy, Effects on the Fetuses and Recommendations for Monitoring and Diagnostics - Geipel, Annegret; Enders, Martin; Mylonas, Ioannis; Seelbach-Goebel, Birgit; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36136

Erratum: Publisher Correction: Shared heritability and functional enrichment across six solid cancers (Nature communications (2019) 10 1 (431)) - Jiang, Xia; Finucane, Hilary K.; Schumacher, Fredrick R.; Schmit, Stephanie L.; Tyrer, Jonathan P.; Han, Younghun; Michailidou, Kyriaki; Lesseur, Corina; Kuchenbaecker, Karoline B.; Dennis, Joe; Conti, David V.; Casey, Graham; et al. (Nature Communications, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2019-10-01

Erratum to: The integrative epigenomic-transcriptomic landscape of ER positive breast cancer - Gao, Yang; Jones, Allison; Fasching, Peter; Rübner, Matthias; Beckmann, Matthias; Widschwendter, Martin; Teschendorff, Andrew E. (Clinical Epigenetics, 2016)
EVALuna2:32978

Establishment of the Certification System "Gynaecological Dysplasia" in Germany - Beckmann, Matthias; Quaas, J.; Bischofberger, A.; Kaemmerle, A.; Lux, Michael P.; Wesselmann, S. (Geburtshilfe und Frauenheilkunde, 2014)
Gynaecological cancer centres have been established nationwide in Germany since 2008 according to the certification system of the German Cancer Society (Deutsche Krebsgesellschaft e. V. [DKG]) and the German Society for Gynaecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe e. V. [DGGG]). However, patient access to the certified gynaecological cancer centres is currently only possible through direct referrals. A longitudinal structure with the corresponding long-term documentation of both the high-grade precursors as well as the cancers does not exist as yet. According to the aims of the National Cancer Plan, a corresponding structure for the cancer entity "cervix carcinoma" should be established. The foundations for such a structure are appropriate diagnostic units that are responsible, after nationwide screening, for clarification according to guideline-conform principles. On the basis of the vote of the certification commission for gynaecological cancer centres under the chairmanship of the DKG, the Working Group for Gynaecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie e. V. [AGO]), the Committee on Cervical Pathology and Colposcopy (Arbeitsgemeinschaft Zervixpathologie & Kolposkopie [AG-CPC]) and the DGGG the certification system for gynaecological dysplasia has been established. As a general principle, a distinction is made between the certification of a consulting practice for gynaecological dysplasia and a gynaecological dysplasia facility in order to integrate both outpatient and inpatient health-care facilities into the certification system. In analogy to the further catalogue of requirements from the DKG, quantitative and qualitative minimum numbers are demanded. Furthermore, the requirements of the certification process include a summary of patient information, the applied guidelines, continuing and further training, interdisciplinary cooperation in tumour boards, contents or, respectively, procedure descriptions for consulting practices and the trial participations. Central components of the questionnaire are quality indicators that can be used as specific and measurable elements to evaluate the quality of treatment. After successful pilot certification, finalisation of the updated version of the questionnaire and a completed specialist auditor training course for the certification of gynaecological dysplasia, it will be possible to establish a nationwide treatment system for dysplasia within certified structures.
EVALuna2:17435

Estrogen receptor beta rs1271572 polymorphism and invasive ovarian carcinoma risk: Pooled analysis within the ovarian cancer association consortium - Lurie, Galina; Wilkens, Lynne R.; Thompson, Pamela J.; Shvetsov, Yurii B.; Matsuno, Rayna K.; Carney, Michael E.; Palmieri, Rachel T.; Wu, Anna H.; Pike, Malcolm C.; Pearce, Celeste L.; Menon, Usha; Gentry-Maharaj, Aleksandra; et al. (PLoS ONE, 2011)
The association of ovarian carcinoma risk with the polymorphism rs1271572 in the estrogen receptor beta (ESR2) gene was examined in 4946 women with primary invasive ovarian carcinoma and 6582 controls in a pooled analysis of ten case-control studies within the Ovarian Cancer Association Consortium (OCAC). All participants were non-Hispanic white women. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using unconditional logistic regression adjusted for site and age. Women with the TT genotype were at increased risk of ovarian carcinoma compared to carriers of the G allele (OR = 1.10; 95%; CI: 1.01-1.21; p = 0.04); the OR was 1.09 (CI: 0.99-1.20; p = 0.07) after excluding data from the center (Hawaii) that nominated this SNP for OCAC genotyping A stronger association of rs1271572 TT versus GT/GG with risk was observed among women aged ≤50 years versus older women (OR = 1.35; CI: 1.12-1.62; p = 0.002; p for interaction = 0.02) that remained statistically significant after excluding Hawaii data (OR = 1.34; CI: 1.11-1.61; p = 0.009). No heterogeneity of the association was observed by study, menopausal status, gravidity, parity, use of contraceptive or menopausal hormones, tumor histological type, or stage at diagnosis. This pooled analysis suggests that rs1271572 might influence the risk of ovarian cancer, in particular among younger women. © 2011 Lurie et al.
CRIS-Team Scopus Importer:2021-07-19

Europe-side external quality assessment (EQA) of RNA based testing of ER, PR, HER2 and Ki67 in invasive breast cancer - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Stöhr, Robert; Beckmann, Matthias; Zentgraf, M.; Rübner, Matthias; Hübner, Hanna; Fischer, J.; Guerini Rocco, E.; Viale, G.; Cayre, A.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Evaluating the Effectiveness of Mobile Health in Breast Cancer Care: A Systematic Review - Flaucher, Madeleine; Zakreuskaya, Anastasiya; Nissen, Michael; Mocker, Alexander; Fasching, Peter; Beckmann, Matthias; Eskofier, Björn; Leutheuser, Heike (Oncologist, 2023)

Evaluating the ovarian cancer gonadotropin hypothesis: a candidate gene study - Lee, Alice W.; Tyrer, Jonathan P.; Doherty, Jennifer A.; Stram, Douglas A.; Kupryjanczyk, Jolanta; Dansonka-Mieszkowska, Agnieszka; Plisiecka-Halasa, Joanna; Spiewankiewicz, Beata; Myers, Emily J.; Chenevix-Trench, Georgia; Fasching, Peter A.; Beckmann, Matthias; et al. (Gynecologic Oncology, 2015)
Ovarian cancer is a hormone-related disease with a strong genetic basis. However, none of its high-penetrance susceptibility genes and GWAS-identified variants to date are known to be involved in hormonal pathways. Given the hypothesized etiologic role of gonadotropins, an assessment of how variability in genes involved in the gonadotropin signaling pathway impacts disease risk is warranted.Genetic data from 41 ovarian cancer study sites were pooled and unconditional logistic regression was used to evaluate whether any of the 2185 SNPs from 11 gonadotropin signaling pathway genes was associated with ovarian cancer risk. A burden test using the admixture likelihood (AML) method was also used to evaluate gene-level associations.We did not find any genome-wide significant associations between individual SNPs and ovarian cancer risk. However, there was some suggestion of gene-level associations for four gonadotropin signaling pathway genes: INHBB (p=0.045, mucinous), LHCGR (p=0.046, high-grade serous), GNRH (p=0.041, high-grade serous), and FSHB (p=0.036, overall invasive). There was also suggestive evidence for INHA (p=0.060, overall invasive).Ovarian cancer studies have limited sample numbers, thus fewer genome-wide susceptibility alleles, with only modest associations, have been identified relative to breast and prostate cancers. We have evaluated the majority of ovarian cancer studies with biological samples, to our knowledge, leaving no opportunity for replication. Using both our understanding of biology and powerful gene-level tests, we have identified four putative ovarian cancer loci near INHBB, LHCGR, GNRH, and FSHB that warrant a second look if larger sample sizes and denser genotype chips become available.
EVALuna2:9278

Evaluation of a Marker Clip System in Sonographically Guided Core Needle Biopsy for Breast Cancer Localization Before and After Neoadjuvant Chemotherapy - Schulz-Wendtland, Rüdiger; Dankerl, P.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Jud, Sebastian; Rauh, C.; Bayer, C. M.; Schrauder, M. G.; Beckmann, Matthias; Uder, M.; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Introduction The placement of intramammary marker clips has proven to be helpful for tumor localization in patients undergoing neoadjuvant chemotherapy and breast-conserving surgery. The purpose of our study was to investigate the feasibility of using a clip marker system for breast cancer localization and its influence on the imaging assessment of treatment responses after neoadjuvant chemotherapy. Patients and Methods Between March and June 2015, a total of 25 patients (n = 25), with a suspicion of invasive breast cancer with diameters of at least 2 cm (cT2), underwent preoperative sonographically guided core needle biopsy using a single-use breast biopsy system (HistoCore(TM)) and intramammary clip marking using a directly adapted clip system based on the established O-Twist Marker(TM), before their scheduled preoperative neoadjuvant chemotherapy. Localization of the intramammary marker clip was controlled by sonography and digital breast tomosynthesis. Results Sonography detected no dislocation of intrammammary marker clips in 20 of 25 patients (80 %), while digital breast tomosynthesis showed accurate placement without dislocation in 24 patients (96 %) (p < 0.05). There was no evidence of significant clip migration during preoperative follow-up imaging after neoadjuvant chemotherapy. No complication related to the clip marking was noted and there was no difficulty in evaluating the treatment response to neoadjuvant chemotherapy. Among the breast-conserving surgeries performed, no cases were identified in which intraoperative loss of the marker clip had occurred. Conclusion Our study underscores the importance of intramammary marking clip systems before neoadjuvant chemotherapy. Placement of marker clips is advised to facilitate accurate tumor bed localization. With regard to digital breast tomosynthesis, its development continues to improve the quality of diagnostics and the therapy of breast cancer particularly for small breast cancer tumors or in neoadjuvant chemotherapy setting.
EVALuna2:14620

Evaluation of automated techniques for extraction of circulating cell-free DNA for implementation in standardized high-throughput workflows - Lehle, Sarah; Emons, Julius; Hack, Caroline; Heindl, Felix; Hein, Alexander; Preuß, Caroline; Seitz, Katharina; Zahn, Anna; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Hübner, Hanna (Scientific Reports, 2023)
Analysis of circulating cell-free DNA (ccfDNA) is a suitable tool for detecting somatic mutations for the purpose of making decisions on treatment, monitoring treatment response, and predicting survival. High-throughput techniques for ccfDNA extraction are essential to implementing ccfDNA testing in the clinical setting. We set out to compare two automated techniques with regard to hands-on time, ccfDNA output and integrity, and circulating mitochondrial DNA (mtDNA). CcfDNA was isolated using the EZ1&2 ccfDNA field test kit (EZ2 kit, QIAGEN) and the Maxwell RSC ccfDNA plasma kit (Maxwell kit, Promega). DNA was extracted from plasma of 30 breast cancer patients enrolled in the iMODE-B (#325_19B; 12.10.2020) study. Real-time PCR, fluorescence-based detection and automated electrophoresis were used to assess ccfDNA concentrations. The ccfDNA yield was significantly higher when extracted with the EZ2 kit. The EZ2 kit enabled the isolation of a higher proportion of short fragments and a lower proportion of long fragments, resulting in lower DNA integrity. Significantly lower mtDNA quantities were detected in the Maxwell eluate than in the EZ2 eluate. Thus, decisions on which extraction method to use should proceed on the basis of the required input for downstream applications, the anticipated fragment size and minimum hands-on time.
CRIS-Team Scopus Importer:2023-01-20

Evaluation of European-based polygenic risk score for breast cancer in Ashkenazi Jewish women in Israel - Levi, Hagai; Carmi, Shai; Rosset, Saharon; Yerushalmi, Rinat; Zick, Aviad; Yablonski-Peretz, Tamar; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; Michailidou, Kyriaki; Lush, Michael; Ahearn, Thomas; et al. (Journal of Medical Genetics, 2023)
To date, most BC GWASs have been performed Background Polygenic risk score (PRS), calculated in individuals of European (EUR) ancestry, and based on genome-wide association studies (GWASs), the generalisation of EUR-based PRS to other can improve breast cancer (BC) risk assessment. populations is a major challenge. In this study, we examined the performance of EUR-based BC PRS models in Ashkenazi Jewish (AJ) women. Methods We generated PRSs based on data on EUR women from the Breast Cancer Association Consortium (BCAC). We tested the performance of the PRSs in a cohort of 2161 AJ women from Israel (1437 cases and 724 controls) from BCAC (BCAC cohort from Israel (BCAC-IL)). In addition, we tested the performance of these EUR-based BC PRSs, as well as the established 313-SNP EUR BC PRS, in an independent cohort of 181 AJ women from Hadassah Medical Center (HMC) in Israel. Results In the BCAC-IL cohort, the highest OR per 1 SD was 1.56 (±0.09). The OR for AJ women at the top 10% of the PRS distribution compared with the middle quintile was 2.10 (±0.24). In the HMC cohort, the OR per 1 SD of the EUR-based PRS that performed best in the BCAC-IL cohort was 1.58±0.27. The OR per 1 SD of the commonly used 313-SNP BC PRS was 1.64 (±0.28). Conclusions Extant EUR GWAS data can be used for generating PRSs that identify AJ women with markedly elevated risk of BC and therefore hold promise for improving BC risk assessment in AJ women.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Genomics; Polymorphism; Genetic

Evaluation of integrated hpv dna as individualized biomarkers for the detection of recurrent cin2/3 during post-treatment surveillance - Hoyer, Heike; Mehlhorn, Grit; Scheungraber, Cornelia; Hagemann, Ingke; Hirchenhain, Christine; Woelber, Linn; Stolte, Claudia; Hampl, Monika; Scherbring, Sarah; Denecke, Agnieszka; Bartels, Janina; Ebert, Andreas D.; et al. (Cancers, 2021)
Purpose: Post-treatment follow-up in women with cervical pre-cancers (CIN3) is mandatory due to relapse in up to 10% of patients. Standard follow-up based on hrHPV-DNA/cytology co-testing has high sensitivity but limited specificity. The aim of our prospective, multicenter, observational study was to test the hypothesis that an individualized viral-cellular-junction test (vcj-PCR) combined with cytology has a lower false positive rate for the prediction of recurrence compared to standard co-testing. Methods: Pre-surgical cervical swabs served for the identification of HPV16/18 DNA integration sites by next-generation-sequencing (NGS). Samples taken at 6, 12 and 24 months post-surgery were evaluated by cytology, hrHPV-DNA and the patients’ individual HPV-integration sites (vcj-PCR on the basis of NGS). Results: Integration sites were detected in 48 of 445 patients (10.8%), 39 of them had valid follow-up data. The false positive rate was 18.2% (95% CI 8.6–34.4%) for standard hrHPV/cytology at six months compared to 12.1% (95% CI 4.8–27.3%) for vcj-PCR/cytology, respectively (McNemar p = 0.50). Six patients developed recurrences (1 CIN2, 5 CIN3) during follow-up. Standard co-testing detected all, whereas vcj-PCR/cytology detected only five patients with recurrences. Data of 269 patients without evidence of HPV16/18 integration were subject to post-hoc analyses. Standard co-testing revealed a false positive rate of 15.7% (95% CI 11.7–20.7%) and predicted ten of fourteen recurrences at six months. Conclusions: Although highly specific on its own vcj-PCR could not detect all recurrent CIN2/3. Possible reasons for this unexpected result may be multifocal lesions, intratumoral heterogeneity with respect to HPV integration and/or incident CIN.
CRIS-Team Scopus Importer:2021-07-09
Keywords: CIN3; HPV DNA integration; Individualized molecular biomarker; Post treatment surveillance; Recurrence

Evaluation of newly adapted clip marker system in ultrasound-guided core needle biopsy for suspicion of breast cancer - Schulz-Wendtland, Rüdiger; Dankerl, Peter; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Jud, Sebastian; Rauh, Claudia; Bayer, Christian M.; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: A newly adapted clip system for intramammary marking during ultrasound-guided core needle biopsy for suspicion of breast cancer is described and evaluated here. Material and Method: Fifty patients with suspicion of breast cancer (cT2) had ultrasound-guided core needle biopsy using a newly adapted clip marker system (HistoCore™ and O-Twist Marker™). Subsequently, ultrasound follow-up and tomosynthesis scans were done to determine the location of the marker clips. Results: No dislocation of the marker clip was detected on ultrasound in 45 of 50 patients (90%), and 5 patients (10%) had a maximum dislocation of 5 mm along the x-, y- or z-axis. Tomosynthesis scans demonstrated precise placement without dislocation of the clip markers in 48 patients (96%); 2 patients (4%) had a maximum dislocation of 3 mm along the x-, y- or z-axis. Conclusion: The newly developed clip marker system, a combination of a single-use breast biopsy needle and a precise, length-adapted intramammary marker clip, represents a further improvement in oncological therapy. This is of particular importance for patients requiring subsequent neoadjuvant chemotherapy, as in cases with complete tumour remission, there is no target point for preoperative, ultrasound-guided wire marking. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: biopsy; breast; breast cancer; ultrasound

EVALUATION OF OPTOACOUSTIC IMAGING FOR ANALYSIS OF PLACENTAL VILLOUS VASCULARIZATION - Hübner, Hanna; Knieling, Ferdinand; Faschingbauer, Florian; Rübner, Matthias; Kehl, Sven; Beckmann, Matthias; Rascher, Wolfgang; Hartner, Andrea; Fahlbusch, Fabian (2018)
EVALuna2:208000

Evaluation of Therapy Management and Patient Compliance in Postmenopausal Patients with Hormone Receptor-positive Breast Cancer Receiving Letrozole Treatment: The EvaluateTM Study - Fasching, Peter; Fehm, T.; Kellner, S.; De Waal, J.; Rezal, M.; Baler, B.; Baake, G.; Kolberg, H. -C; Guggenberger, M.; Warm, N.; Harbeck, N.; Wuerstlein, R.; et al. (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: The EvaluateTM study (Evaluation of therapy management and patient compliance in postmenopausal hormone receptor-positive breast cancer patients receiving letrozole treatment) is a prospective, non-interventional study for the assessment of therapy management and compliance in the routine care of postmenopausal women with invasive hormone receptor-positive breast cancer receiving letrozole. The parameters for inclusion in the study are presented and discussed here. Material and Methods: Between January 2008 and December 2009 a total of 5045 patients in 310 study centers were recruited to the EvaluateTM study. Inclusion criteria were hormone receptor-positive breast cancer and adjuvant treatment or metastasis. 373 patients were excluded from the analysis for various reasons. Results: A total of 4420 patients receiving adjuvant treatment and 252 patients with metastasis receiving palliative treatment were included in the study. For 4181 patients receiving adjuvant treatment, treatment with the aromatase inhibitor letrozole commenced immediately after surgery (upfront). Two hundred patients had initially received tamoxifen and started aromatase inhibitor treatment with letrozole at 1-5 years after diagnosis (switch), und 39 patients only commenced letrozole treatment 5-10 years after diagnosis (extended endocrine therapy). Patient and tumor characteristics were within expected ranges, as were comorbidities and concurrent medication. Conclusion: The data from the EvaluateTM study will offer a good overview of therapy management in the routine care of postmenopausal women with hormone receptor-positive breast cancer. Planned analyses will look at therapy compliance and patient satisfaction with how information is conveyed and the contents of the conveyed informatio
EVALuna2:17459

Evaluation of two different analytical methods for circulating tumor cell detection in peripheral blood of patients with primary breast cancer - Jaeger, B. A. S.; Jueckstock, J.; Andergassen, U.; Salmen, J.; Schochter, F.; Fink, V.; Alunni-Fabbroni, M.; Rezai, M.; Beck, Th.; Beckmann, Matthias; Friese, K.; Friedl, T. W. P.; et al. (BioMed Research International, 2014)
Evidence is accumulating that circulating tumor cells (CTC) out of peripheral blood can serve as prognostic marker not only in metastatic but also in early breast cancer (BC). Various methods are available to detect CTC. Comparisons between the different techniques, however, are rare.We evaluate two different methods for CTC enrichment and detection in primary BC patients: the FDA-approved CellSearch System (CSS; Veridex, Warren, USA) and a manual immunocytochemistry (MICC). The cut-off value for positivity was >=1 CTC.The two different nonoverlapping patient cohorts evaluated with one or the other method were well balanced regarding common clinical parameters. Before adjuvant CHT 21.1% (416 out of 1972) and 20.6% (247 out of 1198) of the patients were CTC-positive, while after CHT 22.5% (359 out of 1598) and 16.6% (177 out of 1066) of the patients were CTC-positive using CSS or MICC, respectively. CTC positivity rate before CHT was thus similar and not significantly different (P = 0.749), while CTC positivity rate immediately after CHT was significantly lower using MICC compared to CSS (P < 0.001).Using CSS or MICC for CTC detection, we found comparable prevalence of CTC before but not after adjuvant CHT.
EVALuna2:17463

Evaluation of variation in the phosphoinositide-3-kinase catalytic subunit alpha oncogene and breast cancer risk - Stevens, K. N.; Garcia-Closas, Montserrat; Fredericksen, Z.; Kosel, M.; Pankratz, V. S.; Hopper, J. L.; Dite, G. S.; Apicella, C.; Southey, M. C.; Schmidt, M. K.; Broeks, A.; Van 'T Veer, L. J.; et al. (British Journal of Cancer, 2011)
Background: Somatic mutations in phosphoinositide-3-kinase catalytic subunit alpha (PIK3CA) are frequent in breast tumours and have been associated with oestrogen receptor (ER) expression, human epidermal growth factor receptor-2 overexpression, lymph node metastasis and poor survival. The goal of this study was to evaluate the association between inherited variation in this oncogene and risk of breast cancer. Methods: A single-nucleotide polymorphism from the PIK3CA locus that was associated with breast cancer in a study of Caucasian breast cancer cases and controls from the Mayo Clinic (MCBCS) was genotyped in 5436 cases and 5280 controls from the Cancer Genetic Markers of Susceptibility (CGEMS) study and in 30 949 cases and 29 788 controls from the Breast Cancer Association Consortium (BCAC). Results: Rs1607237 was significantly associated with a decreased risk of breast cancer in MCBCS, CGEMS and all studies of white Europeans combined (odds ratio (OR)=0.97, 95% confidence interval (CI) 0.95-0.99, P=4.6 × 10 3), but did not reach significance in the BCAC replication study alone (OR=0.98, 95% CI 0.96-1.01, P=0.139).Conclusion: Common germline variation in PIK3CA does not have a strong influence on the risk of breast cancer. © 2011 Cancer Research UK All rights reserved.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Association study; Genetic susceptibility; Neoplasms

Evidence for a time-dependent association between FOLR1 expression and survival from ovarian carcinoma: implications for clinical testing. An Ovarian Tumour Tissue Analysis consortium study - Koebel, M.; Madore, J.; Ramus, S. J.; Clarke, B. A.; Pharoah, P. D. P.; Deen, S.; Bowtell, D. D.; Odunsi, K.; Menon, U.; Morrison, C.; Lele, S.; Bshara, W.; et al. (British Journal of Cancer, 2014)
Folate receptor 1 (FOLR1) is expressed in the majority of ovarian carcinomas (OvCa), making it an attractive target for therapy. However, clinical trials testing anti-FOLR1 therapies in OvCa show mixed results and require better understanding of the prognostic relevance of FOLR1 expression. We conducted a large study evaluating FOLR1 expression with survival in different histological types of OvCa.Tissue microarrays composed of tumour samples from 2801 patients in the Ovarian Tumour Tissue Analysis (OTTA) consortium were assessed for FOLR1 expression by centralised immunohistochemistry. We estimated associations for overall (OS) and progression-free (PFS) survival using adjusted Cox regression models. High-grade serous ovarian carcinomas (HGSC) from The Cancer Genome Atlas (TCGA) were evaluated independently for association between FOLR1 mRNA upregulation and survival.FOLR1 expression ranged from 76% in HGSC to 11% in mucinous carcinomas in OTTA. For HGSC, the association between FOLR1 expression and OS changed significantly during the years following diagnosis in OTTA (Pinteraction=0.01, N=1422) and TCGA (Pinteraction=0.01, N=485). In OTTA, particularly for FIGO stage I/II tumours, patients with FOLR1-positive HGSC showed increased OS during the first 2 years only (hazard ratio=0.44, 95% confidence interval=0.20-0.96) and patients with FOLR1-positive clear cell carcinomas (CCC) showed decreased PFS independent of follow-up time (HR=1.89, 95% CI=1.10-3.25, N=259). In TCGA, FOLR1 mRNA upregulation in HGSC was also associated with increased OS during the first 2 years following diagnosis irrespective of tumour stage (HR: 0.48, 95% CI: 0.25-0.94).FOLR1-positive HGSC tumours were associated with an increased OS in the first 2 years following diagnosis. Patients with FOLR1-negative, poor prognosis HGSC would be unlikely to benefit from anti-FOLR1 therapies. In contrast, a decreased PFS interval was observed for FOLR1-positive CCC. The clinical efficacy of FOLR1-targeted interventions should therefore be evaluated according to histology, stage and time following diagnosis.
EVALuna2:6660

Evidence that breast cancer risk at the 2q35 locus is mediated through IGFBP5 regulation - Ghoussaini, Maya; Edwards, Stacey L.; Michailidou, Kyriaki; Nord, Silje; Lari, Richard Cowper-Sal; Desai, Kinjal; Kar, Siddhartha; Hillman, Kristine M.; Kaufmann, Susanne; Glubb, Dylan M.; Beesley, Jonathan; Dennis, Joe; et al. (Nature Communications, 2014)
GWAS have identified a breast cancer susceptibility locus on 2q35. Here we report the fine mapping of this locus using data from 101,943 subjects from 50 case-control studies. We genotype 276 SNPs using the 'iCOGS' genotyping array and impute genotypes for a further 1,284 using 1000 Genomes Project data. All but two, strongly correlated SNPs (rs4442975 G/T and rs6721996 G/A) are excluded as candidate causal variants at odds against >100:1. The best functional candidate, rs4442975, is associated with oestrogen receptor positive (ER+) disease with an odds ratio (OR) in Europeans of 0.85 (95% confidence interval=0.84-0.87; P=1.7 × 10(-43)) per t-allele. This SNP flanks a transcriptional enhancer that physically interacts with the promoter of IGFBP5 (encoding insulin-like growth factor-binding protein 5) and displays allele-specific gene expression, FOXA1 binding and chromatin looping. Evidence suggests that the g-allele confers increased breast cancer susceptibility through relative downregulation of IGFBP5, a gene with known roles in breast cell biolog
EVALuna2:9236

Evidence that the 5p12 Variant rs10941679 Confers Susceptibility to Estrogen-Receptor-Positive Breast Cancer through FGF10 and MRPS30 Regulation - Ghoussaini, Maya; French, Juliet D.; Michailidou, Kyriaki; Nord, Silje; Beesley, Jonathan; Canisus, Sander; Hillman, Kristine M.; Kaufmann, Susanne; Sivakumaran, Haran; Marjaneh, Mandi Moradi; Lee, Jason S.; Dennis, Joe; et al. (American Journal of Human Genetics, 2016)
Genome-wide association studies (GWASs) have revealed increased breast cancer risk associated with multiple genetic variants at 5p12. Here, we report the fine mapping of this locus using data from 104,660 subjects from 50 case-control studies in the Breast Cancer Association Consortium (BCAC). With data for 3,365 genotyped and imputed SNPs across a 1 Mb region (positions 44,394,495-45,364,167; NCBI build 37), we found evidence for at least three independent signals: the strongest signal, consisting of a single SNP rs10941679, was associated with risk of estrogen-receptor-positive (ER+) breast cancer (per-g allele OR ER+= 1.15; 95% CI 1.13-1.18; p = 8.35 × 10-30). After adjustment for rs10941679, we detected signal 2, consisting of 38 SNPs more strongly associated with ER-negative (ER-) breast cancer (lead SNP rs6864776: per-a allele OR ER-= 1.10; 95% CI 1.05-1.14; p conditional = 1.44 × 10-12), and a single signal 3 SNP (rs200229088: per-t allele OR ER+= 1.12; 95% CI 1.09-1.15; p conditional = 1.12 × 10-05). Expression quantitative trait locus analysis in normal breast tissues and breast tumors showed that the g (risk) allele of rs10941679 was associated with increased expression of FGF10 and MRPS30. Functional assays demonstrated that SNP rs10941679 maps to an enhancer element that physically interacts with the FGF10 and MRPS30 promoter regions in breast cancer cell lines. FGF10 is an oncogene that binds to FGFR2 and is overexpressed in ∼10% of human breast cancers, whereas MRPS30 plays a key role in apoptosis. These data suggest that the strongest signal of association at 5p12 is mediated through coordinated activation of FGF10 and MRPS30, two candidate genes for breast cancer pathogenesis.
EVALuna2:33316

Examination of the effect of seminal plasma on uterus contraction from two different donor collectives with normozoospermia - Hoffmann, Inge; Lotz, Laura; Beckmann, Matthias; Dittrich, Ralf (2017)
EVALuna2:36131

Expression and Regulation of Retinoic Acid Receptor Responders in the Human Placenta - Hübner, Hanna; Rascher, Wolfgang; Strick, Reiner; Kehl, Sven; Heindl, Felix; Wachter, David; Beckmann, Matthias; Fahlbusch, Fabian B.; Rübner, Matthias; Hartner, Andrea (Reproductive Sciences, 2017)
INTRODUCTION: Retinoic acid (RA) signaling through its receptors (RARA, RARB, RARG, and the retinoic X receptor RXRA) is essential for healthy placental and fetal development. An important group of genes regulated by RA are the RA receptor responders (RARRES1, 2, and 3). We set out to analyze their expression and regulation in healthy and pathologically altered placentas of preeclampsia (PE) and intrauterine growth restriction (IUGR) as well as in trophoblast cell lines. METHODS: We performed immunohistochemical staining on placental sections and analyzed gene expression by real-time polymerase chain reaction. Additionally, we performed cell culture experiments and stimulated Swan71 and Jeg-3 cells with different RA derivates and 2'-deoxy-5-azacytidine (AZA) to induce DNA demethylation. RESULTS: RARRES1, 2, and 3 and RARA, RARB, RARG, and RXRA are expressed in the extravillous part of the placenta. RARRES1, RARA, RARG, and RXRA were additionally detected in villous cytotrophoblasts. RARRES gene expression was induced via activation of RARA, RARB, and RARG in trophoblast cells. RARRES1 was overexpressed in villous trophoblasts and the syncytiotrophoblast from PE placentas, but not in IUGR without PE. Promoter methylation was detectable for RARRES1 and RARB based on their sensitivity toward AZA treatment of trophoblast cell lines. DISCUSSION: RARRES1, 2 and 3 are expressed in the functional compartments of the human placenta and can be regulated by RA. We hypothesize that the epigenetic suppression of trophoblast RARRES1 and RARB expression and the upregulation of RARRES1 in PE trophoblast cells suggest an involvement of environmental factors (eg, maternal vitamin A intake) in the pathogenesis of this pregnancy complication.
EVALuna2:34222

Expression of disialoganglioside GD2 in breast cancer subtypes - Gaß, Paul; Kailayangiri, Sareetha; Hübner, Hanna; Rübner, Matthias; Hartmann, Arndt; Häberle, Lothar; Völkl, Simon; Mackensen, Andreas; Landgraf, Laura; Schulz-Wendtland, Rüdiger; Farwick, Nicole; Roessig, Claudia; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Expression of neuroendocrine markers in different molecular subtypes of breast carcinoma - Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Hein, Alexander; Bayer, Christian M.; Agaimy, Abbas (BioMed Research International, 2014)
Carcinomas of the breast with neuroendocrine features are incorporated in the World Health Organization classification since 2003 and include well-differentiated neuroendocrine tumors, poorly differentiated neuroendocrine carcinomas/small cell carcinomas, and invasive breast carcinomas with neuroendocrine differentiation. Neuroendocrine differentiation is known to be more common in certain low-grade histologic special types and has been shown to mainly cluster to the molecular (intrinsic) luminal A subtype.We analyzed the frequency of neuroendocrine differentiation in different molecular subtypes of breast carcinomas of no histologic special type using immunohistochemical stains with specific neuroendocrine markers (chromogranin A and synaptophysin).We found neuroendocrine differentiation in 20% of luminal B-like carcinomas using current WHO criteria (at least 50% of tumor cells positive for synaptophysin or chromogranin A). In contrast, no neuroendocrine differentiation was seen in luminal A-like, HER2 amplified and triple-negative carcinomas. Breast carcinomas with neuroendocrine differentiation presented with advanced stage disease and showed aggressive behavior.We conclude that neuroendocrine differentiation is more common than assumed in poorly differentiated luminal B-like carcinomas. Use of specific neuroendocrine markers is thus encouraged in this subtype to enhance detection of neuroendocrine differentiation and hence characterize the biological and therapeutic relevance of this finding in future studies.
EVALuna2:6612

Expression of the Immunohistochemical Markers CK5, CD117, and EGFR in Molecular Subtypes of Breast Cancer Correlated with Prognosis - Schulmeyer, Carla; Fasching, Peter; Häberle, Lothar; Meyer, Julia; Schneider, Michael; Wachter, David; Rübner, Matthias; Pöschke, Patrik; Beckmann, Matthias; Hartmann, Arndt; Erber, Ramona; Gaß, Paul (Diagnostics, 2023)
Molecular-based subclassifications of breast cancer are important for identifying treatment options and stratifying the prognosis in breast cancer. This study aimed to assess the prognosis relative to disease-free survival (DFS) and overall survival (OS) in patients with triple-negative breast cancer (TNBC) and other subtypes, using a biomarker panel including cytokeratin 5 (CK5), cluster of differentiation 117 (CD117), and epidermal growth factor receptor (EGFR). This cohort–case study included histologically confirmed breast carcinomas as cohort arm. From a total of 894 patients, 572 patients with early breast cancer, sufficient clinical data, and archived tumor tissue were included. Using the immunohistochemical markers CK5, CD117, and EGFR, two subgroups were formed: one with all three biomarkers negative (TBN) and one with at least one of those three biomarkers positive (non-TBN). There were significant differences between the two biomarker subgroups (TBN versus non-TBN) in TNBC for DFS (p = 0.04) and OS (p = 0.02), with higher survival rates (DFS and OS) in the non-TBN subgroup. In this study, we found the non-TBN subgroup of TNBC lesions with at least one positive biomarker of CK5, CD117, and/or EGFR, to be associated with longer DFS and OS.
CRIS-Team Scopus Importer:2023-02-24
Keywords: CD117; CK5; early breast cancer; EGFR; prognosis; therapy; triple-negative breast cancer

External Beam Accelerated Partial Breast Irradiation in Early Breast Cancer and the Risk for Radiogenic Pneumonitis - Ott, Oliver; Stillkrieg, Wilhelm; Lambrecht, Ulrike; Sauer, Tim-Oliver; Schweizer, Claudia; Lamrani, Allison; Strnad, Vratislav; Hack, Caroline; Beckmann, Matthias; Uder, Michael; Fietkau, Rainer; Distel, Luitpold (Cancers, 2022)
Simple Summary Accelerated partial breast irradiation represents a well-established and safe treatment alternative for selected patients with early stage breast cancer after breast-conserving surgery. In a prospective trial on external beam partial breast irradiation, the risk for radiogenic pneumonitis is analyzed. After a median follow-up of 56 (1-129) months, radiogenic pneumonitis grade 2 appeared in only 1/170 (0.6%) patients. Compared to standard whole breast irradiation, the radiation doses applied to the lungs were very low. The patient with the radiogenic pneumonitis was found to have a generally increased radiation susceptibility. Using accelerated partial breast irradiation, the risk of radiogenic pneumonitis appeared quite low and may be limited to very exceptional cases associated with innate risk factors with an increased radiation susceptibility. In order to evaluate the risk for radiation-associated symptomatic pneumonitis in a prospective external beam accelerated partial breast irradiation (APBI) trial, between 2011 and 2021, 170 patients with early stage breast cancer were enclosed in the trial. Patients were eligible for study participation if they had a histologically confirmed breast cancer or an exclusive ductal carcinoma in situ (DCIS), a tumor size <= 3 cm, free safety margins >= 2 mm, no involved axillary lymph nodes, tumor bed clips, and were >= 50 years old. Patients received APBI with 38 Gy with 10 fractions in 10 consecutive working days. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Median follow-up was 56 (1-129) months. Ipsilateral lung MLD, V20, and V30 were 4.3 +/- 1.4 Gy, 3.0 +/- 2.0%, and 1.0 +/- 1.0%, respectively. Radiogenic pneumonitis grade 2 appeared in 1/170 (0.6%) patients two months after radiotherapy. Ipsilateral MLD, V20, and V30 were 6.1 Gy, 7, and 3% in this patient. Additionally, individual radiosensitivity was increased in this specific patient. Compared to WBI, APBI leads to lower lung doses. Using APBI, the risk of symptomatic radiogenic pneumonitis is very low and may be limited, with an ipsilateral V20 < 3% to very exceptional cases associated with innate risk factors with an increased radiation susceptibility.
CRIS-Team WoS Importer:2022-08-12

External-Beam-Accelerated Partial-Breast Irradiation Reduces Organ-at-Risk Doses Compared to Whole-Breast Irradiation after Breast-Conserving Surgery - Ott, Oliver; Stillkrieg, Willy; Lambrecht, Ulrike; Schweizer, Claudia; Lamrani, Allison; Sauer, Tim-Oliver; Strnad, Vratislav; Bert, Christoph; Hack, Carolin; Beckmann, Matthias; Fietkau, Rainer (Cancers, 2023)
In order to evaluate organ-at-risk (OAR) doses in external-beam-accelerated partial-breast irradiation (APBI) compared to standard whole-breast irradiation (WBI) after breast-conserving surgery. Between 2011 and 2021, 170 patients with early breast cancer received APBI within a prospective institutional single-arm trial. The prescribed dose to the planning treatment volume was 38 Gy in 10 fractions on 10 consecutive working days. OAR doses for the contralateral breast, the ipsilateral, contralateral, and whole lung, the whole heart, left ventricle (LV), and the left anterior descending coronary artery (LAD), and for the spinal cord and the skin were assessed and compared to a control group with real-world data from 116 patients who underwent WBI. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Compared to WBI, APBI led to reduced OAR doses for the contralateral breast (0.4 ± 0.6 vs. 0.8 ± 0.9 Gy, p = 0.000), the ipsilateral (4.3 ± 1.4 vs. 9.2 ± 2.5 Gy, p = 0.000) and whole mean lung dose (2.5 ± 0.8 vs. 4.9 ± 1.5 Gy, p = 0.000), the mean heart dose (1.6 ± 1.6 vs. 1.7 ± 1.4 Gy, p = 0.007), the LV V23 (0.1 ± 0.4 vs. 1.4 ± 2.6%, p < 0.001), the mean LAD dose (2.5 ± 3.4 vs. 4.8 ± 5.5 Gy, p < 0.001), the maximum spinal cord dose (1.5 ± 1.1 vs. 4.5 ± 5.7 Gy, p = 0.016), and the maximum skin dose (39.6 ± 1.8 vs. 49.1 ± 5.8 Gy, p = 0.000). APBI should be recommended to suitable patients to minimize the risk of secondary tumor induction and the incidence of consecutive major cardiac events.
CRIS-Team Scopus Importer:2023-08-25
Keywords: accelerated partial-breast irradiation; breast cancer; mean heart dose; mean lung dose; organs-at-risk

Ex Vivo Chromosomal Radiosensitivity Testing in Patients with Pathological Germline Variants in Breast Cancer High-Susceptibility Genes BReast CAncer 1 and BReast CAncer 2 - Zuhair Kassem, Tara; Wunderle, Marius; Kuhlmann, Lukas; Rübner, Matthias; Hübner, Hanna; Hoyer, Juliane; Reis, André; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Current Issues in Molecular Biology, 2023)
Background: Individual radiosensitivity is an important factor in the occurrence of undesirable consequences of radiotherapy. The potential for increased radiosensitivity has been linked to highly penetrant heterozygous mutations in DNA repair genes such as BRCA1 and BRCA2. By studying the chromosomal radiosensitivity of BRCA1/2 mutation carriers compared to the general population, we study whether increased chromosomal radiation sensitivity is observed in patients with BRCA1/2 variants. Methods: Three-color-fluorescence in situ hybridization was performed on ex vivo-irradiated peripheral blood lymphocytes from 64 female patients with a heterozygous germline BRCA1 or BRCA2 mutation. Aberrations in chromosomes #1, #2 and #4 were analyzed. Mean breaks per metaphase (B/M) served as the parameter for chromosomal radiosensitivity. The results were compared with chromosomal radiosensitivity in a cohort of generally healthy individuals and patients with rectal cancer or breast cancer. Results: Patients with BRCA1/2 mutations (n = 64; B/M 0.47) overall showed a significantly higher chromosomal radiosensitivity than general healthy individuals (n = 211; B/M 0.41) and patients with rectal cancer (n = 379; B/M 0.44) and breast cancer (n = 147; B/M 0.45) without proven germline mutations. Chromosomal radiosensitivity varied depending on the locus of the BRCA1/2 mutation. Conclusions: BRCA1/2 mutations result in slightly increased chromosomal sensitivity to radiation. A few individual patients have a marked increase in radiation sensitivity. Therefore, these patients are at a higher risk for adverse therapeutic consequences.
CRIS-Team Scopus Importer:2023-09-08
Keywords: BRCA1; BRCA2; breast cancer; chromosomal radiosensitivity; FISH assay; radiation oncology; radiation sensitivity testing; radiotherapy

Factors Influencing Decision-Making for or against Adjuvant and Neoadjuvant Chemotherapy in Postmenopausal Hormone Receptor-Positive Breast Cancer Patients in the EvAluate-TM Study - Gaß, Paul; Fasching, Peter; Fehm, Tanja; De Waal, Johann; Rezai, Mahdi; Baier, Bernd; Baake, Gerold; Kolberg, Hans-Christian; Guggenberger, Martin; Warm, Mathias; Harbeck, Nadia; Wuerstlein, Rachel; et al. (Breast Care, 2016)
BACKGROUND: Decision-making for or against neoadjuvant or adjuvant chemotherapy in postmenopausal patients with hormone receptor-positive breast cancer does not follow any clear guidelines, and some patients may unnecessarily undergo chemotherapy and be exposed to the associated toxicity. The aim of this study was to identify the patient population for whom this issue may bear relevance. METHODS: Patients being treated with letrozole in the prospective multicenter noninterventional EvAluate-TM study were recruited. The percentage of patients receiving chemotherapy and factors associated with chemotherapy administration were identified. RESULTS: In all, 3,924 (37.4%) patients received chemotherapy before treatment with letrozole. Of these, 293 (20%) underwent neoadjuvant therapy. Younger age was predictive for both adjuvant and neoadjuvant therapy. Overall, decisions in favor of administering chemotherapy are more likely to be made in patients with a higher body mass index (BMI), and neoadjuvant chemotherapy is administered at a higher rate in women with a lower BMI. Concomitant medication influenced the overall decision-making regarding chemotherapy, irrespective of whether it was given on a neoadjuvant or adjuvant basis. CONCLUSION: There is an ongoing debate as to whether all of the many patients who receive chemotherapy actually benefit from it. Neoadjuvant chemotherapy is frequently administered in this patient population, and this should encourage further research to resolve current clinical and research issues.
EVALuna2:33331

FANCM missense variants and breast cancer risk: a case-control association study of 75,156 European women - Figlioli, Gisella; Billaud, Amandine; Ahearn, Thomas U.; Antonenkova, Natalia N.; Becher, Heiko; Beckmann, Matthias; Behrens, Sabine; Benitez, Javier; Bermisheva, Marina; Blok, Marinus J.; Bogdanova, Natalia; Bonanni, Bernardo; et al. (European Journal of Human Genetics, 2023)
Evidence from literature, including the BRIDGES study, indicates that germline protein truncating variants (PTVs) in FANCM confer moderately increased risk of ER-negative and triple-negative breast cancer (TNBC), especially for women with a family history of the disease. Association between FANCM missense variants (MVs) and breast cancer risk has been postulated. In this study, we further used the BRIDGES study to test 689 FANCM MVs for association with breast cancer risk, overall and in ER-negative and TNBC subtypes, in 39,885 cases (7566 selected for family history) and 35,271 controls of European ancestry. Sixteen common MVs were tested individually; the remaining rare 673 MVs were tested by burden analyses considering their position and pathogenicity score. We also conducted a meta-analysis of our results and those from published studies. We did not find evidence for association for any of the 16 variants individually tested. The rare MVs were significantly associated with increased risk of ER-negative breast cancer by burden analysis comparing familial cases to controls (OR = 1.48; 95% CI 1.07-2.04; P = 0.017). Higher ORs were found for the subgroup of MVs located in functional domains or predicted to be pathogenic. The meta-analysis indicated that FANCM MVs overall are associated with breast cancer risk (OR = 1.22; 95% CI 1.08-1.38; P = 0.002). Our results support the definition from previous analyses of FANCM as a moderate-risk breast cancer gene and provide evidence that FANCM MVs could be low/moderate risk factors for ER-negative and TNBC subtypes. Further genetic and functional analyses are necessary to clarify better the increased risks due to FANCM MVs.
CRIS-Team WoS Importer:2023-04-07

Feasibility and Acceptance of Self-Guided Mobile Ultrasound among Pregnant Women in Routine Prenatal Care - Pontones, Constanza; Titzmann, Adriana; Hübner, Hanna; Danzberger, Nina; Rübner, Matthias; Häberle, Lothar; Eskofier, Björn; Nissen, Michael; Kehl, Sven; Faschingbauer, Florian; Beckmann, Matthias; Fasching, Peter; et al. (Journal of Clinical Medicine, 2023)
Background and objectives: Mobile and remote ultrasound devices are becoming increasingly available. The benefits and possible risks of self-guided ultrasound examinations conducted by pregnant women at home have not yet been well explored. This study investigated aspects of feasibility and acceptance, as well as the success rates of such examinations. Methods: In this prospective, single-center, interventional study, forty-six women with singleton pregnancies between 17 + 0 and 29 + 6 weeks of gestation were included in two cohorts, using two different mobile ultrasound systems. The participants examined the fetal heartbeat, fetal profile and amniotic fluid. Aspects of feasibility and acceptance were evaluated using a questionnaire. Success rates in relation to image and video quality were evaluated by healthcare professionals. Results: Two thirds of the women were able to imagine performing the self-guided examination at home, but 87.0% would prefer live support by a professional. Concerns about their own safety and that of the child were expressed by 23.9% of the women. Success rates for locating the target structure were 52.2% for videos of the fetal heartbeat, 52.2% for videos of the amniotic fluid in all four quadrants and 17.9% for videos of the fetal profile. Conclusion: These results show wide acceptance of self-examination using mobile systems for fetal ultrasonography during pregnancy. Image quality was adequate for assessing the amniotic fluid and fetal heartbeat in most participants. Further studies are needed to determine whether ultrasound self-examinations can be implemented in prenatal care and how this would affect the fetomaternal outcome.
CRIS-Team Scopus Importer:2023-07-28
Keywords: acceptance; feasibility; mobile ultrasound; pregnancy; prenatal care; self-guided ultrasound

Feasibility of internal inguinoperitoneal drainage after inguinofemoral lymphadenectomy in vulvar cancer - Dall, Peter; Hildebrandt, Thomas; Du Bois, Andreas; Boetel, Eric; Ahlfaenger, Janine; Beckmann, Matthias; Bommert, Mareike (Archives of Gynecology and Obstetrics, 2020)
Purpose: Despite the introduction of sentinel node biopsy in patients with vulvar cancer, still approximately 50% of all patients have to undergo an inguinofemoral lymphadenectomy. This is associated with a high incidence of postoperative complications, which may be influenced by inguinal drain management. The aim of this study was to investigate the feasibility of a new surgical technique regarding drain management with an inguinoperitoneal drainage. Methods: A retrospective analysis of 21 vulvar cancer patients with inguinofemoral lymphadenectomy was conducted. A silicone drain was circularly placed with the perforated end in the groin and the other end in the space of Douglas. The removal after 3 months was performed under local anesthesia. All patients were questioned during clinical follow-up regarding their personal experiences with the procedure, the occurrence of complications, and side effects using a clinical questionnaire. Results: In 100% of the patients, the procedure was feasible. Regarding the number of groin punctures due to lymphocyst formation, 15 (71.4%) patients did not need any intervention and 3 (14.3%) patients needed 1–3 punctures. The patient satisfaction with the internal drainage was ranked as good by 17 (81.0%) patients and as moderate by 1 (4.8%) patient. In 3 (14.3%) patients, information about the number of groin punctures and the patient satisfaction were missing. Conclusion: Inguinoperitoneal drainage after inguinofemoral lymphadenectomy in vulvar cancer patients is feasible and safe and a patient satisfaction of 81% is promising. For definitive conclusions regarding the efficacy of this technique, further investigations and prospective multicenter trials are needed.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Inguinofemoral lymphadenectomy; Inguinoperitoneal drainage; Postoperative complications; Vulvar cancer

Femoral Placement of Totally Implantable Venous Access Ports in Patients with Bilateral Breast Cancer - Almási-Sperling, Veronika; Hieber, Sabrina; Lermann, J.; Strahl, Olga; Beckmann, Matthias; Lang, Werner; Sagban, T. A. (Geburtshilfe und Frauenheilkunde, 2016)
Purpose: Aim of this study was to determine the rate of complications following femoral placement of totally implantable venous access ports (f-TIVAP) in women with bilateral breast cancer, with a special focus on long-term function, deep vein thrombosis (DVT), and port infection. Methods: 73 patients with bilateral breast cancer treated between October 2000 and January 2013 with placement of an f-TIVAP using a transfemoral approach were retrospectively reviewed. All patients were followed up, and all complications of f-TIVAP were recorded. Results: The median age was 62.5 years (range: 35-86 years). Four patients received f-TIVAP under local anesthesia, and 69 underwent placement under general anesthesia. Mean follow-up was 33.7 months (SD 25.9; range: 0.2-93.5 months). Complications over the entire period of observation included infections in 21 %, DVT in 19 % and catheter occlusion in 12 %. Patients receiving chemotherapy who developed leukopenia were more likely to experience DVT at the access site (p = 0.037). There was a trend towards a higher infection rate when the device was used more often (p = 0.084). Conclusion: Although the rates of complications in the longer term, especially device infections and DVTs, appeared to be relatively high, TIVAP implantation using femoral vein access is recommended in patients with bilateral breast cancer not suitable for cephalic vein cut-down.
EVALuna2:15270

FemZone trial: a randomized phase II trial comparing neoadjuvant letrozole and zoledronic acid with letrozole in primary breast cancer patients - Fasching, Peter; Jud, Sebastian; Hauschild, Maik; Kuemmel, Sherko; Schuette, Martin; Warm, Matthias; Hanf, Volker; Grab, Dieter; Krocker, Jutta; Stickeler, Elmar; Kreienberg, Rolf; Mueller, Thomas; et al. (BMC Cancer, 2014)
The objective of this prospectively randomized phase II trial (Trial registration: EUCTR2004-004007-37-DE) was to compare the clinical response of primary breast cancer patients to neoadjuvant therapy with letrozole alone (LET) or letrozole and zoledronic acid (LET + ZOL).Patients were randomly assigned to receive either LET 2.5 mg/day (n = 79) or the combination of LET 2.5 mg/day and a total of seven infusions of ZOL 4 mg every 4 weeks (n = 89) for 6 months. Primary endpoint was clinical response rate as assessed by mammogram readings. The study was terminated prematurely due to insufficient recruitment. We report here on an exploratory analysis of this data.Central assessment of tumor sizes during the treatment period was available for 131 patients (66 LET, 65 LET + ZOL). Clinical responses (complete or partial) were seen in 54.5% (95% CI: 41.8-66.9) of the patients in the LET arm and 69.2% (95% CI: 56.6-80.1) of those in the LET + ZOL arm (P = 0.106). A multivariate model showed an OR of 1.72 (95% CI: 0.83-3.59) for the experimental arm.No increase in the clinical response rate was observed with the addition of ZOL to a neoadjuvant treatment regimen with LET. However a trend towards a better reponse in the LET + ZOL arm could be observed. This trend is consistent with previous studies that have investigated the addition of ZOL to chemotherapy, and it may support the evidence for a direct antitumor action of zoledronic acid.
EVALuna2:14433

Fertility Preservation for Patients with Malignant Disease. Guideline of the DGGG, DGU and DGRM (S2k-Level, AWMF Registry No. 015/082, November 2017) - Recommendations and Statements for Girls and Women - Dittrich, Ralf; Kliesch, Sabine; Schuering, Andreas; Balcerek, Magdalena; Baston-Buest, Dunja M.; Beck, Ramona; Beckmann, Matthias; Behringer, Karolin; Borgmann-Staudt, Anja; Cremer, Wolfgang; Denzer, Christian; Diemer, Thorsten; et al. (Geburtshilfe und Frauenheilkunde, 2018)
The aim of this official guideline published by the German Society of Gynecology and Obstetrics (DGGG) and coordinated with the German Society of Urology (DGU) and the German Society of Reproductive Medicine (DGRM) is to provide consensus-based recommendations, obtained by evaluating the relevant literature, on counseling and fertility preservation for prepubertal girls and boys as well as patients of reproductive age. Statements and recommendations for girls and women are presented below. Statements or recommendations for boys and men are not the focus of this guideline.This S2k guideline was developed at the suggestion of the guideline commission of the DGGG, DGU and DGRM and represents the structured consensus of representative members from various professional associations (n = 40).The guideline provides recommendations on counseling and fertility preservation for women and girls which take account of the patient's personal circumstances, the planned oncologic therapy and the individual risk profile as well as the preferred approach for selected tumor entities.
EVALuna2:60163

Fertility preservation in breast cancer patients by embryo cryopreservation after ovarian stimulation with letrozole and FSH - Beckmann, Matthias; Findeklee, Sebastian (Strahlentherapie und Onkologie, 2015)
EVALuna2:17546

Fertility Preservation: Optimization of Follicle Extraction before Cultivation in the Artificial Ovary - Keckstein, P.; Fattahi, Amir; Liverani, Liliana; Dittrich, Ralf; Hoffmann, I; Boccaccini, Aldo R.; Beckmann, Matthias; Bleisinger, Nathalie (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Fertility protection: complications of surgery and results of removal and transplantation of ovarian tissue - Beckmann, Matthias; Dittrich, Ralf; Lotz, Laura; Van Der Ven, Karin; Van Der Ven, Hans H.; Liebenthron, Jana; Korell, Matthias; Frambach, Torsten; Suetterlin, Marc; Schwab, Roxana; Seitz, Stefan; Mueller, Andreas; et al. (Reproductive Biomedicine Online, 2018)
Fertility-preserving measures are becoming important for patients receiving oncological treatment. One method involves cryopreservation of ovarian tissue and transplanting it when treatment is completed. We report complications resulting from surgical and fertility medicine, and the results of procedures for the removal and transplantation of ovarian tissue carried out within the FertiProtekt network. A survey using a structured questionnaire was conducted among the FertiProtekt network centres between November 2015 and June 2016. The analysis included surgical techniques used to remove and transplant ovarian tissue, surgical complications and results. Laparoscopic removal and transplantation of ovarian tissue have a low risk of complications. Surgical complications occurred in three of the network's 1373 ovarian tissue removals (n = 1302) and transplantations (n = 71); two complications (0.2%) occurred during removal and one during transplantation. Menstruation resumed in 47 out of 58 women (81%) who underwent ovarian tissue transplantation. Hormonal activity occurred in 63.2% of transplantations with a follow-up of 6 months or over. Sixteen pregnancies occurred in 14 patients, with nine births. The risks and complications of removal and transplantation of ovarian tissue are similar to those of standard laparoscopy. These procedures are becoming standard for fertility protection in cancer patients.
EVALuna2:36435

Fertility Protection in Female Oncology Patients: How Should Patients Be Counseled? - Findeklee, S.; Lotz, Laura; Heusinger, K.; Hoffmann, I.; Dittrich, Ralf; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2015)
Protecting the fertility of patients with oncologic disease is becoming more and more important, as fulfilling the wish to have children is increasingly occurring at a later stage in life and long-term survival rates after cancer are continuing to improve. A number of fertility-preserving options exist. In addition to techniques which have been around for some time such as medical ovarian suppression, ovarian transposition, and organ-preserving surgery, there are other, more recent, innovative methods which have developed over the last few years such as cryopreservation of oocytes or ovarian tissue transplantation after completing cancer therapy. As every procedure has its specific advantages and disadvantages, informed patient consent is essential. The physician's aim must be to select the optimal procedure for each patient. The extent of patients' information about the options to preserve fertility in women with oncologic disease remains limited. One of the main reasons for this is that clinicians are not sure how to inform patients about existing procedures and methods. The aim of this review article is to provide help in clinical practice.
EVALuna2:17544

FGF receptor genes and breast cancer susceptibility: results from the Breast Cancer Association Consortium - Agarwal, D.; Pineda, S.; Michailidou, K.; Herranz, J.; Pita, G.; Moreno, L. T.; Alonso, M. R.; Dennis, J.; Wang, Q.; Bolla, M. K.; Meyer, K. B.; Menendez-Rodriguez, P.; et al. (British Journal of Cancer, 2014)
Breast cancer is one of the most common malignancies in women. Genome-wide association studies have identified FGFR2 as a breast cancer susceptibility gene. Common variation in other fibroblast growth factor (FGF) receptors might also modify risk. We tested this hypothesis by studying genotyped single-nucleotide polymorphisms (SNPs) and imputed SNPs in FGFR1, FGFR3, FGFR4 and FGFRL1 in the Breast Cancer Association Consortium.Data were combined from 49 studies, including 53 835 cases and 50 156 controls, of which 89 050 (46 450 cases and 42 600 controls) were of European ancestry, 12 893 (6269 cases and 6624 controls) of Asian and 2048 (1116 cases and 932 controls) of African ancestry. Associations with risk of breast cancer, overall and by disease sub-type, were assessed using unconditional logistic regression.Little evidence of association with breast cancer risk was observed for SNPs in the FGF receptor genes. The strongest evidence in European women was for rs743682 in FGFR3; the estimated per-allele odds ratio was 1.05 (95% confidence interval=1.02-1.09, P=0.0020), which is substantially lower than that observed for SNPs in FGFR2.Our results suggest that common variants in the other FGF receptors are not associated with risk of breast cancer to the degree observed for FGFR2.
EVALuna2:9221

Filtration based assessment of CTCs and CellSearch® based assessment are both powerful predictors of prognosis for metastatic breast cancer patients - Hübner, Hanna; Fasching, Peter; Gumbrecht, Walter; Jud, Sebastian; Rauh, Claudia; Matzas, Mark; Paulicka, Peter; Friedrich, Katja; Lux, Michael P.; Volz, Bernhard; Gaß, Paul; Häberle, Lothar; et al. (BMC Cancer, 2018)
The assessment of circulating tumor cells (CTCs) has been shown to enable monitoring of treatment response and early detection of metastatic breast cancer (MBC) recurrence. The aim of this study was to compare a well-established CTC detection method based on immunomagnetic isolation with a new, filtration-based platform.In this prospective study, two 7.5 ml blood draws were obtained from 60 MBC patients and CTC enumeration was assessed using both the CellSearch® and the newly developed filtration-based platform. We analyzed the correlation of CTC-positivity between both methods and their ability to predict prognosis. Overall survival (OS) was calculated and Kaplan-Meier curves were estimated with thresholds of >=1 and >=5 detected CTCs.The CTC positivity rate of the CellSearch® system was 56.7% and of the filtration-based platform 66.7%. There was a high correlation of CTC enumeration obtained with both methods. The OS for patients without detected CTCs, regardless of the method used, was significantly higher compared to patients with one or more CTCs (p < 0.001). The median OS of patients with no CTCs vs. >= 1 CTC assessed by CellSearch® was 1.83 years (95% CI: 1.63-2.02) vs. 0.74 years (95% CI: 0.51-1.52). If CTCs were detected by the filtration-based method the median OS times were 1.88 years (95% CI: 1.74-2.03) vs. 0.59 years (95% CI: 0.38-0.80).The newly established EpCAM independently filtration-based system is a suitable method to determine CTC counts for MBC patients. Our study confirms CTCs as being strong predictors of prognosis in our population of MBC patients.
EVALuna2:51529

Fine-mapping identifies two additional breast cancer susceptibility loci at 9q31.2 - Orr, Nick; Dudbridge, Frank; Dryden, Nicola; Maguire, Sarah; Novo, Daniela; Perrakis, Eleni; Johnson, Nichola; Ghoussaini, Maya; Hopper, John L.; Southey, Melissa C.; Apicella, Carmel; Stone, Jennifer; et al. (Human Molecular Genetics, 2015)
We recently identified a novel susceptibility variant, rs865686, for estrogen-receptor positive breast cancer at 9q31.2. Here, we report a fine-mapping analysis of the 9q31.2 susceptibility locus using 43 160 cases and 42 600 controls of European ancestry ascertained from 52 studies and a further 5795 cases and 6624 controls of Asian ancestry from nine studies. Single nucleotide polymorphism (SNP) rs676256 was most strongly associated with risk in Europeans (odds ratios [OR] = 0.90 [0.88-0.92]; P-value = 1.58 × 10(-25)). This SNP is one of a cluster of highly correlated variants, including rs865686, that spans 14.5 kb. We identified two additional independent association signals demarcated by SNPs rs10816625 (OR = 1.12 [1.08-1.17]; P-value = 7.89 × 10(-09)) and rs13294895 (OR = 1.09 [1.06-1.12]; P-value = 2.97 × 10(-11)). SNP rs10816625, but not rs13294895, was also associated with risk of breast cancer in Asian individuals (OR = 1.12 [1.06-1.18]; P-value = 2.77 × 10(-05)). Functional genomic annotation using data derived from breast cancer cell-line models indicates that these SNPs localise to putative enhancer elements that bind known drivers of hormone-dependent breast cancer, including ER-?, FOXA1 and GATA-3. In vitro analyses indicate that rs10816625 and rs13294895 have allele-specific effects on enhancer activity and suggest chromatin interactions with the KLF4 gene locus. These results demonstrate the power of dense genotyping in large studies to identify independent susceptibility variants. Analysis of associations using subjects with different ancestry, combined with bioinformatic and genomic characterisation, can provide strong evidence for the likely causative alleles and their functional basi
EVALuna2:9279

Fine-Mapping of the 1p11.2 Breast Cancer Susceptibility Locus - Horne, Hisani N.; Chung, Charles C.; Zhang, Han; Yu, Kai; Prokunina-Olsson, Ludmila; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Hopper, John L.; Southey, Melissa C.; Schmidt, Marjanka K.; et al. (PLoS ONE, 2016)
The Cancer Genetic Markers of Susceptibility genome-wide association study (GWAS) originally identified a single nucleotide polymorphism (SNP) rs11249433 at 1p11.2 associated with breast cancer risk. To fine-map this locus, we genotyped 92 SNPs in a 900kb region (120,505,799-121,481,132) flanking rs11249433 in 45,276 breast cancer cases and 48,998 controls of European, Asian and African ancestry from 50 studies in the Breast Cancer Association Consortium. Genotyping was done using iCOGS, a custom-built array. Due to the complicated nature of the region on chr1p11.2: 120,300,000-120,505,798, that lies near the centromere and contains seven duplicated genomic segments, we restricted analyses to 429 SNPs excluding the duplicated regions (42 genotyped and 387 imputed). Per-allelic associations with breast cancer risk were estimated using logistic regression models adjusting for study and ancestry-specific principal components. The strongest association observed was with the original identified index SNP rs11249433 (minor allele frequency (MAF) 0.402; per-allele odds ratio (OR) = 1.10, 95% confidence interval (CI) 1.08-1.13, P = 1.49 x 10-21). The association for rs11249433 was limited to ER-positive breast cancers (test for heterogeneity P≤8.41 x 10-5). Additional analyses by other tumor characteristics showed stronger associations with moderately/well differentiated tumors and tumors of lobular histology. Although no significant eQTL associations were observed, in silico analyses showed that rs11249433 was located in a region that is likely a weak enhancer/promoter. Fine-mapping analysis of the 1p11.2 breast cancer susceptibility locus confirms this region to be limited to risk to cancers that are ER-positive.
EVALuna2:33323

Fine-mapping of the HNF1B multicancer locus identifies candidate variants that mediate endometrial cancer risk - Painter, Jodie N.; O'Mara, Tracy A.; Batra, Jyotsna; Cheng, Timothy; Lose, Felicity A.; Dennis, Joe; Michailidou, Kyriaki; Tyrer, Jonathan P.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; Kaufmann, Susanne; et al. (Human Molecular Genetics, 2015)
Common variants in the hepatocyte nuclear factor 1 homeobox B (HNF1B) gene are associated with the risk of Type II diabetes and multiple cancers. Evidence to date indicates that cancer risk may be mediated via genetic or epigenetic effects on HNF1B gene expression. We previously found single-nucleotide polymorphisms (SNPs) at the HNF1B locus to be associated with endometrial cancer, and now report extensive fine-mapping and in silico and laboratory analyses of this locus. Analysis of 1184 genotyped and imputed SNPs in 6608 Caucasian cases and 37 925 controls, and 895 Asian cases and 1968 controls, revealed the best signal of association for SNP rs11263763 (P = 8.4 × 10(-14), odds ratio = 0.86, 95% confidence interval = 0.82-0.89), located within HNF1B intron 1. Haplotype analysis and conditional analyses provide no evidence of further independent endometrial cancer risk variants at this locus. SNP rs11263763 genotype was associated with HNF1B mRNA expression but not with HNF1B methylation in endometrial tumor samples from The Cancer Genome Atlas. Genetic analyses prioritized rs11263763 and four other SNPs in high-to-moderate linkage disequilibrium as the most likely causal SNPs. Three of these SNPs map to the extended HNF1B promoter based on chromatin marks extending from the minimal promoter region. Reporter assays demonstrated that this extended region reduces activity in combination with the minimal HNF1B promoter, and that the minor alleles of rs11263763 or rs8064454 are associated with decreased HNF1B promoter activity. Our findings provide evidence for a single signal associated with endometrial cancer risk at the HNF1B locus, and that risk is likely mediated via altered HNF1B gene expression.
EVALuna2:9243

Fine-scale mapping of 8q24 locus identifies multiple independent risk variants for breast cancer - Shi, Jiajun; Zhang, Yanfeng; Zheng, Wei; Michailidou, Kyriaki; Ghoussaini, Maya; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Lush, Michael; Milne, Roger L.; Shu, Xiao-Ou; Beesley, Jonathan; et al. (International Journal of Cancer, 2016)
Previous genome-wide association studies among women of European ancestry identified two independent breast cancer susceptibility loci represented by single nucleotide polymorphisms (SNPs) rs13281615 and rs11780156 at 8q24. A fine-mapping study across 2.06 Mb (chr8:127,561,724-129,624,067, hg19) in 55,540 breast cancer cases and 51,168 controls within the Breast Cancer Association Consortium was conducted. Three additional independent association signals in women of European ancestry, represented by rs35961416 (OR = 0.95, 95% CI = 0.93-0.97, conditional p = 5.8 × 10(-6) ), rs7815245 (OR = 0.94, 95% CI = 0.91-0.96, conditional p = 1.1 × 10(-6) ) and rs2033101 (OR = 1.05, 95% CI = 1.02-1.07, conditional p = 1.1 × 10(-4) ) were found. Integrative analysis using functional genomic data from the Roadmap Epigenomics, the Encyclopedia of DNA Elements project, the Cancer Genome Atlas and other public resources implied that SNPs rs7815245 in Signal 3, and rs1121948 in Signal 5 (in linkage disequilibrium with rs11780156, r(2) = 0.77), were putatively functional variants for two of the five independent association signals. The results highlighted multiple 8q24 variants associated with breast cancer susceptibility in women of European ancestry.
EVALuna2:33319

Fine scale mapping of the 17q22 breast cancer locus using dense SNPs, genotyped within the Collaborative Oncological Gene-Environment Study (COGs) - Darabi, Hatef; Beesley, Jonathan; Droit, Arnaud; Kar, Siddhartha; Nord, Silje; Marjaneh, Mahdi Moradi; Soucy, Penny; Michailidou, Kyriaki; Ghoussaini, Maya; Wahl, Hanna Fues; Bolla, Manjeet K.; Wang, Qin; et al. (Scientific Reports, 2016)
Genome-wide association studies have found SNPs at 17q22 to be associated with breast cancer risk. To identify potential causal variants related to breast cancer risk, we performed a high resolution fine-mapping analysis that involved genotyping 517 SNPs using a custom Illumina iSelect array (iCOGS) followed by imputation of genotypes for 3,134 SNPs in more than 89,000 participants of European ancestry from the Breast Cancer Association Consortium (BCAC). We identified 28 highly correlated common variants, in a 53 Kb region spanning two introns of the STXBP4 gene, that are strong candidates for driving breast cancer risk (lead SNP rs2787486 (OR = 0.92; CI 0.90-0.94; P = 8.96 × 10(-15))) and are correlated with two previously reported risk-associated variants at this locus, SNPs rs6504950 (OR = 0.94, P = 2.04 × 10(-09), r(2) = 0.73 with lead SNP) and rs1156287 (OR = 0.93, P = 3.41 × 10(-11), r(2) = 0.83 with lead SNP). Analyses indicate only one causal SNP in the region and several enhancer elements targeting STXBP4 are located within the 53 kb association signal. Expression studies in breast tumor tissues found SNP rs2787486 to be associated with increased STXBP4 expression, suggesting this may be a target gene of this locus.
EVALuna2:33320

Fine-scale mapping of the 4q24 locus identifies two independent loci associated with breast cancer risk - Guo, Xingyi; Long, Jirong; Zeng, Chenjie; Michailidou, Kyriaki; Ghoussaini, Maya; Bolla, Manjeet K.; Wang, Qin; Milne, Roger L.; Shu, Xiao-Ou; Cai, Qiuyin; Beesley, Jonathan; Kar, Siddhartha P.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
A recent association study identified a common variant (rs9790517) at 4q24 to be associated with breast cancer risk. Independent association signals and potential functional variants in this locus have not been explored.We conducted a fine-mapping analysis in 55,540 breast cancer cases and 51,168 controls from the Breast Cancer Association Consortium.Conditional analyses identified two independent association signals among women of European ancestry, represented by rs9790517 [conditional P = 2.51 × 10(-4); OR, 1.04; 95% confidence interval (CI), 1.02-1.07] and rs77928427 (P = 1.86 × 10(-4); OR, 1.04; 95% CI, 1.02-1.07). Functional annotation using data from the Encyclopedia of DNA Elements (ENCODE) project revealed two putative functional variants, rs62331150 and rs73838678 in linkage disequilibrium (LD) with rs9790517 (r(2) >= 0.90) residing in the active promoter or enhancer, respectively, of the nearest gene, TET2. Both variants are located in DNase I hypersensitivity and transcription factor-binding sites. Using data from both The Cancer Genome Atlas (TCGA) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC), we showed that rs62331150 was associated with level of expression of TET2 in breast normal and tumor tissue.Our study identified two independent association signals at 4q24 in relation to breast cancer risk and suggested that observed association in this locus may be mediated through the regulation of TET2.Fine-mapping study with large sample size warranted for identification of independent loci for breast cancer risk.
EVALuna2:17572

Fine-scale mapping of the 5q11.2 breast cancer locus reveals at least three independent risk variants regulating MAP3K1 - Glubb, Dylan M.; Maranian, Mel J.; Michailidou, Kyriaki; Pooley, Karen A.; Meyer, Kerstin B.; Kar, Siddhartha; Carlebur, Saskia; O'Reilly, Martin; Betts, Joshua A.; Hillman, Kristine M.; Kaufmann, Susanne; Beesley, Jonathan; et al. (American Journal of Human Genetics, 2015)
Genome-wide association studies (GWASs) have revealed SNP rs889312 on 5q11.2 to be associated with breast cancer risk in women of European ancestry. In an attempt to identify the biologically relevant variants, we analyzed 909 genetic variants across 5q11.2 in 103,991 breast cancer individuals and control individuals from 52 studies in the Breast Cancer Association Consortium. Multiple logistic regression analyses identified three independent risk signals: the strongest associations were with 15 correlated variants (iCHAV1), where the minor allele of the best candidate, rs62355902, associated with significantly increased risks of both estrogen-receptor-positive (ER(+): odds ratio [OR] = 1.24, 95% confidence interval [CI] = 1.21-1.27, ptrend = 5.7 × 10(-44)) and estrogen-receptor-negative (ER(-): OR = 1.10, 95% CI = 1.05-1.15, ptrend = 3.0 × 10(-4)) tumors. After adjustment for rs62355902, we found evidence of association of a further 173 variants (iCHAV2) containing three subsets with a range of effects (the strongest was rs113317823 [pcond = 1.61 × 10(-5)]) and five variants composing iCHAV3 (lead rs11949391; ER(+): OR = 0.90, 95% CI = 0.87-0.93, pcond = 1.4 × 10(-4)). Twenty-six percent of the prioritized candidate variants coincided with four putative regulatory elements that interact with the MAP3K1 promoter through chromatin looping and affect MAP3K1 promoter activity. Functional analysis indicated that the cancer risk alleles of four candidates (rs74345699 and rs62355900 [iCHAV1], rs16886397 [iCHAV2a], and rs17432750 [iCHAV3]) increased MAP3K1 transcriptional activity. Chromatin immunoprecipitation analysis revealed diminished GATA3 binding to the minor (cancer-protective) allele of rs17432750, indicating a mechanism for its action. We propose that the cancer risk alleles act to increase MAP3K1 expression in vivo and might promote breast cancer cell surviva
EVALuna2:9276

Five endometrial cancer risk loci identified through genome-wide association analysis - Cheng, Timothy H. T.; Thompson, Deborah J.; O'Mara, Tracy A.; Painter, Jodie N.; Glubb, Dylan M.; Flach, Susanne; Lewis, Annabelle; French, Juliet D.; Freeman-Mills, Luke; Church, David; Gorman, Maggie; Martin, Lynn; et al. (Nature Genetics, 2016)
We conducted a meta-analysis of three endometrial cancer genome-wide association studies (GWAS) and two follow-up phases totaling 7,737 endometrial cancer cases and 37,144 controls of European ancestry. Genome-wide imputation and meta-analysis identified five new risk loci of genome-wide significance at likely regulatory regions on chromosomes 13q22.1 (rs11841589, near KLF5), 6q22.31 (rs13328298, in LOC643623 and near HEY2 and NCOA7), 8q24.21 (rs4733613, telomeric to MYC), 15q15.1 (rs937213, in EIF2AK4, near BMF) and 14q32.33 (rs2498796, in AKT1, near SIVA1). We also found a second independent 8q24.21 signal (rs17232730). Functional studies of the 13q22.1 locus showed that rs9600103 (pairwise r(2) = 0.98 with rs11841589) is located in a region of active chromatin that interacts with the KLF5 promoter region. The rs9600103[T] allele that is protective in endometrial cancer suppressed gene expression in vitro, suggesting that regulation of the expression of KLF5, a gene linked to uterine development, is implicated in tumorigenesis. These findings provide enhanced insight into the genetic and biological basis of endometrial cancer.
EVALuna2:9326

From the Past to the Future The 1st Volume of "Obstetrics and Women's Medicine - Research Findings for Practice". A Review of the 75th Birthday - Ebert, Andreas D.; Beckmann, Matthias; Wallwiener, Diethelm; David, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32950

Früh- und Spättoxizitäten sowie sozialmedizinisch-relevante Folgestörungen bei Brustkrebs-Patientinnen als Basis der Abschätzung des Reha-Bedarfes - Hass, Holger G.; Seywald, Marianne; Stepien, Jürgen; Muco, Blerta; Tanriverdi, Miro; Beckmann, Matthias; Kunzmann, Volker; Wöckel, Achim (Rehabilitation (Germany), 2021)
Introduction Reasonable to the improved prognosis of breast cancer (BC) long-term toxicities and side effects of oncological therapy gain more importance for work ability and social life of BC patients. Aim of this study was the analysis of occurence and differences of treatment-related side effects in relation to type of rehabilitation (so-called AHB vs. later rehabilitation) after therapy for BC. Methods Clinical and patient related data as early and late toxicities after oncological treatment of 8.000 patients with BC (55.7±10.4y) were analyzed and compared with current literature. Results In 23.9% a mastectomy was performed, in 87.3% radiotherapy. In most cases an additional systemic treatment (57,6% CTX, 15,1% anti-Her2, 71% antihormonal treatment) was carried out. In 8.1% women suffered from recurrent or metastatic BC. As most common side effects of multimodal treatment weakness/fatigue (73,6%), insomnia (51,9%), CIPN (33%), lymph edema (13,9%) and drug-induced arthralgia (24,8%) were detected. In addition, 60.4% of women reported high levels of psychological distress. Shortly after therapy typical side effects were drug-induced toxicities (Leucopenia, p<0.0001; anemia, p<0.001; weakness/fatigue p<0.001; CIPN, p<0.0001), whereas in a later course chronic lymphedema (p<0.0001), chronic or recurrent disease (p<0.0001), status after mastectomy (p<0.0001) and psychological distress (p<0.0001) were significantly more often seen. Moreover, in this collective patients were significantly younger (53,7±9,8 vs. 56,3±10,7y). Conclusions In BC patients, significantly different impairments and toxicities were documented between patients with early rehabilitation and patients with later onset of rehabilitation. These data may help to establish more individual and focused rehabilitation concepts in specialized centers.
CRIS-Team Scopus Importer:2021-04-30
Keywords: breast cancer; CIPN; fatigue; indoor rehabilitation; psychological distress

Full field digital mammography (FFDM) versus cmos technology, specimen radiography system (SRS) and tomosynthesis (DBT) - Which system can optimise surgical therapy? - Schulz-Wendtland, Rüdiger; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Brehm, Barbara; Hammon, Matthias; Saake, Marc; Dankerl, Peter; Jud, Sebastian; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: This prospective clinical study aimed to evaluate whether it would be possible to reduce the rate of re-excisions using CMOS technology, a specimen radiography system (SRS) or digital breast tomosynthesis (DBT) compared to a conventional full field digital mammography (FFDM) system. Material and Method: Between 12/2012 and 2/2013 50 patients were diagnosed with invasive breast cancer (BI-RADS™ 5). After histological verification, all patients underwent breast-conserving therapy with intraoperative imaging using 4 different systems and differing magnifications: 1. Inspiration™ (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 m pixel pitch, 8 lp/mm; 2. BioVision™ (Bioptics, Tucson, AZ, USA), CMOS technology, photodiode array, flat panel, tungsten source, focus 0.05, resolution 50 m pixel pitch, 12 lp/mm; 3. the Trident™ specimen radiography system (SRS) (Hologic, Bedford, MA, USA), amorphous selenium, tungsten source, focus 0.05, resolution 70 m pixel pitch, 7.1 lp/mm; 4. tomosynthesis (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 m pixel pitch, 8 lp/mm, angular range 50 degrees, 25 projections, scan time > 20 s, geometry: uniform scanning, reconstruction: filtered back projection. The 600 radiographs were prospectively shown to 3 radiologists. Results: Of the 50 patients with histologically proven breast cancer (BI-RADS™ 6), 39 patients required no further surgical therapy (re-excision) after breast-conserving surgery. A retrospective analysis (n = 11) showed a significant (p < 0.05) increase of sensitivity with the BioVision™, the Trident™ and tomosynthesis compared to the Inspiration™ at a magnification of 1.0: 2.0 or 1.0: 1.0 (tomosynthesis) (2.6, 3.3 or 3.6 %), i.e. re-excision would not have been necessary in 2, 3 or 4 patients, respectively, compared to findings obtained with a standard magnification of 1.0: 1.0. Conclusion: The sensitivity of the BioVision™, the Trident™ and tomosynthesis was significantly (p < 0.05) higher and the rate of re-excisions was reduced compared to FFDM using a conventional detector at a magnification of 2.0 but without zooming. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast; breast cancer; breast malignancy; mammography

Fully automated nipple detection in 3D breast ultrasound images - Wang, Lei; Böhler, Tobias; Zöhrer, Fabian; Georgii, Joachim; Rauh, Claudia; Fasching, Peter; Brehm, Barbara; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Uder, Michael; Hahn, Horst K. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
Nipple position provides useful diagnostic informations in reading automated 3D breast ultrasound (ABUS) images. The identification of nipples is required to localize and determine the quadrants of breast lesions. Additionally, the nipple position serves as an effective landmark to register an ABUS image to other imaging modalities, such as digital mammography, breast magnet resonance imaging (MRI), or tomosynthesis. Nevertheless, the presence of speckle noise induced by interference waves and variant imaging directions in ultrasonography poses challenges to the task. In this work, we propose a fast and automated algorithm to detect nipples in 3D breast ultrasound images. The method fully takes advantages of the consistent characteristics of ultrasonographic signals observed at nipples and employs a multi-scale Laplacian-based blob detector to eventually identify nipple positions. The accuracy of the proposed method was tested on 113 ABUS images, resulting in a distance error of 6.6±8.9 mm (mean ±std). © 2014 Springer International Publishing.
CRIS-Team Scopus Importer:2023-03-08

Fumarate hydratase (FH) deficiency in uterine leiomyomas: recognition by histological features versus blind immunoscreening - Siegler, Lisa; Erber, Ramona; Burghaus, Stefanie; Brodkorb, Tobias; Wachter, David; Wilkinson, Nafisa; Bolton, James; Stringfellow, Helen; Haller, Florian; Beckmann, Matthias; Hartmann, Arndt; Agaimy, Abbas (Virchows Archiv, 2018)
Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome is a rare autosomal dominant disease caused by germline mutations in the fumarate hydratase (FH) gene. Affected individuals develop cutaneous and uterine leiomyomas and aggressive RCC. To date, only few publications described the frequency and morphology of FH-deficient uterine leiomyomas. We reviewed 22 cases collected over 8 years from routine and consultation files based on distinctive histological features. In addition, we screened 580 consecutive uterine leiomyomas from 484 patients, 23 extra-uterine and 8 uterine leiomyosarcomas, and 6 leiomyomas with bizarre nuclei for FH loss using immunohistochemistry (IHC) on tissue microarrays (TMAs). All 22 FH-deficient cases were suspected on H&E sections and confirmed by FH IHC. Patients' ages ranged from 25 to 70 years (median 36). Seventeen patients had multiple nodules (2-14) measuring up to 11.8 cm. None of the patients had stigmata or family history of the HLRCC syndrome. Histologically, all FH-deficient tumors showed consistent and reproducible features as reported previously. FH loss was detected in 2/534 evaluable leiomyomas (0.4%), but in none of leiomyosarcomas. Two of six leiomyomas with bizarre nuclei were FH-deficient. FH-deficient uterine leiomyomas are rare in routine material (= 0.4%). They can be reliably identified or suspected by consistent morphological features. Our data showed predictive morphology to be superior to blind IHC screening for detecting them. The relationship of FH-deficient uterine smooth muscle tumors to the HLRCC syndrome needs further clarification.
EVALuna2:33962

Functional Analysis and Fine Mapping of the 9p22.2 Ovarian Cancer Susceptibility Locus - Buckley, Melissa A.; Woods, Nicholas T.; Tyrer, Jonathan P.; Mendoza-Fandino, Gustavo; Lawrenson, Kate; Hazelett, Dennis J.; Najafabadi, Hamed S.; Gjyshi, Anxhela; Carvalho, Renato S.; Lyra, Paulo C.; Coetzee, Simon G.; Shen, Howard C.; et al. (Cancer Research, 2019)
Genome-wide association studies have identified 40 ovarian cancer risk loci. However, the mechanisms underlying these associations remain elusive. In this study, we conducted a two-pronged approach to identify candidate causal SNPs and assess underlying biological mechanisms at chromosome 9p22.2, the first and most statistically significant associated locus for ovarian cancer susceptibility. Three transcriptional regulatory elements with allele-specific effects and a scaffold/matrix attachment region were characterized and, through physical DNA interactions, BNC2 was established as the most likely target gene. We determined the consensus binding sequence for BNC2 in vitro, verified its enrichment in BNC2 ChIP-seq regions, and validated a set of its downstream target genes. Fine-mapping by dense regional genotyping in over 15,000 ovarian cancer cases and 30,000 controls identified SNPs in the scaffold/ matrix attachment region as among the most likely causal variants. This study reveals a comprehensive regulatory landscape at 9p22.2 and proposes a likely mechanism of susceptibility to ovarian cancer.
CRIS-Team WoS Importer:2019-02-21

Functional mechanisms underlying pleiotropic risk alleles at the 19p13.1 breast-ovarian cancer susceptibility locus - Lawrenson, Kate; Kar, Siddhartha; Mccue, Karen; Kuchenbaeker, Karoline; Michailidou, Kyriaki; Tyrer, Jonathan; Beesley, Jonathan; Ramus, Susan J.; Li, Qiyuan; Delgado, Melissa K.; Lee, Janet M.; Aittomaki, Kristiina; et al. (Nature Communications, 2016)
A locus at 19p13 is associated with breast cancer (BC) and ovarian cancer (OC) risk. Here we analyse 438 SNPs in this region in 46,451 BC and 15,438 OC cases, 15,252 BRCA1 mutation carriers and 73,444 controls and identify 13 candidate causal SNPs associated with serous OC (P=9.2 × 10(-20)), ER-negative BC (P=1.1 × 10(-13)), BRCA1-associated BC (P=7.7 × 10(-16)) and triple negative BC (P-diff=2 × 10(-5)). Genotype-gene expression associations are identified for candidate target genes ANKLE1 (P=2 × 10(-3)) and ABHD8 (P<2 × 10(-3)). Chromosome conformation capture identifies interactions between four candidate SNPs and ABHD8, and luciferase assays indicate six risk alleles increased transactivation of the ADHD8 promoter. Targeted deletion of a region containing risk SNP rs56069439 in a putative enhancer induces ANKLE1 downregulation; and mRNA stability assays indicate functional effects for an ANKLE1 3'-UTR SNP. Altogether, these data suggest that multiple SNPs at 19p13 regulate ABHD8 and perhaps ANKLE1 expression, and indicate common mechanisms underlying breast and ovarian cancer risk.
EVALuna2:33322

Galactography with Tomosynthesis Technique (Galactomosynthesis) - Renaissance of a Method? - Schulz-Wendtland, Rüdiger; Preuss, Caroline; Fasching, Peter; Löhberg, Christian; Lux, Michael P.; Emons, Julius; Beckmann, Matthias; Uder, Michael; Mueller-Schimpfle, Markus (Geburtshilfe und Frauenheilkunde, 2018)
Introduction: For decades, conventional galactography was the only imaging technique capable of showing the mammary ducts. Today, diagnosis is based on a multimodal concept which combines high-resolution ultrasound with magnetic resonance (MR) mammography and ductoscopy/galactoscopy and has a sensitivity and specificity of up to 95%. This study used tomosynthesis in galactography for the first time and compared the synthetic digital 2D full-field mammograms generated with this technique with the images created using the established method of ductal sonography. Both methods should be able to detect invasive breast cancers and their precursors such as ductal carcinoma in situ (DCIS) as well as being able to identify benign findings. Material and Methods: Five patients with pathological nipple discharge were examined using ductal sonography, contrast-enhanced 3D galactography with tomosynthesis and the synthetic digital 2D full-field mammograms generated with the latter method. Evaluation of the images created with the different imaging modalities was done by three investigators with varying levels of experience with complementary breast diagnostics (1, 5 and 15 years), and their evaluations were compared with the histological findings. Results: All 3 investigators independently evaluated the images created with ductal sonography, contrast-enhanced 3D galactography with tomosynthesis, and generated synthetic digital 2D full-field mammograms. Their evaluations were compared with the histopathological assessment of the surgical specimens resected from the 5 patients. There was 1 case of invasive breast cancer, 2 cases with ductal carcinoma in situ and 2 cases with benign findings. All 3 investigators made more mistakes when they used the standard imaging technique of ductal sonography to diagnose suspicious lesions than when they used contrast-enhanced galactography with tomosynthesis and the generated synthetic digital 2D full-field mammograms. Conclusion: This is the first time breast tomosynthesis was used in galactography (galactomosynthesis) to create digital 3-dimensional images of suspicious findings. When used together with the generated synthetic digital 2D full-field mammograms, it could be a useful complementary procedure for the diagnosis of breast anomalies and could herald a renaissance of this method. Compared with high-resolution ductal ultrasound, the investigators achieved better results with contrast-enhanced galactography using tomosynthesis and the generated synthetic digital 2D full-field mammograms, as confirmed by histopathological findings.
EVALuna2:34697

Gemcitabine as adjuvant chemotherapy in patients with high-risk early breast cancer—results from the randomized phase III SUCCESS-A trial - de Gregorio, Amelie; Häberle, Lothar; Fasching, Peter; Müller, Volkmar; Schrader, Iris; Lorenz, Ralf; Forstbauer, Helmut; Friedl, Thomas W.P.; Bauer, Emanuel; de Gregorio, Nikolaus; Deniz, Miriam; Fink, Visnja; et al. (Breast Cancer Research, 2020)
Background: When chemotherapy is indicated in patients with early breast cancer, regimens that contain anthracyclines and taxanes are established standard treatments. Gemcitabine has shown promising effects on the response and prognosis in patients with metastatic breast cancer. The SUCCESS-A trial (NCT02181101) examined the addition of gemcitabine to a standard chemotherapy regimen in high-risk early breast cancer patients. Methods: A total of 3754 patients with at least one of the following characteristics were randomly assigned to one of the two treatment arms: nodal positivity, tumor grade 3, age ≤ 35 years, tumor larger than 2 cm, or negative hormone receptor status. The treatment arms received either three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide, followed by three cycles of docetaxel (FEC → Doc); or three cycles of FEC followed by three cycles of docetaxel and gemcitabine (FEC → Doc/Gem). The primary study aim was disease-free survival (DFS), and the main secondary objectives were overall survival (OS) and safety. Results: No differences were observed in the 5-year DFS or OS between FEC → Doc and FEC → Doc/Gem. The hazard ratio was 0.93 (95% CI, 0.78 to 1.12; P = 0.47) for DFS and 0.94 (95% CI, 0.74 to 1.19; P = 0.60) for OS. For patients treated with FEC → Doc and FEC → Doc/Gem, the 5-year probabilities of DFS were 86.6% and 87.2%, and the 5-year probabilities of OS were 92.8% and 92.5%, respectively. Conclusion: Adding gemcitabine to a standard chemotherapy does not improve the outcomes in patients with high-risk early breast cancer and should therefore not be included in the adjuvant treatment setting. Trial registration: Clinicaltrials.gov NCT02181101 and EU Clinical Trials Register EudraCT 2005-000490-21. Registered September 2005.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Chemotherapy; Early breast cancer; Gemcitabine

Gene-environment interactions involving functional variants: Results from the Breast Cancer Association Consortium - Barrdahl, Myrto; Rudolph, Anja; Hopper, John L.; Southey, Melissa C.; Broeks, Annegien; Fasching, Peter; Beckmann, Matthias; Gago-Dominguez, Manuela; Castelao, J. Esteban; Guenel, Pascal; Truong, Therese; Bojesen, Stig E.; et al. (International Journal of Cancer, 2017)
Investigating the most likely causal variants identified by fine-mapping analyses may improve the power to detect gene-environment interactions. We assessed the interplay between 70 single nucleotide polymorphisms identified by genetic fine-scale mapping of susceptibility loci and 11 epidemiological breast cancer risk factors in relation to breast cancer. Analyses were conducted on up to 58,573 subjects (26,968 cases and 31,605 controls) from the Breast Cancer Association Consortium, in one of the largest studies of its kind. Analyses were carried out separately for estrogen receptor (ER) positive (ER+) and ER negative (ER-) disease. The Bayesian False Discovery Probability (BFDP) was computed to assess the noteworthiness of the results. Four potential gene-environment interactions were identified as noteworthy (BFDP < 0.80) when assuming a true prior interaction probability of 0.01. The strongest interaction result in relation to overall breast cancer risk was found between CFLAR-rs7558475 and current smoking (ORint = 0.77, 95% CI: 0.67-0.88, pint = 1.8 × 10-4 ). The interaction with the strongest statistical evidence was found between 5q14-rs7707921 and alcohol consumption (ORint =1.36, 95% CI: 1.16-1.59, pint = 1.9 × 10-5 ) in relation to ER- disease risk. The remaining two gene-environment interactions were also identified in relation to ER- breast cancer risk and were found between 3p21-rs6796502 and age at menarche (ORint = 1.26, 95% CI: 1.12-1.43, pint =1.8 × 10-4 ) and between 8q23-rs13267382 and age at first full-term pregnancy (ORint = 0.89, 95% CI: 0.83-0.95, pint = 5.2 × 10-4 ). While these results do not suggest any strong gene-environment interactions, our results may still be useful to inform experimental studies. These may in turn, shed light on the potential interactions observed.
EVALuna2:36122

Gene-Expression Profiling of Mucinous Ovarian Tumors and Comparison with Upper and Lower Gastrointestinal Tumors Identifies Markers Associated with Adverse Outcomes. - Meagher, Nicola S.; Gorringe, Kylie L.; Wakefield, Matthew J.; Bolithon, Adelyn; Pang, Chi Nam Ignatius; Chiu, Derek S.; Anglesio, Michael S.; Mallitt, Kylie-Ann; Doherty, Jennifer A.; Harris, Holly R.; Schildkraut, Joellen M.; Berchuck, Andrew; et al. (Clinical Cancer Research, 2022)
PURPOSE: Advanced-stage mucinous ovarian carcinoma (MOC) has poor chemotherapy response and prognosis and lacks biomarkers to aid stage I adjuvant treatment. Differentiating primary MOC from gastrointestinal (GI) metastases to the ovary is also challenging due to phenotypic similarities. Clinicopathologic and gene-expression data were analyzed to identify prognostic and diagnostic features. EXPERIMENTAL DESIGN: Discovery analyses selected 19 genes with prognostic/diagnostic potential. Validation was performed through the Ovarian Tumor Tissue Analysis consortium and GI cancer biobanks comprising 604 patients with MOC (n = 333), mucinous borderline ovarian tumors (MBOT, n = 151), and upper GI (n = 65) and lower GI tumors (n = 55). RESULTS: Infiltrative pattern of invasion was associated with decreased overall survival (OS) within 2 years from diagnosis, compared with expansile pattern in stage I MOC [hazard ratio (HR), 2.77; 95% confidence interval (CI), 1.04-7.41, P = 0.042]. Increased expression of THBS2 and TAGLN was associated with shorter OS in MOC patients (HR, 1.25; 95% CI, 1.04-1.51, P = 0.016) and (HR, 1.21; 95% CI, 1.01-1.45, P = 0.043), respectively. ERBB2 (HER2) amplification or high mRNA expression was evident in 64 of 243 (26%) of MOCs, but only 8 of 243 (3%) were also infiltrative (4/39, 10%) or stage III/IV (4/31, 13%). CONCLUSIONS: An infiltrative growth pattern infers poor prognosis within 2 years from diagnosis and may help select stage I patients for adjuvant therapy. High expression of THBS2 and TAGLN in MOC confers an adverse prognosis and is upregulated in the infiltrative subtype, which warrants further investigation. Anti-HER2 therapy should be investigated in a subset of patients. MOC samples clustered with upper GI, yet markers to differentiate these entities remain elusive, suggesting similar underlying biology and shared treatment strategies.
EVALuna2:513963

Gene panel sequencing in familial breast/ovarian cancer patients identifies multiple novel mutations also in genes others than BRCA1/2 - Kraus, Cornelia; Hoyer, Juliane; Vasileiou, Georgia; Wunderle, Marius; Lux, Michael P.; Fasching, Peter; Krumbiegel, Mandy; Uebe, Steffen; Reuter, Miriam; Beckmann, Matthias; Reis, André (International Journal of Cancer, 2017)
Breast and ovarian cancer (BC/OC) predisposition has been attributed to a number of high- and moderate to low-penetrance susceptibility genes. With the advent of next generation sequencing (NGS) simultaneous testing of these genes has become feasible. In this monocentric study, we report results of panel-based screening of 14 BC/OC susceptibility genes (BRCA1, BRCA2, RAD51C, RAD51D, CHEK2, PALB2, ATM, NBN, CDH1, TP53, MLH1, MSH2, MSH6 and PMS2) in a group of 581 consecutive individuals from a German population with BC and/or OC fulfilling diagnostic criteria for BRCA1 and BRCA2 testing including 179 with a triple-negative tumor. Altogether we identified 106 deleterious mutations in 105 (18%) patients in 10 different genes, including seven different exon deletions. Of these 106 mutations, 16 (15%) were novel and only six were found in BRCA1/2. To further characterize mutations located in or nearby splicing consensus sites we performed RT-PCR analysis which allowed confirmation of pathogenicity in 7 of 9 mutations analyzed. In PALB2, we identified a deleterious variant in six cases. All but one were associated with early onset BC and a positive family history indicating that penetrance for PALB2 mutations is comparable to BRCA2. Overall, extended testing beyond BRCA1/2 identified a deleterious mutation in further 6% of patients. As a downside, 89 variants of uncertain significance were identified highlighting the need for comprehensive variant databases. In conclusion, panel testing yields more accurate information on genetic cancer risk than assessing BRCA1/2 alone and wide-spread testing will help improve penetrance assessment of variants in these risk genes.
EVALuna2:9340

Genetically Predicted Body Mass Index and Breast Cancer Risk: Mendelian Randomization Analyses of Data from 145,000 Women of European Descent - Guo, Yan; Andersen, Shaneda Warren; Shu, Xiao-Ou; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Garcia-Closas, Montserrat; Milne, Roger L.; Schmidt, Marjanka K.; Chang-Claude, Jenny; Dunning, Allison; Bojesen, Stig E.; et al. (Plos Medicine, 2016)
BACKGROUND: Observational epidemiological studies have shown that high body mass index (BMI) is associated with a reduced risk of breast cancer in premenopausal women but an increased risk in postmenopausal women. It is unclear whether this association is mediated through shared genetic or environmental factors. METHODS: We applied Mendelian randomization to evaluate the association between BMI and risk of breast cancer occurrence using data from two large breast cancer consortia. We created a weighted BMI genetic score comprising 84 BMI-associated genetic variants to predicted BMI. We evaluated genetically predicted BMI in association with breast cancer risk using individual-level data from the Breast Cancer Association Consortium (BCAC) (cases = 46,325, controls = 42,482). We further evaluated the association between genetically predicted BMI and breast cancer risk using summary statistics from 16,003 cases and 41,335 controls from the Discovery, Biology, and Risk of Inherited Variants in Breast Cancer (DRIVE) Project. Because most studies measured BMI after cancer diagnosis, we could not conduct a parallel analysis to adequately evaluate the association of measured BMI with breast cancer risk prospectively. RESULTS: In the BCAC data, genetically predicted BMI was found to be inversely associated with breast cancer risk (odds ratio [OR] = 0.65 per 5 kg/m2 increase, 95% confidence interval [CI]: 0.56-0.75, p = 3.32 × 10-10). The associations were similar for both premenopausal (OR = 0.44, 95% CI:0.31-0.62, p = 9.91 × 10-8) and postmenopausal breast cancer (OR = 0.57, 95% CI: 0.46-0.71, p = 1.88 × 10-8). This association was replicated in the data from the DRIVE consortium (OR = 0.72, 95% CI: 0.60-0.84, p = 1.64 × 10-7). Single marker analyses identified 17 of the 84 BMI-associated single nucleotide polymorphisms (SNPs) in association with breast cancer risk at p < 0.05; for 16 of them, the allele associated with elevated BMI was associated with reduced breast cancer risk. CONCLUSIONS: BMI predicted by genome-wide association studies (GWAS)-identified variants is inversely associated with the risk of both pre- and postmenopausal breast cancer. The reduced risk of postmenopausal breast cancer associated with genetically predicted BMI observed in this study differs from the positive association reported from studies using measured adult BMI. Understanding the reasons for this discrepancy may reveal insights into the complex relationship of genetic determinants of body weight in the etiology of breast cancer.
EVALuna2:33324

Genetic Breast Cancer Susceptibility Variants and Prognosis in the Prospectively Randomized SUCCESS A Study - Hein, Alexander; Rack, B.; Li, L.; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, J. M.; Rübner, Matthias; Fridley, B. L.; Schneeweiss, A.; Tesch, H.; Lichtenegger, W.; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Large-scale genotyping studies have identified over 70 single nucleotide polymorphisms (SNPs) associated with breast cancer (BC) risk. However, knowledge regarding genetic risk factors associated with the prognosis is limited. The aim of this study was therefore to investigate the prognostic effect of nine known breast cancer risk SNPs. BC patients (n = 1687) randomly sampled in an adjuvant, randomized phase III trial (SUCCESS A study) were genotyped for nine BC risk SNPs: rs17468277 (CASP8) , rs2981582 (FGFR2) , rs13281615(8q24), rs3817198 (LSP1) , rs889312 (MAP3K1) , rs3803662 (TOX3) , rs13387042(2q35), rs4973768 (SLC4A7) , rs6504950 (COX11) . Cox proportional hazards models were used to test the SNPs' association with overall survival (OS) and progression-free survival (PFS). Additional analyses were carried out for molecular subgroups. rs3817198 in LSP1 (lymphocyte-specific protein 1) was the only SNP that significantly influenced OS (p = 0.01) and PFS (p < 0.01) in the likelihood ratio test comparing the genetic survival model with the clinical survival model. In the molecular subgroups, triple-negative patients with two minor alleles in rs3817198 had a much better prognosis relative to OS (adjusted HR 0.03; 95% CI 0.002 - 0.279) and PFS (HR 0.09; 95% CI 0.02 - 0.36) than patients with the common alleles. The same effect on PFS was shown for patients with luminal A tumors (HR 0.19; 95% CI 0.05 - 0.84), whereas patients with luminal B tumors had a poorer PFS with two minor alleles (HR 2.13; 95% CI 1.02 - 4.40). The variant in rs3817198 has a prognostic effect particularly in the subgroup of patients with triple-negative BC, suggesting a possible link with immunomodulation and BC.
EVALuna2:9355

Genetic modifiers of CHEK2*1100delC-associated breast cancer risk - Muranen, Taru A.; Greco, Dario; Blomqvist, Carl; Aittomaki, Kristiina; Khan, Sofia; Hogervorst, Frans; Verhoef, Senno; Pharoah, Paul D. P.; Dunning, Alison M.; Shah, Mitul; Luben, Robert; Bojesen, Stig E.; et al. (Genetics in Medicine, 2017)
PURPOSE: CHEK2*1100delC is a founder variant in European populations that confers a two- to threefold increased risk of breast cancer (BC). Epidemiologic and family studies have suggested that the risk associated with CHEK2*1100delC is modified by other genetic factors in a multiplicative fashion. We have investigated this empirically using data from the Breast Cancer Association Consortium (BCAC). METHODS: Using genotype data from 39,139 (624 1100delC carriers) BC patients and 40,063 (224) healthy controls from 32 BCAC studies, we analyzed the combined risk effects of CHEK2*1100delC and 77 common variants in terms of a polygenic risk score (PRS) and pairwise interaction. RESULTS: The PRS conferred odds ratios (OR) of 1.59 (95% CI: 1.21-2.09) per standard deviation for BC for CHEK2*1100delC carriers and 1.58 (1.55-1.62) for noncarriers. No evidence of deviation from the multiplicative model was found. The OR for the highest quintile of the PRS was 2.03 (0.86-4.78) for CHEK2*1100delC carriers, placing them in the high risk category according to UK NICE guidelines. The OR for the lowest quintile was 0.52 (0.16-1.74), indicating a lifetime risk close to the population average. CONCLUSION: Our results confirm the multiplicative nature of risk effects conferred by CHEK2*1100delC and the common susceptibility variants. Furthermore, the PRS could identify carriers at a high lifetime risk for clinical actions.Genet Med advance online publication 06 October 2016.
EVALuna2:36144

Genetic overlap between endometriosis and endometrial cancer: evidence from cross-disease genetic correlation and GWAS meta-analyses - Painter, Jodie N.; O'Mara, Tracy A.; Morris, Andrew P.; Cheng, Timothy H. T.; Gorman, Maggie; Martin, Lynn; Hodson, Shirley; Jones, Angela; Martin, Nicholas G.; Gordon, Scott; Henders, Anjali K.; Attia, John; et al. (Cancer Medicine, 2018)
Epidemiological, biological, and molecular data suggest links between endometriosis and endometrial cancer, with recent epidemiological studies providing evidence for an association between a previous diagnosis of endometriosis and risk of endometrial cancer. We used genetic data as an alternative approach to investigate shared biological etiology of these two diseases. Genetic correlation analysis of summary level statistics from genomewide association studies (GWAS) using LD Score regression revealed moderate but significant genetic correlation (rg = 0.23, P = 9.3 × 10-3 ), and SNP effect concordance analysis provided evidence for significant SNP pleiotropy (P = 6.0 × 10-3 ) and concordance in effect direction (P = 2.0 × 10-3 ) between the two diseases. Cross-disease GWAS meta-analysis highlighted 13 distinct loci associated at P ≤ 10-5 with both endometriosis and endometrial cancer, with one locus (SNP rs2475335) located within PTPRD associated at a genomewide significant level (P = 4.9 × 10-8 , OR = 1.11, 95% CI = 1.07-1.15). PTPRD acts in the STAT3 pathway, which has been implicated in both endometriosis and endometrial cancer. This study demonstrates the value of cross-disease genetic analysis to support epidemiological observations and to identify biological pathways of relevance to multiple diseases.
EVALuna2:34631

Genetic predictors of chemotherapy-related amenorrhea in women with breast cancer - Ruddy, Kathryn J.; Schaid, Daniel J.; Partridge, A. H.; Larson, Nicholas B.; Batzler, Anthony; Häberle, Lothar; Dittrich, Ralf; Widschwendter, P.; Fink, Visnja; Bauer, Emanuel; Schwitulla, Judith; Rübner, Matthias; et al. (Fertility and Sterility, 2019)
Objective: To study how genetics may play a role in determining risk of chemotherapy-related amenorrhea (CRA) in young women with breast cancer. Design: Genome-wide association study. Setting: Not applicable. Patient(s): Premenopausal women ≤45 years of age enrolled in one of these three trials were included if they had at least one menstrual case report form after chemotherapy ended and if they were of European ancestry. Forms during and up to 3 months after receipt of GnRH agonist were excluded. Intervention(s): None. Main Outcome Measure(s): The association of single-nucleotide polymorphisms with post-chemotherapy menstruation adjusted for trial and arm, age, tamoxifen use, and nodal status. Result(s): The median age of the 1,168 women was 41 years (range 19–45). Among these, 457 (39%) never resumed menses after chemotherapy. Older age, tamoxifen use, and node-negative disease were associated with increased risk of CRA. Adjusting for these, rs147451859, in an intron of PPCDC (phosphopantothenoylcysteine decarboxylase), and rs17587029, located 5′ upstream of RPS20P11 (ribosomal protein S20 pseudogene 11), were associated with post-chemotherapy menstruation. Conclusion(s): Genetic variation may contribute to risk of CRA. Better prediction of who will experience CRA may inform reproductive and treatment decision making in young women with cancer.
CRIS-Team Scopus Importer:2019-08-06
Keywords: amenorrhea; Breast neoplasms; drug therapy; toxicity

Genetic predisposition to ductal carcinoma in situ of the breast - Petridis, Christos; Brook, Mark N.; Shah, Vandna; Kohut, Kelly; Gorman, Patricia; Caneppele, Michele; Levi, Dina; Papouli, Efterpi; Orr, Nick; Cox, Angela; Cross, Simon S.; Dos-Santos-Silva, Isabel; et al. (Breast Cancer Research, 2016)
BACKGROUND: Ductal carcinoma in situ (DCIS) is a non-invasive form of breast cancer. It is often associated with invasive ductal carcinoma (IDC), and is considered to be a non-obligate precursor of IDC. It is not clear to what extent these two forms of cancer share low-risk susceptibility loci, or whether there are differences in the strength of association for shared loci. METHODS: To identify genetic polymorphisms that predispose to DCIS, we pooled data from 38 studies comprising 5,067 cases of DCIS, 24,584 cases of IDC and 37,467 controls, all genotyped using the iCOGS chip. RESULTS: Most (67 %) of the 76 known breast cancer predisposition loci showed an association with DCIS in the same direction as previously reported for invasive breast cancer. Case-only analysis showed no evidence for differences between associations for IDC and DCIS after considering multiple testing. Analysis by estrogen receptor (ER) status confirmed that loci associated with ER positive IDC were also associated with ER positive DCIS. Analysis of DCIS by grade suggested that two independent SNPs at 11q13.3 near CCND1 were specific to low/intermediate grade DCIS (rs75915166, rs554219). These associations with grade remained after adjusting for ER status and were also found in IDC. We found no novel DCIS-specific loci at a genome wide significance level of P < 5.0x10(-8). CONCLUSION: In conclusion, this study provides the strongest evidence to date of a shared genetic susceptibility for IDC and DCIS. Studies with larger numbers of DCIS are needed to determine if IDC or DCIS specific loci exist.
EVALuna2:33330

Genetic predisposition to in situ and invasive lobular carcinoma of the breast - Sawyer, Elinor; Roylance, Rebecca; Petridis, Christos; Brook, Mark N.; Nowinski, Salpie; Papouli, Efterpi; Fletcher, Olivia; Pinder, Sarah; Hanby, Andrew; Kohut, Kelly; Gorman, Patricia; Caneppele, Michele; et al. (PLoS Genetics, 2014)
Invasive lobular breast cancer (ILC) accounts for 10-15% of all invasive breast carcinomas. It is generally ER positive (ER+) and often associated with lobular carcinoma in situ (LCIS). Genome-wide association studies have identified more than 70 common polymorphisms that predispose to breast cancer, but these studies included predominantly ductal (IDC) carcinomas. To identify novel common polymorphisms that predispose to ILC and LCIS, we pooled data from 6,023 cases (5,622 ILC, 401 pure LCIS) and 34,271 controls from 36 studies genotyped using the iCOGS chip. Six novel SNPs most strongly associated with ILC/LCIS in the pooled analysis were genotyped in a further 516 lobular cases (482 ILC, 36 LCIS) and 1,467 controls. These analyses identified a lobular-specific SNP at 7q34 (rs11977670, OR (95%CI) for ILC = 1.13 (1.09-1.18), P = 6.0 × 10(-10); P-het for ILC vs IDC ER+ tumors = 1.8 × 10(-4)). Of the 75 known breast cancer polymorphisms that were genotyped, 56 were associated with ILC and 15 with LCIS at P<0.05. Two SNPs showed significantly stronger associations for ILC than LCIS (rs2981579/10q26/FGFR2, P-het = 0.04 and rs889312/5q11/MAP3K1, P-het = 0.03); and two showed stronger associations for LCIS than ILC (rs6678914/1q32/LGR6, P-het = 0.001 and rs1752911/6q14, P-het = 0.04). In addition, seven of the 75 known loci showed significant differences between ER+ tumors with IDC and ILC histology, three of these showing stronger associations for ILC (rs11249433/1p11, rs2981579/10q26/FGFR2 and rs10995190/10q21/ZNF365) and four associated only with IDC (5p12/rs10941679; rs2588809/14q24/RAD51L1, rs6472903/8q21 and rs1550623/2q31/CDCA7). In conclusion, we have identified one novel lobular breast cancer specific predisposition polymorphism at 7q34, and shown for the first time that common breast cancer polymorphisms predispose to LCIS. We have shown that many of the ER+ breast cancer predisposition loci also predispose to ILC, although there is some heterogeneity between ER+ lobular and ER+ IDC tumors. These data provide evidence for overlapping, but distinct etiological pathways within ER+ breast cancer between morphological subtypes.
EVALuna2:9234

Genetic risk factors for ovarian cancer and their role for endometriosis risk - Burghaus, Stefanie; Fasching, Peter; Haeberle, Lothar; Rübner, Matthias; Buechner, Kathrin; Blum, Simon; Engel, Anne; Ekici, Arif Bülent; Hartmann, Arndt; Hein, Alexander; Beckmann, Matthias; Renner, Stefan (Gynecologic Oncology, 2017)
Several genetic variants have been validated as risk factors for ovarian cancer. Endometriosis has also been described as a risk factor for ovarian cancer. Identifying genetic risk factors that are common to the two diseases might help improve our understanding of the molecular pathogenesis potentially linking the two conditions.In a hospital-based case-control analysis, 12 single nucleotide polymorphisms (SNPs), validated by the Ovarian Cancer Association Consortium (OCAC) and the Collaborative Oncological Gene-environment Study (COGS) project, were genotyped using TaqMan® OpenArray(TM) analysis. The cases consisted of patients with endometriosis, and the controls were healthy individuals without endometriosis. A total of 385 cases and 484 controls were analyzed. Odds ratios and P values were obtained using simple logistic regression models, as well as from multiple logistic regression models with adjustment for clinical predictors.rs11651755 in HNF1B was found to be associated with endometriosis in this case-control study. The OR was 0.66 (95% CI, 0.51 to 0.84) and the P value after correction for multiple testing was 0.01. None of the other genotypes was associated with a risk for endometriosis.As rs11651755 in HNF1B modified both the ovarian cancer risk and also the risk for endometriosis, HNF1B may be causally involved in the pathogenetic pathway leading from endometriosis to ovarian cancer.
EVALuna2:6871

Genetic Risk Score Mendelian Randomization Shows that Obesity Measured as Body Mass Index, but not Waist:Hip Ratio, Is Causal for Endometrial Cancer - Painter, Jodie N.; O'Mara, Tracy A.; Marquart, Louise; Webb, Penelope M.; Attia, John; Medland, Sarah E.; Cheng, Timothy; Dennis, Joe; Holliday, Elizabeth G.; Mcevoy, Mark; Scott, Rodney J.; Ahmed, Shahana; et al. (Cancer Epidemiology Biomarkers & Prevention, 2016)
The strongest known risk factor for endometrial cancer is obesity. To determine whether SNPs associated with increased body mass index (BMI) or waist-hip ratio (WHR) are associated with endometrial cancer risk, independent of measured BMI, we investigated relationships between 77 BMI and 47 WHR SNPs and endometrial cancer in 6,609 cases and 37,926 country-matched controls.Logistic regression analysis and fixed effects meta-analysis were used to test for associations between endometrial cancer risk and (i) individual BMI or WHR SNPs, (ii) a combined weighted genetic risk score (wGRS) for BMI or WHR. Causality of BMI for endometrial cancer was assessed using Mendelian randomization, with BMIwGRS as instrumental variable.The BMIwGRS was significantly associated with endometrial cancer risk (P = 3.4 × 10(-17)). Scaling the effect of the BMIwGRS on endometrial cancer risk by its effect on BMI, the endometrial cancer OR per 5 kg/m(2) of genetically predicted BMI was 2.06 [95% confidence interval (CI), 1.89-2.21], larger than the observed effect of BMI on endometrial cancer risk (OR = 1.55; 95% CI, 1.44-1.68, per 5 kg/m(2)). The association attenuated but remained significant after adjusting for BMI (OR = 1.22; 95% CI, 1.10-1.39; P = 5.3 × 10(-4)). There was evidence of directional pleiotropy (P = 1.5 × 10(-4)). BMI SNP rs2075650 was associated with endometrial cancer at study-wide significance (P < 4.0 × 10(-4)), independent of BMI. Endometrial cancer was not significantly associated with individual WHR SNPs or the WHRwGRS.BMI, but not WHR, is causally associated with endometrial cancer risk, with evidence that some BMI-associated SNPs alter endometrial cancer risk via mechanisms other than measurable BMI.The causal association between BMI SNPs and endometrial cancer has possible implications for endometrial cancer risk modeling. Cancer Epidemiol Biomarkers Prev; 25(11); 1503-10. ©2016 AACR.
EVALuna2:9342

Genetic variants in the genes of the sex steroid hormone metabolism and depressive symptoms during and after pregnancy - Schneider, Michael; Pretscher, Jutta; Goecke, Tamme; Häberle, Lothar; Engel, Anne; Kornhuber, Johannes; Eichler, Anna; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aim of this study was to conduct an association analysis of depressive symptoms and polymorphisms in the ESR1, PGR, CYP19A1, and COMT genes in pregnant and postpartum women. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for assessment of maternal and fetal health. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of pregnancy, visit 2 was shortly after birth, and visit 3 was 6–8 months after birth. Germline DNA and depression measurements from 361 pregnant women were available for analysis. Six single nucleotide polymorphisms (SNPs) in the above-mentioned genes were genotyped. After reconstruction of haplotypes for PGR (rs1042838 and rs10895068) and CYP19A1 (rs10046 and rs4646), a multifactorial linear mixed model was applied to the data to describe the association between haplotypes and depression values. The single SNPs for ESR1 (rs488133) and COMT (rs4680) were analyzed separately using linear mixed models analogously. Results: The mean antepartum EPDS measurement was 5.1, the mean postpartal measurement after 48–72 h was 3.5, and the mean value 6–8 months postpartum was 4.2. The SNPs in PGR were reconstructed into three haplotypes. The most common haplotype was GG, with 63.43% of patients carrying two copies and 33.52% carrying one copy. For haplotype GA, the group of carriers of two copies (0.28%) was combined with the carriers of one copy (9.70%). Haplotype reconstruction using CYP19A1 SNPs resulted in three haplotypes. The most common haplotype was TC, with 25.48% of patients carrying two copies and 51.52% one copy. None of the haplotype blocks and neither of the two single SNPs showed any significant associations with EPDS values. Conclusions: The candidate haplotypes analyzed in PGR and CYP19A1 and single SNPs in ESR1 and COMT did not show any association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
CRIS-Team Scopus Importer:2022-06-17
Keywords: COMT; CYP19A1; Depression; EPDS; ESR1; PGR; Single nucleotide polymorphisms

Genetic variants in the genes of the stress hormone signalling pathway and depressive symptoms during and after pregnancy - Schneider, Michael; Engel, Anne; Fasching, Peter; Haeberle, Lothar; Binder, Elisabeth B.; Voigt, Franziska; Grimm, Jennifer; Faschingbauer, Florian; Eichler, Anna; Dammer, Ulf; Rebhan, Dirk; Amann, Manuela; et al. (BioMed Research International, 2014)
The aim of this study was to investigate whether single nucleotide polymorphisms (SNPs) in genes of the stress hormone signaling pathway, specifically FKBP5, NR3C1, and CRHR1, are associated with depressive symptoms during and after pregnancy.The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health including the assessment of depressiveness. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of the pregnancy, visit 2 was shortly after birth, and visit 3 was 6-8 months after birth. Germline DNA was collected from 361 pregnant women. Nine SNPs in the above mentioned genes were genotyped. After construction of haplotypes for each gene, a multifactorial linear mixed model was performed to analyse the depression values over time.EPDS values were within expected ranges and comparable to previously published studies. Neither did the depression scores differ for comparisons among haplotypes at fixed time points nor did the change over time differ among haplotypes for the examined genes. No haplotype showed significant associations with depressive symptoms severity during pregnancy or the postpartum period.The analysed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show an association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
EVALuna2:17356

Genetic variants in the glucocorticoid pathway genes and birth weight - Schneider, Michael; Hübner, Theresa; Pretscher, Jutta; Goecke, Tamme W.; Schwitulla, Judith; Häberle, Lothar; Kornhuber, Johannes; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: The aim of this study was to examine associations between single nucleotide polymorphisms (SNPs) that tag genetic variation in the glucocorticoid pathways (particularly in maternal genes FKBP5, NR3C1, and CRHR1) and birth weight. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health. Germline DNA was collected from 375 pregnant women. Nine SNPs in the above-mentioned genes were genotyped. After reconstruction of haplotypes for each gene, a linear regression model was applied to the data to describe the association between haplotypes and birth weight. Results: Female sex in the newborn (compared to male) was associated with lower birth weight, whereas a later week of gestation, higher body mass index pre-pregnancy, and higher parity were associated with higher birth weight. No association with birthweight was shown for the haplotypes of the selected SNPs. Conclusions: In this cohort of healthy unselected pregnant women, the analyzed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show any association with birth weight. This might be in line with several other studies that have found no influence of fetal polymorphisms in the glucocorticoid receptor gene or triggers of the maternal HPA axis such as stress and psychosocial problems on birth weight. However, the small sample size in this study and the lack of consideration of individual risk factors and levels of stress in this cohort needs to be taken into account when interpreting the results.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Birth weight; CRHR1; FKBP5; NR3C1; Single nucleotide polymorphisms

Genetic variants in VEGF pathway genes in neoadjuvant breast cancer patients receiving bevacizumab: Results from the randomized phase III GeparQuinto study - Hein, Alexander; Lambrechts, Diether; Von Minckwitz, Gunter; Haeberle, Lothar; Eidtmann, Holger; Tesch, Hans; Untch, Michael; Hilfrich, Joern; Schem, Christian; Rezai, Mahdi; Gerber, Bernd; Costa, Serban Dan; et al. (International Journal of Cancer, 2015)
Studies assessing the effect of bevacizumab (BEV) on breast cancer (BC) outcome have shown different effects on progression-free and overall survival, suggesting that a subgroup of patients may benefit from this treatment. Unfortunately, no biomarkers exist to identify these patients. Here, we investigate whether single nucleotide polymorphisms (SNPs) in VEGF pathway genes correlate with pathological complete response (pCR) in the neoadjuvant GeparQuinto trial. HER2-negative patients were randomized into treatment arms receiving either BEV combined with standard chemotherapy or chemotherapy alone. In a pre-planned biomarker study, DNA was collected from 729 and 724 patients, respectively from both treatment arms, and genotyped for 125 SNPs. Logistic regression assessed interaction between individual SNPs and both treatment arms to predict pCR. Five SNPs may be associated with a better response to BEV, but none of them remained significant after correction for multiple testing. The two SNPs most strongly associated, rs833058 and rs699947, were located upstream of the VEGF-A promoter. Odds ratios for the homozygous common, heterozygous and homozygous rare rs833058 genotypes were 2.36 (95% CI, 1.49-3.75), 1.20 (95% CI, 0.88-1.64) and 0.61 (95% CI, 0.34-1.12). Notably, some SNPs in VEGF-A exhibited a more pronounced effect in the triple-negative subgroup. Several SNPs in VEGF-A may be associated with improved pCR when receiving BEV in the neoadjuvant setting. Although none of the observed effects survived correction for multiple testing, our observations are consistent with previous studies on BEV efficacy in BC. Further research is warranted to clarify the predictive value of these markers.
EVALuna2:9285

Genetic variation at CYP3A is associated with age at menarche and breast cancer risk: a case-control study - Johnson, Nichola; Dudbridge, Frank; Orr, Nick; Gibson, Lorna; Jones, Michael E.; Schoemaker, Minouk J.; Folkerd, Elizabeth J.; Haynes, Ben P.; Hopper, John L.; Southey, Melissa C.; Dite, Gillian S.; Apicella, Carmel; et al. (Breast Cancer Research, 2014)
We have previously shown that a tag single nucleotide polymorphism (rs10235235), which maps to the CYP3A locus (7q22.1), was associated with a reduction in premenopausal urinary estrone glucuronide levels and a modest reduction in risk of breast cancer in women age <=50 years.We further investigated the association of rs10235235 with breast cancer risk in a large case control study of 47,346 cases and 47,570 controls from 52 studies participating in the Breast Cancer Association Consortium. Genotyping of rs10235235 was conducted using a custom Illumina Infinium array. Stratified analyses were conducted to determine whether this association was modified by age at diagnosis, ethnicity, age at menarche or tumor characteristics.We confirmed the association of rs10235235 with breast cancer risk for women of European ancestry but found no evidence that this association differed with age at diagnosis. Heterozygote and homozygote odds ratios (ORs) were OR = 0.98 (95% CI 0.94, 1.01; P = 0.2) and OR = 0.80 (95% CI 0.69, 0.93; P = 0.004), respectively (P(trend) = 0.02). There was no evidence of effect modification by tumor characteristics. rs10235235 was, however, associated with age at menarche in controls (P(trend) = 0.005) but not cases (P(trend) = 0.97). Consequently the association between rs10235235 and breast cancer risk differed according to age at menarche (P(het) = 0.02); the rare allele of rs10235235 was associated with a reduction in breast cancer risk for women who had their menarche age >=15 years (OR(het) = 0.84, 95% CI 0.75, 0.94; OR(hom) = 0.81, 95% CI 0.51, 1.30; P(trend) = 0.002) but not for those who had their menarche age <=11 years (OR(het) = 1.06, 95% CI 0.95, 1.19, OR(hom) = 1.07, 95% CI 0.67, 1.72; P(trend) = 0.29).To our knowledge rs10235235 is the first single nucleotide polymorphism to be associated with both breast cancer risk and age at menarche consistent with the well-documented association between later age at menarche and a reduction in breast cancer risk. These associations are likely mediated via an effect on circulating hormone levels.
EVALuna2:9240

Genetic variation in mitotic regulatory pathway genes is associated with breast tumor grade - Purrington, Kristen S.; Slettedahl, Seth; Bolla, Manjeet K.; Michailidou, Kyriaki; Czene, Kamila; Nevanlinna, Heli; Bojesen, Stig E.; Andrulis, Irene L.; Cox, Angela; Hall, Per; Carpenter, Jane; Yannoukakos, Drakoulis; et al. (Human Molecular Genetics, 2014)
Mitotic index is an important component of histologic grade and has an etiologic role in breast tumorigenesis. Several small candidate gene studies have reported associations between variation in mitotic genes and breast cancer risk. We measured associations between 2156 single nucleotide polymorphisms (SNPs) from 194 mitotic genes and breast cancer risk, overall and by histologic grade, in the Breast Cancer Association Consortium (BCAC) iCOGS study (n = 39 067 cases; n = 42 106 controls). SNPs in TACC2 [rs17550038: odds ratio (OR) = 1.24, 95% confidence interval (CI) 1.16-1.33, P = 4.2 × 10(-10)) and EIF3H (rs799890: OR = 1.07, 95% CI 1.04-1.11, P = 8.7 × 10(-6)) were significantly associated with risk of low-grade breast cancer. The TACC2 signal was retained (rs17550038: OR = 1.15, 95% CI 1.07-1.23, P = 7.9 × 10(-5)) after adjustment for breast cancer risk SNPs in the nearby FGFR2 gene, suggesting that TACC2 is a novel, independent genome-wide significant genetic risk locus for low-grade breast cancer. While no SNPs were individually associated with high-grade disease, a pathway-level gene set analysis showed that variation across the 194 mitotic genes was associated with high-grade breast cancer risk (P = 2.1 × 10(-3)). These observations will provide insight into the contribution of mitotic defects to histological grade and the etiology of breast cancer.
EVALuna2:6629

Genetic variations in estrogen and progesterone pathway genes in preeclampsia patients and controls in Bavaria - Pretscher, Jutta; Rübner, Matthias; Ekici, Arif Bülent; Rödl, Melanie; Hübner, Hanna; Schwitulla, Judith; Titzmann, Adriana; Hartwig, Charlotte; Beckmann, Matthias; Fasching, Peter; Schneider, Michael; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: Hypertensive pregnancy disorders and preeclampsia are major causes of maternal and fetal morbidity and mortality worldwide. Many different organs are involved in the diseases’ clinical phenotype. The underlying mechanism is still unknown, with a possible genetic component. This case–control study investigated effects on the risk of preeclampsia of genetic variations (single nucleotide polymorphisms, SNPs) in the estrogen and progesterone pathway genes. Methods: The study included 167 patients with preeclampsia and 115 healthy controls from the “Franconian Maternal Health Evaluation Studies” (FRAMES). All patients completed an epidemiological questionnaire, data from which were correlated with prospective data on pregnancy and labor. DNA was isolated from blood samples and genotyping was done by PCR. Variants in the aromatase gene CYP19A1 (rs10046, rs4646), progesterone receptor gene (rs1042838, rs10895068), and estrogen receptor-α gene (rs488133) were examined, and the genotype distribution in the two groups was analyzed statistically. Results: A significant difference in the distribution frequency of genotypes between preeclampsia patients and controls was identified in one of the five SNPs. For rs10895068 in the progesterone receptor gene, genotype G/A was significantly more frequent among cases than controls (P = 0.023). No significant differences between the two cohorts were found in the other SNPs. Conclusions: This study showed a significant association between only one SNP in the progesterone receptor and preeclampsia. Other studies have also noted genetic aspects of preeclampsia. The underlying mechanism and causal relationship are not yet known, and further research is needed to explain the extent of genetic variations and the causal relationship in preeclampsia.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Genetic marker; Preeclampsia; Pregnancy; Single nucleotide polymorphism (SNP)

Genome-wide Analysis Identifies Novel Loci Associated with Ovarian Cancer Outcomes: Findings from the Ovarian Cancer Association Consortium - Johnatty, Sharon E.; Tyrer, Jonathan P.; Kar, Siddhartha; Beesley, Jonathan; Lu, Yi; Gao, Bo; Fasching, Peter; Hein, Alexander; Ekici, Arif Bülent; Beckmann, Matthias; Lambrechts, Diether; Van Nieuwenhuysen, Els; et al. (Clinical Cancer Research, 2015)
Chemotherapy resistance remains a major challenge in the treatment of ovarian cancer. We hypothesize that germline polymorphisms might be associated with clinical outcome.We analyzed approximately 2.8 million genotyped and imputed SNPs from the iCOGS experiment for progression-free survival (PFS) and overall survival (OS) in 2,901 European epithelial ovarian cancer (EOC) patients who underwent first-line treatment of cytoreductive surgery and chemotherapy regardless of regimen, and in a subset of 1,098 patients treated with >=4 cycles of paclitaxel and carboplatin at standard doses. We evaluated the top SNPs in 4,434 EOC patients, including patients from The Cancer Genome Atlas. In addition, we conducted pathway analysis of all intragenic SNPs and tested their association with PFS and OS using gene set enrichment analysis.Five SNPs were significantly associated (P <= 1.0 × 10(-5)) with poorer outcomes in at least one of the four analyses, three of which, rs4910232 (11p15.3), rs2549714 (16q23), and rs6674079 (1q22), were located in long noncoding RNAs (lncRNAs) RP11-179A10.1, RP11-314O13.1, and RP11-284F21.8, respectively (P <= 7.1 × 10(-6)). ENCODE ChIP-seq data at 1q22 for normal ovary show evidence of histone modification around RP11-284F21.8, and rs6674079 is perfectly correlated with another SNP within the super-enhancer MEF2D, expression levels of which were reportedly associated with prognosis in another solid tumor. YAP1- and WWTR1 (TAZ)-stimulated gene expression and high-density lipoprotein (HDL)-mediated lipid transport pathways were associated with PFS and OS, respectively, in the cohort who had standard chemotherapy (pGSEA <=6 × 10(-3)).We have identified SNPs in three lncRNAs that might be important targets for novel EOC therapies. Clin Cancer Res; 21(23); 5264-76. ©2015 AACR.
EVALuna2:9298

Genome-wide association analysis identifies three new breast cancer susceptibility loci - Ghoussaini, Maya; Fletcher, Olivia; Michailidou, Kyriaki; Turnbull, Clare; Schmidt, Marjanka K.; Dicks, Ed; Dennis, Joe; Wang, Qin; Humphreys, Manjeet K.; Luccarini, Craig; Baynes, Caroline; Conroy, Don; et al. (Nature Genetics, 2012)
Breast cancer is the most common cancer among women. To date, 22 common breast cancer susceptibility loci have been identified accounting for 8% of the heritability of the disease. We attempted to replicate 72 promising associations from two independent genome-wide association studies (GWAS) in 70,000 cases and 68,000 controls from 41 case-control studies and 9 breast cancer GWAS. We identified three new breast cancer risk loci at 12p11 (rs10771399; P = 2.7 × 10(-35)), 12q24 (rs1292011; P = 4.3 × 10(-19)) and 21q21 (rs2823093; P = 1.1 × 10(-12)). rs10771399 was associated with similar relative risks for both estrogen receptor (ER)-negative and ER-positive breast cancer, whereas the other two loci were associated only with ER-positive disease. Two of the loci lie in regions that contain strong plausible candidate genes: PTHLH (12p11) has a crucial role in mammary gland development and the establishment of bone metastasis in breast cancer, and NRIP1 (21q21) encodes an ER cofactor and has a role in the regulation of breast cancer cell growth.
EVALuna2:9145

Genome-wide association analysis of more than 120,000 individuals identifies 15 new susceptibility loci for breast cancer - Michailidou, Kyriaki; Beesley, Jonathan; Lindstrom, Sara; Canisius, Sander; Dennis, Joe; Lush, Michael J.; Maranian, Mel J.; Bolla, Manjeet K.; Wang, Qin; Shah, Mitul; Perkins, Barbara J.; Czene, Kamila; et al. (Nature Genetics, 2015)
Genome-wide association studies (GWAS) and large-scale replication studies have identified common variants in 79 loci associated with breast cancer, explaining 14% of the familial risk of the disease. To identify new susceptibility loci, we performed a meta-analysis of 11 GWAS, comprising 15,748 breast cancer cases and 18,084 controls together with 46,785 cases and 42,892 controls from 41 studies genotyped on a 211,155-marker custom array (iCOGS). Analyses were restricted to women of European ancestry. We generated genotypes for more than 11 million SNPs by imputation using the 1000 Genomes Project reference panel, and we identified 15 new loci associated with breast cancer at P < 5 × 10(-8). Combining association analysis with ChIP-seq chromatin binding data in mammary cell lines and ChIA-PET chromatin interaction data from ENCODE, we identified likely target genes in two regions: SETBP1 at 18q12.3 and RNF115 and PDZK1 at 1q21.1. One association appears to be driven by an amino acid substitution encoded in EXO
EVALuna2:17570

Genome-wide association and transcriptome studies identify target genes and risk loci for breast cancer - Ferreira, Manuel A.; Gamazon, Eric R.; Al-Ejeh, Fares; Aittomaki, Kristiina; Andrulis, Irene L.; Anton-Culver, Hoda; Arason, Adalgeir; Arndt, Volker; Aronson, Kristan J.; Arun, Banu K.; Asseryanis, Ella; Azzollini, Jacopo; et al. (Nature Communications, 2019)
Genome-wide association studies (GWAS) have identified more than 170 breast cancer susceptibility loci. Here we hypothesize that some risk-associated variants might act in non-breast tissues, specifically adipose tissue and immune cells from blood and spleen. Using expression quantitative trait loci (eQTL) reported in these tissues, we identify 26 previously unreported, likely target genes of overall breast cancer risk variants, and 17 for estrogen receptor (ER)-negative breast cancer, several with a known immune function. We determine the directional effect of gene expression on disease risk measured based on single and multiple eQTL. In addition, using a gene-based test of association that considers eQTL from multiple tissues, we identify seven (and four) regions with variants associated with overall (and ER-negative) breast cancer risk, which were not reported in previous GWAS. Further investigation of the function of the implicated genes in breast and immune cells may provide insights into the etiology of breast cancer.
CRIS-Team WoS Importer:2019-04-30

Genome-wide association study and functional follow-up identify 14q12 as a candidate risk locus for cervical cancer - Ramachandran, Dhanya; Dennis, Joe; Fachal, Laura; Schurmann, Peter; Bousset, Kristine; Huelse, Fabienne; Mao, Qianqian; Wang, Yingying; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; Hirchenhain, Christine; et al. (Human Molecular Genetics, 2022)
Cervical cancer is among the leading causes of cancer-related death in females worldwide. Infection by human papillomavirus (HPV) is an established risk factor for cancer development. However, genetic factors contributing to disease risk remain largely unknown. We report on a genome-wide association study (GWAS) on 375 German cervical cancer patients and 866 healthy controls, followed by a replication study comprising 658 patients with invasive cervical cancer, 1361 with cervical dysplasia and 841 healthy controls. Functional validation was performed for the top GWAS variant on chromosome 14q12 (rs225902, close to PRKD1). After bioinformatic annotation and in silico predictions, we performed transcript analysis in a cervical tissue series of 317 samples and demonstrate rs225902 as an expression quantitative trait locus (eQTL) for FOXG1 and two tightly co-regulated long non-coding RNAs at this genomic region, CTD-2251F13 (lnc-PRKD1-1) and CTD-2503I6 (lnc-FOXG1-6). We also show allele-specific effects of the 14q12 variants via luciferase assays. We propose a combined effect of genotype, HPV status and gene expression at this locus on cervical cancer progression. Taken together, this work uncovers a potential candidate locus with regulatory functions and contributes to the understanding of genetic susceptibility to cervical cancer.
CRIS-Team WoS Importer:2022-05-06

Genome-wide association study identifies 25 known breast cancer susceptibility loci as risk factors for triple-negative breast cancer - Purrington, Kristen S.; Slager, Susan; Eccles, Diana; Yannoukakos, Drakoulis; Fasching, Peter A.; Miron, Penelope; Carpenter, Jane; Chang-Claude, Jenny; Martin, Nicholas G.; Montgomery, Grant W.; Kristensen, Vessela; Anton-Culver, Hoda; et al. (Carcinogenesis, 2014)
Triple-negative (TN) breast cancer is an aggressive subtype of breast cancer associated with a unique set of epidemiologic and genetic risk factors. We conducted a two-stage genome-wide association study of TN breast cancer (stage 1: 1529 TN cases, 3399 controls; stage 2: 2148 cases, 1309 controls) to identify loci that influence TN breast cancer risk. Variants in the 19p13.1 and PTHLH loci showed genome-wide significant associations (P < 5 × 10(-) (8)) in stage 1 and 2 combined. Results also suggested a substantial enrichment of significantly associated variants among the single nucleotide polymorphisms (SNPs) analyzed in stage 2. Variants from 25 of 74 known breast cancer susceptibility loci were also associated with risk of TN breast cancer (P < 0.05). Associations with TN breast cancer were confirmed for 10 loci (LGR6, MDM4, CASP8, 2q35, 2p24.1, TERT-rs10069690, ESR1, TOX3, 19p13.1, RALY), and we identified associations with TN breast cancer for 15 additional breast cancer loci (P < 0.05: PEX14, 2q24.1, 2q31.1, ADAM29, EBF1, TCF7L2, 11q13.1, 11q24.3, 12p13.1, PTHLH, NTN4, 12q24, BRCA2, RAD51L1-rs2588809, MKL1). Further, two SNPs independent of previously reported signals in ESR1 [rs12525163 odds ratio (OR) = 1.15, P = 4.9 × 10(-) (4)] and 19p13.1 (rs1864112 OR = 0.84, P = 1.8 × 10(-) (9)) were associated with TN breast cancer. A polygenic risk score (PRS) for TN breast cancer based on known breast cancer risk variants showed a 4-fold difference in risk between the highest and lowest PRS quintiles (OR = 4.03, 95% confidence interval 3.46-4.70, P = 4.8 × 10(-) (69)). This translates to an absolute risk for TN breast cancer ranging from 0.8% to 3.4%, suggesting that genetic variation may be used for TN breast cancer risk prediction.
EVALuna2:6530

Genome-wide association study identifies a common variant associated with risk of endometrial cancer - Spurdle, Amanda B.; Thompson, Deborah J.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; O'Mara, Tracy; Walker, Logan C.; Montgomery, Stephen B.; Dermitzakis, Emmanouil T.; Fahey, Paul; Montgomery, Grant W.; Webb, Penelope M.; et al. (Nature Genetics, 2011)
Endometrial cancer is the most common malignancy of the female genital tract in developed countries. To identify genetic variants associated with endometrial cancer risk, we performed a genome-wide association study involving 1,265 individuals with endometrial cancer (cases) from Australia and the UK and 5,190 controls from the Wellcome Trust Case Control Consortium. We compared genotype frequencies in cases and controls for 519,655 SNPs. Forty seven SNPs that showed evidence of association with endometrial cancer in stage 1 were genotyped in 3,957 additional cases and 6,886 controls. We identified an endometrial cancer susceptibility locus close to HNF1B at 17q12 (rs4430796, P = 7.1 × 10-10) that is also associated with risk of prostate cancer and is inversely associated with risk of type 2 diabetes. © 2011 Nature America, Inc. All rights reserved.
CRIS-Team Scopus Importer:2021-07-19

Genome-wide association study of germline variants and breast cancer-specific mortality - Escala-Garcia, Maria; Guo, Qi; Doerk, Thilo; Canisius, Sander; Keeman, Renske; Dennis, Joe; Beesley, Jonathan; Lecarpentier, Julie; Bolla, Manjeet K.; Wang, Qin; Abraham, Jean; Andrulis, Irene L.; et al. (British Journal of Cancer, 2019)
BACKGROUND: We examined the associations between germline variants and breast cancer mortality using a large meta-analysis of women of European ancestry.
CRIS-Team WoS Importer:2019-03-29

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Earp, Madalene A.; Kelemen, Linda E.; Magliocco, Anthony M.; Swenerton, Kenneth D.; Chenevix-Trench, Georgia; Lu, Yi; Hein, Alexander; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Lambrechts, Diether; Despierre, Evelyn; et al. (Human genetics, 2014)
Epithelial ovarian cancer (EOC) is a heterogeneous cancer with both genetic and environmental risk factors. Variants influencing the risk of developing the less-common EOC subtypes have not been fully investigated. We performed a genome-wide association study (GWAS) of EOC according to subtype by pooling genomic DNA from 545 cases and 398 controls of European descent, and testing for allelic associations. We evaluated for replication 188 variants from the GWAS [56 variants for mucinous, 55 for endometrioid and clear cell, 53 for low-malignant potential (LMP) serous, and 24 for invasive serous EOC], selected using pre-defined criteria. Genotypes from 13,188 cases and 23,164 controls of European descent were used to perform unconditional logistic regression under the log-additive genetic model; odds ratios (OR) and 95 % confidence intervals are reported. Nine variants tagging six loci were associated with subtype-specific EOC risk at P < 0.05, and had an OR that agreed in direction of effect with the GWAS results. Several of these variants are in or near genes with a biological rationale for conferring EOC risk, including ZFP36L1 and RAD51B for mucinous EOC (rs17106154, OR = 1.17, P = 0.029, n = 1,483 cases), GRB10 for endometrioid and clear cell EOC (rs2190503, P = 0.014, n = 2,903 cases), and C22orf26/BPIL2 for LMP serous EOC (rs9609538, OR = 0.86, P = 0.0043, n = 892 cases). In analyses that included the 75 GWAS samples, the association between rs9609538 (OR = 0.84, P = 0.0007) and LMP serous EOC risk remained statistically significant at P < 0.0012 adjusted for multiple testing. Replication in additional samples will be important to verify these results for the less-common EOC subtypes.
EVALuna2:9208

Genome-Wide DNA Methylation Patterns in Children Exposed to Nonpharmacologically Treated Prenatal Depressive Symptoms: Results From 2 Independent Cohorts - Stonawski, Valeska; Roetner, Jakob; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna; Heinrich, Hartmut; Frey, Stefan (Epigenetics Insights, 2020)
Background: Maternal depressive symptoms are a common phenomenon during pregnancy and are related to negative outcomes for child development and health. Modifications in child DNA methylation are discussed as an underlying mechanism for the association between prenatal depressive symptoms and alterations in child outcomes. However, formerly reported genome-wide associations have yet to be replicated. Methods: In an epigenome-wide association study (EWAS), alterations of DNA methylation related to maternal prenatal depressive symptoms were investigated in buccal cell samples from 174 children (n = 52 exposed to prenatal depressive symptoms; 6-9 years old) of the German longitudinal study FRAMES-FRANCES. Whole blood samples from the independent, age-comparable ARIES subsample of the ARIES/ALSPAC study (n = 641; n = 159 exposed to prenatal depressive symptoms; 7-8 years old) were examined as a confirmation sample. Depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale. DNA methylation was analyzed with the Infinium Human Methylation 450k BeadChip. Modifications in single CpGs, regions, and biological pathways were investigated. Results were adjusted for age and birth outcomes as well as postnatal and current maternal depressive symptoms. Analyses were performed for the whole sample as well as separated for sex. Results: The EWAS yielded no differentially methylated CpG or region as well as no accordance between samples withstanding correction for multiple testing. In pathway analyses, no overlapping functional domain was found to be enriched for either sample. A comparison of current and former findings suggests some overlapping methylation modifications from infancy to childhood. Results suggest that there might be sex-specific differential methylation, which should be further investigated in additional studies. Conclusions: The current, mainly nonsignificant, results challenge the assumption of consistent modifications of DNA methylation in children exposed to prenatal depressive symptoms. Despite the relatively small sample size used in this study, this lack of significant results may reflect diverse issues of environmental epigenetic studies, which need to be addressed in future research.
CRIS-Team Scopus Importer:2020-06-26
Keywords: ALSPAC; ARIES; DNA methylation; epigenetics; FRANCES; Pregnancy; prenatal depression

Genome-Wide Meta-Analyses of Breast, Ovarian, and Prostate Cancer Association Studies Identify Multiple New Susceptibility Loci Shared by at Least Two Cancer Types - Kar, Siddhartha P.; Beesley, Jonathan; Al Olama, Ali Amin; Michailidou, Kyriaki; Tyrer, Jonathan; Kote-Jarai, Zsofi A.; Lawrenson, Kate; Lindstrom, Sara; Ramus, Susan J.; Thompson, Deborah J.; Kibel, Adam S.; Dansonka-Mieszkowska, Agnieszka; et al. (Cancer Discovery, 2016)
Breast, ovarian, and prostate cancers are hormone-related and may have a shared genetic basis, but this has not been investigated systematically by genome-wide association (GWA) studies. Meta-analyses combining the largest GWA meta-analysis data sets for these cancers totaling 112,349 cases and 116,421 controls of European ancestry, all together and in pairs, identified at P < 10(-8) seven new cross-cancer loci: three associated with susceptibility to all three cancers (rs17041869/2q13/BCL2L11; rs7937840/11q12/INCENP; rs1469713/19p13/GATAD2A), two breast and ovarian cancer risk loci (rs200182588/9q31/SMC2; rs8037137/15q26/RCCD1), and two breast and prostate cancer risk loci (rs5013329/1p34/NSUN4; rs9375701/6q23/L3MBTL3). Index variants in five additional regions previously associated with only one cancer also showed clear association with a second cancer type. Cell-type-specific expression quantitative trait locus and enhancer-gene interaction annotations suggested target genes with potential cross-cancer roles at the new loci. Pathway analysis revealed significant enrichment of death receptor signaling genes near loci with P < 10(-5) in the three-cancer meta-analysis.We demonstrate that combining large-scale GWA meta-analysis findings across cancer types can identify completely new risk loci common to breast, ovarian, and prostate cancers. We show that the identification of such cross-cancer risk loci has the potential to shed new light on the shared biology underlying these hormone-related cancers. Cancer Discov; 6(9); 1052-67. ©2016 AACR.This article is highlighted in the In This Issue feature, p. 932.
EVALuna2:9322

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk - Day, Felix R.; Thompson, Deborah J.; Helgason, Hannes; Chasman, Daniel I.; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S.; Whalen, Sean; Sarkar, Abhishek K.; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nature Genetics, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10-8) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
EVALuna2:36141

Germline HOXB13 mutations p.G84E and p.R217C do not confer an increased breast cancer risk - Liu, Jingjing; Prager-van der Smissen, Wendy J.C.; Collée, J. Margriet; Bolla, Manjeet K.; Wang, Qin; Michailidou, Kyriaki; Dennis, Joe; Ahearn, Thomas U.; Aittomäki, Kristiina; Ambrosone, Christine B.; Andrulis, Irene L.; Anton-Culver, Hoda; et al. (Scientific Reports, 2020)
In breast cancer, high levels of homeobox protein Hox-B13 (HOXB13) have been associated with disease progression of ER-positive breast cancer patients and resistance to tamoxifen treatment. Since HOXB13 p.G84E is a prostate cancer risk allele, we evaluated the association between HOXB13 germline mutations and breast cancer risk in a previous study consisting of 3,270 familial non-BRCA1/2 breast cancer cases and 2,327 controls from the Netherlands. Although both recurrent HOXB13 mutations p.G84E and p.R217C were not associated with breast cancer risk, the risk estimation for p.R217C was not very precise. To provide more conclusive evidence regarding the role of HOXB13 in breast cancer susceptibility, we here evaluated the association between HOXB13 mutations and increased breast cancer risk within 81 studies of the international Breast Cancer Association Consortium containing 68,521 invasive breast cancer patients and 54,865 controls. Both HOXB13 p.G84E and p.R217C did not associate with the development of breast cancer in European women, neither in the overall analysis (OR = 1.035, 95% CI = 0.859-1.246, P = 0.718 and OR = 0.798, 95% CI = 0.482-1.322, P = 0.381 respectively), nor in specific high-risk subgroups or breast cancer subtypes. Thus, although involved in breast cancer progression, HOXB13 is not a material breast cancer susceptibility gene.
CRIS-Team Scopus Importer:2020-06-26

Germline polymorphisms in an enhancer of PSIP1 are associated with progression-free survival in epithelial ovarian cancer - French, Juliet D.; Johnatty, Sharon E.; Lu, Yi; Beesley, Jonathan; Gao, Bo; Kalimutho, Murugan; Henderson, Michelle J.; Russell, Amanda J.; Kar, Siddhartha; Chen, Xiaoqing; Hillman, Kristine M.; Kaufmann, Susanne; et al. (Oncotarget, 2016)
Women with epithelial ovarian cancer (EOC) are usually treated with platinum/taxane therapy after cytoreductive surgery but there is considerable inter-individual variation in response. To identify germline single-nucleotide polymorphisms (SNPs) that contribute to variations in individual responses to chemotherapy, we carried out a multi-phase genome-wide association study (GWAS) in 1,244 women diagnosed with serous EOC who were treated with the same first-line chemotherapy, carboplatin and paclitaxel. We identified two SNPs (rs7874043 and rs72700653) in TTC39B (best P=7x10-5, HR=1.90, for rs7874043) associated with progression-free survival (PFS). Functional analyses show that both SNPs lie in a putative regulatory element (PRE) that physically interacts with the promoters of PSIP1, CCDC171 and an alternative promoter of TTC39B. The C allele of rs7874043 is associated with poor PFS and showed increased binding of the Sp1 transcription factor, which is critical for chromatin interactions with PSIP1. Silencing of PSIP1 significantly impaired DNA damage-induced Rad51 nuclear foci and reduced cell viability in ovarian cancer lines. PSIP1 (PC4 and SFRS1 Interacting Protein 1) is known to protect cells from stress-induced apoptosis, and high expression is associated with poor PFS in EOC patients. We therefore suggest that the minor allele of rs7874043 confers poor PFS by increasing PSIP1 expression.
EVALuna2:9320

Germline variants and breast cancer survival in patients with distant metastases at primary breast cancer diagnosis - Escala-Garcia, Maria; Canisius, Sander; Keeman, Renske; Beesley, Jonathan; Anton-Culver, Hoda; Arndt, Volker; Augustinsson, Annelie; Becher, Heiko; Beckmann, Matthias; Behrens, Sabine; Bermisheva, Marina; Bojesen, Stig E.; et al. (Scientific Reports, 2021)
Breast cancer metastasis accounts for most of the deaths from breast cancer. Identification of germline variants associated with survival in aggressive types of breast cancer may inform understanding of breast cancer progression and assist treatment. In this analysis, we studied the associations between germline variants and breast cancer survival for patients with distant metastases at primary breast cancer diagnosis. We used data from the Breast Cancer Association Consortium (BCAC) including 1062 women of European ancestry with metastatic breast cancer, 606 of whom died of breast cancer. We identified two germline variants on chromosome 1, rs138569520 and rs146023652, significantly associated with breast cancer-specific survival (P = 3.19 x 10(-8) and 4.42 x 10(-8)). In silico analysis suggested a potential regulatory effect of the variants on the nearby target genes SDE2 and H3F3A. However, the variants showed no evidence of association in a smaller replication dataset. The validation dataset was obtained from the SNPs to Risk of Metastasis (StoRM) study and included 293 patients with metastatic primary breast cancer at diagnosis. Ultimately, larger replication studies are needed to confirm the identified associations.
CRIS-Team WoS Importer:2021-10-15

Gestational and Non-gestational Trophoblastic Disease. Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Registry No. 032/049, December 2015) - Tempfer, C.; Horn, L. -C.; Ackermann, S.; Beckmann, Matthias; Dittrich, Ralf; Einenkel, J.; Guenthert, A.; Haase, H.; Kratzsch, J.; Kreissl, M. C.; Polterauer, S.; Ebert, A. D.; et al. (Geburtshilfe und Frauenheilkunde, 2016)
Purpose: The aim was to establish an official interdisciplinary guideline, published and coordinated by the German Society of Gynecology and Obstetrics (DGGG). The guideline was developed for use in German-speaking countries. In addition to the Germany Society of Gynecology and Obstetrics, the guideline has also been approved by the Swiss Society of Gynecology and Obstetrics (SGGG) and the Austrian Society of Gynecology and Obstetrics (OEGGG). The aim was to standardize diagnostic procedures and the management of gestational and non-gestational trophoblastic disease in accordance with the principles of evidence-based medicine, drawing on the current literature and the experience of the colleagues involved in compiling the guideline. Methods: This s2k guideline represents the consensus of a representative panel of experts with a range of different professional backgrounds commissioned by the DGGG. Following a review of the international literature and international guidelines on trophoblastic tumors, a structural consensus was achieved in a formalized, multi-step procedure. This was done using uniform definitions, objective assessments, and standardized management protocols. Recommendations: The recommendations of the guideline cover the epidemiology, classification and staging of trophoblastic tumors; the measurement of human chorionic gonadotropin (hCG) levels in serum, and the diagnosis, management, and follow-up of villous trophoblastic tumors (e.g., partial mole, hydatidiform mole, invasive mole) and non-villous trophoblastic tumors (placental site nodule, exaggerated placental site, placental site tumor, epitheloid trophoblastic tumor, and choriocarcinoma).
EVALuna2:32997

GWAS meta-analysis and replication identifies three new susceptibility loci for ovarian cancer - Pharoah, Paul D. P.; Tsai, Ya-Yu; Ramus, Susan J.; Phelan, Catherine M.; Goode, Ellen L.; Lawrenson, Kate; Buckley, Melissa; Fridley, Brooke L.; Tyrer, Jonathan P.; Shen, Howard; Weber, Rachel; Karevan, Rod; et al. (Nature Genetics, 2013)
Genome-wide association studies (GWAS) have identified four susceptibility loci for epithelial ovarian cancer (EOC), with another two suggestive loci reaching near genome-wide significance. We pooled data from a GWAS conducted in North America with another GWAS from the UK. We selected the top 24,551 SNPs for inclusion on the iCOGS custom genotyping array. We performed follow-up genotyping in 18,174 individuals with EOC (cases) and 26,134 controls from 43 studies from the Ovarian Cancer Association Consortium. We validated the two loci at 3q25 and 17q21 that were previously found to have associations close to genome-wide significance and identified three loci newly associated with risk: two loci associated with all EOC subtypes at 8q21 (rs11782652, P = 5.5 × 10-9) and 10p12 (rs1243180, P = 1.8 × 10-8) and another locus specific to the serous subtype at 17q12 (rs757210, P = 8.1 × 10-10). An integrated molecular analysis of genes and regulatory regions at these loci provided evidence for functional mechanisms underlying susceptibility and implicated CHMP4C in the pathogenesis of ovarian cancer.
CRIS-Team Scopus Importer:2021-07-19

Gynecologic oncologists' attitudes and practices relating to integrative medicine: results of a nationwide AGO survey - Klein, Evelyn; Beckmann, Matthias; Bader, Werner; Brucker, Cosima; Dobos, Gustav; Fischer, Dorothea; Hanf, Volker; Hasenburg, Annette; Jud, Sebastian; Kalder, Matthias; Kiechle, Marion; Kuemmel, Sherko; et al. (Archives of Gynecology and Obstetrics, 2017)
PURPOSE: The growing popularity and acceptance of integrative medicine is evident both among patients and among the oncologists treating them. As little data are available regarding health-care professionals' knowledge, attitudes, and practices relating to the topic, a nationwide online survey was designed. METHODS: Over a period of 11 weeks (from July 15 to September 30, 2014) a self-administered, 17-item online survey was sent to all 676 members of the Research Group on Gynecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie) in the German Cancer Society. The questionnaire items addressed the use of integrative therapy methods, fields of indications for them, advice services provided, level of specific qualifications, and other topics. RESULTS: Of the 104 respondents (15.4%) using integrative medicine, 93% reported that integrative therapy was offered to breast cancer patients. The second most frequent type of tumor in connection with which integrative therapy methods were recommended was ovarian cancer, at 80% of the participants using integrative medicine. Exercise, nutritional therapy, dietary supplements, herbal medicines, and acupuncture were the methods the patients were most commonly advised to use. CONCLUSION: There is considerable interest in integrative medicine among gynecological oncologists, but integrative therapy approaches are at present poorly implemented in routine clinical work. Furthermore there is a lack of specific training. Whether future efforts should focus on extending counseling services on integrative medicine approaches in gynecologic oncology or not, have to be discussed. Evidence-based training on integrative medicine should be implemented in order to safely guide patients in their wish to do something by themselves.
EVALuna2:36130

Gynecologists’ attitudes toward and use of complementary and integrative medicine approaches: results of a national survey in Germany - Grimm, Donata; Voiss, Petra; Paepke, Daniela; Dietmaier, Johanna; Cramer, Holger; Kümmel, Sherko; Beckmann, Matthias; Woelber, Linn; Schmalfeldt, Barbara; Freitag, Ulrich; Kalder, Matthias; Wallwiener, Markus; et al. (Archives of Gynecology and Obstetrics, 2020)
Purpose: Despite patients’ widespread use and acceptance of complementary and integrative medicine (IM), few data are available regarding health-care professionals’ current implementation of it in clinical routine. A national survey was conducted to assess gynecologists’ attitudes to and implementation of complementary and integrative treatment approaches. Methods: The Working Group on Integrative Medicine of the German Society of Gynecological Oncology conducted an online survey in collaboration with the German Society of Gynecology and Obstetrics (DGGG) in July 2019. A 29-item survey was sent to all DGGG members by email. Results: Questionnaires from 180 gynecologists were analyzed, of whom 61 were working office-based in private practice and 95 were employed in hospitals. Seventy percent stated that IM concepts are implemented in their routine clinical work. Most physicians reported using IM methods in gynecological oncology. The main indications for IM therapies were fatigue (n = 98), nausea and vomiting (n = 89), climacteric symptoms (n = 87), and sleep disturbances (n = 86). The most commonly recommended methods were exercise therapy (n = 86), mistletoe therapy (n = 78), and phytotherapy (n = 74). Gynecologists offering IM were more often female (P = 0.001), more often had qualifications in anthroposophic medicine (P = 0.005) or naturopathy (P = 0.019), and were more often based in large cities (P = 0.016). Conclusions: There is strong interest in IM among gynecologists. The availability of evidence-based training in IM is increasing. Integrative therapy approaches are being implemented in clinical routine more and more, and integrative counseling services are present all over Germany. Efforts should focus on extending evidence-based knowledge of IM in both gynecology and gynecological oncology.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Attitude; Breast cancer; Complementary and alternative medicine; Gynecologic oncology; Integrative medicine; Supportive care

Gynecologists ' attitude towards their use of complementary and integrative medicine approaches: results of a nationwide AGO IMed survey - Grimm, D.; Paepke, D.; Voiss, P.; Cramer, H.; Kuemmel, S.; Beckmann, Matthias; Kalder, M.; Woelber, L.; Kiechle, M.; Schmalfeldt, B.; Hasenburg, A.; Hack, Carolin (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Health utilities in gynecological oncology and mastology in Germany - Hildebrandt, Thomas; Thiel, Falk; Fasching, Peter; Graf, Christiane; Bani, Mayada; Löhberg, Christian; Schrauder, Michael G.; Jud, Sebastian; Hack, Carolin; Beckmann, Matthias; Lux, Michael P. (Anticancer Research, 2014)
Cost increases in the healthcare system are leading to a need to distribute financial resources in accordance with the value of each service performed. Health-economic decision-making models can support these decisions. Due to the previous unavailability of health utilities in Germany (scored states of health as a basis for calculating quality-adjusted life-years, QALYs) for women undergoing treatment, international data are often used for such models. However, these may widely deviate from the values for a woman actually living in Germany. It is, therefore, necessary to collect and analyze health utilities in Germany.In a questionnaire survey, health utilities were collected, along with data for a healthy control group, for 580 female patients receiving treatment in the fields of mastology and gynecological oncology using a German version of the EuroQol questionnaire (EQ-5D) and a visual analogue scale (VAS). Data were also collected for the patients' medical history, tumor disease, and treatment.Significant differences with regard to quality of life were measured in relation to the individual tumor entities and in comparison to the controls. Apart from the healthy control group, patients with breast or cervical carcinoma had the best quality of life. In patients with recurrent and metastatic disease, those with breast carcinoma experienced the greatest impairment of their quality of life. According to current treatment, the most important impairment of life quality occurred in patients under radiotherapy and after surgical treatment. There are significant differences from the health utilities recorded for other countries - for example, the state of health declines much more markedly in patients with metastatic disease among American women with breast carcinoma than among German women, in whom recurrent disease and a first diagnosis of metastasis were comparable. Overall, the VAS was able to distinguish more adequately than the EQ-5D questionnaire between the different situations and impairments resulting from diagnosis and therapy.Health utilities are now, for the first time, available for further health-economics analyses in the field of gynecological oncology and mastology for women living in Germany. Important differences in these utilities from those of other countries are evident.
EVALuna2:17453

Heart Rate Measurement Accuracy of Fitbit Charge 4 and Samsung Galaxy Watch Active2: Device Evaluation Study - Nissen, Michael; Slim, Syrine; Jäger, Katharina; Flaucher, Madeleine; Hübner, Hanna; Danzberger, Nina; Fasching, Peter; Beckmann, Matthias; Gradl, Stefan; Eskofier, Björn (JMIR Formative Research, 2022)
Background: Fitness trackers and smart watches are frequently used to collect data in longitudinal medical studies. They allow continuous recording in real-life settings, potentially revealing previously uncaptured variabilities of biophysiological parameters and diseases. Adequate device accuracy is a prerequisite for meaningful research. Objective: This study aims to assess the heart rate recording accuracy in two previously unvalidated devices: Fitbit Charge 4 and Samsung Galaxy Watch Active2. Methods: Participants performed a study protocol comprising 5 resting and sedentary, 2 low-intensity, and 3 high-intensity exercise phases, lasting an average of 19 minutes 27 seconds. Participants wore two wearables simultaneously during all activities: Fitbit Charge 4 and Samsung Galaxy Watch Active2. Reference heart rate data were recorded using a medically certified Holter electrocardiogram. The data of the reference and evaluated devices were synchronized and compared at 1-second intervals. The mean, mean absolute error, mean absolute percentage error, Lin concordance correlation coefficient, Pearson correlation coefficient, and Bland-Altman plots were analyzed. Results: A total of 23 healthy adults (mean age 24.2, SD 4.6 years) participated in our study. Overall, and across all activities, the Fitbit Charge 4 slightly underestimated the heart rate, whereas the Samsung Galaxy Watch Active2 overestimated it (−1.66 beats per minute [bpm]/3.84 bpm). The Fitbit Charge 4 achieved a lower mean absolute error during resting and sedentary activities (seated rest: 7.8 vs 9.4; typing: 8.1 vs 11.6; laying down [left]: 7.2 vs 9.4; laying down [back]: 6.0 vs 8.6; and walking slowly: 6.8 vs 7.7 bpm), whereas the Samsung Galaxy Watch Active2 performed better during and after low- and high-intensity activities (standing up: 12.3 vs 9.0; walking fast: 6.1 vs 5.8; stairs: 8.8 vs 6.9; squats: 15.7 vs 6.1; resting: 9.6 vs 5.6 bpm). Conclusions: Device accuracy varied with activity. Overall, both devices achieved a mean absolute percentage error of just <10%. Thus, they were considered to produce valid results based on the limits established by previous work in the field. Neither device reached sufficient accuracy during seated rest or keyboard typing. Thus, both devices may be eligible for use in respective studies; however, researchers should consider their individual study requirement
Keywords: wearable validation; heart rate validation; Fitbit Charge 4; Samsung Galaxy Watch Active2; heart rate accuracy; fitness tracker accuracy; wearable accuracy; wearable (21); Fitbit (10); heart rate (14); fitness tracker (3); fitness (2); cardiovascular (8)

Height and Breast Cancer Risk: Evidence From Prospective Studies and Mendelian Randomization - Zhang, Ben; Shu, Xiao-Ou; Delahanty, Ryan J.; Zeng, Chenjie; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Wen, Wanqing; Long, Jirong; Li, Chun; Dunning, Alison M.; et al. (Journal of the National Cancer Institute, 2015)
Epidemiological studies have linked adult height with breast cancer risk in women. However, the magnitude of the association, particularly by subtypes of breast cancer, has not been established. Furthermore, the mechanisms of the association remain unclear.We performed a meta-analysis to investigate associations between height and breast cancer risk using data from 159 prospective cohorts totaling 5216302 women, including 113178 events. In a consortium with individual-level data from 46325 case patients and 42482 control patients, we conducted a Mendelian randomization analysis using a genetic score that comprised 168 height-associated variants as an instrument. This association was further evaluated in a second consortium using summary statistics data from 16003 case patients and 41335 control patients.The pooled relative risk of breast cancer was 1.17 (95% confidence interval [CI] = 1.15 to 1.19) per 10cm increase in height in the meta-analysis of prospective studies. In Mendelian randomization analysis, the odds ratio of breast cancer per 10cm increase in genetically predicted height was 1.22 (95% CI = 1.13 to 1.32) in the first consortium and 1.21 (95% CI = 1.05 to 1.39) in the second consortium. The association was found in both premenopausal and postmenopausal women but restricted to hormone receptor-positive breast cancer. Analyses of height-associated variants identified eight new loci associated with breast cancer risk after adjusting for multiple comparisons, including three loci at 1q21.2, DNAJC27, and CCDC91 at genome-wide significance level P < 5×10(-8).Our study provides strong evidence that adult height is a risk factor for breast cancer in women and certain genetic factors and biological pathways affecting adult height have an important role in the etiology of breast cancer.
EVALuna2:9301

HER2 and TOP2A amplification in a hospital-based cohort of breast cancer patients: associations with patient and tumor characteristics - Fasching, Peter A.; Weihbrecht, Sebastian; Haeberle, Lothar; Gasparyan, Armen; Villalobos, Ivonne E.; Ma, Yanling; Ekici, Arif Bülent; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Slamon, Dennis J.; Press, Michael F. (Breast Cancer Research and Treatment, 2014)
Gene amplification is an important factor for altered gene expression in breast cancers. TOP2A-amplification often occurs concomitantly with HER2 amplification, and it has been suggested to be predictive for the response to anthracycline chemotherapy. This study assessed the correlation between HER2 status and TOP2A co-amplification, the possible association of TOP2A single-nucleotide polymorphisms with the frequency of this co-amplification as well as confirmation of association with outcome. HER2 and TOP2A amplification were analyzed in a tissue microarray from a clinical cohort study. Additionally, a common genetic variant (rs13695) in the TOP2A gene was genotyped in germline DNA. HER2 gene amplification was compared with HER2-IHC findings assessed during clinical routine work, and the association between all the biomarkers analyzed and the clinical outcome was determined. As an exploratory aim, rs13695 genotypes were compared with TOP2A amplification status. HER2 amplification was seen in 101 of 628 (16.1 %) and TOP2A amplification in 32 (5.1 %) cancers. No TOP2A amplification occurred without HER2 co-amplification. HER2 amplification was found in 8, 13.6, and 55.1 % of patients with HER2-IHC 0/1+, 2+, and 3+ tumors, respectively. HER2-IHC was not associated with an effect on the prognosis, but HER2-FISH was. There was an association between the rs13695 genotype and TOP2A amplification status (P = 0.03). Although there was a significant correlation between HER2 status determined by IHC and HER2 by FISH, only HER2 gene amplification status by FISH was correlated with outcome indicating greater utility for FISH in routine clinical settings.
EVALuna2:6613

Heregulin (HRG) assessment for clinical trial eligibility testing in a molecular registry (PRAEGNANT) in Germany - Hübner, Hanna; Kurbacher, Christian M.; Kuesters, Geoffrey; Hartkopf, Andreas D.; Lux, Michael P.; Huober, Jens; Volz, Bernhard; Taran, Florin Andrei; Overkamp, Friedrich; Tesch, Hans; Häberle, Lothar; Lüftner, Diana; et al. (BMC Cancer, 2020)
Background: Eligibility criteria are a critical part of clinical trials, as they define the patient population under investigation. Besides certain patient characteristics, clinical trials often include biomarker testing for eligibility. However, patient-identification mostly relies on the trial site itself and is often a time-consuming procedure, which could result in missing out on potentially eligible patients. Pre-selection of those patients using a registry could facilitate the process of eligibility testing and increase the number of identified patients. One aim with the PRAEGNANT registry (NCT02338167) is to identify patients for therapies based on clinical and molecular data. Here, we report eligibility testing for the SHERBOC trial using the German PRAEGNANT registry. Methods: Heregulin (HRG) has been reported to identify patients with better responses to therapy with the anti-HER3 monoclonal antibody seribantumab (MM-121). The SHERBOC trial investigated adding seribantumab (MM-121) to standard therapy in patients with advanced HER2-negative, hormone receptor–positive (HR-positive) breast cancer and HRG overexpression. The PRAEGNANT registry was used for identification and tumor testing, helping to link potential HRG positive patients to the trial. Patients enrolled in PRAEGNANT have invasive and metastatic or locally advanced, inoperable breast cancer. Patients eligible for SHERBOC were identified by using the registry. Study aims were to describe the HRG positivity rate, screening procedures, and patient characteristics associated with inclusion and exclusion criteria. Results: Among 2769 unselected advanced breast cancer patients, 650 were HER2-negative, HR-positive and currently receiving first- or second-line treatment, thus potentially eligible for SHERBOC at the end of current treatment; 125 patients also met further clinical eligibility criteria (e.g. menopausal status, ECOG). In the first/second treatment lines, patients selected for SHERBOC based on further eligibility criteria had a more favorable prognosis than those not selected. HRG status was tested in 38 patients, 14 of whom (36.8%) proved to be HRG-positive. Conclusion: Using a real-world breast cancer registry allowed identification of potentially eligible patients for SHERBOC focusing on patients with HER3 overexpressing, HR-positive, HER2-negative metastatic breast cancer. This approach may provide insights into differences between patients eligible or non-eligible for clinical trials. Trial registration: Clinicaltrials, NCT02338167, Registered 14 January 2015 - retrospectively registered.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Advanced breast cancer; Antihormone therapy; Heregulin; Metastatic; MM-121; Seribantumab

History of Comorbidities and Survival of Ovarian Cancer Patients, Results from the Ovarian Cancer Association Consortium - Minlikeeva, Albina N.; Freudenheim, Jo L.; Eng, Kevin H.; Cannioto, Rikki A.; Friel, Grace; Szender, J. Brian; Segal, Brahm; Odunsi, Kunle; Mayor, Paul; Diergaarde, Brenda; Zsiros, Emese; Kelemen, Linda E.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2017)
Background: Comorbidities can affect survival of ovarian cancer patients by influencing treatment efficacy. However, little evidence exists on the association between individual concurrent comorbidities and prognosis in ovarian cancer patients.Methods: Among patients diagnosed with invasive ovarian carcinoma who participated in 23 studies included in the Ovarian Cancer Association Consortium, we explored associations between histories of endometriosis; asthma; depression; osteoporosis; and autoimmune, gallbladder, kidney, liver, and neurological diseases and overall and progression-free survival. Using Cox proportional hazards regression models adjusted for age at diagnosis, stage of disease, histology, and study site, we estimated pooled HRs and 95% confidence intervals to assess associations between each comorbidity and ovarian cancer outcomes.Results: None of the comorbidities were associated with ovarian cancer outcome in the overall sample nor in strata defined by histologic subtype, weight status, age at diagnosis, or stage of disease (local/regional vs. advanced).Conclusions: Histories of endometriosis; asthma; depression; osteoporosis; and autoimmune, gallbladder, kidney, liver, or neurologic diseases were not associated with ovarian cancer overall or progression-free survival.Impact: These previously diagnosed chronic diseases do not appear to affect ovarian cancer prognosis. Cancer Epidemiol Biomarkers Prev; 26(9); 1470-3. ©2017 AACR.
EVALuna2:36128

HLA-G and HLA-F protein isoform expression in breast cancer patients receiving neoadjuvant treatment - Würfel, Franziska; Hübner, Hanna; Häberle, Lothar; Gaß, Paul; Hein, Alexander; Jud, Sebastian; Hack, Carolin; Wunderle, Marius; Schulz-Wendtland, Rüdiger; Erber, Ramona; Hartmann, Arndt; Ekici, Arif Bülent; et al. (Scientific Reports, 2020)
The immunosuppressive human leukocyte antigens HLA-G and HLA-F are expressed on trophoblast and malignant cells. Four membrane-bound and three soluble HLA-G protein isoforms have been described, which have different immunosuppressive potentials. HLA-F has three transcript variants, resulting in three different protein isoforms. The aim of this study was to evaluate the prognostic and predictive value of HLA-G and HLA-F protein isoform expression patterns in patients with breast cancer. Core biopsies were taken at diagnosis in patients with HER2+ (n = 28), luminal B-like (n = 49) and triple-negative (n = 38) breast cancers who received neoadjuvant chemotherapy. Expression levels of HLA-F and -G were correlated with the pathological complete response (pCR). Protein expression was determined by Western blot analysis, using two antibodies for each HLA, specific for different isoforms. The protein expression of HLA isoforms did not significantly differ between breast cancer subtypes. However, some initial indications were found for an association between the soluble HLA-G6 protein isoform and pCR in HER2+ breast cancer. The study provides preliminary evidence for the evaluation of HLA-G isoform expression, in particular HLA-G6, as a possible new marker for pCR in HER2+ breast cancer.
CRIS-Team Scopus Importer:2020-10-02

Hormone replacement therapy and prognosis in ovarian cancer patients - Hein, Alexander; Thiel, Falk; Bayer, Christian M.; Fasching, Peter; Häberle, Lothar; Lux, Michael P.; Renner, Stefan; Jud, Sebastian; Schrauder, Michael G.; Müller, Andreas; Wachter, David; Strehl, Johanna; et al. (European Journal of Cancer Prevention, 2013)
Estrogen exposure has at least a moderate effect on the risk for ovarian cancer, and antiestrogen therapy may be helpful in treating the disease. It is known from breast cancer that previous hormone replacement therapy (HRT) may influence the molecular profile and prognostic behavior of these tumors. The aim of this study was therefore to investigate the influence of previous HRT on the prognosis in a cohort of patients with invasive epithelial ovarian cancer. Among 547 patients who were treated for ovarian malignancies at a single institution from 1995 to 2008, a total of 244 postmenopausal patients with epithelial cancer and under the age of 75 were identified for whom information about HRT before the onset of the disease was available. HRT was correlated with tumor and patient characteristics. Analyses of overall survival and progression-free survival were carried out using Cox proportional hazards models. Age, tumor stage, and resection status correlated significantly with HRT in the univariate analysis. Patients with previous HRT were more likely to have a lower stage, to be younger, and to have optimal debulking. With regard to survival, HRT had a positive effect on overall survival, specifically in the subgroup of patients with optimal debulking. No correlation was seen in relation to progression-free survival. Sex hormone exposure through HRT may influence the behavior of ovarian cancers after the onset of the disease. This study supports the hypothesis that ovarian cancer is a hormonally influenced tumor. © 2012 Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-07-19
Keywords: estrogen; hormone replacement therapy; ovarian cancer; pathogenesis; prognosis

Hormone Therapy and its Effect on the Prognosis in Breast Cancer Patients - Rauh, C.; Schuetz, F.; Rack, B.; Stickeler, E.; Klar, M.; Orlowska-Volk, M.; Windfuhr-Blum, M.; Heil, J.; Rom, J.; Sohn, C.; Andergassen, U.; Jueckstock, J.; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Use of hormone therapy (HT) has declined dramatically in recent years. Some studies have reported that HT use before a diagnosis of breast cancer (BC) may be a prognostic factor in postmenopausal patients. This study aimed to examine the prognostic relevance of HT use before BC diagnosis. Methods: Four BC cohort studies in Germany were pooled, and 4492 postmenopausal patients with HT use data were identified. Patient data and tumor characteristics were compared between users and nonusers, along with overall survival (OS), distant metastasis-free survival (DMFS), and local recurrence-free survival (LRFS). Cox proportional hazards models were stratified by study center and adjusted for age at diagnosis, tumor stage, grading, nodal status, and hormone receptors. Results: Women with HT use before the diagnosis of BC were more likely to have a lower tumor stage, to be estrogen receptor-negative, and to have a lower grading. With regard to prognosis there were effects seen for OS, DMFS and LRFS, specifically in the subgroup of women with a positive hormone receptor. In these subgroups, BC patients had a better prognosis with previous HT use. Conclusions: HT use before a diagnosis of BC is associated with a more favorable prognosis in women with a positive hormone receptor status. It may be recommended that the prognostic factor HT should be documented and analyzed as a confounder for prognosis in studies of postmenopausal hormone-responsive breast cancers.
EVALuna2:6745

HPV16-L1-specific antibody response is associated with clinical remission of high-risk HPV-positive early dysplastic lesions - Mehlhorn, Grit; Hautmann, Simone K.; Koch, Martin; Strehl, Johanna D.; Hartmann, Arndt; Hilfrich, Ralf; Beckmann, Matthias; Griesser, Henrik (Anticancer Research, 2014)
The present study was aimed at clarifying if use of a rapid human papillomavirus type 16 L1-specific antibody test could be used to improve clinical management of high-risk HPV-positive low-grade squamous intraepithelial lesion (LSIL)/high-grade squamous intraepithelial lesion (HSIL).The study was nested within a prospective study of 801 patients with early dysplastic high-risk HPV-positive lesions to examine the prognostic significance of HPV-L1 protein detection. Serum samples of 87 patients were tested with a rapid HPV16-L1-specific antibody test. The results were correlated with the clinical outcome during 66 months of follow-up.A combined analysis of the 22 antibody-positive women showed that 17 were also L1 protein-positive, and 5 were L1 capsid protein-negative. An HPV-specific immune competence strongly correlates with clinical remission of low-grade squamous intraepithelial lesion (76.6%). For L1 antigen and HPV16-L1 antibody double-positive women, the risk of progression to cervical intraepithelial neoplasia grade 3 was low (5.8%).The rapid anti-HPV16-L1 test could be a promising tool to improve risk assessment and appropriate clinical management of high-risk HPV-positive early dysplastic lesions.
EVALuna2:6623

Human endogenous retroviruses differentially regulate immune checkpoints and modulation of immune responses in serous ovarian carcinoma - Strissel, Pamela; Chiappinelli, Katherine B.; Strehl, Johanna; Wuefel, Franziska M. B.; Beckmann, Matthias; Baylin, Stephen B.; Strick, Reiner (2017)
EVALuna2:34862

Human papilloma virus genotype distribution in women with premalignant or malignant lesions of the uterine cervix - Stübs, Frederik; Gaß, Paul; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2021)
Objective: Cervical cancer is caused by persistent infection with high-risk human papillomavirus (hrHPV). Cytology-based national screening programs have reduced the incidence and mortality of cervical cancer. Different hrHPV subtypes have different carcinogenic potentials. This study evaluated the distribution of different types of hrHPV relative to age in cervical cancer and its precursor lesions. Methods: HPV testing was performed between November 2018 and February 2020 using the Abbott RealTime high-risk HPV assay on an Abbott m2000sp instrument. This assay separately detects HPV-16, HPV-18, and a pool of 12 additional hrHPV types (HPV-31, -33, -35, -39, -45, -51, -52, -56, -58, -59, -66, and -68). Results: The study included 652 women with HPV samples and biopsies of the cervix or histology samples obtained during surgery. In all, 30.8% (95% CI, 27.3–34.6%) were HPV-negative. Among HPV-positive women, HPV-16, HPV-18, and “HPV other” types were found in 33.5, 4.4, and 49.4%, respectively. Cervical intraepithelial neoplasia (CIN) 3/high-grade squamous intraepithelial lesions (HSILs) in women ≤ 34 years were positive for HPV-16 in 54.5% of cases and in those ≥ 35 years in 45.4% of cases. Among women with cervical cancer, 75.8% were infected with HPV-16 or had coinfection with HPV-16 and “HPV other”. Conclusions: HPV-16 is the most common type of hrHPV in HSIL + lesions. It is more common in women diagnosed with CIN 3/HSIL who are aged ≤ 35 and is decreasing with age. Therefore, women age ≥ 35 with persistent infection with this type of hrHPV need careful surveillance, as they are at high risk of progression to cervical cancer.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Age-distribtuion of HPV; Cervical cancer; Colposcopy; HPV-distribution; HSIL

Hyperandrogenemia and high prolactin in congenital utero-vaginal aplasia patients - Oppelt, Patricia; Mueller, Andreas; Stephan, Liana; Dittrich, Ralf; Lermann, Johannes; Büttner, Christian; Ekici, Arif Bülent; Conzelmann, Gabi; Seeger, Harald; Schoeller, Dorit; Rall, Katharina; Beckmann, Matthias; et al. (Reproduction, 2017)
Patients with the Mayer-Rokitansky-Küster-Hauser syndrome (MRKH) have a congenital utero-vaginal cervical aplasia, but normal or hypoplastic adnexa and develop with normal female phenotype. Some reports mostly demonstrated regular steroid hormone levels in small MRKH cohorts including single MRKH patients with hyperandrogenemia and a clinical presentationof hirsutism and acne has also been shown. Genetically a correlation of WNT4 mutations with singular MRKH patients and hyperandrogenemia was noted. This study analyzed the hormone status of 215 MRKH patients by determining the levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol, 17-OH progesterone, testosterone, dehydroepiandrosterone sulfate (DHEAS), sex hormone-binding globulin (SHBG) and prolactin to determine the incidence of hyperandrogenemia and hyperprolactinemia in MRKH patients. Additional calculations and a ratio of free androgen index and biologically active testosterone revealed a hyperandrogenemia rate of 48.3%, hyperprolactinemia of 9.8% and combined hyperandrogenemia and hyperprolactinemia of 4.2% in MRKH patients. The rates of hirsutism, acne and especially polycystic ovary syndrome (PCOS) were in the normal range of the population and showed no correlation with hyperandrogenemia. A weekly hormone assessment over 30 days comparing 5 controls and 7 MRKH patients revealed high androgen and prolactin, but lower LH/FSH and SHBG levels with MRKH patients. The sequencing of WNT4, WNT5A, WNT7A and WNT9B demonstrated no significant mutations correlating with hyperandrogenemia. Taken together, this study shows that over 52% of MRKH patients have hyperandrogenemia without clinical presentation and 14% hyperprolactinemia, which appeals for general hormone assessment and adjustments of MRKH patients.
EVALuna2:9378

Hypermethylation and loss of retinoic acid receptor responder 1 expression in human choriocarcinoma - Hübner, Hanna; Strick, Reiner; Wachter, David Lukas; Kehl, Sven; Strissel, Pamela; Schneider-Stock, Regine; Rascher, Wolfgang; Horn, L. C.; Beckmann, Matthias; Rübner, Matthias; Fahlbusch, F. B.; Hartner, Andrea (Journal of Experimental & Clinical Cancer Research, 2017)
BACKGROUND: Human placental development resembles tumorigenesis, due to the invasive and fusogenic potential of trophoblasts. However, these features are tightly controlled in trophoblasts. Disturbance of this spatial and temporal regulation is thought to contribute to the rare formation of choriocarcinomas. Promoter hypermethylation and loss of the tumor suppressor Retinoic acid receptor responder 1 (RARRES1) were shown to contribute to cancer progression. Our study investigated the epigenetic and transcriptional regulation of RARRES1 in healthy human placenta in comparison to choriocarcinoma cell lines and cases. METHODS: Three choriocarcinoma cell lines (Jeg-3, JAR and BeWo) were treated with three different retinoic acid derivates (Am580, Tazarotene and all-trans retinoic acid) and 5-aza-2'-deoxycytidine. We analyzed RARRES1 promoter methylation by pyrosequencing and performed realtime-PCR quantification to determine RARRES1 expression in placental tissue and trophoblastic cell lines. Additionally, RARRES1 was stained in healthy placentas and in biopsies of choriocarcinoma cases (n = 10) as well as the first trimester trophoblast cell line Swan71 by immunofluorescence and immunohistochemistry. RESULTS: In the choriocarcinoma cell lines, RARRES1 expression could not be induced by sole retinoic acid treatment. Stimulation with 5-aza-2'-deoxycytidine significantly induced RARRES1 expression, which then could be further increased with Am580, Tazarotene and all-trans retinoic acid. In comparison to healthy placenta, choriocarcinoma cell lines showed a hypermethylation of the RARRES1 promoter, which correlated with a reduced RARRES1 expression. In concordance, RARRES1 protein expression was lost in choriocarcinoma tissue. Additionally, in the trophoblastic cell line Swan71, we found a significant induction of RARRES1 expression with increased cell density, during mitosis and in syncytial knots. CONCLUSIONS: Our findings showed that RARRES1 expression is absent in choriocarcinoma due to promoter methylation. Based on our analysis, we hypothesize that RARRES1 might exert tumor suppressive functions in multiple cellular processes (e.g. cell cycle regulation, adhesion, invasion and apoptosis).
EVALuna2:33950

Hypohidrotic Ectodermal Dysplasia: Breastfeeding Complications Due to Impaired Breast Development - Wahlbuhl-Becker, Mandy; Faschingbauer, Florian; Beckmann, Matthias; Schneider, Holm (Geburtshilfe und Frauenheilkunde, 2017)
Background X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common form of ectodermal dysplasia, is caused by mutations in the gene EDA. While only affected men develop the full-blown clinical picture, females who are heterozygous for an EDA mutation often also show symptoms such as hypodontia, hypotrichosis and hypohidrosis. These women may also suffer from malformations of the mammary gland which represent not just a cosmetic problem but can limit their breastfeeding capability. This paper summarizes the findings of the first systematic study on the impact of hypohidrotic ectodermal dysplasia on breastfeeding. Patients Thirty-eight adult female members of the German-Swiss-Austrian ectodermal dysplasia patient support group participated in a structured interview; most of them also agreed to a photodocumentation of their mammary region. Thirty-one women carried mutations in EDA (Group A) and seven were affected by other forms of hypohidrotic ectodermal dysplasia (Group B). Results 39 % of the women of Group A reported that their breasts were of different size or entirely absent on one side. In Group B, 86 % of the women reported differently sized or even absent breasts; two of these women lacked both breasts entirely. Most women described their nipples as exceptionally flat. 10 % of the women of Group A had more than two nipples. The high percentage of deviations from the norm was confirmed in the photodocumentation. Both groups had few or no sebaceous glands of Montgomery in the areolar region. Around 80 % of interviewed women had children and had attempted to breastfeed their first child. 67 % of the mothers in Group A had had difficulty in breastfeeding their infants and generally attributed this difficulty to their flat nipples. All of the mothers in Group B reported difficulties in breastfeeding; 60 % had not been able to breastfeed their first child. Conclusion Mothers with hypohidrotic ectodermal dysplasia very often have difficulty in breastfeeding because of their impaired breast development. This causal relationship needs to be taken into account in lactation counseling.
EVALuna2:34219

Identification and characterization of novel associations in the CASP8/ALS2CR12 region on chromosome 2 with breast cancer risk - Lin, Wei-Yu; Camp, Nicola J.; Ghoussaini, Maya; Beesley, Jonathan; Michailidou, Kyriaki; Hopper, John L.; Apicella, Carmel; Southey, Melissa C.; Stone, Jennifer; Schmidt, Marjanka K.; Broeks, Annegien; Van'T Veer, Laura J.; et al. (Human Molecular Genetics, 2015)
Previous studies have suggested that polymorphisms in CASP8 on chromosome 2 are associated with breast cancer risk. To clarify the role of CASP8 in breast cancer susceptibility, we carried out dense genotyping of this region in the Breast Cancer Association Consortium (BCAC). Single-nucleotide polymorphisms (SNPs) spanning a 1 Mb region around CASP8 were genotyped in 46 450 breast cancer cases and 42 600 controls of European origin from 41 studies participating in the BCAC as part of a custom genotyping array experiment (iCOGS). Missing genotypes and SNPs were imputed and, after quality exclusions, 501 typed and 1232 imputed SNPs were included in logistic regression models adjusting for study and ancestry principal components. The SNPs retained in the final model were investigated further in data from nine genome-wide association studies (GWAS) comprising in total 10 052 case and 12 575 control subjects. The most significant association signal observed in European subjects was for the imputed intronic SNP rs1830298 in ALS2CR12 (telomeric to CASP8), with per allele odds ratio and 95% confidence interval [OR (95% confidence interval, CI)] for the minor allele of 1.05 (1.03-1.07), P = 1 × 10(-5). Three additional independent signals from intronic SNPs were identified, in CASP8 (rs36043647), ALS2CR11 (rs59278883) and CFLAR (rs7558475). The association with rs1830298 was replicated in the imputed results from the combined GWAS (P = 3 × 10(-6)), yielding a combined OR (95% CI) of 1.06 (1.04-1.08), P = 1 × 10(-9). Analyses of gene expression associations in peripheral blood and normal breast tissue indicate that CASP8 might be the target gene, suggesting a mechanism involving apoptosi
EVALuna2:9254

Identification and validation of expressed HLA-binding breast cancer neoepitopes for potential use in individualized cancer therapy - Reimann, Hannah; Nguyen, Andrew; Sanborn, J. Zachary; Vaske, Charles J.; Benz, Stephen C.; Niazi, Kayvan; Rabizadeh, Shahrooz; Spilman, Patricia; Mackensen, Andreas; Rübner, Matthias; Hein, Alexander; Beckmann, Matthias; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Therapeutic regimens designed to augment the immunological response of a patient with breast cancer (BC) to tumor tissue are critically informed by tumor mutational burden and the antigenicity of expressed neoepitopes. Herein we describe a neoepitope and cognate neoepitope-reactive T-cell identification and validation program that supports the development of next-generation immunotherapies. Methods Using GPS Cancer, NantOmics research, and The Cancer Genome Atlas databases, we developed a novel bioinformatic-based approach which assesses mutational load, neoepitope expression, human leukocyte antigen (HLA)-binding prediction, and in vitro confirmation of T-cell recognition to preferentially identify targetable neoepitopes. This program was validated by application to a BC cell line and confirmed using tumor biopsies from two patients with BC enrolled in the Tumor-Infiltrating Lymphocytes and Genomics (TILGen) study. Results The antigenicity and HLA-A2 restriction of the BC cell line predicted neoepitopes were determined by reactivity of T cells from HLA-A2-expressing healthy donors. For the TILGen subjects, tumor-infiltrating lymphocytes (TILs) recognized the predicted neoepitopes both as peptides and on retroviral expression in HLA-matched Epstein-Barr virus-lymphoblastoid cell line and BC cell line MCF-7 cells; PCR clonotyping revealed the presence of T cells in the periphery with T-cell receptors for the predicted neoepitopes. These high-avidity immune responses were polyclonal, mutation-specific and restricted to either HLA class I or II. Interestingly, we observed the persistence and expansion of polyclonal T-cell responses following neoadjuvant chemotherapy. Conclusions We demonstrate our neoepitope prediction program allows for the successful identification of neoepitopes targeted by TILs in patients with BC, providing a means to identify tumor-specific immunogenic targets for individualized treatment, including vaccines or adoptively transferred cellular therapies.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Antigens; Breast neoplasms; Neoplasm

Identification of 12 new susceptibility loci for different histotypes of epithelial ovarian cancer - Phelan, Catherine M.; Kuchenbaecker, Karoline B.; Tyrer, Jonathan P.; Kar, Siddhartha P.; Lawrenson, Kate; Winham, Stacey J.; Dennis, Joe; Pirie, Ailith; Riggan, Marjorie J.; Chornokur, Ganna; Earp, Madalene A.; Lyra, Paulo C.; et al. (Nature Genetics, 2017)
To identify common alleles associated with different histotypes of epithelial ovarian cancer (EOC), we pooled data from multiple genome-wide genotyping projects totaling 25,509 EOC cases and 40,941 controls. We identified nine new susceptibility loci for different EOC histotypes: six for serous EOC histotypes (3q28, 4q32.3, 8q21.11, 10q24.33, 18q11.2 and 22q12.1), two for mucinous EOC (3q22.3 and 9q31.1) and one for endometrioid EOC (5q12.3). We then performed meta-analysis on the results for high-grade serous ovarian cancer with the results from analysis of 31,448 BRCA1 and BRCA2 mutation carriers, including 3,887 mutation carriers with EOC. This identified three additional susceptibility loci at 2q13, 8q24.1 and 12q24.31. Integrated analyses of genes and regulatory biofeatures at each locus predicted candidate susceptibility genes, including OBFC1, a new candidate susceptibility gene for low-grade and borderline serous EOC.
EVALuna2:9375

Identification of Disparities in Personalized Cancer Care—A Joint Approach of the German WERA Consortium - Lüke, Florian; Haller, Florian; Utpatel, Kirsten; Krebs, Markus; Meidenbauer, Norbert; Scheiter, Alexander; Spörl, Silvia; Heudobler, Daniel; Sparrer, Daniela; Kaiser, Ulrich; Keil, Felix; Schubart, Christoph; et al. (Cancers, 2022)
(1) Background: molecular tumor boards (MTBs) are crucial instruments for discussing and allocating targeted therapies to suitable cancer patients based on genetic findings. Currently, limited evidence is available regarding the regional impact and the outreach component of MTBs; (2) Methods: we analyzed MTB patient data from four neighboring Bavarian tertiary care oncology centers in Würzburg, Erlangen, Regensburg, and Augsburg, together constituting the WERA Alliance. Absolute patient numbers and regional distribution across the WERA-wide catchment area were weighted with local population densities; (3) Results: the highest MTB patient numbers were found close to the four cancer centers. However, peaks in absolute patient numbers were also detected in more distant and rural areas. Moreover, weighting absolute numbers with local population density allowed for identifying so-called white spots—regions within our catchment that were relatively underrepresented in WERA MTBs; (4) Conclusions: investigating patient data from four neighboring cancer centers, we comprehensively assessed the regional impact of our MTBs. The results confirmed the success of existing collaborative structures with our regional partners. Additionally, our results help identifying potential white spots in providing precision oncology and help establishing a joint WERA-wide outreach strategy.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cancer care; MTB; outcomes research; outreach; patient access; precision oncology; real world data

Identification of four novel susceptibility loci for oestrogen receptor negative breast cancer - Couch, Fergus J.; Kuchenbaecker, Karoline B.; Michailidou, Kyriaki; Mendoza-Fandino, Gustavo A.; Nord, Silje; Lilyquist, Janna; Olswold, Curtis; Hallberg, Emily; Agata, Simona; Ahsan, Habibul; Aittomaeki, Kristiina; Ambrosone, Christine; et al. (Nature Communications, 2016)
Common variants in 94 loci have been associated with breast cancer including 15 loci with genome-wide significant associations (P<5 × 10(-8)) with oestrogen receptor (ER)-negative breast cancer and BRCA1-associated breast cancer risk. In this study, to identify new ER-negative susceptibility loci, we performed a meta-analysis of 11 genome-wide association studies (GWAS) consisting of 4,939 ER-negative cases and 14,352 controls, combined with 7,333 ER-negative cases and 42,468 controls and 15,252 BRCA1 mutation carriers genotyped on the iCOGS array. We identify four previously unidentified loci including two loci at 13q22 near KLF5, a 2p23.2 locus near WDR43 and a 2q33 locus near PPIL3 that display genome-wide significant associations with ER-negative breast cancer. In addition, 19 known breast cancer risk loci have genome-wide significant associations and 40 had moderate associations (P<0.05) with ER-negative disease. Using functional and eQTL studies we implicate TRMT61B and WDR43 at 2p23.2 and PPIL3 at 2q33 in ER-negative breast cancer aetiology. All ER-negative loci combined account for 11% of familial relative risk for ER-negative disease and may contribute to improved ER-negative and BRCA1 breast cancer risk prediction.
EVALuna2:9317

Identification of new genetic susceptibility Loci for breast cancer through consideration of gene-environment interactions - Schoeps, Anja; Rudolph, Anja; Seibold, Petra; Dunning, Alison M.; Milne, Roger L.; Bojesen, Stig E.; Swerdlow, Anthony; Andrulis, Irene; Brenner, Hermann; Behrens, Sabine; Orr, Nicholas; Jones, Michael; et al. (Genetic Epidemiology, 2014)
Genes that alter disease risk only in combination with certain environmental exposures may not be detected in genetic association analysis. By using methods accounting for gene-environment (G × E) interaction, we aimed to identify novel genetic loci associated with breast cancer risk. Up to 34,475 cases and 34,786 controls of European ancestry from up to 23 studies in the Breast Cancer Association Consortium were included. Overall, 71,527 single nucleotide polymorphisms (SNPs), enriched for association with breast cancer, were tested for interaction with 10 environmental risk factors using three recently proposed hybrid methods and a joint test of association and interaction. Analyses were adjusted for age, study, population stratification, and confounding factors as applicable. Three SNPs in two independent loci showed statistically significant association: SNPs rs10483028 and rs2242714 in perfect linkage disequilibrium on chromosome 21 and rs12197388 in ARID1B on chromosome 6. While rs12197388 was identified using the joint test with parity and with age at menarche (P-values = 3 × 10(-07) ), the variants on chromosome 21 q22.12, which showed interaction with adult body mass index (BMI) in 8,891 postmenopausal women, were identified by all methods applied. SNP rs10483028 was associated with breast cancer in women with a BMI below 25 kg/m(2) (OR = 1.26, 95% CI 1.15-1.38) but not in women with a BMI of 30 kg/m(2) or higher (OR = 0.89, 95% CI 0.72-1.11, P for interaction = 3.2 × 10(-05) ). Our findings confirm comparable power of the recent methods for detecting G × E interaction and the utility of using G × E interaction analyses to identify new susceptibility loci.
EVALuna2:9203

Identification of nine new susceptibility loci for endometrial cancer - O'Mara, Tracy A.; Glubb, Dylan M.; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias; Black, Amanda; Bolla, Manjeet K.; Brauch, Hiltrud; Brenner, Hermann; et al. (Nature Communications, 2018)
Endometrial cancer is the most commonly diagnosed cancer of the female reproductive tract in developed countries. Through genome-wide association studies (GWAS), we have previously identified eight risk loci for endometrial cancer. Here, we present an expanded meta-analysis of 12,906 endometrial cancer cases and 108,979 controls (including new genotype data for 5624 cases) and identify nine novel genome-wide significant loci, including a locus on 12q24.12 previously identified by meta-GWAS of endometrial and colorectal cancer. At five loci, expression quantitative trait locus (eQTL) analyses identify candidate causal genes; risk alleles at two of these loci associate with decreased expression of genes, which encode negative regulators of oncogenic signal transduction proteins (SH2B3 (12q24.12) and NF1 (17q11.2)). In summary, this study has doubled the number of known endometrial cancer risk loci and revealed candidate causal genes for future study.
EVALuna2:34618

Identification of novel genetic markers of breast cancer survival - Guo, Qi; Schmidt, Marjanka K.; Kraft, Peter; Canisius, Sander; Chen, Constance; Khan, Sofia; Tyrer, Jonathan; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Lush, Michael; et al. (Journal of the National Cancer Institute, 2015)
Survival after a diagnosis of breast cancer varies considerably between patients, and some of this variation may be because of germline genetic variation. We aimed to identify genetic markers associated with breast cancer-specific survival.We conducted a large meta-analysis of studies in populations of European ancestry, including 37954 patients with 2900 deaths from breast cancer. Each study had been genotyped for between 200000 and 900000 single nucleotide polymorphisms (SNPs) across the genome; genotypes for nine million common variants were imputed using a common reference panel from the 1000 Genomes Project. We also carried out subtype-specific analyses based on 6881 estrogen receptor (ER)-negative patients (920 events) and 23059 ER-positive patients (1333 events). All statistical tests were two-sided.We identified one new locus (rs2059614 at 11q24.2) associated with survival in ER-negative breast cancer cases (hazard ratio [HR] = 1.95, 95% confidence interval [CI] = 1.55 to 2.47, P = 1.91 x 10(-8)). Genotyping a subset of 2113 case patients, of which 300 were ER negative, provided supporting evidence for the quality of the imputation. The association in this set of case patients was stronger for the observed genotypes than for the imputed genotypes. A second locus (rs148760487 at 2q24.2) was associated at genome-wide statistical significance in initial analyses; the association was similar in ER-positive and ER-negative case patients. Here the results of genotyping suggested that the finding was less robust.This is currently the largest study investigating genetic variation associated with breast cancer survival. Our results have potential clinical implications, as they confirm that germline genotype can provide prognostic information in addition to standard tumor prognostic factors.
EVALuna2:9260

Identification of six new susceptibility loci for invasive epithelial ovarian cancer - Kuchenbaecker, Karoline B.; Ramus, Susan J.; Tyrer, Jonathan; Lee, Andrew; Shen, Howard C.; Beesley, Jonathan; Lawrenson, Kate; Mcguffog, Lesley; Healey, Sue; Lee, Janet M.; Spindler, Tassja J.; Lin, Yvonne G.; et al. (Nature Genetics, 2015)
Genome-wide association studies (GWAS) have identified 12 epithelial ovarian cancer (EOC) susceptibility alleles. The pattern of association at these loci is consistent in BRCA1 and BRCA2 mutation carriers who are at high risk of EOC. After imputation to 1000 Genomes Project data, we assessed associations of 11 million genetic variants with EOC risk from 15,437 cases unselected for family history and 30,845 controls and from 15,252 BRCA1 mutation carriers and 8,211 BRCA2 mutation carriers (3,096 with ovarian cancer), and we combined the results in a meta-analysis. This new study design yielded increased statistical power, leading to the discovery of six new EOC susceptibility loci. Variants at 1p36 (nearest gene, WNT4), 4q26 (SYNPO2), 9q34.2 (ABO) and 17q11.2 (ATAD5) were associated with EOC risk, and at 1p34.3 (RSPO1) and 6p22.1 (GPX6) variants were specifically associated with the serous EOC subtype, all with P < 5 × 10(-8). Incorporating these variants into risk assessment tools will improve clinical risk predictions for BRCA1 and BRCA2 mutation carriers.
EVALuna2:9273

Identification of ten variants associated with risk of estrogen-receptor-negative breast cancer - Milne, Roger L.; Kuchenbaecker, Karoline B.; Michailidou, Kyriaki; Beesley, Jonathan; Kar, Siddhartha; Lindstrom, Sara; Hui, Shirley; Lemacon, Audrey; Soucy, Penny; Dennis, Joe; Jiang, Xia; Rostamianfar, Asha; et al. (Nature Genetics, 2017)
Most common breast cancer susceptibility variants have been identified through genome-wide association studies (GWAS) of predominantly estrogen receptor (ER)-positive disease. We conducted a GWAS using 21,468 ER-negative cases and 100,594 controls combined with 18,908 BRCA1 mutation carriers (9,414 with breast cancer), all of European origin. We identified independent associations at P < 5 × 10-8 with ten variants at nine new loci. At P < 0.05, we replicated associations with 10 of 11 variants previously reported in ER-negative disease or BRCA1 mutation carrier GWAS and observed consistent associations with ER-negative disease for 105 susceptibility variants identified by other studies. These 125 variants explain approximately 16% of the familial risk of this breast cancer subtype. There was high genetic correlation (0.72) between risk of ER-negative breast cancer and breast cancer risk for BRCA1 mutation carriers. These findings may lead to improved risk prediction and inform further fine-mapping and functional work to better understand the biological basis of ER-negative breast cancer.
EVALuna2:9391

Identification of Two Genetic Loci Associated with Leukopenia after Chemotherapy in Patients with Breast Cancer - Fasching, Peter; Liu, Duan; Scully, Steve; Ingle, James N.; Lyra, Paulo C.; Rack, Brigitte; Hein, Alexander; Ekici, Arif Bülent; Reis, André; Schneeweiss, Andreas; Tesch, Hans; Fehm, Tanja N.; et al. (Clinical Cancer Research, 2022)
Purpose: To identify molecular predictors of grade 3/4 neutropenic or leukopenic events (NLE) after chemotherapy using a genome-wide association study (GWAS). Experimental Design: A GWAS was performed on patients in the phase III chemotherapy study SUCCESS-A (n = 3,322). Genotyping was done using the Illumina HumanOmniExpress-12v1 array. Findings were functionally validated with cell culture models and the genotypes and gene expression of possible causative genes were correlated with clinical treatment response and prognostic outcomes. Results: One locus on chromosome 16 (rs4784750; NLRC5; P = 1.56E-8) and another locus on chromosome 13 (rs16972207; TNFSF13B; P = 3.42E-8) were identified at a genome-wide significance level. Functional validation revealed that expression of these two genes is altered by genotype-dependent and chemotherapy-dependent activity of two transcription factors. Genotypes also showed an association with disease-free survival in patients with an NLE. Conclusions: Two loci in NLRC5 and TNFSF13B are associated with NLEs. The involvement of theMHCI regulator NLRC5 implies the possible involvement of immuno-oncological pathways.
CRIS-Team Scopus Importer:2022-08-19

Impact of disease progression on health-related quality of life in patients with metastatic breast cancer in the PRAEGNANT breast cancer registry - Mueller, Volkmar; Nabieva, Naiba; Häberle, Lothar; Taran, Florin-Andrei; Hartkopf, Andreas D.; Volz, Bernhard; Overkamp, Friedrich; Brandl, Anna; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; et al. (BREAST, 2018)
OBJECTIVES: Improved progression-free survival is considered as treatment goal for patients with metastatic breast cancer (MBC) since it is assumed to delay or prevent deterioration of quality of life. Aim of our analysis was to examine the influence of disease progression on health-related quality of life (HRQoL). MATERIALS AND METHODS: The PRAEGNANT study comprises a real-life registry for patients with MBC. HRQoL was assessed with the EORTC-QLQ-C30 Version 3.0 questionnaire at study entry and every 3 months thereafter. The primary endpoint was minimally important deterioration (MID) in global HRQoL score by ≥ five points between baseline and any follow-up assessment. A logistic regression model was built with MID (yes/no) at a follow-up timepoint as outcome variable and several covariates as predictors. RESULTS: In total, 329 patients were included in this analysis, with disease progression in 63 patients. Concerning the primary study aim, progression status predicted MID of global HRQoL status in addition to the other covariates. The adjusted odds ratio for the effect of progression status on MID was 2.22 (95% CI: 1.04 - 4.73). Comparisons of mean differences of QoL domains/scales yielded no differences. CONCLUSIONS: We provide evidence that disease progression in patients with metastatic breast cancer in a real-world registry has a significant negative impact on HRQoL as measured by MID of HRQoL. This study emphasizes the relevance of avoiding progression and prolonging PFS to maintain QoL.
EVALuna2:36438

Impact of fibroblast growth factor receptor 1 (FGFR1) amplification on the prognosis of breast cancer patients - Erber, Ramona; Rübner, Matthias; Davenport, Simon; Hauke, Sven; Beckmann, Matthias; Hartmann, Arndt; Häberle, Lothar; Gaß, Paul; Press, Michael F.; Fasching, Peter (Breast Cancer Research and Treatment, 2020)
Purpose: Various aberrations in the fibroblast growth factor receptor genes FGFR1, FGFR2, and FGFR3 are found in different cancers, including breast cancer (BC). This study analyzed the impact of FGFR amplification on the BC prognosis. Methods: The study included 894 BC patients. The amplification rates of FGFR1, FGFR2, and FGFR3 were evaluated on tissue microarrays using fluorescence in situ hybridization (FISH). Associations between these parameters and prognosis were analyzed using multivariate Cox regression analyses. Results: FGFR1 FISH was assessable in 503 samples, FGFR2 FISH in 447, and FGFR3 FISH in 562. The FGFR1 amplification rate was 6.6% (n = 33). Increased FGFR2 copy numbers were seen in 0.9% (n = 4); only one patient had FGFR3 amplification (0.2%). Most patients with FGFR1 amplification had luminal B-like tumors (69.7%, n = 23); only 32.6% (n = 153) of patients without FGFR1 amplification had luminal B-like BC. Other patient and tumor characteristics appeared similar between these two groups. Observed outcome differences between BC patients with and without FGFR1 amplification did not achieve statistical significance; however, there was a trend toward poorer distant metastasis-free survival in BC patients with FGFR1 amplification (HR = 2.08; 95% CI 0.98 to 4.39, P = 0.05). Conclusion: FGFR1 amplification occurs most frequently in patients with luminal B-like BC. The study showed a nonsignificant correlation with the prognosis, probably due to the small sample size. Further research is therefore needed to address the role of FGFR1 amplifications in early BC patients. FGFR2 and FGFR3 amplifications are rare in patients with primary BC.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Amplification; Breast cancer; FGFR1; FGFR2; FGFR3; FISH; Prognosis

IMPAIRED GENE-EXPRESSION AND EPIGENETIC REGULATION OF RETINOIC ACID RECEPTOR RESPONDER 1 IN PREECLAMPSIA AND CHORIOCARCINOMA - Hübner, Hanna; Fahlbusch, Fabian B.; Strissel, Pamela; Strick, Reiner; Wachter, David; Beckmann, Matthias; Rübner, Matthias (2016)
EVALuna2:32961

Implementation and Feasibility of Electronic Patient-Reported Outcome (ePRO) Data Entry in the PRAEGNANT Real-Time Advanced and Metastatic Breast Cancer Registry - Wallwiener, Markus; Heindl, Felix; Brucker, Sara Y.; Taran, Florin-Andrei; Hartkopf, Andreas; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Patient-reported outcomes (PROs) have been incorporated into clinical trials for many symptoms and medical conditions. A transition from paper-based capture of PROs to electronic PROs (ePROs) has recently started. This study reports on the feasibility of ePRO assessment in a prospective registry including molecular data for patients with advanced breast cancer.As part of the PRAEGNANT network, patients were invited by clinical trial staff, physicians, and nurses to complete three standardized Internet-based questionnaires (EQ 5D 5 L, CES-D and IPAQ). Feasibility was assessed by the staff members who assigned the user accounts by the patients. The completeness of the questionnaires was also assessed.Fifteen of 17 patients who were asked agreed to participate to complete the PRO questionnaires (EQ-5D-5L and CES-D). However, the IPAQ (physical activity) questionnaire was only validly completed by 9 patients. Feasibility was ranked better by the physicians and dedicated clinical trial staff than by the nursing staff.Incorporating ePRO questionnaires into an advanced breast cancer registry is feasible, and no major hurdles were reported. Involving stakeholders from the start, the application is tailored to the capacities and abilities of both patients and clinical staff. The patients' compliance was better with some questionnaires, but others may present difficulties.
EVALuna2:176

Implementation and update of guideline-derived quality indicators for cervical cancer in gynecological cancer centers certified by the German Cancer Society (DKG) - Stübs, Frederik; Beckmann, Matthias; Fehm, Tanja; Dannecker, Christian; Follmann, Markus; Langer, Thomas; Wesselmann, Simone (Journal of Cancer Research and Clinical Oncology, 2023)
Purpose: In 2008, the first gynecological cancer centres were certified by the German Cancer Society (DKG). Guideline-based quality Indicators (QIs) are a core element of the certification process. These QI are defined to assess the quality of care within the centres and can serve to measure the implementation of guideline recommendation. This article aims to give an overview of the developing and updating process of guideline based-QIs for women with cervical cancer and presents the QI results from the certified gynaecological cancer centres. Methods: The QIs are derived in a multiple step review process and then implemented in the certification data sheet of the certified centres. The first set of QIs created in 2014 was revised in the update process of the S3-Guideline in 2020. QIs are based on strong recommendations of the evidence-based “Guideline for patients with Cervical Carcinoma” (registry-number: 032/033OL). Results: In total, there are nine guideline-based QIs for cervical cancer. Four QIs are part of the certification process. In the treatment year 2020, 3.522 cases of cervical cancer were treated in 169 centers. The target values for the four QIs were met in at least 95% of the certified centers. In the guideline update in 2020, a new QI was added to the set of QIs “Complete pathological report on conization findings” and the QI “Exenteration” was removed. Conclusions: QIs derived from strong recommendations of a guideline are an important tool to make essential parts of patient’s care measurable and enable the centers to draw consequences in process optimization. Over the years, the number of certified centers has grown, and the quality was improved. The certification systems is under constant revision to further improve patient’s care in the future, based on the results of the QI re-evaluation.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Certified gynecological cancer centers; Cervical cancer; Quality indicator; S3-guideline

Implementation of CDK4/6 Inhibitors and its Influence on the Treatment Landscape of Advanced Breast Cancer Patients – Data from the Real-World Registry PRAEGNANT - Engler, Tobias; Fasching, Peter; Lueftner, Diana; Hartkopf, Andreas D.; Mueller, Volkmar; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Wallwiener, Markus; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Background Comprehensive data from prospective clinical trials have led to a high level of evidence establishing CDK4/6 inhibitors in combination with endocrine treatment (CDK4/6i + ET) as a standard for the treatment of HER2-negative, hormone receptor-positive (HER2- HR+) breast cancer patients in the first-line advanced therapy setting. Data on patient populations that have been treated in the real-world setting may provide an insight into changes of patient characteristics and prognosis over time. Methods The data were extracted from the prospective real-world registry PRAEGNANT (NCT02338167). Patients had to have HER2- HR+ advanced breast cancer in the first-line metastatic setting. The chosen therapies were described as well as progression-free survival (PFS) and overall survival (OS) in relation to the given therapies and time periods during which they were indicated. Results CDK4/6 inhibitors have been rapidly implemented since their introduction in November 2016. In recent years (2018-2022), about 70-80% of the patient population have been treated with CDK4/6 inhibitors, while endocrine monotherapy was given to about 10% and chemotherapy to about 15% of all patients. The prognosis was worst in patients treated with chemotherapy. Recently, mainly patients with a good prognosis are being treated with endocrine monotherapy, and patients who are treated with chemotherapy have an unfavorable prognosis. The PFS and OS of patients treated with CDK4/6i + ET have remained similar over time despite changes in patient characteristics. Conclusion A treatment with CDK4/6i + ET has rapidly become the therapy standard for patients in the first-line advanced breast cancer setting. After the implementation of CDK4/6i + ET, endocrine monotherapy is only given to patients with a very favorable prognosis, while chemotherapy is provided to patients with a rather unfavorable prognosis. These changes in patient characteristics did not seem to influence the prognosis of patients treated with CDK4/6i + ET.
CRIS-Team Scopus Importer:2022-07-22
Keywords: advanced breast cancer; CDK4/6 inhibitor; chemotherapy; endocrine treatment; real world data

Implementation of machine learning into clinical breast MRI: Potential for objective and accurate decision-making in suspicious breast masses - Ellmann, Stephan; Wenkel, Evelyn; Dietzel, Matthias; Bielowski, Christian; Vesal, Sulaiman; Maier, Andreas; Hammon, Matthias; Janka, Rolf Matthias; Fasching, Peter; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Uder, Michael; et al. (PLoS ONE, 2020)
We investigated whether the integration of machine learning (ML) into MRI interpretation can provide accurate decision rules for the management of suspicious breast masses. A total of 173 consecutive patients with suspicious breast masses upon complementary assessment (BI-RADS IV/V: n = 100/76) received standardized breast MRI prior to histological verification. MRI findings were independently assessed by two observers (R1/R2: 5 years of experience/no experience in breast MRI) using six (semi-)quantitative imaging parameters. Interobserver variability was studied by ICC (intraclass correlation coefficient). A polynomial kernel function support vector machine was trained to differentiate between benign and malignant lesions based on the six imaging parameters and patient age. Ten-fold cross-validation was applied to prevent overfitting. Overall diagnostic accuracy and decision rules (rule-out criteria) to accurately exclude malignancy were evaluated. Results were integrated into a web application and published online. Malignant lesions were present in 107 patients (60.8%). Imaging features showed excellent interobserver variability (ICC: 0.81–0.98) with variable diagnostic accuracy (AUC: 0.65–0.82). Overall performance of the ML algorithm was high (AUC = 90.1%; BI-RADS IV: AUC = 91.6%). The ML algorithm provided decision rules to accurately rule-out malignancy with a false negative rate <1% in 31.3% of the BI-RADS IV cases. Thus, integration of ML into MRI interpretation can provide objective and accurate decision rules for the management of suspicious breast masses, and could help to reduce the number of potentially unnecessary biopsies.<br

Improved Bladder Tumor RNA Isolation from Archived Tissues Using Methylene Blue for Normalization, Multiplex RNA Hybridization, Sequencing and Subtyping - Köhler, Stefanie; Brandl, Lisa; Strissel, Pamela; Glossner, Laura; Ekici, Arif Bülent; Angeloni, Miriam; Ferrazzi, Fulvia; Bahlinger, Veronika; Hartmann, Arndt; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner (International Journal of Molecular Sciences, 2022)
Methylene blue (MB) is a dye used for histology with clinical importance and intercalates into nucleic acids. After MB staining of formalin fixed paraffin embedded (FFPE) muscle invasive bladder cancer (MIBC) and normal urothelium, specific regions could be microdissected. It is not known if MB influences RNA used for gene expression studies. Therefore, we analyzed MIBC using five different RNA isolation methods comparing patient matched FFPE and fresh frozen (FF) tissues pre-stained with or without MB. We demonstrate a positive impact of MB on RNA integrity with FF tissues using real time PCR with no interference of its chemical properties. FFPE tissues showed no improvement of RNA integrity, which we propose is due to formalin induced nucleotide crosslinks. Using direct multiplex RNA hybridization the best genes for normalization of MIBC and control tissues were identified from 34 reference genes. In addition, 5SrRNA and 5.8SrRNA were distinctive reference genes detecting <200 bp fragments important for mRNA analyses. Using these normalized RNAs from MB stained MIBC and applying multiplex RNA hybridization and mRNA sequencing, a minimal gene expression panel precisely identified luminal and basal MIBC tumor subtypes, important for diagnosis, prognosis and chemotherapy response.
CRIS-Team WoS Importer:2022-09-30

Improved HER2 Tumor Segmentation with Subtype Balancing Using Deep Generative Networks - Öttl, Mathias; Steenpaß, Jana; Rübner, Matthias; Geppert, Carol-Immanuel; Qiu, Jingna; Wilm, Frauke; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Maier, Andreas; Erber, Ramona; Breininger, Katharina (Proceedings - International Symposium on Biomedical Imaging, 2023)
Tumor segmentation in histopathology images is often complicated by its composition of different histological subtypes and class imbalance. Oversampling subtypes with low prevalence features is not a satisfactory solution since it eventually leads to overfitting. We propose to create synthetic images with semantically-conditioned deep generative networks and to combine subtype-balanced synthetic images with the original dataset to achieve better segmentation performance. We show the suitability of Generative Adversarial Networks (GANs) and especially diffusion models to create realistic images based on subtype-conditioning for the use case of HER2-stained histopathology. Additionally, we show the capability of diffusion models to conditionally inpaint HER2 tumor areas with modified subtypes. Combining the original dataset with the same amount of diffusion-generated images increased the tumor Dice score from 0.833 to 0.854 and almost halved the variance between the HER2 subtype recalls. These results create the basis for more reliable automatic HER2 analysis with lower performance variance between individual HER2 subtypes.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Diffusion Models; Generative Models; HER2; Histopathology; Segmentation; Subtypes

Improving the Quality of Care for Cancer Patients through Oncological Second Opinions in a Comprehensive Cancer Center: Feasibility of Patient-Initiated Second Opinions through a Health-Insurance Service Point - Schulmeyer, Carla; Beckmann, Matthias; Fasching, Peter; Häberle, Lothar; Golcher, Henriette; Kunath, Frank; Wullich, Bernd; Emons, Julius (Diagnostics, 2023)
Background: To improve the quality and cost-effectiveness of care, cancer patients can obtain a second medical opinion on their treatment. Validation of the diagnostic procedure (e.g., imaging), diagnosis, and treatment recommendation allows oncological therapy to be applied in a more targeted way, optimizing interdisciplinary care. This study describes patients who received second opinions at the Comprehensive Cancer Center for Erlangen–Nuremberg metropolitan area in Germany over a 6-year period, as well as the amount of time spent on second-opinion counseling. Methods: This prospective, descriptive, single-center observational study included 584 male and female cancer patients undergoing gynecological, urologic, or general surgery who sought a second medical opinion. The extent to which the first opinion complied with standard guidelines was assessed solely descriptively. Results: The first opinion was in accordance with the guidelines and complete in 54.5% of the patients, and guideline compliant but incomplete in 13.2%. The median time taken to form a second opinion was 225 min, and the cancer information service was contacted by patients an average of eight times. Conclusions: The initial opinion was guideline compliant and complete in every second case. Without a second opinion, the remaining patients would have been denied a guideline-compliant treatment recommendation. Obtaining a second opinion gives patients an opportunity to receive a guideline-compliant treatment recommendation and enables them to benefit from newer, individualized therapeutic approaches in clinical trials. Establishing patient-initiated second opinions via central contact points appears to be a feasible option for improving guideline compliance.
CRIS-Team Scopus Importer:2023-11-24
Keywords: gastrointestinal cancer; gynecologic cancer; sarcoma; second medical opinion; urologic cancer

Incorporating progesterone receptor expression into the PREDICT breast prognostic model - Grootes, Isabelle; Keeman, Renske; Blows, Fiona M.; Milne, Roger L.; Giles, Graham G.; Swerdlow, Anthony J.; Fasching, Peter A.; Abubakar, Mustapha; Andrulis, Irene L.; Anton-Culver, Hoda; Beckmann, Matthias; Blomqvist, Carl; et al. (European Journal of Cancer, 2022)
Background: Predict Breast (www.predict.nhs.uk) is an online prognostication and treatment benefit tool for early invasive breast cancer. The aim of this study was to incorporate the prognostic effect of progesterone receptor (PR) status into a new version of PREDICT and to compare its performance to the current version (2.2).
CRIS-Team WoS Importer:2022-11-25

Individual dynamics of uterine natural killer cells in natural and stimulated cycles monitored using a new endometrial dating method - Alfer, Joachim; Fattahi, Amir; Bleisinger, Nathalie; Antoniadis, Sophia; Krieg, Jurgen; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Popovici, Roxana M.; Tremellen, Kelton (American Journal of Reproductive Immunology, 2022)
Problem It is important to evaluate the dynamics of uterine natural killer (uNK) cells in hormone replacement therapy (HRT) cycles, given their potential role in implantation and the common usage of HRT cycles with in vitro fertilization (IVF). Method of study A total of 132 subfertile patients were evaluated during the secretory phase of either natural ovulation (OV) or HRT cycles, with two biopsies taken on approximately days 5 and 10 after ovulation/progesterone administration in a single menstrual cycle. Immunohistochemical Personal Endometrial Maturation Analysis (PEMA) was used to better quantify secretory-phase endometrial development, in combination with subsequent evaluation of uNK cell density. Results uNK cell density increased rapidly from the early to mid-secretory phase, with mean uNK densities of 113 and 117 per mm(2) in first biopsies and 315 and 387 per mm(2) in second biopsies for OV and HRT cycles, respectively. After reassessment of endometrial development with PEMA, the first and second biopsies in HRT and OV cycles were histologically dated to developmental ranges between days 15-20 (first biopsy) and days 19-25 (second biopsy). Conclusion Subfertile women showed variable endometrial development in PEMA assessment, with uNK cell density correlating with the dating results. Overall, comparable levels of uNK cell density were observed in OV and HRT cycles. Importantly, uNK cell density depends on the histological maturation stage, with similar low coefficients of determination. This observation suggests that aberrant uNK cell results more likely reflect displaced endometrial maturation, rather than an intrinsic anomaly in uNK cell trafficking.
CRIS-Team WoS Importer:2022-09-30

Induction of Labour: Change of Method and its Effects - Kehl, Sven; Weiss, C.; Dammer, U.; Raabe, E.; Burghaus, Stefanie; Heimrich, J.; Hackl, J.; Winkler, Michael; Beckmann, Matthias; Faschingbauer, Florian (Geburtshilfe und Frauenheilkunde, 2015)
Aim: The combination of mechanical and drug procedures for the induction of labour seems to be beneficial. Accordingly, the normal procedure in clinical routine has been changed and induction of labour by means of a balloon catheter has been implemented. The aim of this study was to find out if this procedural change has resulted in a more effective induction of labour. Materials and Method: In this historical cohort study 230 inductions of labour at term in the year 2012 were compared with 291 inductions of labour in the year 2013, all at the University of Erlangen Perinatal Centre. Exclusion criteria were, among others, a multiple pregnancy, a premature rupture of membranes and a prior Caesarean section. In 2012 births were induced solely by use of the drugs dinoprostone and misoprostol, in 2013 not only with misoprostol but also mainly by use of a balloon catheter. The primary target parameter was the rate of failed labour inductions, defined as "no birth within 72 hours". Results: Altogether 521 inductions of labour were analysed. The rate of failed inductions of labour could be reduced by the changes in induction method (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204). Furthermore, the rate of primary Caesarean sections due to failed induction of labour (5.7 vs. 1.4 %, p = 0.0064), that of the observation of green amniotic fluid (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204) and of infantile infections (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204) were all reduced as well. Conclusion: The routine use of a balloon catheter for induction of labour has markedly improved the procedure. There were fewer failed labour inductions and fewer Caesarean sections due to failed induction of labour.
EVALuna2:17598

Induction of Labour In Growth Restricted and Small for Gestational Age Fetuses - A Historical Cohort Study - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Berlit, Sebastian; Grosse-Steffen, Thomas; Faschingbauer, Florian; Suetterlin, Marc; Beckmann, Matthias; Schneider, Michael (Zeitschrift für Geburtshilfe und Neonatologie, 2019)
Purpose Induction of labour for small-for-gestational-age (SGA) foetus or intrauterine growth restriction (IUGR) is common, but data are limited. The aim of this trial was therefore to compare labour induction for SGA/IUGR with cases with normal fetal growth beyond the 10th percentile.
CRIS-Team WoS Importer:2019-03-15

Induction of Labour in Growth Restricted and Small for Gestational Age Foetuses - A Historical Cohort Study. - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Berlit, Sebastian; Grosse-Steffen, Thomas; Faschingbauer, Florian; Suetterlin, Marc; Beckmann, Matthias; Schneider, Michael (Geburtshilfe und Frauenheilkunde, 2019)
Purpose Induction of labour for small-for-gestational-age (SGA) foetus or intrauterine growth restriction (IUGR) is common, but data are limited. The aim of this study was therefore to compare labour induction for SGA/IUGR with cases of normal foetal growth above the 10th percentile. Material and Methods This historical multicentre cohort study included singleton pregnancies at term. Labour induction for SGA/IUGR (IUGR group) was compared with cases of foetal growth above the 10th percentile (control group). Primary outcome measure was caesarean section rate. Results The caesarean section rate was not different between the 2 groups (27.0 vs. 26.2%, p = 0.9154). In the IUGR group, abnormal CTG was more common (30.8 vs. 21.9%, p = 0.0214), and foetal blood analysis was done more often (2.5 vs. 0.5%, p = 0.0261). There were more postpartum transfers to the NICU in the IUGR group (40.0 vs. 12.8%, p < 0.0001), too. Conclusion Induction of labour for foetal growth restriction was not associated with an increased rate of caesarean section.
EVALuna2:212315

Induction of Labour in Nulliparous Women Beyond Term in a Low-Risk Population - Pretscher, Jutta; Weiss, Christel; Dammer, Ulf; Stumpfe, Florian; Faschingbauer, Florian; Beckmann, Matthias; Kehl, Sven (Zeitschrift für Geburtshilfe und Neonatologie, 2019)
Purpose To evaluate the influence of gestational age on induction of labour in nulliparous women.
CRIS-Team WoS Importer:2019-03-15

Induction of labour with sequential double-balloon catheter and oral misoprostol versus oral misoprostol alone in obese women - Kehl, Sven; Born, Tilman; Weiss, Christel; Faschingbauer, Florian; Pretscher, Jutta; Beckmann, Matthias; Sütterlin, Marc; Dammer, Ulf (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2019)
Objective: To evaluate the efficacy of induction of labour in obese women using sequential double-balloon catheter and oral misoprostol in comparison with oral misoprostol alone. Study design: In this cohort study, 400 pregnant women with BMI higher than 35 kg/m2 undergoing labour induction at term were included. Induction of labour with a double-balloon catheter and, if necessary, sequential oral misoprostol (n = 216) was compared to oral misoprostol alone (n = 184). The primary outcome measure was the caesarean section rate. Secondary outcome parameters were, among others, the induction-to-delivery-interval, the rate of vaginal delivery within 24 and 48 h as well as fetal outcome parameters. Results: The caesarean section rate was significantly lower in the group with sequential use of double-balloon catheter and oral misoprostol (27.6% versus 37.5%, p = 0.0345). After stratification for parity this reduction was seen especially in nulliparous (38.6% versus 56.9%, p = 0.0039). The rate of abnormal CTG was significantly lower as well (19.9% versus 30.4%, p = 0.0150), particularly in nulliparous (25.9% versus 40.4%, p = 0.0138). Uni- and multivariable analyzes showed that the caesarean section rate was significantly influenced by the method of induction of labour (p = 0.0026), parity (p < 0.0001) and Bishop score (p = 0.0425). Conclusion: In obese women, induction of labour with sequential use of double-balloon catheter and oral misoprostol is associated with significantly more normal vaginal deliveries and less caesarean sections.
EVALuna2:212316

Influence of body mass index on induction of labor: A historical cohort study - Dammer, Ulf; Bogner, Roswitha; Weiss, Christel; Faschingbauer, Florian; Pretscher, Jutta; Beckmann, Matthias; Suetterlin, Marc; Kehl, Sven (Journal of Obstetrics and Gynaecology Research, 2018)
AIM: We aimed to determine the influence of body mass index (BMI) on induction of labor. METHODS: In this historical multicenter cohort study, 2122 labor inductions were analyzed. Women were divided into four groups according to their body mass index (BMI): BMI < 30 (normal group [NG]), 30 ≤ BMI < 35 (group 1 [G1]), 35 ≤ BMI < 40 (group 2 [G2]), and BMI ≥ 40 (group 3 [G3]). The primary outcome measure was the induction-to-delivery interval. The secondary outcome parameter was, among others, the rate of cesarean section. RESULTS: A total of 1113 inductions of labor were analyzed in the NG, 610 in G1, 239 in G2, and 160 in G3. The induction-to-delivery interval was shorter in the NG compared to G1 (mean values 1550 min vs 1669 min, P = 0.0406), G2 (1745 min, P = 0.0294), and G3 (1899 min, P = 0.0008). The cesarean section rate was significantly higher in G1-G3 (G1: 30.8%, P < 0.001; G2: 30.5%, P < 0.0067; G3: 42.5%, P < 0.0001) compared to the NG (21.8%). There were more vaginal deliveries within 48 h in the NG (84%) compared to G1-G3 (78%, P = 0.0186; 75%, P = 0.0049; 75%, P = 0.0329). However, these findings could mainly be seen in nulliparous women when stratifying for parity. Multivariable analysis showed that high BMI increased the induction-to-delivery interval whereas high parity, gestational age, and Bishop score decreased it. CONCLUSION: An increased body mass index has a negative impact on induction of labor at term, especially in nulliparous women.
EVALuna2:209950

Influence of Family History of Breast or Ovarian Cancer on Pathological Complete Response and Long-Term Prognosis in Breast Cancer Patients Treated with Neoadjuvant Chemotherapy - Wunderle, Marius; Häberle, Lothar; Hein, Alexander; Jud, Sebastian; Lux, Michael P.; Hack, Carolin; Emons, Julius; Heindl, Felix; Nabieva, Naiba; Löhberg, Christian; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; et al. (Breast Care, 2020)
Purpose: In breast cancer, a pathological complete response (pCR) has been described as generally resulting in a favorable prognosis. However, there are subgroups, such as patients with a mutation in BRCA1 or BRCA2,in which the effect of pCR on the prognosis is suspected to be weaker. Patients with a family history of breast and/or ovarian cancer may therefore react differently in relation to pCR and prognosis, and this is investigated in this study. Patients and Methods: Breast cancer patients were identified from a clinical breast cancer registry. The study subjects had been treated with neoadjuvant chemotherapy from 2001 to 2018 and their pathological and clinical information as well as medical family history were available. They were considered to have a positive family history if they had at least 1 first-degree relative with breast and/or ovarian cancer. Multivariate logistic regression analyses were performed to study the association between family history, pCR (ypT0; ypN0), and disease-free survival (DFS). Results: Of 1,480 patients, 228 (15.4%) had a positive family history. The pCR rates were 24.9% in all patients, and 24.4% and 27.6% in those without/with a family history, respectively. Family history was not associated with a higher pCR rate (adjusted odds ratio [OR] 1.23; 95% confidence interval [CI] 0.85-1.76; p = 0.27) or a different disease-free survival (DFS; adjusted hazard ratio [HR] 1.15; 95% CI 0.88-1.52; p = 0.30). pCR did not affect the prognosis differently in relation to family history. Conclusions: In this retrospective analysis, family history was not associated with pCR and DFS. pCR improved survival, independently of family history.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Breast cancer; Family history; Neoadjuvant chemotherapy; Ovarian cancer; Pathological complete response; Prognosis

Influence of labor on direct and indirect determinants of placental 11beta-hydroxysteroid dehydrogenase activity - Hübner, Hanna; Heussner, Kirsten; Rübner, Matthias; Schmid, Matthias; Nadal, Jennifer; Wölfle, Joachim; Hartner, Andrea; Menendez-Castro, Carlos; Rauh, Manfred; Beckmann, Matthias; Kehl, Sven; Fahlbusch, Fabian (Archives of Gynecology and Obstetrics, 2020)
Purpose: Labor is a complex process involving multiple para-, auto- and endocrine cascades. The interaction of cortisol, corticotropin-releasing hormone (CRH) and progesterone is essential. The action of cortisol on the human feto-placental unit is regulated by 11beta-hydroxysteroid dehydrogenase type 2 (11β-HSD2/HSD11B2) that converts cortisol into inactive cortisone. The majority of studies on the assessment of placental 11β-HSD2 function determined indirect activity parameters. It remains elusive if indirect measurements correlate with enzymatic function and if these parameters are affected by potential confounders (e.g., mode of delivery). Thus, we compared determinants of indirect 11β-HSD2 tissue activity with its direct enzymatic turnover rate in placental samples from spontaneous births and cesarean (C)-sections. Methods: Using LC–MS/MS, we determined CRH, cortisol, cortisone, progesterone and 17-hydroxy(OH)-progesterone in human term placentas (spontaneous birth vs. C-section, n = 5 each) and measured the enzymatic glucocorticoid conversion rates in placental microsomes. Expression of HSD11B1, 2 and CRH was determined via qRT-PCR in the same samples. Results: Cortisol–cortisone ratio correlated with direct microsomal enzymatic turnover. While this observation seemed independent of sampling site, a strong influence of mode of delivery on tissue steroids was observed. The mRNA expression of HSD11B2 correlated with indirect and direct cortisol turnover rates in C-section placentas only. In contrast to C-sections, CRH, cortisol and cortisone levels were significantly increased in placental samples following spontaneous birth. Conclusion: Labor involves a series of complex hormonal processes including activation of placental CRH and glucocorticoid metabolism. This has to be taken into account when selecting human cohorts for comparative analysis of placental steroids.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 11beta-hydroxysteroid dehydrogenase; CRH; LC–MS/MS; Mode of delivery; Placenta

Influence of mindfulness-based Stress Reduction on Patients with Endometriosis in a randomized Cohort Study - Antoniadis, Sophia; Burghaus, Stefanie; Becker, Karina; Beckmann, Matthias; Hack, Caroline (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Influence of Patient and Hospital Characteristics on the Performance of Direct Reconstruction after Mastectomy - Hartrampf, J.; Ansmann, L.; Wesselmann, S.; Beckmann, Matthias; Pfaff, H.; Kowalski, C. (Geburtshilfe und Frauenheilkunde, 2014)
Aim: International studies have shown that the performance of a direct (or immediate) reconstruction (DR) after mastectomy is associated with patient (e.g., socio-economic status, insurance status, age) and hospital (number of cases, teaching status) characteristics. The present article addresses the question if such relationships also exist in Germany. Material and Methods: The results of a nationwide questionnaire to the patients of certified breast cancer centres were coupled with the clinical features of the patients and the characteristics of the hospital. Predictors for receiving a DR (vs. delayed or no reconstruction) were estimated by means of a logistic multilevel model for a sample of 1165 patients from 105 certified locations. Results: Substantial differences between the treating hospitals were found (intraclass correlation coefficient null model: 0.195) which can in part be explained by the total model (total model: 0.169). Patients with the following features are more likely to receive a DR: younger age, private health insurance, secondary school leaving certificate (vs. primary school leaving certificate), lower stage and acquisition of more information about reconstruction. ASA and partnership status are not statistically significantly related with DR. DR is more likely to be performed in hospitals with higher caseload of patients with primary breast cancer. Teaching status, operations per surgeon and urbanity of the location are not related to receiving a DR. Conclusions: Non-clinical features of the patients and the primary case number are associated with the performance of a DR, this poses questions concerning reasons and the equality of health care.
EVALuna2:17452

Influence of patient and tumor characteristics on early therapy persistence with letrozole in postmenopausal women with early breast cancer: results of the prospective Evaluate-TM study with 3941 patients - Nabieva, Naiba; Kellner, S.; Fehm, T.; Häberle, Lothar; De Waal, J.; Rezai, M.; Baier, B.; Baake, G.; Kolberg, H. -C.; Guggenberger, M.; Warm, M.; Harbeck, N.; et al. (Annals of Oncology, 2018)
Patients' compliance and persistence with endocrine treatment has a significant effect on the prognosis in early breast cancer (EBC). The purpose of this analysis was to identify possible reasons for non-persistence, defined as premature cessation of therapy, on the basis of patient and tumor characteristics in individuals receiving adjuvant treatment with letrozole.The EvAluate-TM study is a prospective, multicenter, noninterventional study in which treatment with the aromatase inhibitor letrozole was evaluated in postmenopausal women with hormone receptor-positive EBC in the early therapy phase. Treatment persistence was evaluated at two pre-specified study visits after 6 and 12 months. As a measure of early therapy persistence the time from the start to the end of treatment (TTEOT) was analyzed. Cox regression analyses were carried out to identify patient characteristics and tumor characteristics predicting TTEOT.Out of the total population of 3941 patients with EBC, 540 (13.7%) events involving treatment cessation unrelated to disease progression were observed. This was due to drug-related toxicity in the majority of cases (73.5%). Persistence rates were 92.2%, 86.9%, and 86.3% after 6, 12, and 15 months, respectively. The main factors influencing premature treatment discontinuation were older age [hazard ratio (HR) 1.02/year], comorbidities (HR 1.06 per comorbidity), low body mass index, and lower tumor grade (HR 0.85 per grade unit).These results support the view that older, multimorbid patients with low tumor grade and low body mass index are at the greatest risk for treatment discontinuation and might benefit from compliance and support programs.
EVALuna2:51618

Influence of patient and tumor characteristics on therapy persistence with letrozole in postmenopausal women with advanced breast cancer: results of the prospective observational EvAluate-TM study - Wallwiener, Markus; Nabieva, Naiba; Feisst, Manuel; Fehm, Tanja; De Waal, Johann; Rezai, Mahdi; Baier, Bernd; Baake, Gerold; Kolberg, Hans-Christian; Guggenberger, Martin; Warm, Mathias; Harbeck, Nadia; et al. (BMC Cancer, 2019)
BackgroundTreatment of postmenopausal, hormone receptor-positive metastatic breast cancer (MBC) patients varies despite clear therapy guidelines, favoring endocrine treatment (ET). Aim of this study was to analyze persistence of palliative aromatase inhibitor (AI) monotherapy in MBC patients.MethodsEvAluate-TM is a prospective, multicenter, noninterventional study to evaluate treatment with letrozole in postmenopausal women with hormone receptor-positive breast cancer. To assess therapy persistence, defined as the time from therapy start to the end of the therapy (TTEOT), two pre-specified study visits took place after 6 and 12months. Competing risk survival analyses were performed to identify patient and tumor characteristics that predict TTEOT.ResultsOut of 200 patients, 66 patients terminated treatment prematurely, 26 (13%) of them due to causes other than disease progression. Persistence rate for reasons other than progression at 12months was 77.7%. Persistence was lower in patients who reported any adverse event (AE) in the first 30days of ET (89.5% with no AE and 56% with AE). Furthermore, patients had a lower persistence if they reported compliance problems in the past before letrozole treatment.ConclusionsDespite suffering from a life-threatening disease, AEs of an AI will result in a relevant number of treatment terminations that are not related to progression. Some subgroups of patients have very low persistence rates. Especially with regard to novel endocrine combination therapies, these data imply that some groups of patients will need special attention to guide them through the therapy process.Trial registrationClinical Trials Number: CFEM345DDE19
CRIS-Team WoS Importer:2019-07-09

Influence of Preeclampsia on Induction of Labor at Term: A Cohort Study - Pretscher, Jutta; Weiss, Christel; Dammer, Ulf; Stumpfe, Florian; Faschingbauer, Florian; Beckmann, Matthias; Kehl, Sven (In Vivo, 2020)
Background/Aim: Even though vaginal delivery is a feasible option in patients with preeclampsia, the cesarean section rate in those patients is high. The aim of this study was to evaluate the influence of preeclampsia on induction of labor at term. Patients and Methods: This historical cohort study analyzed inductions of labor in women at term having preeclampsia versus women who were induced due to other reasons. The primary outcome measure was the cesarean section rate. Results: The cesarean section rate was higher in the preeclampsia group for both nulliparous and multiparous women after induction of labor but failed to reach statistical significane. The induction-to-delivery interval was longer in nulliparous women and the rate of vaginal birth within 48 h was lower in the nulliparous patiens with preeclampsia. However, the impact of preeclampsia on the cesarean section rate was not significant in the multivariable analysis following adjustment for BMI and parity. Conclusion: Preeclampsia at term did not influence the cesarean section rate in nulliparous and parous women when labor was induced.
CRIS-Team WoS Importer:2020-05-22

Influence of side-effects on early therapy persistence with letrozole in post-menopausal patients with early breast cancer: Results of the prospective EvAluate-TM study - Nabieva, Naiba; Fehm, T.; Häberle, Lothar; De Waal, J.; Rezai, M.; Baier, B.; Baake, G.; Kolberg, H. -C.; Guggenberger, M.; Warm, M.; Harbeck, N.; Wuerstlein, R.; et al. (European Journal of Cancer, 2018)
Endocrine treatment (ET) with an aromatase inhibitor (AI) is the treatment of choice in post-menopausal patients with hormone receptor-positive early breast cancer (EBC). However, adverse events (AEs) often lead to treatment discontinuation. This analysis aimed to identify side-effects that lead to patients failing to persist with letrozole treatment.Post-menopausal hormone receptor-positive EBC patients starting ET with letrozole were enroled in EvAluate-TM, a non-interventional study. Information regarding treatment compliance and persistence was gathered in months 6 and 12. Persistence was defined as the time from 30 d after the start to the end of treatment. The influence on persistence of musculoskeletal syndrome, menopausal disorder, sleep disorder and other AEs within the first 30 d was analysed using Cox regression analyses.Among 3887 patients analysed, the persistence rate after 12 months was >85%. In all, 568 patients (14.6%) discontinued the treatment, 358 of whom (63.0%) did so only because of side-effects. The main AEs influencing persistence were musculoskeletal symptoms (hazard ratio [HR] 2.55; 95% confidence interval [CI], 1.90-3.42), sleep disorders (HR 1.95; 95% CI, 1.41-2.70) and other AEs (HR 2.03; 95% CI, 1.51-2.73). Menopausal disorder was not associated with non-persistence (HR 1.17; 95% CI, 0.74-1.84).These results suggest that side-effects of AIs such as musculoskeletal syndrome and sleep disorder lead to ET discontinuation within the first treatment year in significant numbers of EBC patients. Compliance programmes adapted for subgroups that are at risk for early non-persistence might help to ensure the recommended therapy duration.CFEM345DDE19.
EVALuna2:51279

Influence of Sonographic Fetal Weight Estimation Inaccuracies in Macrosomia on Perinatal Outcome - Pretscher, Jutta; Kehl, Sven; Stelzl, Patrick; Stumpfe, Florian; Mayr, Andreas; Schmid, Matthias; Staerk, Christian; Schild, Ralf; Beckmann, Matthias; Faschingbauer, Florian (Ultraschall in der Medizin, 2020)
Objective To evaluate the influence of inaccurate sonographic fetal weight estimation in macrosomia on the mode of delivery and neonatal outcome (NO). Methods In 14633 pregnancies between 2002 and 2016, this retrospective study evaluated the association between sonographic fetal weight estimation, true birth weight (BW), mode of delivery (primary cesarean section [pCS], secondary cesarean section, vaginal delivery, and operative vaginal delivery rates) and NO parameters (5-min Apgar <7, pH <7.1, neonatal intensive care unit [NICU] admission, shoulder dystocia). Singleton pregnancies >37+0 weeks with ultrasound-estimated fetal weight (EFW) within 7 days before delivery were included. The study population was divided into four groups: Group 1 (false-negative): EFW <4000g/BW ≥4000g; Group 2 (true-positive): EFW ≥4000g/BW ≥4000g; Group 3 (false-positive): EFW ≥4000g/BW <4000g; and Group 4 (true-negative): EFW <4000g/BW <4000g. Results As expected, the highest secondary cesarean section (sCS) rate was found in Group 2 (true-positive) (30.62%), compared with only 17.68% in Group 4 (true-negative). The sCS rate in the false-positive Group 3 was significantly higher (28.48%) in comparison with the false-negative Group 1 (21.22%; OR 1.48; 95% CI, 1.16 to 1.89; P=0.002). In comparison with the true-negative Group 4, univariate analyses showed significantly higher rates for sCS in all other groups: Odds ratio (OR) 2.06 for Group 2 (95% CI, 1.74 to 2.42; P<0.001), 1.85 for Group 3 (95% CI, 1.54 to 2.22, P <0.001), and 1.25 for Group 1 (95% CI, 1.05 to 1.49; P <0.01). No significant differences were found for NO between Groups 1 and 3 for the parameters 5-min Apgar <7 (P=0.75), pH <7.1 (P=0.28), or NICU admission (P=0.54). However, there was a significantly higher chance for shoulder dystocia in Group 1 compared with Group 3 (OR 4.58; 95% CI, 1.34 to 24.30; P=0.008). Conclusion Sonographic EFW inaccuracies in fetal macrosomia appear to have a greater impact on the mode of delivery than birth weight itself. Underestimation of fetal weight may be associated with a higher probability of shoulder dystocia.
CRIS-Team Scopus Importer:2021-04-19
Keywords: cesarean section rate; fetal macrosomia; fetal weight estimation; perinatal outcome; sonography

Influence of sonographic fetal weight estimation in (suspected) fetal macrosomia on perinatal outcome - Pretscher, Jutta; Kehl, Sven; Stelzl, Patrick; Stumpfe, Florian; Mayr, A.; Schmid, M.; Staerk, C.; Schild, R. L.; Beckmann, Matthias; Faschingbauer, Florian (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Influence of the Family Anamnesis of Breast or Ovarian Cancer on the pathological Complete Remission and the Prognosis in Patients with Breast Cancer after neoadjuvant Chemotherapy - Gaß, Paul; Haberle, L.; Hein, Alexander; Jud, Sebastian; Lux, M. P.; Hack, Caroline; Emons, J.; Heindl, Felix; Nabieva, Naiba; Löhberg, Christian; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Influence of Timing of Antenatal Corticosteroid Administration on Morbidity of Preterm Neonates - Morhart, Patrick; Gärtner, Janis; Weiss, Christel; Stumpfe, Florian; Dammer, Ulf; Faschingbauer, Florian; Fahlbusch, Fabian; Beckmann, Matthias; Kehl, Sven (In Vivo, 2022)
Background/Aim: We investigated the impact of the timing of antenatal corticosteroid (ACS) administration on the clinical outcome of preterm infants. Patients and Methods: Two hundred and fifty-five preterm infants between 28+0 and 34+0 weeks of gestation were retrospectively assigned to one of two groups: In the first group, ACS was given within 7 days before birth; the second group, did not receive ACS during that period. The primary outcome parameter was respiratory failure (defined by need for continuous positive airway pressure or mechanical ventilation) due to grade 1-4 respiratory distress syndrome (RDS). Secondary outcomes included the rates of intraventricular hemorrhage (IVH), periventricular leukomalacia, and necrotizing enterocolitis. Results: The rate of RDS was significantly higher in the no ACS group (40% vs. 62%, p=0.0009), especially of the more severe grades 24 (n=37 vs. n=48, p=0.0121). In addition, IVH (1% vs. 9%, p=0.0041) and neonatal infections (72% vs. 89%, p=0.0025) were significantly increased. Univariable and multivariable regression analyses showed a lower likelihood of RDS in the ACS group [odds ratio (OR)=0.295] in infants born closer to term (OR=0.907) and following preterm onset of labor (OR=0.495). Similarly, we observed a lower probability of IVH in the ACS group (OR=0.098), with a higher probability of occurrence of IVH in pre-eclampsia/HELLP syndrome (hemolysis, elevated liver enzyme levels, low platelet count) (OR=7.914). Conclusion: ACS treatment within the last 7 days before birth significantly reduced the risk of RDS and IVH in preterm. These data emphasize that the timing of ACS administration determines its success.
CRIS-Team WoS Importer:2022-07-15

Inherited mutations in 17 breast cancer susceptibility genes among a large triple-negative breast cancer cohort unselected for family history of breast cancer - Couch, Fergus J.; Hart, Steven N.; Sharma, Priyanka; Toland, Amanda Ewart; Wang, Xianshu; Miron, Penelope; Olson, Janet E.; Godwin, Andrew K.; Pankratz, V. Shane; Olswold, Curtis; Slettedahl, Seth; Hallberg, Emily; et al. (Journal of Clinical Oncology, 2015)
Recent advances in DNA sequencing have led to the development of breast cancer susceptibility gene panels for germline genetic testing of patients. We assessed the frequency of mutations in 17 predisposition genes, including BRCA1 and BRCA2, in a large cohort of patients with triple-negative breast cancer (TNBC) unselected for family history of breast or ovarian cancer to determine the utility of germline genetic testing for those with TNBC.Patients with TNBC (N = 1,824) unselected for family history of breast or ovarian cancer were recruited through 12 studies, and germline DNA was sequenced to identify mutations.Deleterious mutations were identified in 14.6% of all patients. Of these, 11.2% had mutations in the BRCA1 (8.5%) and BRCA2 (2.7%) genes. Deleterious mutations in 15 other predisposition genes were detected in 3.7% of patients, with the majority observed in genes involved in homologous recombination, including PALB2 (1.2%) and BARD1, RAD51D, RAD51C, and BRIP1 (0.3% to 0.5%). Patients with TNBC with mutations were diagnosed at an earlier age (P < .001) and had higher-grade tumors (P = .01) than those without mutations.Deleterious mutations in predisposition genes are present at high frequency in patients with TNBC unselected for family history of cancer. Mutation prevalence estimates suggest that patients with TNBC, regardless of age at diagnosis or family history of cancer, should be considered for germline genetic testing of BRCA1 and BRCA2. Although mutations in other predisposition genes are observed among patients with TNBC, better cancer risk estimates are needed before these mutations are used for clinical risk assessment in relatives.
EVALuna2:9246

Inherited variants affecting RNA editing may contribute to ovarian cancer susceptibility: results from a large-scale collaboration - Permuth, Jennifer B.; Reid, Brett; Earp, Madalene; Chen, Y. Ann; Monteiro, Alvaro N. A.; Chen, Zhihua; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Lambrechts, Diether; Vanderstichele, Adriaan; Van Niewenhuyse, Els; et al. (Oncotarget, 2016)
RNA editing in mammals is a form of post-transcriptional modification in which adenosine is converted to inosine by the adenosine deaminases acting on RNA (ADAR) family of enzymes. Based on evidence of altered ADAR expression in epithelial ovarian cancers (EOC), we hypothesized that single nucleotide polymorphisms (SNPs) in ADAR genes modify EOC susceptibility, potentially by altering ovarian tissue gene expression. Using directly genotyped and imputed data from 10,891 invasive EOC cases and 21,693 controls, we evaluated the associations of 5,303 SNPs in ADAD1, ADAR, ADAR2, ADAR3, and SND1. Unconditional logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI), with adjustment for European ancestry. We conducted gene-level analyses using the Admixture Maximum Likelihood (AML) test and the Sequence-Kernel Association test for common and rare variants (SKAT-CR). Association analysis revealed top risk-associated SNP rs77027562 (OR (95% CI)= 1.39 (1.17-1.64), P=1.0x10-4) in ADAR3 and rs185455523 in SND1 (OR (95% CI)= 0.68 (0.56-0.83), P=2.0x10-4). When restricting to serous histology (n=6,500), the magnitude of association strengthened for rs185455523 (OR=0.60, P=1.0x10-4). Gene-level analyses revealed that variation in ADAR was associated (P<0.05) with EOC susceptibility, with PAML=0.022 and PSKAT-CR=0.020. Expression quantitative trait locus analysis in EOC tissue revealed significant associations (P<0.05) with ADAR expression for several SNPs in ADAR, including rs1127313 (G/A), a SNP in the 3' untranslated region. In summary, germline variation involving RNA editing genes may influence EOC susceptibility, warranting further investigation of inherited and acquired alterations affecting RNA editing.
EVALuna2:33315

Inherited variants in the inner centromere protein (INCENP) gene of the chromosomal passenger complex contribute to the susceptibility of ER-negative breast cancer - Kabisch, Maria; Bermejo, Justo Lorenzo; Duennebier, Thomas; Ying, Shibo; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Shah, Mitul; Perkins, Barbara J.; Czene, Kamila; Darabi, Hatef; et al. (Carcinogenesis, 2015)
The chromosomal passenger complex (CPC) plays a pivotal role in the regulation of cell division. Therefore, inherited CPC variability could influence tumor development. The present candidate gene approach investigates the relationship between single nucleotide polymorphisms (SNPs) in genes encoding key CPC components and breast cancer risk. Fifteen SNPs in four CPC genes (INCENP, AURKB, BIRC5 and CDCA8) were genotyped in 88 911 European women from 39 case-control studies of the Breast Cancer Association Consortium. Possible associations were investigated in fixed-effects meta-analyses. The synonymous SNP rs1675126 in exon 7 of INCENP was associated with overall breast cancer risk [per A allele odds ratio (OR) 0.95, 95% confidence interval (CI) 0.92-0.98, P = 0.007] and particularly with estrogen receptor (ER)-negative breast tumors (per A allele OR 0.89, 95% CI 0.83-0.95, P = 0.0005). SNPs not directly genotyped were imputed based on 1000 Genomes. The SNPs rs1047739 in the 3' untranslated region and rs144045115 downstream of INCENP showed the strongest association signals for overall (per T allele OR 1.03, 95% CI 1.00-1.06, P = 0.0009) and ER-negative breast cancer risk (per A allele OR 1.06, 95% CI 1.02-1.10, P = 0.0002). Two genotyped SNPs in BIRC5 were associated with familial breast cancer risk (top SNP rs2071214: per G allele OR 1.12, 95% CI 1.04-1.21, P = 0.002). The data suggest that INCENP in the CPC pathway contributes to ER-negative breast cancer susceptibility in the European population. In spite of a modest contribution of CPC-inherited variants to the total burden of sporadic and familial breast cancer, their potential as novel targets for breast cancer treatment should be further investigated.
EVALuna2:9268

Inhibiting DNA Methylation Causes an Interferon Response in Cancer via dsRNA Including Endogenous Retroviruses - Chiappinelli, Katherine B.; Strissel, Pamela; Desrichard, Alexis; Li, Huili; Henke, Christine; Akman, Benjamin; Hein, Alexander; Rote, Neal S.; Cope, Leslie M.; Snyder, Alexandra; Makarov, Vladimir; Buhu, Sadna; et al. (Cell, 2015)
We show that DNA methyltransferase inhibitors (DNMTis) upregulate immune signaling in cancer through the viral defense pathway. In ovarian cancer (OC), DNMTis trigger cytosolic sensing of double-stranded RNA (dsRNA) causing a type I interferon response and apoptosis. Knocking down dsRNA sensors TLR3 and MAVS reduces this response 2-fold and blocking interferon beta or its receptor abrogates it. Upregulation of hypermethylated endogenous retrovirus (ERV) genes accompanies the response and ERV overexpression activates the response. Basal levels of ERV and viral defense gene expression significantly correlate in primary OC and the latter signature separates primary samples for multiple tumor types from The Cancer Genome Atlas into low versus high expression groups. In melanoma patients treated with an immune checkpoint therapy, high viral defense signature expression in tumors significantly associates with durable clinical response and DNMTi treatment sensitizes to anti-CTLA4 therapy in a pre-clinical melanoma model.
EVALuna2:17550

Inhibition of adhesion, proliferation, and invasion of primary endometriosis and endometrial stromal and ovarian carcinoma cells by a nonhyaluronan adhesion barrier gel - Renner, Stefan; Strissel, Pamela; Beckmann, Matthias; Lermann, Johannes; Burghaus, Stefanie; Hackl, Janina; Fasching, Peter; Strick, Reiner (BioMed Research International, 2015)
Endometriosis is a chronic disease of women in the reproductive age, defined as endometrial cells growing outside of the uterine cavity and associated with relapses. Relapses are hypothesized to correlate with incomplete surgical excision or result from nonrandom implantation of new endometrial implants in adjacent peritoneum. Thus, surgical excision could lead to free endometriotic cells or tissue residues, which readhere, grow, and invade into recurrent lesions. Barrier agents are frequently used to prevent postoperative adhesions. We tested if the absorbable cell adhesion barrier gel Intercoat consisting of polyethylene oxide and sodium carboxymethyl cellulose could inhibit cellular adhesion, proliferation, and invasion of primary endometriosis and endometrial cells. Due to an association of endometriosis with ovarian carcinoma, we tested two ovarian carcinoma cell lines. Prior to cell seeding, a drop of the barrier gel was placed in cell culture wells in order to test inhibition of adherence and proliferation or coated over a polymerized collagen gel to assay for prevention of invasion. Results showed that the barrier gel significantly inhibited cell adherence, proliferation, and invasion of endometriosis and endometrial stromal cells as well as ovarian carcinoma cells in culture. Our findings could help to prevent local cell growth/invasion and possible consequent recurrences.
EVALuna2:17548

Initial clinical results with a fusion prototype for mammography and three-dimensional ultrasound with a standard mammography system and a standard ultrasound probe - Emons, Julius; Wunderle, Marius; Hartmann, Arndt; Radicke, Marcus; Rauh, Claudia; Uder, Michael; Gaß, Paul; Fasching, Peter; Langemann, Hanna; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Jud, Sebastian (Acta Radiologica, 2018)
BACKGROUND: Combinations *Equal contributors. of different imaging techniques in fusion devices appear to be associated with improvements in diagnostic assessment. PURPOSE: The aim of this study was to test the feasibility of using an automated standard three-dimensional (3D) ultrasound (US) device fused with standard mammography for the first time in breast cancer patients. MATERIAL AND METHODS: Digital mammograms and 3D automated US images were obtained in 23 patients with highly suspicious breast lesions. A recently developed fusion machine consisting of an ABVS 3D US transducer from an Acuson S2000 machine and a conventional Mammomat Inspiration device (both Siemens Healthcare GmbH, Erlangen, Germany) were used for the purpose. The feasibility of the examinations, imaging coverage, and patients' experience of the procedure were examined. RESULTS: In 15 out of 19 patients, the region of interest (ROI) with the tumor marked in the mammogram was visible on US. The examination was experienced positively by the patients, with no unexpected pain or injury. The examination was time-saving and well tolerated. CONCLUSION: In conclusion, we have shown initial clinical feasibility of an US/radiography fusion prototype with good localization and evaluation of the ROIs. The combined examination was well tolerated. The simultaneous evaluation with mammography and US imaging may be able to improve detection and reduce examiner-related variability.
EVALuna2:34810

Initial experience with CDK4/6 inhibitor-based therapies compared to antihormone monotherapies in routine clinical use in patients with hormone receptor positive, HER2 negative breast cancer — Data from the PRAEGNANT research network for the first 2 years of drug availability in Germany - Schneeweiss, Andreas; Ettl, Johannes; Lüftner, Diana; Beckmann, Matthias; Belleville, Erik; Fasching, Peter; Fehm, Tanja N.; Geberth, Matthias; Häberle, Lothar; Hadji, Peyman; Hartkopf, Andreas D.; Hielscher, Carsten; et al. (BREAST, 2020)
Purpose: Treatment with CDK4/6 inhibitors and endocrine therapy (CDK4/6i + ET) is a standard for patients with advanced hormone receptor–positive, HER2-negative (HR + HER2–) breast cancer (BC). However, real-world data on the implementation of therapy usage, efficacy, and toxicity have not yet been reported. Methods: The PRAEGNANT registry was used to identify advanced HR + HER2– BC patients (n = 1136). The use of chemotherapy, ET, everolimus + ET, and CDK4/6i + ET was analyzed for first-line, second-line, and third-line therapy. Progression-free survival (PFS) and overall survival (OS) were also compared between patients treated with CDK4/6i + ET and ET monotherapy. Also toxicity was assessed. Results: CDK4/6i + ET use increased from 38.5% to 62.7% in the first 2 years after CDK4/6i treatment became available (November 2016). Chemotherapy and ET monotherapy use decreased from 2015 to 2018 from 42.2% to 27.2% and from 53% to 9.5%, respectively. In this early analysis no statistically significant differences were found comparing CDK4/6i + ET and ET monotherapy patients with regard to PFS and OS. Leukopenia was was seen in 11.3% of patients under CDK4/6i + ET and 0.5% under ET monotherapy. Conclusions: In clinical practice, CDK4/6i + ET has been rapidly implemented. A group of patients with a more unfavorable prognosis was possibly treated in the real-world setting than in the reported randomized clinical trials. The available data suggest that longer follow-up times and a larger sample size are required in order to identify differences in survival outcomes. Studies should be supported that investigate whether chemotherapy can be avoided or delayed in this patient population by using CDK4/6i + ET.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Abemaciclib; Advanced breast cancer; CDK4/6; Chemotherapy; Endocrine therapy; Metastatic; Palbociclib; Ribociclib

Insufficient Angiogenesis: Cause of Abnormally Thin Endometrium in Subfertile Patients? - Alfer, Joachim; Happel, Lars; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Gaumann, Andreas; Buck, Volker U.; Classen-Linke, Irmgard (Geburtshilfe und Frauenheilkunde, 2017)
This study investigated subfertile patients with abnormally thin endometrium after infertility treatment. As they had adequate serum concentrations of hormones, an endometrial factor for subfertility was suspected.To elucidate the cause of subfertility, endometrial biopsies were taken in each patient in the late proliferative and mid-secretory phases of one menstrual cycle. Endometrial biopsies from women with normal menstrual cycles and confirmed fertility who were undergoing hysterectomy for benign uterine disease were used as positive controls. The tissue samples were investigated for steroid hormone receptor expression and for the proliferation marker Ki-67. Immunohistochemistry was performed with antibodies against the marker molecules for endometrial receptivity - ? 3 integrin, VEGF, LIF, and CD56 (large granular lymphocytes, LGLs).The steroid hormone receptors for estrogen (E2) and progesterone (P) were expressed normally (at the first biopsy) and were down-regulated (at the second biopsy) within the cycle. Strikingly, all of the marker molecules investigated showed negative or weak and inadequate expression in the mid-secretory phase. Numbers of LGLs remained as low as in the proliferative phase. In contrast, fertile patients were found to express these marker molecules distinctly in the mid-secretory phase.It may be hypothesized that a severe deficiency of these angiogenesis-related marker molecules leads to defective development of the endometrium, which remains thin. Deficient angiogenetic development may thus provide an explanation for the endometrial factor that causes infertility. Further investigations will need to focus on identifying the regulating factors that act between steroid receptor activation and the expression of these marker molecules.
EVALuna2:6870

Interdisciplinary Diagnosis, Therapy and Follow-up of Patients with Endometrial Cancer. Guideline (S3-Level, AWMF Registry Number 032/034-OL, April 2018) - Part 2 with Recommendations on the Therapy and Follow-up of Endometrial Cancer, Palliative Care, Psycho-oncological/Psychosocial Care/Rehabilitation/Patient Information and Healthcare Facilities - Emons, Guenter; Steiner, Eric; Vordermark, Dirk; Uleer, Christoph; Bock, Nina; Paradies, Kerstin; Ortmann, Olaf; Aretz, Stefan; Mallmann, Peter; Kurzeder, Christian; Hagen, Volker; Van Oorschot, Birgitt; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Summary The first German interdisciplinary S3-guideline on the diagnosis, therapy and follow-up of patients with endometrial cancer was published in April 2018. Funded by German Cancer Aid as part of an Oncology Guidelines Program, the lead coordinators of the guideline were the German Society of Gynecology and Obstetrics (DGGG) and the Gynecological Oncology Working Group (AGO) of the German Cancer Society (DKG). Purpose Using evidence-based, risk-adapted therapy to treat low-risk women with endometrial cancer avoids unnecessarily radical surgery and non-useful adjuvant radiotherapy and/or chemotherapy. This can significantly reduce therapy-induced morbidity and improve the patient's quality of life as well as avoiding unnecessary costs. For women with endometrial cancer and a high risk of recurrence, the guideline defines the optimal extent of surgical radicality together with the appropriate chemotherapy and/or adjuvant radiotherapy if required. An evidence-based optimal use of different therapeutic modalities should improve the survival rates and quality of life of these patients. This S3-guideline on endometrial cancer is intended as a basis for certified gynecological cancer centers. The aim is that the quality indicators established in this guideline will be incorporated in the certification processes of these centers. Methods The guideline was compiled in accordance with the requirements for S3-level guidelines. This includes, in the first instance, the adaptation of source guidelines selected using the DELBI instrument for appraising guidelines. Other consulted sources included reviews of evidence, which were compiled from literature selected during systematic searches of literature databases using the PICO scheme. In addition, an external biostatistics institute was commissioned to carry out a systematic search and assessment of the literature for one part of the guideline. Identified materials were used by the interdisciplinary working groups to develop suggestions for Recommendations and Statements, which were then subsequently modified during structured consensus conferences and/or additionally amended online using the DELPHI method, with consent between members achieved online. The guideline report is freely available online. Recommendations Part 2 of this short version of the guideline presents recommendations for the therapy of endometrial cancer including precancers and early endometrial cancer as well as recommendations on palliative medicine, psycho-oncology, rehabilitation, patient information and healthcare facilities to treat endometrial cancer. The management of precancers of early endometrial precancerous conditions including fertility-preserving strategies is presented. The concept used for surgical primary therapy of endometrial cancer is described. Radiotherapy and adjuvant medical therapy to treat endometrial cancer and uterine carcinosarcomas are described. Recommendations are given for the follow-up care of endometrial cancer, recurrence and metastasis. Palliative medicine, psycho-oncology including psychosocial care, and patient information and rehabilitation are presented. Finally, the care algorithm and quality assurance steps for the diagnosis, therapy and follow-up of patients with endometrial cancer are outlined.
EVALuna2:36537

Interdisciplinary Diagnosis, Therapy and Follow-up of Patients with Endometrial Cancer. Guideline (S3-Level, AWMF Registry Nummer 032/034-OL, April 2018) - Part 1 with Recommendations on the Epidemiology, Screening, Diagnosis and Hereditary Factors of Endometrial Cancer - Emons, Guenter; Steiner, Eric; Vordermark, Dirk; Uleer, Christoph; Bock, Nina; Paradiess, Kerstin; Ortmann, Olaf; Aretz, Stefan; Mallmann, Peter; Kurzeder, Christian; Hagen, Volker; Van Oorschot, Birgitt; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Summary The first German interdisciplinary S3-guideline on the diagnosis, therapy and follow-up of patients with endometrial cancer was published in April 2018. Funded by German Cancer Aid as part of an Oncology Guidelines Program, the lead coordinators of the guideline were the German Society of Gynecology and Obstetrics (DGGG) and the Gynecological Oncology Working Group (AGO) of the German Cancer Society (DKG). Purpose The use of evidence-based, risk-adapted therapy to treat low-risk women with endometrial cancer avoids unnecessarily radical surgery and non-useful adjuvant radiotherapy and/or chemotherapy. This can significantly reduce therapy-induced morbidity and improve the patient's quality of life as well as avoiding unnecessary costs. For women with endometrial cancer and a high risk of recurrence, the guideline defines the optimal surgical radicality together with the appropriate chemotherapy and/or adjuvant radiotherapy where required. The evidence-based optimal use of different therapeutic modalities should improve survival rates and the quality of life of these patients. The S3-guideline on endometrial cancer is intended as a basis for certified gynecological cancer centers. The aim is that the quality indicators established in this guideline will be incorporated in the certification processes of these centers. Methods The guideline was compiled in accordance with the requirements for S3-level guidelines. This includes, in the first instance, the adaptation of source guidelines selected using the DELBI instrument for appraising guidelines. Other consulted sources include reviews of evidence which were compiled from literature selected during systematic searches of literature databases using the PICO scheme. In addition, an external biostatistics institute was commissioned to carry out a systematic search and assessment of the literature for one area of the guideline. The identified materials were used by the interdisciplinary working groups to develop suggestions for Recommendations and Statements, which were then modified during structured consensus conferences and/or additionally amended online using the DELPHI method with consent being reached online. The guideline report is freely available online. Recommendations Part 1 of this short version of the guideline presents recommendations on epidemiology, screening, diagnosis and hereditary factors, The epidemiology of endometrial cancer and the risk factors for developing endomentrial cancer are presented. The options for screening and the methods used to diagnose endometrial cancer including the pathology of the cancer are outlined. Recommendations are given for the prevention, diagnosis, and therapy of hereditary forms of endometrial cancer.
EVALuna2:36539

Interdisciplinary Screening, Diagnosis, Therapy and Follow-up of Breast Cancer. Guideline of the DGGG and the DKG (S3-Level, AWMF Registry Number 032/045OL, December 2017) - Part 1 with Recommendations for the Screening, Diagnosis and Therapy of Breast Cancer - Woeckel, Achim; Festl, Jasmin; Stueber, Tanja; Brust, Katharina; Stangl, Stephanie; Heuschmann, Peter U.; Albert, Ute-Susann; Budach, Wilfried; Follmann, Markus; Janni, Wolfgang; Kopp, Ina; Kreienberg, Rolf; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Purpose The aim of this official guideline coordinated and published by the German Society for Gynecology and Obstetrics (DGGG) and the German Cancer Society (DKG) was to optimize the screening, diagnosis, therapy and follow-up care of breast cancer. Methods The process of updating the S3 guideline dating from 2012 was based on the adaptation of identified source guidelines which were combined with reviews of evidence compiled using PICO (Patients/Interventions/Control/Outcome) questions and the results of a systematic search of literature databases and the selection and evaluation of the identified literature. The interdisciplinary working groups took the identified materials as their starting point to develop recommendations and statements which were modified and graded in a structured consensus procedure. Recommendations Part 1 of this short version of the guideline presents recommendations for the screening, diagnosis and follow-up care of breast cancer. The importance of mammography for screening is confirmed in this updated version of the guideline and forms the basis for all screening. In addition to the conventional methods used to diagnose breast cancer, computed tomography (CT) is recommended for staging in women with a higher risk of recurrence. The follow-up concept includes suggested intervals between physical, ultrasound and mammography examinations, additional high-tech diagnostic procedures, and the determination of tumor markers for the evaluation of metastatic disease.
EVALuna2:36235

Interdisciplinary Screening, Diagnosis, Therapy and Follow-up of Breast Cancer. Guideline of the DGGG and the DKG (S3-Level, AWMF Registry Number 032/045OL, December 2017) - Part 2 with Recommendations for the Therapy of Primary, Recurrent and Advanced Breast Cancer - Woeckel, Achim; Festl, Jasmin; Stueber, Tanja; Brust, Katharina; Krockenberger, Mathias; Heuschmann, Peter U.; Jiru-Hillmann, Steffi; Albert, Ute-Susann; Budach, Wilfried; Follmann, Markus; Janni, Wolfgang; Kopp, Ina; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Purpose The aim of this official guideline coordinated and published by the German Society for Gynecology and Obstetrics (DGGG) and the German Cancer Society (DKG) was to optimize the screening, diagnosis, therapy and follow-up care of breast cancer. Method The process of updating the S3 guideline published in 2012 was based on the adaptation of identified source guidelines. They were combined with reviews of evidence compiled using PICO (Patients/Interventions/Control/Outcome) questions and with the results of a systematic search of literature databases followed by the selection and evaluation of the identified literature. The interdisciplinary working groups took the identified materials as their starting point and used them to develop suggestions for recommendations and statements, which were then modified and graded in a structured consensus process procedure. Recommendations Part 2 of this short version of the guideline presents recommendations for the therapy of primary, recurrent and metastatic breast cancer. Loco-regional therapies are de-escalated in the current guideline. In addition to reducing the safety margins for surgical procedures, the guideline also recommends reducing the radicality of axillary surgery. The choice and extent of systemic therapy depends on the respective tumor biology. New substances are becoming available, particularly to treat metastatic breast cancer.
EVALuna2:36231

Interdisciplinary Treatment for Cutaneous Abdominal Wall Metastasis from Cervical Cancer with Resection and Reconstruction of the Abdominal Wall Using Free Latissimus Dorsi Muscle Flap: A Case Report - Boos, Anja; Beckmann, Matthias; Horch, Raymund E.; Beier, Justus (Geburtshilfe und Frauenheilkunde, 2014)
EVALuna2:15567

Interest in Integrative Medicine Among Postmenopausal Hormone Receptor-Positive Breast Cancer Patients in the EvAluate-TM Study - Hack, Carolin; Fasching, Peter; Fehm, Tanja; De Waal, Johann; Rezai, Mahdi; Baier, Bernd; Baake, Gerold; Kolberg, Hans-Christian; Guggenberger, Martin; Warm, Mathias; Harbeck, Nadia; Wuerstlein, Rachel; et al. (Integrative Cancer Therapies, 2017)
BACKGROUND: Breast cancer patients often use complementary and alternative medicine, but few prospectively collected data on the topic are available specifically for postmenopausal breast cancer patients. A large prospective study was therefore conducted within a noninterventional study in order to identify the characteristics of patients interested in integrative medicine. METHODS: The EvAluate-TM study is a prospective, multicenter noninterventional study in which treatment with the aromatase inhibitor letrozole was evaluated in postmenopausal women with hormone receptor-positive primary breast cancer. Between 2008 and 2009, 5045 postmenopausal patients were enrolled at 339 certified breast centers in Germany. As part of the data collection process, patients were asked at the baseline about their interest in and information needs relating to integrative medicine. RESULTS: Of the 5045 patients recruited, 3411 responded to the questionnaire on integrative medicine and took part in the analysis, 1583 patients expressed an interest in integrative medicine, and 1828 patients declared no interest. Relevant predictors of interest in integrative medicine were age, body mass index, tumor size, previous chemotherapy, and use of concomitant medications for other medical conditions. Interest in integrative medicine declined highly significantly ( P < .001) with age (<50 years, 74.1%; 50-60 years, 54.1%; >65 years, 38.0%). Patients in favor of integrative medicine were significantly less satisfied with the information received about individual treatments and antihormonal therapy. Patients with interest in integrative medicine were more often interested in rehabilitation and fitness, nutritional counseling, and additional support from self-help organizations. These women were mostly interested in receiving information about their disease and integrative medicine from a physician, rather than from other sources. CONCLUSIONS: This study shows that a considerable proportion of postmenopausal breast cancer patients are interested in integrative medicine. Information about integrative medicine should therefore be provided as part of patient care for this group. It was found that receiving concomitant medication for other medical conditions is one of the main predictors for women not being interested in integrative medicine. This group of patients may need special attention and individualized information about integrative medicine. Additionally, most patients were interested in obtaining the relevant information from their doctor.
EVALuna2:36142

Intra- and Postoperative Blood Flow Monitoring in a Sheep Model of Uterus Transplantation - Kengelbach-Weigand, Annika; Lotz, Laura; Schmid, Rafael; Lang, Werner; Beckmann, Matthias; Hoffmann, Inge; Horch, Raymund E.; Renner, Stefan; Dittrich, Ralf; Boos, Anja; Hildebrandt, Thomas (In Vivo, 2019)
Background: The introduction of the opportunity to transplant a viable uterus into women for fulfilling their desire to have a child has awakened high expectations worldwide. Materials and Methods: A sheep model was used to evaluate tools for optimizing measurement of blood flow in uterine transplantation. Intraoperatively, blood flow was measured using unidirectional Doppler and indocyanine green (ICG) fluorescence imaging. Postoperatively, an implantable Doppler probe served as a tool for clinical monitoring the patency of anastomosed vessels. Results: ICG imaging showed complete vascularization of the uterus before and in short-term evaluation after surgery. The implantable Doppler probe proved to be highly suitable for assessing patency of vessels in a non-invasive way. Results of histology, and real-time polymerase chain reaction demonstrated viability of the transplanted uterus. Conclusion: Different methods to monitor vasculature patency have proven to be advantageous in supporting both surgeons and researchers in ensuring successful implementation of uterine transplantation.
CRIS-Team WoS Importer:2019-03-08

Intrapartum sonographic weight estimation - Faschingbauer, Florian; Dammer, U.; Raabe, E.; Schneider, M.; Faschingbauer, Cornelia; Schmid, M.; Schild, R. L.; Beckmann, Matthias; Kehl, Sven; Mayr, Andreas (Archives of Gynecology and Obstetrics, 2015)
To evaluate the accuracy of intrapartum sonographic weight estimation (WE).This retrospective, cross-sectional study included 1958 singleton pregnancies. Inclusion criteria were singleton pregnancy with cephalic presentation, vaginal delivery and ultrasound examination with complete biometric parameters performed on the day of delivery during the latent or active phase of labor, and absence of chromosomal or structural anomalies. The accuracy of intrapartum WE was compared to a control group of fetuses delivered by primary cesarean section at our perinatal center and an ultrasound examination with complete biometric parameters performed within 3 days before delivery (n = 392). Otherwise, the same inclusion criteria as in the study group were applied. The accuracy of WE was compared between five commonly applied formulas using means of percentage errors (MPE), medians of absolute percentage errors (MAPE), and proportions of estimates within 10 % of actual birth weight.In the whole study group, all equations showed a systematic underestimation of fetal weight (negative MPEs). Overall, best MAPE and MPE values were found with the Hadlock II formula, using BPD, AC and FL as biometric parameters (Hadlock II, MPE: -1.28; MAPE: 6.52). MPEs differed significantly between WE in the study and control group for all evaluated formulas: in the control group, either no systematic error (Hadlock III, IV and V) or a significant overestimation (Hadlock I, II) was found. Regarding MAPEs, application of the Hadlock III (HC, AC, FL) and V (AC) formula resulted in significant lower values in the control group (Hadlock III, MAPE: 7.48 vs. 5.95, p = 0.0008 and Hadlock V, MAPE: 8.79 vs. 7.52, p = 0.0085). No significant differences were found for the other equations.A systematic underestimation of fetal weight has to be taken into account in sonographic WE performed intrapartum. Overall, the best results can be achieved with WE formulas using the BPD as the only head measurement.
EVALuna2:5506

Intrauterine Growth Restriction (IUGR) Induces Signs of Subclinical Atherosclerosis in 6-Year-Old Infants Despite Absence Of Excessive Growth - Tzschoppe, Anja; Von Kries, Ruediger; Struwe, Ellen; Rascher, Wolfgang; Dörr, Helmuth-Günther; Juengert, Joerg; Rauh, Manfred; Beckmann, Matthias; Schild, Ralf; Goecke, Tamme W.; Doetsch, Joerg (Klinische Pädiatrie, 2017)
Background Postnatal catch-up growth and rapid weight gain after intrauterine growth restriction (IUGR) seem to increase the risk for later disease. This study aimed to compare features of the metabolic syndrome early in life between IUGR and appropriate for gestational age (AGA) infants. Patients Data for 9 infants with IUGR defined by a birth weight<10th percentile and ultrasound-proven placental insufficiency and 11 AGA children were available. Method Postnatal growth, auxological, cardiovascular, and metabolic parameters up to a chronological age of 6 years were assessed: Fasting serum concentrations of LDL-cholesterol, insulin, leptin, IGF-I, DHEAS, skinfold thicknesses, blood pressure, and mean carotid intima-media thickness (cIMT). Results All IUGR infants showed catch-up growth, although mean BMI SDS and total subcutaneous fat mass at the age of 6 years were still slightly lower compared to the AGA cohort. Reduced serum leptin concentrations were observed in IUGR infants (p=0.02), whereas no significant difference was found for IGF-I, insulin, LDL-cholesterol and DHEAS concentrations. Mean cIMT was significantly higher in IUGR infants (p<0.05). Mean arterial pressure did no differ. Discussion and Conclusion In 6-year-old IUGR infants with catch-up growth, who still had a slightly reduced BMI SDS compared to the AGA group, signs of subclinical atherosclerosis were detectable suggesting that cardiovascular risk in IUGR may be present even in the absence of excessive growth.
EVALuna2:34095

Introducing a novel highly prognostic grading scheme based on tumour budding and cell nest size for squamous cell carcinoma of the uterine cervix - Jesinghaus, Moritz; Strehl, Johanna; Boxberg, Melanie; Bruehl, Frido; Wenzel, Adrian; Konukiewitz, Bjoern; Schlitter, Anna M.; Steiger, Katja; Warth, Arne; Schnelzer, Andreas; Kiechle, Marion; Beckmann, Matthias; et al. (Journal of Pathology: Clinical Research, 2018)
A novel histopathological grading system based on tumour budding and cell nest size has recently been shown to outperform conventional (WHO-based) grading algorithms in several tumour entities such as lung, oral, and oesophageal squamous cell carcinoma (SCC) in terms of prognostic patient stratification. Here, we tested the prognostic value of this innovative grading approach in two completely independent cohorts of SCC of the uterine cervix. To improve morphology-based grading, we investigated tumour budding activity and cell nest size as well as several other histomorphological factors (e.g., keratinization, nuclear size, mitotic activity) in a test cohort (n = 125) and an independent validation cohort (n = 122) of cervical SCC. All parameters were correlated with clinicopathological factors and patient outcome. Small cell nest size and high tumour budding activity were strongly associated with a dismal patient prognosis (p < 0.001 for overall survival [OS], disease-specific survival, and disease-free survival; test cohort) in both cohorts of cervical SCC. A novel grading algorithm combining these two parameters proved to be a highly effective, stage-independent prognosticator in both cohorts (OS: p < 0.001, test cohort; p = 0.001, validation cohort). In the test cohort, multivariate statistical analysis of the novel grade revealed that the hazard ratio (HR) for OS was 2.3 for G2 and 5.1 for G3 tumours compared to G1 neoplasms (p = 0.010). In the validation cohort, HR for OS was 3.0 for G2 and 7.2 for G3 tumours (p = 0.012). In conclusion, our novel grading algorithm incorporating cell nest size and tumour budding allows strongly prognostic histopathological grading of cervical SCC superior to WHO-based grading. Therefore, our data can be regarded as a cross-organ validation of previous results demonstrated for oesophageal, lung, and oral SCC. We suggest this grading algorithm as an additional morphology-based parameter for the routine diagnostic assessment of this tumour entity.
EVALuna2:35627

Introducing multiple-choice questions to promote learning for medical students: effect on exam performance in obstetrics and gynecology - Jud, Sebastian; Cupisti, Susanne; Frobenius, Wolfgang; Winkler, Andrea; Schultheis, Franziska; Antoniadis, Sophia; Beckmann, Matthias; Heindl, Felix (Archives of Gynecology and Obstetrics, 2020)
Purpose: Testing is required in medical education. The large number of exams that students face requires effective learning strategies. Various methods of improving knowledge retention and recall have been discussed, two of the most widely evaluated of which are test-enhanced learning and pause procedures. This study investigated the effect of voluntary multiple-choice questions on students’ performance. Methods: In a prospective study from April 2013 to March 2015, 721 students were randomly assigned to receive supplementary online material only (control group) or additional multiple-choice questions (investigative group) accompanying lectures. Their performance in the final exam was evaluated. Results: A total of 675 students were ultimately included, with 299 randomly assigned to the investigative group and 376 to the control group. Students in the investigative group scored significantly better in relation to grades and points (2.11 vs. 2.49; 33 vs 31.31; p < 0.05). The effect declined over time. Conclusion: This is the first study of the use of voluntary multiple-choice questions to improve medical students’ performance. The results support test-enhanced learning and the feasibility of implementing multiple-choice questions in lectures.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Gynecology; Lecture; Multiple choice; Obstetrics; Teaching; Testing

Introduction of Inhaled Nitrous Oxide and Oxygen for Pain Management during Labour - Evaluation of Patients' and Midwives' Satisfaction - Dammer, U.; Weiss, C.; Raabe, E.; Heimrich, J.; Koch, Matthias; Winkler, Michael; Faschingbauer, F.; Beckmann, Matthias; Kehl, Sven (Geburtshilfe und Frauenheilkunde, 2014)
Aim: Effective pain management during labour is important because pain affects the birth experience. Epidural analgesia is effective but often it may not be possible; however, inhaled analgesia offers another option. Use of inhaled nitrous oxide and oxygen for pain management in labour is well established in obstetrics but is still not used much in Germany. This study aimed to investigate the acceptance of the inhaled analgesia of inhaled nitrous oxide and oxygen by midwives and pregnant women during labour. Material and Methods: In this observational study carried out between April and September 2013, a total of 66 pregnant women received inhaled nitrous oxide and oxygen during labour on request and after prior assessment of suitability. After the birth, all of the women and the responsible midwives were interviewed about their experience and satisfaction with the inhaled analgesia. Results: A statistically significant reduction of pain was achieved with nitrous oxide and oxygen. The inhaled analgesia was mostly used by women who refused epidural analgesia. The likelihood of using inhaled nitrous oxide and oxygen again was reported as higher for patients who tolerated it well (p = 0.0129) and used it in the second stage of labour (p = 0.0003) and when bearing down (p = 0.0008). Conclusion: Inhaled nitrous oxide and oxygen is an effective method for pain management during labour and is accepted well by women in labour and by midwives.
EVALuna2:17457

Investigation of gene-environment interactions between 47 newly identified breast cancer susceptibility loci and environmental risk factors - Rudolph, Anja; Milne, Roger L.; Truong, Therese; Knight, Julia A.; Seibold, Petra; Flesch-Janys, Dieter; Behrens, Sabine; Eilber, Ursula; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Dunning, Alison M.; et al. (International Journal of Cancer, 2015)
A large genotyping project within the Breast Cancer Association Consortium (BCAC) recently identified 41 associations between single nucleotide polymorphisms (SNPs) and overall breast cancer (BC) risk. We investigated whether the effects of these 41 SNPs, as well as six SNPs associated with estrogen receptor (ER) negative BC risk are modified by 13 environmental risk factors for BC. Data from 22 studies participating in BCAC were pooled, comprising up to 26,633 cases and 30,119 controls. Interactions between SNPs and environmental factors were evaluated using an empirical Bayes-type shrinkage estimator. Six SNPs showed interactions with associated p-values (pint ) <1.1 × 10(-3) . None of the observed interactions was significant after accounting for multiple testing. The Bayesian False Discovery Probability was used to rank the findings, which indicated three interactions as being noteworthy at 1% prior probability of interaction. SNP rs6828523 was associated with increased ER-negative BC risk in women >=170 cm (OR = 1.22, p = 0.017), but inversely associated with ER-negative BC risk in women <160 cm (OR = 0.83, p = 0.039, pint = 1.9 × 10(-4) ). The inverse association between rs4808801 and overall BC risk was stronger for women who had had four or more pregnancies (OR = 0.85, p = 2.0 × 10(-4) ), and absent in women who had had just one (OR = 0.96, p = 0.19, pint = 6.1 × 10(-4) ). SNP rs11242675 was inversely associated with overall BC risk in never/former smokers (OR = 0.93, p = 2.8 × 10(-5) ), but no association was observed in current smokers (OR = 1.07, p = 0.14, pint = 3.4 × 10(-4) ). In conclusion, recently identified BC susceptibility loci are not strongly modified by established risk factors and the observed potential interactions require confirmation in independent studies.
EVALuna2:9245

Is ovarian tissue transport at supra-zero temperatures compared to body temperature optimal for follicle survival? - Raffel, Nathalie; Dittrich, Ralf; Orlowski, Paul; Tischer, Hannah; Sӧder, Stephan; Erber, Ramona; Hoffmann, Inge; Beckmann, Matthias; Lotz, Laura (In Vivo, 2020)
Background/Aim: Transportation of ovarian cortex prior to freezing is used clinically; however, basic investigations of ovarian storage are limited and the question remains what temperature is optimal for transport over long distances and time periods. The aim of this study was to evaluate the rate of follicular loss over various time periods under two different temperatures and assess whether ovarian follicle viability is affected following cryopreservation and thawing subsequent to the transportation of ovarian tissue. Materials and Methods: Pig ovaries were transported at 4oC (n=10) or at 38oC (n=10) prior to cryopreservation. At 0, 4, 12 and 24 h tissues were fixed for histological examination and a LIVE/DEAD Assay. At the same time-points ovarian tissues were cryopreserved and analysed after thawing. Results: Histological evaluation and LIVE/DEAD Assay of freshly transported ovarian tissue showed significantly better follicle survival at 4oC during transportation duration. In cryopreserved ovarian tissues the LIVE/DEAD Assay showed a significant difference in the number of intact and dead follicles at 24 h in favor of 4oC (p<0.05). Conclusion: Ovarian tissue transportation should be kept at a minimum to prevent potential damage.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Cryopreservation; Fertility preservation; Follicle loss; Ovarian follicle viability; Ovarian storage; Ovarian tissue transportation

Is Reduction Mammoplasty Cost-Effective? A Cost-Utility Analysis of Surgical Treatment for Macromastia in Germany - Lux, Michael P.; Brendle-Behnisch, Anne; Hack, Carolin; Preuss, Caroline; Arkudas, Andreas; Horch, Raymund E.; Beckmann, Matthias; Jud, Sebastian (Breast Care, 2021)
Background/Aims: Macromastia can cause physical and psychological problems. Conservative treatments such as physiotherapy and painkillers lead to substantial long-term costs, without any proven medical benefit. In contrast, surgical treatment with reduction mammoplasty leads to improvements in nearly all respects. This study analyzed the costs of reduction mammoplasty and calculated an incremental cost-utility ratio for the treatment. Patients and Methods: The data on 76 patients who underwent reduction mammoplasty between 2008 and 2016 were collected using a two-part questionnaire (preoperative and postoperative) as well as the patients' files. Topics examined besides demographic data included physician visits, medical imaging, integrative medical procedures, remedial procedures, rehabilitation and convalescent measures, drug intake, medical aids, exercise activity, and sick leave days before and after surgery. The data were used to calculate costs per year after surgical treatment for symptomatic macromastia. Costs of surgery, including the process of obtaining insurance reimbursement and postoperative complications, were taken into account to calculate the one-time costs of reduction mammoplasty. Results: The patients' quality of life and satisfaction with the breasts improve after surgery. The one-time costs of reduction mammoplasty per patient amount to EUR 5,885, and the annual costs after surgery are EUR 200. The incremental cost-utility ratio for surgical treatments shows a saving of EUR 380 per quality-adjusted life-year (QALY) gained. Conclusions: These results show that reduction mammoplasty is a treatment that not only improves a patient's quality of life but also saves money in the longer term in comparison with expensive and ineffective conservative treatment for macromastia.
CRIS-Team WoS Importer:2021-02-19

Is there a benefit of lymphadenectomy for overall and recurrence-free survival in type I FIGO IB G1-2 endometrial carcinoma? A retrospective population-based cohort analysis - Papathemelis, Thomas; Hassas, Dunja; Gerken, Michael; Klinkhammer-Schalke, Monika; Scharl, Anton; Lux, Michael P.; Beckmann, Matthias; Scharl, Sophia (Journal of Cancer Research and Clinical Oncology, 2018)
The recommended therapy for type I FIGO IB endometrial cancer (EC) is hysterectomy and adnexectomy, but the therapeutic benefits of additional pelvic and paraaortic lymph node dissection (LND) are still under discussion. In this study, we retrospectively evaluated overall survival (OAS) and recurrence-free survival (RFS) among patients with type I FIGO IB EC who did undergo systematic or elective lymphadenectomy or none at all.We selected 299 individuals from the database of the German Tumor Centre Regensburg who were diagnosed between 1998 and 2015 with endometrial adenocarcinoma of the uterus type I FIGO IB. We applied multivariable Cox regression to the selected patient data and estimated hazard ratios for OAS and RFS against the performed intervention. Further, we carried out risk adjustments with respect to clinicopathological parameters, and performed model selection using conditional stepwise forward selection.We observed significant benefits of LND in the unadjusted survival analysis; however, we did not confirm this effect in multivariable regression analysis upon risk adjustment. In this case, hazard ratio (HR) for OAS in patients without LND versus patients with LND is reduced to 1.214 (95% CI 0.771-1.911; p = 0.402), HR for RFS is 1.059 (95% CI 0.689-1.626; p = 0.795). Similarly, we were also able to eliminate the statistical benefit of systematic versus elective LND by risk adjustment.In contrast to previous observations in high-grade EC, our study provides compelling evidence that LND, in particular systematic lymphadenectomy, is not beneficial for patients with type I FIGO IB EC in terms of long-term OAS and RFS.
EVALuna2:92113

Is there an Advantage of Lymphadenectomy for Overall and Recurrence-Free Survival in Endometrial Carcinoma Type I FIGO IB G1-2? A Retrospective Population-Based Cohort Analysis - Hassas, Dunja; Papathemelis, Thomas; Gerken, Michael; Scharl, Sophia; Scharl, Anton; Lux, Michael P.; Beckmann, Matthias; Ortmann, Olaf; Klinkhamtner-Schalke, Monika (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

IT infrastructure components to support clinical care and translational research projects in a comprehensive cancer center - Prokosch, Hans-Ulrich; Ries, Markus; Beyer, Alexander; Schwenk, Martin; Seggewies, Christof; Köpcke, Felix; Mate, Sebastian; Martin, Marcus; Bärthlein, Barbara; Beckmann, Matthias; Stürzl, Michael; Croner, Roland; et al. (User Centred Networked Health Care, 2011)
This paper presents the concept of an integrated IT infrastructure framework established at the comprehensive cancer center at the University Hospital Erlangen. The framework is based on the single source concept where data from the electronic medical record are reused for clinical and translational research projects. The applicability of the approach is illustrated by two case studies from colon cancer and prostate cancer research projects. © 2011 European Federation for Medical Informatics. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.tech.IMMD.infome.itinfr
Keywords: Cancer documentation; Center; Comprehensive cancer; IT infrastructure framework; Single source concept; Translational research

Joint associations of a polygenic risk score and environmental risk factors for breast cancer in the Breast Cancer Association Consortium - Rudolph, Anja; Song, Minsun; Brook, Mark N.; Milne, Roger L.; Mavaddat, Nasim; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Wilcox, Amber N.; Hopper, John L.; Southey, Melissa C.; et al. (International Journal of Epidemiology, 2018)
Background: Polygenic risk scores (PRS) for breast cancer can be used to stratify the population into groups at substantially different levels of risk. Combining PRS and environmental risk factors will improve risk prediction; however, integrating PRS into risk prediction models requires evaluation of their joint association with known environmental risk factors. Methods: Analyses were based on data from 20 studies; datasets analysed ranged from 3453 to 23 104 invasive breast cancer cases and similar numbers of controls, depending on the analysed environmental risk factor. We evaluated joint associations of a 77-single nucleotide polymorphism (SNP) PRS with reproductive history, alcohol consumption, menopausal hormone therapy (MHT), height and body mass index (BMI). We tested the null hypothesis of multiplicative joint associations for PRS and each of the environmental factors, and performed global and tail-based goodness-of-fit tests in logistic regression models. The outcomes were breast cancer overall and by estrogen receptor (ER) status. Results: The strongest evidence for a non-multiplicative joint associations with the 77-SNP PRS was for alcohol consumption (P-interaction = 0.009), adult height (P-interaction = 0.025) and current use of combined MHT (P-interaction = 0.038) in ER-positive disease. Risk associations for these factors by percentiles of PRS did not follow a clear dose-response. In addition, global and tail-based goodness of fit tests showed little evidence for departures from a multiplicative risk model, with alcohol consumption showing the strongest evidence for ER-positive disease (P = 0.013 for global and 0.18 for tail-based tests). Conclusions: The combined effects of the 77-SNP PRS and environmental risk factors for breast cancer are generally well described by a multiplicative model. Larger studies are required to confirm possible departures from the multiplicative model for individual risk factors, and assess models specific for ER-negative disease.
EVALuna2:209951

Ki67, chemotherapy response, and prognosis in breast cancer patients receiving neoadjuvant treatment - Fasching, Peter A.; Heusinger, Katharina; Haeberle, Lothar; Niklos, Melitta; Hein, Alexander; Bayer, Christian M.; Rauh, Claudia; Schulz-Wendtland, Rüdiger; Bani, Mayada; Schrauder, Michael; Kahmann, Laura; Lux, Michael P.; et al. (BMC Cancer, 2011)
Background: The pathological complete response (pCR) after neoadjuvant chemotherapy is a surrogate marker for a favorable prognosis in breast cancer patients. Factors capable of predicting a pCR, such as the proliferation marker Ki67, may therefore help improve our understanding of the drug response and its effect on the prognosis. This study investigated the predictive and prognostic value of Ki67 in patients with invasive breast cancer receiving neoadjuvant treatment for breast cancer.Methods: Ki67 was stained routinely from core biopsies in 552 patients directly after the fixation and embedding process. HER2/neu, estrogen and progesterone receptors, and grading were also assessed before treatment. These data were used to construct univariate and multivariate models for predicting pCR and prognosis. The tumors were also classified by molecular phenotype to identify subgroups in which predicting pCR and prognosis with Ki67 might be feasible.Results: Using a cut-off value of > 13% positively stained cancer cells, Ki67 was found to be an independent predictor for pCR (OR 3.5; 95% CI, 1.4, 10.1) and for overall survival (HR 8.1; 95% CI, 3.3 to 20.4) and distant disease-free survival (HR 3.2; 95% CI, 1.8 to 5.9). The mean Ki67 value was 50.6 ± 23.4% in patients with pCR. Patients without a pCR had an average of 26.7 ± 22.9% positively stained cancer cells.Conclusions: Ki67 has predictive and prognostic value and is a feasible marker for clinical practice. It independently improved the prediction of treatment response and prognosis in a group of breast cancer patients receiving neoadjuvant treatment. As mean Ki67 values in patients with a pCR were very high, cut-off values in a high range above which the prognosis may be better than in patients with lower Ki67 values may be hypothesized. Larger studies will be needed in order to investigate these findings further. © 2011 Fasching et al; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2021-07-19

Klinische Endpunkte in Real-World-Register-Studien - Hartkopf, Andreas D.; Emons, Julius; Lux, Michael P.; Taran, Florin Andrei; Overkamp, Friedrich; Tesch, Hans; Titzmann, Adriana; Pöschke, Patrik; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; et al. (Onkologe, 2020)
Background: The therapeutic options for the individual patient with metastatic breast cancer are becoming more and more specific. Evidence for therapeutic recommendations from clinical trials is not available for all treatment situations and patient subgroups. This makes the collection and evaluation of real-world data meaningful. Methods and aims: To provide recommendations for up-to-date treatments and participation in clinical trials for patients with metastatic breast cancer, the Prospective Academic Translational Research Network (PREAGNANT) has been established to optimize the oncological quality of care in the advanced therapeutic setting. The main aim is to systematically record medical care of patients with metastatic breast cancer in real life including the therapeutic effects and side effects of the different treatment strategies, to monitor the quality of life changes during therapy, to identify patients who could participate in a clinical drug study and to enable a targeted therapy based on molecular structures of breast cancer patients. Conclusion: This article presents a summary of the PRAEGNANT network and sheds light on the question of the portability of the various endpoints from clinical trials into the real world treatment situation.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Artificial intelligence; Big data; Clinical decision-making; Evidence-based medicine; Information systems

KNOCK-OUT OF THE HUMAN ENDOGENOUS RETROVIRUS ERV3 USING CRISPR/CAS9 TECHNOLOGY - Hübner, Hanna; Fahlbusch, Fabian B.; Ekici, Arif Bülent; Vasileiou, Georgia; Beckmann, Matthias; Strick, Reiner; Rübner, Matthias (2016)
EVALuna2:9327

Knowledge and attitudes regarding medical research studies among patients with breast cancer and gynecological diseases - Lux, Michael P.; Hildebrandt, Thomas; Knetzger, Sandra-Maria; Schrauder, Michael G.; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Fasching, Peter; Beckmann, Matthias; Thiel, Falk (BMC Cancer, 2015)
Medical research studies are becoming increasingly important for optimizing the prevention, diagnosis and treatment of illnesses. Participation in research studies can have many benefits for patients. In randomized and controlled clinical studies, they can receive the best possible medical care currently available. However, only a small proportion of patients nowadays are treated within the framework of medical research. The primary endpoint of this study was to discover what level of knowledge patients have about clinical studies and how they currently perceive them, in order to identify ways of optimizing the information provided about studies from the patients' point of view.The study included 2546 patients (breast cancer 21.6%, gynecological cancer 8.3%, obstetrics 32.7%, endometriosis 7.8%, fertility treatment 3.2%, other benign gynecological illnesses 19.2%, no information for 7.2%) in the outpatient clinic (45.2%) and in the in-patient sector (54.8%) at the Department of Gynecology at Erlangen University Hospital and associated centers. In the single-center study, conducted between January 2011 and January 2012, the patients were asked about their level of knowledge regarding the background to medical research studies and the ways in which they are carried out and used. The patients were also asked how they perceived medical studies and how they thought study conditions might be optimized. The three-page questionnaire was included in the feedback sheet received by patients as part of the hospital's quality management system.As a whole, the group only had moderate knowledge about clinical studies. A majority of the respondents considered that studies were valuable (91.6%), but only a few were also willing to take part in them (58.4%). Knowledge and willingness to participate strongly depended on age (P < 0.001), educational level (P < 0.001) and patient group (P < 0.001). Most patients would prefer to decide about participating in studies through a discussion with their outpatient physicians.The information that patients have about clinical studies affects whether they participate in them. It is therefore extremely important for patients to be well informed, for their anxieties about participation to be relieved, and for the benefits of participation to be explained to them.
EVALuna2:17441

Korrelate der Depressivität von Müttern von Grundschulkindern - Zalan, Vera; Ziegler, Clara; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (50. Jahreskongress der Deutschen Gesellschaft für Psychologie, 2016)

Labour Induction with Misoprostol in German Obstetric Clinics: What Are the Facts on Such Use? - Kehl, Sven; Weiss, Christel; Rath, Werner; Schneider, Michael; Stumpfe, Florian; Faschingbauer, Florian; Beckmann, Matthias; Stelzl, Patrick (Geburtshilfe und Frauenheilkunde, 2021)
Subject While the synthetic prostaglandin E1 analogue misoprostol is the most effect labour induction agent, its use is off-label for the most part. For this reason, and in view of its potential adverse effects and varying approaches to its administration, the drug has recently once again become a focus of critical attention. The objective of this survey was thus to establish a record of labour induction with misoprostol in German clinics and determine the impact of the negative reporting on everyday obstetric practice.
CRIS-Team WoS Importer:2021-09-03

Lack of evidence for effects of lockdowns on stillbirth rates during the SARS-CoV-2 pandemic in Bavaria: analysis of the Bavarian perinatal survey from 2010 to 2020 - Stumpfe, Florian; Schneider, Michael; Antoniadis, Sophia; Mayr, Andreas; Fleckenstein, Tobias; Staerk, Christian; Kehl, Sven; Hermanek, Peter; Boehm, Julian; Scharl, Anton; Beckmann, Matthias; Hein, Alexander (Archives of Gynecology and Obstetrics, 2022)
Background: Internationally, potential effects of national SARS-CoV-2-related lockdowns on stillbirth rates have been reported, but data for Germany, including risk factors for fetal pregnancy outcome, are lacking. The aim of this study is to compare the stillbirth rates during the two first lockdown periods in 2020 with previous years from 2010 to 2019 in a large Bavarian cohort. Methods: This study is a secondary analysis of the Bavarian perinatal data from 2010 to 2020, including 349,245 births. Univariate and multivariable regression analyses were performed to investigate the effect of two Bavarian lockdowns on the stillbirth rate in 2020 compared to the corresponding periods from 2010 to 2019. Results: During the first lockdown, the stillbirth rate was significantly higher compared to the reference period (4.04 vs. 3.03 stillbirths per 1000 births; P = 0.03). After adjustment for seasonal and long-term trends, this effect can no longer be observed (P = 0.2). During the second lockdown, the stillbirth rate did not differ in univariate (3.46 vs. 2.93 stillbirths per 1000 births; P = 0.22) as well as in multivariable analyses (P = 0.68), compared to the years 2010 to 2019. Conclusion: After adjustment for known long-term effects, in this study we did not find evidence that the two Bavarian lockdowns had an effect on the rate of stillbirths.
CRIS-Team Scopus Importer:2022-11-25
Keywords: COVID-19; Stillbirths; Stillborn

Large-scale evaluation of common variation in regulatory T cell-related genes and ovarian cancer outcome - Charbonneau, Bridget; Moysich, Kirsten B.; Kalli, Kimberly R.; Oberg, Ann L.; Vierkant, Robert A.; Fogarty, Zachary C.; Block, Matthew S.; Maurer, Matthew J.; Goergen, Krista M.; Fridley, Brooke L.; Cunningham, Julie M.; Rider, David N.; et al. (Cancer Immunology Research, 2014)
The presence of regulatory T cells (Treg) in solid tumors is known to play a role in patient survival in ovarian cancer and other malignancies. We assessed inherited genetic variations via 749 tag single-nucleotide polymorphisms (SNP) in 25 Treg-associated genes (CD28, CTLA4, FOXP3, IDO1, IL10, IL10RA, IL15, 1L17RA, IL23A, IL23R, IL2RA, IL6, IL6R, IL8, LGALS1, LGALS9, MAP3K8, STAT5A, STAT5B, TGFB1, TGFB2, TGFB3, TGFBR1, TGRBR2, and TGFBR3) in relation to ovarian cancer survival. We analyzed genotype and overall survival in 10,084 women with invasive epithelial ovarian cancer, including 5,248 high-grade serous, 1,452 endometrioid, 795 clear cell, and 661 mucinous carcinoma cases of European descent across 28 studies from the Ovarian Cancer Association Consortium (OCAC). The strongest associations were found for endometrioid carcinoma and IL2RA SNPs rs11256497 [HR, 1.42; 95% confidence interval (CI), 1.22-1.64; P = 5.7 × 10(-6)], rs791587 (HR, 1.36; 95% CI, 1.17-1.57; P = 6.2 × 10(-5)), rs2476491 (HR, = 1.40; 95% CI, 1.19-1.64; P = 5.6 × 10(-5)), and rs10795763 (HR, 1.35; 95% CI, 1.17-1.57; P = 7.9 × 10(-5)), and for clear cell carcinoma and CTLA4 SNP rs231775 (HR, 0.67; 95% CI, 0.54-0.82; P = 9.3 × 10(-5)) after adjustment for age, study site, population stratification, stage, grade, and oral contraceptive use. The rs231775 allele associated with improved survival in our study also results in an amino acid change in CTLA4 and previously has been reported to be associated with autoimmune conditions. Thus, we found evidence that SNPs in genes related to Tregs seem to play a role in ovarian cancer survival, particularly in patients with clear cell and endometrioid epithelial ovarian cance
EVALuna2:9223

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair - Day, Felix R.; Ruth, Katherine S.; Thompson, Deborah J.; Lunetta, Kathryn L.; Pervjakova, Natalia; Chasman, Daniel I.; Stolk, Lisette; Finucane, Hilary K.; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tonu; Johnson, Andrew D.; et al. (Nature Genetics, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in 70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk ( 6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.
EVALuna2:17562

Lifetime ovulatory years and risk of epithelial ovarian cancer: a multinational pooled analysis - Fu, Zhuxuan; Brooks, Maria Mori; Irvin, Sarah; Jordan, Susan; Aben, Katja K. H.; Anton-Culver, Hoda; Bandera, Elisa; Beckmann, Matthias; Berchuck, Andrew; Brooks-Wilson, Angela; Chang-Claude, Jenny; Cook, Linda S.; et al. (Journal of the National Cancer Institute, 2023)
Background The role of ovulation in epithelial ovarian cancer (EOC) is supported by the consistent protective effects of parity and oral contraceptive use. Whether these factors protect through anovulation alone remains unclear. We explored the association between lifetime ovulatory years (LOY) and EOC. Methods LOY was calculated using 12 algorithms. Odds ratios (ORs) and 95% confidence intervals (CIs) estimated the association between LOY or LOY components and EOC among 26 204 control participants and 21 267 case patients from 25 studies. To assess whether LOY components act through ovulation suppression alone, we compared beta coefficients obtained from regression models with expected estimates assuming 1 year of ovulation suppression has the same effect regardless of source. Results LOY was associated with increased EOC risk (OR per year increase = 1.014, 95% CI = 1.009 to 1.020 to OR per year increase = 1.044, 95% CI = 1.041 to 1.048). Individual LOY components, except age at menarche, also associated with EOC. The estimated model coefficient for oral contraceptive use and pregnancies were 4.45 times and 12- to 15-fold greater than expected, respectively. LOY was associated with high-grade serous, low-grade serous, endometrioid, and clear cell histotypes (ORs per year increase = 1.054, 1.040, 1.065, and 1.098, respectively) but not mucinous tumors. Estimated coefficients of LOY components were close to expected estimates for high-grade serous but larger than expected for low-grade serous, endometrioid, and clear cell histotypes. Conclusions LOY is positively associated with nonmucinous EOC. Differences between estimated and expected model coefficients for LOY components suggest factors beyond ovulation underlie the associations between LOY components and EOC in general and for non-HGSOC.
CRIS-Team WoS Importer:2023-04-21

Limited Effects of SARS-CoV-2 Pandemic-related Lockdowns and Reduced Population Mobility on Preterm Birth Rates: A Secondary Analysis of Bavarian Obstetric Quality Parameters from 2010 to 2020 - Stumpfe, Florian; Schneider, Michael Oliver; Hein, Alexander; Faschingbauer, Florian; Kehl, Sven; Hermanek, Peter; Boehm, Julian; Scharl, Anton; Beckmann, Matthias; Staerk, Christian; Mayr, Andreas (Geburtshilfe und Frauenheilkunde, 2022)
Introduction International studies on preterm birth rates during COVID-19 lockdowns report different results. This study examines preterm birth rates during lockdown periods and the impact of the mobility changes of the population in Bavaria, Germany. Material and Methods This is a secondary analysis of centrally collected data on preterm births in Bavaria from 2010 to 2020. Preterm births (< 37 weeks) in singleton and twin pregnancies during two lockdowns were compared with corresponding periods in 2010 - 2019. Fisher & apos;s exact test was used to compare raw prevalence between groups. Potential effects of two fixed lockdown periods and of variable changes in population mobility on preterm birth rates in 2020 were examined using additive logistic regression models, adjusting for long-term and seasonal trends. Results Unadjusted preterm birth rates in 2020 were significantly lower for singleton pregnancies during the two lockdown periods (Lockdown 1: 5.71% vs. 6.41%; OR 0.88; p < 0.001; Lockdown 2: 5.71% vs. 6.60%; OR = 0.86; p < 0.001). However, these effects could not be confirmed after adjusting for long-term trends (Lockdown 1: adj. OR = 0.99; p = 0.73; Lockdown 2: adj. OR = 0.96; p = 0.24). For twin pregnancies, differences during lockdown were less marked (Lockdown 1: 52.99% vs. 56.26%; OR = 0.88; p = 0.15; Lockdown 2: 58.06% vs. 58.91%; OR = 0.97; p = 0.70). Reduced population mobility had no significant impact on preterm birth rates in singleton pregnancies (p = 0.14) but did have an impact on twin pregnancies (p = 0.02). Conclusions Reduced preterm birth rates during both lockdown periods in 2020 were observed for singleton and twin pregnancies. However, these effects are reduced when adjusting for long-term and seasonal trends. Reduced population mobility was associated with lower preterm birth rates in twin pregnancies.
CRIS-Team WoS Importer:2022-07-29

Local and Systemic Therapies for Breast Cancer Patients: Reducing Short-term Symptoms with the Methods of Integrative Medicine - Hack, Carolin; Voiss, P.; Lange, S.; Paul, A. E.; Conrad, S.; Dobos, G. J.; Beckmann, Matthias; Kuemmel, S. (Geburtshilfe und Frauenheilkunde, 2015)
With improved prognosis due to advances in the diagnosis and therapy of breast cancer, physicians and therapists now focus on aspects such as quality of life and the management of side effects from breast cancer treatment. Therapy- and disease-related side effects often reduce the patient's quality of life and can place a further burden on patients, with non-compliance or discontinuation of therapy a potential consequence. Study data have shown that therapy- and disease-related side effects can be reduced using the methods of integrative medicine. Reported benefits include improving patients' wellbeing and quality of life, reducing stress, and improving patients' mood, sleeping patterns and capacity to cope with disease. Examining the impact of integrative medicine on the side effects of cancer treatment would be beyond the scope of this review. This article therefore looks at short-term side effects of cancer treatment which are usually temporary and occur during or after local and systemic therapy. The focus is on mind-body medicine, acupuncture and classic naturopathic treatments developed by Sebastian Kneipp as complementary therapies. The latter includes hydrotherapy, phytotherapy, nutritional therapy, exercise therapy and a balanced lifestyle.
EVALuna2:17601

Logbooks alone are not enough: initial experience with implementing a logbook for medical students in a clinical internship in gynecology and obstetrics - Jud, Sebastian; Cupisti, Susanne; Frobenius, Wolfgang; Benn, Sigrid; Winkler, Andrea; Antoniadis, Sophia; Beckmann, Matthias; Heindl, Felix (European Journal of Medical Research, 2020)
BACKGROUND: Logbooks are being increasingly widely used as a means of improving medical education and further training. They will in all probability continue to be mandatory in the Practical Year (PJ) in Germany even after the upcoming amendment of the Medical Licensing Regulations (ÄAppO). However, there are different approaches to their design and use, and these are also currently undergoing considerable change. This study for the first time examines and discusses the influence of logbooks on students' evaluation of a gynecology internship. METHODS: The study was based on a well-established two-part 1-week internship course, with initially unstructured morning classes on wards and duty areas, along with precisely planned afternoon classes with skills training by peer teachers and seminars supervised by duty-exempted physicians. The postgraduate lecturers were prepared for the introduction of the logbook in a special course, and the aim was to optimize morning classes by introducing learning objectives adapted to the respective locations. The effects over 38 weeks of practical training were examined in evaluations by 235 prospectively group-randomized students with and without logbooks (n = 166 and n = 66, respectively; three datasets were not evaluable). RESULTS: In the cohort comparison, the logbook group responded significantly more positively toward the internship at the start of the course (P = 0.046). In the final evaluation, however, medical supervision during the entire internship was rated significantly more poorly (P = 0.007). The logbook cohort also considered that guidance based on learning objectives was significantly worse, as was the extent to which wards and duty areas were prepared for the students (P = 0.001 and P = 0.029). CONCLUSIONS: Introducing a logbook to optimize clinical teaching in internships may raise expectations that cannot always be met. In addition to adapting the learning objectives to a general framework that is less favorable in comparison with the Practical Year, the least that is required appears to be simultaneous and continuous mentoring of the lecturers, as well as an increase in staffing resources.
CRIS-Team Scopus Importer:2020-05-26
Keywords: Gynecology; Internship; Logbook; Teaching

Longitudinal Assessment of Examiner Experience and the Accuracy of Sonographic Fetal Weight Estimation at Term - Faschingbauer, Florian; Heimrich, Jutta; Raabe, Eva; Kehl, Sven; Schneider, Michael; Schmid, Matthias; Beckmann, Matthias; Hepp, Tobias; Luebke, Anika; Mayr, Andreas; Schild, Ralf L. (Journal of Ultrasound in Medicine, 2017)
OBJECTIVES: To evaluate the influence of examiner experience on the accuracy of sonographic weight estimation and to further analyze examiners' individual learning curves. METHODS: In this multicenter study, 4613 sonographic weight estimations performed by 18 examiners at the beginning of their ultrasound training were included. To assess the effect of experience on the accuracy of weight estimation, a multivariable mixed regression model analysis was performed, with percentage error and absolute percentage error as outcome variables and the examiner, the examiner's experience (number of examinations), birth weight, gestational age, scan-to-delivery interval, and maternal body mass index as fixed effects and the perinatal center as random intercepts. To further analyze the individual learning curves of the examiners, the cumulative summation technique was used. RESULTS: Regression analyses showed a significant influence of the number of examinations on the accuracy of sonographic weight estimation after adjustment for the above-mentioned parameters (P < .001). A typical learning curve with improving accuracy was found until approximately 200 examinations. Between 200 and 300 examinations, the diagnostic performance started to deteriorate again, with a continuous decrease until the end of the study period. Cumulative summation charts representing individual learning curves varied greatly between different examiners. CONCLUSIONS: These findings indicate the great importance of continuous quality control systems in sonographic weight estimation.
EVALuna2:34214

Longitudinal Course of Short-Term Variation and Doppler Parameters in Early Onset Growth Restricted Fetuses - Baier, Friederike; Weinhold, Leonie; Stumpfe, Florian; Kehl, Sven; Pretscher, Jutta; Bayer, Christian M.; Topal, Nalan; Pontones, Constanza; Mayr, Andreas; Schild, Ralf Lothar; Schmid, Matthias; Beckmann, Matthias; et al. (Ultraschall in der Medizin, 2019)
PURPOSE: To evaluate the longitudinal pattern of fetal heart rate short term variation (STV) and Doppler indices and their correlation to each other in severe growth restricted (IUGR) fetuses. MATERIALS AND METHODS: In this retrospective study, pregnancies with a birth weight below the 10th percentile, born between 24 and 34 gestational weeks with serial Doppler measurements in combination with a computerized CTG (cCTG) with calculated STV were included. Longitudinal changes of both Doppler indices and STV values were evaluated with generalized additive models, adjusted for gestational age and the individual. For all measurements the frequency of abnormal values with regard to the time interval before delivery and Pearson correlations between Doppler indices and STV values were calculated. RESULTS: 41 fetuses with a total of 1413 observations were included. Over the course of the whole study period, regression analyses showed no significant change of STV values (p = 0.38). Only on the day of delivery, a prominent decrease was observed (mean STV d28-22: 7.97 vs. mean STV on day 0: 6.8). Doppler indices of UA and MCA showed a continuous, significant deterioration starting about three weeks prior to delivery (p = 0.007; UA and p < 0.001, MCA). Correlation between any Doppler index and STV values was poor. CONCLUSION: Fetal heart rate STV does not deteriorate continuously. Therefore, cCTG monitoring should be performed at least daily in these high-risk fetuses. Doppler indices of umbilical artery (UA) and middle cerebral artery (MCA), however, showed continuous deterioration starting about 3 weeks prior to delivery.
EVALuna2:212318

Longitudinal z Score Distribution in Sonographic Fetal Biometry: Influence of Examiner and Experience - Faschingbauer, Florian; Heimrich, Jutta; Raabe, Eva; Kehl, Sven; Schneider, Michael; Schmid, Matthias; Beckmann, Matthias; Schild, Ralf L.; Mayr, Andreas (Journal of Ultrasound in Medicine, 2017)
OBJECTIVES: To analyze the influence of examiners and their experience on the quality of biometric measurements via the evolution of z scores in a longitudinal multicenter study. METHODS: This retrospective study included 4607 sonographic fetal biometric examinations performed by 18 examiners at the beginning of their sonography training. To analyze the quality of biometric measurements, z scores comparing the individual measurements with the expected values from a standard population were computed. To investigate the effect of examiners and their experience, we applied a multivariable regression analysis via generalized additive mixed models. RESULTS: Mean z scores for biparietal diameter, abdominal circumference, and femur length were statistically different from the expected value of 0 (P < .001); no significant differences were found for head circumference measurements. Regression analyses showed a significant effect of the number of examinations on the distribution of z scores for each type of measurement. This effect yielded z score values close to the expected value of 0 at 100 to 200 examinations for all biometric measurements, indicating good consistency with the distribution of values in the reference population. Near the end of the study period, an increasing tendency toward either overestimation (head circumference) or underestimation (biparietal diameter, abdominal circumference, and femur length) was observed. CONCLUSIONS: A longitudinal analysis of the z score distribution for quality control of biometry is feasible. A prospective and automatized use of this technique could help identify potential systematic errors and therefore improve the detection rate for high-risk pregnancies.
EVALuna2:34191

Long-Term Endurance Exercise in Humans Stimulates Cell Fusion of Myoblasts along with Fusogenic Endogenous Retroviral Genes In Vivo - Frese, Sebastian; Rübner, Matthias; Suhr, Frank; Konou, Thierry M.; Tappe, Kim A.; Toigo, Marco; Jung, Hans H.; Henke, Christine; Steigleder, Ruth; Strissel, Pamela; Hübner, Hanna; Beckmann, Matthias; et al. (PLoS ONE, 2015)
Myogenesis is defined as growth, differentiation and repair of muscles where cell fusion of myoblasts to multinucleated myofibers is one major characteristic. Other cell fusion events in humans are found with bone resorbing osteoclasts and placental syncytiotrophoblasts. No unifying gene regulation for natural cell fusions has been found. We analyzed skeletal muscle biopsies of competitive cyclists for muscle-specific attributes and expression of human endogenous retrovirus (ERV) envelope genes due to their involvement in cell fusion of osteoclasts and syncytiotrophoblasts. Comparing muscle biopsies from post- with the pre-competitive seasons a significant 2.25-fold increase of myonuclei/mm fiber, a 2.38-fold decrease of fiber area/nucleus and a 3.1-fold decrease of satellite cells (SCs) occurred. We propose that during the pre-competitive season SC proliferation occurred following with increased cell fusion during the competitive season. Expression of twenty-two envelope genes of muscle biopsies demonstrated a significant increase of putative muscle-cell fusogenic genes Syncytin-1 and Syncytin-3, but also for the non-fusogenic erv3. Immunohistochemistry analyses showed that Syncytin-1 mainly localized to the sarcolemma of myofibers positive for myosin heavy-chain isotypes. Cellular receptors SLC1A4 and SLC1A5 of Syncytin-1 showed significant decrease of expression in post-competitive muscles compared with the pre-competitive season, but only SLC1A4 protein expression localized throughout the myofiber. Erv3 protein was strongly expressed throughout the myofiber, whereas envK1-7 localized to SC nuclei and myonuclei. Syncytin-1 transcription factors, PPAR? and RXR?, showed no protein expression in the myofiber, whereas the pCREB-Ser133 activator of Syncytin-1 was enriched to SC nuclei and myonuclei. Syncytin-1, Syncytin-3, SLC1A4 and PAX7 gene regulations along with MyoD1 and myogenin were verified during proliferating or actively-fusing human primary myoblast cell cultures, resembling muscle biopsies of cyclists. Myoblast treatment with anti-Synycytin-1 abrogated cell fusion in vitro. Our findings support functional roles for ERV envelope proteins, especially Syncytin-1, contributing to cell fusion of myotubes.
EVALuna2:17549

Long-term outcome of patients with intermediate- and high-risk endometrial cancer after pelvic and paraaortic lymph node dissection: a comparison of laparoscopic vs. open procedure - Papathemelis, Thomas; Oppermann, Helen; Grafl, Stella; Gerken, Michael; Pauer, Armin; Scharl, Sophia; Scharl, Anton; Inwald, Elisabeth; Ignatov, Atanas; Ortmann, Olaf; Klinkhammer-Schalke, Monika; Hein, Alexander; et al. (Journal of Cancer Research and Clinical Oncology, 2020)
Objective: The primary therapy for intermediate- and high-risk endometrial cancer includes pelvic and paraaortic lymph node evaluation. Laparoscopic surgery is an increasingly popular intervention due to decreased risk and better short-term morbidity; however, a recent study casts doubt on the benefit of this approach in terms of oncological safety. In this cancer registry study, we sought to evaluate the benefit of laparoscopy versus laparotomy and retrospectively compared overall survival, recurrence rates, and recurrence-free survival among patients with intermediate- and high-risk endometrial cancer who underwent either laparoscopic or open surgery. Methods: This observational study included 419 patients who have been treated from 2011 to 2017. We employed Kaplan–Meier method, and univariable and multivariable Cox-regression to compare overall survival, recurrence rates, and recurrence-free survival in 110 patients, who underwent laparoscopic, with 309 patients, who underwent open surgery. To address the confounding bias in this retrospective study, we also performed a propensity score matching (PSM) analysis including 357 patients (laparoscopy: n = 107; open surgery: n = 250). Results: We found a benefit for laparoscopic over open surgery in patients with intermediate- and high-risk endometrial cancer for overall survival in both univariable (p = 0.002; PSM: p = 0.016) and multivariable analyses (p = 0.019; PSM: p = 0.007). In contrast, there was no statistically significant difference between both patient groups regarding the cumulative recurrence rates. A univariable analysis identified a significant benefit for laparoscopy regarding recurrence-free survival (p = 0.003; PSM: p = 0.029) but a multivariable analysis failed to confirm this finding (p = 0.108; PSM: p = 0.118). Conclusions: Our study provides evidence that laparoscopic systematic lymphadenectomy does not present a lower oncological efficacy than open surgery in the treatment of patients with endometrial cancer.
CRIS-Team Scopus Importer:2020-01-10
Keywords: Cancer registry study; Endometrial cancer; Laparoscopy; Laparotomy; Observational study; Overall survival; Pelvic and paraaortic lymphadenectomy

Low-dose methotrexate treatment in ectopic pregnancy: a retrospective analysis of 164 ectopic pregnancies treated between 2000 and 2008 - Lermann, Johannes; Segl, Petra; Jud, Sebastian; Beckmann, Matthias; Oppelt, Peter; Thiel, Falk; Renner, Stefan; Mueller, Andreas (Archives of Gynecology and Obstetrics, 2014)
Ectopic pregnancy is an acute, potentially life-threatening condition. The aim of this study was to compare the results of surgery and methotrexate treatment in women with ectopic pregnancy, along with a review of the literature.164 women with ectopic pregnancy, treated from 2000 to 2008 at the university gynecology department, were examined in a retrospective analysis. Patients with diagnosed ectopic pregnancy underwent one of the following treatments: Salpingotomy, salpingectomy or administration of a single dose of 30 mg methotrexate. The main outcome measures were treatment success rate, rate of patients wishing to have children after the ectopic pregnancy, and rates of pregnancy, live births, recurrent ectopic pregnancy, miscarriage, use of assisted reproduction and side effects.There were no significant differences in success rates between the groups (methotrexate 83.9 %, salpingotomy 88.2 %, salpingectomy 96.8 %). Significantly more patients in the salpingotomy group wished to become pregnant afterward than in the salpingectomy group. No significant differences were observed between the groups in the rates of intrauterine pregnancy, live births, recurrences, miscarriages, or side effects.With defined inclusion criteria, similar results can be achieved with low-dose single administration of 30 mg methotrexate in comparison with surgical treatment for ectopic pregnancy. On the basis of the data presented here, further research to establish optimal dosages for methotrexate is needed.
EVALuna2:17460

Low-Risk Women with Suspicious Microcalcifications in Mammography-Can an Additional Breast MRI Reduce the Biopsy Rate? - Pöschke, Patrik; Wenkel, Evelyn; Hack, Caroline; Beckmann, Matthias; Uder, Michael; Ohlmeyer, Sabine (Diagnostics, 2023)
Background: In the German Mammography Screening Program, 62% of ductal carcinoma in situ (DCIS) and 38% of invasive breast cancers are associated with microcalcifications (MCs). Vacuum-assisted stereotactic breast biopsies are necessary to distinguish precancerous lesions from benign calcifications because mammographic discrimination is not possible. The aim of this study was to investigate if breast magnetic resonance imaging (MRM) could assist the evaluation of MCs and thus help reduce biopsy rates. Methods: In this IRB-approved study, 58 women (mean age 58 +/- 24 years) with 59 suspicious MC clusters in the MG were eligible for this prospective single-center trial. Additional breast magnetic resonance imaging (MRI) was conducted before biopsy. Results: The breast MRI showed a sensitivity of 86%, a specificity of 84%, a positive predictive value (PPV) of 75% and a negative predictive value (NPV) of 91% for the differentiation between benign and malignant in these 59 MCs found with MG. Breast MRI in addition to MG could increase the PPV from 36% to 75% compared to MG alone. The MRI examination led to nine additional suspicious classified lesions in the study cohort. A total of 55% (5/9) of them turned out to be malignant. A total of 32 of 59 (54 %) women with suspicious MCs and benign histology were classified as non-suspicious by MRI. Conclusion: An additionally performed breast MRI could have increased the diagnostic reliability in the assessment of MCs. Further, in our small cohort, a considerable number of malignant lesions without mammographically visible MCs were revealed.
CRIS-Team WoS Importer:2023-04-14

Macromastia: an economic burden? A disease cost analysis based on real-world data in Germany - Jud, Sebastian; Brendle-Behnisch, Anne; Hack, Carolin; Preuss, Caroline; Arkudas, Andreas; Horch, Raymund E.; Beckmann, Matthias; Lux, Michael P. (Archives of Gynecology and Obstetrics, 2020)
Purpose: Symptomatic macromastia causes physical and psychological problems that can lead to restrictions in the patients’ social and working lives and a reduced quality of life. Associated medical treatments also have a considerable impact on health-care costs. Several studies have assessed these costs, but the total disease costs of macromastia have never been evaluated on the basis of real-world data. Methods: The data for 76 patients who underwent reduction mammoplasty between 2008 and 2016 were collected using a two-part questionnaire (preoperative and postoperative), as well as the patient files. Topics surveyed, besides demographic data, included physician visits, medical imaging, medical procedures, medical treatments, rehabilitation and convalescent measures, drug intake, medical aids, exercise activity, and sick leave days before surgery, to calculate the costs per year of conservative treatment of symptomatic macromastia. Results: The mean time from start of symptoms to surgery was 11.82 years. The data for this group of patients with symptomatic macromastia show that costs per patient amount to €1677.55 per year. These costs include medical consultation, radiological imaging, medical treatments and procedures, physical therapy and rehabilitation, medication, special brassieres, exercise classes costs for sick leave due to problems with macromastia, and travel expenses. Conclusions: These results show that considerable health-care costs arise due to macromastia with conservative treatment. Overall, macromastia costs €1677.55 per patient/year. In particular, lost productivity due to sick days and the costs of physiotherapy are factors driving the high costs.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Breast reduction mammoplasty; Conservative treatment; Disease costs; Gigantomastia; Health care; Macromastia

Maillard Reaction Products Inhibit Oxidation of Human Low-Density Lipoproteins in Vitro - Dittrich, Ralf; El-Massry, Khaled Farouk; Kunz, Katrin; Rinaldi, Francesco; Peich, Carlo; Beckmann, Matthias; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2003)
Dietary intake of antioxidants has been associated with a reduced risk of cardiovascular diseases, which is very likely caused by their capability of prevent oxidation of low-density lipoproteins (LDL). During food processing and storage, substances with antioxidative properties are formed by Maillard reactions. In this study, the activity of Maillard products to inhibit copper-induced oxidation of human LDL in vitro was investigated. D-Glucose was heated with an equimolar amount of glycine, L-lysine, or L-arginine, for 1 h under reflux. The increase of the antioxidative activity (AOA) of the Maillard mixtures was highly significant compared to the control mixtures. Additionally, two defined Maillard products with amino reductone structure were tested. 3-Hydroxy-4-(morpholino)-3-buten-2-one (1) and amino hexose reductone (2) showed a significant and dose dependent AOA. Compound 1 was about half as active as ascorbic acid, which served as positive control. Thus, it can be concluded that Maillard products, particularly those with amino reductone structure, have the strong potential to inhibit LDL oxidation.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.mailla_0
Keywords: Amino hexose reductone; Amino reductones; LDL oxidation; Low-density lipoprotein; Maillard reaction

Major and minor complications after anterior rectal resection for deeply infiltrating endometriosis - Renner, Stefan; Kessler, Hermann; Topal, Nalan; Proske, Kim; Adler, Werner; Burghaus, Stefanie; Haupt, Werner; Beckmann, Matthias; Lermann, Johannes (Archives of Gynecology and Obstetrics, 2017)
The aim of the present study was to analyze major and minor complications-including long-term impairment of intestinal, bladder, and sexual function-following surgery for deeply infiltrating endometriosis using anterior rectal resection.Patients who had undergone anterior rectal resection due to endometriosis between 2001 and 2011 were included (n = 113). Clinical and surgical data, as well as minor and major complications, were recorded. A questionnaire was sent to the patients and also to a healthy control group (n = 100).Major complications occurred in 15.9% of cases and minor complications in 15%. Patients with postoperative ileostomies (n = 8) initially had ultralow anastomoses significantly more often. The questionnaire response rate was 77%, with a mean follow-up period of 85.9 months. Weak urinary flow was reported by 22.4% of the patients: a feeling of residual urine by 18.4%; more than one bowel movement/day by 57.5%; and insufficient lubrication during intercourse by 36.5%. These results differed significantly from the control group. Subgroup analysis showed no statistical associations between questionnaire responses and major or minor complications, ultralow anastomoses, bilateral dissection of the sacrouterine ligaments, or dissection of the vagina and rectovaginal space.The major complication rate was consistent with the literature, but there were fewer minor complications. Patients with bowel anastomoses below 6 cm (ultralow) should receive information postoperatively about the high risk of insufficiency and should be closely monitored. The high rate of bladder, bowel, and sexual function impairment, and inadequate data make further prospective studies on this topic necessary.
EVALuna2:15312

Major and minor complications after resection without bowel resection for deeply infiltrating endometriosis - Lermann, Johannes; Topal, Nalan; Adler, Werner; Hildebrandt, Thomas; Renner, Stefan P.; Beckmann, Matthias; Burghaus, Stefanie (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: To analyze major and minor complications following surgery for deeply infiltrating endometriosis including long-term impairment of intestinal, bladder, and sexual function. METHODS: Patients who had undergone resection for deeply infiltrating endometriosis without anterior rectal resection between 2001 and 2011 were included (n = 134). Clinical and surgical data, as well as minor and major complications, were recorded. A questionnaire was sent to the patients and to a healthy control group (n = 100). RESULTS: Major complications occurred in 3.7% and minor complications in 12.7% of the patients. Surgical revision was necessary in five cases. The questionnaire response rate was 66.4%, with a mean follow-up period of 75.6 months. Weak urinary flow was reported by 26.4% of the patients; a feeling of residual urine by 16.1%; constipation by 13.5%; more than one bowel movement/day by 16.9%; insufficient lubrication during intercourse by 30.3%. The findings for weak urinary flow, feeling of residual urine, and insufficient lubrication differed significantly from the control group. Subgroup analysis did not identify any statistical associations between questionnaire responses and dyspareunia or dysmenorrhea as reasons for surgery, or previous endometriosis surgery in the patient's history. CONCLUSIONS: The major and minor complication rates were consistent with or lower than the literature data. Few studies have investigated complication rates associated with treatment for endometriosis in the sacrouterine ligaments and/or the rectovaginal septum. The high rates of impaired bladder function and sexual function after endometriosis surgery, as well as inadequate data, make further prospective studies on this topic necessary.
EVALuna2:35657

Mammary carcinoma in men - Preuss, Caroline; Wunderle, Marius; Hack, Carolin; Beckmann, Matthias; Wenkel, Evelyn; Jud, Sebastian; Heindl, Felix (Deutsche Medizinische Wochenschrift, 2023)
CRIS-Team WoS Importer:2023-03-31

Mammographic Density and Prediction of Nodal Status in Breast Cancer Patients - Hack, Carolin; Häberle, Lothar; Geisler, K.; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Fasching, Peter; Uder, Michael; Wachter, David; Jud, Sebastian; Löhberg, Christian; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: Nodal status remains one of the most important prognostic factors in breast cancer. The cellular and molecular reasons for the spread of tumor cells to the lymph nodes are not well understood and there are only few predictors in addition to tumor size and multifocality that give an insight into additional mechanisms of lymphatic spread. Aim of our study was therefore to investigate whether breast characteristics such as mammographic density (MD) add to the predictive value of the presence of lymph node metastases in patients with primary breast cancer. Methods: In this retrospective study we analyzed primary, metastasis-free breast cancer patients from one breast center for whom data on MD and staging information were available. A total of 1831 patients were included into this study. MD was assessed as percentage MD (PMD) using a semiautomated method and two readers for every patient. Multiple logistic regression analyses with nodal status as outcome were used to investigate the predictive value of PMD in addition to age, tumor size, Ki-67, estrogen receptor (ER), progesterone receptor (PR), grading, histology, and multi-focality. Results: Multifocality, tumor size, Ki-67 and grading were relevant predictors for nodal status. Adding PMD to a prediction model which included these factors did not significantly improve the prediction of nodal status (p = 0.24, likelihood ratio test). Conclusion: Nodal status could be predicted quite well with the factors multifocality, tumor size, Ki-67 and grading. PMD does not seem to play a role in the lymphatic spread of tumor cells. It could be concluded that the amount of extracellular matrix and stromal cell content of the breast which is reflected by MD does not influence the probability of malignant breast cells spreading from the primary tumor to the lymph nodes. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: breast cancer; estrogen receptor; Ki-67; mammographic density; nodal status; progesterone receptor

Mammographic Density and Prognosis in Patients with primary Breast Cancer - Loss of Risk with increasing Age - Heindl, Felix; Fasching, Peter; Hein, Alexander; Hack, Caroline; Heusinger, K.; Gaß, Paul; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Erber, Ramona; Beckmann, Matthias; Meyer, J.; Häberle, Lothar; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Mammographic density and prognosis in primary breast cancer patients - Heindl, Felix; Fasching, Peter; Hein, Alexander; Hack, Carolin; Heusinger, Katharina; Gaß, Paul; Pöschke, Patrik; Stübs, Frederik; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Erber, Ramona; Beckmann, Matthias; et al. (BREAST, 2021)
Purpose: Mammographic density (MD) is one of the strongest risk factors for breast cancer (BC). However, the influence of MD on the BC prognosis is unclear. The objective of this study was therefore to investigate whether percentage MD (PMD) is associated with a difference in disease-free or overall survival in primary BC patients. Methods: A total of 2525 patients with primary, metastasis-free BC were followed up retrospectively for this analysis. For all patients, PMD was evaluated by two readers using a semi-automated method. The association between PMD and prognosis was evaluated using Cox regression models with disease-free survival (DFS) and overall survival (OS) as the outcome, and the following adjustments: age at diagnosis, year of diagnosis, body mass index, tumor stage, grading, lymph node status, hormone receptor and HER2 status. Results: After median observation periods of 9.5 and 10.0 years, no influence of PMD on DFS (p = 0.46, likelihood ratio test (LRT)) or OS (p = 0.22, LRT), respectively, was found. In the initial unadjusted analysis higher PMD was associated with longer DFS and OS. The effect of PMD on DFS and OS disappeared after adjustment for age and was caused by the underlying age effect. Conclusions: Although MD is one of the strongest independent risk factors for BC, in our collective PMD is not associated with disease-free and overall survival in patients with BC.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Breast cancer; Breast cancer risk; Mammographic breast density; Mammographic density; Prognosis

Mammographic density as a risk factor for breast cancer in a German case-control study - Heusinger, Katharina; Löhberg, Christian; Häberle, Lothar; Jud, Sebastian; Klingsiek, Peter; Hein, Alexander; Bayer, Christian M.; Rauh, Claudia; Uder, Michael; May, Matthias; Adamietz, Boris; Schulz-Wendtland, Rüdiger; et al. (European Journal of Cancer Prevention, 2011)
Mammographic percent density (MD) is recognized as one of the strongest risk factors associated with breast cancer. This matched case-control study investigated whether MD represents an independent risk factor. Mammograms were obtained from 1025 breast cancer patients and from 520 healthy controls. MD was measured using a quantitative computer-based threshold method (0-100%). Breast cancer patients had a higher MD than healthy controls (38 vs. 32%, P<0.01). MD was significantly higher in association with factors such as age over 60 years, body mass index (BMI) of 25-30 kg/m, nulliparity or low parity (one to two births). Average MD was inversely associated with age, BMI, parity and positively associated with age at first full-term pregnancy. MD was higher in women with at least one first-degree relative affected, but only among patients and not in the group of healthy controls (P<0.01/P=0.61). In women with an MD of 25% or more, the risk of breast cancer was doubled compared with women with an MD of less than 10% (odds ratio: 2.1; 95% confidence interval: 1.3-3.4; P<0.01); in the postmenopausal subgroup, the risk was nearly tripled (odds ratio: 2.7; 95% confidence interval: 1.6-4.7; P<0.001). This study provides further evidence that MD is an important risk factor for breast cancer. These results indicate strong associations between MD and the risk of breast cancer in a matched case-control study in Germany © 2010 Wolters Kluwer Health.
CRIS-Team Scopus Importer:2021-07-19

Mammographic density is the main correlate of tumors detected on ultrasound but not on mammography - Haeberle, Lothar; Fasching, Peter; Brehm, Barbara; Heusinger, Katharina; Jud, Sebastian; Löhberg, Christian; Hack, Carolin; Preuss, Caroline; Lux, Michael P.; Hartmann, Arndt; Vachon, Celine M.; Meier-Meitinger, Martina; et al. (International Journal of Cancer, 2016)
Although mammography screening programs do not include ultrasound examinations, some diagnostic units do provide women with both mammography and ultrasonography. This article is concerned with estimating the risk of a breast cancer patient diagnosed in a hospital-based mammography unit having a tumor that is visible on ultrasound but not on mammography. A total of 1,399 women with invasive breast cancer from a hospital-based diagnostic mammography unit were included in this retrospective study. For inclusion, mammograms from the time of the primary diagnosis had to be available for computer-assisted assessment of percentage mammographic density (PMD), as well as Breast Imaging Reporting and Data System (BIRADS) assessment of mammography. In addition, ultrasound findings were available for the complete cohort as part of routine diagnostic procedures, regardless of any patient or imaging characteristics. Logistic regression analyses were conducted to identify predictors of mammography failure, defined as BIRADS assessment 1 or 2. The probability that the visibility of a tumor might be masked at diagnosis was estimated using a regression model with the identified predictors. Tumors were only visible on ultrasound in 107 cases (7.6%). PMD was the strongest predictor for mammography failure, but age, body mass index and previous breast surgery also influenced the risk, independently of the PMD. Risk probabilities ranged from 1% for a defined low-risk group up to 40% for a high-risk group. These findings might help identify women who should be offered ultrasound examinations in addition to mammography.
EVALuna2:6818

Management of Cervical Intraepithelial Neoplasia in Pregnant Women - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Schulmeyer, Carla; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; et al. (Anticancer Research, 2023)
BACKGROUND/AIM: The aims of the present study were to evaluate the accuracy of colposcopic findings, investigate the way in which untreated cervical intraepithelial neoplasia (CIN) 2/3 develops during pregnancy, and identify factors associated with regression, persistence, or progression rates. PATIENTS AND METHODS: In a tertiary gynecology and obstetrics department, 655 pregnant women were seen for colposcopy. The most common reason for referral was abnormal cytology findings. The follow-up findings were analyzed retrospectively on the basis of colposcopic findings and cytological and histological tests. RESULTS: The rate of accuracy for major colposcopic findings was 89.2%. Among the colposcopic findings considered "suspicious for invasion" were invasive carcinoma in 42.9% and CIN 3 in 57.1%. The persistence of CIN 3 postpartum was 80% and the rate of progression 4.1%. The rate of regression for CIN 3 was 21.9%. For CIN 2, the rate of persistence was 37.5%, with a regression rate of 31.3%. The rate of regression was higher after vaginal delivery in comparison with caesarean section. CONCLUSION: The accuracy rate of colposcopy is comparatively high, at 89.2%. This might be because pregnant women are seen by more experienced examiners in our dysplasia unit. The rate of progression is comparable with that in other studies. Vaginal delivery increases the regression rate. The newborns' birth weight or birth week did not affect the rates of regression or persistence.
CRIS-Team Scopus Importer:2023-07-07
Keywords: cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); mode of delivery; pregnancy; treatment

Management of Uterus bicornis unicollis with a right-sided Outflow Obstruction in a 13-year-old Girl - Lubrich, Hannah; Pontones, Constanza; Koch, Matthias; Fahlbusch, C.; Oppelt, Patricia; Beckmann, Matthias (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Management operations- und karzinombedingter Blutungen - Emons, Julius; Heindl, Felix; Hein, Alexander; Beckmann, Matthias (Gynäkologe, 2016)
Background: Bleeding is a symptom in many gynecologic and obstetric diseases. Perioperative hemorrhage and bleeding in cancer patients are extraordinary situations in gynecological patients. An acute abdomen in oncological patients also requires differential diagnosis of symptoms caused by advanced cancers. Perioperative hemorrhage: Perioperative gynecologic hemorrhage is still an acute emergency requiring immediate action. Preoperative identification of patients with increased bleeding risk by thorough anamnesis is essential. Local hemostasis and, if needed, systemic treatment for underlying coagulopathies are essential to treat acute intraabdominal bleeding. Postoperative bleeding is diagnosed by clinical and instrument-based techniques and demands immediate treatment. Tumor bleeding: Bleeding occurs in patients with early and end-stage gynecologic cancers and requires – depending on the underlying cancer and clinical stage – surgical, conservative, interventional, or radiotherapeutic treatment. Acute abdomen in cancer patients: For gynecologic oncologic patients, both tumor-associated and classic causes for acute abdomen must be taken into account.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Acute abdomen; Blood coagulation factors; Blood transfusion; Hemostasis; Postoperative hemorrhage

Maternal Attachment Style and her Perinatal Wellbeing Influence Early Childhood Development - Goecke, Tamme W.; Schoeberl, Gudrun; Beckmann, Matthias; Beetz, Andrea M. (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
An increasing number of children show signs of behavioral problems and dysregulation in early childhood. It is assumed that maternal depression and her attachment representations affect child development. This was investigated in a prospective study with 161 primiparae women. Via standardized questionnaires during the third trimester, 3 weeks, 6 months and 18 months postpartum, prenatal attachment of the mother to the unborn child, her general attachment style and postpartum depression as well as the child's dysregulation at 18 months were assessed. In the GLM, longer-lasting pre- and postpartum depressivity and insecure partnership attachment representation were associated with child dysregulation. Therefore, early detection of pre- and postpartum depression is important in order to support both the affected women and the children for better child development.
CRIS-Team WoS Importer:2022-07-29

Maternal depression and child development: A prospective analysis of consequences, risk and protective factors - Roetner, Jakob; Petry, Janna; Niekamp, Julia; Maschkel, Janina; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2022)
Maternal depression and child development: A prospective analysis of consequences, risk and protective factors Abstract. Objective: Maternal stress, specifically maternal mental health problems, are considered risk factors for child development. The literature suggests that prenatal depressive symptoms as well as depressive symptoms are a widespread phenomenon during the further development of the child and have repeatedly been shown to have adverse effects on child mental health outcomes. The present study examined the longitudinal relationships between maternal depression (prenatal, postnatal, during childhood and adolescence) and child mental health from childhood to adolescence. Possible risk and protective factors were also considered. Method: N = 112 mothers were assessed for depressive symptoms via a questionnaire at four different timepoints (prenatal, T1; postnatal, T2; during childhood, T3; during adolescence, T4). Children's externalizing and internalizing symptoms (50.9 % girls) were assessed by their mothers both during childhood (M = 7.68, SD = 0.76 years) and during adolescence (M = 13.23, SD = 0.27 years). We evaluated the relationships between maternal depressive symptoms and children's externalizing/internalizing symptoms using multiple regression models and analyzed possible risk and protective factors using moderation analysis. Results: Externalizing/Internalizing symptoms were not directly associated with maternal depressive symptoms, while associations between such symptoms and maladaptive behavior were found in adolescents. The socioeconomic status of families showed a different risk profile for prenatal and postnatal depressive symptoms. The IQ of the children proved to be a risk factor for internalizing symptoms. Conclusions: Maternal depressive symptoms at any time during child development - in combination with further risk factors - have an impact on child mental health. The early identification of maternal symptoms followed by interventions to differentiate between prenatal and postnatal depression - especially in the context of socioeconomic status - are highly relevant for child development.
CRIS-Team WoS Importer:2022-04-08
Keywords: Pränatale Depressivität; kindliche Erlebens- und Verhaltensauffälligkeiten; Risiko- und Schutzfaktoren; sozioökonomischer Status; Intelligenzquotient; Prenatal depression; child behavior; risk and protective factors; socioeconomic status; intelligence quotient

Maternal perinatal or current depressive symptoms and parenting behavior in middle childhood - Zalan, Vera; Ziegler, Clara; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (International Attachment Conference, 2017)

MCM3 is a novel proliferation marker associated with longer survival for patients with tubo-ovarian high-grade serous carcinoma - Kang, Eun Young; Millstein, Joshua; Popovic, Gordana; Meagher, Nicola S.; Bolithon, Adelyn; Talhouk, Aline; Chiu, Derek S.; Anglesio, Michael S.; Leung, Betty; Tang, Katrina; Lambie, Neil; Pavanello, Marina; et al. (Virchows Archiv, 2021)
Tubo-ovarian high-grade serous carcinomas (HGSC) are highly proliferative neoplasms that generally respond well to platinum/taxane chemotherapy. We recently identified minichromosome maintenance complex component 3 (MCM3), which is involved in the initiation of DNA replication and proliferation, as a favorable prognostic marker in HGSC. Our objective was to further validate whether MCM3 mRNA expression and possibly MCM3 protein levels are associated with survival in patients with HGSC. MCM3 mRNA expression was measured using NanoString expression profiling on formalin-fixed and paraffin-embedded tissue (N = 2355 HGSC) and MCM3 protein expression was assessed by immunohistochemistry (N = 522 HGSC) and compared with Ki-67. Kaplan-Meier curves and the Cox proportional hazards model were used to estimate associations with survival. Among chemotherapy-naive HGSC, higher MCM3 mRNA expression (one standard deviation increase in the score) was associated with longer overall survival (HR = 0.87, 95% CI 0.81-0.92, p < 0.0001, N = 1840) in multivariable analysis. MCM3 mRNA expression was highest in the HGSC C5.PRO molecular subtype, although no interaction was observed between MCM3, survival and molecular subtypes. MCM3 and Ki-67 protein levels were significantly lower after exposure to neoadjuvant chemotherapy compared to chemotherapy-naive tumors: 37.0% versus 46.4% and 22.9% versus 34.2%, respectively. Among chemotherapy-naive HGSC, high MCM3 protein levels were also associated with significantly longer disease-specific survival (HR = 0.52, 95% CI 0.36-0.74, p = 0.0003, N = 392) compared to cases with low MCM3 protein levels in multivariable analysis. MCM3 immunohistochemistry is a promising surrogate marker of proliferation in HGSC.
CRIS-Team WoS Importer:2021-11-26

Me2SO perfusion time for whole-organ cryopreservation can be shortened: Results of micro-computed tomography monitoring during Me2SO perfusion of rat hearts - Bleisinger, Nathalie; Dittrich, Ralf; Strahl, Olga; Brauweiler, Robert; Hoffmann, Inge; Beckmann, Matthias; Volk, Tilmann (PLoS ONE, 2020)
Cryopreservation of whole organs and specific tissues is an important and continually expanding field of medicine. The protocols currently used for organ preservation do not ensure survivability and functionality; the protocols for ovarian tissue lead to acceptable outcomes, but these are still capable of further improvement. In general, cryopreservation protocols need to be optimized. One important approach to improving cryopreservation protocols in general involves reducing exposure to cytotoxic cryoprotective agents prior to freezing. This study, therefore, evaluated the real-time tissue penetration of dimethyl sulfoxide, a cryoprotective agent that is widely used in cryopreservation. Dimethyl sulfoxide penetration in rat hearts perfused with a 15% (v/v) dimethyl sulfoxide solution was examined in real-time using dynamic contrast-enhanced micro-computed tomography imaging. Viability of cardiomyocytes was not significantly affected by the dimethyl sulfoxide perfusion procedure. Two different perfusion rates were evaluated and compared with perfusion using a common iodine-based contrast agent (iomeprol). The dynamic contrast-enhanced micro-computed tomography imaging data showed that dimethyl sulfoxide flushes both the extracellular and intracellular spaces in rat heart tissue to 95% equilibration after ≈ 35 s via perfusion. Subsequent wash-out via perfusion is completed to 95% within ≈ 49 s. The equilibration duration routinely used in dimethyl sulfoxide-based protocols for cryopreservation should therefore be questioned. Shorter incubation duration would perhaps be sufficient, as well as being beneficial in relation to cell survivability. It would be helpful to have techniques for non-invasive real-time monitoring of the penetration of cryoprotective agents and such techniques should be used to revise cryopreservation protocols. Switching to perfusion-based equilibration procedures might be beneficial, if feasible.
CRIS-Team Scopus Importer:2020-09-11

Meconium indicators of maternal alcohol abuse during pregnancy and association with patient characteristics - Goecke, Tamme W.; Burger, Pascal; Fasching, Peter; Bakdash, Abdulsallam; Engel, Anne; Haeberle, Lothar; Voigt, Franziska; Faschingbauer, Florian; Raabe, Eva; Maass, Nicolai; Rothe, Michael; Beckmann, Matthias; et al. (BioMed Research International, 2014)
Identification of women with moderate alcohol abuse during pregnancy is difficult. We correlated self-reported alcohol consumption during pregnancy and patient characteristics with objective alcohol indicators measured in fetal meconium.A total of 557 women singleton births and available psychological tests, obstetric data and meconium samples were included in statistical analysis. Alcohol metabolites (fatty acid ethyl esters (FAEEs) and ethyl glucuronide (EtG)), were determined from meconium and correlated with patient characteristics.We found that 21.2% of the 557 participants admitted low-to-moderate alcohol consumption during pregnancy. Of the parameters analyzed from meconium, only EtG showed an association with alcohol history (P < 0.01). This association was inverse in cases with EtG value above 120 ng/g. These values indicate women with most severe alcohol consumption, who obviously denied having consumed alcohol during pregnancy. No other associations between socioeconomic or psychological characteristics and the drinking status (via meconium alcohol metabolites) could be found.Women who drink higher doses of ethanol during pregnancy, according to metabolite measures in meconium, might be less likely to admit alcohol consumption. No profile of socioeconomic or psychological characteristics of those women positively tested via meconium could be established.
EVALuna2:17357

Medication safety in patients treated with new oral antitumor agents: A prospective, randomized investigation on the impact of intensified clinical pharmaceutical/clinical pharmacological care on patient safety, patient knowledge and patient well-being (AMBORA). Supported by the German Cancer Aid within the Comprehensive Cancer Center Erlangen-EMN - Schlichtig, Katja; Lechner, P.; Grafe, Carolin; Ferstl, B.; Fuchs, F.; Hein, Alexander; Meidenbauer, N.; Sell, C.; Semrau, S.; Pavel, Marianne Ellen; Wullich, Bernd; Neurath, Markus; et al. (2018)
EVALuna2:33795

Medikamentöse Therapie der Endometriose - Burghaus, Stefanie; Beckmann, Matthias (Die Gynäkologie, 2024)
In Germany, the progestin dienogest, the gonadotropin-releasing hormone (GnRH) agonists leuprorelin, goserelin, and nafarelin, and, since November 2023, the GnRH antagonist relugolix combination therapy (relugolix-CT) have been approved for hormonal drug therapy of endometriosis. In the first-line treatment of endometriosis, oral progestin preparations have proven effective. In second-line treatment, oral estrogen–progestin combination preparations, alternative forms of progestin administration such as the hormone coil, and GnRH agonists have proven effective. GnRH agonists have low compliance due to their range of side effects and their administration should be supplemented by add-back therapy. Another option is now treatment with the GnRH antagonist relugolix-CT following previous pharmaco- or surgical therapy. Non-hormonal drug therapy can be carried out symptomatically with analgesics such as nonsteroidal anti-inflammatory drugs.
CRIS-Team Scopus Importer:2024-02-09
Keywords: Dienogest; Estrogens; GnRH analoga; Progestins; Relugolix

Mendelian randomization analyses suggest a role for cholesterol in the development of endometrial cancer - Kho, Pik Fang; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias; Black, Amanda; Brinton, Louise; Buchanan, Daniel D.; Chanock, Stephen J.; Chen, Chu; et al. (International Journal of Cancer, 2020)
Blood lipids have been associated with the development of a range of cancers, including breast, lung and colorectal cancer. For endometrial cancer, observational studies have reported inconsistent associations between blood lipids and cancer risk. To reduce biases from unmeasured confounding, we performed a bidirectional, two-sample Mendelian randomization analysis to investigate the relationship between levels of three blood lipids (low-density lipoprotein [LDL] and high-density lipoprotein [HDL] cholesterol, and triglycerides) and endometrial cancer risk. Genetic variants associated with each of these blood lipid levels (P < 5 × 10−8) were identified as instrumental variables, and assessed using genome-wide association study data from the Endometrial Cancer Association Consortium (12 906 cases and 108 979 controls) and the Global Lipids Genetic Consortium (n = 188 578). Mendelian randomization analyses found genetically raised LDL cholesterol levels to be associated with lower risks of endometrial cancer of all histologies combined, and of endometrioid and non-endometrioid subtypes. Conversely, higher genetically predicted HDL cholesterol levels were associated with increased risk of non-endometrioid endometrial cancer. After accounting for the potential confounding role of obesity (as measured by genetic variants associated with body mass index), the association between genetically predicted increased LDL cholesterol levels and lower endometrial cancer risk remained significant, especially for non-endometrioid endometrial cancer. There was no evidence to support a role for triglycerides in endometrial cancer development. Our study supports a role for LDL and HDL cholesterol in the development of non-endometrioid endometrial cancer. Further studies are required to understand the mechanisms underlying these findings.
CRIS-Team Scopus Importer:2020-08-14
Keywords: endometrial cancer risk; HDL cholesterol; LDL cholesterol; Mendelian randomization; triglycerides

Meta-analysis of genome-wide association studies identifies common susceptibility polymorphisms for colorectal and endometrial cancer near SH2B3 and TSHZ1 - Cheng, Timothy H. T.; Thompson, Deborah; Painter, Jodie; O'Mara, Tracy; Gorman, Maggie; Martin, Lynn; Palles, Claire; Jones, Angela; Buchanan, Daniel D.; Win, Aung Ko; Hopper, John; Jenkins, Mark; et al. (Scientific Reports, 2015)
High-risk mutations in several genes predispose to both colorectal cancer (CRC) and endometrial cancer (EC). We therefore hypothesised that some lower-risk genetic variants might also predispose to both CRC and EC. Using CRC and EC genome-wide association series, totalling 13,265 cancer cases and 40,245 controls, we found that the protective allele [G] at one previously-identified CRC polymorphism, rs2736100 near TERT, was associated with EC risk (odds ratio (OR) = 1.08, P = 0.000167); this polymorphism influences the risk of several other cancers. A further CRC polymorphism near TERC also showed evidence of association with EC (OR = 0.92; P = 0.03). Overall, however, there was no good evidence that the set of CRC polymorphisms was associated with EC risk, and neither of two previously-reported EC polymorphisms was associated with CRC risk. A combined analysis revealed one genome-wide significant polymorphism, rs3184504, on chromosome 12q24 (OR = 1.10, P = 7.23 × 10(-9)) with shared effects on CRC and EC risk. This polymorphism, a missense variant in the gene SH2B3, is also associated with haematological and autoimmune disorders, suggesting that it influences cancer risk through the immune response. Another polymorphism, rs12970291 near gene TSHZ1, was associated with both CRC and EC (OR = 1.26, P = 4.82 × 10(-8)), with the alleles showing opposite effects on the risks of the two cancers.
EVALuna2:9303

Methodological Establishment of an in-vitro ADCC Assay by using patient-specific Immune Cells - Lehle, Sarah; Völkl, Simon; Rübner, Matthias; Emons, Julius; Seitz, Katharina; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

MicroRNA in diagnosis and therapy monitoring of early-stage triple-negative breast cancer - Kahraman, Mustafa; Roeske, Anne; Laufer, Thomas; Fehlmann, Tobias; Backes, Christina; Kern, Fabian; Kohlhaas, Jochen; Schroers, Hannah; Saiz, Anna; Zabler, Cassandra; Ludwig, Nicole; Fasching, Peter; et al. (Scientific Reports, 2018)
Breast cancer is a heterogeneous disease with distinct molecular subtypes including the aggressive subtype triple-negative breast cancer (TNBC). We compared blood-borne miRNA signatures of early-stage basal-like (cytokeratin-CK5-positive) TNBC patients to age-matched controls. The miRNAs of TNBC patients were assessed prior to and following platinum-based neoadjuvant chemotherapy (NCT). After an exploratory genome-wide study on 21 cases and 21 controls using microarrays, the identified signatures were verified independently in two laboratories on the same and a new cohort by RT-qPCR. We differentiated the blood of TNBC patients before NCT from controls with 84% sensitivity. The most significant miRNA for this diagnostic classification was miR-126-5p (two tailed t-test p-value of 1.4 × 10-5). Validation confirmed the microarray results for all tested miRNAs. Comparing cancer patients prior to and post NCT highlighted 321 significant miRNAs (among them miR-34a, p-value of 1.2 × 10-23). Our results also suggest that changes in miRNA expression during NCT may have predictive potential to predict pathological complete response (pCR). In conclusion we report that miRNA expression measured from blood facilitates early and minimally-invasive diagnosis of basal-like TNBC. We also demonstrate that NCT has a significant influence on miRNA expression. Finally, we show that blood-borne miRNA profiles monitored over time have potential to predict pCR.
EVALuna2:209952

MicroRNA Related Polymorphisms and Breast Cancer Risk - Khan, Sofia; Greco, Dario; Michailidou, Kyriaki; Milne, Roger L.; Muranen, Taru A.; Heikkinen, Tuomas; Aaltonen, Kirsimari; Dennis, Joe; Bolla, Manjeet K.; Liu, Jianjun; Hall, Per; Irwanto, Astrid; et al. (PLoS ONE, 2014)
Genetic variations, such as single nucleotide polymorphisms (SNPs) in microRNAs (miRNA) or in the miRNA binding sites may affect the miRNA dependent gene expression regulation, which has been implicated in various cancers, including breast cancer, and may alter individual susceptibility to cancer. We investigated associations between miRNA related SNPs and breast cancer risk. First we evaluated 2,196 SNPs in a case-control study combining nine genome wide association studies (GWAS). Second, we further investigated 42 SNPs with suggestive evidence for association using 41,785 cases and 41,880 controls from 41 studies included in the Breast Cancer Association Consortium (BCAC). Combining the GWAS and BCAC data within a meta-analysis, we estimated main effects on breast cancer risk as well as risks for estrogen receptor (ER) and age defined subgroups. Five miRNA binding site SNPs associated significantly with breast cancer risk: rs1045494 (odds ratio (OR) 0.92; 95% confidence interval (CI): 0.88-0.96), rs1052532 (OR 0.97; 95% CI: 0.95-0.99), rs10719 (OR 0.97; 95% CI: 0.94-0.99), rs4687554 (OR 0.97; 95% CI: 0.95-0.99, and rs3134615 (OR 1.03; 95% CI: 1.01-1.05) located in the 3' UTR of CASP8, HDDC3, DROSHA, MUSTN1, and MYCL1, respectively. DROSHA belongs to miRNA machinery genes and has a central role in initial miRNA processing. The remaining genes are involved in different molecular functions, including apoptosis and gene expression regulation. Further studies are warranted to elucidate whether the miRNA binding site SNPs are the causative variants for the observed risk effects.
EVALuna2:9235

Mindfulness-based Stress Reduction in Pregnancy: an App-Based Programme to Improve the Health of Mothers and Children (MINDFUL/PMI Study) - Lenz, Bernd; Eichler, Anna; Schwenke, Eva; Buchholz, Verena N.; Hartwig, Charlotte; Moll, Gunther; Reich, Karin; Mühle, Christiane; Volz, Bernhard; Titzmann, Adriana; Beckmann, Matthias; Heinrich, Hartmut; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Unfavourable intrauterine environmental factors increase the risk of delivery complications as well as postpartum developmental and behavioural problems in children and adolescents with ongoing effects into older age. Biomarker studies show that maternal stress and the use of alcohol and tobacco during pregnancy are associated with a higher intrauterine testosterone exposure of the child. The antenatal testosterone load, in turn, is a risk factor for lasting adverse health effects which extend into adulthood. A 15-week, mindfulness-oriented, app-based programme for the reduction of stress as well as for the reduction of alcohol and tobacco use in pregnant women is established. In the monocentre, prospective, controlled, and investigator-blinded MINDFUL/PMI (Maternal Health and Infant Development in the Follow-up after Pregnancy and a Mindfulness Intervention) study, pregnant women carry out the programme. Its effect on antenatal testosterone exposure of the child is examined by assessing the index/ring finger length ratio and other biomarkers in the 1-year-old children. In addition, the programme's effects on self-regulation, the developmental status and the mental health of the children at the age of one year will be investigated. Additional aspects of the course of the pregnancy and delivery represent exploratory study objectives. This longitudinal study project is intended to improve the understanding of the impact of intrauterine environmental factors on early childhood development and health. Maternal stress as well as alcohol and tobacco use during pregnancy are modifiable factors and represent potential preventive targets.
EVALuna2:36366

Mitomycin C and Capecitabine (MiX Trial) for Therapy of Patients with Metastasized, Breast Cancer Pretreated with Anthracycline - Almstedt, Katrin; Fasching, Peter; Scharl, Anton; Rauh, Claudia; Rack, Brigitte; Hein, Alexander; Hack, Carolin; Bayer, Christian M.; Jud, Sebastian; Schrauder, Michael G.; Beckmann, Matthias; Lux, Michael P. (Anticancer Research, 2016)
BACKGROUND/AIM: The aim of this single-arm, prospective, multicenter phase II trial (MiX) was to increase treatment options for women with metastatic breast cancer pretreated with anthracycline and taxane by evaluation of the efficacy and toxicity of the combination of mitomycin C and capecitabine. PATIENTS AND METHODS: From 03/2004 to 06/2007, a total of 39 patients were recruited and received mitomycin C in combination with capecitabine. The primary end-point was to determinate the tumor response according to Response Evaluation Criteria in Solid Tumors and the rate of toxicities (safety). The secondary study objective was the evaluation of the time to progression (i.e. efficacy). RESULTS: The median time to progression was 9.3 months (95% confidence interval=6.6-12.0 months) and the median survival was 12.8 months (95% confidence interval=6.8-18.8 months). Most treatment-related adverse events were mild to moderate. CONCLUSION: Mitomycin C and capecitabine is a good taxane-free option in patients with metastatic breast cancer previously treated with anthracycline.
EVALuna2:33006

Modern systemic therapy concepts in cervical cancer. Innovations from the S3 guideline: "Diagnosis, treatment and after care of the patient with cervical cancer" - Koch, Martin; Mehlhorn, Grit; Beckmann, Matthias (Onkologe, 2016)
The problems of uncertain treatment, mortality and morbidity rates that have not declined over the last 15 years, and the current wide variations in treatment, made necessary an upgrade from the existing Level 2k consensus-based guideline from 2008 to a Level 3 guideline. These factors also induced the current Level 3 guideline on diagnosis, treatment, and follow-up of patients with cervical carcinoma (AWMF register no. 032-033OL) since 2014. This overview describes the current standard of cervical cancer treatment. Therefore, it focusses on the drug therapy of patients suffering from cervical cancer. This is in line with the focus of the journal. A further topic is the diagnostic chain that is essential for therapeutic decision-making. Based on the recommendations of the S3 guideline, the current algorithms for treating cervical cancer are shown and discussed. Surgical procedures are mainly carried out in the early stages. From stage IIB, a simultaneous cisplatin-containing radiochemotherapy is recommended. The therapy of choice for non-operable local recurrence or metastasic situation consists of palliative chemotherapy regimens. Since 2014 the addition of a targeted therapy with bevacizumab has been integrated to the treatment approach. Therapy for patients with cervical cancer has changed significantly over the last decades. There are various new therapeutic options, which are applied according to tumour stage and on an individual basis. The decision of which therapeutic method has to be applied is based on the interdisciplinary consultation and is individualized. The patient has to be involved in the decision process. Age and life situation have to be considered as well as the stage of the disease, risk factors and the side effects of the different therapies. The aim is to provide the best quality of life and the best outcome.
EVALuna2:32954

Molecular Subtyping of Invasive Breast Cancer Using a PAM50-Based Multigene Expression Test-Comparison with Molecular-Like Subtyping by Tumor Grade/Immunohistochemistry and Influence on Oncologist's Decision on Systemic Therapy in a Real-World Setting - Erber, Ramona; Angeloni, Miriam; Stöhr, Robert; Lux, Michael P.; Ulbrich-Gebauer, Daniel; Pelz, Enrico; Bankfalvi, Agnes; Schmid, Kurt W.; Walter, Robert F. H.; Vetter, Martina; Thomssen, Christoph; Mayr, Doris; et al. (International Journal of Molecular Sciences, 2022)
In intermediate risk hormone receptor (HR) positive, HER2 negative breast cancer (BC), the decision regarding adjuvant chemotherapy might be facilitated by multigene expression tests. In all, 142 intermediate risk BCs were investigated using the PAM50-based multigene expression test Prosigna (R) in a prospective multicentric study. In 119/142 cases, Prosigna (R) molecular subtyping was compared with local and two central (C1 and C6) molecular-like subtypes relying on both immunohistochemistry (IHC; HRs, HER2, Ki-67) and IHC + tumor grade (IHC+G) subtyping. According to local IHC, 35.4% were Luminal A-like and 64.6% Luminal B-like subtypes (local IHC+G subtype: 31.9% Luminal A-like; 68.1% Luminal B-like). In contrast to local and C1 subtyping, C6 classified >2/3 of cases as Luminal A-like. Pairwise agreement between Prosigna (R) subtyping and molecular-like subtypes was fair to moderate depending on molecular-like subtyping method and center. The best agreement was observed between Prosigna (R) (53.8% Luminal A; 44.5% Luminal B) and C1 surrogate subtyping (Cohen's kappa = 0.455). Adjuvant chemotherapy was suggested to 44.2% and 88.6% of Prosigna (R) Luminal A and Luminal B cases, respectively. Out of all Luminal A-like cases (locally IHC/IHC+G subtyping), adjuvant chemotherapy was recommended if Prosigna (R) testing classified as Prosigna (R) Luminal A at high / intermediate risk or upgraded to Prosigna (R) Luminal B.
CRIS-Team WoS Importer:2022-08-26

MUC1 (CA27.29) before and after Chemotherapy and Prognosis in High-Risk Early Breast Cancer Patients - Hübner, Hanna; Häberle, Lothar; Müller, Volkmar; Schrader, Iris; Lorenz, Ralf; Forstbauer, Helmut; Fink, Visnja; Schochter, Fabienne; Bekes, Inga; Mahner, Sven; Jückstock, Julia; Nabieva, Naiba; et al. (Cancers, 2022)
Soluble MUC1 has been discussed as a biomarker for predicting prognosis, treatment efficacy, and monitoring disease activity in breast cancer (BC) patients. Most studies in adjuvant settings have used preoperative assessment. This study, part of the SUCCESS-A trial (NCT02181101), assessed the prognostic value of soluble MUC1 before and after standard adjuvant chemotherapy. Patients with high-risk BC were treated within the SUCCESS-A trial with either three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide followed by three cycles of docetaxel or three cycles of FEC followed by three cycles of docetaxel and gemcitabine. Cox regression analyses were performed to investigate the prognostic value of CA27.29 before and after chemotherapy relative to disease-free survival (DFS), along with established BC prognostic factors such as age, body mass index, tumor size, nodal status, estrogen receptor, progesterone receptor, HER2 status, and grading. Pre-chemotherapy and post-chemotherapy CA27.29 assessments were available for 2687 patients of 3754 randomized patients. Pre-chemotherapy CA27.29 assessment was associated with DFS in addition to established prognostic factors. It had no prognostic value in node-negative patients, but there was a clear association in node-positive patients. Post-chemotherapy CA27.29 assessment did not add any prognostic value, either on its own or in addition to pre-chemotherapy CA27.29 assessment.
CRIS-Team Scopus Importer:2022-04-08
Keywords: anthracycline; CA15-3; CA27.29; chemotherapy; early breast cancer; MUC1; taxane; tumor marker

Multicenter evaluation of blood-based biomarkers for the detection of endometriosis and adenomyosis: A prospective non-interventional study - Burghaus, Stefanie; Drazic, Predrag; Wölfler, Monika; Mechsner, Sylvia; Zeppernick, Magdalena; Meinhold-Heerlein, Ivo; Mueller, Michael D.; Rothmund, Ralf; Vigano, Paola; Becker, Christian M.; Zondervan, Krina T.; Beckmann, Matthias; et al. (International Journal of Gynecology & Obstetrics, 2023)
Objective: To evaluate blood-based biomarkers to detect endometriosis and/or adenomyosis across nine European centers (June 2014–April 2018). Methods: This prospective, non-interventional study assessed the diagnostic accuracy of 54 blood-based biomarker immunoassays in samples from 919 women (aged 18–45 years) with suspicion of endometriosis and/or adenomyosis versus symptomatic controls. Endometriosis was stratified by revised American Society for Reproductive Medicine stage. Symptomatic controls were “pathologic symptomatic controls” or “pathology-free symptomatic controls”. The main outcome measure was receiver operating characteristic-area under the curve (ROC-AUC) and Wilcoxon P values corrected for multiple testing (q values). Results: CA-125 performed best in “all endometriosis cases” versus “all symptomatic controls” (AUC 0.645, 95% confidence interval [CI] 0.600–0.690, q < 0.001) and increased (P < 0.001) with disease stage. In “all endometriosis cases” versus “pathology-free symptomatic controls”, S100-A12 performed best (AUC 0.692, 95% CI 0.614–0.769, q = 0.001) followed by CA-125 (AUC 0.649, 95% CI 0.569–0.729, q = 0.021). In “adenomyosis only cases” versus “symptomatic controls” or “pathology-free symptomatic controls”, respectively, the top-performing biomarkers were sFRP-4 (AUC 0.615, 95% CI 0.551–0.678, q = 0.045) and S100-A12 (AUC 0.701, 95% CI 0.611–0.792, q = 0.004). Conclusion: This study concluded that no biomarkers tested could diagnose or rule out endometriosis/adenomyosis with high certainty.
CRIS-Team Scopus Importer:2023-09-29
Keywords: adenomyosis; blood-based biomarkers; CA-125; diagnosis; endometriosis; S100-A12; sFRP-4

Mutations in BRCA1/2 and Other Panel Genes in Patients With Metastatic Breast Cancer -Association With Patient and Disease Characteristics and Effect on Prognosis - Fasching, Peter; Yadav, Siddhartha; Hu, Chunling; Wunderle, Marius; Häberle, Lothar; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Lee, Kun Y.; Gnanaolivu, Rohan D.; Hadji, Peyman; Hübner, Hanna; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Among patients with metastatic breast cancer (mBC), the frequency of germline mutations in cancer susceptibility genes and the clinical relevance of these mutations are unclear. In this study, a prospective cohort of patients with mBC was used to determine mutation rates for breast cancer (BC) predisposition genes, to evaluate the clinical characteristics of patients with mutations, and to assess the influence of mutations on patient outcome. PATIENTS AND METHODS: Germline DNA from 2,595 patients with mBC enrolled in the prospective PRAEGNANT registry was evaluated for mutations in cancer predisposition genes. The frequencies of mutations in known BC predisposition genes were compared with results from a prospective registry of patients with nonmetastatic BC sequenced using the same QIAseq method and with public reference controls. Associations between mutation status and tumor characteristics, progression-free survival, and overall survival were assessed. RESULTS: Germline mutations in 12 established BC predisposition genes (including BRCA1 and BRCA2) were detected in 271 (10.4%) patients. A mutation in BRCA1 or BRCA2 was seen in 129 patients (5.0%). BRCA1 mutation carriers had a higher proportion of brain metastasis (27.1%) compared with nonmutation carriers (12.8%). Mutations were significantly enriched in PRAEGNANT patients with mBC compared with patients with nonmetastatic BC (10.4% v 6.6%, P < .01). Mutations did not significantly modify progression-free survival or overall survival for patients with mBC. CONCLUSION: Multigene panel testing may be considered in all patients with mBC because of the high frequency of germline mutations in BRCA1/2 and other BC predisposition genes. Although the prognosis of mutation carriers and nonmutation carriers with mBC was similar, differences observed in tumor characteristics have implications for treatment and for future studies of targeted therapies.
CRIS-Team Scopus Importer:2021-06-04

Mutation status of the mediator complex subunit 12 (MED12) in uterine leiomyomas and concurrent/metachronous multifocal peritoneal smooth muscle nodules (leiomyomatosis peritonealis disseminata) - Rieker, Ralf; Agaimy, Abbas; Moskalev, Evgeny; Hebele, Simone; Hein, Alexander; Mehlhorn, Grit; Beckmann, Matthias; Hartmann, Arndt; Haller, Florian (Pathology, 2013)
Aims: The pathogenesis and classification of multicentric smooth muscle tumours with benign appearance and concurrent/metachronous uterine and peritoneal involvement is controversial and may on occasion be diagnostically challenging. Leiomyomatosis peritonealis disseminata (LPD) is a rare condition affecting women of reproductive age, characterised by the occurrence of multiple small peritoneal smooth muscle nodules with bland histology. Methods: We investigated a total of 12 uterine and seven concurrent/metachronous peritoneal smooth muscle nodules with benign appearance from two females for mutations in the mediator complex subunit 12 (MED12), which has recently been identified as the most frequent genetic aberration in uterine leiomyomas. Results: The first case harboured different MED12 mutations in the peritoneal nodules. Mutational status of peritoneal nodules was discordant with that of the uterine leiomyomas. The second case displayed the same MED12 mutation in all five peritoneal nodules, but this mutation was not detected in her current uterine leiomyomas. Conclusions: Our results suggest that smooth muscle neoplasms with benign appearance of the primary and secondary mü llerian system share a similar genetic background of MED12 mutation in combination with oestrogen dependency. Analysis of MED12 mutation status might be a valuable adjunct tool for the future classification of these sometimes diagnostically challenging multicentric tumours. © 2013 Royal College of Pathologists of Australasia.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Leiomyomatosis peritonealis disseminata; MED12; Uterine leiomyoma

Nachsorge bei Patientinnen mit Zervixkarzinom - Schulmeyer, Carla; Stuebs, Frederik A.; Beckmann, Matthias (Gynäkologe, 2020)
Follow-up of patients who underwent treatment for cervical cancer starts after completion of the primary treatment. It is important in aftercare to provide the patient with care both medically, in order to detect a recurrence as soon as possible and also as psychological guidance in order to record the effects of treatment, sexuality and relationship as well as the quality of life of the patient. It is also important to provide information about offers of assistance and psycho-oncological treatment options. The type of educational procedure and the approach for special collectives, such as patients after chemo(radio)therapy or after trachelectomy, are currently under discussion.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Counselling; Diagnostic imaging; Human papillomaviruses; Quality of life; Sonography

(Neo-)Adjuvant and first-line therapy: Prognostic and predictive factors (Neo-)Adjuvanten und First-Line-Therapie: Prognostische und prädiktive Faktoren - Lux, Michael P.; Oenuegoeren, Onur; Wunderle, Marius; Hein, Alexander; Rauh, Claudia; Schrauder, Michael G.; Fasching, Peter; Beckmann, Matthias (Gynäkologe, 2015)
The number of cancer cases is increasing steadily. In Germany, 97,480 women are diagnosed with a gynecological malignancy each year, which represents 43 % of all cancer cases in women. Furthermore, gynecological malignancies are responsible for 28 % of cancer deaths. These numbers highlight the need for optimal, individualized treatment decisions in order to achieve maximum effectiveness, prevent recurrence and metastatic progression, and avoid overtreatment. Reliable and validated prognostic and predictive factors are required for the therapy decision of (neo-)adjuvant or first-line treatment of patients with gynecological cancers or breast cancer. In the era of individualized and targeted therapy there are fewer predictive factors available than originally thought. Nevertheless, future perspectives for various tumor entities present promising approaches which can support therapeutic decisions for adjuvant systemic therapy, e.g. gene expression analyses, studies of gene copy variations or the detection of single mutations which play an important role in signaling pathways of tumor cells.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Antineoplastic agents; Biomarkers; Breast neoplasms; Decision making; Gene expression

Neoadjuvant chemotherapy in breast cancer: Which diagnostic procedures can be used? - Löhberg, Christian; Lux, Michael P.; Ackermann, Sven; Pöhls, Uwe G.; Bani, Mayada; Schulz-Wendtland, Rüdiger; Papadopoulos, Thomas; Schmucker, Martin; Beckmann, Matthias; Fasching, Peter (Anticancer Research, 2005)
BACKGROUND To improve breast cancer treatment, the evaluation of predictive factors is in the focus of clinical research. Significant discrepancies between the clinical assessment of response to neoadjuvant chemotherapy (NACT) and the pathological assessment of response from post-therapy surgical specimens have been demonstrated. We focused on comparing the value of various diagnostic methods used in medical routine. PATIENTS AND METHODS A clinical evaluation of the primary tumour and regional lymph nodes before and after NACT was performed in 139 patients by physical examination, sonography and mammography. RESULTS Mammography and physical examination correlated best with pathological findings in the measurement of the tumour, whereas sonography was the most accurate predictor of the status for axillary lymph nodes. CONCLUSION Mammography and physical examination are the best non-invasive predictors of the real size of the primary breast cancer, whereas sonography correlates better with the proven status of axillary lymph nodes.
Keywords: Neoadjuvant chemotherapy; breast cancer; mammography; sonography

Neoadjuvante Therapiekonzepte beim Zervixkarzinom - Stübs, Frederik A.; Koch, Martin; Beckmann, Matthias (Gynäkologe, 2019)
Background: The neoadjuvant treatment concept is nowadays the standard of care for many different organ entities. The neoadjuvant treatment also seems to be of interest in special situations for cervical cancer. Objective: This article gives an overview of the currently discussed fields of application of neoadjuvant therapy in treating patients with cervical cancer and the various options are discussed. Material and methods: This article is based on the national S3 guidelines for diagnostics, treatment and follow-up of patients with cervical cancer of the Association of the Scientific Medical Societies of Germany (AWMF, register number 032/033OL in the version from 2014). Additionally, this was extended by the literature for the update research of the new version of the guidelines. Results: The response rate to neoadjuvant therapy is 84%. The 5‑year progression-free survival and overall survival are 61.9% and 72.8%, respectively. Women responding to neoadjuvant therapy have a better long-term survival than non-responders. In a Cochrane meta-analysis from 2012 neoadjuvant chemotherapy before the planned operation improved the progression-free survival (hazard ratio, HR 0.75, 95% confidence interval, CI 0.61–0.93, P = 0.008) and the overall survival (HR 0.77, 95% CI 0.62–0.96, P = 0.02). The results were no longer significant when the random effects model was used (odds ratio, OR 0.60, 95% CI 0.32–1.12, P = 0.11). In macroinvasive cervical cancer during pregnancy neoadjuvant therapy is an established component of treatment. Discussion: The data on the use of neoadjuvant therapy in treating cervical cancer is unclear. The neoadjuvant therapy is currently not a standard of care in the treatment of cervical cancer. The roles of operative staging and positive lymph nodes after neoadjuvant therapy are also unresolved. Various meta-analyses could show that neoadjuvant therapy improves progression-free and overall survival. This is especially true for women who respond to this treatment.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Disease progression; Disease progression; Disease-free survival; Pregnancy; Standard of care

Neoadjuvant trastuzumab, pertuzumab, and chemotherapy versus trastuzumab emtansine plus pertuzumab in patients with HER2-positive breast cancer (KRISTINE): a randomised, open-label, multicentre, phase 3 trial - Hurvitz, Sara A.; Martin, Miguel; Symmans, W. Fraser; Jung, Kyung Hae; Huang, Chiun-Sheng; Thompson, Alastair M.; Harbeck, Nadia; Valero, Vicente; Stroyakovskiy, Daniil; Wildiers, Hans; Campone, Mario; Boileau, Jean-Francois; et al. (Lancet Oncology, 2018)
BACKGROUND: HER2-targeted treatments have improved outcomes in patients with HER2-positive breast cancer in the neoadjuvant, adjuvant, and metastatic settings; however, some patients remain at risk of relapse or death for many years after treatment of early-stage disease. Therefore, new strategies are needed. We did a phase 3 trial to assess a neoadjuvant regimen for HER2-positive breast cancer that replaces traditional systemic chemotherapy with targeted treatment. METHODS: We did a randomised, open-label phase 3 KRISTINE trial in 68 Translational Research In Oncology centres (hospitals and specialty cancer centres in Asia, Europe, USA, and Canada). Eligible participants were aged 18 years or older with centrally confirmed HER2-positive stage II-III operable breast cancer (>2 cm tumour size), an Eastern Cooperative Oncology Group performance status of 0-1, and a baseline left ventricular ejection fraction of at least 55% (by echocardiogram or multiple-gated acquisition scan). We randomly assigned participants (1:1) to receive either trastuzumab emtansine plus pertuzumab or docetaxel, carboplatin, and trastuzumab plus pertuzumab. We did the randomisation via an interactive response system under a permuted block randomisation scheme (block size of four), stratified by hormone receptor status, stage at diagnosis, and geographical location. Patients received six cycles (every 3 weeks) of neoadjuvant trastuzumab emtansine plus pertuzumab (trastuzumab emtansine 3·6 mg/kg; pertuzumab 840 mg loading dose, 420 mg maintenance doses) or docetaxel, carboplatin, and trastuzumab plus pertuzumab (docetaxel 75 mg/m2; carboplatin area under the concentration-time curve 6 mg/mL × min; trastuzumab 8 mg/kg loading dose, 6 mg/kg maintenance doses) plus pertuzumab [same dosing as in the other group]). All treatments were administered intravenously. The primary objective was to compare the number of patients who achieved a pathological complete response (ypT0/is, ypN0), between groups in the intention-to-treat population (two-sided assessment), based on local evaluation of tumour samples taken at breast cancer surgery done between 14 days and 6 weeks after completion of neoadjuvant therapy. Safety was analysed in patients who received at least one dose of study medication. This trial is registered with ClinicalTrials.gov, number NCT02131064, and follow-up of the adjuvant phase is ongoing. FINDINGS: Between June 25, 2014, and June 15, 2015, we randomly assigned 444 patients to neoadjuvant treatment with trastuzumab emtansine plus pertuzumab (n=223) or docetaxel, carboplatin, and trastuzumab plus pertuzumab (n=221). A pathological complete response was achieved by 99 (44·4%) of 223 patients in the trastuzumab emtansine plus pertuzumab group and 123 (55·7%) of 221 patients in the docetaxel, carboplatin, and trastuzumab plus pertuzumab group (absolute difference -11·3 percentage points, 95% CI -20·5 to -2·0; p=0·016). During neoadjuvant treatment, compared with patients receiving docetaxel, carboplatin, and trastuzumab plus pertuzumab, fewer patients receiving trastuzumab emtansine plus pertuzumab had a grade 3-4 adverse event (29 [13%] of 223 vs 141 [64%] of 219) or a serious adverse event (11 [5%] of 223 vs 63 [29%] of 219). The most common grade 3-4 adverse events in the trastuzumab emtansine plus pertuzumab group were decreased platelet count (three [1%] of 223 patients vs 11 [5%] of 219 with docetaxel, carboplatin, and trastuzumab plus pertuzumab), fatigue (three [1%] vs seven [3%]), alanine aminotransferase increase (three [1%] vs four [2%]), and hypokalaemia (three [1%] vs five [2%]). The most common grade 3-4 adverse events in the docetaxel, carboplatin, and trastuzumab plus pertuzumab group were neutropenia (55 [25%] of 219 vs one [<1%] of 223 with trastuzumab emtansine plus pertuzumab), diarrhoea (33 [15%] vs 2 [<1%]), and febrile neutropenia (33 [15%] vs 0). No deaths were reported during neoadjuvant treatment. INTERPRETATION: Traditional neoadjuvant systemic chemotherapy plus dual HER2-targeted blockade (docetaxel, carboplatin, and trastuzumab plus pertuzumab) resulted in significantly more patients achieving a pathological complete response than HER2-targeted chemotherapy plus HER2-targeted blockade (trastuzumab emtansine plus pertuzumab); however, numerically more grade 3-4 and serious adverse events occurred in the chemotherapy plus trastuzumab and pertuzumab group. Further efforts to improve the efficacy of chemotherapy without imparting more toxicity are warranted. FUNDING: F Hoffmann-La Roche and Genentech.
EVALuna2:36439

Network-Based Integration of GWAS and Gene Expression Identifies a HOX-Centric Network Associated with Serous Ovarian Cancer Risk - Kar, Siddhartha P.; Tyrer, Jonathan P.; Li, Qiyuan; Lawrenson, Kate; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Chenevix-Trench, Georgia; Baker, Helen; Bandera, Elisa V.; Bean, Yukie T.; Beckmann, Matthias; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
Genome-wide association studies (GWAS) have so far reported 12 loci associated with serous epithelial ovarian cancer (EOC) risk. We hypothesized that some of these loci function through nearby transcription factor (TF) genes and that putative target genes of these TFs as identified by coexpression may also be enriched for additional EOC risk associations.We selected TF genes within 1 Mb of the top signal at the 12 genome-wide significant risk loci. Mutual information, a form of correlation, was used to build networks of genes strongly coexpressed with each selected TF gene in the unified microarray dataset of 489 serous EOC tumors from The Cancer Genome Atlas. Genes represented in this dataset were subsequently ranked using a gene-level test based on results for germline SNPs from a serous EOC GWAS meta-analysis (2,196 cases/4,396 controls).Gene set enrichment analysis identified six networks centered on TF genes (HOXB2, HOXB5, HOXB6, HOXB7 at 17q21.32 and HOXD1, HOXD3 at 2q31) that were significantly enriched for genes from the risk-associated end of the ranked list (P < 0.05 and FDR < 0.05). These results were replicated (P < 0.05) using an independent association study (7,035 cases/21,693 controls). Genes underlying enrichment in the six networks were pooled into a combined network.We identified a HOX-centric network associated with serous EOC risk containing several genes with known or emerging roles in serous EOC development.Network analysis integrating large, context-specific datasets has the potential to offer mechanistic insights into cancer susceptibility and prioritize genes for experimental characterization. Cancer Epidemiol Biomarkers Prev; 24(10); 1574-84. ©2015 AACR.
EVALuna2:9287

Neurovascular compression of medulla oblongata - Association for gestation-induced hypertension - Tanrikulu, Levent; Naraghi, Ramin; Ernst, Veronika; Voigt, Franziska; Hastreiter, Peter; Dörfler, Arnd; Buchfelder, Michael; Beckmann, Matthias; Goecke, Tamme W. (Medical Hypotheses, 2015)
Patients with essential hypertension may show neurovascular compression (NVC) at the rostral ventrolateral medulla oblongata (RVLM). Ectatic loops of the vertebral artery (VA) or the inferior posterior cerebellar artery (PICA) cause NVC. This study aims to show the existence and morphology of NVC in patients with gestation-induced hypertension. 17 females were prospectively examined between 19. +. 0 and 35. +. 6. weeks of gestation. 3 patients with chronic hypertension (group A), 10 patients with preeclampsia (group B), 3 patients with superimposed preeclampsia (chronic hypertension with preeclampsia; group C) and one normotensive patient were included. Groups B and C represented patients with gestation-induced hypertension. All 17 patients underwent imaging by high resolution magnetic resonance imaging (MR-CISS, constructive interference in the steady state). Image processing was done with segmentation and three-dimensional (3D)-visualization was implemented with direct volume rendering of the individual neurovascular details of each patient. 9 of 17 patients (53%) showed NVC of the RVLM. Right-sided NVC was seen in 7 patients (41%). Left-sided NVC was seen in 6 patients (35%). Bilateral NVC was seen in 4 patients (24%). NVC was missing in 8 of the examined 17 patients (47%). The existence of NVC with high-resolution MRI was analyzed in gestation-induced hypertensive pregnant females for the first time. Neurovascular conflicts were seen in hypertensive pregnants. It is possible that NVC is potentially associated in patients with gestation-induced hypertension.
CRIS-Team Scopus Importer:2022-08-05

New Screening Proposals: the Federal Joint Commission Defines the Parameters for Cervical Cancer Screening from 2018 Statement of the Gynecology Oncology Working Group (AGO) - Hillemanns, P.; Mallmann, P.; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
The Gynecology Oncology Working Group (AGO e.V.) unequivocally welcomes the decision taken by the German Federal Joint Commission (Gemeinsamer Bundesausschuss, G-BA) on March 19, 2015 regarding screening for cervical cancer. AGO is convinced that, in view of recent medical advances, this evidence-based decision will improve screening for cervical cancer.
EVALuna2:32998

New WHO Classification of Endometrial Hyperplasias - Emons, G.; Beckmann, Matthias; Schmidt, D.; Mallmann, P. (Geburtshilfe und Frauenheilkunde, 2015)
EVALuna2:17599

Ninety-five orthotopic transplantations in 74 women of ovarian tissue after cytotoxic treatment in a fertility preservation network: tissue activity, pregnancy and delivery rates - Van Der Ven, H.; Liebenthron, J.; Beckmann, Matthias; Toth, B.; Korell, M.; Kruessel, J.; Frambach, T.; Kupka, M.; Hohl, M. K.; Winkler-Crepaz, K.; Seitz, S.; Dogan, A.; et al. (Human Reproduction, 2016)
STUDY QUESTION: What is the success rate in terms of ovarian activity (menstrual cycles) as well as pregnancy and delivery rates 1 year after orthotopic ovarian transplantations conducted in a three-country network? SUMMARY ANSWER: In 49 women with a follow-up >1 year after transplantation, the ovaries were active in 67% of cases and the pregnancy and delivery rates were 33 and 25%, respectively. WHAT IS KNOWN ALREADY: Cryopreservation of ovarian tissue in advance of cytotoxic therapies and later transplantation of the tissue is being performed increasingly often, and the total success rates in terms of pregnancy and delivery have been described in case series. However, published case series have not allowed either a more detailed analysis of patients with premature ovarian insufficiency (POI) or calculation of success rates based on the parameter 'tissue activity'. STUDY DESIGN, SIZE, DURATION: Retrospective analysis of 95 orthotopic transplantations in 74 patients who had been treated for cancer, performed in the FertiPROTEKT network from 2008 to June 2015. Of those 95 transplantations, a first subgroup (Subgroup 1) was defined for further analysis, including 49 women with a follow-up period >1 year after transplantation. Of those 49 women, a second subgroup (Subgroup 5) was further analysed, including 40 women who were transplanted for the first time and who were diagnosed with POI before transplantation. PARTICIPANTS/MATERIALS, SETTING, METHODS: Transplantation was performed in 16 centres and data were transferred to the FertiPROTEKT registry. The transplantations were carried out after oncological treatment had been completed and after a remission period of at least 2 years. Tissue was transplanted orthotopically, either into or onto the residual ovaries or into a pelvic peritoneal pocket. The success rates were defined as tissue activity (menstrual cycles) after 1 year (primary outcome) and as pregnancies and deliveries achieved. MAIN RESULTS AND THE ROLE OF CHANCE: The average age of all transplanted 74 women was 31 ± 5.9 years at the time of cryopreservation and 35 ± 5.2 at the time of transplantation. Twenty-one pregnancies and 17 deliveries were recorded. In Subgroup 1, tissue was cryopreserved at the age of 30 ± 5.6 and transplanted at 34 ± 4.9 years. Ovaries remained active 1 year after transplantation in 67% of cases (n = 33/49), the pregnancy rate was 33% (n = 16/49) and the delivery rate was 25% (n = 12/49). In Subgroup 5, tissue was cryopreserved at the age 30 ± 5.9 years and transplanted at 34 ± 5.2 years. Ovaries remained active 1 year after transplantation in 63% of cases (n = 25/40), the pregnancy rate was 28% (n = 11/40) and the delivery rate was 23% (n = 9/40). The success rates were age dependant with higher success in women who cryopreserved at a younger age. In Subgroup 5, tissue was exclusively transplanted into the ovary in 10% (n = 4/40) of women and into a peritoneal pocket in 75% (n = 30/40), resulting in spontaneous conceptions in 91% of patients (n = 10/11). LIMITATIONS, REASONS FOR CAUTION: The data were drawn from a retrospective analysis. The cryopreservation and transplantation techniques used have changed during the study period. The tissue was stored in many tissue banks and many surgeons were involved, leading to heterogeneity of the procedures. However, this does reflect the realistic situation in many countries. Although patients with POI were evaluated before transplantation to allow specific analysis of the transplanted tissue itself, the possibility cannot be excluded that residual ovarian tissue was also reactivated. WIDER IMPLICATIONS OF THE FINDINGS: This is the largest case series worldwide to date and it confirms that cryopreservation and transplantation of ovarian tissue can be a successful option for preserving fertility. Persistent tissue activity 12 months after transplantation suggests that the pregnancy and delivery rates may increase further in the future. As transplantation into the peritoneum results in a high success rate, this approach may be an alternative to transplantation into the ovary. However, in order to establish the best transplantation site, a randomized study is required. STUDY FUNDING/COMPETING INTEREST: This study was in part funded from the Deutsche Forschungsgemeinschaft (# DI 1525) and the Wilhelm Sander Foundation (2012.127.1) and did not receive any funding from a commercial company. No competing interests. TRIAL REGISTRATION NUMBER: None.
EVALuna2:33464

No clinical utility of KRAS variant rs61764370 for ovarian or breast cancer - Hollestelle, Antoinette; Van Der Baan, Frederieke H.; Berchuck, Andrew; Johnatty, Sharon E.; Aben, Katja K.; Agnarsson, Bjarni A.; Aittomaki, Kristiina; Alducci, Elisa; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Antoniou, Antonis C.; et al. (Gynecologic Oncology, 2016)
Clinical genetic testing is commercially available for rs61764370, an inherited variant residing in a KRAS 3' UTR microRNA binding site, based on suggested associations with increased ovarian and breast cancer risk as well as with survival time. However, prior studies, emphasizing particular subgroups, were relatively small. Therefore, we comprehensively evaluated ovarian and breast cancer risks as well as clinical outcome associated with rs61764370.Centralized genotyping and analysis were performed for 140,012 women enrolled in the Ovarian Cancer Association Consortium (15,357 ovarian cancer patients; 30,816 controls), the Breast Cancer Association Consortium (33,530 breast cancer patients; 37,640 controls), and the Consortium of Modifiers of BRCA1 and BRCA2 (14,765 BRCA1 and 7904 BRCA2 mutation carriers).We found no association with risk of ovarian cancer (OR=0.99, 95% CI 0.94-1.04, p=0.74) or breast cancer (OR=0.98, 95% CI 0.94-1.01, p=0.19) and results were consistent among mutation carriers (BRCA1, ovarian cancer HR=1.09, 95% CI 0.97-1.23, p=0.14, breast cancer HR=1.04, 95% CI 0.97-1.12, p=0.27; BRCA2, ovarian cancer HR=0.89, 95% CI 0.71-1.13, p=0.34, breast cancer HR=1.06, 95% CI 0.94-1.19, p=0.35). Null results were also obtained for associations with overall survival following ovarian cancer (HR=0.94, 95% CI 0.83-1.07, p=0.38), breast cancer (HR=0.96, 95% CI 0.87-1.06, p=0.38), and all other previously-reported associations.rs61764370 is not associated with risk of ovarian or breast cancer nor with clinical outcome for patients with these cancers. Therefore, genotyping this variant has no clinical utility related to the prediction or management of these cancers.
EVALuna2:9251

No Evidence That Genetic Variation in the Myeloid-Derived Suppressor Cell Pathway Influences Ovarian Cancer Survival - Sucheston-Campbell, Lara E.; Cannioto, Rikki; Clay, Alyssa I.; Etter, John Lewis; Eng, Kevin H.; Liu, Song; Battaglia, Sebastiano; Hu, Qiang; Szender, J. Brian; Minlikeeva, Albina; Joseph, Janine M.; Mayor, Paul; et al. (Cancer Epidemiology Biomarkers & Prevention, 2017)
Background: The precise mechanism by which the immune system is adversely affected in cancer patients remains poorly understood, but the accumulation of immunosuppressive/protumorigenic myeloid-derived suppressor cells (MDSCs) is thought to be a prominent mechanism contributing to immunologic tolerance of malignant cells in epithelial ovarian cancer (EOC). To this end, we hypothesized genetic variation in MDSC pathway genes would be associated with survival after EOC diagnoses.Methods: We measured the hazard of death due to EOC within 10 years of diagnosis, overall and by invasive subtype, attributable to SNPs in 24 genes relevant in the MDSC pathway in 10,751 women diagnosed with invasive EOC. Versatile Gene-based Association Study and the admixture likelihood method were used to test gene and pathway associations with survival.Results: We did not identify individual SNPs that were significantly associated with survival after correction for multiple testing (P < 3.5 × 10-5), nor did we identify significant associations between the MDSC pathway overall, or the 24 individual genes and EOC survival.Conclusions: In this well-powered analysis, we observed no evidence that inherited variations in MDSC-associated SNPs, individual genes, or the collective genetic pathway contributed to EOC survival outcomes.Impact: Common inherited variation in genes relevant to MDSCs was not associated with survival in women diagnosed with invasive EOC. Cancer Epidemiol Biomarkers Prev; 26(3); 420-4. ©2016 AACR.
EVALuna2:36152

No evidence that protein truncating variants in BRIP1 are associated with breast cancer risk: implications for gene panel testing - Easton, Douglas F.; Lesueur, Fabienne; Decker, Brennan; Michailidou, Kyriaki; Li, Jun; Allen, Jamie; Luccarini, Craig; Pooley, Karen A.; Shah, Mitul; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; et al. (Journal of Medical Genetics, 2016)
BACKGROUND: BRCA1 interacting protein C-terminal helicase 1 (BRIP1) is one of the Fanconi Anaemia Complementation (FANC) group family of DNA repair proteins. Biallelic mutations in BRIP1 are responsible for FANC group J, and previous studies have also suggested that rare protein truncating variants in BRIP1 are associated with an increased risk of breast cancer. These studies have led to inclusion of BRIP1 on targeted sequencing panels for breast cancer risk prediction. METHODS: We evaluated a truncating variant, p.Arg798Ter (rs137852986), and 10 missense variants of BRIP1, in 48 144 cases and 43 607 controls of European origin, drawn from 41 studies participating in the Breast Cancer Association Consortium (BCAC). Additionally, we sequenced the coding regions of BRIP1 in 13 213 cases and 5242 controls from the UK, 1313 cases and 1123 controls from three population-based studies as part of the Breast Cancer Family Registry, and 1853 familial cases and 2001 controls from Australia. RESULTS: The rare truncating allele of rs137852986 was observed in 23 cases and 18 controls in Europeans in BCAC (OR 1.09, 95% CI 0.58 to 2.03, p=0.79). Truncating variants were found in the sequencing studies in 34 cases (0.21%) and 19 controls (0.23%) (combined OR 0.90, 95% CI 0.48 to 1.70, p=0.75). CONCLUSIONS: These results suggest that truncating variants in BRIP1, and in particular p.Arg798Ter, are not associated with a substantial increase in breast cancer risk. Such observations have important implications for the reporting of results from breast cancer screening panels.
EVALuna2:33328

Non-embryo-destructive Extraction of Pluripotent Embryonic Stem Cells: Implications for Regenerative Medicine and Reproductive Medicine - Dittrich, Ralf; Beckmann, Matthias; Wuerfel, W. (Geburtshilfe und Frauenheilkunde, 2015)
On August 1, 2013, the German Patent and Trademark Office issued a patent for the "Non-embryo-destructive extraction of pluripotent embryonic stem cells, stem cells obtained by this process and their uses" (DE 10 2004 062 184 B4). The patent document describes a non-embryo-destructive process to harvest embryonic stem cells from the inner cell mass (ICM) during the blastocyst development stage. The patent application was filed with the German Patent Office in Munich on December 23, 2004 and the patent claim was published in 2006. The patent was granted on August 1, 2013. Processing the patent application was a lengthy affair due to the fact that, for a long time, the prevailing opinion in Germany was that genetic screening of embryos (preimplantation genetic diagnosis) was prohibited under the German Embryo Protection Act (ESchG). A ruling by the German Federal Court in 2010 proved this opinion to be false. Animal studies have provided the evidence that the described procedure is technically feasible; healthy offspring were born after stem cells were harvested from the blastocyst and stored. We report here on a technique for the non-embryo-destructive extraction of pluripotent embryonic stem cells together with potential future applications for stem cells harvested in this manner.
EVALuna2:17552

Novel approach for the assessment of ovarian follicles infiltration in polymeric electrospun patterned scaffolds - Raffel, Nathalie; Dittrich, Ralf; Bäuerle, Tobias; Seyler, Lisa; Amir, Fattahi; Hoffmann, Inge; Leal-Egaña, Aldo; Beckmann, Matthias; Boccaccini, Aldo R.; Liverani, Liliana (PLoS ONE, 2019)
Reproductive tissue engineering (REPROTEN) has been recently defined as the application of the tissue engineering approach targeting reproductive organs and several research works are focusing on this novel strategy. Being still an innovative field, most of the scaffold characterization techniques suitable for other tissue targets give inappropriate results, and there is the need to evaluate and investigate novel approaches. In particular the focus of this paper is the evaluation of the infiltration of ovarian follicles inside patterned electrospun scaffolds. Beyond the standard techniques, for the first time the use of magnetic resonance imaging (MRI) for this purpose is proposed and specific protocols for scaffold preparation are reported. Positive results in terms of evaluation of scaffolds incorporating follicles confirm this technique as highly effective for further applications in this field.
CRIS-Team Scopus Importer:2019-05-17

Novel Associations between Common Breast Cancer Susceptibility Variants and Risk-Predicting Mammographic Density Measures - Stone, Jennifer; Thompson, Deborah J.; Silva, Isabel Dos Santos; Scott, Christopher; Tamimi, Rulla M.; Lindstrom, Sara; Kraft, Peter; Hazra, Aditi; Li, Jingmei; Eriksson, Louise; Czene, Kamila; Hall, Per; et al. (Cancer Research, 2015)
Mammographic density measures adjusted for age and body mass index (BMI) are heritable predictors of breast cancer risk, but few mammographic density-associated genetic variants have been identified. Using data for 10,727 women from two international consortia, we estimated associations between 77 common breast cancer susceptibility variants and absolute dense area, percent dense area and absolute nondense area adjusted for study, age, and BMI using mixed linear modeling. We found strong support for established associations between rs10995190 (in the region of ZNF365), rs2046210 (ESR1), and rs3817198 (LSP1) and adjusted absolute and percent dense areas (all P < 10(-5)). Of 41 recently discovered breast cancer susceptibility variants, associations were found between rs1432679 (EBF1), rs17817449 (MIR1972-2: FTO), rs12710696 (2p24.1), and rs3757318 (ESR1) and adjusted absolute and percent dense areas, respectively. There were associations between rs6001930 (MKL1) and both adjusted absolute dense and nondense areas, and between rs17356907 (NTN4) and adjusted absolute nondense area. Trends in all but two associations were consistent with those for breast cancer risk. Results suggested that 18% of breast cancer susceptibility variants were associated with at least one mammographic density measure. Genetic variants at multiple loci were associated with both breast cancer risk and the mammographic density measures. Further understanding of the underlying mechanisms at these loci could help identify etiologic pathways implicated in how mammographic density predicts breast cancer risk.
EVALuna2:17571

Obesity and survival among women with ovarian cancer: results from the Ovarian Cancer Association Consortium - Nagle, C. M.; Dixon, S. C.; Jensen, A.; Kjaer, S. K.; Modugno, F.; Defazio, A.; Fereday, S.; Hung, J.; Johnatty, S. E.; Fasching, Peter; Beckmann, Matthias; Lambrechts, D.; et al. (British Journal of Cancer, 2015)
Observational studies have reported a modest association between obesity and risk of ovarian cancer; however, whether it is also associated with survival and whether this association varies for the different histologic subtypes are not clear. We undertook an international collaborative analysis to assess the association between body mass index (BMI), assessed shortly before diagnosis, progression-free survival (PFS), ovarian cancer-specific survival and overall survival (OS) among women with invasive ovarian cancer.We used original data from 21 studies, which included 12 390 women with ovarian carcinoma. We combined study-specific adjusted hazard ratios (HRs) using random-effects models to estimate pooled HRs (pHR). We further explored associations by histologic subtype.Overall, 6715 (54%) deaths occurred during follow-up. A significant OS disadvantage was observed for women who were obese (BMI: 30-34.9, pHR: 1.10 (95% confidence intervals (CIs): 0.99-1.23); BMI: ?35, pHR: 1.12 (95% CI: 1.01-1.25)). Results were similar for PFS and ovarian cancer-specific survival. In analyses stratified by histologic subtype, associations were strongest for women with low-grade serous (pHR: 1.12 per 5 kg m(-2)) and endometrioid subtypes (pHR: 1.08 per 5 kg m(-2)), and more modest for the high-grade serous (pHR: 1.04 per 5 kg m(-2)) subtype, but only the association with high-grade serous cancers was significant.Higher BMI is associated with adverse survival among the majority of women with ovarian cancer.
EVALuna2:17568

Occurrence and characteristics of patients with de novo advanced breast cancer according to patient and tumor characteristics – A retrospective analysis of a real world registry - Muller, Volkmar; Hein, Alexander; Hartkopf, Andreas D.; Fasching, Peter; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Luftner, Diana; Wallwiener, Markus; Beckmann, Matthias; et al. (European Journal of Cancer, 2022)
Background: Patients with de novo metastatic breast cancer (dnMBC) may have different clinical and pathological characteristics. In studies concerned with first-line metastatic patients, the proportion of these patients without secondary resistance mechanisms may have a large influence ont the study results. The aim of this study was to identify patient and tumor characteristics that are associated with dnMBC vs. recurrent MBC (rMBC). Methods: This is a retrospective analysis of data prospectively collected in the PRAEGNANT metastatic breast cancer registry (NCT02338167). Firs line treated patients were eligible. Patient and tumor characteristics were compared with common disease and tumor characteristics relative to de novo metastatic status, as well as early and late recurrences after primary disease without metastases. Results: Among the 947 patients identified, 355 were included with de novo metastatic disease (37.5%). Older age and HER2-positive disease were significantly associated with a higher frequency of dnMBC. Patients younger than 50, 50–69, or 70 years or older had dnMBC frequencies of 22.7%, 44.0%, and 57.6%, respectively. HER2-positive patients had dnMBC at initial presentation in 49.1% of cases, in comparison with 21.9%, 35.5%, and 37.6% in patients with triple-negative, luminal A–like and luminal B–like breast cancer, respectively. Conclusion: Age and breast cancer subtype are associated with the frequency of first-line MBC patients. Inclusion criteria concerning age or breast cancer subtype can influence the frequency of these patients in a selected patient population and can therefore modify the number of patients with secondary resistance to specific therapies in clinical trials.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Advanced breast cancer; Clinical trials; de novo metastatic breast cancer; Recurrent breast cancer metastases

Oncological heath care networks. The triangle formed by research, quality, and competition - Schrauder, Michael G.; Bamberg, Michael; Beckmann, Matthias (Onkologe, 2016)
The establishment of medical networks has recently gained momentum in health care policy. However, many questions regarding this topic still remain unanswered, including how exactly the terms "supply network" and "network" are defined, and the relevance of such structures in current oncological care in Germany is vague. This manuscript is based on selective literature research in different databases using the search term "networks of medical facilities in oncology". Searching the Internet with the term "supply network" mainly delivers hits related to supply of electricity. Searching for an exact definition of oncological supply networks is largely unfruitful, even when concrete search terms are used. If less vague statements on oncological networks are found, these vary greatly depending on the context. We present an extensive description of the adoption and significance of networking among oncological facilities in the German public health sector. Moreover, the legal requirements as well as future development opportunities of health care services within oncological networks are characterized.
EVALuna2:32990

Operative techniques and complications of extraction and transplantation of ovarian tissue: the Erlangen experience - Beckmann, Matthias; Dittrich, Ralf; Lotz, Laura; Oppelt, Patricia; Findeklee, Sebastian; Hildebrandt, Thomas; Heusinger, Katharina; Cupisti, Susanne; Mueller, Andreas (Archives of Gynecology and Obstetrics, 2017)
PURPOSE: Extracting ovarian tissue before oncologic therapy and transplanting it afterwards are increasingly being used to preserve fertility in women. This study describes standardized and safe operative procedures, with few complications, and reports the resulting ovarian function and pregnancy rates. METHODS: The standardized operative techniques for removing and transplanting ovarian tissue used at the Erlangen center are: for tissue removal, one-third to half of the tissue from one ovary is excised with scissors, without tissue coagulation; for subsequent transplantation, pieces of ovarian tissue are placed in a retroperitoneal pocket without closure of the pocket. RESULTS: Between January 2007 and December 2015, ovarian tissue was extracted in 399 women and transplanted following cancer therapy in 38. No surgical complications were observed within 28 days. To date, there have been ten pregnancies and nine live births after transplantation in seven different women; 26 of the 38 women developed hormonal activity, confirmed by a menstrual cycle or raised serum estradiol levels. CONCLUSIONS: The techniques for laparoscopic removal and transplantation of ovarian tissue described here provide a standardized method with a very low risk of complications. The pregnancy rate after ovarian tissue transplantation, currently 15-30%, can be expected to rise further in the near future.
EVALuna2:36149

Opinion of the German Society of Gynecology and Obstetrics on the Topic - More Knowledge "Risk Factors for Breast Cancer" - Seelbach-Goebel, Birgit; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36147

Optimization of Porcine Ovarian Follicle Isolation Methods for Better Developmental Potential - Fattahi, Amir; Liverani, Liliana; Dittrich, Ralf; Hoffmann, Inge; Boccaccini, Aldo R.; Beckmann, Matthias; Bleisinger, Nathalie (Tissue Engineering - Part A, 2020)
In the present study, we present a comparative analysis among the outputs of porcine follicle isolation using either mechanical technique alone or in combination with enzymes, proposing an optimized protocol useful for all further applications related to folliclein vitrogrowth and reproductive tissue engineering. The porcine follicles were isolated using mechanical technique alone (hand blender and scalpels) or in combination with collagenase or Liberase Dispase High (DH) at different doses applying different protocols. Finally, the number, morphology, and stage of isolated follicles were compared between the protocols. Moreover, the follicle viability (live/dead assay) and morphology (rhodamine phalloidin and 4 ',6-diamidino-2-phenylindole staining and scanning electron microscopy analysis) were evaluated after 10 days of culture. We found an optimum protocol for intact follicle isolation using the mechanical technique in combination with enzymes at a concentration of 0.5 mg/mL. However, the number of total isolated follicles and primordial follicles was significantly higher when collagenase was used compared to Liberase DH (p < 0.05), while Liberase DH could isolate a significantly higher percentage of preantral follicles. After 10 days of culture, the morphology and health status of follicles were statistically higher when Liberase DH was used in comparison with collagenase. Moreover, on the follicles extracted with Liberase DH, it was possible to observe theca cells covering part of the follicle surface. In conclusion, we demonstrated that the intact primary or secondary follicles could not be obtained using only mechanical methods, which led to the isolation of denuded oocytes and dramatically damaged follicles. We concluded that the collagenase-based follicle isolation could negatively affect the morphology and developmental potential of the follicles. Moreover, the incubation of ovarian cortex tissues with Liberase DH solution is an optimized protocol for porcine ovarian follicle isolation with developmental competence.
CRIS-Team WoS Importer:2020-07-24

Orofacial clefts alter early life oral microbiome maturation towards higher levels of potentially pathogenic species: A prospective observational study - Seidel, Corinna L.; Strobel, Karin; Weider, Matthias; Tschaftari, Marco; Unertl, Christoph; Willershausen, Ines; Weber, Manuel; Hörning, André; Morhart, Patrick; Schneider, Michael; Beckmann, Matthias; Bogdan, Christian; et al. (Journal of Oral Microbiology, 2023)
Orofacial clefts (OFC) present different phenotypes with a postnatal challenge for oral microbiota development. In order to investigate the impact of OFC on oral microbiota, smear samples from 15 neonates with OFC and 17 neonates without OFC were collected from two oral niches (tongue, cheek) at two time points, i.e. after birth (T0: Ø3d OFC group; Ø2d control group) and 4–5 weeks later (T1: Ø32d OFC group; Ø31d control group). Subsequently, the samples were analyzed using next-generation sequencing. We detected a significant increase of alpha diversity and anaerobic and Gram-negative species from T0 to T1 in both groups. Further, we found that at T1 OFC neonates presented a significantly lower alpha diversity (lowest values for high cleft severity) and significantly higher levels of Enterobacteriaceae (Citrobacter, Enterobacter, Escherichia-Shigella, Klebsiella), Enterococcus, Bifidobacterium, Corynebacterium, Lactocaseibacillus, Staphylococcus, Acinetobacter and Lawsonella compared to controls. Notably, neonates with unilateral and bilateral cleft lip and palate (UCLP/BCLP) presented similarities in beta diversity and a mixture with skin microbiota. However, significant differences were seen in neonates with cleft palate only compared to UCLP/BCLP with higher levels of anaerobic species. Our findings revealed an influence of OFC as well as cleft phenotype and severity on postnatal oral microbiota maturation.
CRIS-Team Scopus Importer:2023-01-20
Keywords: early life dysbiosis; microbiome maturation; neonates; oral microbiome; Orofacial clefts

Orofacial clefts lead to increased pro-inflammatory cytokine levels on neonatal oral mucosa - Seidel, Corinna L.; Percivalle, Elena; Tschaftari, Marco; Weider, Matthias; Strobel, Karin; Willershausen, Ines; Unertl, Christoph; Schmetzer, Helga M.; Weber, Manuel; Schneider, Michael; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Immunology, 2022)
Orofacial clefts (OFC) are frequent congenital malformations characterized by insufficient separation of oral and nasal cavities and require presurgical infant orthopedics and surgical interventions within the first year of life. Wound healing disorders and higher prevalence of gingivitis and plaque levels are well-known challenges in treatment of children with OFC. However, oral inflammatory mediators were not investigated after birth using non-invasive sampling methods so far. In order to investigate the impact of OFC on oral cytokine levels, we collected tongue smear samples from 15 neonates with OFC and 17 control neonates at two time points (T), T0 at first consultation after birth, and T1, 4 to 5 weeks later. The samples were analyzed using multiplex immunoassay. Overall, we found significantly increased cytokine levels (TNF, IL-1β/-2/-6/-8/-10) in tongue smear samples from neonates with OFC compared to controls, especially at T0. The increase was even more pronounced in neonates with a higher cleft severity. Further, we detected a significant positive correlation between cleft severity score and distinct pro-inflammatory mediators (GM-CSF, IL-1β, IL-6, IL-8) at T0. Further, we found that breast-milk (bottle) feeding was associated with lower levels of pro-inflammatory cytokines (IL-6/-8) in neonates with OFC compared to formula-fed neonates. Our study demonstrated that neonates with OFC, especially with high cleft severity, are characterized by markedly increased inflammatory mediators in tongue smear samples within the first weeks of life potentially presenting a risk for oral inflammatory diseases. Therefore, an inflammatory monitoring of neonates with (severe) OFC and the encouragement of mother to breast-milk (bottle) feed might be advisable after birth and/or prior to cleft surgery.
CRIS-Team Scopus Importer:2022-12-16
Keywords: cleft lip and palate; cytokines; mucosal homeostasis; mucosal immunity; neonates; oral; oral inflammation; orofacial clefts

Outcome and prognosis in uterine sarcoma and malignant mixed Mullerian tumor - Burghaus, Stefanie; Halmen, Sonja; Gaß, Paul; Mehlhorn, Grit; Schrauder, Michael G.; Lux, Michael P.; Renner, Stefan; Beckmann, Matthias; Hein, Alexander; Thiel, Falk (Archives of Gynecology and Obstetrics, 2016)
PURPOSE: There is low evidence regarding the optimal treatment in patients with uterine sarcomas and malignant mixed Mullerian tumors (MMMTs). This study provides an overview of experience at our center with patients diagnosed with uterine sarcoma and MMMT, in relation to the clinical management and outcome. METHODS: The medical records for 143 patients with low-grade endometrial stromal sarcoma (ESS), leiomyosarcoma (LMS), and high-grade (undifferentiated) endometrial sarcoma (UES) and MMMT were reviewed. All available clinical and pathological data were collected and analyzed. Putative prognostic factors were entered into a multivariate analysis using a Cox proportional hazards ratio model, and survival data were calculated. RESULTS: The 5-year overall survival rates were significantly different between patients with ESS, LMS, and UES and MMMT (86 vs. 40 vs. 57 vs. 45 %; P < 0.001). The multivariate analysis showed that the patients' age, higher FIGO stage (III-IV), a history of smoking, prior pelvic radiation, diabetes, and residual tumor after surgery were associated with a poorer overall survival. Histological subtypes of LMS (HR 4.68; 95 % CI 1.35-16.17), UES (HR 1.21; 95 % CI 0.26-5.77) and MMMT (HR 1.63; 95 % CI 0.42-6.43) were also associated with a poorer overall survival than ESS (P = 0.008). Adjuvant therapies showed no associations with overall survival. CONCLUSIONS: Adjuvant therapy has so far not shown any overall survival benefit, and the focus is therefore on primary surgery. In future studies, the entities should be investigated separately in relation to prognostic factors and effective therapeutic management.
EVALuna2:32968

Ovarian tissue cryopreservation and retransplantation–what do patients think about it? - Lotz, Laura; Maktabi, Amina; Hoffmann, Inge; Findeklee, Sebastian; Beckmann, Matthias; Dittrich, Ralf (Reproductive Biomedicine Online, 2016)
Cryopreservation of ovarian tissue has been successfully applied clinically, with over 60 live births to date. The aim of the present study was to perform a survey of patients who have had ovarian tissue cryopreserved in the Department of Obstetrics and Gynecology, Erlangen University Hospital, in order to obtain information about: why patients opt for fertility preservation; their current fertility; pregnancy attempts and outcomes; and their intended plans for the cryopreserved ovarian tissue. In total, 147 women took part in the survey (average age 25.0 ± 7.0 years; response rate 48%; mean follow-up period 6 years). Sixty-six reported regular menstrual cycles; 48 were amenorrhoeic. Sixty-two women had tried to conceive; 33 reported pregnancies. Twenty-five had delivered healthy children after conceiving naturally; eight had conceived with assisted reproduction. Five patients had had their ovarian tissue retransplanted. Although many patients continued to have ovarian function, none of them regretted choosing cryopreservation of ovarian tissue. Cryopreservation of ovarian tissue is an effective option and is very important for women diagnosed with cancer. Analyses of the clinical outcomes in these patients are essential in order to identify those patients capable of benefiting most from the procedure and in order to improve the technique.
EVALuna2:32986

Ovarian Tissue Transplantation: Experience From Germany and Worldwide Efficacy - Lotz, Laura; Dittrich, Ralf; Hoffmann, Inge; Beckmann, Matthias (Clinical Medicine Insights: Reproductive Health, 2019)
Extraction of ovarian tissue prior to oncologic therapy and subsequent transplantation is being performed increasingly often to preserve fertility in women. The procedure can be performed at any time of the cycle and, therefore, generally does not lead to any delay in oncological therapy. Success rates with transplantation of cryopreserved ovarian tissue have reached promising levels. More than 130 live births have been reported worldwide with the aid of cryopreserved ovarian tissue and the estimated birth rate is currently approximately 30%. In Germany, Austria, and Switzerland, the FertiPROTEKT consortium has successfully achieved 21 pregnancies and 17 deliveries generated after 95 ovarian tissue transplantations by 2015, one of the largest case series worldwide confirming that ovarian tissue cryopreservation and transplantation are successful. Approximately, more than 400 ovarian tissue cryopreservation procedures are performed each year in the FertiPROTEKT consortium. and the request and operations for ovarian tissue transplantation have increased in recent years. Therefore. recommendations for managing transplantation of ovarian tissue to German-speaking reproductive medicine centers were developed. In this overview. these recommendations and our experience in ovarian tissue transplantation are presented and discussed with international procedures.
CRIS-Team WoS Importer:2019-10-22

Ovarian tissue transplantations in 196 women by FertiPROTEKT- live birth rate of 26.5% per woman is associated with female age and first versus repeated transplantation - Lotz, Laura; Bender-Liebenthron, J.; Dittrich, Ralf; Häberle, Lothar; Beckmann, Matthias; Germeyer, A.; Korell, M.; Saenger, N.; Von Wolff, M. (HUMAN REPRODUCTION, 2022)
CRIS-Team WoS Importer:2022-10-21

Oxytocin receptor DNA methylation in postpartum depression - Kimmel, Mary; Clive, Makena; Gispen, Fiona; Guintivano, Jerry; Brown, Tori; Cox, Olivia; Beckmann, Matthias; Kornhuber, Johannes; Fasching, Peter; Osborne, Lauren M.; Binder, Elisabeth; Payne, Jennifer L.; et al. (Psychoneuroendocrinology, 2016)
The oxytocin receptor (OXTR) is a key regulator of stress and anxiety and may be regulated by both psychosocial risk factors and gonadal hormones, making it an attractive candidate for study in postpartum depression (PPD). The objective of this study was to investigate both serum hormone and PPD specific DNA methylation variation in the OXTR. Illumina HM450 microarray data generated in a prospective PPD cohort identified significant associations (P=0.014) with PPD in an intronic region in the OXTR located 4bp proximal to an estrogen receptor (ER) binding region. Pyrosequencing confirmed moderate evidence for an interaction of CpGs in the region with childhood abuse status to mediate PPD. These CpGs located on chr3 at positions 8810078 and 8810069 exhibited significant associations with postpartum depression scores from an independent cohort of 240 women with no prior psychiatric history. Hormone analysis suggested a PPD specific negative correlation of DNA methylation in the region with serum estradiol levels. Estradiol levels and OXTR DNA methylation exhibited a significant interaction to associate with the ratio of allopregnanolone to progesterone. Cumulatively, the data corroborate our previous hypotheses of a PPD specific increased sensitivity of epigenetic reprogramming at estrogen target genes and suggests that OXTR epigenetic variation may be an important mediator of mood relevant neuroactive steroid production.
EVALuna2:23775

p53 and p16 expression profiles in vulvar cancer: a translational analysis by the Arbeitsgemeinschaft Gynäkologische Onkologie Chemo and Radiotherapy in Epithelial Vulvar Cancer study group - Woelber, Linn; Prieske, Katharina; Eulenburg, Christine; Oliveira-Ferrer, Leticia; de Gregorio, Nikolaus; Klapdor, Ruediger; Kalder, Matthias; Braicu, Iona; Fuerst, Sophie; Klar, Maximilian; Strauss, Hans Georg; Beckmann, Matthias; et al. (American Journal of Obstetrics and Gynecology, 2021)
Background: There are 2 known pathways for tumorigenesis of vulvar squamous cell carcinoma—a human papillomavirus–dependent pathway characterized by p16 overexpression and a human papillomavirus–independent pathway linked to lichen sclerosus, characterized by TP53 mutation. A correlation of human papillomavirus dependency with a favorable prognosis has been proposed. Objective: The objective of the study was to further understand the role of human papillomavirus and p53 status in vulvar squamous cell carcinoma and characterize its clinical relevance. Study Design: The Arbeitsgemeinschaft Gynaecological Oncology Chemo and Radiotherapy in Epithelial Vulvar Cancer-1 study is a retrospective cohort study of 1618 patients with primary vulvar squamous cell carcinoma Fédération Internationale de Gynécologie et d'Obstétrique stage ≥1B treated at 29 gynecologic cancer centers in Germany between 1998 and 2008. For this translational substudy, formalin-fixed paraffin-embedded tissue was collected. A tissue microarray was constructed (n=652 samples); p16 and p53 expression was determined by immunohistochemistry. Human papillomavirus status and subtype were analyzed by polymerase chain reaction. Results: p16 immunohistochemistry was positive in 166 of 550 tumors (30.2%); p53 staining in 187 of 597 tumors (31.3%). Only tumors with available information regarding p16 and p53 immunohistochemistry and without p53 silent expression pattern were further analyzed (n=411); 3 groups were defined: p53+ (n=163), p16+/p53− (n=132), and p16−/p53− (n=116). Human papillomavirus DNA was detected in 85.6% of p16+/p53− tumors; human papillomavirus-16 was the most common subtype (86.3%). Patients with p16+ tumors were younger (64 vs 72 years for p53+, respectively, 69 years for p16−/p53− tumors; P<.0001) and showed lower rates of lymph-node involvement (28.0% vs 42.3% for p53+, respectively, 30.2% for p16−/p53− tumors; P=.050). Notably, 2-year-disease-free and overall survival rates were significantly different among the groups: disease-free survival, 47.1% (p53+), 60.2% (p16−/p53−), and 63.9% (p16+/p53−) (P<.001); overall survival, 70.4% (p53+), 75.4% (p16−/p53−), and 82.5% (p16+/p53−) (P=.002). In multivariate analysis, the p16+/p53− phenotype showed a consistently improved prognosis compared with the other groups (hazard ratio, 0.66; 95% confidence interval, 0.44–0.99; P=.042). Conclusion: p16 overexpression is associated with an improved prognosis whereas p53 positivity is linked to an adverse outcome. Our data support the hypothesis of a clinically relevant third subgroup of vulvar squamous cell carcinoma with a p53−/p16− phenotype showing an intermediate prognosis that needs to be further characterized.
CRIS-Team Scopus Importer:2021-04-09
Keywords: HPV; p16; p53; prognosis; vulvar cancer

PALB2, CHEK2 and ATM rare variants and cancer risk: data from COGS - Southey, Melissa C.; Goldgar, David E.; Winqvist, Robert; Pylkas, Katri; Couch, Fergus; Tischkowitz, Marc; Foulkes, William D.; Dennis, Joe; Michailidou, Kyriaki; Van Rensburg, Elizabeth J.; Heikkinen, Tuomas; Nevanlinna, Heli; et al. (Journal of Medical Genetics, 2016)
The rarity of mutations in PALB2, CHEK2 and ATM make it difficult to estimate precisely associated cancer risks. Population-based family studies have provided evidence that at least some of these mutations are associated with breast cancer risk as high as those associated with rare BRCA2 mutations. We aimed to estimate the relative risks associated with specific rare variants in PALB2, CHEK2 and ATM via a multicentre case-control study.We genotyped 10 rare mutations using the custom iCOGS array: PALB2 c.1592delT, c.2816T>G and c.3113G>A, CHEK2 c.349A>G, c.538C>T, c.715G>A, c.1036C>T, c.1312G>T, and c.1343T>G and ATM c.7271T>G. We assessed associations with breast cancer risk (42 671 cases and 42 164 controls), as well as prostate (22 301 cases and 22 320 controls) and ovarian (14 542 cases and 23 491 controls) cancer risk, for each variant.For European women, strong evidence of association with breast cancer risk was observed for PALB2 c.1592delT OR 3.44 (95% CI 1.39 to 8.52, p=7.1×10(-5)), PALB2 c.3113G>A OR 4.21 (95% CI 1.84 to 9.60, p=6.9×10(-8)) and ATM c.7271T>G OR 11.0 (95% CI 1.42 to 85.7, p=0.0012). We also found evidence of association with breast cancer risk for three variants in CHEK2, c.349A>G OR 2.26 (95% CI 1.29 to 3.95), c.1036C>T OR 5.06 (95% CI 1.09 to 23.5) and c.538C>T OR 1.33 (95% CI 1.05 to 1.67) (p<=0.017). Evidence for prostate cancer risk was observed for CHEK2 c.1343T>G OR 3.03 (95% CI 1.53 to 6.03, p=0.0006) for African men and CHEK2 c.1312G>T OR 2.21 (95% CI 1.06 to 4.63, p=0.030) for European men. No evidence of association with ovarian cancer was found for any of these variants.This report adds to accumulating evidence that at least some variants in these genes are associated with an increased risk of breast cancer that is clinically important.
EVALuna2:6832

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche - Perry, John R. B.; Day, Felix; Elks, Cathy E.; Sulem, Patrick; Thompson, Deborah J.; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I.; Esko, Toenu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q.; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and ?-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
EVALuna2:17437

Pathology of Tumors Associated With Pathogenic Germline Variants in 9 Breast Cancer Susceptibility Genes - Mavaddat, Nasim; Dorling, Leila; Carvalho, Sara; Allen, Jamie; Gonzalez-Neira, Anna; Keeman, Renske; Bolla, Manjeet K.; Dennis, Joe; Wang, Qin; Ahearn, Thomas U.; Andrulis, Irene L.; Beckmann, Matthias; et al. (JAMA Oncology, 2022)
IMPORTANCE Rare germline genetic variants in several genes are associated with increased breast cancer (BC) risk, but their precise contributions to different disease subtypes are unclear. This information is relevant to guidelines for gene panel testing and risk prediction.
CRIS-Team WoS Importer:2022-02-11

Pathway-Based Analysis of Genome-Wide Association Data Identified SNPs in as Biomarker for Chemotherapy- Induced Neutropenia in Breast Cancer Patients - Bidadi, Behzad; Liu, Duan; Kalari, Krishna R.; Rübner, Matthias; Hein, Alexander; Beckmann, Matthias; Rack, Brigitte; Janni, Wolfgang; Fasching, Peter; Weinshilboum, Richard M.; Wang, Liewei (Frontiers in Pharmacology, 2018)
Neutropenia secondary to chemotherapy in breast cancer patients can be life-threatening and there are no biomarkers available to predict the risk of drug-induced neutropenia in those patients. We previously performed a genome-wide association study (GWAS) for neutropenia events in women with breast cancer who were treated with 5-fluorouracil, epirubicin and cyclophosphamide and recruited to the SUCCESS-A trial. A genome-wide significant single-nucleotide polymorphism (SNP) signal in the tumor necrosis factor superfamily member 13B () gene, encoding the cytokine B-cell activating factor (BAFF), was identified in that GWAS. Taking advantage of these existing GWAS data, in the present study we utilized a pathway-based analysis approach by leveraging knowledge of the pharmacokinetics and pharmacodynamics of drugs and breast cancer pathophysiology to identify additional SNPs/genes associated with the underlying etiology of chemotherapy-induced neutropenia. We identified three SNPs in the hyaluronan mediated motility receptor ( gene that were significantly associated with neutropenia ( < 1.0E-04). Those three SNPs were trans-expression quantitative trait loci for the expression of ( < 1.0E-04). The minor allele of these SNPs was associated with a decreased mRNA level. Additional functional studies performed with lymphoblastoid cell lines (LCLs) demonstrated that LCLs possessing the minor allele for the SNPs were more sensitive to drug treatment. Knock-down of in LCLs and HL-60 promyelocytic cells and treatment of those cells with BAFF modulated the cell sensitivity to chemotherapy treatment. These results demonstrate that SNP-dependent cytotoxicity of these chemotherapeutic agents might be related to expression level. In summary, utilizing a pathway-based approach for the analysis of GWAS data, we identified additional SNPs in the gene that were associated with neutropenia and also were correlated with expression.
EVALuna2:56169

Patient survival and tumor characteristics associated with CHEK2:p.I157T - findings from the Breast Cancer Association Consortium - Muranen, Taru A.; Blomqvist, Carl; Doerk, Thilo; Jakubowska, Anna; Heikkila, Paivi; Fagerholm, Rainer; Greco, Dario; Aittomaki, Kristiina; Bojesen, Stig E.; Shah, Mitul; Dunning, Alison M.; Rhenius, Valerie; et al. (Breast Cancer Research, 2016)
BACKGROUND: P.I157T is a CHEK2 missense mutation associated with a modest increase in breast cancer risk. Previously, another CHEK2 mutation, the protein truncating c.1100delC has been associated with poor prognosis of breast cancer patients. Here, we have investigated patient survival and characteristics of breast tumors of germ line p.I157T carriers. METHODS: We included in the analyses 26,801 European female breast cancer patients from 15 studies participating in the Breast Cancer Association Consortium. We analyzed the association between p.I157T and the clinico-pathological breast cancer characteristics by comparing the p.I157T carrier tumors to non-carrier and c.1100delC carrier tumors. Similarly, we investigated the p.I157T associated risk of early death, breast cancer-associated death, distant metastasis, locoregional relapse and second breast cancer using Cox proportional hazards models. Additionally, we explored the p.I157T-associated genomic gene expression profile using data from breast tumors of 183 Finnish female breast cancer patients (ten p.I157T carriers) (GEO: GSE24450). Differential gene expression analysis was performed using a moderated t test. Functional enrichment was investigated using the DAVID functional annotation tool and gene set enrichment analysis (GSEA). The tumors were classified into molecular subtypes according to the St Gallen 2013 criteria and the PAM50 gene expression signature. RESULTS: P.I157T was not associated with increased risk of early death, breast cancer-associated death or distant metastasis relapse, and there was a significant difference in prognosis associated with the two CHEK2 mutations, p.I157T and c.1100delC. Furthermore, p.I157T was associated with lobular histological type and clinico-pathological markers of good prognosis, such as ER and PR expression, low TP53 expression and low grade. Gene expression analysis suggested luminal A to be the most common subtype for p.I157T carriers and CDH1 (cadherin 1) target genes to be significantly enriched among genes, whose expression differed between p.I157T and non-carrier tumors. CONCLUSIONS: Our analyses suggest that there are fundamental differences in breast tumors of CHEK2:p.I157T and c.1100delC carriers. The poor prognosis associated with c.1100delC cannot be generalized to other CHEK2 mutations.
EVALuna2:32945

Pattern of SMARCB1 (INI1) and SMARCA4 (BRG1) in poorly differentiated endometrioid adenocarcinoma of the uterus: analysis of a series with emphasis on a novel SMARCA4-deficient dedifferentiated rhabdoid variant - Strehl, Johanna D.; Wachter, David; Fiedler, Jutta; Heimerl, Engelbert; Beckmann, Matthias; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2015)
The role of the switch/sucrose nonfermenting chromatin remodeling complex in the initiation and progression of cancer is emerging. In the female genital tract, only ovarian small cell carcinoma, hypercalcemic type harbors recurrent inactivating SMARCA4 mutations. Otherwise, only rare case reports documented SMARCB1 involvement in endometrial cancer. We analyzed 24 grade 3 uterine endometrioid adenocarcinomas and 2 undifferentiated carcinomas for immunohistochemical expression of SMARCB1 and SMARCA4. All tumors showed high-grade nuclear features with a predominance of solid growth pattern. All cases showed intact nuclear SMARCB1 expression in all tumor cells. However, 1 case of a 78-year-old woman showed complete loss of SMARCA4 in 90% of the tumor with retained expression in 10% of the tumor. The SMARCA4-intact component was a moderate-to-poorly differentiated endometrioid adenocarcinoma. The SMARCA4-deficient dominating component showed solid growth of highly anaplastic undifferentiated large cells with prominent rhabdoid features. None of the 25 SMARCA4-intact cases showed rhabdoid cell morphology. To our knowledge, this is the first systematic study of SMARCB1 and SMARCA4 expression in endometrioid adenocarcinoma of uterus and the first description of a novel SMARCA4-deficient variant of dedifferentiated/undifferentiated endometrial carcinoma. The presence of a differentiated SMARCA4-intact endometrioid component points to a novel pathway of dedifferentiation in endometrioid adenocarcinoma as a consequence of a "second hit." This case further underlines the close link between the "rhabdoid phenotype" and the SWI/SNF pathway.
EVALuna2:6700

Patterns and Trends of Herbal Medicine Use among Patients with Gynecologic Cancer - Theuser, Anna Katharin; Hack, Carolin; Fasching, Peter; Antoniadis, Sophia; Grasruck, Katharina; Wasner, Sonja; Knoll, Stefanie; Sievers, Hartwig; Beckmann, Matthias; Thiel, Falk C. (Geburtshilfe und Frauenheilkunde, 2021)
Background More and more information about complementary and integrative medicine is becoming available, especially among cancer patients. However, little is known about the use of herbal medicine by patients with gynecologic cancers. This study aimed to assess the use of herbal products by gynecologic cancer patients compared with healthy controls. Methods This cross-sectional study was conducted at the Department for Gynecology and Obstetrics of Erlangen University Hospital and included 201 patients with gynecologic cancer and 212 healthy controls. Use of herbal medicines was evaluated using a standardized questionnaire. Medical information on cancer patients was collected from hospital records. Group comparisons were done using a logistic regression model. Risk ratios were assessed using a Poisson regression model. Results Gynecologic cancer patients used herbal medicine significantly less often than healthy persons. 69% of gynecologic cancer patients and 81% of healthy participants reported using herbal products. 40% of cancer patients and 56% of healthy persons reported using plants for medicinal purposes. Motives of cancer patients for using herbal medicine included treatment of cancer-related symptoms. The major source of information for both groups was family and friends. Conclusions Although herbal medicine was used less by patients with gynecologic cancer, herbal products were used by both cancer patients and healthy individuals. To provide cancer patients with optimal therapy, oncologists should be informed about the herbal products used by their patients as this will allow them to take their patients' self-medication with herbal medicine into account. Counseling by oncologists on the use of herbal medicine should be encouraged.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cancer; complementary and alternative medicine; gynecologic oncology; herbal medicine; integrative medicine

Pelvic Lymphadenectomy in Vulvar Cancer – Does it make sense? - Woelber, Linn; Bommert, Mareike; Prieske, Katharina; Fischer, Inger; Zu Eulenburg, Christine; Vettorazzi, Eik; Harter, Philipp; Jueckstock, Julia; Hilpert, Felix; De Gregorio, Niko; Iborra, Severine; Sehouli, Jalid; et al. (Geburtshilfe und Frauenheilkunde, 2020)
Since the publication of the updated German guideline in 2015, the recommendations for performing pelvic lymphadenectomy (LAE) in patients with vulvar cancer (VSCC) have changed considerably. The guideline recommends surgical lymph node staging in all patients with a higher risk of pelvic lymph node involvement. However, the current data do not allow the population at risk to be clearly defined, therefore, the indication for pelvic lymphadenectomy is still not clear. There are currently two published German patient populations who had pelvic LAE which can be used to investigate both the prognostic effect of histologically verified pelvic lymph node metastasis and the relation between inguinal and pelvic lymph node involvement. A total of 1618 patients with primary FIGO stage ≥ IB VSCC were included in the multicenter AGO CaRE-1 study (1998-2008), 70 of whom underwent pelvic LAE. During a retrospective single-center evaluation carried out at the University Medical Center Hamburg-Eppendorf (UKE), a total of 514 patients with primary VSCC treated between 1996-2018 were evaluated, 21 of whom underwent pelvic LAE. In both cohorts, around 80% of the patients who underwent pelvic LAE were inguinally node-positive, with a median number of three affected groin lymph nodes. There were no cases of pelvic lymph node metastasis without inguinal lymph node metastasis in either of the two cohorts. Between 33-35% of the inguinal node-positive patients also had pelvic lymph node metastasis; the median number of affected groin lymph nodes in these patients was high (> 4), and the maximum median diameter of the largest inguinal metastasis was > 40 mm in both cohorts. Pelvic lymph node staging and pelvic radiotherapy is therefore probably not necessary for the majority of node-positive patients with VSCC, as the relevant risk of pelvic lymph node involvement was primarily found in node-positive patients with high-grade disease. More, ideally prospective data collections are necessary to validate the relation between inguinal and pelvic lymph node involvement.
CRIS-Team Scopus Importer:2020-12-25
Keywords: lymph node metastasis; pelvic lymphadenectomy; prognosis; recurrence; vulvar cancer

Percent mammographic density and dense area as risk factors for breast cancer - Rauh, C.; Hack, Caroline; Häberle, Lothar; Hein, Alexander; Engel, Anne; Schrauder, Michael G.; Fasching, Peter; Jud, Sebastian; Ekici, Arif Bülent; Loehberg, C. R.; Meier-Meitinger, Martina; Ozan-Mergner, Sevil Julia; et al. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Mammographic characteristics are known to be correlated to breast cancer risk. Percent mammographic density (PMD), as assessed by computer-assisted methods, is an established risk factor for breast cancer. Along with this assessment the absolute dense area (DA) of the breast is reported as well. Aim of this study was to assess the predictive value of DA concerning breast cancer risk in addition to other risk factors and in addition to PMD. Methods: We conducted a case control study with hospital-based patients with a diagnosis of invasive breast cancer and healthy women as controls. A total of 561 patients and 376 controls with available mammographic density were included into this study. We describe the differences concerning the common risk factors BMI, parital status, use of hormone replacement therapy (HRT) and menopause between cases and controls and estimate the odds ratios for PMD and DA, adjusted for the mentioned risk factors. Furthermore we compare the prediction models with each other to find out whether the addition of DA improves the model. Results: Mammographic density and DA were highly correlated with each other. Both variables were as well correlated to the commonly known risk factors with an expected direction and strength, however PMD (ρ = 0.56) was stronger correlated to BMI than DA (ρ = 0.11). The group of women within the highest quartil of PMD had an OR of 2.12 (95 % CI: 1.25-3.62). This could not be seen for the fourth quartile concerning DA. However the assessment of breast cancer risk could be improved by including DA in a prediction model in addition to common risk factors and PMD. Conclusions: The inclusion of the parameter DA into a prediction model for breast cancer in addition to established risk factors and PMD could improve the breast cancer risk assessment. As DA is measured together with PMD in the process of computer-assisted assessment of PMD it might be considered to include it as one additional breast cancer risk factor that is obtained from breast imaging. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: breast cancer; mammographic density; risk

pH dependence of the decomposition behavior of urogynecological fixation materials - Keckstein, P.; Lotz, Laura; Palmisano, Ralf; Hübner, Sabine; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Burghaus, Stefanie; Beckmann, Matthias; Hoeffmann,; Dittrich, Ralf; Hein, Alexander; Lermann, Johannes (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

PHIP - a novel candidate breast cancer susceptibility locus on 6q14.1 - Jiao, Xiang; Aravidis, Christos; Marikkannu, Rajeshwari; Rantala, Johanna; Picelli, Simone; Adamovic, Tatjana; Liu, Tao; Maguire, Paula; Kremeyer, Barbara; Luo, Liping; Von Holst, Susanna; Kontham, Vinaykumar; et al. (Oncotarget, 2017)
Most non-BRCA1/2 breast cancer families have no identified genetic cause. We used linkage and haplotype analyses in familial and sporadic breast cancer cases to identify a susceptibility locus on chromosome 6q. Two independent genome-wide linkage analysis studies suggested a 3 Mb locus on chromosome 6q and two unrelated Swedish families with a LOD >2 together seemed to share a haplotype in 6q14.1. We hypothesized that this region harbored a rare high-risk founder allele contributing to breast cancer in these two families. Sequencing of DNA and RNA from the two families did not detect any pathogenic mutations. Finally, 29 SNPs in the region were analyzed in 44,214 cases and 43,532 controls from BCAC, and the original haplotypes in the two families were suggested as low-risk alleles for European and Swedish women specifically. There was also some support for one additional independent moderate-risk allele in Swedish familial samples. The results were consistent with our previous findings in familial breast cancer and supported a breast cancer susceptibility locus at 6q14.1 around the PHIP gene.
EVALuna2:36117

Piwi-like 1 and piwi-like 2 expression in breast cancer - Erber, Ramona; Meyer, Julia; Taubert, Helge; Fasching, Peter; Wach, Sven; Häberle, Lothar; Gaß, Paul; Schulz-Wendtland, Rüdiger; Landgraf, Laura; Olbricht, Sabrina; Jung, Rudolf; Beckmann, Matthias; et al. (Cancers, 2020)
PIWI-like 1 and PIWI-like 2 play a role in stem cell self-renewal, and enhanced expression has been reported for several tumor entities. However, few studies have investigated PIWI-like 1 and PIWI-like 2 expressions in breast cancer subtypes regarding prognosis. Therefore, we examined protein expression in a large consecutive cohort of breast cancer patients and correlated it to breast cancer subtypes and survival outcome. PIWI-like 1 and PIWI-like 2 expressions were evaluated using immunohistochemistry in a cohort of 894 breast cancer patients, of whom 363 were eligible for further analysis. Percentage and intensity of stained tumor cells were analyzed and an immunoreactive score (IRS) was calculated. The interaction of PIWI-like 1 and PIWI-like 2 showed a prognostic effect on survival. For the combination of high PIWI-like 1 and low PIWI-like 2 expressions, adjusted hazard ratios (HRs) were significantly higher with regard to overall survival (OS) (HR 2.92; 95% confidence interval (CI) 1.24, 6.90), disease-free survival (DFS) (HR 3.27; 95% CI 1.48, 7.20), and distant disease-free survival (DDFS) (HR 7.64; 95% CI 2.35, 24.82). Both proteins were significantly associated with molecular-like and PAM50 subgroups. Combining high PIWI-like 1 and low PIWI-like 2 expressions predicted poorer prognosis and both markers were associated with aggressive molecular subtypes.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Breast cancer; HER2; Luminal A; Luminal B; Molecular breast cancer subtypes; PIWI-like 1; PIWI-like 2; PIWIL1; PIWIL2; TNBC

Plasticity of patient-matched normal mammary epithelial cells is dependent on autologous adipose-derived stem cells - Kengelbach-Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Schmid, Rafael; Marques, Jasmin Monteiro; Beier, Justus; Beckmann, Matthias; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Scientific Reports, 2019)
Due to the increasing clinical application of adipose-derived stem cells (ADSC), e.g. lipotransfer for breast reconstruction, this study aimed to gain novel insights regarding ADSC influence on breast tissue remodeling and determine patient-dependent factors affecting lipotransfer as well as begin to address its oncological risks. The ADSC secretome was analyzed from five normal breast reduction patients and contained elevated levels of growth factors, cytokines and proteins mediating invasion. ADSC/ADSC secretomes were tested for their influence on the function of primary mammary epithelial cells, and tumor epithelial cells using cell culture assays. ADSC/ADSC secretomes significantly stimulated proliferation, transmigration and 3D-invasion of primary normal and tumor epithelial cells. IL-6 significantly induced an EMT and invasion. The ADSC secretome significantly upregulated normal epithelial cell gene expression including MMPs and ECM receptors. Our study supports that ADSC and its secretome promote favorable conditions for normal breast tissue remodeling by changing the microenvironment. and may also be important regarding residual breast cancer cells following surgery.
CRIS-Team Scopus Importer:2019-08-06

Polygenic risk modeling for prediction of epithelial ovarian cancer risk - Dareng, Eileen O.; Tyrer, Jonathan P.; Barnes, Daniel R.; Jones, Michelle R.; Yang, Xin; Aben, Katja K. H.; Adank, Muriel A.; Agata, Simona; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Aravantinos, Gerasimos; et al. (European Journal of Human Genetics, 2022)
Polygenic risk scores (PRS) for epithelial ovarian cancer (EOC) have the potential to improve risk stratification. Joint estimation of Single Nucleotide Polymorphism (SNP) effects in models could improve predictive performance over standard approaches of PRS construction. Here, we implemented computationally efficient, penalized, logistic regression models (lasso, elastic net, stepwise) to individual level genotype data and a Bayesian framework with continuous shrinkage, "select and shrink for summary statistics" (S4), to summary level data for epithelial non-mucinous ovarian cancer risk prediction. We developed the models in a dataset consisting of 23,564 non-mucinous EOC cases and 40,138 controls participating in the Ovarian Cancer Association Consortium (OCAC) and validated the best models in three populations of different ancestries: prospective data from 198,101 women of European ancestries; 7,669 women of East Asian ancestries; 1,072 women of African ancestries, and in 18,915 BRCA1 and 12,337 BRCA2 pathogenic variant carriers of European ancestries. In the external validation data, the model with the strongest association for non-mucinous EOC risk derived from the OCAC model development data was the S4 model (27,240 SNPs) with odds ratios (OR) of 1.38 (95% CI: 1.28-1.48, AUC: 0.588) per unit standard deviation, in women of European ancestries; 1.14 (95% CI: 1.08-1.19, AUC: 0.538) in women of East Asian ancestries; 1.38 (95% CI: 1.21-1.58, AUC: 0.593) in women of African ancestries; hazard ratios of 1.36 (95% CI: 1.29-1.43, AUC: 0.592) in BRCA1 pathogenic variant carriers and 1.49 (95% CI: 1.35-1.64, AUC: 0.624) in BRCA2 pathogenic variant carriers. Incorporation of the S4 PRS in risk prediction models for ovarian cancer may have clinical utility in ovarian cancer prevention programs.
CRIS-Team WoS Importer:2022-01-28

Polygenic Risk Scores for Prediction of Breast Cancer and Breast Cancer Subtypes - Mavaddat, Nasim; Michailidou, Kyriaki; Dennis, Joe; Lush, Michael; Fachal, Laura; Lee, Andrew; Tyrer, Jonathan P.; Chen, Ting-Huei; Wang, Qin; Bolla, Manjeet K.; Yang, Xin; Adank, Muriel A.; et al. (American Journal of Human Genetics, 2019)
Stratification of women according to their risk of breast cancer based on polygenic risk scores (PRSs) could improve screening and prevention strategies. Our aim was to develop PRSs, optimized for prediction of estrogen receptor (ER)-specific disease, from the largest available genome-wide association dataset and to empirically validate the PRSs in prospective studies. The development dataset comprised 94,075 case subjects and 75,017 control subjects of European ancestry from 69 studies, divided into training and validation sets. Samples were genotyped using genome-wide arrays, and single-nucleotide polymorphisms (SNPs) were selected by stepwise regression or lasso penalized regression. The best performing PRSs were validated in an independent test set comprising 11,428 case subjects and 18,323 control subjects from 10 prospective studies and 190,040 women from UK Biobank (3,215 incident breast cancers). For the best PRSs (313 SNPs), the odds ratio for overall disease per 1 standard deviation in ten prospective studies was 1.61 (95%CI: 1.57-1.65) with area under receiver-operator curve (AUC) = 0.630 (95%CI: 0.628-0.651). The lifetime risk of overall breast cancer in the top centile of the PRSs was 32.6%. Compared with women in the middle quintile, those in the highest 1% of risk had 4.37- and 2.78-fold risks, and those in the lowest 1% of risk had 0.16- and 0.27-fold risks, of developing ER-positive and ER-negative disease, respectively. Goodness-of-fit tests indicated that this PRS was well calibrated and predicts disease risk accurately in the tails of the distribution. This PRS is a powerful and reliable predictor of breast cancer risk that may improve breast cancer prevention programs.
EVALuna2:35122

Polymorphisms in a Putative Enhancer at the 10q21.2 Breast Cancer Risk Locus Regulate NRBF2 Expression - Darabi, Hatef; Mccue, Karen; Beesley, Jonathan; Michailidou, Kyriaki; Nord, Silje; Kar, Siddhartha; Humphreys, Keith; Thompson, Deborah; Ghoussaini, Maya; Bolla, Manjeet K.; Dennis, Joe; Wang, Qin; et al. (American Journal of Human Genetics, 2015)
Genome-wide association studies have identified SNPs near ZNF365 at 10q21.2 that are associated with both breast cancer risk and mammographic density. To identify the most likely causal SNPs, we fine mapped the association signal by genotyping 428 SNPs across the region in 89,050 European and 12,893 Asian case and control subjects from the Breast Cancer Association Consortium. We identified four independent sets of correlated, highly trait-associated variants (iCHAVs), three of which were located within ZNF365. The most strongly risk-associated SNP, rs10995201 in iCHAV1, showed clear evidence of association with both estrogen receptor (ER)-positive (OR = 0.85 [0.82-0.88]) and ER-negative (OR = 0.87 [0.82-0.91]) disease, and was also the SNP most strongly associated with percent mammographic density. iCHAV2 (lead SNP, chr10: 64,258,684:D) and iCHAV3 (lead SNP, rs7922449) were also associated with ER-positive (OR = 0.93 [0.91-0.95] and OR = 1.06 [1.03-1.09]) and ER-negative (OR = 0.95 [0.91-0.98] and OR = 1.08 [1.04-1.13]) disease. There was weaker evidence for iCHAV4, located 5' of ADO, associated only with ER-positive breast cancer (OR = 0.93 [0.90-0.96]). We found 12, 17, 18, and 2 candidate causal SNPs for breast cancer in iCHAVs 1-4, respectively. Chromosome conformation capture analysis showed that iCHAV2 interacts with the ZNF365 and NRBF2 (more than 600 kb away) promoters in normal and cancerous breast epithelial cells. Luciferase assays did not identify SNPs that affect transactivation of ZNF365, but identified a protective haplotype in iCHAV2, associated with silencing of the NRBF2 promoter, implicating this gene in the etiology of breast cancer.
EVALuna2:9266

Polymorphisms in inflammation pathway genes and endometrial cancer risk - Delahanty, Ryan J.; Xiang, Yong-Bing; Spurdle, Amanda; Beeghly-Fadiel, Alicia; Long, Jirong; Thompson, Deborah; Tomlinson, Ian; Yu, Herbert; Lambrechts, Diether; Doerk, Thilo; Goodman, Marc T.; Zheng, Ying; et al. (Cancer Epidemiology Biomarkers & Prevention, 2013)
Background: Experimental and epidemiologic evidence have suggested that chronic inflammation may play a critical role in endometrial carcinogenesis. Methods: To investigate this hypothesis, a two-stage study was carried out to evaluate single-nucleotide polymorphisms (SNP) in inflammatory pathway genes in association with endometrial cancer risk. In stage I, 64 candidate pathway genes were identified and 4,542 directly genotyped or imputed SNPs were analyzed among 832 endometrial cancer cases and 2,049 controls, using data from the Shanghai Endometrial Cancer Genetics Study. Linkage disequilibrium of stage I SNPs significantly associated with endometrial cancer (P < 0.05) indicated that the majority of associations could be linked to one of 24 distinct loci. One SNP from each of the 24 loci was then selected for follow-up genotyping. Of these, 21 SNPs were successfully designed and genotyped in stage II, which consisted of 10 additional studies including 6,604 endometrial cancer cases and 8,511 controls. Results: Five of the 21 SNPs had significant allelic odds ratios (ORs) and 95% confidence intervals (CI) as follows: FABP1, 0.92 (0.85-0.99); CXCL3, 1.16 (1.05-1.29); IL6, 1.08 (1.00-1.17); MSR1, 0.90 (0.82-0.98); and MMP9, 0.91 (0.87-0.97). Two of these polymorphisms were independently significant in the replication sample (rs352038 in CXCL3 and rs3918249 in MMP9). The association for the MMP9 polymorphism remained significant after Bonferroni correction and showed a significant association with endometrial cancer in both Asian- and European-ancestry samples. Conclusions: These findings lend support to the hypothesis that genetic polymorphisms in genes involved in the inflammatory pathway may contribute to genetic susceptibility to endometrial cancer. Impact statement: This study adds to the growing evidence that inflammation plays an important role in endometrial carcinogenesis. © 2012 American Association for Cancer Research.
CRIS-Team Scopus Importer:2021-07-19

Polymorphisms in the RANK/RANKL genes and their effect on bone specific prognosis in breast cancer patients - Hein, Alexander; Bayer, Christian M.; Schrauder, Michael G.; Haeberle, Lothar; Heusinger, Katharina; Strick, Reiner; Ruebner, Matthias; Lux, Michael P.; Renner, Stefan; Schulz-Wendtland, Rüdiger; Ekici, Arif Bülent; Hartmann, Arndt; et al. (BioMed Research International, 2014)
The receptor activator of NF-?B (RANK) pathway is involved in bone health as well as breast cancer (BC) pathogenesis and progression. Whereas the therapeutic implication of this pathway is established for the treatment of osteoporosis and bone metastases, the application in adjuvant BC is currently investigated. As genetic variants in this pathway have been described to influence bone health, aim of this study was the prognostic relevance of genetic variants in RANK and RANKL. Single nucleotide polymorphisms in RANK(L) (rs1054016/rs1805034/rs35211496) were genotyped and analyzed with regard to bone metastasis-free survival (BMFS), disease-free survival, and overall survival for a retrospective cohort of 1251 patients. Cox proportional hazard models were built to examine the prognostic influence in addition to commonly established prognostic factors. The SNP rs1054016 seems to influence BMFS. Patients with two minor alleles had a more favorable prognosis than patients with at least one common allele (HR 0.37 (95% CI: 0.17, 0.84)), whereas other outcome parameters remained unaffected. rs1805034 and rs35211496 had no prognostic relevance. The effect of rs1054016(RANKL) adds to the evidence that the RANK pathway plays a role in BC pathogenesis and progression with respect to BMFS, emphasizing the connection between BC and bone health.
EVALuna2:6628

Pooled analysis of the prognostic relevance of progesterone receptor status in five German cohort studies - Salmen, Jessica; Neugebauer, Julia; Fasching, Peter; Häberle, Lothar; Huober, Jens; Woeckel, Achim; Rauh, Claudia; Schuetz, Florian; Weissenbacher, Tobias; Kost, Bernd; Stickeler, Elmar; Klar, Maximilian; et al. (Breast Cancer Research and Treatment, 2014)
The progesterone receptor (PR) has been increasingly well described as an important mediator of the pathogenesis and progression of breast cancer. The aim of this study was to assess the role of PR status as a prognostic factor in addition to other well-established prognostic factors. Data from five independent German breast cancer centers were pooled. A total of 7,965 breast cancer patients were included for whom information about their PR status was known, as well as other patient and tumor characteristics commonly used as prognostic factors. Cox proportional hazards models were built to compare the predictive value of PR status in addition to age at diagnosis, tumor size, nodal status, grading, and estrogen receptor (ER) status. PR status significantly increased the accuracy of prognostic predictions with regard to overall survival, distant disease-free survival, and local recurrence-free survival. There were differences with regard to its prognostic value relative to subgroups such as nodal status, ER status, and grading. The prognostic value of PR status was greatest in patients with a positive nodal status, negative ER status, and low grading. The PR-status adds prognostic value in addition to ER status and should not be omitted from clinical routine testing. The significantly greater prognostic value in node-positive and high-grade tumors suggests a greater role in the progression of advanced and aggressive tumors.
EVALuna2:6666

Precancerous Lesions of the Cervix, Vulva and Vagina According to the 2014 WHO Classification of Tumors of the Female Genital Tract - Reich, O.; Regauer, S.; Marth, C.; Schmidt, D.; Horn, L. -C.; Dannecker, C.; Menton, M.; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2015)
EVALuna2:17605

Preconceptual Counseling, Prenatal Care and peripartum Management of Female Patients with Ullrich-Turner Syndrome and a High-risk cardiovascular Profile - Pontones, Constanza; Lubrich, Hannah; Schwenke, E.; Cupisti, Susanne; Dittrich, Ralf; Kehl, Sven; Beckmann, Matthias; Fahlbusch, C.; Oppelt, Patricia (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Predicting attention deficit hyperactivity disorder using pregnancy and birth characteristics - Schwenke, Eva; Fasching, Peter; Faschingbauer, Florian; Pretscher, Jutta; Kehl, Sven; Peretz, Roberta; Keller, Andrea; Häberle, Lothar; Eichler, Anna; Irlbauer-Müller, Viktoria; Dammer, Ulf; Beckmann, Matthias; et al. (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: The aim of this study was to evaluate maternal, prenatal, perinatal, and postpartum parameters as risk factors for the later development of an attention deficit hyperactivity disorder (ADHD) in the child. METHODS: Women who had given birth at Erlangen University Hospital between 1996 and 1999 were sent a questionnaire in 2009. The results of the questionnaire were correlated with the prospectively collected data for the births in 1996-1999. RESULTS: A total of 573 mother and child pairs were analyzed. Forty-four of the mothers reported that their child had ADHD (7.7%). No significant associations were found for the following parameters: mother's age; mother's educational level; number of the pregnancy; maternal weight before and at the end of pregnancy; mother's height; alcohol consumption during pregnancy; mode of delivery; gestational week; birthweight; umbilical artery blood values; Apgar score at 5 and 10 min; or breastfeeding. The parameters of smoking in pregnancy and an Apgar score lower than 7 after 1 min were significantly associated with a risk for later development of ADHD. CONCLUSIONS: This analysis of maternal, prenatal, perinatal, and postnatal parameters found that smoking in pregnancy and a low Apgar score 1 min after birth are associated with a significantly greater risk for the development of ADHD. Beyond the question of the causal mechanism involved, this is a relevant finding, since smoking during pregnancy is a preventable risk factor.
EVALuna2:36367

Predicting mammographic density with linear ultrasound transducers - Behrens, Annika; Fasching, Peter; Schwenke, Eva; Gaß, Paul; Häberle, Lothar; Heindl, Felix; Heusinger, Katharina; Lotz, Laura; Lubrich, Hannah; Preuß, Caroline; Schneider, Michael; Schulz-Wendtland, Rüdiger; et al. (European Journal of Medical Research, 2023)
Background: High mammographic density (MD) is a risk factor for the development of breast cancer (BC). Changes in MD are influenced by multiple factors such as age, BMI, number of full-term pregnancies and lactating periods. To learn more about MD, it is important to establish non-radiation-based, alternative examination methods to mammography such as ultrasound assessments. Methods: We analyzed data from 168 patients who underwent standard-of-care mammography and performed additional ultrasound assessment of the breast using a high-frequency (12 MHz) linear probe of the VOLUSON® 730 Expert system (GE Medical Systems Kretztechnik GmbH & Co OHG, Austria). Gray level bins were calculated from ultrasound images to characterize mammographic density. Percentage mammographic density (PMD) was predicted by gray level bins using various regression models. Results: Gray level bins and PMD correlated to a certain extent. Spearman’s ρ ranged from − 0.18 to 0.32. The random forest model turned out to be the most accurate prediction model (cross-validated R 2, 0.255). Overall, ultrasound images from the VOLUSON® 730 Expert device in this study showed limited predictive power for PMD when correlated with the corresponding mammograms. Conclusions: In our present work, no reliable prediction of PMD using ultrasound imaging could be observed. As previous studies showed a reasonable correlation, predictive power seems to be highly dependent on the device used. Identifying feasible non-radiation imaging methods of the breast and their predictive power remains an important topic and warrants further evaluation. Trial registration 325-19 B (Ethics Committee of the medical faculty at Friedrich Alexander University of Erlangen-Nuremberg, Erlangen, Germany).
CRIS-Team Scopus Importer:2023-10-13
Keywords: Breast cancer risk; Percent mammographic density; Ultrasound

Predicting Triple-Negative Breast Cancer Subtype Using Multiple Single Nucleotide Polymorphisms for Breast Cancer Risk and Several Variable Selection Methods - Häberle, Lothar; Hein, Alexander; Rübner, Matthias; Schneider, Michael; Ekici, Arif Bülent; Gaß, Paul; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lo, Wing-Yee; Schroth, Werner; Brauch, Hiltrud; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Studies of triple-negative breast cancer have recently been extending the inclusion criteria and incorporating additional molecular markers into the selection criteria, opening up scope for targeted therapies. The screening phases required for studies of this type are often prolonged, since the process of determining the molecular subtype and carrying out additional biomarker assessment is time-consuming. Parameters such as germline genotypes capable of predicting the molecular subtype before it becomes available from pathology might be helpful for treatment planning and optimizing the timing and cost of screening phases. This appears to be feasible, as rapid and low-cost genotyping methods are becoming increasingly available. The aim of this study was to identify single nucleotide polymorphisms (SNPs) for breast cancer risk capable of predicting triple negativity, in addition to clinical predictors, in breast cancer patients.This cross-sectional observational study included 1271 women with invasive breast cancer who were treated at a university hospital. A total of 76 validated breast cancer risk SNPs were successfully genotyped. Univariate associations between each SNP and triple negativity were explored using logistic regression analyses. Several variable selection and regression techniques were applied to identify a set of SNPs that together improve the prediction of triple negativity in addition to the clinical predictors of age at diagnosis and body mass index (BMI). The most accurate prediction method was determined by cross-validation.The SNP rs10069690 (TERT, CLPTM1L) was the only significant SNP (corrected p = 0.02) after correction of p values for multiple testing in the univariate analyses. This SNP and three additional SNPs from the genes RAD51B, CCND1, and FGFR2 were selected for prediction of triple negativity. The addition of these SNPs to clinical predictors increased the cross-validated area under the curve (AUC) from 0.618 to 0.625. Age at diagnosis was the strongest predictor, stronger than any genetic characteristics.Prediction of triple-negative breast cancer can be improved if SNPs associated with breast cancer risk are added to a prediction rule based on age at diagnosis and BMI. This finding could be used for prescreening purposes in complex molecular therapy studies for triple-negative breast cancer.
EVALuna2:6850

Prediction of breast cancer risk based on profiling with common genetic variants - Mavaddat, Nasim; Pharoah, Paul D. P.; Michailidou, Kyriaki; Tyrer, Jonathan; Brook, Mark N.; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Dunning, Alison M.; Shah, Mitul; Luben, Robert; Brown, Judith; et al. (Journal of the National Cancer Institute, 2015)
Data for multiple common susceptibility alleles for breast cancer may be combined to identify women at different levels of breast cancer risk. Such stratification could guide preventive and screening strategies. However, empirical evidence for genetic risk stratification is lacking.We investigated the value of using 77 breast cancer-associated single nucleotide polymorphisms (SNPs) for risk stratification, in a study of 33 673 breast cancer cases and 33 381 control women of European origin. We tested all possible pair-wise multiplicative interactions and constructed a 77-SNP polygenic risk score (PRS) for breast cancer overall and by estrogen receptor (ER) status. Absolute risks of breast cancer by PRS were derived from relative risk estimates and UK incidence and mortality rates.There was no strong evidence for departure from a multiplicative model for any SNP pair. Women in the highest 1% of the PRS had a three-fold increased risk of developing breast cancer compared with women in the middle quintile (odds ratio [OR] = 3.36, 95% confidence interval [CI] = 2.95 to 3.83). The ORs for ER-positive and ER-negative disease were 3.73 (95% CI = 3.24 to 4.30) and 2.80 (95% CI = 2.26 to 3.46), respectively. Lifetime risk of breast cancer for women in the lowest and highest quintiles of the PRS were 5.2% and 16.6% for a woman without family history, and 8.6% and 24.4% for a woman with a first-degree family history of breast cancer.The PRS stratifies breast cancer risk in women both with and without a family history of breast cancer. The observed level of risk discrimination could inform targeted screening and prevention strategies. Further discrimination may be achievable through combining the PRS with lifestyle/environmental factors, although these were not considered in this repor
EVALuna2:9271

Prediction of pathological complete response and prognosis in patients with neoadjuvant treatment for triple-negative breast cancer - Gaß, Paul; Lux, Michael P.; Rauh, Claudia; Hein, Alexander; Bani, Mayada; Fießler, Cornelia; Hartmann, Arndt; Häberle, Lothar; Pretscher, Jutta; Erber, Ramona; Wachter, David; Schulz-Wendtland, Rüdiger; et al. (BMC Cancer, 2018)
BACKGROUND: It has been reported that pathological complete response is an important surrogate marker for disease-free survival and overall survival in patients with triple-negative breast cancer. This study investigates predictors of the response to neoadjuvant platinum-based or anthracycline-based treatment, and of the prognosis, in patients with triple-negative breast cancer. METHODS: A total of 121 patients with triple-negative breast cancer received neoadjuvant treatment with either platinum or anthracycline between 2008 and 2013. Pathological complete response was assessed relative to different treatments using logistic regression models with age, clinical tumor stage, grading, and Ki-67 as predictors and interaction terms, to obtain adjusted and subgroup-specific results. The impact of the pathological complete response rate on disease-free survival and overall survival was also analyzed. RESULTS: The pathological complete response rate was higher after platinum/taxane treatment compared with anthracycline/taxane (50.0% vs. 41.8%), but this was not significant in the adjusted analysis (OR 1.44; 95% CI, 0.68 to 3.09). A high histological grade (G3) was a predictor for higher pathological complete response in platinum-based therapy (OR 2.27; 95% CI, 1.00 to 5.30). The effect of neoadjuvant chemotherapy on pathological complete response was significantly different for G1-2 vs. G3 (Pinteraction = 0.013), and additional subgroup-specific differences were noted. Pathological complete response was a predictor for improved disease-free survival and overall survival in both treatment groups, with and without platinum chemotherapy. CONCLUSIONS: This retrospective study of patients with triple-negative breast cancer adds to the evidence that the treatment effect of platinum may be greatest particularly in G3 tumors. In addition, the effect of pathological complete response on the prognosis does not depend on the treatment used.
EVALuna2:34850

Preexisting musculoskeletal burden and its development under letrozole treatment in early breast cancer patients - Nabieva, Naiba; Häberle, Lothar; Brucker, Sara Y.; Janni, Wolfgang; Volz, Bernhard; Löhberg, Christian; Hartkopf, Andreas D.; Walter, Christina Barbara; Baake, Gerold; Fridman, Alexander; Malter, Wolfram; Wuerstlein, Rachel; et al. (International Journal of Cancer, 2019)
One of the most common adverse events (AEs) occurring during treatment with aromatase inhibitors (AIs) is musculoskeletal pain. The aim of our study was to analyze the influence of preexisting muscle/limb pain and joint pain on the development of AI-induced musculoskeletal AEs. Women eligible for upfront adjuvant endocrine therapy with letrozole were included in the PreFace study, a multicenter phase IV trial. During the first treatment year, they were asked to record musculoskeletal AEs monthly by answering questions regarding pain symptoms and rating the pain intensity on a numeric rating scale from 0 (no pain) to 10 (very strong pain). Pain values were compared using nonparametric statistical tests. Overall, 1,416 patients were evaluable. The average pain value over all time points in women with preexisting muscle/limb pain was 4.3 (median 4.3); in those without preexisting pain, it was 2.0 (median 1.7). In patients without preexisting muscle/limb pain, pain levels increased relatively strongly within the first 6 months (mean increase +0.9, p < 0.00001) in comparison with those with preexisting pain (mean increase +0.3, p < 0.001), resulting in a statistically significant difference (p < 0.00001) between the two groups. The development of joint pain was similar in the two groups. Women without preexisting muscle/limb pain or joint pain have the greatest increase in pain after the start of adjuvant AI therapy. Women with preexisting pain have significantly higher pain values. The main increase in pain values takes place during the first 6 months of treatment.
Keywords: aromatase inhibitor; arthralgia/joint pain; breast cancer; endocrine treatment/therapy; letrozole; myalgia/muscle and limb pain

Pregnancies and live births after 20 transplantations of cryopreserved ovarian tissue in a single center - Dittrich, Ralf; Hackl, Janina; Lotz, Laura; Hoffmann, Inge; Beckmann, Matthias (Fertility and Sterility, 2015)
To report the results of 20 orthotopic retransplantations of cryopreserved ovarian tissue after cancer treatment.Retrospective analysis.Tertiary gynecology department.Twenty patients with malignant disease: 11 with hematological malignancies (55%), four with breast cancer (20%), three with anal cancer (15%), and two with ovarian cancer (10%); the mean age before oncological treatment was 30.5 years.Ovarian tissue was removed from patients in various centers in Germany in 2005-2009. All patients received chemotherapy and/or radiotherapy. Afterward, 17 patients had complete premature ovarian insufficiency, while three still showed some ovarian activity. Overnight transportation of tissue before freezing was necessary in eight cases. Cryopreservation followed slow freezing protocols in all cases. Retransplantation was performed at Erlangen University Hospital 3.75 years after extraction, on average. Thawed tissue was transplanted into a peritoneal pouch in the broad ligament region, below the tube, in 16 cases. Fragments were sutured both onto the remaining ovary and into a peritoneal pouch in four cases.Restoration of ovarian activity, pregnancy, birth.Ovarian activity resumed in all patients except one. Seven patients conceived, with one miscarriage and four ongoing pregnancies. Four patients delivered healthy babies. One pregnancy and live birth after oocyte donation need to be considered separately.These data clearly demonstrate that preserving fertility by cryopreserving ovarian tissue is a successful and safe clinical option that can be considered for selected cancer patients.
EVALuna2:17542

Pregnancy and Obstetrical Outcomes in Women Over 40 Years of Age - Dietl, A.; Cupisti, S.; Beckmann, Matthias; Schwab, M.; Zollner, U. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Delayed childbearing is increasing, and advanced maternal age has been associated with an increased risk of obstetrical complications. The purpose of this study was to evaluate pregnancy outcomes in women with advanced maternal age (>= 40 years). Methods: Maternal and obstetrical data were collected from the Department of Obstetrics and Gynecology of the University of Wuerzburg for the period from 2006 to 2011. In this retrospective analysis we compared the outcomes for women aged >= 40 years (n = 405) with those of three younger subgroups (I: < 30 y; II: 30-34 y; III: 35-39 y). Results: Pregnant women older than 40 years had more chronic diseases such as hypertension, needed medical treatment more frequently and had a higher thrombosis risk. Pregnancy-induced diseases such as gestational diabetes, preeclampsia and pregnancy-associated hypertension occurred more often in women >= 40 years of age. Compared to mothers who were younger than 30 years, primiparous women >= 40 years had a more than four times higher overall cesarean section rate and four times higher elective cesarean section rate. Furthermore, they required longer hospital stays, both after cesarean section and after vaginal delivery. The preterm birth rate (<= 32 weeks of gestation) was similar across the different age groups. Conclusions: The outcomes of pregnancy and childbirth and for newborns born to women >= 40 years did not vary significantly from those of younger women if the following conditions were met: a) pre-existing chronic diseases were treated medically and dietetically; b) pregnancy-induced morbidity was monitored regularly and controlled medically; c) women attended regular prenatal check-ups; d) a healthy lifestyle was adhered to during pregnancy, and e) delivery occurred in a perinatal center.
EVALuna2:17603

Preliminary observations on whole-ovary xenotransplantation as an experimental model for fertility preservation - Nichols-Burns, Stephanie M.; Lotz, Laura; Schneider, Heike; Adamek, Edyta; Daniel, Christoph; Stief, Andrea; Grigo, Christina; Klump, Dorothee; Hoffmann, Inge; Beckmann, Matthias; Dittrich, Ralf (Reproductive Biomedicine Online, 2014)
Ovarian tissue preservation and retransplantation is a promising strategy to restore fertility in cancer survivors. Ischaemia accompanying ovarian tissue grafting, however, can lead to significant follicle loss. Transplantation of the whole ovary by vascular anastomosis has been considered as an alternative to prevent widespread ischaemic damage. In this study, the feasibility and function of transplanting whole ovary with intact vasculature were evaluated, with the goal of developing a xenograft model for studies using donated human ovaries. Whole-swine ovaries with vascular pedicles were perfused and transplanted as intact ovaries by anastomosis into irradiated ovariectomized nude rats (n = 10). The observation period was between 1 and 4 weeks. Fresh swine ovaries served as controls (n = 10). Ovarian stroma and follicle populations were assessed through histological examination in both transplanted and control ovaries. Most of the transplanted whole ovaries (n = 6) maintained stromal quality and all preantral follicle classes were represented, although follicle numbers decreased compared with fresh control. Four transplanted ovaries were fibrotic after 1-4 weeks within the nude rat. Our results demonstrate transplantation of whole-pig ovary into nude rats is possible and support development of this xenograft model system for human studies.
EVALuna2:15573

Prenatal alcohol exposure and the facial phenotype in adolescents: A study based on meconium ethyl glucuronide - Maschke, Janina; Roetner, Jakob; Goecke, Tamme; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; Eichler, Anna (Brain Sciences, 2021)
Here, we explore the effects of prenatal alcohol exposure (PAE) in adolescence. We investigated associations between meconium ethyl glucoronide (EtG) and facial malformation. For 29 children (66/63 male/female; M = 13.3, SD = 0.32, 12–14 years), PAE was implemented by newborn meconium EtG and maternal self-reports during the third trimester. Cognitive development was operationalized by standardized scores (WISC V). The EtG cut-off values were set at ≥10 ng/g (n = 32, 24.8% EtG10+) and ≥112 ng/g (n = 20, 15.5% EtG112+). The craniofacial shape was measured using FAS Facial Photographic Analysis Software. EtG10+− and EtG112+-affected children exhibited a shorter palpebral fissure length (p = 0.031/p = 0.055). Lip circularity was smaller in EtG112+-affected children (p = 0.026). Maternal self-reports were not associated (p > 0.164). Lip circularity correlated with fluid reasoning (EtG10+ p = 0.031; EtG112+ p = 0.298) and working memory (EtG10+ p = 0.084; EtG112+ p = 0.144). The present study demonstrates visible effects of the facial phenotype in exposed adolescents. Facial malformation was associated with a child’s cognitive performance in the alcohol-exposed group. The EtG biomarker was a better predictor than maternal self-reports.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Alcohol; Biomarker; Craniofacial shape; Ethyl glucuronide (EtG); Facial malformations; Inner canthal distance; Intrauterine alcohol exposure; Lip circularity; Meconium; Palpebral fissure length

Prenatal and adult androgen activities in alcohol dependence - Lenz, Bernd; Mühle, Christiane; Braun, B.; Weinland, C.; Bouna-Pyrrou, Polyxeni; Behrens, Juliane; Kubis, S.; Mikolaiczik, Katrin; Muschler, M. -R.; Saigali, Sarah; Sibach, M.; Tanovska, P.; et al. (Acta Psychiatrica Scandinavica, 2017)
OBJECTIVE: Alcohol dependence is more prevalent in men than in women. The evidence for how prenatal and adult androgens influence alcohol dependence is limited. We investigated the effects of prenatal and adult androgen activity on alcohol dependence. Moreover, we studied how the behaviours of pregnant women affect their children's prenatal androgen load. METHOD: We quantified prenatal androgen markers (e.g., second-to-fourth finger length ratio [2D : 4D]) and blood androgens in 200 early-abstinent alcohol-dependent in-patients and 240 controls (2013-2015, including a 12-month follow-up). We also surveyed 134 women during pregnancy (2005-2007) and measured the 2D : 4D of their children (2013-2016). RESULTS: The prenatal androgen loads were higher in the male alcohol-dependent patients compared to the controls (lower 2D : 4D, P = 0.004) and correlated positively with the patients' liver transaminase activities (P < 0.001) and alcohol withdrawal severity (P = 0.019). Higher prenatal androgen loads and increasing androgen levels during withdrawal predicted earlier and more frequent 12-month hospital readmission in alcohol-dependent patients (P < 0.005). Moreover, stress levels (P = 0.002), alcohol (P = 0.010) and tobacco consumption (P = 0.017), and lifetime stressors (P = 0.019) of women during pregnancy related positively to their children's prenatal androgen loads (lower 2D : 4D). CONCLUSION: Androgen activities in alcohol-dependent patients and behaviours of pregnant women represent novel preventive and therapeutic targets of alcohol dependence.
EVALuna2:33408

Prenatal Correction of X-Linked Hypohidrotic Ectodermal Dysplasia - Schneider, Holm; Faschingbauer, Florian; Schuepbach-Mallepell, Sonia; Koerber, Iris; Wohlfart, Sigrun; Dick, Angela; Wahlbuhl, Mandy; Kowalczyk-Quintas, Christine; Vigolo, Michele; Kirby, Neil; Tannert, Corinna; Rompel, Oliver; et al. (New England Journal of Medicine, 2018)
Genetic deficiency of ectodysplasin A (EDA) causes X-linked hypohidrotic ectodermal dysplasia (XLHED), in which the development of sweat glands is irreversibly impaired, an condition that can lead to life-threatening hyperthermia. We observed normal development of mouse fetuses with Eda mutations after they had been exposed in utero to a recombinant protein that includes the receptor-binding domain of EDA. We administered this protein intraamniotically to two affected human twins at gestational weeks 26 and 31 and to a single affected human fetus at gestational week 26; the infants, born in week 33 (twins) and week 39 (singleton), were able to sweat normally, and XLHED-related illness had not developed by 14 to 22 months of age. (Funded by Edimer Pharmaceuticals and others.).
EVALuna2:35486

Presence of circulating tumor cells in high-risk early breast cancer during follow-up and prognosis - Trapp, Elisabeth; Janni, Wolfgang; Schindlbeck, Christian; Jückstock, Julia; Andergassen, Ulrich; De Gregorio, Amelie; Alunni-Fabbroni, Marianna; Tzschaschel, Marie; Polasik, Arkadius; Koch, Julian G.; Friedl, Thomas W.P.; Fasching, Peter; et al. (Journal of the National Cancer Institute, 2019)
Background: The prognostic relevance of circulating tumor cells (CTCs) at the time of primary diagnosis has been well established. However, little information is available regarding their prognostic relevance to follow-up care. Methods: The multicenter, open-label, phase III SUCCESS A trial compared two adjuvant chemotherapy regimens followed by 2 vs 5 years of zoledronate for early-stage, high-risk breast cancer patients. The presence of CTCs was assessed before and 2 years after chemotherapy using the FDA-approved CellSearch System. Overall survival (OS) and disease-free survival (DFS) were analyzed using univariate log-rank tests and multivariable Cox regressions. OS and DFS were measured starting from an assessment of CTCs 2 years after the completion of chemotherapy. All statistical tests were two-sided. Results: The sample included 1087 patients who participated in the translational research program of the SUCCESS A trial and for whom sufficient translational data were available regarding CTC status at baseline and at the 2-year follow-up visit. Two years after chemotherapy, 198 (18.2%) patients were CTC-positive. The median follow-up after this timepoint was 37 months. Cox regressions that included CTC status at baseline revealed that CTC status 2 years after chemotherapy had statistically significant and independent prognostic relevance for OS (hazard ratio [HR] ¼ 3.91, 95% confidence interval [CI] ¼ 2.04 to 7.52, P < .001) and DFS (HR ¼ 2.31, 95% CI ¼ 1.50 to 3.55, P < .001). Conclusion: The presence of CTCs 2 years after chemotherapy was associated with decreased OS and DFS. Based on these results, active individualized surveillance strategies for breast cancer survivors based on biomarkers should be reconsidered.
CRIS-Team Scopus Importer:2019-09-24

Prevalence of circulating tumor cells in early breast cancer patients 2 and 5 years after adjuvant treatment - Bauer, Emanuel C. A.; Schochter, Fabienne; Widschwendter, Peter; Degregorio, Amelie; Andergassen, Ulrich; Friedl, Thomas W. P.; Fasching, Peter; Fehm, Tanja; Schneeweiss, Andreas; Beckmann, Matthias; Pantel, Klaus; Janni, Wolfgang; et al. (Breast Cancer Research and Treatment, 2018)
Several studies have provided evidence on the prognostic relevance of circulating tumor cells (CTCs) detected before and after chemotherapy regarding overall survival (OS) and progression-free survival (PFS) in early breast cancer (EBC). We provide data on the prevalence of CTCs 2 and 5 years after primary diagnosis in a cohort of patients with EBC.The SUCCESS study is a multicenter, prospective, randomized trial comparing PFS in primary breast cancer patients undergoing one of two adjuvant chemotherapy regimens followed by 2 versus 5 years of treatment with zoledronate. CTCs from patients without signs of breast cancer recurrence were analyzed in peripheral blood using the FDA cleared CellSearch® System (Veridex, USA) 2 and 5 years after primary diagnosis.CTCs were detected at 2 and 5 years after primary diagnosis in 96 (16.7%) and 47 (8.2%) of the 574 patients, respectively. There were no associations between CTC status and patient and tumor characteristics or treatment regimens. In 442 (77.0%) patients, no CTCs were detected at either of the two time points, and in 11 patients (1.9%), CTCs were found at both 2 and 5 years after primary diagnosis. In 85 (14.8%) patients, CTCs were present 2 years after primary diagnosis but not after 5 years, while 36 (6.3%) patients had CTCs in their blood only at the 5-year follow-up.In patients with EBC, CTCs can be detected even 5 years after primary diagnosis without clinical signs of disease recurrence.
EVALuna2:56145

Prevalence of SARS-CoV-2 in Pregnant Women Assessed by RT-PCR in Franconia, Germany: First Results of the SCENARIO Study (SARS-CoV-2 prEvalence in pregNAncy and at biRth In FrancOnia) - Hein, Alexander; Kehl, Sven; Häberle, Lothar; Tiemann, Carsten; Peuker, Rebecca; Mereutanu, Denise; Stumpfe, Florian; Faschingbauer, Florian; Meyer-Schlinkmann, Kirstin; Koch, Martin C.; Kainer, Franz; Dammer, Ulf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Detection of SARS-CoV-2-infected pregnant women admitted to maternity units during a pandemic is crucial. In addition to the fact that pregnancy is a risk factor for severe COVID-19 and that medical surveillance has to be adjusted in infected women and their offspring, knowledge about infection status can provide the opportunity to protect other patients and healthcare workers against virus transmission. The aim of this prospective observational study was to determine the prevalence of SARS-CoV-2 infection among pregnant women in the hospital setting. Material and Methods All eligible pregnant women admitted to the nine participating hospitals in Franconia, Germany, from 2 June 2020 to 24 January 2021 were included. COVID-19-related symptoms, secondary diseases and pregnancy abnormalities were documented. SARS-CoV-2 RNA was detected by RT-PCR from nasopharyngeal swabs. The prevalence of acute SARS-CoV-2 infection was estimated by correcting the positive rate using the Rogan-Gladen method. The risk of infection for healthcare workers during delivery was estimated using a risk calculator. Results Of 2414 recruited pregnant women, six were newly diagnosed RT-PCR positive for SARS-CoV-2, which yielded a prevalence of SARS-CoV-2 infection of 0.26% (95% CI, 0.10-0.57%). Combining active room ventilation and wearing FFP2 masks showed an estimated reduction of risk of infection for healthcare workers in the delivery room to < 1%. Conclusions The prevalence of newly diagnosed SARS-CoV-2 infection during pregnancy in this study is low. Nevertheless, a systematic screening in maternity units during pandemic situations is important to adjust hygienic and medical management. An adequate hygienic setting can minimise the calculated infection risk for medical healthcare workers during patients' labour.
CRIS-Team Scopus Importer:2022-02-25
Keywords: COVID-19; infection; pregnancy; prevalence; SARS-CoV-2

Prevention of Cervical Cancer - Hillemanns, Peter; Friese, Klaus; Dannecker, Christian; Klug, Stefanie; Seifert, Ulrike; Iftner, Thomas; Haedicke, Juliane; Loening, Thomas; Horn, Lars; Schmidt, Dietmar; Ikenberg, Hans; Steiner, Manfred; et al. (Geburtshilfe und Frauenheilkunde, 2019)
Aims Annual opportunistic screening for cervical carcinoma has been done in Germany since 1971. The creation of this S3 guideline meets an important need, outlined in the National Cancer Plan, with regard to screening for cervical cancer, as this guideline aims to provide important information and support for planned organized screening for cervical cancer in Germany. Methods With the financial support of German Cancer Aid, 21 professional societies developed evidence-based statements and recommendations (classified using the GRADE system) for the screening, management and treatment of precancerous conditions of the cervix. Two independent scientific institutes compiled systematic reviews for this guideline. Recommendations The second part of this short summary deals with the triage, treatment and follow-up care of cervical dysplasia. With regard to those women who do not participate in screening, the guideline authors recommend sending out repeat invitation letters or an HPV self-collection kit. Colposcopy should be carried out for further investigation if cytology findings are Pap II-p and HPV test results are positive or if the results of an HPV 16 or HPV 18 screening test are positive. A single abnormal Pap smear should be triaged and investigated using HPV testing or p16/Ki67 dual staining.
CRIS-Team Scopus Importer:2019-05-02
Keywords: cervical cancer; cervical intraepithelial neoplasia (CIN); cervical precancerous condition; HPV

Prevention of Cervical Cancer: Guideline of the DGGG and the DKG (S3 Level, AWMF Register Number 015/027OL, December 2017) - Part 1 with Introduction, Screening and the Pathology of Cervical Dysplasia - Hillemanns, Peter; Friese, Klaus; Dannecker, Christian; Klug, Stefanie; Seifert, Ulrike; Iftner, Thomas; Haedicke, Juliane; Loening, Thomas; Horn, Lars; Schmidt, Dietmar; Ikenberg, Hans; Steiner, Manfred; et al. (Geburtshilfe und Frauenheilkunde, 2019)
Annual opportunistic screening for cervical carcinoma has been carried out in Germany since 1971. The creation of this S3 guideline meets an important need, outlined in the National Cancer Plan, with regard to screening for cervical cancer, as the guideline aims to provide important information and support for planned organized screening for cervical cancer in Germany. With the financial support of German Cancer Aid, 21 professional societies developed evidence-based statements and recommendations (classified using the GRADE system) for the screening, management and treatment of precancerous conditions of the cervix. Two independent scientific institutes compiled systematic reviews for this guideline. The first part of this short summary presents the pathological basis and considers various questions related to screening for cervical cancer. As also reported in earlier reviews, the meta-analysis by Kleijnen Systematic Reviews showed that HPV-based screening offers better protection against invasive cervical cancer compared to cytology-based screening. The authors of this guideline therefore recommend - in accordance with the guideline of the Joint National Committee of Germany (Gemeinsamer Bundesauschuss, G-BA) - that women aged 35 and above should be examined at regular intervals (at least every 3 years) and undergo HPV-based screening. Co-testing can also be carried out. Women between the ages of 20 and 35 should have cytological screening every 2 years.
EVALuna2:157339

Primäre Prävention - Mamma- und Genitalkarzinome - Preu, Caroline; Heindl, Felix; Hein, Alexander; Koch, Martin; Ga, Paul; Beckmann, Matthias; Lux, Michael P.; Emons, Julius (TumorDiagnostik & Therapie, 2019)
Zusammenfassung In den letzten Jahren haben sich Diagnostik und Therapie im Bereich der gynäkologischen Onkologie und Senologie stetig weiterentwickelt. Dennoch ist das Versterben an einer Krebserkrankung in den hoch entwickelten Ländern eine der häufigsten Todesursachen der Frau 1. Manahmen zur Primärprävention sind daher von hoher Bedeutung, um die Morbidität und Mortalität von Krebserkrankungen zu senken.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Endometriumkarzinom; Mammakarzinom; Ovarialkarzinom; primäre Prävention; Zervixkarzinom

Primary Therapy of Patients with Early Breast Cancer: Evidence, Controversies, Consensus: Opinions of German Specialists to the 14th St. Gallen International Breast Cancer Conference 2015 (Vienna 2015) - Untch, M.; Harbeck, N.; Huober, J.; Von Minckwitz, G.; Gerber, B.; Kreipe, H. -H.; Liedtke, C.; Marschner, N.; Moebus, V.; Scheithauer, H.; Schneeweiss, A.; Thomssen, C.; et al. (Geburtshilfe und Frauenheilkunde, 2015)
For the first time, this year's St. Gallen International Consensus Conference on the treatment of patients with primary breast cancer, which takes place every two years, was held not in St. Gallen (Switzerland) but - for logistical reasons - in Vienna (Austria) under its usual name. The 2015 St. Gallen International Consensus Conference was the 14th of its kind. As the international panel of the St. Gallen conference consists of experts from different countries, the consensus mirrors an international cross-section of opinions. From a German perspective, it was considered useful to translate the results of the votes of the St. Gallen conference into practical suggestions, particularly in light of the recently updated treatment guideline of the Gynecologic Oncology Group (AGO-Mamma 2015) in Germany. A German group consisting of 14 breast cancer experts, three of whom are members of the international St. Gallen panel, has therefore provided comments on the results of this year's votes at the 2015 St. Gallen Consensus Conference and their impact on clinical care in Germany. The 14th St. Gallen conference once again focused on surgery of the breast and the axilla, radio-oncologic and systemic treatment options for primary breast cancer depending on tumor biology, and the clinical use of multigene assays. The conference also considered targeted therapies for older and for younger patients, including the diagnosis/treatment of breast cancer during and after pregnancy and the preservation of fertility.
EVALuna2:17567

Prognosis of Patients with Early Breast Cancer Receiving 5 Years vs 2 Years of Adjuvant Bisphosphonate Treatment: A Phase 3 Randomized Clinical Trial - Friedl, Thomas W. P.; Fehm, Tanja; Mueller, Volkmar; Lichtenegger, Werner; Blohmer, Jens; Lorenz, Ralf; Forstbauer, Helmut; Fink, Visnja; Bekes, Inga; Huober, Jens; Jueckstock, Julia; Schneeweiss, Andreas; et al. (JAMA Oncology, 2021)
Importance: Bisphosphonate treatment in patients with early breast cancer has become part of care, but the optimal treatment duration is still unclear. Objective: To compare 2 vs 5 years of zoledronate treatment following adjuvant chemotherapy in patients with early breast cancer. Design, Setting, and Participants: The SUCCESS A phase 3 multicenter randomized open-label clinical trial with a 2 × 2 factorial design enrolled 3754 patients from September 21, 2005, to March 12, 2007 (last patient out, May 7, 2014). Final data analysis was conducted from September 2019 to October 2020. In 250 German study centers, patients were eligible for participation in the SUCCESS A trial if they had either node-positive or high-risk node-negative (defined as at least 1 of the following: tumor size ≥ pT2, histologic grade 3, negative hormone receptor status, or age ≤35 years) primary invasive breast cancer. Interventions: Patients were first randomized to adjuvant chemotherapy with 3 cycles of fluorouracil, epirubicin, and cyclophosphamide followed by 3 cycles of docetaxel with or without gemcitabine (not presented in this report). After chemotherapy, patients underwent a second randomization of 5 years of zoledronate treatment (4 mg intravenously every 3 months for 2 years, followed by 4 mg intravenously every 6 months for 3 years) vs 2 years of zoledronate treatment (4 mg intravenously every 3 months for 2 years). Main Outcomes and Measures: The primary end point of the study was disease-free survival; secondary end points were overall survival, distant disease-free survival, and the incidence of skeletal-related adverse events. Survival times were measured from 2 years after the start of zoledronate treatment (landmark analysis). Results: Overall, data on 2987 patients were available for analysis; median age was 53 (range, 21-86) years. Disease-free survival, overall survival, and distant disease-free survival did not differ significantly between the 2 treatment arms (5 vs 2 years) as shown by adjusted multivariable Cox proportional hazards regression models (disease-free survival: hazard ratio [HR], 0.97; 95% CI, 0.75-1.25; P =.81; overall survival: HR, 0.98; 95% CI, 0.67-1.42; P =.90; distant disease-free survival: HR, 0.87; 95% CI, 0.65-1.18; P =.38). Adverse events were observed more often in the 5-year (46.2%) vs 2-year (27.2%) zoledronate treatment arm, which was particularly true for the skeletal-related events bone pain (5 years, 8.3% vs 2 years, 3.7%) and arthralgia (5 years, 5.1% vs 2 years, 3.1%). Conclusions and Relevance: The results of this phase 3 randomized clinical trial indicate that extending the zoledronate treatment beyond 2 years does not improve the prognosis of high-risk patients with early breast cancer receiving chemotherapy, suggesting that the currently recommended bisphosphonate treatment duration of 3 to 5 years could be reduced. Trial Registration: ClinicalTrials.gov Identifier: NCT02181101.
CRIS-Team Scopus Importer:2021-07-09

Prognostic effect of Ki-67 in common clinical subgroups of patients with HER2-negative, hormone receptor-positive early breast cancer - Fasching, Peter; Gaß, Paul; Häberle, Lothar; Volz, Bernhard; Hein, Alexander; Hack, Carolin; Lux, Michael P.; Jud, Sebastian; Hartmann, Arndt; Beckmann, Matthias; Slamon, Dennis J.; Erber, Ramona (Breast Cancer Research and Treatment, 2019)
Purpose: Several clinical trials have investigated the prognostic and predictive usefulness of molecular markers. With limited predictive value, molecular markers have mainly been used to identify prognostic subgroups in which the indication for chemotherapy is doubtful and the prognosis is favorable enough for chemotherapy to be avoided. However, limited information is available about which groups of patients may benefit from additional therapy. This study aimed to describe the prognostic effects of Ki-67 in several common subgroups of patients with early breast cancer. Methods: This retrospective study analyzed a single-center cohort of 3140 patients with HER2−, hormone receptor-positive breast cancer. Five-year disease-free survival (DFS) rates were calculated for low (< 10%), intermediate (10–19%), and high (≥ 20%) Ki-67 expression levels, as assessed by immunohistochemistry, and for subgroups relative to age, body mass index, disease stage, tumor grade, and (neo-)adjuvant chemotherapy. It was also investigated whether Ki-67 had different effects on DFS in these subgroups. Results: The 5-year DFS rates for patients with low, intermediate, and high levels of Ki-67 expression were 0.90, 0.89, and 0.77, respectively. Ki-67 was able to further differentiate patients with an intermediate prognosis into different prognostic groups relative to common clinical parameters. Patients with stage II breast cancer had 5-year DFS rates of 0.84, 0.88, and 0.79 for low, intermediate, and high levels of Ki-67 expression. Ki-67 had different prognostic effects in subgroups defined by age and tumor grade. Conclusions: Ki-67 may help identify patients in intermediate prognostic groups with an unfavorable prognosis who may benefit from further therapy.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Breast cancer; Ki-67; Molecular marker; Prognosis; Proliferation

Prognostic effect of low-level HER2 expression in patients with clinically negative HER2 status - Hein, Alexander; Hartkopf, Andreas D.; Emons, Julius; Lux, Michael P.; Volz, Bernhard; Taran, Florin Andrei; Overkamp, Friedrich; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; et al. (European Journal of Cancer, 2021)
Purpose: Assessment of HER2 overexpression using immunohistochemistry (IHC) and/or in situ hybridisation (ISH) for the detection of HER2 amplifications is standard to identify patients for established HER2-directed treatments. Patients with lower HER2 expression levels have recently also become candidates for novel therapies targeting HER2. This study aimed to assess tumour and patient characteristics and prognosis in patients with advanced breast cancer (aBC), relative to low HER2 expression levels. Methods: PRAEGNANT is a prospective aBC registry (NCT02338167), focusing on molecular biomarkers. Patients in all therapy lines receiving any kind of treatment are eligible. This analysis includes patients with conventionally HER2-negative aBC. Clinical outcome was compared in the groups with no (IHC score 0) or with low HER2 expression (IHC 1+, or IHC 2+/ISH negative). Results: Low HER2 expression levels in triple-negative aBC patients did not influence progression-free survival. Overall survival appeared poorer in patients with IHC 2+ compared with patients with no HER2 expression in the unadjusted analysis (hazard ratio 2.24, 95% confidence interval 0.1.12–4.47). However, this effect was not maintained in the adjusted analysis. In HER2-negative, hormone receptor–positive patients, low HER2 expression appeared to have no effect on prognosis, neither progression-free survival nor overall survival. Conclusions: We could not demonstrate that HER2 expression at a low level and assessed in clinical routine can differentiate patients into prognostic groups. However, the prevalence of patients with a low expression makes this population interesting for clinical trials with potentially active treatments using HER2 as a target.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Advanced breast cancer; Antihormone therapy; Chemotherapy; HER2; HER2/neu; Lapatinib; Metastatic; Pertuzumab; TDM-1; Trastuzumab

Prognostic Impact of Weight Change During Adjuvant Chemotherapy in Patients With High-Risk Early Breast Cancer: Results From the ADEBAR Study - Mutschler, Nikola S.; Scholz, Christoph; Friedl, Thomas W. P.; Zwingers, Thomas; Fasching, Peter; Beckmann, Matthias; Fehm, Tanja; Mohrmann, Svjetlana; Salmen, Jessica; Ziegler, Carola; Jaeger, Bernadette; Widschwendter, Peter; et al. (Clinical Breast Cancer, 2018)
In addition to established prognostic factors, individual lifestyle-associated factors, such as obesity, physical activity, and diet, seem to modulate the course of breast cancer. The aim of this analysis was to evaluate the influence of weight changes during adjuvant chemotherapy on outcome in a large multicenter prospectively randomized trial.The ADEBAR trial compares a sequential chemotherapy consisting of epirubicin/cyclophosphamide followed by docetaxel to an epirubicin/5-fluorouracil/cyclophosphamide regimen in patients with lymph node-positive early breast cancer. Body weight was measured before each cycle of chemotherapy. According to the relative weight change (>= 5%) between the first and the last cycle, patients were categorized into the weight gain, weight loss, or stable weight group. Overall survival (OS) and disease-free survival were assessed by univariate Kaplan-Meier and multivariate Cox regression analyses.Concise data from 1080 of 1493 participants who completed all cycles of chemotherapy were available for analysis. Of 307 patients (24.8%) whose weight changed by >= 5%, 120 patients (11.1%) lost and 187 (17.3%) gained weight. Multivariate analysis showed a significant independent effect of weight change on OS (P = .039), but not on disease-free survival (P = .111). Both weight change groups had a worse OS compared to patients with stable weight (weight gain: hazard ratio, 1.55; 95% confidence interval, 1.01-2.40; P = .047; weight loss: hazard ratio, 1.55; 95% CI, 0.97-2.47; P = .067).Weight change of > 5% during adjuvant chemotherapy in patients with high-risk early breast cancer is associated with poor OS.
EVALuna2:56149

Prognostic relevance of Ki-67 in the primary tumor for survival after a diagnosis of distant metastasis - Loehberg, Christian R.; Almstedt, Katrin; Jud, Sebastian; Haeberle, Lothar; Fasching, Peter; Hack, Carolin; Lux, Michael P.; Thiel, Falk; Schrauder, Michael G.; Brunner, Michaela; Bayer, Christian M.; Hein, Alexander; et al. (Breast Cancer Research and Treatment, 2013)
Prediction of the prognosis for metastatic breast cancer patients depends on molecular subtypes similar to those found in patients with primary breast cancer. Several studies have shown that estrogen receptor (ER) and progesterone receptor (PR) status determine the course of the disease and the prognosis. As Ki-67 helps to differentiate molecular subtypes in patients with primary breast cancer, the aim of this study was to assess the prognostic relevance of Ki-67 in the primary tumor in relation to its prognostic relevance for patients with metastatic breast cancer. A total of 467 patients with invasive breast cancer were identified in the database of a single breast cancer center, in whom Ki-67 had been assessed in tumor material from the breast at the time of the primary diagnosis and who had developed a metastasis at any time during the subsequent course. For these patients, tumor and patient characteristics were used to determine prognostic factors relative to overall survival after the diagnosis of distant metastases. Ki-67 was added to this model to investigate whether this might improve the prediction of overall survival. In the multivariate Cox model, age at diagnosis, body mass index, nodal status, tumor size, ER and PR status, and time from diagnosis to metastasis were identified as relevant prognostic factors. Adding Ki-67 to the model improved the prediction of overall survival. There was also a significant and relevant interaction with the PR status. In patients with a low-proliferation primary tumor, a high level of PR expression would indicate an extraordinarily good prognosis (HR 0.39; 95 % CI, 0.23-0.66). In patients with higher-proliferation primary tumors, PR status was not capable of differentiating prognostic groups. Ki-67 is useful in addition to known prognostic factors for breast cancer. It is able to indicate a group of women with a poorer prognosis, specifically in the group of patients with PR-positive breast cancer. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Ki-67; Metastatic breast cancer; Progesterone receptor; Prognosis; Proliferation

Progression-free survival and overall survival in patients with advanced her2-positive breast cancer treated with trastuzumab emtansine (T-dm1) after previous treatment with pertuzumab - Michel, Laura L.; Hartkopf, Andreas D.; Fasching, Peter; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; et al. (Cancers, 2020)
The approval of trastuzumab emtansine (T-DM1) was conducted without pertuzumab as previous therapy. Efficacy data on T-DM1 following pertuzumab treatment are therefore limited. This study explores this issue in a real-world setting. Within the prospective PRAEGNANT (Prospective Academic Translational Research Network for the Optimization of the Oncological Health Care Quality in the Advanced Setting) metastatic breast cancer registry (NCT02338167), patients in all therapy lines receiving any kind of treatment were eligible for inclusion. This report describes patient characteristics and progression-free survival (PFS) in human epidermal growth factor receptor 2 (HER2)-positive patients receiving T-DM1 after pertuzumab treatment. Seventy-six patients were identified, 39 of whom received T-DM1 as second-line therapy, 25 as third-line, and 12 as fourth-line therapy or higher. Pertuzumab was mostly administered as a first-line treatment (n = 61; 80.3%). The median PFS in all patients was 3.5 months (95% CI: 2.8–7.8); in second-line treatment, 7.7 months (95% CI: 2.8–11.0); in third-line, 3.4 months (95% CI: 2.3–not reached (NR)); and in fourth-line therapy or higher, 2.7 months (95% CI: 1.2–NR). T-DM1 was mainly administered second-line after pertuzumab, but also in more heavily pretreated patients. The PFS in higher therapy lines appears to be shorter than in second-line.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Advanced breast cancer; Chemotherapy; HER2 c-erbB2; HER2/neu; Metastatic; Pertuzumab; T-DM1; Trastuzumab

Psychological Predictors of Acute Postoperative Pain after Hysterectomy for Benign Causes - Scheel, Jennifer; Sittl, Reinhard; Grießinger, Norbert; Strupf, Marion; Parthum, Andreas; Dimova, Violeta; Horn-Hofmann, Claudia; Thiel, Falk; Beckmann, Matthias; Lautenbacher, Stefan (Clinical Journal of Pain, 2016)
Psychological parameters have been shown to contribute significantly to the development of acute postoperative pain (APOP). For the prediction of APOP in chest malformation patients and cancer patients, we found pain-specific psychological predictors to be of higher relevance than general psychological predictors. The current study aims to further substantiate these findings.In a sample of 73 middle-aged hysterectomy patients, three predictor sets were assessed 1 day before surgery: attentional biases (towards pain-related, social threat, and positive words in a dot-probe task), pain-related emotions and cognitions (pain anxiety, pain catastrophizing, and pain hypervigilance), and affective state variables (depression and somatization). APOP intensity rated 2-3 days after surgery and analgesic consumption during the first 48 postoperative hours were used as outcome measures.APOP intensity ratings were significantly explained by their best single predictors in a multiple regression analysis: social threat words of the dot-probe task, pain anxiety, and somatization (14.7% of explained variance). When comparing standardized beta coefficients, pain-specific psychological predictors appeared to be of higher explanatory relevance than general psychological predictors. In contrast, analgesic consumption could not be significantly predicted by the psychological variables.Hysterectomy patients at risk for high APOP intensity could be characterized by the psychological variables used, whereas their predictive value for analgesic consumption was limited. The high predictive potency of pain-specific psychological variables should be considered for further improvement of pain management and prevention, because pain-specific variables like pain anxiety can be the target of focal psychological interventions when preparing for surgery.
EVALuna2:16734

Psychooncological counseling and treatment as part of the Comprehensive Cancer Center (CCC): Multicenter study to detect the psycho-oncological needs, indications and using - Buettner-Teleaga, A.; Weis, J.; Goerling, U.; Hornemann, B.; Erim, Yesim; Beckmann, Matthias; Senf, B.; Gresch, C.; Schulz-Kindermann, K.; Friedrich, H. -C.; Albus, C.; Geiser, F.; et al. (2016)
EVALuna2:24037

Qualitätssicherungsrichtlinie Früh- und Reifgeborene des Gemeinsamen Bundesausschusses als Qualitätsrisiko? Analyse zu Erfüllungsgrad und Konsequenzen in der Versorgung weiterer intensivpflichtiger Patienten sowie drohender Frühgeburten am Beispiel eines regionalen Verbund-Perinatalzentrums - Kleeberg, Markus; Beckmann, Matthias; Fusch, Christoph; Hanf, Volker; Kainer, Franz; Klinge, Jens; Koehler, Wolfgang; Morhart, Patrick; Schroth, Michael Andreas (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Background The quality guideline for care delivery to preterm and mature infants (QFR-RL) places high demands on perinatal centers. In this analysis, the degree of fulfillment was determined. Additionally, care delivery to further patient groups and sufficient nursing staff capacity for caredelivery to imminent preterm infants (FG) were evaluated. Methods A network of 4 perinatal centers (level 1) with about 10,000 births per year supplied the data on the ratio of 1:1/1:2-care infants,patients per nurse, and nursing staff capacity. This data was statistically evaluated by center, shift, and week day over a period of 5 months for compliance with QFR-RL and DGPM recommendations. Furthermore, imminent preterm infants were recorded and compared with available nursing staff capacity. Results In total, the QFR-RL was fulfilled in 88% of shifts (n=1,584). Only one center reached the required 95. The degree of fulfillment and the number of staff nurses declined from late to night shifts (p<0.001). The ratio of 1:1-care infants was significantly higher when demands were not fulfilled (p<0.001). Only 14.1 of imminent preterm infants could have been attended in accordance with the QFR-RL. Conclusion 1:1 care as well as lower nurse staffing in late and night shifts lead to non-fulfillment of requirements and poorer care delivery to other intensive care patients. This was also reflected in the lower degree of fulfillment of DGPM recommendations. Sufficient nursing staff capacity was rare with the consequence that it was almost impossible to deliver care to imminent preterm infants per the guideline.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 1:1-Care; preterm infants care; quality guideline of care delivery of preterm and mature infants; quality of care; staffing ratio

Quality assurance and improvement in oncology using guideline-derived quality indicators - results of gynaecological cancer centres certified by the German cancer society (DKG) - Griesshammer, Ellen; Wesselmann, S.; Beckmann, Matthias; Dannecker, C.; Wagner, U.; Sibert, N. T.; Armbrust, R.; Sehouli, J. (Journal of Cancer Research and Clinical Oncology, 2022)
Purpose Based on the example of Gynaecological Cancer Centres (GCCs) certified by the German Cancer Society, this study evaluates the results of medical-guideline-derived quality indicators (QIs) for cervical cancer (CC) and ovarian cancer (OC), examines the development of indicator implementation over time as well as the status of guideline-compliant care and identifies improvement measures. Methods QI results for patients with CC and OC treated in GCCs between 2015 and 2019 are analysed. The median, overall proportion and standard deviation of each QI were calculated. Two-sided Cochran-Armitage tests were applied. Results QIs are divided into two categories: process-organization (PO-QIs) and treatment-procedures (TP-QIs), to allow a differentiated analysis for identifying improvement measures. PO-QIs that reflect the implementation of processes and structures show a high degree of application. PO-QIs have a tremendous influence on the quality of care and are easy to implement through SOPs. TP-QIs report on treatments that are performed in the GCC. TP-QIs that report on systemic therapies reach a plateau where the guideline is known, but patient-related-factors meaningfully prevent further increase. TP-QIs that report on surgical interventions fluctuate. The most relevant factors are practitioners' personal skills. Besides the discussion of results amongst peers during the audit, improvement measures could include surgical courses or coaching. Conclusion The analysis shows that a combination of different measures is necessary to anchor quality sustainably in health care and thus improve it.
CRIS-Team WoS Importer:2022-06-17
Keywords: Quality indicators; Quality assurance; Health service research; Certification

Quality of life and oncological outcome in endometrial cancer patients after vaginal brachytherapy: comparison of two dosing schemes - Papathemelis, Thomas; Scharl, Sophia; Hipp, Matthias; Scharl, Anton; Beckmann, Matthias; Lux, Michael P.; Koelbl, Oliver (Archives of Gynecology and Obstetrics, 2019)
Purpose: Vaginal brachytherapy reduces the risk of local recurrence and was shown to be equieffective in preventing vaginal vault recurrence, but less toxic compared to external-beam radiotherapy in a subset of high intermediate-risk endometrial cancer patients and is administered as single adjuvant treatment in those patients. Different radiotherapeutic approaches with various dosing schemes exist toward brachytherapy. The aim of this study was to compare the outcome and long-term quality of life after brachytherapy with two different high-dose-rate dosing schemes. Methods: Retrospective analysis was conducted of the recurrence and survival rates of 104 patients with endometrial cancer FIGO stage I–II that underwent adjuvant brachytherapy with three times 5 Gy or four times 5 Gy to the upper two-thirds of the vaginal vault in two different institutions between January 2010 and December 2013. Quality of life was assessed by EORTC QLQ-30 questionnaire and EN 24 module. Results: The vaginal vault recurrence rates were 4.9% and 5.0% for patients treated with 3 × 5 Gy and 4 × 5 Gy, respectively (p = 0.98). We did not observe a difference in pelvic recurrence (p = 0.96), overall survival (p = 0.33) or quality of life between the different radiotherapy regimens. Metastatic recurrence and the use of chemotherapy contribute to impairment on quality of life. Younger patients (< 70 years) reported worse emotional functioning (p = 0.02) and higher symptom scales of diarrhea (p = 0.01) and financial problems (p = 0.03). Sexual activity was lower in patients younger than 70 years (p = 0.05). Conclusions: Further prospective studies are needed to evaluate the effect of dosing schemes on recurrence rates and quality of life. Younger patients (< 70 years) seem to experience greater reduction in quality of life due to endometrial cancer diagnosis.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Adjuvant treatment; Brachytherapy; Endometrial cancer; Radiotherapy

RAD51B in Familial Breast Cancer - Pelttari, Liisa M.; Khan, Sofia; Vuorela, Mikko; Kiiski, Johanna I.; Vilske, Sara; Nevanlinna, Viivi; Ranta, Salla; Schleutker, Johanna; Winqvist, Robert; Kallioniemi, Anne; Doerk, Thilo; Bogdanova, Natalia V.; et al. (PLoS ONE, 2016)
Common variation on 14q24.1, close to RAD51B, has been associated with breast cancer: rs999737 and rs2588809 with the risk of female breast cancer and rs1314913 with the risk of male breast cancer. The aim of this study was to investigate the role of RAD51B variants in breast cancer predisposition, particularly in the context of familial breast cancer in Finland. We sequenced the coding region of RAD51B in 168 Finnish breast cancer patients from the Helsinki region for identification of possible recurrent founder mutations. In addition, we studied the known rs999737, rs2588809, and rs1314913 SNPs and RAD51B haplotypes in 44,791 breast cancer cases and 43,583 controls from 40 studies participating in the Breast Cancer Association Consortium (BCAC) that were genotyped on a custom chip (iCOGS). We identified one putatively pathogenic missense mutation c.541C>T among the Finnish cancer patients and subsequently genotyped the mutation in additional breast cancer cases (n = 5259) and population controls (n = 3586) from Finland and Belarus. No significant association with breast cancer risk was seen in the meta-analysis of the Finnish datasets or in the large BCAC dataset. The association with previously identified risk variants rs999737, rs2588809, and rs1314913 was replicated among all breast cancer cases and also among familial cases in the BCAC dataset. The most significant association was observed for the haplotype carrying the risk-alleles of all the three SNPs both among all cases (odds ratio (OR): 1.15, 95% confidence interval (CI): 1.11-1.19, P = 8.88 x 10-16) and among familial cases (OR: 1.24, 95% CI: 1.16-1.32, P = 6.19 x 10-11), compared to the haplotype with the respective protective alleles. Our results suggest that loss-of-function mutations in RAD51B are rare, but common variation at the RAD51B region is significantly associated with familial breast cancer risk.
EVALuna2:33327

RANK and RANKL Expression in Tumors of Patients with Early Breast Cancer - Behrens, Annika; Wurmthaler, Lena; Heindl, Felix; Gaß, Paul; Häberle, Lothar; Volz, Bernhard; Hack, Carolin; Emons, Julius; Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Rübner, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction The receptor activator of nuclear factor-κB (RANK) pathway was associated with the pathogenesis of breast cancer. Several studies attempted to link the RANK/RANKL pathway to prognosis; however, with inconsistent outcomes. We aimed to further contribute to the knowledge about RANK/RANKL as prognostic factors in breast cancer. Within this study, protein expression of RANK and its ligand, RANKL, in the tumor tissue was analyzed in association with disease-free survival (DFS) and overall survival (OS) in a study cohort of patients with early breast cancer. Patients and Methods 607 samples of female primary and early breast cancer patients from the Bavarian Breast Cancer Cases and Controls Study were analyzed to correlate the RANK and RANKL expression with DFS and OS. Therefore, expression was quantified using immunohistochemical staining of a tissue microarray. H-scores were determined with the cut-off value of 8.5 for RANK and 0 for RANKL expression, respectively. Results RANK and RANKL immunohistochemistry were assessed by H-score. Both biomarkers did not correlate (ρ = -0.04). According to molecular subtypes, triple-negative tumors and HER2-positive tumors showed a higher number of RANK-positive tumors (H-score ≥ 8.5), however, no subtype-specific expression of RANKL could be detected. Higher RANKL expression tended to correlate with a better prognosis. However, RANK and RANKL expression could not be identified as statistically significant prognostic factors within the study cohort. Conclusions Tumor-specific RANK and RANKL expressions are not applicable as prognostic factors for DFS and OS, but might be associated with subtype-specific breast cancer progression.
CRIS-Team Scopus Importer:2023-12-22
Keywords: breast cancer; immunohistochemistry; prognosis; RANK; RANKL

RANKL and OPG and their influence on breast volume changes during pregnancy in healthy women - Wunderle, Marius; Rübner, Matthias; Häberle, Lothar; Schwenke, Eva; Hack, Carolin; Bayer, Christian M.; Koch, Martin; Schwitulla, Judith; Schulz-Wendtland, Rüdiger; Kozieradzki, Ivona; Lux, Michael P.; Beckmann, Matthias; et al. (Scientific Reports, 2020)
Breast cancer risk is reduced by number of pregnancies and breastfeeding duration, however studies of breast changes during or after pregnancy are rare. Breast volume changes - although not linked to breast cancer risk - might be an interesting phenotype in this context for correlative studies, as changes of breast volume vary between pregnant women. Serum receptor activator of nuclear factor kappa B ligand (RANKL) and its antagonist osteoprotegerin (OPG) were measured prospectively before gestational week 12, and three-dimensional breast volume assessments were performed. A linear regression model including breast volume at the start of pregnancy, RANKL, OPG, and other factors was used to predict breast volume at term. The mean breast volume was 413 mL at gestational week 12, increasing by a mean of 99 mL up to gestational week 40. In addition to body mass index and breast volume at the beginning of pregnancy, RANKL and OPG appeared to influence breast volume with a mean increase by 32 mL (P = 0.04) and a mean reduction by 27 mL (P = 0.04), respectively. Linking the RANKL/RANK/OPG pathway with breast volume changes supports further studies aiming at analysing breast changes during pregnancy with regard to breast cancer risk.
CRIS-Team Scopus Importer:2020-03-31

Rare Case Report - Mucoepidermoid Carcinoma (MEC) of the Vulva - Dietl, Anna; Stübs, Frederik; Schulmeyer, Carla; Behrens, Annika; Hartmann, Arndt; Agaimy, Abbas; Beckmann, Matthias; Gaß, Paul (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Rare germline copy number variants (CNVs) and breast cancer risk - Dennis, Joe; Tyrer, Jonathan P.; Walker, Logan C.; Michailidou, Kyriaki; Dorling, Leila; Bolla, Manjeet K.; Wang, Qin; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Arndt, Volker; et al. (Communications Biology, 2022)
Germline copy number variants (CNVs) are pervasive in the human genome but potential disease associations with rare CNVs have not been comprehensively assessed in large datasets. We analysed rare CNVs in genes and non-coding regions for 86,788 breast cancer cases and 76,122 controls of European ancestry with genome-wide array data. Gene burden tests detected the strongest association for deletions in BRCA1 (P = 3.7E-18). Nine other genes were associated with a p-value < 0.01 including known susceptibility genes CHEK2 (P = 0.0008), ATM (P = 0.002) and BRCA2 (P = 0.008). Outside the known genes we detected associations with p-values < 0.001 for either overall or subtype-specific breast cancer at nine deletion regions and four duplication regions. Three of the deletion regions were in established common susceptibility loci. To the best of our knowledge, this is the first genome-wide analysis of rare CNVs in a large breast cancer case-control dataset. We detected associations with exonic deletions in established breast cancer susceptibility genes. We also detected suggestive associations with non-coding CNVs in known and novel loci with large effects sizes. Larger sample sizes will be required to reach robust levels of statistical significance.
CRIS-Team Scopus Importer:2022-02-04

Reconstructive and Aesthetic Surgeries on the Female GenitaliaGuideline of the DGGG, DGPRAC, OEGGG and SGGG (S2k-Level, AWMF Registry No. 009/019, May 2022) - Beckmann, Matthias; Borkenhagen, Ada; Fahlbusch, Christine; Gold, Daniela; Hoffmann, Juergen; Löhrs, Bettina; Luze, Hanna; Mirastschijski, Ursula; O'Dey, Dan M.; Pöschke, Patrik; Remmel, Eugenia; Schaefer, Dirk; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Aim This official guideline was coordinated and published by the German Society for Gynaecology and Obstetrics (DGGG), the German Society for Plastic, Reconstructive and Aesthetic Surgery (DGPRAC), the Austrian Society for Gynaecology and Obstetrics (OEGGG), and the Swiss Society for Gynaecology and Obstetrics (SGGG). The guideline aims to provide a consensus-based overview of reconstructive and aesthetic surgeries on female genitalia based on an evaluation of the relevant literature. Methods This S2k-guideline was developed by representative members from different medical professions on behalf of the guidelines commission of the DGGG, DGPRAC, OEGGG and SGGG using a structured consensus process. Recommendations Statements and recommendations on the epidemiology, aetiology, classification, symptoms, diagnosis, and treatment of acquired changes of the external genitalia are presented and special situations are discussed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: aesthetic surgeries; female genital mutilation (FGM); female genitalia; guideline; reconstructive surgeries

Recording of the regional Origin Areas of Patients from the Molecular Tumor Board to Identify the "white Spots" in the Service Area - A joint Initiative of the Bavarian CCC WERA Alliance - Lueke, F.; Haller, F.; Utpatel, K.; Krebs, M.; Meidenbauer, Norbert; Scheiter, A.; Spörl, Silvia; Heudobler, D.; Keil, F.; Schubart, Christoph; Tögel, Lars; Einhell, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Recurrent KAT6B/A::KANSL1 Fusions Characterize a Potentially Aggressive Uterine Sarcoma Morphologically Overlapping With Low-grade Endometrial Stromal Sarcoma. - Agaimy, Abbas; Clarke, Blaise A.; Kolin, David L.; Lee, Cheng-Han; Lee, Jen-Chieh; Mccluggage, W. Glenn; Pöschke, Patrik; Stöhr, Robert; Swanson, David; Turashvili, Gulisa; Beckmann, Matthias; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2022)
With the widespread application of next-generation sequencing, the genetic landscape of uterine mesenchymal neoplasms has been evolving rapidly to include several recently identified fusion genes. Although chromosomal rearrangements involving the 10q22 and 17q21.31 loci have been reported in occasional uterine leiomyomas decades ago, the corresponding KAT6B::KANSL1 fusion has been only recently identified in 2 uterine tumors diagnosed as leiomyoma and leiomyosarcoma. We herein describe 13 uterine stromal neoplasms carrying a KAT6B::KANSL1 (n=11) and KAT6A::KANSL1 (n=2) fusion. Patient ages ranged from 33 to 81 years (median, 49 y). Tumor size was 2.6 to 23.5 cm (median, 8.2 cm). Nine tumors were myometrium-centered, and 3 had an intracavitary component. Original diagnoses were mostly low-grade endometrial stromal sarcoma (LG-ESS; 10 cases) with atypical features (limited CD10 expression, sex cord-like features, pericytic vasculature, and frequent myxoid changes). Treatment was hysterectomy±bilateral salpingo-oophorectomy (10), myomectomy (1), and curettage (2). Five patients were disease-free at 6 to 34 months, 3 (27%) died of disease at 2 to 47 months, and 3 were alive with disease at 2, 17, and 17 years. Histologically, most tumors showed variable overlap with LG-ESS, but they were generally well-circumscribed lacking the extensive permeative and angioinvasive growth typical of LG-ESS. They were composed of monotonous medium-sized oval and spindle cells arranged into diffuse sheets with prominent spiral-type arterioles and frequent pericytoma-like vascular pattern. Variable myxoid stromal changes were frequent. Mitotic activity ranged from 1 to >20 in 10 HPFs. Immunohistochemistry showed variable expression of CD10 (12/13), estrogen receptor (8/11), progesterone receptor (8/11), smooth muscle actin (9/11), desmin (4/12), h-caldesmon (2/10), calretinin (3/8), inhibin (1/7), WT1 (4/7), cyclin D1 (5/11; diffuse in only 1 case), and pankeratin (5/10). This series characterizes a KAT6B/A::KANSL1 fusion-positive uterine stromal neoplasm within the morphologic spectrum of LG-ESS but with atypical features. The relationship of these neoplasms to genuine LG-ESS remains unclear. This molecular subtype of uterine endometrial stromal sarcoma has the potential for an unfavorable clinical course despite the absence of widely invasive growth; nevertheless, analysis of more cases is necessary to delineate the phenotypic spectrum and biological potential of this tumor.
EVALuna2:504168

Refined histopathological predictors of BRCA1 and BRCA2 mutation status: a large-scale analysis of breast cancer characteristics from the BCAC, CIMBA, and ENIGMA consortia - Spurdle, Amanda B.; Couch, Fergus J.; Parsons, Michael T.; Mcguffog, Lesley; Barrowdale, Daniel; Bolla, Manjeet K.; Wang, Qin; Healey, Sue; Schmutzler, Rita Katharina; Wappenschmidt, Barbara; Rhiem, Kerstin; Hahnen, Eric; et al. (Breast Cancer Research, 2014)
The distribution of histopathological features of invasive breast tumors in BRCA1 or BRCA2 germline mutation carriers differs from that of individuals with no known mutation. Histopathological features thus have utility for mutation prediction, including statistical modeling to assess pathogenicity of BRCA1 or BRCA2 variants of uncertain clinical significance. We analyzed large pathology datasets accrued by the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) and the Breast Cancer Association Consortium (BCAC) to reassess histopathological predictors of BRCA1 and BRCA2 mutation status, and provide robust likelihood ratio (LR) estimates for statistical modeling.Selection criteria for study/center inclusion were estrogen receptor (ER) status or grade data available for invasive breast cancer diagnosed younger than 70 years. The dataset included 4,477 BRCA1 mutation carriers, 2,565 BRCA2 mutation carriers, and 47,565 BCAC breast cancer cases. Country-stratified estimates of the likelihood of mutation status by histopathological markers were derived using a Mantel-Haenszel approach.ER-positive phenotype negatively predicted BRCA1 mutation status, irrespective of grade (LRs from 0.08 to 0.90). ER-negative grade 3 histopathology was more predictive of positive BRCA1 mutation status in women 50 years or older (LR = 4.13 (3.70 to 4.62)) versus younger than 50 years (LR = 3.16 (2.96 to 3.37)). For BRCA2, ER-positive grade 3 phenotype modestly predicted positive mutation status irrespective of age (LR = 1.7-fold), whereas ER-negative grade 3 features modestly predicted positive mutation status at 50 years or older (LR = 1.54 (1.27 to 1.88)). Triple-negative tumor status was highly predictive of BRCA1 mutation status for women younger than 50 years (LR = 3.73 (3.43 to 4.05)) and 50 years or older (LR = 4.41 (3.86 to 5.04)), and modestly predictive of positive BRCA2 mutation status in women 50 years or older (LR = 1.79 (1.42 to 2.24)).These results refine likelihood-ratio estimates for predicting BRCA1 and BRCA2 mutation status by using commonly measured histopathological features. Age at diagnosis is an important variable for most analyses, and grade is more informative than ER status for BRCA2 mutation carrier prediction. The estimates will improve BRCA1 and BRCA2 variant classification and inform patient mutation testing and clinical management.
EVALuna2:9304

Regulation of murine placentogenesis by the retroviral genes Syncytin-A, Syncytin-B and Peg10 - Henke, Christine; Ruebner, Matthias; Faschingbauer, Florian; Stolt, Claus; Schäfer, Natascha; Lang, Nadine; Beckmann, Matthias; Strissel, Pamela; Strick, Reiner (Differentiation, 2013)
The murine placenta has a trichorial structure with two multinucleated syncytiotrophoblast (SCT) layers representing a barrier between the maternal and fetal blood system. Genes of endogenous retroviruses and retrotransposon-derived paternally expressed genes (Peg), remnants of past infections and integrations in the genome, have essential functions in placentogenesis. Previous studies showed that the envelope genes Syncytin-A and Syncytin-B were essential for cell-cell fusion of the SCT. The goal of this study was to analyze the temporal localization and expression of nine genes throughout placental development from embryonic day (E)8.5 to E18.5 using in situ-hybridization and absolute RNA-quantification. These included a comparison of previously characterized genes from the labyrinth Syncytin-A, Syncytin-B, Gcm1, the junctional zone PL-1, PL-2, Plf, Tpbpa with two further characterized genes Peg10 and Tpbpb. Syncytin-A and Syncytin-B RNA localized to SCT-I and SCT-II, respectively. Peg10 RNA localized to all extraembryonic tissues, specifically to the parietal and sinusoidal TGC of the labyrinth layer, which is in contact with SCT-I and the maternal blood. All three retroviral/retrotransposon-derived genes showed the highest expression at E16.5, but Peg10 with 188,917.1 molecules/ng cDNA was 208-fold and 106.8-fold higher expressed than Syncytin-A and Syncytin-B, respectively. Tpbpb localized to the junctional zone and showed the highest expression at E16.5 along with PL-2, Plf, Tpbpa, but not PL-1, which decreased in expression at E10.5. To investigate a role of Syncytin-A, Syncytin-B and Peg10 in cell-cell fusion, we established a cell culture system with fractionated primary trophoblasts from murine placentae. Culturing trophoblasts for up to 72h partly resembled trophoblast development in vivo according to the nine marker genes. Knockdown of Syncytin-A demonstrated a functional regulation of cell-cell fusion, where knockdown of Peg10 showed no involvement in cell fusion. Due to the expression of Peg10 in TGCs, we propose an essential functional role in the fetal-maternal blood system.
EVALuna2:4934

Re-irradiation of the chest wall for local breast cancer recurrence : Results of salvage brachytherapy with hyperthermia - Auoragh, A.; Strnad, Vratislav; Ott, O. J.; Beckmann, Matthias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
Following mastectomy and adjuvant external beam radiation therapy in patients with breast cancer, the incidence of local or locoregional recurrence is approximately 9 % (2-20 %). Alongside the often limited possibilities of surgical treatment, radiation therapy combined with superficial hyperthermia is the most effective local therapy. In the present work, a retrospective analysis of salvage brachytherapy combined with superficial hyperthermia for chest wall recurrences is presented.Between 2004 and 2011, 18 patients with a total of 23 target volumes resulting from chest wall recurrences after previously mastectomy and external beam radiation therapy (median 56 Gy, range 50-68 Gy) were treated with superficial brachytherapy as salvage treatment: 8 patients (44 %) had macroscopic tumor, 3 (17 %) had microscopic tumor (R1), and 7 (39 %) had undergone R0 resection and were treated due to risk factors. A dose of 50 Gy was given (high-dose rate [HDR] and pulsed-dose rate [PDR] procedures). In all, 5 of 23 patients (22 %) received additional concurrent chemotherapy, and in 20 of 23 (87 %) target volumes additional superficial hyperthermia was carried out twice weekly.The 5-year local recurrence-free survival was 56 %, the disease-free survival was 28 %, and a 5-year overall survival was 22 %. Late side effects Common Toxicity Criteria (CTC) grade 3 were reported in 17 % of the patients: 2 of 18 (11 %) had CTC grade 3 fibrosis, and 1 of 18 (6 %) had a chronic wound healing disorder.Re-irradiation as salvage brachytherapy with superficial hyperthermia for chest wall recurrences is a feasible and safe treatment with good local control results and acceptable late side effects.
EVALuna2:18364

Reliability of prenatal detection of X-linked hypohidrotic ectodermal dysplasia by tooth germ sonography - Hammersen, Johanna; Wohlfart, Sigrun; Goecke, Tamme W.; Köninger, Angela; Stepan, Holger; Gallinat, Ralph; Morris, Susan; Bücher, Katharina; Clarke, Angus; Wünsche, Stephanie; Beckmann, Matthias; Schneider, Holm; et al. (Prenatal Diagnosis, 2019)
Objective: In X-linked hypohidrotic ectodermal dysplasia (XLHED), dysfunction of ectodysplasin A1 (EDA1) due to EDA mutations results in malformation of hair, teeth, and sweat glands. Hypohidrosis, which can cause life-threatening hyperthermia, is amenable to intrauterine therapy with recombinant EDA1. This study aimed at evaluating tooth germ sonography as a noninvasive means to identify affected fetuses in pregnant carrier women. Methods: Sonography, performed at 10 study sites between gestational weeks 18 and 28, led to the diagnosis of XLHED if fewer than six tooth germs were detected in mandible or maxilla. The assessment was verified postnatally by EDA sequencing and/or clinical findings. Estimated fetal weights and postnatal weight gain of boys with XLHED were assessed using appropriate growth charts. Results: In 19 of 38 sonographic examinations (23 male and 13 female fetuses), XLHED was detected prenatally. The prenatal diagnosis proved to be correct in 37 cases; one affected male fetus was missed. Specificity and positive predictive value were both 100%. Tooth counts obtained by clinical examination corresponded well with findings on panoramic radiographs. We observed no weight deficits of subjects with XLHED in utero but occasionally during infancy. Conclusion: Tooth germ sonography is highly specific and reliable in detecting XLHED prenatally.
CRIS-Team Scopus Importer:2019-08-27

Repetitive Maturation of Oocytes From Non-Stimulated Xenografted Ovarian Tissue From a Prepubertal Patient Indicating the Independence of Human Ovarian Tissue - Raffel, Nathalie; Lotz, Laura; Hoffmann, Inge; Liebenthron, Jana; Söder, Stephan; Beckmann, Matthias; Dittrich, Ralf (Geburtshilfe und Frauenheilkunde, 2017)
Introduction: Modern anti-cancer strategies have distinctly increased survival rates; nevertheless, often accompanied by sterility. Currently, the only option for preserving fertility in prepubertal females is to cryopreserve ovarian tissue and re-transplant frozen-thawed tissue to restore fertility after treatment. Our aim was to report the occurrence of repetitive antral follicle formation and oocyte maturation in a prepubescent ovarian tissue xenograft without exogenous hormone stimulation. Material and Methods: Frozen-thawed ovarian tissue from a 6-year-old patient suffering from nephroblastoma was xenotransplanted in oophorectomized severe combined immunodeficiency (SCID) mice to evaluate follicle development. Ergebnisse: Repetitive follicle development to the antral stage occurred in the same xenograft of prepubertal ovarian tissue without exogenous hormone administration; 37 days after retrieving a maturing oocyte (this first retrieval has been previously published), another, completely mature oocyte was harvested from the xenograft. Subsequent histological evaluation of the grafted tissue showed primordial follicles, nearly all stages of developing follicles, as well as large atretic ones. Many clusters with dormant primordial follicles were also present. Conclusion: Xenotransplanted prepubertal ovarian tissue has the potential for repetitive oocyte retrieval cycles without administering exogenous hormones. The results indicate that the human ovarian tissue might be able to synchronize the hypothalamus-hypophysis-axes of the mouse to the physiological human cycle; this should be investigated in future studies.
EVALuna2:34929

Replication of Epigenetic Postpartum Depression Biomarkers and Variation with Hormone Levels - Osborne, Lauren; Clive, Makena; Kimmel, Mary; Gispen, Fiona; Guintivano, Jerry; Brown, Tori; Cox, Olivia; Judy, Jennifer; Meilman, Samantha; Braier, Aviva; Beckmann, Matthias; Kornhuber, Johannes; et al. (Neuropsychopharmacology, 2016)
DNA methylation variation at HP1BP3 and TTC9B is modified by estrogen exposure in the rodent hippocampus and was previously shown to be prospectively predictive of postpartum depression (PPD) when modeled in antenatal blood. The objective of this study was to replicate the predictive efficacy of the previously established model in women with and without a previous psychiatric diagnosis and to understand the effects of changing hormone levels on PPD biomarker loci. Using a statistical model trained on DNA methylation data from N=51 high-risk women, we prospectively predicted PPD status in an independent N=51 women using first trimester antenatal gene expression levels of HP1BP3 and TTC9B, with an area under the receiver operator characteristic curve (AUC) of 0.81 (95% CI: 0.69-0.92, p<5 × 10(-4)). Modeling DNA methylation of these genes in N=240 women without a previous psychiatric diagnosis resulted in a cross-sectional prediction of PPD status with an AUC of 0.81 (95% CI: 0.68-0.93, p=0.01). TTC9B and HP1BP3 DNA methylation at early antenatal time points showed moderate evidence for association to the change in estradiol and allopregnanolone over the course of pregnancy, suggesting that epigenetic variation at these loci may be important for mediating hormonal sensitivity. In addition both loci showed PPD-specific trajectories with age, possibly mediated by age-associated hormonal changes. The data add to the growing body of evidence suggesting that PPD is mediated by differential gene expression and epigenetic sensitivity to pregnancy hormones and that modeling proxies of this sensitivity enable accurate prediction of PPD.
EVALuna2:23791

Reply to "Response to: Dittrich et al.: Non-Embryo-Destructive Extraction of Pluripotent Embryonic Stem Cells - Overlooked Legal Prohibitions, Professional Legal Consequences and Inconsistencies in Patent Law" - Dittrich, Ralf; Beckmann, Matthias; Wuerfel, W. (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32938

Reproducibility of mRNA-Based Testing of ESR1, PGR, ERBB2, and MKI67 Expression in Invasive Breast Cancer-A Europe-Wide External Quality Assessment - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Rübner, Matthias; Stöhr, Robert; Beckmann, Matthias; Zentgraf, Miriam; Popp, Verena; Weidler, Jodi; Simon, Iris; Becker, Steffi; Hübner, Hanna; et al. (Cancers, 2021)
Simple Summary Four biomarkers [estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2], are used to stratify breast cancer (BC) into subtypes predictive of therapy response. In a Europe-wide external quality assessment, we compared performance of an mRNA-based method [Xpert(R) Breast Cancer STRAT4 (CE-IVD)] for determining ESR1, PGR, ERBB2, and MKI67 expression against the gold standard [immunohistochemistry (IHC)/HER2 in situ hybridization (ISH)]. The coordinating center (CC) and five European laboratories tested ten breast cancer samples. STRAT4 binary (positive or negative) results of each marker were compared with the gold standard. ESR1 and ERBB2 mRNA results were concordant with IHC/ISH in all single analyses. In contrast, PGR and MKI67 results were discordant in a few cases, which had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. STRAT4 assay may be a reproducible method. However, cases with expression values close to cut-offs should be carefully reviewed. Estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2 immunohistochemistry (IHC) together with HER2 in situ hybridization (ISH) are utilized to classify invasive breast cancer (IBC) into predictive molecular subtypes. As IHC evaluation may be hampered by analytical errors, gene expression assays could offer a reliable alternative. In this first Europe-wide external quality assessment (EQA) study, we investigated performance of mRNA-based Xpert(R) Breast Cancer STRAT4 (CE-IVD) in five European laboratories. The cohort comprised ten pre-therapy IBC core biopsies diagnosed in the coordinating center (CC). STRAT4 binary (positive or negative) mRNA results of each marker (ESR1, PGR, ERBB2, MKI67) were compared with the gold standard IHC/ISH performed by the CC. Sensitivity, specificity, and accuracy of ESR1 and ERBB2 mRNA were 100% for all samples. In contrast, PGR expression was falsely negative for one case by two sites and MKI67 falsely negative for two cases (respectively by four and one sites). These cases had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. Our EQA shows that STRAT4 mRNA assay may be a reproducible method to evaluate ER, PgR, HER2, and Ki-67 status. However, cases with expression values close to assay cut-offs should be carefully reviewed.
CRIS-Team WoS Importer:2021-10-08

Reproductive profiles and risk of breast cancer subtypes: a multi-center case-only study - Brouckaert, Olivier; Rudolph, Anja; Laenen, Annouschka; Keeman, Renske; Bolla, Manjeet K.; Wang, Qin; Soubry, Adelheid; Wildiers, Hans; Andrulis, Irene L.; Arndt, Volker; Beckmann, Matthias; Benitez, Javier; et al. (Breast Cancer Research, 2017)
BACKGROUND: Previous studies have shown that reproductive factors are differentially associated with breast cancer (BC) risk by subtypes. The aim of this study was to investigate associations between reproductive factors and BC subtypes, and whether these vary by age at diagnosis. METHODS: We used pooled data on tumor markers (estrogen and progesterone receptor, human epidermal growth factor receptor-2 (HER2)) and reproductive risk factors (parity, age at first full-time pregnancy (FFTP) and age at menarche) from 28,095 patients with invasive BC from 34 studies participating in the Breast Cancer Association Consortium (BCAC). In a case-only analysis, we used logistic regression to assess associations between reproductive factors and BC subtype compared to luminal A tumors as a reference. The interaction between age and parity in BC subtype risk was also tested, across all ages and, because age was modeled non-linearly, specifically at ages 35, 55 and 75 years. RESULTS: Parous women were more likely to be diagnosed with triple negative BC (TNBC) than with luminal A BC, irrespective of age (OR for parity = 1.38, 95% CI 1.16-1.65, p = 0.0004; p for interaction with age = 0.076). Parous women were also more likely to be diagnosed with luminal and non-luminal HER2-like BCs and this effect was slightly more pronounced at an early age (p for interaction with age = 0.037 and 0.030, respectively). For instance, women diagnosed at age 35 were 1.48 (CI 1.01-2.16) more likely to have luminal HER2-like BC than luminal A BC, while this association was not significant at age 75 (OR = 0.72, CI 0.45-1.14). While age at menarche was not significantly associated with BC subtype, increasing age at FFTP was non-linearly associated with TNBC relative to luminal A BC. An age at FFTP of 25 versus 20 years lowered the risk for TNBC (OR = 0.78, CI 0.70-0.88, p < 0.0001), but this effect was not apparent at a later FFTP. CONCLUSIONS: Our main findings suggest that parity is associated with TNBC across all ages at BC diagnosis, whereas the association with luminal HER2-like BC was present only for early onset BC.
EVALuna2:36119

Resilience, Fear of Progression and Psychosocial Distress in Patients with Breast Cancer and Gynecological Tumors Seeking a Second Opinion. - Krebs, Jessica; Wasner, Sonja; Egloffstein, Sainab; Lux, Michael P.; Morawa, Eva; Beckmann, Matthias; Erim, Yesim (Psychotherapie Psychosomatik Medizinische Psychologie, 2018)

Response to di Cosimo, Torri, and Porcu - Trapp, Elisabeth; Janni, Wolfgang; Schindlbeck, Christian; Jückstock, Julia; Andergassen, Ulrich; Degregorio, Amelie; Alunni-Fabbroni, Marianna; Tzschaschel, Marie; Polasik, Arkadius; Koch, Julian G.; Friedl, Thomas W.P.; Fasching, Peter A.; et al. (Journal of the National Cancer Institute, 2019)
CRIS-Team Scopus Importer:2019-12-24

Results of Stimulation Treatment through pulsatile GnRH Substitution by using an innovative, patient-controlled System (LutrePulse((R))) - Hildebrandt, Thomas; Lotz, Laura; Blum, Simon; Fahlbusch, C.; Heusinger, K.; Cupisti, S.; Dittrich, Ralf; Beckmann, Matthias; Antoniadis, Sophia (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Return of individual genomic research results within the PRAEGNANT multicenter registry study - Hübner, Hanna; Rübner, Matthias; Kurbacher, Christian; Hadji, Peyman; Hartkopf, Andreas D.; Lux, Michael P.; Huober, Jens; Uhrig, Sabrina; Taran, Florin Andrei; Overkamp, Friedrich; Tesch, Hans; Häberle, Lothar; et al. (Breast Cancer Research and Treatment, 2022)
Purpose: The PRAEGNANT study is a registry study for metastatic breast cancer patients, focusing on biomarker detection. Recently, within this study, genetic alterations in 37 breast cancer predisposition genes were analyzed and genetic findings were detected for 396 participants. The aim of this project was to return genetic results to the physicians and to analyze actions taken (e.g., disclosure of results to patients, validation of results, clinical impact, and impact on the patient’s quality of life) using a questionnaire. Methods: 235 questionnaires were sent out to the study centers, with each questionnaire representing one patient with a genetic finding. The questionnaire consisted of twelve questions in the German language, referring to the disclosure of results, validation of test results, and their impact on treatment decisions and on the patient’s quality of life. Results: 135 (57.5%) questionnaires were completed. Of these, 46 (34.1%) stated that results were returned to the patients. In 80.0% (N = 36) of cases where results were returned, the patient had not been aware of the finding previously. For 27 patients (64.3%), genetic findings had not been validated beforehand. All validation procedures (N = 15) were covered by the patients’ health insurance. For 11 (25.0%) patients, physicians reported that the research results influenced current or future decision-making on treatment, and for 37.8% (N = 17) the results influenced whether family members will be genetically tested. Conclusion: This study provides novel insights into the return of research results and into clinical and personal benefits of disclosure of genetic findings within a German registry.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Breast cancer; Genetic testing; Incidental findings; Research results; Return of results

Revised German guidelines on the diagnosis and treatment of carcinoma of the uterine cervix-what's new for pathologists in 2021? - Horn, Lars-Christian; Beckmann, Matthias; Follmann, Markus; Koch, Martin C.; Nothacker, Monika; Poschel, Birgit; Stübs, Frederik; Schmidt, Dietmar; Hohn, Anne Kathrin (Pathologe, 2022)
In 2021, the 2015 German consensus guideline for the diagnosis and treatment of uterine cervical carcinoma was updated. The present article summarises the new recommendations for pathologists: the incorporation of the International Endocervical Adenocarcinoma Classification (IECC), which morphologically separates HPV-associated and non-HPV-associated adenocarcinomas, as well as the reporting of the prognostic relevant growth pattern of the adenocarcinoma of the endocervical subtype (Silva pattern). Histologically, multifocality has been defined as the presence of clearly invasive foci with a minimum distance between each focus of 0.2 cm. Because of its intratumoural heterogeneity, all carcinomas <= 2 cm in their largest dimension should be processed completely, and tumours > 2 cm should be processed with one block per centimetre of their greatest dimension. In cases of (radical) trachelectomy/hysterectomy, the distal vaginal resection margin and all parametrial tissue should be processed completely. Sentinel lymph nodes have to be processed completely by lamellation along its long axis in 0.2 cm intervals. Immunohistochemical ultrastaging is mandatory. Staging should be performed using the 2009 FIGO classification and 2017 TNM classification. Reporting the revised 2018 FIGO classification is optional. To date, molecular markers have not been relevant for prognostication and treatment decision making.
CRIS-Team WoS Importer:2022-03-04
Keywords: Cutting; Workup; Diagnostic

Risk of Ovarian Cancer and the NF-?B Pathway: Genetic Association with IL1A and TNFSF10 - Charbonneau, Bridget; Block, Matthew S.; Bamlet, William R.; Vierkant, Robert A.; Kalli, Kimberly R.; Fogarty, Zachary; Rider, David N.; Sellers, Thomas A.; Tworoger, Shelley S.; Poole, Elizabeth; Risch, Harvey A.; Salvesen, Helga B.; et al. (Cancer Research, 2014)
A missense single-nucleotide polymorphism (SNP) in the immune modulatory gene IL1A has been associated with ovarian cancer risk (rs17561). Although the exact mechanism through which this SNP alters risk of ovarian cancer is not clearly understood, rs17561 has also been associated with risk of endometriosis, an epidemiologic risk factor for ovarian cancer. Interleukin-1? (IL1A) is both regulated by and able to activate NF-?B, a transcription factor family that induces transcription of many proinflammatory genes and may be an important mediator in carcinogenesis. We therefore tagged SNPs in more than 200 genes in the NF-?B pathway for a total of 2,282 SNPs (including rs17561) for genotype analysis of 15,604 cases of ovarian cancer in patients of European descent, including 6,179 of high-grade serous (HGS), 2,100 endometrioid, 1,591 mucinous, 1,034 clear cell, and 1,016 low-grade serous, including 23,235 control cases spanning 40 studies in the Ovarian Cancer Association Consortium. In this large population, we confirmed the association between rs17561 and clear cell ovarian cancer [OR, 0.84; 95% confidence interval (CI), 0.76-0.93; P = 0.00075], which remained intact even after excluding participants in the prior study (OR, 0.85; 95% CI, 0.75-0.95; P = 0.006). Considering a multiple-testing-corrected significance threshold of P < 2.5 × 10(-5), only one other variant, the TNFSF10 SNP rs6785617, was associated significantly with a risk of ovarian cancer (low malignant potential tumors OR, 0.85; 95% CI, 0.79-0.91; P = 0.00002). Our results extend the evidence that borderline tumors may have a distinct genetic etiology. Further investigation of how these SNPs might modify ovarian cancer associations with other inflammation-related risk factors is warranted. Cancer Res; 74(3); 852-61. ©2013 AACR.
EVALuna2:9204

Risk of postmenopausal hormone therapy and patient history factors for the survival rate in women with endometrial carcinoma - Hein, Alexander; Schneider, Michael; Renner, Stefan; Fasching, Peter; Fießler, Cornelia; Titz, Susanna; Hartmann, Arndt; Beckmann, Matthias; Thiel, Falk C. (Archives of Gynecology and Obstetrics, 2019)
Purpose: Postmenopausal hormone therapy (HT) is known to affect the development of hormone-dependent endometrial carcinoma (type I EC). Several studies on breast and ovarian carcinoma have shown that HT influences the molecular profile and prognostic behavior of these tumors. This study aimed to investigate the influence of prior HT and other risk factors on the prognosis in a cohort of patients with invasive endometrial carcinoma (EC). Methods: Among 525 patients diagnosed with EC between 1987 and 2010, 426 postmenopausal patients were identified. Information regarding HT was available in 287 of these patients, 78 of whom had a history of HT and 209 of whom did not. Both overall survival (OS) and progression-free survival (PFS) were analyzed. In addition to OS and PFS, risk factors such as age at diagnosis, postmenopausal HT, body mass index (BMI), diabetes mellitus, tumor stage, EC type (I or II), and recurrences were analyzed. Results: Relative to HT alone, women with EC and a history of HT had a longer survival than those with no HT. However, the Cox proportional hazards model showed that it was not HT itself, but rather other characteristics in the HT group that were causally associated with longer survival. Conclusions: Age (the older, the worse) and tumor stage (the higher, the worse) were significant influences on overall survival. Patients with HT also had lower BMIs, less diabetes, more type I EC, and fewer recurrences in comparison with the non-HT group. With regard to the PFS, it made no difference whether the patient was receiving HT.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Endometrial carcinoma; Estrogen; Hormone replacement therapy; Hormone therapy; Overall survival; Progesterone; Prognosis; Risk factors

Risk, Prediction and Prevention of Hereditary Breast Cancer - Large-Scale Genomic Studies in Times of Big and Smart Data - Wunderle, Marius; Olmes, Gregor; Nabieva, Naiba; Häberle, Lothar; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Hack, Carolin; Erber, Ramona; Ekici, Arif Bülent; Hoyer, Juliane; Vasileiou, Georgia; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Over the last two decades genetic testing for mutations in BRCA1 and BRCA2 has become standard of care for women and men who are at familial risk for breast or ovarian cancer. Currently, genetic testing more often also includes so-called panel genes, which are assumed to be moderate-risk genes for breast cancer. Recently, new large-scale studies provided more information about the risk estimation of those genes. The utilization of information on panel genes with regard to their association with the individual breast cancer risk might become part of future clinical practice. Furthermore, large efforts have been made to understand the influence of common genetic variants with a low impact on breast cancer risk. For this purpose, almost 450 000 individuals have been genotyped for almost 500 000 genetic variants in the OncoArray project. Based on first results it can be assumed that - together with previously identified common variants - more than 170 breast cancer risk single nucleotide polymorphisms can explain up to 18% of familial breast cancer risk. The knowledge about genetic and non-genetic risk factors and its implementation in clinical practice could especially be of use for individualized prevention. This includes an individualized risk prediction as well as the individualized selection of screening methods regarding imaging and possible lifestyle interventions. The aim of this review is to summarize the most recent developments in this area and to provide an overview on breast cancer risk genes, risk prediction models and their utilization for the individual patient.
EVALuna2:34612

Role of Pelvic Lymph Node Resection in Vulvar Squamous Cell Cancer: A Subset Analysis of the AGO-CaRE-1 Study - Woelber, Linn; Bommert, Mareike; Harter, Philipp; Prieske, Katharina; zu Eulenburg, Christine; Jueckstock, Julia; Hilpert, Felix; de Gregorio, Nikolaus; Iborra, Severine; Sehouli, Jalid; Ignatov, Atanas; Hillemanns, Peter; et al. (Annals of Surgical Oncology, 2021)
Background: As the population at risk for pelvic nodal involvement remains poorly described, the role of pelvic lymphadenectomy (LAE) in vulvar squamous cell cancer (VSCC) has been a matter of discussion for decades. Methods: In the AGO-CaRE-1 study, 1618 patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB or higher primary VSCC treated at 29 centers in Germany between 1998 and 2008 were documented. In this analysis, only patients with pelvic LAE (n = 70) were analyzed with regard to prognosis and correlation between inguinal and pelvic lymph node involvement. Results: The majority of patients had T1b/T2 tumors (n = 47; 67.1%), with a median diameter of 40 mm (2–240 mm); 54/70 patients (77.1%) who received pelvic LAE had positive groin nodes. For 42 of these 54 patients, the number of affected groin nodes had been documented as a median of 3; 14/42 (33.3%) of these patients had histologically confirmed pelvic nodal metastases (median number of affected pelvic nodes 3 [1–12]). In these 14 patients, the median number of affected groin nodes was 7 (1–30), with a groin metastases median maximum diameter of 42.5 mm (12–50). Receiver operating characteristic analysis showed an area under the curve of 0.85, with 83.3% sensitivity and 92.6% specificity for the prediction of pelvic involvement in cases of six or more positive groin nodes. No cases of pelvic nodal involvement without groin metastases were observed. Prognosis in cases of pelvic metastasis was poor, with a median progression-free survival of only 12.5 months. Conclusion: For the majority of node-positive patients with VSCC, pelvic nodal staging appears unnecessary since a relevant risk for pelvic nodal involvement only seems to be present in highly node-positive disease.
CRIS-Team Scopus Importer:2021-04-02

rs2735383, located at a microRNA binding site in the 3'UTR of NBS1, is not associated with breast cancer risk - Liu, Jingjing; Loncar, Ivona; Collee, J. Margriet; Bolla, Manjeet K.; Dennis, Joe; Michailidou, Kyriaki; Wang, Qin; Andrulis, Irene L.; Barile, Monica; Beckmann, Matthias; Behrens, Sabine; Benitez, Javier; et al. (Scientific Reports, 2016)
NBS1, also known as NBN, plays an important role in maintaining genomic stability. Interestingly, rs2735383 G > C, located in a microRNA binding site in the 3'-untranslated region (UTR) of NBS1, was shown to be associated with increased susceptibility to lung and colorectal cancer. However, the relation between rs2735383 and susceptibility to breast cancer is not yet clear. Therefore, we genotyped rs2735383 in 1,170 familial non-BRCA1/2 breast cancer cases and 1,077 controls using PCR-based restriction fragment length polymorphism (RFLP-PCR) analysis, but found no association between rs2735383CC and breast cancer risk (OR = 1.214, 95% CI = 0.936-1.574, P = 0.144). Because we could not exclude a small effect size due to a limited sample size, we further analyzed imputed rs2735383 genotypes (r2 > 0.999) of 47,640 breast cancer cases and 46,656 controls from the Breast Cancer Association Consortium (BCAC). However, rs2735383CC was not associated with overall breast cancer risk in European (OR = 1.014, 95% CI = 0.969-1.060, P = 0.556) nor in Asian women (OR = 0.998, 95% CI = 0.905-1.100, P = 0.961). Subgroup analyses by age, age at menarche, age at menopause, menopausal status, number of pregnancies, breast feeding, family history and receptor status also did not reveal a significant association. This study therefore does not support the involvement of the genotype at NBS1 rs2735383 in breast cancer susceptibility.
EVALuna2:33244

rs495139 in the TYMS-ENOSF1 Region and Risk of Ovarian Carcinoma of Mucinous Histology - Kelemen, Linda E.; Earp, Madalene; Fridley, Brooke L.; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Ekici, Arif Bülent; Hein, Alexander; Lambrechts, Diether; Lambrechts, Sandrina; Van Nieuwenhuysen, Els; Vergote, Ignace; et al. (International Journal of Molecular Sciences, 2018)
Thymidylate synthase (TYMS) is a crucial enzyme for DNA synthesis. TYMS expression is regulated by its antisense mRNA, ENOSF1. Disrupted regulation may promote uncontrolled DNA synthesis and tumor growth. We sought to replicate our previously reported association between rs495139 in the TYMS-ENOSF1 3' gene region and increased risk of mucinous ovarian carcinoma (MOC) in an independent sample. Genotypes from 24,351 controls to 15,000 women with invasive OC, including 665 MOC, were available. We estimated per-allele odds ratios (OR) and 95% confidence intervals (CI) using unconditional logistic regression, and meta-analysis when combining these data with our previous report. The association between rs495139 and MOC was not significant in the independent sample (OR = 1.09; 95% CI = 0.97⁻1.22; p = 0.15; N = 665 cases). Meta-analysis suggested a weak association (OR = 1.13; 95% CI = 1.03⁻1.24; p = 0.01; N = 1019 cases). No significant association with risk of other OC histologic types was observed (p = 0.05 for tumor heterogeneity). In expression quantitative trait locus (eQTL) analysis, the rs495139 allele was positively associated with ENOSF1 mRNA expression in normal tissues of the gastrointestinal system, particularly esophageal mucosa (r = 0.51, p = 1.7 × 10-28), and nonsignificantly in five MOC tumors. The association results, along with inconclusive tumor eQTL findings, suggest that a true effect of rs495139 might be small.
EVALuna2:35118

S1 Guideline: Impairment of gonadal function after Cancer in Childhood and Adolescence - Borgmann-Staudt, Anja; Jantke, Andreas; Hinz, Stefan; Beckmann, Matthias; Dittrich, Ralf; Lotz, Laura; Balcerek, Magdalena (Klinische Pädiatrie, 2023)
A possible negative consequence of cancer treatment is the fertility impairment of young cancer survivors. However, most former patients express the wish to have biological children. Fertility-preserving measures are available and are - under certain circumstances - financed by health insurance. Separate information at the time of diagnosis and during follow-up care should be adapted to the individual risk and enable those affected to make a self-determined decision about cryopreservation of germ cells or germ cell tissue. Hyopgonadotropic hypogonadism can be treated by the pulsatile administration of gonadotropins. Affected individuals can be reassured. A health restriction of the offspring due to the cancer treatment is not to be expected, even after artificial insemination.
CRIS-Team Scopus Importer:2023-09-22
Keywords: childhood cancer; fertility impairment treatment; offspring health; patient education; self-determined decision

S3 guidelines on diagnostics and treatment of cervical cancer: Demands on pathology - Horn, L. -C.; Beckmann, Matthias; Follmann, M.; Koch, Matthias; Mallmann, P.; Marnitz, S.; Schmidt, D. (Pathologe, 2015)
Between 2011 and the end of 2014 the former consensus S2k guidelines for the diagnostics and treatment of cervical cancer were updated and upgraded to S3 level, methodologically based on the regulations of the German Cancer Society (DKG). The present article summarizes the relevant aspects for the sectioning, histopathological workup, diagnostics and reporting for the pathology of invasive cancer of the uterine cervix. The recommendations are based on the most recent World Health Organization (WHO) and TNM classification systems and consider the needs of the clinician for appropriate surgical and radiotherapeutic treatment of patients. Detailed processing rules of colposcopy-guided diagnostic biopsies, conization and trachelectomy as well as for radical hysterectomy specimens and lymph node resection (including sentinel lymph node resection) are given. In the guidelines deep stromal invasion in macroinvasive cervical cancer is defined for the first time as tumor infiltration of > 66% of the cervical stromal wall. Furthermore, morphological prognostic factors for microinvasive and macroinvasive cervical cancer are summarized.
EVALuna2:17602

S3 guidelines on the diagnosis and treatment of carcinoma of the endometrium : Requirements for pathology - Horn, L. -C.; Emons, G.; Aretz, Stefan; Bock, N.; Follmann, Markus; Lax, Sigurd F.; Nothacker, M.; Steiner, E.; Mayr, D.; Alt-Epping, Bernd; Aretz, Stefan; Bauerschmitz, Gerd; et al. (Pathologe, 2019)
The present article summarises the relevant aspects of the S3 guidelines on endometrioid carcinomas. The recommendations include the processing rules of fractional currettings as well as for hysterectomy specimens and lymph node resections (including sentinel lymph nodes). Besides practical aspects, the guidelines consider the needs of the clinicians for appropriate surgical and radiotherapeutic treatment of the patients. Carcinosarcomas are assigned to the endometrial carcinoma as a special variant. For the first time, an algorithmic approach for evaluation of the tumour tissue for Lynch syndrome is given. Prognostic factors based on morphologic findings are summarised.
EVALuna2:36536

Salivary and hair cortisol as biomarkers of emotional and behavioral symptoms in 6–9 year old children - Golub, Yulia; Kuitunen-Paul, Sören; Panaseth, Kerstin; Stonawski, Valeska; Frey, Stefan; Steigleder, Ruth; Grimm, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; et al. (Physiology & behavior, 2019)
The aim of the present work is to investigate the association of salivary and cumulative cortisol levels with emotional and behavioral symptoms in a Franconian Cognition and Emotion Studies (FRANCES) general population cohort of 158 6- to 9 year old children. Salivary cortisol values were measured by one-day diurnal cortisol profile, whereas cumulative cortisol was estimated via one-month hair cortisol concentrations (rHCC). Nearly all significant associations of clinical symptoms with child cortisol indices were age dependent: We report emotional symptoms being associated with lower rHCC in younger children (6.06–7.54 years). In older children (7.55–9.41 years) behavioral problems were further associated with higher rHCC and lower salivary cortisol awakening responses. In summary, child clinical symptoms were stronger associated with markers of hair cortisol compared to salivary cortisol. To picture developmental mechanisms, we suggest longitudinal designs for cortisol measures of stress systems in children and adolescents.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Behavioral symptoms; Emotional symptoms; FRANCES; Hair cortisol; HPA axis; Salivary cortisol

Saliva samples as a source of DNA for high throughput genotyping: an acceptable and sufficient means in improvement of risk estimation throughout mammographic diagnostics - Poehls, U. G.; Hack, Caroline; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Hübner, Hanna (European Journal of Medical Research, 2018)
BACKGROUND: Breast cancer screening programs seem to be an insufficient tool for women at high genetic risk for breast cancer. These women are not adequately monitored yet. Genetic testing may improve clearly the quality of breast cancer prevention programs. At present, blood samples are favored for obtaining high-quality DNA; however, DNA can also be obtained by collecting saliva. The aim of this study was, on the one hand, to determine whether saliva sampling is a practicable means to obtain sufficient quantity and quality of DNA and, on the other hand, whether it is accepted by patients throughout mammographic diagnostics. METHODS: 67 consecutive women with diagnostic need for mammography with or without a family history for breast cancer were asked for their basic willingness to undergo a genetic testing by saliva sample in addition to standard diagnostics. Saliva samples were analyzed in terms of DNA quantity and quality. RESULTS: 64 (95.6%) women agreed to provide a saliva sample; 3 of them denied participation. And even 63 out of 64 (98.4%) were interested in their specific results. 45 out of 64 samples contained a DNA concentration above 50 ng/µl, 12 samples were between 25 and 50 ng/µl and only 7 of them were under 25 ng/µl with the standard extraction procedure. CONCLUSION: A high number of patients seem to accept salvia samples as a risk assessment tool in breast diagnostics and are interested in their specific risk situation. At the same time, it could be demonstrated that it is an effective way to provide high-quality DNA for breast cancer gene analysis. However, it remains to be shown whether it would be possible to integrate it with the same acceptance in a nationwide breast cancer screening program.
EVALuna2:34632

Sarcoma of the Uterus. Guideline of the DGGG and OEGGG (S2k Level, AWMF Register Number 015/074, February 2019) - Denschlag, Dominik; Ackermann, Sven; Battista, Marco Johannes; Cremer, Wolfgang; Egerer, Gerlinde; Follmann, Markus; Haas, Heidemarie; Harter, Philipp; Hettmer, Simone; Horn, Lars Christian; Juhasz-Boess, Ingolf; Kast, Karin; et al. (Geburtshilfe und Frauenheilkunde, 2019)
Aims This is an official guideline published and coordinated by the German Society of Gynecology and Obstetrics (DGGG) and the Austrian Society of Gynecology and Obstetrics (OEGGG). Because of their rarity and heterogeneous histopathology, uterine sarcomas are challenging in terms of how they should be managed clinically, and treatment requires a multidisciplinary approach. To our knowledge, there are currently no binding evidence-based recommendations for the appropriate management of this heterogeneous group of tumors. Methods This S2k guideline was first published in 2015. The update published here is the result of the consensus of a representative interdisciplinary group of experts who carried out a systematic search of the literature on uterine sarcomas in the context of the guidelines program of the DGGG, OEGGG and SGGG. Members of the participating professional societies achieved a formal consensus after a moderated structured consensus process. Recommendations The consensus-based recommendations and statements include the epidemiology, classification, staging, symptoms, general diagnostic work-up and general pathology of uterine sarcomas as well as the genetic predisposition to develop uterine sarcomas. Also included are statements on the management of leiomyosarcomas, (low and high-grade) endometrial stromal sarcomas and undifferentiated uterine sarcomas and adenosarcomas. Finally, the guideline considers the follow-up and morcellation of uterine sarcomas and the information provided to patients.
CRIS-Team Scopus Importer:2019-11-05
Keywords: adenosarcoma; endometrial stromal sarcoma; leiomyosarcoma; morcellation; uterine sarcoma

Sarcoma of the UterusGuideline of the DGGG, OEGGG and SGGG (S2k-Level, AWMF Registry No. 015/074, April 2021) - Denschlag, Dominik; Ackermann, Sven; Battista, Marco Johannes; Cremer, Wolfgang; Egerer, Gerlinde; Fehr, Matthias; Follmann, Markus; Haase, Heidemarie; Harter, Philipp; Hettmer, Simone; Horn, Lars Christian; Juhasz-Boess, Ingolf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose This is an official guideline, published and coordinated by the Germany Society for Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG). Because of their rarity and heterogeneous histopathology, uterine sarcomas are challenging in terms of their clinical management and therefore require a multidisciplinary approach. To our knowledge, there are currently no binding evidence-based recommendations for the appropriate management of this heterogeneous group of tumors. Methods This S2k guideline was first published in 2015. The update published here is once again the result of the consensus of a representative interdisciplinary committee of experts who were commissioned by the Guidelines Committee of the DGGG to carry out a systematic search of the literature on uterine sarcomas. Members of the participating professional societies achieved a formal consensus after a structured consensus process. Recommendations 1.1 Epidemiology, classification, staging of uterine sarcomas. 1.2 Symptoms, general diagnostic workup, general pathology or genetic predisposition to uterine sarcomas. 2. Management of leiomyosarcomas. 3. Management of low-grade endometrial stromal sarcomas. 4. Management of high-grade endometrial stromal sarcoma and undifferentiated uterine sarcomas. 5. Management of adenosarcomas. 6. Rhabdomyosarcomas of the uterus in children and adolescents. 7. Follow-up of uterine sarcomas. 8. Management of morcellated uterine sarcomas. 9. Information provided to patients.
CRIS-Team Scopus Importer:2022-12-16
Keywords: adenosarcoma; endometrial stromal sarcoma; guideline; leiomyosarcoma; morcellation; uterine sarcoma

Sarcoma of the Uterus. Guideline of the DGGG (S2k-Level, AWMF Registry No. 015/074, August 2015) - Denschlag, D.; Thiel, F. C.; Ackermann, S.; Harter, P.; Juhasz-Boess, I.; Mallmann, P.; Strauss, H. -G.; Ullrich, U.; Horn, L. -C.; Schmidt, D.; Vordermark, D.; Vogl, T.; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Purpose: Official guideline published and coordinated by the German Society of Gynecology and Obstetrics (DGGG). Due to their rarity and their heterogeneous histopathology uterine sarcomas remain challenging tumors to manage and need a multidisciplinary approach. To our knowledge so far there is no evidence-based guideline on the appropiate management of these heterogeneous tumors. Methods: This S2k-guideline is the work of an representative committee of experts from a variety of different professions who were commissioned by the DGGG to carry out a systematic literature review of uterine sarcoma. Members of the participating scientific societies developed a structured consensus in a formal procedure. Recommendations: 1. The incidence and histopathologic classification of uterine sarcoma. 2. The clinical manifestations, diagnosis and staging of uterine sarcoma. 3. The management of leiomyosarcoma. 4. The management of endometrial stromal sarcoma and undifferentiated uterine sarcoma. 5. The management of adenosarcoma as well as carcinosarcomas. 6. The management of morcellated uterine sarcoma.
EVALuna2:17600

SARS-CoV-2 Infection in Pregnancy - a Review of the Current Literature and Possible Impact on Maternal and Neonatal Outcome - Stumpfe, Florian; Titzmann, Adriana; Schneider, Michael; Stelzl, Patrick; Kehl, Sven; Fasching, Peter; Beckmann, Matthias; Enßer, Armin (Geburtshilfe und Frauenheilkunde, 2020)
In December 2019, cases of pneumonia of unknown cause first started to appear in Wuhan in China; subsequently, a new coronavirus was soon identified as the cause of the illness, now known as Coronavirus Disease 2019 (COVID-19). Since then, infections have been confirmed worldwide in numerous countries, with the number of cases steadily rising. The aim of the present review is to provide an overview of the new severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2) and, in particular, to deduce from it potential risks and complications for pregnant patients. For this purpose, the available literature on cases of infection in pregnancy during the SARS epidemic of 2002/2003, the MERS (Middle East respiratory syndrome) epidemic ongoing since 2012, as well as recent publications on cases infected with SARS-CoV-2 in pregnancy are reviewed and reported. Based on the literature available at the moment, it can be assumed that the clinical course of COVID-19 disease may be complicated by pregnancy which could be associated with a higher mortality rate. It may also be assumed at the moment that transmission from mother to child in utero is unlikely. Breastfeeding is possible once infection has been excluded or the disease declared cured.
CRIS-Team Scopus Importer:2020-05-19
Keywords: 2019-nCoV; coronavirus; COVID-19; pregnancy; SARS-CoV-2

Sebaceous breast carcinoma: report of a rare histological special subtype - Wachter, David; Rauh, C.; Wenkel, Evelyn; Fasching, Peter; Beckmann, Matthias; Hartmann, Arndt (Pathologe, 2014)
We report on a case of sebaceous carcinoma of the breast as a rare histological special subtype of breast cancer. Because these tumors are uncommon, differential diagnostic considerations and the exclusion of Muir-Torre syndrome are emphasized. Finally possible mechanisms of development and therapeutic strategies for this carcinoma are discussed.
EVALuna2:6578

Selective expression of sense and antisense transcripts of the sushi-ichi-related retrotransposon - derived family during mouse placentogenesis - Henke, Christine; Strissel, Pamela; Schubert, Maria-Theresa; Mitchell, Megan; Stolt, Claus; Faschingbauer, Florian; Beckmann, Matthias; Strick, Reiner (Retrovirology, 2015)
LTR-retrotransposons became functional neogenes through evolution by acquiring promoter sequences, regulatory elements and sequence modification. Mammalian retrotransposon transcripts (Mart1-9), also called sushi-ichi-related retrotransposon-homolog (SIRH) genes, are a class of Ty3/gypsy LTR-retroelements showing moderate homology to the sushi-ichi LTR-retrotransposon in pufferfish. Rtl1/Mart1 and Peg10/Mart2 expression in mouse placenta and demonstration of their functional roles during placental development exemplifies their importance in cellular processes. In this study, we analyzed all eleven mouse Mart genes from the blastocyst stage and throughout placentogenesis in order to gain information about their expression and regulation.Quantitative PCR, in situ hybridization (ISH) and immunoblotting showed various expression patterns of the 11 mouse Mart genes through different placental stages. Zcchc5/Mart3, Zcchc16/ Mart4 and Rgag1/Mart9 expression was undetectable. Rtl1/Mart1, Peg10/Mart2, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a gene expression was very low at the blastocyst stage. Later placental stages showed an increase of expression for Rtl1/Mart1, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a, the latter up to 1,489 molecules/ng cDNA at E9.5. From our recently published findings Peg10/Mart2 was the most highly expressed Mart gene. ISH demonstrated sense and antisense transcript co-localization of Rgag4/Mart5 to Cxx1a,b,c/Mart8b,c,a in trophoblast subtypes at the junctional zone, with an accumulation of antisense transcripts in the nuclei. To validate these results, we developed a TAG-aided sense/antisense transcript detection (TASA-TD) method, which verified sense and antisense transcripts for Rtl1/Mart1, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a. Except for Rtl1/Mart1 and Cxx1a,b/Mart8b,c all other Mart genes showed a reduced amount of antisense transcripts. Northern blot and 5' and 3' RACE confirmed both sense and antisense transcripts for Ldoc1/Mart7 and Cxx1a,b,c/Mart8b,c,a. Immunoblotting demonstrated a single protein throughout all placental stages for Ldoc1/Mart7, but for Cxx1a,b,c/Mart8b,c,a a switch occurred from a 57 kDa protein at E10.5 and E14.5 to a 25 kDa protein at E16.5 and E18.5.RNA and protein detection of mouse Mart genes support neo-functionalization of retrotransposons in mammalian genomes. Undetectable expression of Zcchc5/Mart3, Zcchc16/Mart4 and Rgag1/Mart9 indicate no role during mouse placentogenesis. Rgag4/Mart5 to Cxx1a,b,c/Mart8b,c,a gene expression support a role for differentiation from the ectoplacental cone. Mart antisense transcripts and protein alterations predict unique and complex molecular regulation in a time directed manner throughout mouse placentogenesis.
EVALuna2:4979

Selective isolation and characterization of primary cells from normal breast and tumors reveal plasticity of adipose derived stem cells - Weigand, Annika; Boos, Anja; Tasbihi, Kereshmeh; Beier, Justus; Dalton, Paul D.; Schrauder, Michael; Horch, Raymund E.; Beckmann, Matthias; Strissel, Pamela; Strick, Reiner (Breast Cancer Research, 2016)
There is a need to establish more cell lines from breast tumors in contrast to immortalized cell lines from metastatic effusions in order to represent the primary tumor and not principally metastatic biology of breast cancer. This investigation describes the simultaneous isolation, characterization, growth and function of primary mammary epithelial cells (MEC), mesenchymal cells (MES) and adipose derived stem cells (ADSC) from four normal breasts, one inflammatory and one triple-negative ductal breast tumors.A total of 17 cell lines were established and gene expression was analyzed for MEC and MES (n = 42) and ADSC (n = 48) and MUC1, pan-KRT, CD90 and GATA-3 by immunofluorescence. DNA fingerprinting to track cell line identity was performed between original primary tissues and isolates. Functional studies included ADSC differentiation, tumor MES and MEC invasion co-cultured with ADSC-conditioned media (CM) and MES adhesion and growth on 3D-printed scaffolds.Comparative analysis showed higher gene expression of EPCAM, CD49f, CDH1 and KRTs for normal MEC lines; MES lines e.g. Vimentin, CD10, ACTA2 and MMP9; and ADSC lines e.g. CD105, CD90, CDH2 and CDH11. Compared to the mean of all four normal breast cell lines, both breast tumor cell lines demonstrated significantly lower ADSC marker gene expression, but higher expression of mesenchymal and invasion gene markers like SNAI1 and MMP2. When compared with four normal ADSC differentiated lineages, both tumor ADSC showed impaired osteogenic and chondrogenic but enhanced adipogenic differentiation and endothelial-like structures, possibly due to high PDGFRB and CD34. Addressing a functional role for overproduction of adipocytes, we initiated 3D-invasion studies including different cell types from the same patient. CM from ADSC differentiating into adipocytes induced tumor MEC 3D-invasion via EMT and amoeboid phenotypes. Normal MES breast cells adhered and proliferated on 3D-printed scaffolds containing 20 fibers, but not on 2.5D-printed scaffolds with single fiber layers, important for tissue engineering.Expression analyses confirmed successful simultaneous cell isolations of three different phenotypes from normal and tumor primary breast tissues. Our cell culture studies support that breast-tumor environment differentially regulates tumor ADSC plasticity as well as cell invasion and demonstrates applications for regenerative medicine.
EVALuna2:15613

Self-reported Improvement in Side Effects and Quality of Life With Integrative Medicine in Breast Cancer Patients - Hack, Carolin; Hackl, Janina; Huettner, Nina B. M.; Langemann, Hanna; Schwitulla, Judith; Dietzel-Drentwett, Svenja; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Integrative Cancer Therapies, 2018)
PURPOSE: Although the demand from patients for integrative medicine is increasing, complementary medicine services are still quite heterogeneous and have not been incorporated into clinical routine. The aim of this study was to systematically evaluate improvements in side effects and quality of life associated with a hospital-based integrative medicine program in the modern breast cancer patient care setting. METHODS: In a cross-sectional study, integrative health counseling and treatment were evaluated in women with breast cancer. Over a 15-month period, data for 75 patients from an integrative medicine consultancy service with standardized operating procedures were collected at the University Breast Center for Franconia. At baseline, the patients answered a questionnaire on their medical history, symptoms, and the treatment goals they were hoping to achieve with integrative medicine. In the follow-up, patient-reported outcomes related to side effects of conventional cancer treatment and patients' quality of life were analyzed. RESULTS: Among 60 patients with the therapy goal of reducing the side effects of conventional treatment, 46 (76.7%) were successful. Among 57 patients hoping to improve disease-related quality of life, 46 (82%) reported success. Whereas patients with metastatic disease achieved a reduction in the side effects of conventional therapy, quality-of-life improvements were predominantly achieved by patients with a good treatment prognosis. CONCLUSIONS: Breast cancer patients benefit from the counseling and treatment provided with integrative medicine in all phases of tumor disease. Integrative treatment services should be included as part of patient care in clinical routine work to offer patients the maximum quality of care and safety with complementary therapies.
EVALuna2:209953

Semi-automated delineation of breast cancer tumors and subsequent materialization using three-dimensional printing (rapid prototyping) - Schulz-Wendtland, Rüdiger; Harz, Markus; Meier-Meitinger, Martina; Brehm, Barbara; Wacker, Till; Hahn, Horst K.; Wagner, Florian; Wittenberg, Thomas; Beckmann, Matthias; Uder, Michael; Fasching, Peter; Emons, Julius (Journal of Surgical Oncology, 2017)
Three-dimensional (3D) printing has become widely available, and a few cases of its use in clinical practice have been described. The aim of this study was to explore facilities for the semi-automated delineation of breast cancer tumors and to assess the feasibility of 3D printing of breast cancer tumors.In a case series of five patients, different 3D imaging methods-magnetic resonance imaging (MRI), digital breast tomosynthesis (DBT), and 3D ultrasound-were used to capture 3D data for breast cancer tumors. The volumes of the breast tumors were calculated to assess the comparability of the breast tumor models, and the MRI information was used to render models on a commercially available 3D printer to materialize the tumors.The tumor volumes calculated from the different 3D methods appeared to be comparable. Tumor models with volumes between 325 mm(3) and 7,770 mm(3) were printed and compared with the models rendered from MRI. The materialization of the tumors reflected the computer models of them.3D printing (rapid prototyping) appears to be feasible. Scenarios for the clinical use of the technology might include presenting the model to the surgeon to provide a better understanding of the tumor's spatial characteristics in the breast, in order to improve decision-making in relation to neoadjuvant chemotherapy or surgical approaches. J. Surg. Oncol. 2017;115:238-242. © 2016 Wiley Periodicals, Inc.
EVALuna2:14618

Shared genetics underlying epidemiological association between endometriosis and ovarian cancer - Lu, Yi; Cuellar-Partida, Gabriel; Painter, Jodie N.; Nyholt, Dale R.; Morris, Andrew P.; Fasching, Peter A.; Hein, Alexander; Burghaus, Stefanie; Beckmann, Matthias; Lambrechts, Diether; Van Nieuwenhuysen, Els; Vergote, Ignace; et al. (Human Molecular Genetics, 2015)
Epidemiological studies have demonstrated associations between endometriosis and certain histotypes of ovarian cancer, including clear cell, low-grade serous and endometrioid carcinomas. We aimed to determine whether the observed associations might be due to shared genetic aetiology. To address this, we used two endometriosis datasets genotyped on common arrays with full-genome coverage (3194 cases and 7060 controls) and a large ovarian cancer dataset genotyped on the customized Illumina Infinium iSelect (iCOGS) arrays (10 065 cases and 21 663 controls). Previous work has suggested that a large number of genetic variants contribute to endometriosis and ovarian cancer (all histotypes combined) susceptibility. Here, using the iCOGS data, we confirmed polygenic architecture for most histotypes of ovarian cancer. This led us to evaluate if the polygenic effects are shared across diseases. We found evidence for shared genetic risks between endometriosis and all histotypes of ovarian cancer, except for the intestinal mucinous type. Clear cell carcinoma showed the strongest genetic correlation with endometriosis (0.51, 95% CI = 0.18-0.84). Endometrioid and low-grade serous carcinomas had similar correlation coefficients (0.48, 95% CI = 0.07-0.89 and 0.40, 95% CI = 0.05-0.75, respectively). High-grade serous carcinoma, which often arises from the fallopian tubes, showed a weaker genetic correlation with endometriosis (0.25, 95% CI = 0.11-0.39), despite the absence of a known epidemiological association. These results suggest that the epidemiological association between endometriosis and ovarian adenocarcinoma may be attributable to shared genetic susceptibility loci.
EVALuna2:17569

Shared heritability and functional enrichment across six solid cancers - Jiang, Xia; Finucane, Hilary K.; Schumacher, Fredrick R.; Schmit, Stephanie L.; Tyrer, Jonathan P.; Han, Younghun; Michailidou, Kyriaki; Lesseur, Corina; Kuchenbaecker, Karoline B.; Dennis, Joe; Conti, David V.; Casey, Graham; et al. (Nature Communications, 2019)
Quantifying the genetic correlation between cancers can provide important insights into the mechanisms driving cancer etiology. Using genome-wide association study summary statistics across six cancer types based on a total of 296,215 cases and 301,319 controls of European ancestry, here we estimate the pair-wise genetic correlations between breast, colorectal, head/neck, lung, ovary and prostate cancer, and between cancers and 38 other diseases. We observed statistically significant genetic correlations between lung and head/neck cancer (r g = 0.57, p = 4.6 × 10 −8 ), breast and ovarian cancer (r g = 0.24, p = 7 × 10 −5 ), breast and lung cancer (r g = 0.18, p =1.5 × 10 −6 ) and breast and colorectal cancer (r g = 0.15, p = 1.1 × 10 −4 ). We also found that multiple cancers are genetically correlated with non-cancer traits including smoking, psychiatric diseases and metabolic characteristics. Functional enrichment analysis revealed a significant excess contribution of conserved and regulatory regions to cancer heritability. Our comprehensive analysis of cross-cancer heritability suggests that solid tumors arising across tissues share in part a common germline genetic basis.
CRIS-Team Scopus Importer:2019-05-02

Shifting cancer care towards Multidisciplinarity: the cancer center certification program of the German cancer society - Kowalski, Christoph; Graeven, Ullrich; Von Kalle, Christof; Lang, Hauke; Beckmann, Matthias; Blohmer, Jens-Uwe; Burchardt, Martin; Ehrenfeld, Michael; Fichtner, Jan; Grabbe, Stephan; Hoffmann, Hans; Iro, Heinrich; et al. (BMC Cancer, 2017)
BACKGROUND: Over the last decades numerous initiatives have been set up that aim at translating the best available medical knowledge and treatment into clinical practice. The inherent complexity of the programs and discrepancies in the terminology used make it difficult to appreciate each of them distinctly and compare their specific strengths and weaknesses. To allow comparison and stimulate dialogue between different programs, we in this paper provide an overview of the German Cancer Society certification program for multidisciplinary cancer centers that was established in 2003. MAIN BODY: In the early 2000s the German Cancer Society assessed the available information on quality of cancer care in Germany and concluded that there was a definite need for a comprehensive, transparent and evidence-based system of quality assessment and control. This prompted the development and implementation of a voluntary cancer center certification program that was promoted by scientific societies, health-care providers, and patient advocacy groups and based on guidelines of the highest quality level (S3). The certification system structures the entire process of care from prevention to screening and multidisciplinary treatment of cancer and places multidisciplinary teams at the heart of this program. Within each network of providers, the quality of care is documented using tumor-specific quality indicators. The system started with breast cancer centers in 2003 and colorectal cancer centers in 2006. In 2017, certification systems are established for the majority of cancers. Here we describe the rationale behind the certification program, its history, the development of the certification requirements, the process of data collection, and the certification process as an example for the successful implementation of a voluntary but powerful system to ensure and improve quality of cancer care. CONCLUSION: Since 2003, over 1 million patients had their primary tumors treated in a certified center. There are now over 1200 sites for different tumor entities in four countries that have been certified in accordance with the program and transparently report their results from multidisciplinary treatment for a substantial proportion of cancers. This led to a fundamental change in the structure of cancer care in Germany and neighboring countries within one decade.
EVALuna2:33190

Shifts in Macrophage as a prognostic Biomarker in Patients with luminal Breast Cancer - A Confirmatory Study - Schnellhardt, Sören; Segelhorst, Sarah; Erber, Ramona; Daniel, Christoph; Hartmann, Arndt; Fasching, Peter; Beckmann, Matthias; Fietkau, Rainer; Distel, Luitpold; Rübner, Matthias (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Short Report on the Commission Work Financing Commission - successful work continues! - Renner, Stefan; Wallwiener, Diethelm; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:32993

Should Breast Cancer Surgery Be Done in an Outpatient Setting?: Health Economics From the Perspective of Service Providers - Formago, Margaret; Schrauder, Michael G.; Rauh, Claudia; Hack, Carolin; Jud, Sebastian; Hildebrandt, Thomas; Schulz-Wendtland, Rüdiger; Frentz, S.; Graubert, S.; Beckmann, Matthias; Lux, Michael P. (Geburtshilfe und Frauenheilkunde, 2017)
INTRODUCTION: The care of patients with breast cancer is extremely complex and requires interdisciplinary care in certified facilities. These specialized facilities provide numerous services without being correspondingly remunerated. The question whether breast cancer surgery should be performed in an outpatient setting to reduce costs is increasingly being debated. This study compares inpatient surgical treatment with a model of the same surgery performed on an outpatient basis to examine the potential financial impact. MATERIAL AND METHODS: A theoretical model was developed and the DRG fees for surgical interventions to treat primary breast cancer were calculated. A theoretical 1-day DRG was then calculated to permit comparisons with outpatient procedures. The costs of outpatient surgery were calculated based on the remuneration rates of the AOP (Outpatient Surgery) Contract and the EBM (Uniform Assessment Scale) and compared to the costs of the 1-day DRG. RESULTS: The DRG fee for both breast-conserving surgery and mastectomy is higher than the fee paid in the context of the EBM system, although the same procedures were carried out in both systems. If a hospital were to carry out breast-conserving surgery as an outpatient procedure, the fee would be € 1313.81; depending on the type of surgery, the hospital would therefore only receive between 39.20% and 52.82% of the DRG fee. This was the case even for a 1-day treatment. Compared to the real DRG fees the difference would be even more striking. CONCLUSION: Carrying out breast cancer surgery as an outpatient procedure would result in a significant shortfall of revenues. Additional services from certified centers, such as the interdisciplinary planning of treatment, psycho-oncological and social-medical care with the involvement of relatives, detailed documentation, etc., which are currently provided without surcharge or adequate remuneration, could no longer be maintained. The quality of processes and excellent results which have been achieved and ultimately the care given by certified facilities would be significantly at risk.
EVALuna2:34710

Signal decomposition for X-ray dark-field imaging - Käppler, Sebastian; Bayer, Florian; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Beckmann, Matthias; Fasching, Peter; Hartmann, Arndt; Heindl, Felix; Michel, Thilo; Oezguel, Gueluemser; et al. (MICCAI 2014, 2014)
Grating-based X-ray dark-field imaging is a new imaging modality. It allows the visualization of structures at micrometer scale due to small-angle scattering of the X-ray beam. However, reading darkfield images is challenging as absorption and edge-diffraction effects also contribute to the dark-field signal, without adding diagnostic value. In this paper, we present a novel–and to our knowledge the first–algorithm for isolating small-angle scattering in dark-field images, which greatly improves their interpretability. To this end, our algorithm utilizes the information available from the absorption and differential phase images to identify clinically irrelevant contributions to the dark-field image. Experimental results on phantom and ex-vivo breast data promise a greatly enhanced diagnostic value of dark-field image
EVALuna2:6632

Simultaneous amniotic membrane patch in high-risk keratoplasty - Seitz, Berthold; Das, Sujata; Sauer, Rolf; Hofmann-Rummelt, Carmen; Beckmann, Matthias; Kruse, Friedrich (Cornea, 2011)
To analyze the short- and intermediate-term results of simultaneous transplantation of amniotic membrane with high-risk keratoplasty.Between January 2002 and February 2004, a simultaneous amniotic membrane patch was transplanted with penetrating keratoplasty in 16 eyes of 16 patients. In 13 eyes, a soft contact lens was applied afterward. Corneal perforation was present in 10 of 14 eyes with emergency keratoplasty. Five patients received systemic immunosuppressive medication for 4-6 months after penetrating keratoplasty.The amniotic membrane patch fell off after 8 ± 3 (range: 4-14) days without residual tissue except in 1 case. In 15 of 16 eyes, the epithelium was completely closed after 10 ± 8 (range: 4-30) days. In 3 eyes, recurrence of the epithelial defect occurred after 3-6 months. During a follow-up period of 18 ± 6 months, 13 of 16 corneal grafts were clear.Simultaneous amniotic membrane transplantation and penetrating keratoplasty may improve the prognosis of corneal graft in eyes with risk of epithelial healing problems.
EVALuna2:17178

Single deepest vertical pocket or amniotic fluid index as evaluation test for predicting adverse pregnancy outcome (SAFE trial): a multicenter, open-label, randomized controlled trial - Kehl, Sven; Schelkle, A.; Thomas, A.; Puhl, A.; Meqdad, K.; Tuschy, B.; Berlit, S.; Weiss, C.; Bayer, C.; Heimrich, J.; Dammer, U.; Raabe, E.; et al. (Ultrasound in Obstetrics & Gynecology, 2016)
OBJECTIVE: To determine whether the amniotic fluid index (AFI) or the single deepest vertical pocket (SDP) technique for estimating amniotic fluid volume is superior for predicting adverse pregnancy outcome. METHODS: This was a multicenter randomized controlled trial including 1052 pregnant women with a term singleton pregnancy across four hospitals in Germany. Women were assigned randomly, according to a computer-generated allocation sequence, to AFI or SDP measurement for estimation of amniotic fluid volume. Oligohydramnios was defined as AFI ≤ 5 cm or the absence of a pocket measuring at least 2 × 1 cm. The diagnosis of oligohydramnios was followed by labor induction. The primary outcome measure was postpartum admission to a neonatal intensive care unit. Further outcome parameters were the rates of diagnosis of oligohydramnios and induction of labor (for oligohydramnios or without specific indication), and mode of delivery. RESULTS: Postpartum admission to a neonatal intensive care unit was similar between groups (4.2% (n = 21) vs 5.0% (n = 25); relative risk (RR), 0.85 (95% CI, 0.48-1.50); P = 0.57). In the AFI group, there were more cases of oligohydramnios (9.8% (n = 49) vs 2.2% (n = 11); RR, 4.51 (95% CI, 2.2-8.57); P < 0.01) and more cases of labor induction for oligohydramnios (12.7% (n = 33) vs 3.6% (n = 10); RR, 3.50 (95% CI, 1.76-6.96); P < 0.01) than in the SDP group. Moreover, an abnormal cardiotocography was seen more often in the AFI group than in the SDP group (32.3% (n = 161) vs 26.2% (n = 132); RR, 1.23 (95% CI, 1.02-1.50); P = 0.03). The other outcome measures were not significantly different between the two groups. CONCLUSIONS: Use of the AFI method increased the rate of diagnosis of oligohydramnios and labor induction for oligohydramnios without improving perinatal outcome. The SDP method is therefore the favorable method to estimate amniotic fluid volume, especially in a population with many low-risk pregnancies. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.
EVALuna2:32976

Single Deepest Vertical Pocket or Amniotic Fluid Index as Evaluation Test for Predicting Adverse Pregnancy Outcome (SAFE Trial): A Multicenter, Open-Label, Randomized Controlled Trial EDITORIAL COMMENT - Kehl, Sven; Schelkle, A.; Thomas, A.; Puhl, A.; Meqdad, K.; Tuschy, B.; Berlit, S.; Weiss, C.; Bayer, C.; Heimrich, J.; Dammer, U.; Raabe, E.; et al. (Obstetrical & Gynecological Survey, 2016)
One of the important aspects of fetal well-being assessment is amniotic fluid volume, lack of which leads to oligohydramnios and consequently adverse perinatal outcomes. Amniotic fluid estimation by ultrasound can be performed by assessment of the amniotic fluid index (AFI) or the single deepest vertical pocket (SDP) technique. This study aimed to investigate the best technique for amniotic fluid volume estimation to predict adverse pregnancy outcomes in both high-and low-risk pregnancies. In a randomized controlled trial (RCT), participants from 4 hospitals in Germany were allocated randomly to AFI or SDP measurement (1: 1). Oligohydramnios was defined by an AFI 5 cm or less or by the absence of an SDP measuring less than 2 x 1 cm. The primary outcome measure was admission to a neonatal intensive care unit (NICU) following childbirth, and other outcome measures included perinatal death, oligohydramnios, labor induction (for oligohydramnios or without specific indication), umbilical artery pH less than 7.10, 5-minute Apgar score of less than 7, meconium-stained amniotic fluid, abnormal cardiotocography, need for fetal scalp blood sampling, assisted vaginal delivery (for fetal distress or without specified indication), and cesarean delivery (for and without fetal distress). Statistical analyses were performed using the Student t test, Mann-Whitney U test,.2 test, or Fisher exact test and a logistic regression analysis or a 2-way analysis of variance. There were fewer women with gestational diabetes and a previous cesarean delivery in the AFI group among the 1002 women analyzed. Women with a high-risk pregnancy were older, shorter, and more overweight than women with a low-risk pregnancy. Postnatal admission rates to the NICU (4.2% vs 5%; relative risk [ RR], 0.85; 95% confidence interval [ CI], 0.481.50) and rate of arterial pH less than 7.10 were similar between the 2 groups (1.6% vs 3%; RR, 0.54; 95% CI, 0.23-1.26). There weremore participants with oligohydramnios (9.8% vs 2.2%; RR, 4.51; 95% CI, 2.37-8.57), more labor inductions for oligohydramnios (12.7% vs 3.6%; RR, 3.50; 95% CI, 1.76-6.96), and higher occurrences of abnormal cardiotocography (32.3% vs 26.2%; RR, 1.23; 95% CI, 1.02-1.50) in the AFI group than in the SDP group. More cases of oligohydramnios and labor inductions for oligohydramnios were found in low-risk pregnancies measured by the AFI method than by the SDP technique, and a lower arterial pH was observed in the AFI group compared with the SDP group in high-risk pregnancies. The AFI technique increased the diagnosis rate of oligohydramnios without improvement in perinatal outcome; hence, the SDP technique is preferred over AFI especially in low-risk pregnancies.
EVALuna2:32953

Single nucleotide polymorphism D1853N of the ATM gene may alter the risk for breast cancer - Schrauder, M.; Frank, S.; Strissel, Pamela; Lux, Michael P.; Bani, Mayada; Rauh, C.; Sieber, Cornel; Heusinger, K.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strick, Reiner; Beckmann, Matthias; et al. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose Various ATM (ataxia telangiectasia-mutated) mutations and polymorphisms have been reported to be associated with an increased breast cancer risk. Recent studies have produced contradictory results regarding the association between ATM genetic variants and breast cancer risk.Materials and methods The common ATM polymorphism 5557G > A (p.D1853N) (rs1801516), previously suggested to be associated with bilateral breast cancer, was analyzed using real-time PCR in 514 unselected patients with breast cancer and 511 age-matched healthy control individuals. DNA was obtained from peripheral blood draw.Results The ATM genotype was weakly associated with the risk for breast cancer (P = 0.04 for the overall test). The odds ratio for women with a heterozygous genotype was 0.70 (95% CI, 0.52-0.94) and for the homozygous variant 0.63 (95% CI, 0.27-1.49). Disease-free survival and overall survival showed no significant association with specific genotypes.Conclusions The results of this study might suggest a minor association between polymorphism 5557G > A and a reduced risk of breast cancer.
Keywords: TM gene variants; polymorphism; breast cancer; DNA damage; epidemiology; association

Smartphone-Based Colorimetric Analysis of Urine Test Strips for At-Home Prenatal Care - Flaucher, Madeleine; Nissen, Michael; Jäger, Katharina; Titzmann, Adriana; Pontones, Constanza; Hübner, Hanna; Fasching, Peter; Beckmann, Matthias; Gradl, Stefan; Eskofier, Björn (IEEE Journal of Translational Engineering in Health and Medicine, 2022)
Objective: Clinical urine tests are a key component of prenatal care. As of now, urine test strips are evaluated through a time consuming, often error-prone and operator-dependent visual color comparison of test strips and reference cards by medical staff. Methods and procedures: This work presents an automated pipeline for urinalysis with urine test strips using smartphone camera images in home environments, combining several image processing and color combination techniques. Our approach is applicable to off-the-shelf test strips in home conditions with no additional hardware required. For development and evaluation of our pipeline we collected image data from two sources: i) A user study (26 participants, 150 images) and ii) a lab study (135 images). Results: We trained a region-based convolutional neural network that is able to detect the urine test strip location and orientation in images with a wide variety of light conditions, backgrounds and perspectives with an accuracy of 85.5%. The reference card can be robustly detected through a feature matching approach in 98.6% of the images. Color comparison by Hue channel (0.81 F1-Score), Matching factor (0.80 F1-Score) and Euclidean distance (0.70 F1-Score) were evaluated to determine the urinalysis results. Conclusion: We show that an automated smartphone-based colorimetric analysis of urine test strips in a home environment is feasible. It facilitates examinations and provides the possibility to shift care into an at-home environment. Clinical impact: The findings demonstrate that routine urine examinations can be transferred into the home environment using a smartphone. Simultaneously, human error is avoided, accuracy is increased and medical staff is relieve

Smart sensing in pregnancy: a survey-based evaluation of readiness to use wearable sensory applications in prenatal care - Weidenthaler, Filip; Danzberger, Nina; Pontones, Constanza; Titzmann, Adriana; Hein, Alexander; Beckmann, Matthias; Fasching, Peter; Huebner, H. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Socioeconomic status and depression during and after pregnancy in the Franconian Maternal Health Evaluation Studies (FRAMES) - Hein, Alexander; Rauh, Claudia; Engel, Anne; Häberle, Lothar; Dammer, Ulf; Voigt, Franziska; Fasching, Peter; Faschingbauer, Florian; Burger, Pascal; Beckmann, Matthias; Kornhuber, Johannes; Goecke, Tamme W. (Archives of Gynecology and Obstetrics, 2014)
Depression during and after pregnancy can have a negative impact on women's quality of life and on the development of the newborn child. Interventions have been shown to have a positive influence on both mothers and children. Predictive factors for depressive symptoms might possibly be able to identify groups that are at high risk. The aim of this study was to investigate the value of socioeconomic factors in predicting depressive symptoms during and after pregnancy.Depressiveness was measured using the German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) at three time-points, in a prospective cohort study (n = 1,100). Visit 1 (Q1) was at study entry in the third trimester of the pregnancy, visit 2 (Q2) was shortly after birth, and visit 3 (Q3) was 6-8 months after birth. Depression scores were associated with socioeconomic factors and time in linear mixed models.Parity status, education status, monthly income, residential property status, and partnership status, as well as interactions between them, were found to be predictive factors for EPDS scores. The strongest factor influencing depressive symptoms was partnership status. Women who did not have an intact partnership had EPDS scores that were on average four points higher than in women with a partner at all three study visits (P < 0.000001).Socioeconomic factors define subgroups that have different depression scores during and after pregnancy. Partnership status appears to be one of the most important influencing factors and could be useful for identifying women who should be offered an intervention to prevent possible negative effects on the mother or child.
EVALuna2:17434

Sonographic weight estimation in fetal macrosomia: influence of the time interval between estimation and delivery - Faschingbauer, Florian; Dammer, U.; Raabe, E.; Schneider, M.; Faschingbauer, Cornelia; Schmid, M.; Mayr, Andreas; Schild, R. L.; Beckmann, Matthias; Kehl, Sven (Archives of Gynecology and Obstetrics, 2015)
To evaluate the influence of the time interval between examination and delivery on the accuracy of sonographic weight estimation (WE) in fetal macrosomia.896 singleton pregnancies (birth weight > 4,000 g) with a total of 1,281 sonographic weight estimations were included in this retrospective cohort study. Fetuses were divided into six groups with regard to the time interval between estimation and delivery: group 1: scan-to-delivery interval: 0 days; group 2: scan-to-delivery interval: 1-3 days; group 3: scan-to-delivery interval: 4-7 days; group 4: scan-to-delivery interval: 8-14 days; group 5: scan-to-delivery interval: 15-21 days; group 6: scan-to-delivery interval: 22-42 days. The accuracy of WE was compared between five commonly used formulas using means of percentage errors (MPE), random error, medians of absolute percentage errors (MAPE), and proportions of estimates within 10 % of actual birth weight.Significant differences were found between the time interval groups with regard to MAPE and MPE values (p < 0.001). All formulas showed a systematic underestimation of fetal weight (negative MPEs) (p < 0.05). MPE values were closest to zero in time interval group 1 and 2. From group 3 to 6, a continuous decrease was observed. The lowest MAPE was found with the Merz formula in group 1 and 2. Values increased continuously from group 3 to 6. Differences between time interval group one and three did not reach statistical significance.WE in fetal macrosomia shows the best results when examinations are performed within 7 days before delivery, using the formula of Merz et al. Accuracy significantly decreases after this time period.
EVALuna2:5469

Sonographic Weight Estimation in Small-for-Gestational-Age Fetuses - Dammer, U.; Raabe, E.; Kehl, Sven; Schmid, M.; Mayr, Andreas; Schild, R. L.; Beckmann, Matthias; Faschingbauer, Florian (Ultraschall in der Medizin, 2015)
Purpose: To determine the accuracy of sonographic weight estimation (WE) for small-for-gestational-age (SGA) fetuses, and to further differentiate the evaluation between symmetric and asymmetric SGA fetuses. Materials and Methods: The accuracy of WE in SGA fetuses (n = 898) was evaluated using 14 sonographic models and was further differentiated between symmetric (n = 750) and asymmetric (n = 148) SGA fetuses. SGA fetuses were considered to be asymmetric with a head circumference to abdominal circumference ratio above the 95th percentile. The accuracy of the different formulas was compared using means of percentage errors (MPE), medians of absolute percentage errors (MAPE), and proportions of estimates within 10 % of actual birth weight. Results: Results for the subgroup of asymmetric SGA fetuses differed significantly from the subgroup of symmetric SGA fetuses. MPE values were closer to zero with most of the formulas in the asymmetric SGA group. Apart from the Siemer, Shepard, Merz and Warsof equations, all formulas showed an underestimation of fetal weight in asymmetric SGA fetuses. In contrast, in the symmetric SGA group, all of the formulas commonly used for fetuses in a normal weight range showed a systematic overestimation of fetal weight. Overall the best accuracy was achieved by using the Sabbagha equation (MPE 1.7 %; SD 9.0 %; MAPE: 6.0). Conclusion: An accurate WE in SGA fetuses is feasible using the Sabbagha formula. However, one has to be aware of the significant differences in WE between symmetric and asymmetric SGA fetuses.
EVALuna2:5471

Spatial expression of claudin 18.2 in matched primaries and metastases of tubo-ovarian carcinoma of all subtypes - Wagner, Paul; Gaß, Paul; Pöschke, Patrik; Eckstein, Markus; Gloßner, Laura; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Emons, Julius; Erber, Ramona (Virchows Archiv, 2024)
Physiologically, claudin 18 splice variant 2 (CLDN18.2) expression is restricted to the gastric epithelium, but its expression has been detected in solid cancers. Zolbetuximab, a chimeric IgG1 antibody targeting CLDN18.2, has demonstrated promising effects in patients suffering from CLDN18.2-positive, HER2-negative locally advanced gastric cancer and is currently being studied further. To date, little is known about CLDN18.2 expression in other histological subtypes of tubo-ovarian carcinoma (TOC) and their matching metastases. Using a cohort of all histological TOC subtypes, we investigated the immunohistochemical (IHC) CLDN18.2 expression in both TOCs (n = 536), their matching metastatic tissue (n = 385) and in 93 metastases without primary. Tissue microarrays comprised both the tumor center and periphery. IHC positivity was defined as biomarker expression of ≥ 75% in tumor cells with moderate-to-strong membranous staining. Overall CLDN18.2 positivity was 4.1% (21/515) in the TOC centers and 3.6% (18/498) in their peripheries. In primaries of mucinous tubo-ovarian carcinoma (MTOC), CLDN18.2 positivity rates were 45% (18/40) and 36.6% (15/41), respectively. Positivity rates for the corresponding metastases were 33% (4/12, center) and 27% (3/11, periphery). The expression was relatively homogenous throughout all tumor sites. With no expression in 99.5% of nonmucinous tumors, CLDN18.2 positivity was almost exclusively seen in the mucinous subtype. In tubo-ovarian carcinoma, CLDN18.2 expression was, with rare exceptions, restricted to the mucinous subtype. Among them, 33% of metastasized MTOCs presented with CLDN18.2 positivity. Hence, CLDN18.2 might display a promising target for personalized therapy in patients with advanced MTOC.
CRIS-Team Scopus Importer:2024-02-16
Keywords: CLDN18.2; Immunohistochemistry; Mucinous tubo-ovarian carcinoma; Targeted therapy; Tubo-ovarian cancer

Spontaneous antral follicle formation and metaphase II oocyte from a non-stimulated prepubertal ovarian tissue xenotransplant - Lotz, Laura; Liebenthron, Jana; Nichols-Burns, Stephanie M.; Montag, Markus; Hoffmann, Inge; Beckmann, Matthias; Van Der Ven, Hans; Toepfer, Dagmar; Dittrich, Ralf (Reproductive Biology and Endocrinology, 2014)
Current strategies in cancer treatment have markedly increased the rates of remission and survival for cancer patients, but are often associated with subsequent sterility. While there are various options available to an adult female depending on the patient's particular situation, the only realistic option for preserving fertility in prepubertal females is to cryopreserve ovarian tissue. This is the first report of a morphologically mature oocyte collected from non-stimulated prepubertal ovarian tissue xenotransplants.Ovarian tissue from a 6 year old patient suffering from nephroblastoma was removed and cryopreserved for fertility preservation. The frozen-thawed ovarian tissue fragments were xenotransplanted to bilaterally oophorectomized severe combined immunodeficiency (SCID) mice to assess follicle development.Antral follicle formation occurred post-xenotransplantation in a single ovarian fragment without exogenous hormone stimulation. A morphologically maturing oocyte was harvested from these follicles.Prepubertal human ovarian follicles and oocytes can be matured after xenotransplantation even without exogenous hormone stimulation. These results indicate that tissue collected from prepubertal patients can support fertility in cancer survivors.
EVALuna2:17456

Standard changing news der Senologie und der Gynäkologischen Onkologie 2018 - Preu, Caroline; Heindl, Felix; Jud, Sebastian; Hein, Alexander; Hack, Carolin; Beckmann, Matthias; Lux, Michael P.; Rauh, Claudia (Klinikarzt, 2018)
CRIS-Team Scopus Importer:2021-07-19

Standard changing news der Senologie und der Gynäkologischen Onkologie 2019: Neue Arzneimittelzulassungen und Änderungen bestehender Therapiekonzepte - Preuβ, Caroline; Hein, Alexander; Beckmann, Matthias; Jud, Sebastian (Klinikarzt, 2019)
CRIS-Team Scopus Importer:2020-02-21

Standard Changing News der Senologie und der Gynäkologischen Onkologie 2020 - Preuβ, Caroline; Hein, Alexander; Beckmann, Matthias; Jud, Sebastian (Klinikarzt, 2020)
CRIS-Team Scopus Importer:2020-12-11

Standard Changing News der Senologie und Gynäkologischen Onkologie - Rauh, Claudia; Jud, Sebastian; Hein, Alexander; Hack, Carolin; Fasching, Peter; Beckmann, Matthias; Lux, Michael P. (Klinikarzt, 2017)
CRIS-Team Scopus Importer:2021-07-19

Standardized Procedures for Patients with Dysplasia and Other Diseases of the Cervix, Vulva, and Vagina at a Certified Dysplasia Unit Prior to the Introduction of the Organized Cervical Cancer Screening Program. - Schulmeyer, Carla; Koch, Martin C.; Dietl, Anna; Stübs, Frederik; Behrens, Annika; Renner, Simone K.; Mehlhorn, Grit; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckmann, Matthias; Gaß, Paul (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Gynecologic dysplasia units and dysplasia consultations are obliged to offer diagnosis and treatment in accordance with the guidelines. The organization of the consultation process, management of patient appointments, diagnosis, and treatment algorithms are heterogeneous. The legislation arising from the new Federal Joint Committee decision, dated 22 November 2018, concerning the organized cervical cancer screening program has been in force since 1 January 2020. In this article we provide an overview of the existing structures and interdisciplinary cooperation of specialized dysplasia units incorporated in certified gynecologic cancer center. Materials and Methods We carried out a retrospective database search of data collected prospectively from 1 July 2014 to 31 December 2019 at the dysplasia unit at the Department of Gynecology and Obstetrics, Erlangen University Hospital, which was the first dysplasia unit to be certified in 2014. Results A total of 5594 patients presented at the unit, and 16061 colposcopic, vulvoscopic, and anoscopic examinations were performed. Approximately 4100 examinations of the cervix, vagina, vulva, and anus are carried out each year, 1600 of these were exclusively cervix colposcopies. A total of 12197 cytology results were assessed, as well as 4850 histology results, and 8193 high-risk HPV tests. The quality indicators required by the dysplasia unit for annual recertification were met each year. Conclusion Certified dysplasia units and consultations form the central component in the algorithm for further investigating abnormal screening results; but they are also the first point of contact for a large number of patients with acute or chronic complaints in the genital region.
EVALuna2:542837

Standards Used by a Clinical and Scientific Endometriosis Center for the Diagnosis and Therapy of Patients with Endometriosis - Burghaus, Stefanie; Hildebrandt, Thomas; Fahlbusch, Christine; Heusinger, Katharina; Antoniadis, Sophia; Lermann, Johannes; Hackl, Janina; Häberle, Lothar; Renner, Stefan P.; Fasching, Peter; Beckmann, Matthias; Blum, Simon (Geburtshilfe und Frauenheilkunde, 2019)
Endometriosis is one of the most common benign gynecological diseases. The extremely heterogeneous complex of symptoms complicates the diagnosis and treatment of this disease. In most patients, there is a latency period of several years between the first occurrence of symptoms and the definitive diagnosis. This paper aims (1) to evaluate standards for the diagnosis and treatment of patients with (symptoms suspicious for) endometriosis in terms of feasibility, and (2) to assess the potential use of data collected by a certified clinical and scientific endometriosis center to answer scientific questions. Standards for outpatient consultations were developed for a special endometriosis outpatient clinic. Between January 2014 and December 2017, a total of 1715 outpatients with a suspicion of endometriosis presented to this special endometriosis outpatient clinic; the diagnosis and treatment of patients was carried out in accordance with the developed standards. Data of this patient cohort obtained from patient records created during outpatient consultations and from a questionnaire recorded in an Oracle-based database was analyzed. The patient cohort was also compared with another patient cohort who had attended different outpatient clinics and had been diagnosed intraoperatively with endometriosis. 41.8% of patients examined during special outpatient consultations had surgery for suspicion or recurrence of endometriosis. Endometriosis was confirmed in 81.5% of cases. Pain symptoms were the main indication for surgery in 70.1% of cases compared to 45.1% of cases in the comparison group. The structured approach used in the special endometriosis outpatient clinic is a key aspect of the care provided by the certified clinical and scientific endometriosis center. It ensures that patients are diagnosed and treated in accordance with guideline recommendations, that diagnosis and treatment comply with certification requirements, and that the collected data can be used to answer scientific questions.
CRIS-Team Scopus Importer:2019-06-04
Keywords: diagnostic; endometriosis; lower abdominal pain; sterility

Statement by the German Society for Gynecology and Obstetrics e.V. on the Topic - More Knowledge "Breast Density" - Seelbach-Goebel, Birgit; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36148

Statement of the AGO and AG-CPC on the Aftercare/Follow-up for Surgical Procedures of the Lower Genital Tract after the Introduction of a New Cancer Screening Guideline - Hillemanns, Peter; Tempfer, Clemens; Beckmann, Matthias; Kueppers, Volkmar; Quaas, Jens (Geburtshilfe und Frauenheilkunde, 2020)
The new guideline on organized cancer screening programs has been in force in Germany since January 1st, 2020. The guideline has amended earlier recommendations on cytological examinations, which were previously carried out annually during screening. The guidelines-based recommendations on the appropriate follow-up for preinvasive and invasive lesions of the uterine cervix and endometrium are briefly outlined and differentiated from screening cytology and Pap/HPV co-testing as described in the guideline on organized cancer screening programs (oKFE-RL).
CRIS-Team WoS Importer:2020-09-11

Statement of the Uterus Commission of the Gynecological Oncology Working Group (AGO) on Surgical Therapy for Patients with Stage IA2-IIB1 Cervical Cancer - Fehm, Tanja; Beckmann, Matthias; Mahner, Sven; Denschlag, Dominik; Brucker, Sara; Hillemanns, Peter; Tempfer, Clemens (Geburtshilfe und Frauenheilkunde, 2023)
The presentation of the results of the prospective randomized international multicenter study AGO-OP.8 - CCTG CX.5 - SHAPE at the annual conference of the American Society of Clinical Oncology (ASCO) in 2023 will affect the surgical treatment of early-stage cervical cancer. In the SHAPE study, simple total hysterectomy (experimental arm) was found to be non-inferior to radical hysterectomy (standard arm) to treat patients with early-stage cervical cancer (FIGO stages [2018] IA2 - IB1 ≤ 2 cm with an infiltration depth of < 1 cm); after 3 years' follow-up the pelvic recurrence rate was 2.52% (experimental arm) compared to 2.17% (standard arm) with no statistically significant difference with regards to recurrence-free survival and overall survival rates. After weighing up the results of the SHAPE study published at the conference, the Uterus Organ Commission of AGO is of the opinion that, in addition to the use of radical hysterectomy to treat patients with invasive cervical cancer which is FIGO stage IA2 - IB1 ≤ 2 cm with an infiltration depth of < 1 cm, simple total hysterectomy may also be considered for primary surgical therapy on a case-by-case basis after suitable explanation of the associated risks. It will be necessary to wait for the data of the full publication before discussing whether this approach should be included in official guidelines and defining it as a new therapy standard.
CRIS-Team Scopus Importer:2023-10-27
Keywords: cervical cancer; early-stage; radical hysterectomy; simple hysterectomy

State-of-the-Art Treatment and Novel Agents in Local and Distant Recurrences of Cervical Cancer - Tempfer, Clemens B.; Beckmann, Matthias (Oncology Research and Treatment, 2016)
Depending on the stage at initial presentation, cervical cancer will recur in 25-61% of women. Typical manifestations of recurrent cervical cancer include the central pelvis and the pelvic side walls as well as retroperitoneal lymph node basins in the pelvis and the para-aortic region, and - more rarely - supraclavicular lymph nodes. There are no typical symptoms of recurrent cervical cancer. Women with suspected recurrence after cervical cancer based on gynecological examination or organ-specific symptoms must undergo imaging studies and - if technically feasible - biopsy with histological verification, especially in cases of distant metastases, in order to rule out a second primary. Radiotherapy-naïve women should be treated with salvage radiochemotherapy with curative intention. For women with previous radiotherapy, surgery in the form of hysterectomy, local resection, or pelvic exenteration is the treatment of choice. Pelvic exenteration can lead to cure in selected patients, but at the price of a high rate of complications and significant morbidity and mortality. If complete surgical resection is not feasible or if the woman is not a candidate for surgery, chemotherapy with palliative intent should be offered. Patients with recurrent disease outside the pelvis are candidates for systemic chemotherapy. Several agents have shown to be active in this situation, either in single-agent or combination regimens. Platinum-containing regimens have a superior efficacy over non-platinum regimens and bevacizumab may be added to chemotherapy.
EVALuna2:32962

Stellenwert der Vakzine gegen humane Papillomaviren in der Prävention von Krebserkrankungen - Schulmeyer, Carla; Knöll, Antje; Iro, Heinrich; Müller, Susanna; Beckmann, Matthias (Onkologe, 2021)
Background: Human papillomaviruses (HPV) are the most common causes of genital viral infections. HPV infections usually heal, but can also persist and thus cause lesions of different grades. Infections with high-risk HPV types (hrHPV) 16, 18, 31, 33, 45, 52, and 58 are responsible for causing 90% of cervical cancer cases in Europe. Head and neck cancer, vaginal and vulvar cancer and their precursors, as well as penile or anal cancer may also be associated with hrHPV. Objectives: The aim of this work is to demonstrate the importance of HPV vaccines in the prevention of genital as well as head and neck cancers. Materials and methods: This work is based on a selective literature search in the PubMed database on the correlation between HPV vaccines and HPV-associated cancer. Results: HPV vaccination ensures a high level of protection against precancerous lesions and cancer of the cervix, vagina, vulva, anus, and genital warts. Conclusions: Results of HPV vaccination and its positive effects on head and neck tumors is expected within the next few decades.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Condylomata acuminata; HPV; Oropharyngeal neoplasms; Sexually transmitted diseases; Uterine cervical neoplasms

Stellungnahme des Präsidenten und des Leitlinien-Beauftragten der DGGG - Absence of Evidence Is Not Evidence of Absence - Carl Edward Sagan (911.1934-20.12.1996, US-amerikanischer Astronom, Astrophysiker, Exobiologe) - Scharl, Anton; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2021)
CRIS-Team Scopus Importer:2021-08-27

Superpixel Pre-segmentation of HER2 Slides for Efficient Annotation - Öttl, Mathias; Mönius, Jana; Marzahl, Christian; Rübner, Matthias; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Maier, Andreas; Erber, Ramona; Breininger, Katharina (Informatik aktuell, 2022)
Supervised deep learning has shown state-of-the-art performance for medical image segmentation across different applications, including histopathology and cancer research; however, the manual annotation of such data is extremely laborious. In this work, we explore the use of superpixel approaches to compute a pre-segmentation of HER2 stained images for breast cancer diagnosis that facilitates faster manual annotation and correction in a second step. Four methods are compared: standard simple linear iterative clustering (SLIC) as a baseline, a domain adapted SLIC, and superpixels based on feature embeddings of a pretrained ResNet-50 and a denoising autoencoder. To tackle oversegmentation, we propose to hierarchically merge superpixels, based on their content in the respective feature space. When evaluating the approaches on fully manually annotated images, we observe that the autoencoder-based superpixels achieve a 23% increase in boundary F1 score compared to the baseline SLIC superpixels. Furthermore, the boundary F1 score increases by 73% when hierarchical clustering is applied on the adapted SLIC and the autoencoder-based superpixels. These evaluations show encouraging first results for a pre-segmentation for efficient manual refinement without the need for an initial set of annotated training data.<br
CRIS-Team Scopus Importer:2022-05-06

Supportive Infusions in Integrative Breast and Gynecological Oncology - Report on Patients' Satisfaction and Self-reported Effects and Side Effects - Hack, Carolin; Antoniadis, Sophia; Beckmann, Matthias; Brandl, Anna; Fasching, Peter; Hackl, Janina; Langemann, Hanna; Stock, Katja; Weber, Natalie; Theuser, Anna-Katharin (Geburtshilfe und Frauenheilkunde, 2018)
Background During cancer therapy, many patients suffer from malnutrition or vitamin deficiency. Treatment for nutrition-related deficiencies should therefore include nutritional therapy and possibly oral or intravenous substitution of micronutrients. Little information exists on multinutrient infusion therapies. The aim of this study was to develop standardized infusion protocols for integrative medicine infusions with micronutrients (IMed infusions) and to report on side effects of the treatment and patients' satisfaction with it. Methods For the IMed consultancy service, four special formulas for intravenous use were developed in cooperation with the pharmacy at Erlangen University Hospital. A retrospective cross-sectional study was conducted between October 2015 and January 2018 in which 45 patients with gynecological or breast cancer (BC) and IMed infusion therapy were included. Follow-up data were obtained from 20 patients using a standardized questionnaire on IMed infusions. Results A total of 280 IMed infusions were administered in the study period. The majority of the patients received an IMed regeneration infusion (78%). The majority of the patients had BC and were receiving chemotherapy. Most patients reported a high or very high level of satisfaction with the organization (60%), general treatment (65%) and counseling (85%). Subjective improvement in their disease-related and therapy-induced symptoms, such as fatigue, polyneuropathy and physical efficiency, was reported by 70% of the patients, while 75% reported a subjective increase in quality of life. Side effects were rare and minor. Conclusions Therapy with IMed infusions in women with BC or gynecological cancer requires the same standards set for drug therapy. Although vitamins represent dietary supplements, appropriate assessment of the patient's medical history is needed and patients must receive appropriate information. For this purpose, standardized processes, as in the context of an IMed consultancy service, are helpful.
EVALuna2:209954

Surgical Aspects of Ovarian Tissue Removal and Ovarian Tissue Transplantation for Fertility Preservation - Beckmann, Matthias; Dittrich, Ralf; Findeklee, S.; Lotz, Laura (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: The removal of ovarian tissue prior to starting oncologic treatment and the subsequent transplantation of this tissue after completing therapy have become increasingly important surgical fertility-preserving techniques. The aim of this review was to investigate the different surgical techniques used for this method reported in the literature to date and to discuss the advantages and disadvantages of the respective techniques.Review:A search was done in MEDLINE using a defined algorithm to find studies published between January 2004 and December 2015. All study designs were included in our review if they contained statements on the surgical technique used. We found 16 publications (8 retrospective cohort studies, 6 case reports and 2 systematic reviews) with a total of 1898 female patients which reported on the surgical technique used for ovarian biopsy and 15 publications (7 retrospective cohort studies, 6 case reports and 2 systematic reviews) with a total of 455 women which mentioned the surgical technique used for ovarian transplantation. Different surgical techniques can be used both for ovarian biopsy and for the transplantation of ovarian tissue. A number of different surgical routes have been used, and the amount of tissue extracted, the instruments used, the treatment of the ovary, the transplantation site, the blood supply to the transplanted ovarian tissue and the procedure used for simultaneous surgical interventions vary.Conclusion:In future, one of the tasks will be to establish a standard surgical method for ovarian extraction and transplantation which will have a low rate of complications and a high pregnancy and birth rate while ensuring that the transplanted tissue is fully functional.
EVALuna2:32951

Surgical treatment of cervical cancer Operative Therapie des Zervixkarzinoms - Fehm, Tanja; Gantert, Daniel; Martignoni, Franca; Koch, Martin; Beckmann, Matthias (Onkologe, 2020)
Background: Surgery represents the first choice for treatment of early cervical carcinoma (FIGO IA1 to FIGO IIa according to Fédération Internationale de Gynécologie et d’Obstétrique). The extent of surgical therapy for the patient should be determined based on the patient’s age and tumor spread, particularly if fertility preservation is desired. More recently, less radical surgical procedures and concepts for sentinel lymph node biopsy are increasingly used in order to reduce mortality and morbidity. Controversy is currently emerging in the context of new studies regarding the choice of surgical approach. Objective: In this article, surgical options for the treatment of cervical cancer are reviewed. Materials and methods: An overview of the current study situation and literature is provided, taking into consideration the current German S3 guideline on cervical carcinoma. Results: Localized cervical cancer (≤FIGO IIA) is primarily treated by surgery. Recent studies, e.g. SHAPE, are investigating whether less radical surgical procedures can provide adequate oncological safety. A fertility-preserving approach is possible up to stage IB1 depending on the presence of risk factors. After the study results of the LACC trial were published with increased recurrence and mortality rate in the group undergoing laparoscopic surgery compared to the laparotomy group, patients must be informed about these data prior to decision making regarding the route of hysterectomy. Conclusion: The treatment of cervical cancer should be conducted according to the stage. Surgery is key in the treatment of early cervical carcinoma. Even less radical procedures seem to provide adequate oncological safety.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Fertility preservation; Hysterectomy; Sentinel lymph node biopsy; Trachelectomy; Uterine cervical neoplasms

Surgical treatment of endometrial cancer - Emons, G.; Brucker, S. Y.; Fleisch, M. C.; Mueller, M.; Juhasz-Boess, E.; Kiesel, L.; Runnebaum, I. B.; Friedrich, M.; Mustea, A.; Erdogan, S.; Beckmann, Matthias (Die Gynäkologie, 2022)
In July 2022, the first update (Version 2.0) of the German S3 guideline on the diagnosis, treatment and follow-up of patients with endometrial cancer was published, supported by the Leitlinienprogramm Onkologie (Oncology Guideline Program). This article is the summary of Chap. 6: "Surgical Treatment". Relevant innovations compared to version 1.0 include the introduction of molecular classification and sentinel node biopsy, as well as the option of neoadjuvant chemotherapy for advanced cases where primary cytoreductive surgery is not possible.
CRIS-Team WoS Importer:2022-07-29

Targeted sequencing of FH-deficient uterine leiomyomas reveals biallelic inactivating somatic fumarase variants and allows characterization of missense variants - Popp, Bernt; Erber, Ramona; Kraus, Cornelia; Vasileiou, Georgia; Hoyer, Juliane; Burghaus, Stefanie; Hartmann, Arndt; Beckmann, Matthias; Reis, André; Agaimy, Abbas (Modern Pathology, 2020)
Uterine leiomyomas (ULs) constitute a considerable health burden in the general female population. The fumarate hydratase (FH) deficient subtype is found in up to 1.6% and can occur in hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome. We sequenced 13 FH deficient ULs from a previous immunohistochemical screen using a targeted panel and identified biallelic FH variants in all. In eight, we found an FH point mutation (two truncating, six missense) with evidence for loss of the second allele. Variant allele-frequencies in all cases with a point mutation pointed to somatic variants. Spatial clustering of the identified missense variants in the lyase domain indicated altered fumarase oligomerization with subsequent degradation as explanation for the observed FH deficiency. Biallelic FH deletions in five tumors confirm the importance of copy number loss as mutational mechanism. By curating all pathogenic FH variants and calculating their population frequency, we estimate a carrier frequency of up to 1/2,563. Comparing with the prevalence of FH deficient ULs, we conclude that most are sporadic and estimate 2.7–13.9% of females with an FH deficient UL to carry a germline FH variant. Further prospective tumor/normal sequencing studies are needed to develop a reliable screening strategy for HLRCC in women with ULs.
CRIS-Team Scopus Importer:2020-07-10

The association between prenatal alcohol consumption and preschool child stress system disturbance - Grimm, Jennifer; Stemmler, Mark; Golub, Yulia; Schwenke, Eva; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Developmental Psychobiology, 2021)
Background: Drinking alcohol during pregnancy is considered a risk factor for child development; however, child biomarkers of prenatal alcohol exposure have been rarely studied. We examined whether a meconium alcohol metabolite (ethyl glucuronide, EtG) was associated with child cortisol concentrations at primary school age. Methods: For 137 children, prenatal alcohol exposure was operationalized by the meconium biomarker EtG and by maternal self-reports during pregnancy. Two EtG cut-offs (EtG ≥10 ng/g and EtG ≥112 ng/g) were applied. Cortisol concentrations were measured in saliva and hair samples. Results: Children with EtG ≥10 ng/g showed significantly reduced hair cortisol concentrations (HCCs) (p =.050, (Formula presented.) = 0.042). For children with EtG ≥112 ng/g, the cortisol awakening response (CAR) was significantly decreased (p =.025, (Formula presented.) = 0.070). These effects were also present in correlational analyses with continuous EtG data, speaking for partly dose-dependent effects. Especially, within the EtG ≥112 ng/g group, the basal (CAR: rp = −.642, p =.120) and cumulative (HCC: rp = −.660, p =.107) cortisol parameters were associated with child emotional symptoms at medium effect size. Conclusions: The present study showed both the biological association of intrauterine alcohol exposure with the cortisol stress system, partly dose-dependent, and the functional association with emotional and behavioral symptoms.
CRIS-Team Scopus Importer:2020-10-16
Keywords: alcohol; biomarker; child; cortisol stress system; ethyl glucuronide; hypothalamus-pituitary-adrenal axis; intrauterine alcohol exposure; meconium; pregnancy

The association of prenatal attachment and perinatal factors with pre- and postpartum depression in first-time mothers - Goecke, T.; Voigt, F.; Faschingbauer, F.; Spangler, Gottfried; Beckmann, Matthias; Beetz, Andrea (Archives of Gynecology and Obstetrics, 2012)
Purpose: This prospective study investigated associations between prenatal attachment of adult first-time mothers to the unborn child, perinatal factors and levels of depression before and up to 18 months after delivery. Method: Primiparas (N = 161) without specific risk factors answered the following questionnaires during the last term of pregnancy (t1): Edinburgh Postnatal Depression Scale (EPDS), Maternal Antenatal Attachment Scale (MAAS), questionnaire on the schema of the unborn child, and a questionnaire about the pregnancy. Perinatal data were taken from the patients' files. The EPDS was answered 3 weeks (t2, N = 157), 6 months (t3, N = 159), and 18 months (t4, N = 132) postpartum. Results: During pregnancy, 16.9 % of the women indicated mild depressive symptoms, and 7.5 %, medium to severe symptoms of depression. Mild symptoms of depression were found in 25.5 % at t2, 10.1 % at t3, and 12.2 % at t4; medium to severe symptoms were reported by 7.6, 1.9 and 5.6 %, respectively. Women with low control during delivery (emergency Caesarean) showed a tendency for higher levels (p = 0.067) of depression at t3 than women with elective Caesarean did. The quality of prenatal attachment to the unborn child correlated negatively with depressive symptoms at t1-t4. Conclusions: The closer the prenatal attachment of a mother to her unborn child, the less symptoms of depression she reports during the last term of pregnancy and postpartum. Therefore, promoting good mother-child attachment during pregnancy might influence the level of postpartum depression. © Springer-Verlag 2012.

The Benefit of a Retrospective Pregnancy Anamnesis in Child and Adolescent Psychiatry: The Reliability of Maternal Self-Report during Childhood Development - Mestermann, Stefan; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Children, 2023)
Pregnancy anamnesis is a crucial part of child and adolescent psychiatry diagnostics. In previous works, the reliability of retrospective maternal self-report on perinatal characteristics was heterogeneous. This prospective longitudinal study aimed to evaluate women’s recall of prenatal events in a within-subject design. A sample of 241 women gave a self-report on prenatal alcohol, smoking, partnership quality, pregnancy satisfaction, and obstetric complications during the 3rd trimester (t0), childhood (t1, 6–10 y), and adolescence (t2, 12–14 y). The intra-individual agreement was examined. The t0–t1–(t2) agreement was poor to substantial; this was highest for smoking and worst for obstetric complications, followed by alcohol (Fleiss’ κ = 0.719 to −0.051). There were significant t0–t1–(t2) differences for all pregnancy variables (p < 0.017), except for 3rd trimester satisfaction (p = 0.256). For alcohol (t0 25.8%, t1 17.4%, t2 41.0%) and smoking (t0 11.9%, t1 16.4%, t2 22.6%), the highest self-reported rates were found during adolescence. During childhood, fewer obstetric complications (t0 84.9%, t1 42.2%) and worse partnerships were reported (t0 M = 8.86, t1 M = 7.89). Thought to be due to social stigmata and memory effects, pregnancy self-reports cannot be precisely reproduced. Creating a respectful and trusting atmosphere is essential for mothers to give honest self-reports that are in the best interest of their children.
CRIS-Team Scopus Importer:2023-06-30
Keywords: alcohol; partnership; pregnancy; pregnancy satisfaction; prenatal; retrospective; risk perceptions; self-report; smoking

The BRCA2 c.68-7T > A variant is not pathogenic: A model for clinical calibration of spliceogenicity - Colombo, Mara; Lopez-Perolio, Irene; Meeks, Huong D.; Caleca, Laura; Parsons, Michael T.; Li, Hongyan; De Vecchi, Giovanna; Tudini, Emma; Foglia, Claudia; Mondini, Patrizia; Manoukian, Siranoush; Behar, Raquel; et al. (Human Mutation, 2018)
Although the spliceogenic nature of the BRCA2 c.68-7T > A variant has been demonstrated, its association with cancer risk remains controversial. In this study, we accurately quantified by real-time PCR and digital PCR (dPCR), the BRCA2 isoforms retaining or missing exon 3. In addition, the combined odds ratio for causality of the variant was estimated using genetic and clinical data, and its associated cancer risk was estimated by case-control analysis in 83,636 individuals. Co-occurrence in trans with pathogenic BRCA2 variants was assessed in 5,382 families. Exon 3 exclusion rate was 4.5-fold higher in variant carriers (13%) than controls (3%), indicating an exclusion rate for the c.68-7T > A allele of approximately 20%. The posterior probability of pathogenicity was 7.44 × 10-115 . There was neither evidence for increased risk of breast cancer (OR 1.03; 95% CI 0.86-1.24) nor for a deleterious effect of the variant when co-occurring with pathogenic variants. Our data provide for the first time robust evidence of the nonpathogenicity of the BRCA2 c.68-7T > A. Genetic and quantitative transcript analyses together inform the threshold for the ratio between functional and altered BRCA2 isoforms compatible with normal cell function. These findings might be exploited to assess the relevance for cancer risk of other BRCA2 spliceogenic variants.
EVALuna2:202794

The Chorioallantoic Membrane Xenograft Assay as a Reliable Model for Investigating the Biology of Breast Cancer - Ranjan, Raphela A.; Muenzner, Julienne K.; Kunze, Philipp; Geppert, Carol-Immanuel; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; Beckmann, Matthias; Bäuerle, Tobias; Hartmann, Arndt; Walther, Wolfgang; Eckstein, Markus; et al. (Cancers, 2023)
The chorioallantoic membrane (CAM) assay is an alternative in vivo model that allows for minimally invasive research of cancer biology. Using the CAM assay, we investigated phenotypical and functional characteristics (tumor grade, mitosis rate, tumor budding, hormone receptor (HR) and HER2 status, Ki-67 proliferation index) of two breast cancer cell lines, MCF-7 and MDA-MB-231, which resemble the HR+ (luminal) and triple-negative breast cancer (TNBC) subgroups, respectively. Moreover, the CAM results were directly compared with murine MCF-7- and MDA-MB-231-derived xenografts and human patient TNBC tissue. Known phenotypical and biological features of the aggressive triple-negative breast cancer cell line (MDA-MB-231) were confirmed in the CAM assay, and mouse xenografts. Furthermore, the histomorphological and immunohistochemical variables assessed in the CAM model were similar to those in human patient tumor tissue. Given the confirmation of the classical biological and growth properties of breast cancer cell lines in the CAM model, we suggest this in vivo model to be a reliable alternative test system for breast cancer research to reduce murine animal experiments.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 3R; alternative in vivo model; CAM model; hormone receptor; HTB-26; MCF-7; MDA-MB-231; mouse xenograft; tumor aggressiveness

The concept of the certification system of the German Cancer Society and its impact on gynecological cancer care - Wesselmann, Simone; Beckmann, Matthias; Winter, A. (Archives of Gynecology and Obstetrics, 2014)
This article describes the status of gynecological cancer care in Germany and gives an overview of the certification of gynecological cancer care by the German Cancer Society (Deutsche Krebsgesellschaft DKG). The DKG certifies cancer centers to promote a high-quality level in the treatment of oncological patients.Searches were conducted in PubMed and ScienceDirect to identify the relevant literature. Catalog of requirements for centers certification as well as benchmark reports were used to characterize cancer care in centers certified by DKG.The certification system of the DKG has been developed to ensure comprehensive care for cancer patients in Germany. The criteria for certification are based on interdisciplinary and inter-professional care conforming to guidelines and specialist expertise. These requirements have been shown to improve structural and process quality, and thus satisfaction and health outcomes in patients.
EVALuna2:17461

The contributions of breast density and common genetic variation to breast cancer risk - Vachon, Celine M.; Pankratz, V. Shane; Scott, Christopher G.; Häberle, Lothar; Ziv, Elad; Jensen, Matthew R.; Brandt, Kathleen R.; Whaley, Dana H.; Olson, Janet E.; Heusinger, Katharina; Hack, Carolin; Jud, Sebastian; et al. (Journal of the National Cancer Institute, 2015)
We evaluated whether a 76-locus polygenic risk score (PRS) and Breast Imaging Reporting and Data System (BI-RADS) breast density were independent risk factors within three studies (1643 case patients, 2397 control patients) using logistic regression models. We incorporated the PRS odds ratio (OR) into the Breast Cancer Surveillance Consortium (BCSC) risk-prediction model while accounting for its attributable risk and compared five-year absolute risk predictions between models using area under the curve (AUC) statistics. All statistical tests were two-sided. BI-RADS density and PRS were independent risk factors across all three studies (P interaction = .23). Relative to those with scattered fibroglandular densities and average PRS (2(nd) quartile), women with extreme density and highest quartile PRS had 2.7-fold (95% confidence interval [CI] = 1.74 to 4.12) increased risk, while those with low density and PRS had reduced risk (OR = 0.30, 95% CI = 0.18 to 0.51). PRS added independent information (P < .001) to the BCSC model and improved discriminatory accuracy from AUC = 0.66 to AUC = 0.69. Although the BCSC-PRS model was well calibrated in case-control data, independent cohort data are needed to test calibration in the general population.
EVALuna2:14513

The Diagnosis, Treatment, and Aftercare of Cervical Carcinoma. - Beckmann, Matthias; Stübs, Frederik; Vordermark, Dirk; Koch, Martin Christoph; Horn, Lars Christian; Fehm, Tanja (Deutsches Ärzteblatt international, 2021)
BACKGROUND: Approximately 4380 cases of cervical carcinoma were diagnosed in Germany in 2016. In women who had not participated in early detection programs, cervical carcinoma was usually already in an advanced stage at the time of diagnosis. Certified structures for care in conformity with the existing guidelines are available. METHODS: The new German clinical practice guideline was revised with the participation of 50 medical societies under the expert guidance of the Guideline Program in Oncology, which includes the German Association of the Scientific Medical Societies (Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften, AWMF). A systematic literature review was conducted. Systematic reviews, meta-analyses, and randomized controlled trials (RCTs) were considered. RESULTS: The histologic tumor stage and lymph-node stage are essential determinants of the treatment strategy. The main innovation regarding surgical treatment is the revival of open hysterectomy (overall survival [minimally invasive vs open hysterectomy]: 94.04% vs 99.4%; hazard ratio [HR]: 6.00; 95% confidence interval [1.77; 20.30]). In addition, for tumors measuring 2 cm or less, sentinel node biopsy is recommended rather than radical pelvic lymphadenectomy. MRI-guided brachytherapy is an oblig atory component of radiochemotherapy (overall survival [radiochemotherapy with vs without brachytherapy]: 58.2% vs 46.2%, p<0.001). The standard palliative treatment consists of bevacizumab combined with a platinum-containing agent (overall survival: HR: 0.77 [0.62; 0.95]; p = 0.007). CONCLUSION: Despite the introduction of new treatments, the outcome of patients with advanced cervical carcinoma has not much improved. In the surgical treatment of cervical carcinoma, the open approach is now favored. The sentinel node biopsy technique has become well established for the surgical staging of small tumors. Controlled trials are needed so that the outcome of women with cervical carcinoma, particularly in its advanced and metastatic stages, can be improved.
EVALuna2:506686

The effect of bpV(HOpic) on in vitro activation of primordial follicles in cultured swine ovarian cortical strips - Raffel, Nathalie; Klemm, Katrin; Dittrich, Ralf; Hoffmann, Inge; Söder, Stefan; Beckmann, Matthias; Lotz, Laura (Reproduction in Domestic Animals, 2019)
The vanadate-derivative dipotassium bisperoxo (5-hydroxy-pyridine-2-carboxylic) oxovanadate (V) (bpV(HOpic)), a pharmacological inhibitor of phosphatase and tensin homolog (PTEN), has been used in ovarian follicle culture systems for activation of follicular growth in vitro and suggested to be responsible for primordial follicle survival through indirect Akt activation. For pig ovarian tissue, it is still not clear which culture medium needs to be used, as well as which factors and hormones could influence follicular development; this also applies to bpV(HOpic) exposure. Therefore, ovarian cortical strips from pigs were cultured in 1 µM bpV(HOpic) (N = 24) or control medium (N = 24) for 48 hr. Media were then replaced with control medium and all tissue pieces incubated for additional 4 days. The strips were embedded in paraffin for histological determination of follicle proportions at the end of the culture period and compared to histological sections from tissue pieces without cultivation, which had been embedded right after preparation; comparison of healthy follicles for each developmental stage was performed to quantify follicle survival and activation. After 6-day culture, follicle activation occurred in tissue samples from both cultured groups but significantly more follicles showed progression of follicular development in the presence of 1 µM bpV(HOpic). The amount of non-vital follicles was not significantly increased during cultivation. BpV(HOpic) affects pig ovarian follicle development by promoting the initiation of follicle growth and development, similar as in rodent species and humans.
CRIS-Team Scopus Importer:2019-06-28
Keywords: bpV (HOpic); fertiprotekt; follicle activation follicle reserve; in vitro culture; ovarian cortical tissue

The effect of participation in neoadjuvant clinical trials on outcomes in patients with early breast cancer - Brennan, Meghan; Gaß, Paul; Häberle, Lothar; Wang, Daidong; Hartmann, Arndt; Lux, Michael P.; Beckmann, Matthias; Untch, Michael; Fasching, Peter (Breast Cancer Research and Treatment, 2018)
BACKGROUND: Clinical trials can offer novel and more advanced and/or novel treatments to cancer patients in advance of them being approved and available for all patients. While several studies have examined the effect of clinical trial participation on prognosis, there has been no clear conclusion from these studies. Therefore, we chose to test the influence of trial participation on pathological complete response (pCR) and mastectomy rates after neoadjuvant chemotherapy. METHODS: In this retrospective study, all patients treated with neoadjuvant chemotherapy from 2001 to 2014 were selected. A total of 1038 patients with complete treatment, patient, and tumor characteristics were included. A total of 260 of those were treated in clinical trials. We examined whether study participation status in addition to commonly known predictors for pCR improves prediction of pCR. Similar analyses were conducted for the mastectomy rate outcome measure. Finally, survival analyses were also conducted as part of an exploratory analysis. RESULTS: Study participation was an independent predictor of pCR in addition to commonly known predictors. Adjusted odds ratio (OR) for trial participants versus non-participants was 1.53 (95% CI 1.03-2.28). Additionally, study participation improved the prediction of mastectomy risk. The adjusted OR for trial participants versus non-participants was 0.62 (95% CI 0.42-0.90). Subgroup-specific differences concerning the impact of study participation could not be shown for either pCR or mastectomy rate. Survival comparisons could not be conducted due to large differences in follow-up data in patients participating in clinical trials versus those who did not participate; however, pCR was a predictor of prognosis in both groups. CONCLUSION: Patients taking part in neoadjuvant chemotherapy clinical trials have a higher pCR rate and a lower mastectomy risk than patients not participating in clinical trials for their cancer care. This finding is a supporting factor for trial participation in neoadjuvant chemotherapy trials.
EVALuna2:34852

The FANCM:p.Arg658* truncating variant is associated with risk of triple-negative breast cancer - Figlioli, Gisella; Bogliolo, Massimo; Catucci, Irene; Caleca, Laura; Lasheras, Sandra Viz; Pujol, Roser; Kiiski, Johanna I.; Muranen, Taru A.; Barnes, Daniel R.; Dennis, Joe; Michailidou, Kyriaki; Bolla, Manjeet K.; et al. (npj Breast Cancer, 2019)
Breast cancer is a common disease partially caused by genetic risk factors. Germline pathogenic variants in DNA repair genes BRCA1, BRCA2, PALB2, ATM, and CHEK2 are associated with breast cancer risk. FANCM, which encodes for a DNA translocase, has been proposed as a breast cancer predisposition gene, with greater effects for the ER-negative and triple-negative breast cancer (TNBC) subtypes. We tested the three recurrent protein-truncating variants FANCM:p.Arg658*, p.Gln1701*, and p.Arg1931* for association with breast cancer risk in 67,112 cases, 53,766 controls, and 26,662 carriers of pathogenic variants of BRCA1 or BRCA2. These three variants were also studied functionally by measuring survival and chromosome fragility in FANCM−/− patient-derived immortalized fibroblasts treated with diepoxybutane or olaparib. We observed that FANCM:p.Arg658* was associated with increased risk of ER-negative disease and TNBC (OR = 2.44, P = 0.034 and OR = 3.79; P = 0.009, respectively). In a country-restricted analysis, we confirmed the associations detected for FANCM:p.Arg658* and found that also FANCM:p.Arg1931* was associated with ER-negative breast cancer risk (OR = 1.96; P = 0.006). The functional results indicated that all three variants were deleterious affecting cell survival and chromosome stability with FANCM:p.Arg658* causing more severe phenotypes. In conclusion, we confirmed that the two rare FANCM deleterious variants p.Arg658* and p.Arg1931* are risk factors for ER-negative and TNBC subtypes. Overall our data suggest that the effect of truncating variants on breast cancer risk may depend on their position in the gene. Cell sensitivity to olaparib exposure, identifies a possible therapeutic option to treat FANCM-associated tumors.
CRIS-Team Scopus Importer:2019-11-12

The Father’s Part: Influences of Paternal Psychopathology and Parenting Behavior on Child and Adolescent Well-Being - Mestermann, Stefan; Arndt, Marie; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Healthcare, 2023)
Family influences on child quality of life (QoL) are increasingly understood. Parenting behavior and parent individual psychopathology are among the established predictors of offspring mental health. However, literature often addresses these factors as ‘parental’, lacking further gender-specific differentiation while predominantly studying maternal aspects. Social and biological fathers are still underrepresented in family research. The aim of this study was to analyze paternal contributions to child well-being. A total of 197 father/mother-dyads gave a standardized self-report on parenting behavior and their own psychopathology at child primary school age (t1; 6–10 y). Ratings were compared mutually and associated with child self-rated QoL at t1 and adolescence (t2; 12–14 y). Fathers and mothers differed in psychopathology and most parenting behavior dimensions (positive parenting, involvement, responsible parenting, poor monitoring, and corporal punishment). Father psychopathology made a relevant predictive contribution to girls’ QoL at t2. Boys’ t1 QoL was significantly influenced by maternal parenting factors (positivity and corporal punishment). Compared to mothers, fathers are faced with different individual stressors; paternal parenting behavior is different, while fathers’ influences are significant, particularly for daughters. Father-addressed pre- and intervention programs in child psychotherapeutic treatment are of high relevance.
CRIS-Team Scopus Importer:2023-08-25
Keywords: child development; father; parent-child-relations; parental influence; parenting; parenting behavior; resilience

The HER2 phenotype of circulating tumor cells in HER2-positive early breast cancer: A translational research project of a prospective randomized phase III trial - Jaeger, B. A. S.; Neugebauer, J.; Andergassen, U.; Melcher, C.; Schochter, F.; Mouarrawy, D.; Ziemendorff, G.; Clemens, M.; Abel, E. V.; Heinrich, G.; Schueller, K.; Schneeweiss, A.; et al. (PLoS ONE, 2017)
BACKGROUND: HER2 is one of the predominant therapeutic targets in breast cancer. The metastatic selection process may lead to discrepancies between the HER2 status of the primary tumor and circulating tumor cells (CTCs). This study analyzed the HER2 status of CTCs in patients with HER2-positive primary breast cancer at the time of diagnosis. Aim of the study was to assess potential discordance of HER2 status between primary tumor and CTCs, as this may have important implications for the use of HER2-targeted therapy. METHODS: The number and HER2 status of CTCs out of 30ml peripheral blood were assessed in 642 patients using the CellSearch System (Janssen Diagnostics, USA). The cutoff for CTC positivity was the presence of at least 1 CTC, and the cutoff for HER2 positivity of CTCs was the presence of at least 1 CTC with a strong HER2 staining. RESULTS: 258 (40.2%) of the 642 patients were positive for CTCs (median 2; range 1-1,689). 149 (57.8%) of these 258 patients had at least 1 CTC with strong HER2 staining. The presence of HER2-positive CTCs was not associated with tumor size (p = 0.335), histopathological grading (p = 0.976), hormone receptor status (ER: p = 0.626, PR: p = 0.263) or axillary lymph node involvement (p = 0.430). Overall, 83 (32.2%) of the CTC-positive patients exclusively had CTCs with strong HER2 staining, whereas 31 (12.0%) had only CTCs with negative HER2 staining. Within-sample variation in the HER2 status of CTCs was found in 86 (57.8%) of the 149 patients with more than 1 CTC. CONCLUSION: This study demonstrated that discordance between the HER2 expression of CTCs and that of the primary tumor frequently occurs in early breast cancer. Future follow-up evaluation will assess whether this discrepancy may contribute to trastuzumab resistance.
EVALuna2:36134

The influence of obesity on survival in early, high-risk breast cancer: results from the randomized SUCCESS A trial - Widschwendter, Peter; Friedl, Thomas W. P.; Schwentner, Lukas; Degregorio, Nikolaus; Jaeger, Bernadette; Schramm, Amelie; Bekes, Inga; Deniz, Miriam; Lato, Krisztian; Weissenbacher, Tobias; Kost, Bernd; Andergassen, Ulrich; et al. (Breast Cancer Research, 2015)
Obese breast cancer patients have worse prognosis than normal weight patients, but the level at which obesity is prognostically unfavorable is unclear.This retrospective analysis was performed using data from the SUCCESS A trial, in which 3754 patients with high-risk early breast cancer were randomized to anthracycline- and taxane-based chemotherapy with or without gemcitabine. Patients were classified as underweight/normal weight (body mass index (BMI) < 25.0), overweight (BMI 25.0-29.9), slightly obese (BMI 30.0-34.9), moderately obese (BMI 35.0-39.9) and severely obese (BMI >= 40.0), and the effect of BMI on disease-free survival (DFS) and overall survival (OS) was evaluated (median follow-up 65 months). In addition, subgroup analyses were conducted to assess the effect of BMI in luminal A-like, luminal B-like, HER2 (human epidermal growth factor 2)-positive and triple-negative tumors.Multivariate analyses revealed an independent prognostic effect of BMI on DFS (p = 0.001) and OS (p = 0.005). Compared with underweight/normal weight patients, severely obese patients had worse DFS (hazard ratio (HR) 2.70, 95 % confidence interval (CI) 1.71-4.28, p < 0.001) and OS (HR 2.79, 95 % CI 1.63-4.77, p < 0.001), while moderately obese, slightly obese and overweight patients did not differ from underweight/normal weight patients with regard to DFS or OS. Subgroup analyses showed a similar significant effect of BMI on DFS and OS in patients with triple-negative breast cancer (TNBC), but not in patients with other tumor subtypes.Severe obesity (BMI >= 40) significantly worsens prognosis in early breast cancer patients, particularly for triple-negative tumors.Clinicaltrials.gov NCT02181101 . Registered September 2005.
EVALuna2:17573

The influence of prenatal risks on attachment, emotion regulation and emotional and behavioral problems in middle childhood: A prospective longitudinal study - Ziegler, Clara; Zalan, Vera; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (International Attachment Conference, 2017)

The integrative epigenomic-transcriptomic landscape of ER positive breast cancer - Gao, Yang; Jones, Allison; Fasching, Peter; Rübner, Matthias; Beckmann, Matthias; Widschwendter, Martin; Teschendorff, Andrew E. (Clinical Epigenetics, 2015)
While recent integrative analyses of copy number and gene expression data in breast cancer have revealed a complex molecular landscape with multiple subtypes and many oncogenic/tumour suppressor driver events, much less is known about the role of DNA methylation in shaping breast cancer taxonomy and defining driver events.Here, we applied a powerful integrative network algorithm to matched DNA methylation and RNA-Seq data for 724 estrogen receptor (ER)-positive (ER+) breast cancers and 111 normal adjacent tissue specimens from The Cancer Genome Atlas (TCGA) project, in order to identify putative epigenetic driver events and to explore the resulting molecular taxonomy. This revealed the existence of nine functionally deregulated epigenetic hotspots encompassing a total of 146 genes, which we were able to validate in independent data sets encompassing over 1000 ER+ breast cancers. Integrative clustering of the matched messenger RNA (mRNA) and DNA methylation data over these genes resulted in only two clusters, which correlated very strongly with the luminal-A and luminal B subtypes. Overall, luminal-A and luminal-B breast cancers shared the same epigenetically deregulated hotspots but with luminal-B cancers exhibiting increased aberrant DNA methylation patterns relative to normal tissue. We show that increased levels of DNA methylation and mRNA expression deviation from the normal state define a marker of poor prognosis. Our data further implicates epigenetic silencing of WNT signalling antagonists and bone morphogenetic proteins (BMP) as key events underlying both luminal subtypes but specially of luminal-B breast cancer. Finally, we show that DNA methylation changes within the identified epigenetic interactome hotspots do not exhibit mutually exclusive patterns within the same cancer sample, instead exhibiting coordinated changes within the sample.Our results indicate that the integrative DNA methylation and transcriptomic landscape of ER+ breast cancer is surprisingly homogeneous, defining two main subtypes which strongly correlate with luminal-A/B subtype status. In particular, we identify WNT and BMP signalling as key epigenetically deregulated tumour suppressor pathways in luminal ER+ breast cancer, with increased deregulation seen in luminal-B breast cancer.
EVALuna2:17561

The International Endometriosis Evaluation Program (IEEP Study) - A Systematic Study for Physicians, Researchers and Patients - Burghaus, Stefanie; Fehm, T.; Fasching, Peter; Blum, Simon; Renner, Stefan; Baier, F.; Brodkorb, T.; Fahlbusch, C.; Findeklee, S.; Häberle, Lothar; Heusinger, K.; Hildebrandt, T.; et al. (Geburtshilfe und Frauenheilkunde, 2016)
INTRODUCTION: Endometriosis is a heterogeneous disease characterized by a range of different presentations. It is usually diagnosed when patients present with pain and/or infertility, but it has also been diagnosed in asymptomatic patients. Because of the different diagnostic approaches and diverse therapies, time to diagnosis can vary considerably and the definitive diagnosis may be delayed, with some cases not being diagnosed for several years. Endometriosis patients have many unmet needs. A systematic registration and follow-up of endometriosis patients could be useful to obtain an insight into the course of the disease. The validation of biomarkers could contribute to the development of diagnostic and predictive tests which could help select patients for surgical assessment earlier and offer better predictions about patients who might benefit from medical, surgical or other interventions. The aim is also to obtain a better understanding of the etiology, pathogenesis and progression of the disease. MATERIAL AND METHODS: To do this, an online multicenter documentation system was introduced to facilitate the establishment of a prospective multicenter case-control study, the IEEP (International Endometriosis Evaluation Program) study. We report here on the first 696 patients with endometriosis included in the program between June 2013 and June 2015. RESULTS: A documentation system was created, and the structure and course of the study were mapped out with regard to data collection and the collection of biomaterials. CONCLUSION: The documentation system permits the history and clinical data of patients with endometriosis to be recorded. The IEEP combines this information with biomaterials and uses it for scientific studies. The recorded data can also be used to evaluate clinical quality control measures such as the certification parameters used by the EEL (European Endometriosis League) to assess certified endometriosis centers.
EVALuna2:32966

The PI3K Pathway: Background and Treatment Approaches - Lux, Michael P.; Fasching, Peter; Schrauder, Michael G.; Hein, Alexander; Jud, Sebastian; Rauh, Claudia; Beckmann, Matthias (Breast Care, 2016)
Two-thirds of all breast cancer patients with metastases have a hormone receptor (HR)-positive/human epidermal growth factor receptor 2 (HER2)-negative subtype. Endocrine therapy is the treatment of choice in these patients since in addition to its effectiveness it can also maintain the patients' quality of life over a longer term. However, 44-62% of postmenopausal patients with metastatic breast carcinoma have primary tamoxifen resistance. After 3-5 years, 30-40% of the patients receiving tamoxifen treatment develop secondary resistance. Understanding the way in which resistance develops is therefore essential for developing treatment approaches that can prevent or reverse endocrine resistance. The phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) signaling pathway plays a central role here. As a result of the numerous interactions involved, complex issues arise that need to be taken into account in the development and use of therapeutic agents. In addition, this signaling pathway is the one that most frequently undergoes mutations in breast cancer. The prognostic and predictive significance of individual mutations has not yet been fully explained, but it might provide a basis for patient selection in clinical studies. Initial research results on the use of PI3K inhibitors suggest that this may be a highly promising therapeutic approach, with an acceptable side effect profile.
EVALuna2:33003

The placental mTOR-pathway: correlation with early growth trajectories following intrauterine growth restriction? - Fahlbusch, F. B.; Menendez-Castro, C.; Nögel, Stephanie; Marek, I.; Beckmann, Matthias; Schleussner, E.; Ruebner, M.; Huebner, H.; Dörr, Helmuth-Günther; Schild, R. L.; Doetsch, J.; Rascher, Wolfgang; et al. (Journal of Developmental Origins of Health and Disease, 2015)
Idiopathic intrauterine growth restriction (IUGR) is a result of impaired placental nutrient supply. Newborns with IUGR exhibiting postnatal catch-up growth are of higher risk for cardiovascular and metabolic co-morbidities in adult life. Mammalian target of rapamycin (mTOR) was recently shown to function as a placental nutrient sensor. Thus, we determined possible correlations of members of the placental mTOR signaling cascade with auxologic parameters of postnatal growth. The protein expression and activity of mTOR-pathway signaling components, Akt, AMP-activated protein kinase ?, mTOR, p70S6kinase1 and insulin receptor substrate-1 were analysed via western blotting in IUGR v. matched appropriate-for-gestational age (AGA) placentas. Moreover, mTOR was immunohistochemically stained in placental sections. Data from western blot analyses were correlated with retrospective auxological follow-up data at 1 year of age. We found significant catch-up growth in the 1st year of life in the IUGR group. MTOR and its activated form are immunohistochemically detected in multiple placental compartments. We identified correlations of placental mTOR-pathway signaling components to auxological data at birth and at 1 year of life in IUGR. Analysis of the protein expression and phosphorylation level of mTOR-pathway components in IUGR and AGA placentas postpartum, however, did not reveal pathognomonic changes. Our findings suggest that the level of activated mTOR correlates with early catch-up growth following IUGR. However, the complexity of signals converging at the mTOR nexus and its cellular distribution pattern seem to limit its potential as biomarker in this setting.
EVALuna2:17439

The Randomized AMBORA Trial: Impact of Pharmacological/Pharmaceutical Care on Medication Safety and Patient-Reported Outcomes During Treatment With New Oral Anticancer Agents - Dürr, Pauline; Schlichtig, Katja; Kelz, Carolin; Deutsch, Birgit; Maas, Renke; Eckart, Michael J.; Wilke, Jochen; Wagner, Harald; Wolff, Kerstin; Preuß, Caroline; Brückl, Valeska; Meidenbauer, Norbert; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Oral anticancer drugs (eg, kinase inhibitors) play an important role in cancer therapy. However, considerable challenges regarding medication safety of oral anticancer drugs have been reported. Randomized, controlled, multicenter studies on the impact of intensified clinical pharmacological/pharmaceutical care on patient safety and patient treatment perception are lacking. METHODS: Patients were eligible for the randomized, multicenter AMBORA study, if they were newly started on any of the oral anticancer drugs approved in 2001 or later without restriction to certain tumor entities. Patients were randomly assigned to receive either standard of care (control group) or an additional, intensified clinical pharmacological/pharmaceutical care, which included medication management and structured patient counseling, over a period of 12 weeks (intervention group). Primary end points were the number of antitumor drug-related problems (ie, side effects and unresolved medication errors) and patient treatment satisfaction with the oral anticancer therapy after 12 weeks measured with the Treatment Satisfaction Questionnaire for Medication, category convenience. RESULTS: Two hundred two patients were included. Antitumor drug-related problems were significantly lower in the intervention compared with the control group (3.85 v 5.81 [mean], P < .001). Patient treatment satisfaction was higher in the intervention group (Treatment Satisfaction Questionnaire for Medication, convenience; 91.6 v 74.4 [mean], P < .001). The hazard ratio for the combined end point of severe side effects (Common Terminology Criteria for Adverse Events ≥ 3), treatment discontinuation, unscheduled hospital admission, and death was 0.48 (95% CI, 0.32 to 0.71, P < .001) in favor of the intervention group. CONCLUSION: Treatment with oral anticancer drugs is associated with a broad range of medication errors and side effects. An intensified clinical pharmacological/pharmaceutical care has considerable, positive effects on the number of medication errors, patient treatment perception, and severe side effects.
CRIS-Team Scopus Importer:2021-07-02

Therapy landscape in patients with metastatic HER2-positive breast cancer: Data from the PRAEGNANT real-world breast cancer registry - Lux, Michael P.; Nabieva, Naiba; Hartkopf, Andreas D.; Huober, Jens; Volz, Bernhard; Taran, Florin-Andrei; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; et al. (Cancers, 2019)
This study presents comprehensive real-world data on the use of anti-human epidermal growth factor receptor 2 (HER2) therapies in patients with HER2-positive metastatic breast cancer (MBC). Specifically, it describes therapy patterns with trastuzumab (H), pertuzumab + trastuzumab (PH), lapatinib (L), and trastuzumab emtansine (T-DM1). The PRAEGNANT study is a real-time, real-world registry for MBC patients. All therapy lines are documented. This analysis describes the utilization of anti-HER2 therapies as well as therapy sequences. Among 1936 patients in PRAEGNANT, 451 were HER2-positive (23.3%). In the analysis set (417 patients), 53% of whom were included in PRAEGNANT in the first-line setting, 241 were treated with H, 237 with PH, 85 with L, and 125 with T-DM1 during the course of their therapies. The sequence PH ! T-DM1 was administered in 51 patients. Higher Eastern Cooperative Oncology Group (ECOG) scores, negative hormone receptor status, and visceral or brain metastases were associated with more frequent use of this therapy sequence. Most patients received T-DM1 after treatment with pertuzumab. Both novel therapies (PH and T-DM1) are utilized in a high proportion of HER2-positive breast cancer patients. As most patients receive T-DM1 after PH, real-world data may help to clarify whether the efficacy of this sequence is similar to that in the approval study.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Advanced breast cancer; Antihormone therapy; Chemotherapy; Her2 c-ERBB2; Her2/neu; Lapatinib; Metastatic; Pertuzumab; T-DM1; Trastuzumab

The safety and satisfaction of ovarian tissue cryopreservation in prepubertal and adolescent girls - Lotz, Laura; Barbosa, Patricia Reis; Knorr, Christian; Hofbeck, Louisa; Hoffmann, Inge; Beckmann, Matthias; Antoniadis, Sophia; Dittrich, Ralf (Reproductive Biomedicine Online, 2020)
Research question: Is ovarian tissue cryopreservation (OTC) for fertility preservation in prepubertal and adolescent girls safe, and who would benefit most from the procedure? Design: Survey and retrospective study including patients who had OTC under the age of 18 years in a single centre for fertility preservation. Serum anti-Müllerian hormone levels were measured as a marker for detection of diminished ovarian reserve. Results: Fifty-three from 102 women participated in the survey (12 deceased, 19 declined, 17 unreachable, 1 palliative). The average age at OTC was 14.8 ± 2.3 (range: 6–17) years and at survey 21.9 ± 4.3 (range: 16–33) years. Ovarian tissue retrieval (laparoscopy: n = 45, laparotomy: n = 8) was without complications in 52 cases. In 23 (53.5%) of the 43 women who were post-menarchal at OTC, transient amenorrhoea occurred. At survey, 15 women reported a regular menstrual cycle, 25 used oral contraceptives, 9 women reported hormone replacement therapy due to primary ovary insufficiency and 4 had amenorrhoea. Two patients reported the birth of a healthy child after IVF, while 51 patients are still childless, mostly due to their young age (mean: 21.2 years). To date, one patient has had transplantation of the ovarian tissue (17 years at cryopreservation). Forty-nine of the interviewees would again decide on OTC, while three argued against it on the basis of the previous financial cost; one woman was unsure. Conclusions: Children with cancer may be at risk for gonadal insufficiency. OTC is practically the only technique that can be offered to young girls. The procedure is safe and well accepted.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Adolescent females; Cancer; Fertility preservation; Ovarian tissue cryopreservation; Ovarian tissue transplantation; Prepubertal females

The UGT1A6_19_GG genotype is a breast cancer risk factor - Justenhoven, Christina; Obazee, Ofure; Winter, Stefan; Rabstein, Sylvia; Lotz, Anne; Harth, Volker; Pesch, Beate; Brüning, Thomas; Baisch, Christian; Hartikainen, Jaana M.; Mannermaa, Arto; Kosma, Veli Matti; et al. (Frontiers in Genetics, 2013)
Validation of an association between the UGT1A6_19_T>G (rs6759892) polymorphism and overall breast cancer risk. A pilot study included two population-based case-control studies from Germany (MARIE-GENICA). An independent validation study comprised four independent breast cancer case-control studies from Finland (KBCP, OBCS), Germany (BBCC), and Sweden (SASBAC). The pooled analysis included 7418 cases and 8720 controls from all six studies. Participants were of European descent. Genotyping was done by MALDI-TOF MS and statistical analysis was performed by logistic regression adjusted for age and study. The increased overall breast cancer risk for women with the UGT1A6_19_GG genotype which was observed in the pilot study was confirmed in the set of four independent study collections (OR 1.13, 95% CI 1.05-1.22; p = 0.001). The pooled study showed a similar effect (OR 1.09, 95% CI 1.04-1.14; p = 0.001). The risk effect on the basis of allele frequencies was highly significant, the pooled analysis showed an OR of 1.11 (95% CI 1.06-1.16; p = 5.8 × 10-6). We confirmed the association of UGT1A6_19_GG with increased overall breast cancer risk and conclude that our result from a well powered multi-stage study adds a novel candidate to the panel of validated breast cancer susceptibility loci. © 2013 Justenhoven, Obazee, Winter, Rabstein, Lotz, Harth, Pesch, Brüning, Baisch, Hartikainen, Mannermaa, Kosma, Kataja, Winqvist, Pylkäs, Jukkola-Vuorinen, Grip, Fasching, Beckmann, Ekici, Hein, Hall, Li, Chang-Claude, Flesch-Janys, Seibold, Rudolph, Hamann, Ko and Brauch.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer risk; Metabolism; Polymorphism; UGT1A6; Validation

The use of PAMG-1 testing in patients with preterm labor, intact membranes and a short sonographic cervix reduces the rate of unnecessary antenatal glucocorticoid administration - Kehl, Sven; Weiss, Christel; Pretscher, Jutta; Baier, Friederike; Faschingbauer, Florian; Beckmann, Matthias; Stumpfe, Florian (Journal of Perinatal Medicine, 2021)
Objectives: To assess the frequency of antenatal corticosteroid (ACS) administration in cases with shortened cervical length by addition of placental alpha-microglobulin-1 (PAMG-1) testing to sonographic examination. Methods: Single centre retrospective cohort study. Rate of ACS administration was compared between cases with cervical length between 15 and 25 mm and cases with positive PAMG-1 testing and cervical length between 15 and 25 mm. We evaluated the following outcome parameters: Rate of ACS administration, gestational age at delivery, time to delivery, delivery within seven days, delivery <34 and <37 weeks' gestation, rate of admission to neonatal intensive care unit (NICU). Results: In total, 130 cases were included. "PAMG-1 group" consisted of 68 women, 62 cases built the "historical control group". ACS administration was performed less frequently in the "PAMG-1 cohort" (18 (26%) vs. 46 (74%); p<0.001). The rate of delivery within seven days did not differ (2 (3%) vs. 4 (6.5%); p=0.4239). The rates of delivery <34 weeks' gestation (7 (10%) vs. 9 (15%); p=0.4643) and <37 weeks' gestation (19 (28%) vs. 26 (42%); p=0.0939) did not differ. Time to delivery interval was longer in the PAMG-1 group (61.5 vs. 43 days, p=0.0117). NICU admission occurred more often in the "historical control group" (22 (38%) vs. 28 (60%); p=0.0272). Conclusions: Addition of biomarker testing can help to avoid unnecessary ACS administrations in women with shortened cervical length.
CRIS-Team WoS Importer:2021-12-03

The villoglandular Adenocarcinoma of the Cervix as a Tumor Model. A Literature Analysis - Dietl, Anna; Aumann, K.; Beckmann, Matthias (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triple-negative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2-positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype ‘lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach.<br

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triplenegative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype 'lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach. (C) 2018 S. Karger GmbH, Freiburg
EVALuna2:34061

TILGen study-immunological targets in patients with breast cancer : Influence of tumor-infiltrating lymphocytes - Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Mackensen, Andreas; Kremer, Anita; Reimann, Hannah; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Häberle, Lothar; Gaß, Paul; et al. (Pathologe, 2018)
BACKGROUND: The interaction of our immune system with breast cancer (BC) cells prompted the investigation of tumor-infiltrating lymphocytes (TILs) and targeted, tumor antigen-specific immunotherapy. OBJECTIVES: Correlation between TILs and pathological complete response (pCR) after neoadjuvant systemic therapy (NACT). Tumor-specific antigens (TSAs) in HER2+ and triple negative BC and establishment of TSA-specific therapies within the interdisciplinary TILGen study. METHODS: Illustration of the TILGen study design. Assessment of TILs and correlation with pCR within this BC study. RESULTS: pCR was achieved in 38.4% (56/146) and associated with estrogen receptor/progesterone receptor negative (ER-/PR-) and HER2+ tumors. Lymphocytic predominant BC (LPBC) was found in 16.4% (24/146), particularly in ER-/PR- (ER-: 27.3% vs. ER+: 9.9%, PR-: 22.3% vs. PR+: 8.2%), large, and poorly differentiated BC. TILs were significantly correlated with pCR in multivariate analysis. In LPBC, pCR was achieved in 66.7%, whereas it was 32.8% in non-LPBC. CONCLUSIONS: First results confirm the influence of the human immune system on the response to NACT in HER2+ and triple negative BC. TSA-specific immunotherapy might improve the outcome in BC patients but there is an urgent need for comprehensive studies to further investigate this issue.
EVALuna2:35097

Time and Resources Needed to Document Patients with Breast Cancer from Primary Diagnosis to Follow-up - Results of a Single-center Study - Lux, Michael P.; Sell, C. S.; Fasching, Peter; Seidl-Ertel, Janine; Bani, Mayada; Schrauder, M. G.; Jud, Sebastian; Löhberg, Christian; Rauh, C.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strnad, Vratislav; et al. (Geburtshilfe und Frauenheilkunde, 2014)
Aim: Certification of breast centers helps improve the quality of care but requires additional resources, particularly for documentation. There are currently no published data on the actual staff costs and financial resources required for such documentation. The aim of this study was to determine the time and resources required to document a patient with primary breast cancer from diagnosis to the end of follow-up, to establish a database for future strategic decisions. Material and Methods: All diagnostic and therapeutic procedures of patients with primary breast cancer were recorded at the University Breast Center of Franconia. All time points for documentation were evaluated using structured interviews. The times required to document a representative number of patients were determined and combined with the staff costs of the different professional groups, to calculate the financial resources required for documentation. Results: A total of 494 time points for documentation were identified. The study also identified 21 departments and 20 different professional groups involved in the documentation. The majority (54 %) of documentation was done by physicians. 62 % of all documentation involved outpatients. The results of different scenarios for the diagnosis, therapy and follow-up of breast cancer patients in a certified breast center showed that the time required for documentation can be as much as 105 hours, costing EUR 4135. Conclusion: This analysis shows the substantial staffing and financial costs required for documentation in certified centers. A multi-center study will be carried out to compare the costs for certified breast centers of varying sizes with the costs of non-certified care facilities.
EVALuna2:6642

Timing of sequential use of double-balloon catheter and oral misoprostol for induction of labor - Kehl, Sven; Böhm, Lea; Weiss, Christel; Heimrich, Jutta; Dammer, Ulf; Baier, Friederike; Suetterlin, Marc; Beckmann, Matthias; Faschingbauer, Florian (Journal of Obstetrics and Gynaecology Research, 2016)
AIM: The best time to commence cervical ripening with a balloon catheter is unknown. The aim of this study was to evaluate whether application of a balloon catheter in the morning or in the evening is better when sequential prostaglandin application is planned. METHODS: This multicenter historical cohort study included 415 women with an unfavorable cervix undergoing labor induction at term. Labor was induced with a double-balloon catheter and the sequential use of oral misoprostol if necessary. The balloon catheter was placed in the morning group between 02:00-15:00 and in the evening group between 15:00-02:00. The primary outcome measure was the cesarean section rate. Secondary outcome measures included failed labor induction (no vaginal delivery within 72 h). RESULTS: The cesarean section rate did not differ between the groups (morning 26.9%, evening 24.3%; P = 0.5553); however, more women in the morning group did not deliver within 72 h (8.8% vs 3.1%; P = 0.0138). In nulliparous women, labor induction failed more often in the morning group (12% vs. 4%, P = 0.043). In parous women, the induction-to-delivery interval was longer in the morning group (1756 vs. 1349 min; P = 0.046), and there were fewer deliveries within 24 h (35% vs. 56%, P = 0.016). CONCLUSIONS: When sequential use of a double-balloon catheter and oral misoprostol for labor induction is planned, the preferable time for catheter placement is in the evening. This resulted in fewer failed inductions in nulliparous women and a shorter induction-to-delivery interval and more deliveries within 24 h in parous women.
EVALuna2:32943

Tomosynthese - Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Fasching, Peter; Uder, Michael (Chirurgische Praxis, 2016)
Full field digital mammography (FFDM) is the most important method for early diagnosis of breast cancer. The typical overlapping of normal and pathological tissue during the standard 2D projection, however, often reduces the specificity and sensitivity of the mammographic investigation. Digital breast tomosynthesis (DBT) provides on the basis of a limited number of single images with different projection angles not superimposed tomograms and may remove the unwanted masking by superimposed structures. Clinical studies show that the digital tomosynthesis has the real potential to reduce the recall rate and simultaneously increase the cancer detection rate, especially in women with dense breasts (detection and volumetry). The use of tomosynthesis seems to be superior to full field digital mammography in mammography screening. Other possibilities of the tomosynthesis are the dual energy mammography, contrast medium-enhanced mammography and intervention.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contrast medium-enhanced mammography; Dual energy mammography; Full-field digital mammography; Intervention; Mammography screening; Tomosynthesis

Total laparoscopic hysterectomy: how does training for surgeons in a standardized operation affect hospitals and patients? - Hildebrandt, Thomas; Emir, Seher; Boosz, Alexander; Beckmann, Matthias; Mueller, Andreas (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: Surgical training usually means inexperienced physicians initially doing operations supervised by an experienced physician, to gain the experience and skills needed to conduct surgery independently. Various issues arise here for both hospitals and patients. Are training procedures associated with higher complication rates, blood losses, and transfusion rates? What does training in the operating room ultimately cost in terms of valuable surgical time? Do longer hospitalization periods potentially mean financial losses for the hospital under the diagnosis-related groups (DRG) system? METHODS: A retrospective analysis was carried out of data for 571 patients who underwent total laparoscopic hysterectomy (TLH) in the Department of Gynecology at the University of Erlangen from 2009 to 2012, with/without adnexectomy, due to benign indication; and of data for 255 patients who underwent the same procedures in Karlsruhe Municipal Hospital in 2013-2014. The patients were classified into two groups: those in whom surgery was carried out by experienced specialists who had carried out at least 40 independent operations; and those in whom it was carried out by a trainee resident who had personally done fewer than 40 operations. RESULTS: In the two groups, the patients had similar mean body mass indexes, uterus weights, and blood losses. Patients in the specialist group were slightly older. There were no differences in complication rates. Over two-thirds of complications occurred in patients with previous surgery. Procedures by residents took significantly longer. Hospitalization periods in both groups were still below the mean threshold length of stay under Germany's DRG system, so that no income losses occurred even with training procedures. CONCLUSIONS: Training and teaching operations supervised by experienced surgeons are just as safe as operations by experienced surgeons themselves. Interpretation of these data is of course limited by the retrospective study design; patients treated by specialists tended to have more prior operations and were older, with a trend toward larger uteri. Surgical training, as the example of TLH in benign indication shows here, involves an additional time of approximately 10-20 min per operation. With regard to the revenue situation, the hospitalization periods in both groups were within the profit zone for the hospital concerned.
EVALuna2:209955

Touch Imprint Cytology and Stereotactically-Guided Core Needle Biopsy of Suspicious Breast Lesions: 15-Year Follow-up - Schulz-Wendtland, Rüdiger; Fasching, Peter; Bani, Mayada; Lux, Michael P.; Jud, Sebastian; Rauh, C.; Bayer, C.; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Uder, Michael; Löhberg, Christian (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Stereotactically-guided core needle biopsies (CNB) of breast tumours allow histological examination of the tumour without surgery. Touch imprint cytology (TIC) of CNB promises to be useful in providing same-day diagnosis for counselling purposes and for planning future surgery. Having addressed the issue of accuracy of immediate microscopic evaluation of TIC, we wanted to re-examine the usefulness of this procedure in light of the present health care climate of cost containment by incorporating the surgical 15-year follow-up data and outcome. Patients and Methods: From January until December 1996 we performed TIC in core needle biopsies of 173 breast tumours in 169 patients, consisting of 122 malignant and 51 benign tumours. Histology of core needle biopsies was proven by surgical histology in all malignant and in 5 benign tumours. Surgical breast biopsy was not performed in 46 patients with 46 benign lesions, as the histological result from the core needle biopsy and the result of the TIC were in agreement with the suspected diagnosis from the complementary breast diagnostics. A 15-year follow-up of these patients followed in 2013 and follow-up data was collected from 40 women. Results: In the 15-year follow-up of the 40 benign lesions primarily confirmed using CNB and TIC, a diagnostic sensitivity, specificity, positive and negative predictive value and accuracy of 100 % was found. Conclusion: TIC and stereotactically guided CNB showed excellent long-term follow-up in patients with benign breast lesions. The use of TIC to complement CNB can therefore provide immediate cytological diagnosis of breast lesions.
EVALuna2:6752

Towards a Computable Data Corpus of Temporal Correlations between Drug Administration and Lab Value Changes - Newe, Axel; Wimmer, Stefan; Neubert, Antje; Becker, Linda; Prokosch, Hans-Ulrich; Beckmann, Matthias; Fietkau, Rainer; Forster, Christian; Neurath, Markus; Schett, Georg; Ganslandt, Thomas (PLoS ONE, 2015)
Background The analysis of electronic health records for an automated detection of adverse drug reactions is an approach to solve the problems that arise from traditional methods like spontaneous reporting or manual chart review. Algorithms addressing this task should be modeled on the criteria for a standardized case causality assessment defined by the World Health Organization. One of these criteria is the temporal relationship between drug intake and the occurrence of a reaction or a laboratory test abnormality. Appropriate data that would allow for developing or validating related algorithms is not publicly available, though. Methods In order to provide such data, retrospective routine data of drug administrations and temporally corresponding laboratory observations from a university clinic were extracted, transformed and evaluated by experts in terms of a reasonable time relationship between drug administration and lab value alteration. Result The result is a data corpus of 400 episodes of normalized laboratory parameter values in temporal context with drug administrations. Each episode has been manually classified whether it contains data that might indicate a temporal correlation between the drug administration and the change of the lab value course, whether such a change is not observable or whether a decision between those two options is not possible due to the data. In addition, each episode has been assigned a concordance value which indicates how difficult it is to assess. This is the first open data corpus of a computable ground truth of temporal correlations between drug administration and lab value alterations. Discussion The main purpose of this data corpus is the provision of data for further research and the provision of a ground truth which allows for comparing the outcome of other assessments of this data with the outcome of assessments made by human experts. It can serve as a contribution towards systematic, computerized ADR detection in retrospective data. With this lab value curve data as a basis, algorithms for detecting temporal relationships can be developed, and with the classification made by human experts, these algorithms can immediately be validated. Due to the normalization of the lab value data, it allows for a generic approach rather than for specific or solitary drug/lab value combination

Toxicity Assessment of a Phase III Study Evaluating FEC-Doc and FEC-Doc Combined with Gemcitabine as an Adjuvant Treatment for High-Risk Early Breast Cancer: the SUCCESS-A Trial - Schroeder, L.; Rack, B.; Sommer, H.; Koch, J. G.; Weissenbacher, T.; Janni, W.; Schneeweiss, A.; Rezai, M.; Lorenz, R.; Jaeger, B.; Schramm, A.; Häberle, Lothar; et al. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: This paper aims to evaluate the toxicity profile of additive gemcitabine to adjuvant taxane-based chemotherapy in breast cancer patients.Methods:Patients enrolled in this open-label randomized controlled Phase III study were treated with 3 cycles of epirubicin-fluorouracil-cyclophosphamide (FEC) chemotherapy followed by 3 cycles of docetaxel with those receiving 3 cycles of FEC followed by 3 cycles of gemcitabine-docetaxel (FEC-DG). 3690 patients were evaluated according to National Cancer Institute (NCI) toxicity criteria (CTCAE). The study medications were assessed by the occurrence of grade 3-4 adverse events, dose reductions, postponements of treatment cycles and granulocyte colony-stimulating factor (G-CSF) support.Results:No differences in neutropenia or febrile neutropenia were demonstrated. However, thrombocytopenia was significantly increased with FEC-DG treatment (2.0 vs. 0.5 %, p < 0.001), as was leukopenia (64.1 vs. 58.5 %, p < 0.001). With FEC-DG significantly more G-CSF support in cycles 4 to 6 (FEC-DG: 57.8 %, FEC-D: 36.3 %, p < 0.001) was provided. Transaminase elevation was significantly more common with FEC-DG (SGPT: 6.3 %, SGOT: 2 %), whereas neuropathy (1.2 %), arthralgia (1.6 %) and bone pain (2.6 %) were more common using FEC-D. Dose reductions > 20 % (4 vs. 2.4 %) and postponement of treatment cycles (0.9 vs. 0.4 %) were significantly more frequent in the FEC-DG arm. Eight deaths occurred during treatment in the FEC-DG arm and four in the FEC-D arm.Conclusion:The addition of gemcitabine increased hematological toxicity and was associated with more dose reductions and postponements of treatment cycles.
EVALuna2:32982

TP53-based interaction analysis identifies cis-eQTL variants for TP53BP2, FBXO28, and FAM53A that associate with survival and treatment outcome in breast cancer - Fagerholm, Rainer; Khan, Sofia; Schmidt, Marjanka K.; Garcia-Closas, Montserrat; Heikkila, Pavi; Saarela, Jani; Beesley, Jonathan; Jamshidi, Maral; Aittomaki, Kristiina; Liu, Jianjun; Ali, H. Raza; Andrulis, Irene L.; et al. (Oncotarget, 2017)
TP53 overexpression is indicative of somatic TP53 mutations and associates with aggressive tumors and poor prognosis in breast cancer. We utilized a two-stage SNP association study to detect variants associated with breast cancer survival in a TP53-dependent manner. Initially, a genome-wide study (n = 575 cases) was conducted to discover candidate SNPs for genotyping and validation in the Breast Cancer Association Consortium (BCAC). The SNPs were then tested for interaction with tumor TP53 status (n = 4,610) and anthracycline treatment (n = 17,828). For SNPs interacting with anthracycline treatment, siRNA knockdown experiments were carried out to validate candidate genes.In the test for interaction between SNP genotype and TP53 status, we identified one locus, represented by rs10916264 (p(interaction) = 3.44 × 10-5; FDR-adjusted p = 0.0011) in estrogen receptor (ER) positive cases. The rs10916264 AA genotype associated with worse survival among cases with ER-positive, TP53-positive tumors (hazard ratio [HR] 2.36, 95% confidence interval [C.I] 1.45 - 3.82). This is a cis-eQTL locus for FBXO28 and TP53BP2; expression levels of these genes were associated with patient survival specifically in ER-positive, TP53-mutated tumors. Additionally, the SNP rs798755 was associated with survival in interaction with anthracycline treatment (p(interaction) = 9.57 × 10-5, FDR-adjusted p = 0.0130). RNAi-based depletion of a predicted regulatory target gene, FAM53A, indicated that this gene can modulate doxorubicin sensitivity in breast cancer cell lines.If confirmed in independent data sets, these results may be of clinical relevance in the development of prognostic and predictive marker panels for breast cancer.
EVALuna2:36150

Transcriptome-wide association study of breast cancer risk by estrogen-receptor status - Feng, Helian; Gusev, Alexander; Pasaniuc, Bogdan; Wu, Lang; Long, Jirong; Abu-Full, Zomoroda; Aittomaki, Kristiina; Andrulis, Irene L.; Anton-Culver, Hoda; Antoniou, Antonis C.; Arason, Adalgeir; Arndt, Volker; et al. (Genetic Epidemiology, 2020)
Previous transcriptome-wide association studies (TWAS) have identified breast cancer risk genes by integrating data from expression quantitative loci and genome-wide association studies (GWAS), but analyses of breast cancer subtype-specific associations have been limited. In this study, we conducted a TWAS using gene expression data from GTEx and summary statistics from the hitherto largest GWAS meta-analysis conducted for breast cancer overall, and by estrogen receptor subtypes (ER+ and ER−). We further compared associations with ER+ and ER− subtypes, using a case-only TWAS approach. We also conducted multigene conditional analyses in regions with multiple TWAS associations. Two genes, STXBP4 and HIST2H2BA, were specifically associated with ER+ but not with ER– breast cancer. We further identified 30 TWAS-significant genes associated with overall breast cancer risk, including four that were not identified in previous studies. Conditional analyses identified single independent breast-cancer gene in three of six regions harboring multiple TWAS-significant genes. Our study provides new information on breast cancer genetics and biology, particularly about genomic differences between ER+ and ER− breast cancer.
CRIS-Team Scopus Importer:2020-03-20
Keywords: breast cancer subtype; causal gene; GWAS; TWAS

Transplantation of refreezed ovarian tissue after unexpected occurrence of endometriosis - Dietl, Anna; Dittrich, Ralf; Hoffmann, Inge; Denschlag, D.; Hanjalic-Beck, A.; Mueller, A.; Beckmann, Matthias; Lotz, Laura (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Treatment landscape and prognosis after treatment with trastuzumab emtansine - Laakmann, Elena; Emons, Julius; Taran, Florin Andrei; Janni, Wolfgang; Uhrig, Sabrina; Overkamp, Friedrich; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2020)
Purpose Pertuzumab and T-DM1 are two efficient anti-HER2 treatments for patients with HER2-positive advanced breast cancer. While pertuzumab is usually given in first-line treatment and T-DM1 in second-line treatment, standard therapy options seem to be exhausted up to now after the treatment of patients with these two therapy options. Therefore, it is important to have data that describes the therapy situation and prognosis after T-DM1 treatment. Methods The PRAEGNANT metastatic breast cancer registry (NCT02338167) is a prospective registry for breast cancer patients with a focus on molecular biomarkers. Patients of all therapy lines with any kind of treatment are eligible. Collected data comprises therapies, adverse events, quality of life and other patient reported outcomes. Here we report on the patient characteristics and descriptive prognostic data for HER2-positive patients who have completed a treatment with T-DM1. Therapy patterns after T-DM1 and progression-free survival are reported as well as overall survival. Results A total of 85 patients were identified for the study who were prospectively observed during therapy after the termination of T-DM1. The main reason for T-DM1 termination was progress. Following T-DM1, lapatinib, trastuzumab and chemotherapy were the main therapy choices. Median progression-free survival was 4.8 months (95% CI: 3.2-6.3) and median overall survival was 18.4 months (95% CI: 15.5-21.3). Conclusions Therapy options after T-DM1 in a real-world setting seem to exhibit a relevant clinical efficacy, supporting the concept of continuous anti-HER2 treatments in the advanced therapy setting for breast cancer patients. Novel therapies are needed to improve the rather short median progression-free survival.
CRIS-Team Scopus Importer:2020-11-20
Keywords: advanced breast cancer; antihormone therapy; chemotherapy; HER2 c-erbB2; HER2/neu; lapatinib; metastatic; pertuzumab; T-DM1; trastuzumab

Treatment landscape of advanced breast cancer patients with hormone receptor positive HER2 negative tumors - Data from the German PRAEGNANT breast cancer registry - Hartkopf, Andreas D.; Huober, Jens; Volz, Bernhard; Nabieva, Naiba; Taran, Florin-Andrei; Schwitulla, Judith; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; et al. (BREAST, 2018)
PURPOSE: This study describes comprehensive data from a breast cancer registry concerning the use of endocrine treatment (ET) and chemotherapy in the first, second and higher therapy lines in hormone receptor (HR) positive, HER2 negative metastatic breast cancer (MBC). METHODS: The PRAEGNANT study is a real-time registry for patients with MBC. Therapies were categorized into the following categories: chemotherapy, aromatase inhibitor (AI), tamoxifen, fulvestrant, or everolimus plus ET and reported for first, second and third line or higher therapy use. Also treatment sequences for the first, second and third therapy line were analyzed. RESULTS: This analysis includes 958 patients with HR positive, HER2 negative MBC. 42.7% were treated with a chemotherapy in the first therapy line compared to 45.9% receiving an ET. A total of 25.9% were treated with everolimus plus anti-hormone therapy in any therapy line. 34.1% were treated with fulvestrant as single agent therapy. Analyzing therapy sequences, the administration of three different chemotherapies in a row was the most frequently used pattern. CONCLUSIONS: This analysis shows that across all three first therapy lines chemotherapy is a dominant therapy for HR positive, HER2 negative MBC patients. Education about the efficacy of ET might help to increase its use and decrease the possible burden of chemotherapy related toxicities.
EVALuna2:36436

Trophoblast expression dynamics of the tumor suppressor gene gastrokine 2 - Fahlbusch, Fabian B.; Ruebner, Matthias; Hübner, Hanna; Volkert, Gudrun; Bartunik, Hannah; Winterfeld, Ilona; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Marek, Ines; Wachter, David; Schneider-Stock, Regine; et al. (Histochemistry and Cell Biology, 2015)
Gastrokines (GKNs) were originally described as stomach-specific tumor suppressor genes. Recently, we identified GKN1 in extravillous trophoblasts (EVT) of human placenta. GKN1 treatment reduced the migration of the trophoblast cell line JEG-3. GKN2 is known to inhibit the proliferation, migration and invasion of gastric cancer cells and may interact with GKN1. Recently, GKN2 was detected in the placental yolk sac of mice. We therefore aimed to further characterize placental GKN2 expression. By immunohistochemistry, healthy first-trimester placenta showed ubiquitous staining for GKN2 at its early gestational stage. At later gestational stages, a more differentiated expression pattern in EVT and villous cytotrophoblasts became evident. In healthy third-trimester placenta, only EVT retained strong GKN2 immunoreactivity. In contrast, HELLP placentas showed a tendency of increased levels of GKN2 expression with a more prominent GKN2 staining in their syncytiotrophoblast. Choriocarcinoma cell lines did not express GKN2. Besides its trophoblastic expression, we found human GKN2 in fibrotic villi, in amniotic membrane and umbilical cord. GKN2 co-localized with smooth muscle actin in villous myofibroblasts and with HLA-G and GKN1 in EVT. In the rodent placenta, GKN2 was specifically located in the spongiotrophoblast layer. Thus, the gestational age-dependent and compartment-specific expression pattern of GKN2 points to a role for placental development. The syncytial expression of GKN2 in HELLP placentas might represent a reduced state of functional differentiation of the syncytiotrophoblast. Moreover, the specific GKN2 expression in the rodent spongiotrophoblast layer (equivalent to human EVT) might suggest an important role in EVT physiology.
EVALuna2:6725

Tumor handling of early-stage cervical cancer: A literature analysis of villoglandular adenocarcinoma of the cervix - Dietl, Anna; Aumann, Konrad; Beckmann, Matthias (Anticancer Research, 2020)
Background/Aim: Recent studies have demonstrated the inferior overall survival outcomes of patients with early-stage cervical cancer who undergo minimally invasive surgery (MIS). One possible explanation for these unexpected results is intraoperative tumor manipulation. Materials and Methods: Considering this hypothesis, we have reviewed the literature on the oncological outcomes of patients with villoglandular adenocarcinoma (VGA) of the cervix, an uncommon variant of cervical cancer that has an excellent prognosis. Results: VGA generally presents as an exophytic mass arising from the endocervix. In a systematic review, we identified 221 patients treated surgically for VGA (FIGO stage Ia-Ib1). Of these, 11 developed recurrence, and four died. The recurrence sites in 8 cases were the pelvis (n=3), vaginal cuff (n=3), episiotomy scar (n=1), and cervix (n=1). Furthermore, 23 VGA-patients were treated by MIS, four experienced recurrence, and one died. Three intraabdominal metastases after MIS were reported. Conclusion: Excessive tumor-handling during MIS or manipulations, e.g. cervix-dilation (during delivery), can worsen the otherwise excellent prognosis.
CRIS-Team Scopus Importer:2020-06-19
Keywords: Early-stage cervical cancer; Minimal handling; Minimal invasive surgery; Review; Villoglandular adenocarcinoma of the uterine cervix

Tumour-infiltrating inflammatory cells in early breast cancer: An underrated prognostic and predictive factor? - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
The role of tumour-infiltrating inflammatory cells (TIICs) in the disease progression of hormone-receptor-positive breast cancer (HR+ BC) is largely unclear since it is generally regarded as the least immunogenic BC subtype. This study investigated the prognostic significance of CD1a+ dendritic cells, CD20+ B cells, CD45RO+ memory T cells and CD4+ T-helper cells in HR+ BC. One hundred and forty-six patients were treated for early stage, distant-metastases-free HR+ BC in an accelerated partial breast irradiation (APBI) phase II trial. Immunohistochemistry was used to double-stain two adjoining sets of tissue microarrays from pre-RT (radiotherapy) tumour resection samples for CD1a/CD20 and CD45RO/CD4. Cell densities of CD1a+, CD20+, CD45RO+ and CD4+ TIICs in the stromal and intraepithelial compartment were registered semiautomatically. High densities of CD20+ and CD4+ TIICs were strongly associated with reduced disease-free survival (DFS), while high stromal CD45RO+ TIIC densities were indicators of subsequent successful treatment. An immunoscore based on CD20+ and CD45RO+ TIIC densities identified three different risk groups (p < 0.001). Thus, contrary to current assumptions, intratumoural immune cell composition might be an important prognostic indicator and a possible contributing factor in the outcome of HR+ BC and should be the subject of further research. Specifically, B-cell infiltration entailed an increased relapse rate and could play an important role in disease progression.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Accelerated partial breast irradiation; Breast cancer; CD1a; CD20; CD4; CD45RO; Hormone receptor positive; Immunoscore; Prognosis; TIL

Tumour stage distribution and survival of malignant melanoma in Germany 2002-2011 - Schoffer, Olaf; Schuelein, Stefanie; Arand, Gerlinde; Arnholdt, Hans; Baaske, Dieter; Bargou, Ralf C.; Becker, Nikolaus; Beckmann, Matthias; Bodack, Yves; Boehme, Beatrix; Bozkurt, Tayfun; Breitsprecher, Regine; et al. (BMC Cancer, 2016)
Over the past two decades, there has been a rising trend in malignant melanoma incidence worldwide. In 2008, Germany introduced a nationwide skin cancer screening program starting at age 35. The aims of this study were to analyse the distribution of malignant melanoma tumour stages over time, as well as demographic and regional differences in stage distribution and survival of melanoma patients.Pooled data from 61 895 malignant melanoma patients diagnosed between 2002 and 2011 and documented in 28 German population-based and hospital-based clinical cancer registries were analysed using descriptive methods, joinpoint regression, logistic regression and relative survival.The number of annually documented cases increased by 53.2% between 2002 (N = 4 779) and 2011 (N = 7 320). There was a statistically significant continuous positive trend in the proportion of stage UICC I cases diagnosed between 2002 and 2011, compared to a negative trend for stage UICC II. No trends were found for stages UICC III and IV respectively. Age (OR 0.97, 95% CI 0.97-0.97), sex (OR 1.18, 95% CI 1.11-1.25), date of diagnosis (OR 1.05, 95% CI 1.04-1.06), 'diagnosis during screening' (OR 3.24, 95% CI 2.50-4.19) and place of residence (OR 1.23, 95% CI 1.16-1.30) had a statistically significant influence on the tumour stage at diagnosis. The overall 5-year relative survival for invasive cases was 83.4% (95% CI 82.8-83.9%).No distinct changes in the distribution of malignant melanoma tumour stages among those aged 35 and older were seen that could be directly attributed to the introduction of skin cancer screening in 2008.
EVALuna2:19618

Twenty-five-year-old Woman with Bilateral Borderline Ovarian Tumour Desiring to Preserve Fertility - Case Report and Literature Review on the Current State of Fertility Preservation in Women with Borderline Ovarian Tumours - Findeklee, S.; Lotz, Laura; Heusinger, K.; Hoffmann, Inge; Dittrich, Ralf; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2016)
Borderline ovarian tumours are semimalignant tumours occurring unilaterally or bilaterally with a peak incidence among women of reproductive age. Since the affected women often wish to preserve fertility, particular precautions must be taken when counselling the patient and obtaining consent prior to planning an individual treatment. Options for preserving fertility include an organ-sparing surgical procedure and cryopreservation of oocytes and/or ovarian tissue. In this article, we report on a 25-year-old patient with a bilateral seromucinous borderline tumour who desired all fertility-preserving options. In order to perform the procedure without delay, we opted to perform luteal phase stimulation prior to oocyte retrieval. We conclude by discussing the current literature on the state of fertility preservation in the treatment of borderline ovarian tumours.
EVALuna2:32942

Two truncating variants in FANCC and breast cancer risk - Dork, Thilo; Peterlongo, Paolo; Mannermaa, Arto; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Ahearn, Thomas; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Aronson, Kristan J.; Augustinsson, Annelie; et al. (Scientific Reports, 2019)
Fanconi anemia (FA) is a genetically heterogeneous disorder with 22 disease-causing genes reported to date. In some FA genes, monoallelic mutations have been found to be associated with breast cancer risk, while the risk associations of others remain unknown. The gene for FA type C, FANCC, has been proposed as a breast cancer susceptibility gene based on epidemiological and sequencing studies. We used the Oncoarray project to genotype two truncating FANCC variants (p.R185X and p.R548X) in 64,760 breast cancer cases and 49,793 controls of European descent. FANCC mutations were observed in 25 cases (14 with p.R185X, 11 with p.R548X) and 26 controls (18 with p.R185X, 8 with p.R548X). There was no evidence of an association with the risk of breast cancer, neither overall (odds ratio 0.77, 95%CI 0.44–1.33, p = 0.4) nor by histology, hormone receptor status, age or family history. We conclude that the breast cancer risk association of these two FANCC variants, if any, is much smaller than for BRCA1, BRCA2 or PALB2 mutations. If this applies to all truncating variants in FANCC it would suggest there are differences between FA genes in their roles on breast cancer risk and demonstrates the merit of large consortia for clarifying risk associations of rare variants.
CRIS-Team Scopus Importer:2019-09-17

Ultrasound Fetal Weight Estimation in Diabetic Pregnancies - Pretscher, Jutta; Kehl, Sven; Stumpfe, Florian M.; Mayr, Andreas; Schmid, Matthias; Schild, Ralf L.; Beckmann, Matthias; Faschingbauer, Florian (Journal of Ultrasound in Medicine, 2019)
Objectives To evaluate different formulas for estimating fetal weight in diabetic pregnancies. Methods This retrospective study evaluated the precision of ultrasound fetal weight estimation in 756 pregnancies complicated by gestational diabetes between 2002 and 2016. The estimated fetal weights (EFWs) were obtained within 7 days of delivery from 10 weight estimation formulas and were compared with pair-wise matched controls from 15,701 patients. The precision of the evaluated formulas for EFW was analyzed by median absolute percentage errors (MAPEs), mean percentage errors (MPEs), and proportions of estimates within 10% of actual birth weight. Results Among the tested formulas, the lowest MAPE was detected with formula I of Hadlock et al (Am J Obstet Gynecol 1985; 151:333-337), and the formula of Schild et al (Ultrasound Obstet Gynecol 2004; 23:30-35) had the highest proportion of estimates within the 10% range. The EFW in diabetic patients showed a slight trend toward overestimation in comparison with the matched controls (MPE estimates showed a trend toward more positive values). In most of the EFW formulas that were evaluated, no significant differences were detected in MAPEs and estimates within the 10% range. The MPE estimates with most formulas in both groups were close to zero. Overall, the differences between most of the evaluated formulas were small. Conclusions Little evidence was found for differences in the accuracy of the EFW in diabetic pregnancies and controls. The Hadlock I formula showed the lowest MAPE, and the Schild formula had the highest proportion of estimates within the 10% range.
CRIS-Team WoS Importer:2019-09-13

Ultrasound Fetal Weight Estimation in Diabetic Pregnancies - Pretscher, Jutta; Kehl, Sven; Stumpfe, Florian M.; Mayr, Andreas; Schmid, Matthias; Schild, Ralf L.; Beckmann, Matthias; Faschingbauer, Florian (Journal of Ultrasound in Medicine, 2020)
OBJECTIVES: To evaluate different formulas for estimating fetal weight in diabetic pregnancies. METHODS: This retrospective study evaluated the precision of ultrasound fetal weight estimation in 756 pregnancies complicated by gestational diabetes between 2002 and 2016. The estimated fetal weights (EFWs) were obtained within 7 days of delivery from 10 weight estimation formulas and were compared with pair-wise matched controls from 15,701 patients. The precision of the evaluated formulas for EFW was analyzed by median absolute percentage errors (MAPEs), mean percentage errors (MPEs), and proportions of estimates within 10% of actual birth weight. RESULTS: Among the tested formulas, the lowest MAPE was detected with formula I of Hadlock et al (Am J Obstet Gynecol 1985; 151:333-337), and the formula of Schild et al (Ultrasound Obstet Gynecol 2004; 23:30-35) had the highest proportion of estimates within the 10% range. The EFW in diabetic patients showed a slight trend toward overestimation in comparison with the matched controls (MPE estimates showed a trend toward more positive values). In most of the EFW formulas that were evaluated, no significant differences were detected in MAPEs and estimates within the 10% range. The MPE estimates with most formulas in both groups were close to zero. Overall, the differences between most of the evaluated formulas were small. CONCLUSIONS: Little evidence was found for differences in the accuracy of the EFW in diabetic pregnancies and controls. The Hadlock I formula showed the lowest MAPE, and the Schild formula had the highest proportion of estimates within the 10% range.
EVALuna2:212326

Unbiased high-dimensional flow cytometry identified NK and DC immune cell signature in Luminal A-type and triple negative breast cancer - Heger, Lukas; Heidkamp, Gordon Frederik; Amon, Lukas; Nimmerjahn, Falk; Bäuerle, Tobias; Maier, Andreas; Erber, Ramona; Hartmann, Arndt; Hack, Carolin; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; et al. (OncoImmunology, 2024)
Breast cancer is the most common malignancy in women worldwide and a highly heterogeneous disease. Four different subtypes are described that differ in the expression of hormone receptors as well as the growth factor receptor HER2. Treatment modalities and survival rate depend on the subtype of breast cancer. However, it is still not clear which patients benefit from immunotherapeutic approaches such as checkpoint blockade. Thus, we aimed to decipher the immune cell signature of the different breast cancer subtypes based on high-dimensional flow cytometry followed by unbiased approaches. Here, we show that the frequency of NK cells is reduced in Luminal A and B as well as triple negative breast cancer and that the phenotype of residual NK cells is changed toward regulatory CD11b−CD16− NK cells. Further, we found higher frequencies of PD-1+ CD4+ and CD8+ T cells in triple negative breast cancer. Moreover, while Luminal A-type breast cancer was enriched for CD14+ cDC2 (named type 3 DC (DC3)), CD14− cDC2 (named DC2) were more frequent in triple negative breast cancer. In contrast, HER2-enriched breast cancer did not show major alterations in the composition of the immune cell compartment in the tumor microenvironment. These findings suggest that patients with Luminal A- and B-type as well as triple negative breast cancer might benefit from immunotherapeutic approaches targeting NK cells.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Breast cancer; immune cell signature; NK cells; PD-1; tumor microenvironment

Unexpected diagnose of endometriosis in women undergoing ovarian tissue transplantation - Lotz, Laura; Dietl, Anna; Hoffmann, Inge; Mueller, A.; Burghaus, Stefanie; Beckmann, Matthias; Dittrich, Ralf (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Update Breast Cancer 2017 - Implementation of Novel Therapies - Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Huober, Jens B.; Lueftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2017)
In recent years, numerous new therapy options for patients with breast cancer have been developed in clinical studies, with some options already approved for routine treatment. As the speed at which innovations are introduced increases, the importance of conferences also increases, as conferences are where the data underpinning new therapies are usually presented for the first time. This review looks at publications of the ASCO (American Society of Clinical Oncology) and ESMO (European Society of Medical Oncology) conferences in 2017, summarizes them and evaluates them in the context of existing data. The focus is on new insights for neoadjuvant therapy and new treatment options in the metastatic setting, such as the use of CDK4/6 inhibitors or PARP inhibitors. The first results of treatments with checkpoint inhibitors are presented. With the patent expiry of trastuzumab, a number of study results for trastuzumab biosimilars have also been published. The digitization of patient care provides the first results on quality of life and prognosis of patients with advanced cancer. Digital communications between patients and physicians are being evaluated in several studies in Germany. As the discussion about patient-relevant endpoints for patients in the metastatic setting continues, overall survival rates from studies of big endocrine-based therapies are urgently needed. Preliminary analyses of small study cohorts offer initial insights. In the context of improving patient care, in the coming years, questions will center on which patients particularly benefit from certain therapies and which patients need particular protection from specific side effects. Questions about these predictors are raised in many scientific projects as attention increasingly focuses on this topic.
EVALuna2:36116

Update Breast Cancer 2018 (Part 1) - Primary Breast Cancer and Biomarkers - Taran, Florin-Andrei; Schneeweiss, Andreas; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Woeckel, Achim; Ettl, Johannes; et al. (Geburtshilfe und Frauenheilkunde, 2018)
This summary provides an overview of how new therapies or new aspects of established therapies relate to the latest findings. Neoadjuvant therapy, local therapy, new aspects of systemic therapy, and prognostic and predictive factors are presented. In the neoadjuvant setting, the association between pathological complete response (pCR) and prognosis is still of interest as is the identification of new molecular predictors for new therapies such as CDK4/6 inhibitors. As regards surgical treatment, the target is still to reduce the aggressiveness of surgery. To achieve this, a better understanding particularly of ductal carcinoma in situ is required. With regard to systemic therapy, more data on the best combinations and therapy sequences for existing therapies is available. Finally, the use of prognostic and predictive factors may help to avoid overtreatment and ensure that patients only receive therapies which have been shown to be effective for their specific condition and have fewer side effects.
EVALuna2:51286

Update Breast Cancer 2018 (Part 2) - Advanced Breast Cancer, Quality of Life and Prevention - Schneeweiss, Andreas; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Woeckel, Achim; Ettl, Johannes; et al. (Geburtshilfe und Frauenheilkunde, 2018)
The treatment of metastatic breast cancer has become more complicated due to increasing numbers of new therapies which need to be tested. Therapies are now being developed to treat special clinical or molecular subgroups. Even though intrinsic molecular subtypes play a major role, more and more new therapies for subgroups and histological subtypes are being developed, such as the use of PARP inhibitors to treat patients with BRCA mutations (breast and ovarian cancer). Supportive therapies are also evolving, allowing problems such as alopecia or nausea and vomiting to be treated more effectively. Treatment-related side effects have a direct impact on the prognosis of patients with metastatic breast cancer, and supportive therapy can improve compliance. Digital tools could be useful to establish better patient management systems. This overview provides an insight into recent trials and how the findings could affect routine treatment. Current aspects of breast cancer prevention are also presented.
EVALuna2:51284

Update in the certification of endometriosis centers Neues in der Zertifizierung von Endometriosezentren - Schaefer, Sebastian D.; Sillem, Martin; Schweppe, Karl-Werner; Burghaus, Stefanie; Beckmann, Matthias (Gynäkologe, 2021)
Endometriosis is among the most frequent diseases of women during reproductive age. The disease itself but also its treatment significantly impairs quality of life. Top-level specialized centers have been established to ensure diagnosis and treatment. The certification process defined by Stiftung Endometriose-Forschung (SEF), European Endometriosis League (EEL) and patient self-help organisations is intended to guarantee comparable quality. Diagnosis and treatment need to be based on current guidelines. The redefinition of the term center by the German Gemeinsame Bundesausschuss (G-BA) has made it necessary to adapt the established staging concept. In the future specialized “endometriosis practices”, “endometriosis units” and “endometriosis centers” will be certified according to predefined criteria.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Guidelines; Integrative medicine; Quality of life; Reproduction; Shared decision making

Update S3-Leitlinie Zervixkarzinom: Diagnostik, Therapie und Nachsorge - Stübs, Frederik; Beckmann, Matthias; Fehm, Tanja (Best Practice Onkologie, 2022)
There is constant progress in the treatment of women with cervical cancer. Therefore, the German S3 guideline requires regular revision. The new statements and recommendations are based on a systematic literature review. The revision process involved around 50 specialist societies under the expert guidance of the Association of the Scientific Medical Societies in Germany (Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften, AWMF). The new standard of care in surgical therapy for cervical cancer up to FIGO stage IB1 is open radical hysterectomy. The evidence base for the role of intensity-modulated radiotherapy and individualized brachytherapy was strengthened. Patients with metastatic cervical cancer benefit from addition of bevacizumab to standard chemotherapy in first-line treatment. From the second line onward, the use of pembrolizumab is recommended for women with PD-L1-positive cervical cancer.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Bevacizumab; Brachytherapy; Open radical hysterectomy; Pembrolizumab; PET-CT

Updates on the role of receptor activator of nuclear factor κB/receptor activator of nuclear factor κB ligand/osteoprotegerin pathway in breast cancer risk and treatment - Bayer, Christian M.; Beckmann, Matthias; Fasching, Peter (Current Opinion in Obstetrics & Gynecology, 2017)
PURPOSE OF REVIEW: Treatment with bisphosphonates and denosumab is the standard of care in bone metastatic disease. In addition, the adjuvant therapy of denosumab or bisphosphonates is very effective to prevent loss of bone mineral density, for example in osteoporosis. However, it is still unclear if this therapy has an influence on preventing cancer. RECENT FINDINGS: Since the identification of novel genes in the 1980s, it took about 30 years until denosumab, as a fully human mAb against receptor activator of nuclear factor (NF)-κB ligand (RANKL), could be introduced to clinical practice. The discovery of the receptor activator of NF-κB/RANKL/osteoprotegerin pathway in the 1990s is an example of how modern databases of genes were utilized to discover new pathways relevant to a variety of diseases. The essential role of this pathway for the function, differentiation and survival of osteoclasts, and the influence on the bone microenvironment helped to understand the vicious circle of bone resorption and destruction in many skeletal diseases. SUMMARY: In the following review, we discuss the important role of rational targeting concerning receptor activator of NF-κB/RANKL/osteoprotegerin and the bisphosphonate therapy and provide an update for the related treatment of patients suffering from breast cancer and further implications for clinical practice and research using denosumab as a potential chemoprevention in BRCA1-related breast cancer.
EVALuna2:36158

Use of a molecular Registry (PRAEGNANT) for Patient-Selection and Biomarker-Analysis for the SHERBOC Study - Hübner, Hanna; Kurbacher, C.; Kuesters, G.; Hartkopf, A. D.; Lux, M. P.; Huober, J.; Volz, B.; Taran, F. A.; Overkamp, F.; Tesch, H.; Häberle, Lothar; Lueftner, D.; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Use of complementary and integrative medicine among German breast cancer patients: predictors and implications for patient care within the PRAEGNANT study network - Fremd, Carlo; Hack, Carolin; Schneeweiss, Andreas; Rauch, Geraldine; Wallwiener, Diethelm; Brucker, Sara Yvonne; Taran, Florin-Andrei; Hartkopf, Andreas; Overkamp, Friedrich; Tesch, Hans; Fehm, Tanja; Hadji, Peyman; et al. (Archives of Gynecology and Obstetrics, 2017)
PURPOSE: The present study aims to analyze a cohort of advanced breast cancer patients in Germany to assess their interest in complementary and alternative medicine (CAM) and patient's use of most frequent CAM methods. PATIENTS AND METHODS: Based on the PREGNANT real-time breast cancer registry which is a multicenter study in Germany, questionnaires of 580 patients with advanced breast cancer were evaluated. The implemented questionnaire for CAM asked for general interest in CAM and for patient's use of different CAM methods at present and in the past. The interest and application of CAM were analyzed for association with patients' characteristics such as tumor, patient, and therapy characteristics. RESULTS: In total, 436 out of 580 (75%) patients claimed to be interested in CAM. Further, interest in CAM is significantly correlated with younger age and absence of metastasis at the time of diagnosis. Multivariate analysis confirmed the patient's age and distant disease status at the time of diagnosis as related to interest in CAM. A total of 56.4% of patients applied any CAM method in the past. Moreover, with increasing lines of therapies, the more frequent use of CAM was observed. Hereby, praying, vitamin supplements, and other food supplements were most frequently applied. CONCLUSION: Our data demonstrate high overall interest and frequent use of CAM in advanced breast cancer patients supporting a strong demand of breast cancer patients for complementary counseling and treatments additional to the established cancer therapies. It is indispensable to implement counseling and evidence-based complementary treatments into clinical routine of cancer centers and to adapt postgraduate medical education, respectively.
EVALuna2:36145

Use of Granulocyte-colony Stimulating Factor During Chemotherapy and Its Association With CA27.29 and Circulating Tumor Cells-Results From the SUCCESS A Trial - Hepp, Philip; Fasching, Peter; Beckmann, Matthias; Fehm, Tanja; Salmen, Jessica; Hagenbeck, Carsten; Jaeger, Bernadette; Widschwendter, Peter; De Gregorio, Nikolaus; Schochter, Fabienne; Mahner, Sven; Harbeck, Nadia; et al. (Clinical Breast Cancer, 2018)
Little is known about the effect of granulocyte colony-stimulating factor (G-CSF) treatment during adjuvant chemotherapy on prognostic markers. The present study explored the association between G-CSF and changes in cancer antigen (CA)27.29 and circulating tumor cell (CTC) levels during therapy.A total of 3754 node-positive or high-risk node-negative early-stage breast cancer patients were treated within the SUCCESS-A trial (simultaneous study of gemcitabine-docetaxel combination adjuvant treatment, as well as extended bisphosphonate and surveillance-trial). CA27.29 and CTCs were determined before the start and within 6 weeks after the end of chemotherapy.Overall, 1324 of the 2646 patients (50.0%) available for analysis had >= 1 G-CSF applications during chemotherapy. G-CSF application was significantly associated with CA27.29 status before and after chemotherapy (? = 30.6, df = 3; P < .001), because 238 patients (18.0%) with G-CSF treatment but only 146 (11.0%) without G-CSF treatment switched from a negative CA27.29 status before to a positive CA27.29 status after chemotherapy. In addition, patients with G-CSF application showed a significantly greater increase in CA27.29 levels after chemotherapy compared with patients without any G-CSF application during chemotherapy (Mann-Whitney U test; Z = -7.81, P < .001). No significant association was found between G-CSF application and CTC status before or after chemotherapy (? = 1.2, df = 3; P = .75).Cautious interpretation is needed regarding elevated levels of MUC-1-derived tumor markers such as CA27.29 shortly after adjuvant chemotherapy when G-CSF has been given, because G-CSF treatment was associated with increased CA27.29 levels after chemotherapy.
EVALuna2:56150

Using automated texture features to determine the probability for masking of a tumor on mammography, but not ultrasound - Haeberle, Lothar; Hack, Carolin; Heusinger, Katharina; Wagner, Florian; Jud, Sebastian; Uder, Michael; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Wittenberg, Thomas; Fasching, Peter (European Journal of Medical Research, 2017)
BACKGROUND: Tumors in radiologically dense breast were overlooked on mammograms more often than tumors in low-density breasts. A fast reproducible and automated method of assessing percentage mammographic density (PMD) would be desirable to support decisions whether ultrasonography should be provided for women in addition to mammography in diagnostic mammography units. PMD assessment has still not been included in clinical routine work, as there are issues of interobserver variability and the procedure is quite time consuming. This study investigated whether fully automatically generated texture features of mammograms can replace time-consuming semi-automatic PMD assessment to predict a patient's risk of having an invasive breast tumor that is visible on ultrasound but masked on mammography (mammography failure). METHODS: This observational study included 1334 women with invasive breast cancer treated at a hospital-based diagnostic mammography unit. Ultrasound was available for the entire cohort as part of routine diagnosis. Computer-based threshold PMD assessments ("observed PMD") were carried out and 363 texture features were obtained from each mammogram. Several variable selection and regression techniques (univariate selection, lasso, boosting, random forest) were applied to predict PMD from the texture features. The predicted PMD values were each used as new predictor for masking in logistic regression models together with clinical predictors. These four logistic regression models with predicted PMD were compared among themselves and with a logistic regression model with observed PMD. The most accurate masking prediction was determined by cross-validation. RESULTS: About 120 of the 363 texture features were selected for predicting PMD. Density predictions with boosting were the best substitute for observed PMD to predict masking. Overall, the corresponding logistic regression model performed better (cross-validated AUC, 0.747) than one without mammographic density (0.734), but less well than the one with the observed PMD (0.753). However, in patients with an assigned mammography failure risk >10%, covering about half of all masked tumors, the boosting-based model performed at least as accurately as the original PMD model. CONCLUSION: Automatically generated texture features can replace semi-automatically determined PMD in a prediction model for mammography failure, such that more than 50% of masked tumors could be discovered.
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD9.usinga
Keywords: Mammographic density; Mammography screening; Masking; Risk prediction; Sensitivity; Texture analysis; Variable selection

Using Probability for Pathological Complete Response (pCR) as a Decision Support Marker for Neoadjuvant Chemotherapy in HER2 Negative Breast Cancer Patients - a Survey Among Physicians - Gaß, Paul; Untch, Michael; Mueller, Volkmar; Moebus, Volker; Thomssen, Christoph; Häberle, Lothar; Erber, Ramona; Hein, Alexander; Jud, Sebastian; Lux, Michael P.; Hack, Carolin; Hartmann, Arndt; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Background: In women with early breast cancer, a pathological complete response (pCR) after neoadjuvant chemotherapy is reported to be associated with an improvement of the survival. The aim of this survey among physicians was to investigate whether the probability of achieving pCR in patients with a hormone receptor-positive, HER2-negative disease encourages physicians to recommend neoadjuvant chemotherapy. Methods: The study was conducted via an online survey that was sent to 493 physicians, who were either known as members of national guideline committees, heads of breast cancer centers, being high recruiters in clinical trials or leading a private practice. Participants were asked about a specific case that should resemble patients for whom it is unclear, whether they should be treated with chemotherapy. Results: 113 (24.5%) physicians participated at the survey, out of which 96.5% had a work experience of more than 10 years and 94.7% were board certified in their specialty. A total of 84.1% would consider pCR for a decision concerning neoadjuvant chemotherapy. With regard to the pCR probability, 2.7 and 10.6% of the participants demanded at least a pCR rate of 5 and 10%, respectively, while 25.7% were satisfied with 20% probability, and another 25.7% with a pCR rate of 30%. Conclusions: The vast majority of the long-term experienced physicians would embrace the implementation of a further method such as the prediction of pCR probability in clinical routine to support decision making regarding the necessity of neoadjuvant chemotherapy. The cut-off of around 30% pCR probability seems to be a realizable rate to distinguish patient groups.
EVALuna2:34856

Uterine contractility changes in a perfused swine uterus model induced by local anesthetics procaine, lidocaine, and ropivacaine - Weinschenk, Fabian; Dittrich, Ralf; Mueller, Andreas; Lotz, Laura; Beckmann, Matthias; Weinschenk, Stefan W. (PLoS ONE, 2018)
BACKGROUND: Local anesthetics (LAs) are increasingly used as therapeutics due to their multiple molecular effects. They may be potential agents also in gynecology and reproductive medicine. The objective of this study was to investigate the contractility response of the perfused swine uterus to different concentrations of the LAs procaine, lidocaine, and ropivacaine. METHODS AND FINDINGS: In an extracorporeal perfusion model with fresh swine uteri, effects of administered boli of these three LAs in concentrations of 0.1 mg/mL, 0.5 mg/mL and 1.0 mg/mL on uterine contractility and peristalsis were assessed using an intrauterine double-chip micro-catheter. A dose-dependent increase in intrauterine pressure (IUP) in the isthmus and corpus uteri was observed after the administration of the ester-LA procaine 0.1, 0.5, and 1.0%, which was not seen with lower concentrations, or buffer solution. An increase-decrease curve was found after increasing concentrations of the amide-LA lidocaine and ropivacaine, with an IUP plateau with 0.1 and 0.5%, and a decrease with 1% (p<0.01). All reactions were seen in both the isthmus and corpus uteri. The difference of the contractility pattern between ester- and amide-LA at 1% concentration was significant. CONCLUSION: LAs dose-dependently modulate contractility in non-pregnant swine uteri. The amid-LAs lidocaine and ropivacaine reduce contractility in higher concentrations and may be used as therapeutics in disorders with increased uterine contractility, as dysmenorrhoea, endometriosis, and infertility. The multiple molecular effects of LAs may explain these effects. This in-vitro pilot study in vitro provides initial data for designing further studies to transfer the results onto humans.
EVALuna2:209956

Variable expression of the disialoganglioside gd2 in breast cancer molecular subtypes - Erber, Ramona; Kailayangiri, Sareetha; Hübner, Hanna; Rübner, Matthias; Hartmann, Arndt; Häberle, Lothar; Meyer, Julia; Völkl, Simon; Mackensen, Andreas; Landgraf, Laura; Geppert, Carol-Immanuel; Schulz-Wendtland, Rüdiger; et al. (Cancers, 2021)
The disialoganglioside GD2 is a tumor-associated antigen that may allow for the application of targeted immunotherapies (anti-GD2 antibodies, GD2 CAR T cells) in patients with neuroblastoma and other solid tumors. We retrospectively investigated GD2 expression in a breast cancer cohort, using immunohistochemistry (IHC) and immunofluorescence (IF) on tissue microarrays (TMAs), and its impact on survival. GD2 expression on IHC (n = 568) and IF (n = 503) was investigated in relation to subtypes and patient outcome. Overall, 50.2% of the 568 IHC-assessed samples and 69.8% of the 503 IF-assessed samples were GD2-positive. The highest proportion of GD2-positive tumors was observed in luminal tumors. Significantly fewer GD2-positive cases were detected in triple-negative breast cancer (TNBC) compared with other subtypes. The proportion of GD2-expressing tumors were significantly lower in HER2-positive breast cancer in comparison with luminal tumors on IF staining (but not IHC). GD2 expression of IHC or IF was not significantly associated with disease-free or overall survival, in either the overall cohort or in individual subtypes. However, GD2 expression can be seen in more than 50% of breast cancer cases, with the highest frequency in hormone receptorpositive tumors. With this high expression frequency, patients with GD2-positive advanced breast cancer of all subtypes may benefit from GD2-targeting immunotherapies, which are currently subject to clinical testing.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Breast cancer; Disialoganglioside; GD2; Immunofluorescence; Immunohistochemistry; Prognosis

Variants in genes encoding small GTPases and association with epithelial ovarian cancer susceptibility - Earp, Madalene; Tyrer, Jonathan P.; Winham, Stacey J.; Lin, Hui-Yi; Chornokur, Ganna; Dennis, Joe; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Bandera, Elisa V.; Bean, Yukie T.; Beckmann, Matthias; et al. (PLoS ONE, 2018)
Epithelial ovarian cancer (EOC) is the fifth leading cause of cancer mortality in American women. Normal ovarian physiology is intricately connected to small GTP binding proteins of the Ras superfamily (Ras, Rho, Rab, Arf, and Ran) which govern processes such as signal transduction, cell proliferation, cell motility, and vesicle transport. We hypothesized that common germline variation in genes encoding small GTPases is associated with EOC risk. We investigated 322 variants in 88 small GTPase genes in germline DNA of 18,736 EOC patients and 26,138 controls of European ancestry using a custom genotype array and logistic regression fitting log-additive models. Functional annotation was used to identify biofeatures and expression quantitative trait loci that intersect with risk variants. One variant, ARHGEF10L (Rho guanine nucleotide exchange factor 10 like) rs2256787, was associated with increased endometrioid EOC risk (OR = 1.33, p = 4.46 x 10-6). Other variants of interest included another in ARHGEF10L, rs10788679, which was associated with invasive serous EOC risk (OR = 1.07, p = 0.00026) and two variants in AKAP6 (A-kinase anchoring protein 6) which were associated with risk of invasive EOC (rs1955513, OR = 0.90, p = 0.00033; rs927062, OR = 0.94, p = 0.00059). Functional annotation revealed that the two ARHGEF10L variants were located in super-enhancer regions and that AKAP6 rs927062 was associated with expression of GTPase gene ARHGAP5 (Rho GTPase activating protein 5). Inherited variants in ARHGEF10L and AKAP6, with potential transcriptional regulatory function and association with EOC risk, warrant investigation in independent EOC study populations.
EVALuna2:34624

Variation in NF-?B signaling pathways and survival in invasive epithelial ovarian cancer - Block, Matthew S.; Charbonneau, Bridget; Vierkant, Robert A.; Fogarty, Zachary; Bamlet, William R.; Pharoah, Paul D. P.; Chenevix-Trench, Georgia; Rossing, Mary Anne; Cramer, Daniel; Pearce, Celeste Leigh; Schildkraut, Joellen; Menon, Usha; et al. (Cancer Epidemiology Biomarkers & Prevention, 2014)
Survival in epithelial ovarian cancer (EOC) is influenced by the host immune response, yet the key genetic determinants of inflammation and immunity that affect prognosis are not known. The nuclear factor-?B (NF-?B) transcription factor family plays an important role in many immune and inflammatory responses, including the response to cancer. We studied common inherited variation in 210 genes in the NF-?B family in 10,084 patients with invasive EOC (5,248 high-grade serous, 1,452 endometrioid, 795 clear cell, and 661 mucinous) from the Ovarian Cancer Association Consortium. Associations between genotype and overall survival were assessed using Cox regression for all patients and by major histology, adjusting for known prognostic factors and correcting for multiple testing (threshold for statistical significance, P < 2.5 × 10(-5)). Results were statistically significant when assessed for patients of a single histology. Key associations were with caspase recruitment domain family, member 11 (CARD11) rs41324349 in patients with mucinous EOC [HR, 1.82; 95% confidence interval (CI), 1.41-2.35; P = 4.13 × 10(-6)] and tumor necrosis factor receptor superfamily, member 13B (TNFRSF13B) rs7501462 in patients with endometrioid EOC (HR, 0.68; 95% CI, 0.56-0.82; P = 2.33 × 10(-5)). Other associations of note included TNF receptor-associated factor 2 (TRAF2) rs17250239 in patients with high-grade serous EOC (HR, 0.84; 95% CI, 0.77-0.92; P = 6.49 × 10(-5)) and phospholipase C, gamma 1 (PLCG1) rs11696662 in patients with clear cell EOC (HR, 0.43; 95% CI, 0.26-0.73; P = 4.56 × 10(-4)). These associations highlight the potential importance of genes associated with host inflammation and immunity in modulating clinical outcomes in distinct EOC histologies.
EVALuna2:9241

Venöse Luftembolie bei vaginalen Verletzungen durch Geschlechtsverkehr - Zack, F.; Zinka, B.; Beckmann, Matthias; Banaschak, Sibylle; Fischer, H.; Gabriel, P.; Gerber, B.; Costa, S. D.; Ledwon, P.; Schwenzer, T.; Buettner, A. (Rechtsmedizin, 2019)
Background: In a criminal trial in Germany in 2013, a medical expert nominated by the defence stated in the appeal trial the controversially discussed opinion that a woman had died from an air embolism due to vaginal intercourse with exclusively penile penetration and injury to the vaginal wall. This diagnosis had been established by the expert based on histological examination of the lungs and vaginal injuries years after the woman‘s death. Objective: The frequency of the diagnosis “air embolism as a result of vaginal injuries due to intravaginal intercourse” and the modality of the diagnosis were reviewed. Material and methods: A selective literature review was performed. Furthermore, questionnaires were sent to all forensic medical institutes and to directors and chief physicians of gynecological clinics of large cities in Germany. Results: In the literature two case reports could be found, which by critical analysis showed significant errors in the diagnosis according to the state of science at the time of publication. In over 300,000 autopsies performed between 1990 and 2016, the 26 forensic medical institutes in Germany, which had answered the questionnaire, had never diagnosed “air embolism as a result of vaginal injuries due to intravaginal intercourse”. All 32 professionally experienced gynecologists who responded to the questionnaire had never in their career treated survived or fatal cases of air embolism after vaginal injuries through sexual intercourse or had knowledge of them. Conclusion: According to the survey and critical analysis of the very few published case reports, there is no evidence for a diagnosis of the cause of death as air embolism after vaginal injuries. When diagnosing a fatal venous air embolism, scientific standards should be strictly followed. A diagnosis made solely by histological examination was and is not possible according to the state of the art in forensic medicine and thus violates the principles of expert medical opinions.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Cause of death; Expert opinion; Pregnancy; Questionnaire; Sexual behavior

Villoglandular adenocarcinoma of the uterine cervix: a systematic review and meta-analysis - Dietl, Anna; Beckmann, Matthias; Aumann, Konrad (Archives of Gynecology and Obstetrics, 2021)
Purpose: Villoglandular adenocarcinoma (VGA) of the uterine cervix has been classified as a rare subtype of cervical adenocarcinoma with good prognosis. A conservative surgical approach is considered feasible. The main risk factor is the presence of other histologic types of cancer. In this largest systematic review to date, we assess oncological outcomes associated with conservative therapy compared to those associated with invasive management in the treatment of stage Ia and Ib1 VGA. Methods: Case series and case reports identified by searching the PubMed database were eligible for inclusion in this review (stage Ia–Ib1). Results: A total of 271 patients were included in our literature review. 54 (20%) patients were treated by “conservative management” (conization, simple hysterectomy, and trachelectomy) and 217 (80%) by “invasive management” (radical hysterectomy ± radiation, hysterectomy, and radiation). Recurrences of disease (RODs) were found in the conservative group in two (4%) cases and in the invasive group in nine (4%) cases. There was no significant difference in disease-free survival (DFS) according to conservative or invasive treatment (p = 0.75). The histology of VGA may be complex with underlying usual adenocarcinoma (UAC) combined with VGA. Conclusion: The excellent prognosis of pure VGA and the young age of the patients may justify the management of this tumor using a less radical procedure. The histological diagnosis of VGA is a challenge, and pretreatment should not be based solely on a simple punch biopsy but rather a conization with wide tumor-free margins.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Cervix; Conservative therapy; Invasive therapy; Review; Villoglandular adenocarcinoma

Virilizing Hilus Cell Tumor of the Ovary Associated With Efferent Ductules-like Metaplasia Within Paratubal Mesonephric Remnants - Wachter, David; Burghaus, Stefanie; Beckmann, Matthias; Agaimy, Abbas (International Journal of Gynecological Pathology, 2016)
EVALuna2:6767

Whole-Body Electromyostimulation combined with personalized Nutritional Support improves the Body Composition of Patients with advanced Cancer - Schink, Kristin; Herrmann, Hans Joachim; Schwappacher, Raphaela; Orlemann, Till; Meyer, Julia; Waldmann, Elisabeth; Wullich, Bernd; Kahlmeyer, Andreas; Fietkau, Rainer; Lubgan, Dorota; Beckmann, Matthias; Hack, Carolin; et al. (2018)
EVALuna2:35187

Xenotransplantation of cryopreserved human ovarian tissue - a systematic review of MII oocyte maturation and discussion of it as a realistic option for restoring fertility after cancer treatment - Dittrich, Ralf; Lotz, Laura; Fehm, Tanja; Kruessel, Jan; Von Wolff, Michael; Toth, Bettina; Van Der Ven, Hans; Schuering, Andreas N.; Wuerfel, Wolfgang; Hoffmann, Inge; Beckmann, Matthias (Fertility and Sterility, 2015)
To systematically review the reporting of MII (MII) oocyte development after xenotransplantation of human ovarian tissue.Systematic review in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA).Not applicable.Not applicable.Formation of MII oocytes after xenotransplantation of human ovarian tissue.Any outcome reported in Pubmed.Six publications were identified that report on formation of MII oocytes after xenotransplantation of human ovarian tissue.Xenografting of human ovarian tissue has proved to be a useful model for examining ovarian function and follicle development in vivo. With human follicles that have matured through xenografting, the possibility of cancer transmission and relapse can also be eliminated, because cancer cells are not able to penetrate the zona pellucida. The reported studies have demonstrated that xenografted ovarian tissue from a range of species, including humans, can produce antral follicles that contain mature (MII) oocytes, and it has been shown that mice oocytes have the potential to give rise to live young. Although some ethical questions remain unresolved, xenotransplantation may be a promising method for restoring fertility. This review furthermore describes the value of xenotransplantation as a tool in reproductive biology and discusses the ethical and potential safety issues regarding ovarian tissue xenotransplantation as a means of recovering fertility.
EVALuna2:17543

Zukunft mammographie-basierter Bildgebung [Future of mammography-based imaging] - Schulz-Wendtland, Rüdiger; Wittenberg, Thomas; Michel, Thilo; Hartmann, Arndt; Beckmann, Matthias; Rauh, Claudia; Judt, Sebastian; Brehm, Barbara; Meier-Meitinger, Martina; Anton, Gisela; Uder, Michael; Fasching, Peter (Radiologe, 2014)
Mammography is the central diagnostic method for clinical diagnostics of breast cancer and the breast cancer screening program. In the clinical routine complementary methods, such as ultrasound, tomosynthesis and optional magnetic resonance imaging (MRI) are already combined for the diagnostic procedure. Future developments will utilize investigative procedures either as a hybrid (combination of several different imaging modalities in one instrument) or as a fusion method (the technical fusion of two or more of these methods) to implement fusion imaging into diagnostic algorithms. For screening there are reasonable hypotheses to aim for studies that individualize the diagnostic process within the screening procedure. Individual breast cancer risk prediction and individualized knowledge about sensitivity and specificity for certain diagnostic methods could be tested. The clinical implementation of these algorithms is not yet in sight. (orig.) [German] Die Mammographie ist die zentrale diagnostische Methode der klinischen symptombezogenen Abklaerung von Brusterkrankungen und des Brustkrebsscreenings. In der klinischen Diagnostik wird sie heute schon oft durch zusaetzliche Untersuchungsmethoden wie dem Ultraschall, der Tomosynthese und ggf. auch der MRT-Bildgebung unterstuetzt. Zukuenftige Entwicklungen gehen in die Richtung, dass diese Kombination aus 2 oder mehr Untersuchungsverfahren entweder in Hybrid- (Aufnahme mehrerer unterschiedlicher Bildmodalitaeten in einem einzigen Geraet) oder in Fusionsmethoden (Zusammenfuehrung und Registrierung von Bilddaten aus verschiedenen Modalitaeten) technisch professionalisiert werden. Des Weiteren koennten an subgruppenbezogene Erkrankungsrisiken und individuelle Sensitivitaeten und Spezifitaeten angepasste Diagnostikkombinationen fuer eine Screeningdiagnostik Gegenstand kuenftiger Studien sein. Wir stellen die aktuellen Entwicklungen auf diesen Gebieten und deren momentane Relevanz fuer die klinische Praxis und Entwicklungspotenzial fuer die Zukunft dar. (orig
UnivIS-Import:2015-04-14:Pub.2014.tech.IMMD.IMMD9.zukunf
Keywords: MAMMOgraphy